Are coffee silverskin extracts safe for topical use? An in vitro and in vivo approach - Rodrigues, F.; Pereira, C.; Pimentel, F. B.; Alves, R. C.; Ferreira, M.; Sarmento, B.; Helena Amaral, M.; Oliveira, M. Beatriz P. P. (Industrial Crops and Products, 2015)

Coffee silverskin: A possible valuable cosmetic ingredient - Rodrigues, Francisca; Palmeira-de-Oliveira, Ana; das Neves, Jose; Sarmento, Bruno; Helena Amaral, M.; Oliveira, M. Beatriz P. P. (Pharmaceutical Biology, 2015)

Combined C4d and CD3 immunostaining predicts immunoglobulin (Ig)A nephropathy progression - Faria, B.; Henriques, C.; Matos, A. C.; Daha, M. R.; Pestana, M.; Seelen, M. (Clinical and Experimental Immunology, 2015)

Cortical and trabecular bone in pediatric end-stage kidney disease - Carvalho, Catarina G.; Pereira, Renata C.; Gales, Barbara; Salusky, Isidro B.; Wesseling-Perry, Katherine (Pediatric Nephrology, 2015)

Finite element analysis of pectus carinatum surgical correction via a minimally invasive approach - Neves, Sara C.; Pinho, A. C. M.; Fonseca, Jaime C.; Rodrigues, Nuno F.; Henriques-Coelho, Tiago; Correia-Pinto, Jorge; Vilaca, Joao L. (Computer Methods in Biomechanics and Biomedical Engineering, 2015)

The interactions between municipal socioeconomic status and age on hip fracture risk - Oliveira, C.M.; Economou, T.; Bailey, T.; Mendona, D.; Pina, M.F. (Osteoporosis International, 2015)

Modulation of the inflammatory response to chitosan through M2 macrophage polarization using pro-resolution mediators - Vasconcelos, Daniela P.; Costa, Madalena; Amaral, Isabel F.; Barbosa, Mario A.; Aguas, Artur P.; Barbosa, Judite N. (Biomaterials, 2015)

Optic disc segmentation using the sliding band filter - Dashtbozorg, Behdad; Mendonca, Ana Maria; Campilho, Aurelio (Computers in Biology and Medicine, 2015)

Rehab@home: a tool for home-based motor function rehabilitation - Faria, Carlos; Silva, Jorge; Campilho, Aurelio (Disability and rehabilitation. Assistive technology, 2015)

The role of the surface on microglia function: implications for central nervous system tissue engineering - Pires, Liliana R.; Rocha, Daniela N.; Ambrosio, Luigi; Pego, Ana Paula (Journal of the Royal Society, Interface / the Royal Society, 2015)

Safety and toxicity concerns of orally delivered nanoparticles as drug carriers - Araujo, Francisca; Shrestha, Neha; Granja, Pedro L.; Hirvonen, Jouni; Santos, Helder A.; Sarmento, Bruno (Expert opinion on drug metabolism & toxicology, 2015)

Study of paraffin-embedded colon cancer tissue using terahertz spectroscopy - Wahaia, Faustino; Kasalynas, Irmantas; Seliuta, Dalius; Molis, Gediminas; Urbanowicz, Andrzej; Carvalho Silva, Catia D.; Carneiro, Fatima; Valusis, Gintaras; Granja, Pedro L. (Journal of Molecular Structure, 2015)

Terahertz spectroscopy for the study of paraffin-embedded gastric cancer samples - Wahaia, Faustino; Kasalynas, Irmantas; Seliuta, Dalius; Molis, Gediminas; Urbanowicz, Andrzej; Silva, Catia D. Carvalho; Carneiro, Fatima; Valusis, Gintaras; Granja, Pedro L. (Journal of Molecular Structure, 2015)

Actively targeted cetuximab conjugated γ-poly(glutamic acid)-docetaxel nanomedicines for epidermal growth factor receptor over expressing colon cancer cells - Maya, S.; Sarmento, B.; Lakshmanan, V.-K.; Menon, D.; Jayakumar, R. (Journal of Biomedical Nanotechnology, 2014)
Receptor targeted therapy is advantageous in overcoming the toxicity burden of conventional cancer chemotherapeutics. Over expression of epidermal growth factor receptor (EGFR) on cancer cells and its role in metastasis, malignancy and drug resistance in many human cancers lead to its selection as a promising target for cancer treatment. The present work investigated the preparation and characterization of docetaxel (DTXL) loaded γ-poly (glutamic acid) (γ-PGA) nanoparticles (Nps) conjugated with EGFR antibody (Cetuximab, CET) targeted to colon cancer cells (HT-29), highly over expressing EGFR. The flow cytometric analysis revealed two fold increased cellular uptake of CET-DTXL-γ-PGA Nps by HT-29 (EGFR +ve) cells compared to that of IEC-6 (EGFR-ve) cells confirming the active targeting. Cytotoxicity assays (MTT and LDH) showed superior anti-proliferative activity of CET-DTXL-γ-PGA NPs over DTXL-γ-PGA Nps against HT-29 cells. The cell cycle analysis indicated that CET-DTXL-γ-PGA NPs induced cell death in enhanced percentage of HT-29 cells by undergoing cell cycle arrest in G2/M phase compared to that of DTXL-γ-PGA Nps. The mechanism of cancer cell death was analyzed via apoptotic and mitochondrial membrane potential assays and showed that targeted Nps treatment reduced the mitochondrial membrane potential thereby inducing enhanced HT-29 cell death (apoptosis and necrosis). The biodistribution of targeted and non-targeted Nps were analyzed in vivo in Swiss albino mice using NIR imaging. ICG-CET-DTXL-γ-PGA Nps (targeted) and ICG-DTXL-γ-PGA Nps (non-targeted) followed the similar biodistribution pattern in vivo, but with different elimination time. In short, CET-DTXL-γ-PGA nanoparticles enhance the tumor selective therapeutic efficacy for colon cancer. Copyright © 2014 American Scientific Publishers All rights reserved.
Keywords: Cetuximab; colon cancer; Docetaxel; Epidermal growth factor receptor; Poly(γ-glutamic acid) nanoparticles; Targeted nanomedicines

Adsorbed fibrinogen enhances production of bone- and angiogenic-related factors by monocytes/macrophages - Maciel, J.; Oliveira, M.I.; Colton, E.; McNally, A.K.; Oliveira, C.; Anderson, J.M.; Barbosa, M.A. (Tissue Engineering - Part A, 2014)
Macrophages are phagocytic cells with great importance in guiding multiple stages of inflammation and tissue repair. By producing a large number of biologically active molecules, they can affect the behavior of other cells and events, such as the foreign body response and angiogenesis. Since protein adsorption to biomaterials is crucial for the inflammatory process, we addressed the ability of the pro-inflammatory molecule fibrinogen (Fg) to modulate macrophage behavior toward tissue repair/regeneration. For this purpose, we used chitosan (Ch) as a substrate for Fg adsorption. Freshly isolated human monocytes were seeded on Ch substrates alone or previously adsorbed with Fg, and allowed to differentiate into macrophages for 10 days. Cell adhesion and morphology, formation of foreign body giant cells (FBGC), and secretion of a total of 80 cytokines and growth factors were evaluated. Both substrates showed similar numbers of adherent macrophages along differentiation as compared with RGD-coated surfaces, which were used as positive controls. Fg did not potentiate FBGC formation. In addition, actin cytoskeleton staining revealed the presence of punctuate F-actin with more elongated and interconnecting cells on Ch substrates. Antibody array screening and quantification of inflammation- and wound-healing-related factors indicated an overall reduction in Ch-based substrates versus RGD-coated surfaces. At late times, most inflammatory agents were down-regulated in the presence of Fg, in contrast to growth factor production, which was stimulated by Fg. Importantly, on Ch+Fg substrates, fully differentiated macrophages produced significant amounts of macrophage inflammatory protein-1delta (MIP-1δ), platelet-derived growth factor-BB, bone morphogenetic protein (BMP)-5, and BMP-7 compared with Ch alone. In addition, other important factors involved in bone homeostasis and wound healing, such as growth hormone, transforming growth factor-β3, and insulin-like growth factor-binding proteins, as well as several angiogenic mediators, including endocrine gland-derived vascular endothelial factor, fibroblast growth factor-7, and placental growth factor, were significantly promoted by Fg. This work provides a new perspective on the inflammatory response in the context of bone repair/regeneration mediated by a pro-inflammatory protein (Fg) adsorbed onto a biomaterial (Ch) that does not otherwise exhibit osteogenic properties. © Copyright 2014, Mary Ann Liebert, Inc.

Age-period-cohort effects in the incidence of hip fractures: Political and economic events are coincident with changes in risk - Alves, S.M.; Castiglione, D.; Oliveira, C.M.; de Sousa, B.; Pina, M.F. (Osteoporosis International, 2014)
Summary: An age-period cohort model was fitted to analyse time effects on hip fracture incidence rates by sex (Portugal, 2000-2008). Rates increased exponentially with age (age effect). Incidence rates decreased after 2004 for women and were random for men (period effect). New but comprehensive fluctuations in risk were coincident with major political/economic changes (cohort effect). Introduction: Healthcare improvements have allowed prevention but have also increased life expectancy, resulting in more people being at risk. Our aim was to analyse the separate effects of age, period and cohort on incidence rates by sex in Portugal, 2000-2008. Methods: From the National Hospital Discharge Register, we selected admissions (aged ≥49 years) with hip fractures (ICD9-CM, codes 820.x) caused by low/moderate trauma (falls from standing height or less), readmissions and bone cancer cases. We calculated person-years at risk using population data from Statistics Portugal. To identify period and cohort effects for all ages, we used an age-period-cohort model (1-year intervals) followed by generalised additive models with a negative binomial distribution of the observed incidence rates of hip fractures. Results: There were 77,083 hospital admissions (77.4% women). Incidence rates increased exponentially with age for both sexes (age effect). Incidence rates fell after 2004 for women and were random for men (period effect). There was a general cohort effect similar in both sexes; risk of hip fracture altered from an increasing trend for those born before 1930 to a decreasing trend following that year. Risk alterations (not statistically significant) coincident with major political and economic change in the history of Portugal were observed around birth cohorts 1920 (stable-increasing), 1940 (decreasing-increasing) and 1950 (increasing-decreasing only among women). Conclusions: Hip fracture risk was higher for those born during major economically/politically unstable periods. Although bone quality reflects lifetime exposure, conditions at birthmay determine future risk for hip fractures. © International Osteoporosis Foundation and National Osteoporosis Foundation 2013.
Keywords: Age-period-cohort; Hip fractures; Osteoporosis; Population-based study; Time trend

Antihyperglycemic Potential of Incretins Orally Delivered via Nano and Microsystems and Subsequent Glucoregulatory Effects - Araujo, Francisca; Shrestha, Neha; Granja, Pedro L.; Hirvonen, Jouni; Santos, Helder A.; Sarmento, Bruno (Current Pharmaceutical Biotechnology, 2014)

Atomic force microscopy measurements reveal multiple bonds between Helicobacter pylori blood group antigen binding adhesin and Lewis b ligand - Parreira, P.; Shi, Q.; Magalhaes, A.; Reis, C.A.; Bugaytsova, J.; Boren, T.; Leckband, D.; Martins, M.C.L. (Journal of the Royal Society, Interface / the Royal Society, 2014)

An Automatic Graph-Based Approach for Artery/Vein Classification in Retinal Images - Dashtbozorg, Behdad; Mendonca, Ana Maria; Campilho, Aurelio (Ieee Transactions on Image Processing, 2014)

Bioactivity of surface tethered Osteogenic Growth Peptide motifs - Panseri, Silvia; Russo, Laura; Montesi, Monica; Taraballi, Francesca; Cunha, Carla; Marcacci, Maurilio; Cipolla, Laura (Medchemcomm, 2014)

A biocomposite of collagen nanofibers and nanohydroxyapatite for bone regeneration - Ribeiro, Nilza; Sousa, Susana R.; van Blitterswijk, Clemens A.; Moroni, Lorenzo; Monteiro, Fernando J. (Biofabrication, 2014)

Biodistribution and pharmacokinetics of Dapivirine-loaded nanoparticles after vaginal delivery in mice - Das Neves, J.; Araújo, F.; Andrade, F.; Amiji, M.; Bahia, M.F.; Sarmento, B. (Pharmaceutical Research, 2014)
Purpose: To assess the potential of polymeric nanoparticles (NPs) to affect the genital distribution and local and systemic pharmacokinetics (PK) of the anti-HIV microbicide drug candidate dapivirine after vaginal delivery. Methods: Dapivirine-loaded, poly(ethylene oxide)-coated poly(epsilon-caprolactone) (PEO-PCL) NPs were prepared by a nanoprecipitation method. Genital distribution of NPs and their ability to modify the PK of dapivirine up to 24 h was assessed after vaginal instillation in a female mouse model. Also, the safety of NPs upon daily administration for 14 days was assessed by histological analysis and chemokine/cytokine content in vaginal lavages. Results: PEO-PCL NPs (180-200 nm) were rapidly eliminated after administration but able to distribute throughout the vagina and lower uterus, and capable of tackling mucus and penetrate the epithelial lining. Nanocarriers modified the PK of dapivirine, with higher drug levels being recovered from vaginal lavages and vaginal/lower uterine tissues as compared to a drug suspension. Systemic drug exposure was reduced when NPs were used. Also, NPs were shown safe upon administration for 14 days. Conclusions: Dapivirine-loaded PEO-PCL NPs were able to provide likely favorable genital drug levels, thus attesting the potential value of using this vaginal drug delivery nanosystem in the context of HIV prophylaxis. © 2014 Springer Science+Business Media New York.
Keywords: HIV/AIDS; microbicides; poly(ε-caprolactone); pre-exposure prophylaxis; vaginal drug delivery

Building and repairing the heart: What can we learn from embryonic development? - Freire, AG; Resende, TP; Pinto-Do-Ó, P. (BioMed Research International, 2014)
Mammalian heart formation is a complex morphogenetic event that depends on the correct temporal and spatial contribution of distinct cell sources. During cardiac formation, cellular specification, differentiation, and rearrangement are tightly regulated by an intricate signaling network. Over the last years, many aspects of this network have been uncovered not only due to advances in cardiac development comprehension but also due to the use of embryonic stem cells (ESCs) in vitro model system. Additionally, several of these pathways have been shown to be functional or reactivated in the setting of cardiac disease. Knowledge withdrawn from studying heart development, ESCs differentiation, and cardiac pathophysiology may be helpful to envisage new strategies for improved cardiac repair/regeneration. In this review, we provide a comparative synopsis of the major signaling pathways required for cardiac lineage commitment in the embryo and murine ESCs. The involvement and possible reactivation of these pathways following heart injury and their role in tissue recovery will also be discussed. © 2014 Ana G. Freire et al.

Can artificial neural networks be used to predict the origin of ozone episodes? - Fontes, T.; Silva, L.M.; Silva, M. P.; Barros, N.; Carvalho, A. C. (Science of the Total Environment, 2014)
Tropospheric ozone is a secondary pollutant having a negative impact on health and environment. To control and minimize such impact the European Community established regulations to promote a clean air all over Europe. However, when an episode is related with natural mechanisms as Stratosphere-Troposphere Exchanges (STE), the benefits of an action plan to minimize precursor emissions are inefficient. Therefore, this work aims to develop a tool to identify the sources of ozone episodes in order to minimize misclassification and thus avoid the implementation of inappropriate air quality plans. For this purpose, an artificial neural network model - the Multilayer Perceptron - is used as a binary classifier of the source of an ozone episode. Long data series, between 2001 and 2010, considering the ozone precursors, 7Be activity and meteorological conditions were used. With this model, 2-7% of a mean error was achieved, which is considered as a good generalization. Accuracy measures for imbalanced data are also discussed. The MCC values show a good performance of the model (0.65-0.92). Precision and F1-measure indicate that the model specifies a little better the rare class. Thus, the results demonstrate that such a tool can be used to help authorities in the management of ozone, namely when its thresholds are exceeded due natural causes, as the above mentioned STE. Therefore, the resources used to implement an action plan to minimize ozone precursors could be better managed avoiding the implementation of inappropriate measures. © 2014 Elsevier B.V.
Keywords: artificial neural network; Classification; Human health; Ozone; Stratosphere; Troposphere

Cellular strategies to promote vascularisation in tissue engineering applications - Costa-Almeida, R.; Granja, P.L.; Soares, R.; Guerreiro, S.G. (European Cells and Materials, 2014)
Vascularisation is considered to be one of the greatest challenges in tissue engineering. Different strategies exist but cell-based approaches have emerged as a promising therapy to achieve successful vascularisation. The use of endothelial cells to engineer vascularised tissues has been extensively investigated. This field of research has evolved with the discovery of endothelial progenitor cells, a subpopulation with a high regenerative potential. However, the survival of endothelial cell populations alone seems to be impaired. To overcome this problem, co-culture systems, involving supporting cells, like mural cells, fibroblasts, or more tissue-specific cells have been developed. Endothelial cells benefit from the extracellular matrix components and growth factors produced by the supporting cells, which results in neovessel stabilisation and maturation. The use of endothelial progenitor cells in co-culture systems appears to be a promising strategy to promote vascularisation in approaches of increasing complexity. Herein, the authors provide an overview of the cellular strategies that can be used for increasing vascularisation in tissue engineering and regeneration.
Keywords: angiogenesis; Cellular therapies; Co-culture models; Endothelial progenitor cells; Regeneration

Characterization of hLF1-11 immobilization onto chitosan ultrathin films, and its effects on antimicrobial activity - Costa, F.; Maia, S.; Gomes, J.; Gomes, P.; Martins, M.C.L. (Acta Biomaterialia, 2014)
hLF1-11 (GRRRRSVQWCA) is an antimicrobial peptide (AMP) with high activity against methicillin-resistant Staphylococcus aureus (MRSA), the most prevalent species in implant-associated infection. In this work, the effect of the surface immobilization on hLF1-11 antimicrobial activity was studied. Immobilization was performed onto chitosan thin films as a model for an implant coating due to its reported osteogenic and antibacterial properties. Chitosan thin films were produced by spin-coating on gold surfaces. hLF1-11 was immobilized onto these films by its C-terminal cysteine in an orientation that exposes the antimicrobial activity-related arginine-rich portion of the peptide. Two levels of exposure (with and without a polyethylene glycol (PEG) spacer) were analyzed. Covalent immobilization was further compared with the AMP physical adsorption onto chitosan films. Surfaces were characterized using ellipsometry, contact angle measurements, atomic force microscopy, infrared and X-ray photoelectron spectroscopies and using a fluorimetric assay for hLF1-11 quantification. Surface antimicrobial activity was assessed through surface adhesion and viability assays using an MRSA (S. aureus ATCC 33591). The incorporation of hLF1-11 increased significantly bacterial adhesion to chitosan films. However, the presence of hLF1-11, namely when immobilized through a PEG spacer, decreased the viability of adherent bacteria with regard to the control surface. These results demonstrated that hLF1-11 after covalent immobilization by its cysteine can maintain activity, particularly if a spacer is applied. However, further studies, exploring the opposite orientation or the same C-terminal orientation, but non-cysteine related, can help to clarify the potential of the hLF1-11 immobilization strategy. © 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Antimicrobial peptides (AMP); Bacterial adhesion; chitosan; Surface characterization; Surface immobilization

Chitosan cross-linked docetaxel loaded EGF receptor targeted nanoparticles for lung cancer cells - Maya, S.; Sarmento, B.; Lakshmanan, V.-K.; Menon, D.; Seabra, V.; Jayakumar, R. (International Journal of Biological Macromolecules, 2014)
Lung cancer, associated with the up-regulated epidermal growth factor receptor (EGFR) led to the development of EGFR targeted anticancer therapeutics. The biopolymeric nanoparticles form an outstanding system for the targeted delivery of therapeutic agents. The present work evaluated the in vitro effects of chitosan cross-linked γ-poly(glutamic acid) (γ-PGA) nanoparticles (Nps) loaded with docetaxel (DTXL) and decorated with Cetuximab (CET), targeted to EGFR over-expressing non-small-cell-lung-cancer (NSCLC) cells (A549). CET-DTXL-γ-PGA Nps was prepared by ionic gelation and CET conjugation via EDC/NHS chemistry. EGFR specificity of targeted Nps was confirmed by the higher uptake rates of EGFR +ve A549 cells compared to that of EGFR -ve cells (NIH3T3). The cytotoxicity of Nps quantified using cell based (MTT/LDH) and flowcytometry (Cell-cycle analysis, Annexin V/PI and JC-1) assays showed superior antiproliferative activity of CET-DTXL-γ-PGA Nps over DTXL-γ-PGA Nps. The A549 cells treated with CET-DTXL-γ-PGA NPs underwent a G2/M phase cell cycle arrest followed by reduction in mitochondrial membrane potential of A549 cells, inducing apoptosis and necrosis resulting in enhanced cancer cell death. CET-DTXL-γ-PGA Nps exhibited enhanced cellular internalization and therapeutic activity, by actively targeting EGFR on NSCLC cells and hence could be an effective alternative to non-specific, conventional chemotherapy by increasing its efficiency by many folds. © 2014 Elsevier B.V.
Keywords: Cetuximab; chitosan; Epidermal growth factor receptor; Poly(γ-glutamic acid) nanoparticles; Targeted nanoparticles

Chitosan-modified porous silicon microparticles for enhanced permeability of insulin across intestinal cell monolayers - Shrestha, N.; Shahbazi, M.-A.; Araújo, F.; Zhang, H.; Mäkilä, E.M.; Kauppila, J.; Sarmento, B.; Salonen, J.J.; Hirvonen, J.T.; Santos, H.A. (Biomaterials, 2014)
Porous silicon (PSi) based particulate systems are emerging as an important drug delivery system due to its advantageous properties such as biocompatibility, biodegradability and ability to tailor the particles' physicochemical properties. Here, annealed thermally hydrocarbonized PSi (AnnTHCPSi) and undecylenic acid modified AnnTHCPSi (AnnUnTHCPSi) microparticles were developed as a PSi-based platform for oral delivery of insulin. Chitosan (CS) was used to modify the AnnUnTHCPSi microparticles to enhance the intestinal permeation of insulin. Surface modification with CS led to significant increase in the interaction of PSi microparticles with Caco-2/HT-29 cell co-culture monolayers. Compared to pure insulin, the CS-conjugated microparticles significantly improved the permeation of insulin across the Caco-2/HT-29 cell monolayers, with ca. 20-fold increase in the amount of insulin permeated and ca. 7-fold increase in the apparent permeability (Papp) value. Moreover, among all the investigated particles, the CS-conjugated microparticles also showed the highest amount of insulin associated with the mucus layer and the intestinal Caco-2 cells and mucus secreting HT-29 cells. Our results demonstrate that CS-conjugated AnnUnTHCPSi microparticles can efficiently enhance the insulin absorption across intestinal cells, and thus, they are promising microsystems for the oral delivery of proteins and peptides across the intestinal cell membrane. © 2014 Elsevier Ltd.
Keywords: Cell monolayers; chitosan; Diabetes; Insulin; Microparticles; Porous silicon

Co-association of methotrexate and SPIONs into anti-CD64 antibody-conjugated PLGA nanoparticles for theranostic application - Moura, Catarina Costa; Segundo, Marcela A.; das Neves, Jose; Reis, Salette; Sarmento, Bruno (International Journal of Nanomedicine, 2014)

Collagen surface modified poly(ε-caprolactone) scaffolds with improved hydrophilicity and cell adhesion properties - Sousa, I.; Mendes, A.; Pereira, R.F.; Bártolo, P.J. (Materials Letters, 2014)
Poly(ε-caprolactone) (PCL)/collagen scaffolds were produced using a four-step procedure comprising (i) the fabrication of PCL scaffolds through an additive bioextrusion system, (ii) the PCL surface modification using a plasma treatment, (iii) the acrylic acid (AAc) grafting by ultraviolet (UV) polymerization, and (iv) the immobilization of collagen into the scaffold surface through the carbodiimide chemistry. This procedure allowed the quick fabrication of highly porous scaffolds with interconnected pores, well-defined internal architecture and improved cell adhesion properties. The immobilization of collagen into the PCL surface led to a significant enhancement in the hydrophilicity, while the biological tests showed a further improvement in the adhesion of fibroblast cells. These results indicate that the collagen surface modification is an effective strategy to render the hydrophobic nature of PCL and overcome the limited cell interaction of 3D PCL scaffolds. © 2014 Elsevier B.V.
Keywords: BioExtruder; Collagen; poly(ε-caprolactone); Scaffold; Surface modification

Complexity-loss in fetal heart rate dynamics during labor as a potential biomarker of acidemia - Costa, Madalena D.; Schnettler, William T.; Amorim-Costa, Celia; Bernardes, Joao; Costa, Antonia; Goldberger, Ary L.; Ayres-de-Campos, Diogo (Early Human Development, 2014)

A critical appraisal of the evidence for using cardiotocography plus ECG ST interval analysis for fetal surveillance in labor. Part I: the randomized controlled trials - Olofsson, Per; Ayres-de-Campos, Diogo; Kessler, Joerg; Tendal, Britta; Yli, Branka M.; Devoe, Lawrence (Acta Obstetricia Et Gynecologica Scandinavica, 2014)

Crucial CD8+ T-lymphocyte cytotoxic role in amphotericin B nanospheres efficacy against experimental visceral leishmaniasis - Costa Lima, S.A.; Silvestre, R.; Barros, D.; Cunha, J.; Baltazar, M.T.; Dinis-Oliveira, R.J.; Cordeiro-da-Silva, A. (Nanomedicine: Nanotechnology, Biology, and Medicine, 2014)
This work aims to develop poly(d,l-lactide-co-glycolide) (PLGA)-nanospheres containing amphotericin B (AmB) with suitable physicochemical properties and anti-parasitic activity for visceral leishmaniasis (VL) therapy. When compared with unloaded-PLGA-nanospheres, the AmB-loaded PLGA-nanospheres displayed an increased particle size without affecting the polydispersity and its negative surface charge. AmB stability in the PLGA-nanospheres was >90% over 60-days at 30°C. The AmB-PLGA-nanospheres demonstrated significant in vitro and in vivo efficacy and preferential accumulation in the visceral organs. In addition, an immune-modulatory effect was observed in mice treated with AmB-PLGA-nanospheres, correlating with improved treatment efficacy. The in vitro cytotoxic response of the T-lymphocytes revealed that AmB-PLGA-nanospheres efficacy against VL infection was strictly due to the action of CD8+- but not CD4+-T lymphocytes. Overall, we demonstrate a crucial role for CD8+ cytotoxic T lymphocytes in the efficacy of AmB-PLGA nanospheres, which could represent a potent and affordable alternative for VL therapy. From the Clinical Editor: This study demonstrates a crucial role for CD8+ T lymphocytes in eliminating visceral leishmaniasis in a murine model by enhancing the cytotoxic efficacy of CD8+ T-cells via amphotericin-B-PLGA nanospheres, paving a way to a unique, potentially more potent and cost-effective therapeutic strategy. © 2014 Elsevier Inc.
Keywords: Amphotericin B; Immune-modulation; Poly(d,l-lactide-co-glycolide) nanospheres; Visceral leishmaniasis

Development and evaluation of an algorithm for computer analysis of maternal heart rate during labor - Pinto, P.; Bernardes, J.; Costa-Santos, C.; Amorim-Costa, C.; Silva, M.; Ayres-de-Campos, D. (Computers in Biology and Medicine, 2014)
Background: Maternal heart rate (MHR) recordings are morphologically similar and sometimes coincident with fetal heart rate (FHR) recordings and may be useful for maternal-fetal monitoring if appropriately interpreted. However, similarly to FHR, visual interpretation of MHR features may be poorly reproducible. Methods: A computer algorithm for on-line MHR analysis was developed based on a previously existing version for FHR analysis. Inter-observer and computer-observer agreement and reliability were assessed in 40 one-hour recordings obtained from 20 women during the last 2. h of labor. Agreement and reliability were evaluated for the detection of basal MHR, long-term variability (LTV), accelerations and decelerations, using proportions of agreement (PA) and Kappa statistic (K), with 95% confidence intervals (95% CI). Changes in MHR characteristics between the first and the second hour of the tracings were also evaluated. Results: There was a statistically significant inter-observer and computer-observer agreement and reliability in estimation of basal MHR, accelerations, decelerations and LTV, with PA values ranging from 0.72 (95% CI: 0.62-0.79) to 1.00 (95% CI: 0.99-1.00), and K values ranging from 0.44 (95% CI: 0.28-0.60) to 0.89 (95% CI: 0.82-0.96). Moreover, basal MHR, number of accelerations and LTV were significantly higher in the last hour of labor, when compared to the initial hour. Discussion: The developed algorithm for on-line computer analysis of MHR recordings provided good to excellent computer-observer agreement and reliability. Moreover, it allowed an objective detection of MHR changes associated with labor progression, providing more information about the interpretation of maternal-fetal monitoring during labor. © 2014 Elsevier Ltd.
Keywords: Agreement; Cardiotocography; computer analysis; Fetal heart rate; Maternal heart rate; reliability

Differences between external and internal fetal heart rate monitoring during the second stage of labor: a prospective observational study - Nunes, Ines; Ayres-de-Campos, Diogo; Costa-Santos, Cristina; Bernardes, Joao (Journal of Perinatal Medicine, 2014)

Dissecting the signaling pathways associated with the oncogenic activity of MLK3 P252H mutation - Velho, Sergia; Pinto, Ana; Licastro, Danilo; Oliveira, Maria Jose; Sousa, Filipa; Stupka, Elia; Seruca, Raquel (Bmc Cancer, 2014)

DNAJB4 molecular chaperone distinguishes WT from mutant E-cadherin, determining their fate in vitro and in vivo - Simões-Correia, J.; Silva, D.I.; Melo, S.; Figueiredo, J.; Caldeira, J.; Pinto, M.T.; Girão, H.; Pereira, P.; Seruca, R. (Human Molecular Genetics, 2014)
E-cadherin (Ecad) is a well-known invasion suppressor and its loss of expression is common in invasive carcinomas. Germline Ecad mutations are the only known genetic cause of hereditary diffuse gastric cancer (HDGC), demonstrating the causative role of Ecad impairment in gastric cancer. HDGC-associated Ecad missense mutations can lead to folding defects and premature proteasome-dependent endoplasmic reticulum-associated degradation (ERAD), but the molecular determinants for this fate were unidentified. Using a Drosophilabased genetic screen, we found that Drosophila DnaJ-1 interacts with wild type (WT) and mutant human Ecad in vivo. DnaJ (Hsp40) homolog, subfamily B, member 4 (DNAJB4), the human homolog of DnaJ-1, influences Ecad localization and stability even in the absence of Ecad endogenous promoter, suggesting a post-transcriptional level of regulation. Increased expression of DNAJB4 leads to stabilization of WT Ecad in the plasma membrane, while it induces premature degradation of unfolded HDGC mutants in the proteasome. The interaction between DNAJB4 and Ecad is direct, and is increased in the context of the unfolded mutant E757K, especially when proteasome degradation is inhibited, suggesting that DNAJB4 is a molecular mediator of ERAD. Post-translational regulation of native Ecad by DNAJB4 molecular chaperone is sufficient to influence cell adhesion in vitro. Using a chick embryo chorioallantoic membrane assay with gastric cancer derived cells, we demonstrate that DNAJB4 stimulates the anti-invasive function of WT Ecad in vivo. Additionally, the expression of DNAJB4 and Ecad is concomitantly decreased in human gastric carcinomas. Altogether, we demonstrate that DNAJB4 is a sensor of Ecad structural features that might contribute to gastric cancer progression. © The Author 2013. Published by Oxford University Press. All rights reserved.

Dysregulation of T cell receptor N-glycosylation: A molecular mechanism involved in ulcerative colitis - Dias, A.M.; Dourado, J.; Lago, P.; Cabral, J.; Marcos-Pinto, R.; Salgueiro, P.; Almeida, C.R.; Carvalho, S.; Fonseca, S.; Lima, M.; Vilanova, M.; Dinis-Ribeiro, M.; et al. (Human Molecular Genetics, 2014)
The incidence of inflammatory bowel disease is increasing worldwide and the underlying molecular mechanisms are far from being fully elucidated. Herein, we evaluated the role of N-glycosylation dysregulation in T cells as a key mechanism in the ulcerative colitis (UC) pathogenesis. The evaluation of the branched N-glycosylation levelsandprofile of intestinalTcell receptor (TCR)wereassessedin colonic biopsies fromUCpatientsand healthy controls. Expression alterations of the glycosyltransferase gene MGAT5 were also evaluated. We demonstrated thatUCpatients exhibit a dysregulation ofTCRbranchedN-glycosylationonlamina propriaTlymphocytes. Patients with severe UC showed the most pronounced defect on N-glycan branching in T cells. Moreover, UC patients showed a significant reduction of MGAT5 gene transcription in T lymphocytes. In this study, we disclose for the first time that a deficiency in branched N-glycosylation on TCR due to a reduced MGAT5 gene expression is a new molecular mechanism underlying UC pathogenesis, being a potential novel biomarker with promising clinical and therapeutic applications. © The Author 2013. Published by Oxford University Press. All rights reserved.

Effect of cell density on mesenchymal stem cells aggregation in RGD-alginate 3D matrices under osteoinductive conditions - Maia, F.R.; Lourenço, A.H.; Granja, P.L.; Gonçalves, R.M.; Barrias, C.C. (Macromolecular Bioscience, 2014)
Cellular activities in 3D are differentially affected by several matrix-intrinsic and extrinsic factors. This study highlights the relevance of optimizing initial cell densities when establishing 3D cultures for specific applications. Independently of the entrapping density, MSCs cultured within RGD-alginate hydrogels showed steady-state levels of metabolic activity and were in a nearly non-proliferative state, but recovered "normal" activity levels when retrieved from 3D matrices and re-cultured as monolayers. Importantly, high-densities promoted the establishment of cell-cell contacts with formation of multicellular clusters stabilized by endogenous ECM, and also stimulated MSCs osteogenic differentiation. These MSC-ECM microtissues may be used as building blocks for tissue engineering. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: alginate hydrogels; encapsulation; Self-assembly; Tissue engineering

The effect of hyaluronan-based delivery of stromal cell-derived factor-1 on the recruitment of MSCs in degenerating intervertebral discs - Pereira, C.L.; Gonçalves, R.M.; Peroglio, M.; Pattappa, G.; D'Este, M.; Eglin, D.; Barbosa, M.A.; Alini, M.; Grad, S. (Biomaterials, 2014)
Intervertebral disc (IVD) degeneration is the leading cause of low back pain and disability in the active population. Transplantation of mesenchymal stem cells (MSCs) in a hydrogel carrier can induce regenerative effects in degenerated IVDs. Moreover, it was found that degenerative discs release chemoattractants effective in MSC recruitment. Based on these findings, we hypothesized that an injectable hydrogel that can enhance the number of migrated MSCs in the IVD and provide a suitable matrix for their survival and differentiation would be ideal. The purpose of this study was to evaluate the potential of a thermoreversible hyaluronan-poly(N-isopropylacrylamide) (HAP) hydrogel as chemoattractant delivery system to recruit human MSCs in degenerative IVDs. The results demonstrate that HAP hydrogels containing stromal cell derived factor-1 (SDF-1) significantly increased the number of MSCs migrating into nucleotomized discs compared with discs treated with only HAP or SDF-1 in solution. HAP hydrogels releasing SDF-1 enhanced both the number of recruited cells and their migration distance in the IVD tissue. Furthermore, this phenomenon was dependent on MSC donor age. In conclusion, HAP SDF-1 is effective for the recruitment of stem cells in the IVD, thus opening new possibilities for the development of regenerative therapies based on endogenous cell migration. © 2014 Elsevier Ltd.
Keywords: Intervertebral disc; Mesenchymal Stem Cells; Recruitment; Stromal cell derived factor-1; Thermoreversible hyaluronan hydrogel

Endoplasmic Reticulum Degradation-Enhancing alpha-Mannosidase-like Protein 1 Targets Misfolded HLA-B27 Dimers for Endoplasmic Reticulum-Associated Degradation - Guiliano, David B.; Fussell, Helen; Lenart, Izabela; Tsao, Edward; Nesbeth, Darren; Fletcher, Adam J.; Campbell, Elaine C.; Yousaf, Nasim; Williams, Sarah; Santos, Susana; Cameron, Amy; Towers, Greg J.; et al. (Arthritis & Rheumatology, 2014)

Engineering proteolytically-degradable artificial extracellular matrices - Fonseca, Keila B.; Granja, Pedro L.; Barrias, Cristina C. (Progress in Polymer Science, 2014)

Eradication of Helicobacter pylori: Past, present and future - Lopes, D.; Nunes, C.; Martins, M.C.L.; Sarmento, B.; Reis, S. (Journal of Controlled Release, 2014)
Helicobacter pylori is the major cause of chronic gastritis and peptic ulcers. Since the classification as a group 1 carcinogenic by International Agency for Research on Cancer, the importance of the complete H. pylori eradication has obtained a novel meaning. Hence, several studies have been made in order to deepen the knowledge in therapy strategies. However, the current therapy presents unsatisfactory eradication rates due to the lack of therapeutic compliance, antibiotic resistance, the degradation of antibiotics at gastric pH and their insufficient residence time in the stomach. Novel approaches have been made in order to overcome these limitations. The purpose of this review is to provide an overview about the current therapy and its limitations, while highlighting the possibility of using micro- and nanotechnology to develop gastric drug delivery systems, overcoming these difficulties in the future. © 2014 Elsevier B.V.
Keywords: Drug delivery; Helicobacter pylori; Microparticles; nanoparticles; Treatment

An evaluation of the latest in vitro tools for drug metabolism studies - Costa, A.; Sarmento, B.; Seabra, V. (Expert Opinion on Drug Metabolism and Toxicology, 2014)
Introduction: Drugs are indispensable for human welfare nevertheless there is a lack of safe drugs. Obtaining pharmacokinetics information, especially metabolism, is a requirement during preclinical and clinical drug development so that in vitro tools represent a simple path where it is possible to assess drug toxicity and predict drug safety in humans. Areas covered: This review covers the latest in vitro tools developed for assessing drug toxicity in different organs. A special focus is given to hepatic models, as it is the main organ responsible for drug metabolism and consequently bioactivation and detoxification reactions. Three-dimensional culture models have been widely developed, resembling in vivo-like conditions, and are also discussed in this review. Expert opinion: Several in vitro tools to assess hepatic drug metabolism have been developed, however, novel in vitro methods to investigate extra-hepatic drug metabolism still need to be improved. These methods are able to reduce the number of animal used in preclinical experiments, but in vivo tests are mandatory for drug approval and commercialization. © 2014 Informa UK, Ltd.
Keywords: Hepatic metabolism; in vitro models; Intestinal metabolism; Pulmonary metabolism; Renal metabolism

External uterine contractions signal analysis in relation to labor progression and dystocia - Gonçalves, H.; Pinto, P.; Ayres-de-Campos, D.; Bernardes, J. (IFMBE Proceedings, 2014)
Labor dystocia is a major cause of operative delivery, which is associated with increased risks for both mother and fetus. We assessed linear and non-linear dynamics of external uterine contraction signals, in relation to labor progression and dystocia. Linear time domain, spectral and entropy methods were used to analyze external uterine contraction recordings obtained during the last two hours of labor, in 28 cases with normal and 27 cases with operative deliveries (forceps, vacuum or caesarean). Progression of labor was associated with a statistically significant increase in most linear time domain and spectral indices, both in normal and operative deliveries, whereas most entropy indices increased in normal deliveries, but did not change in operative deliveries. On the other hand, when compared with normal births, operative deliveries were associated with significantly increased entropy indices before the last hour of labor and significantly decreased (a probably associated) sympatho-vagal balance in the last hour of labor. Linear and non-linear analysis of external uterine contraction recordings may provide useful physiopathological and clinical information on the progression of labor and the diagnosis of dystocia. © Springer International Publishing Switzerland 2014.
Keywords: Cardiotocography; Dystocia; entropy; External uterine contractions; Spectral analysis

Extracellular matrix stiffness and composition jointly regulate the induction of malignant phenotypes in mammary epithelium - Chaudhuri, Ovijit; Koshy, Sandeep T.; Branco da Cunha, Cristiana; Shin, Jae-Won; Verbeke, Catia S.; Allison, Kimberly H.; Mooney, David J. (Nature Materials, 2014)

Fetal behavioral dynamics in cephalic versus breech presentations - Gonçalves, H.; Ayres-de-Campos, D.; Bernardes, J. (Developmental Psychobiology, 2014)
Differences in fetal neurodevelopment can have important implications on future perceptual and learning capabilities. The aim of this study was to assess autonomic nervous system and complexity dynamics in fetal heart rate (FHR) tracings from 27 singleton fetuses in cephalic or breech presentations, matched for gestational age (37+3-40+4 weeks), weight, gender and outcome. Breeches exhibited significantly higher mean FHR and LF/(MF+HF) ratio, as well as lower entropy, denoting increased sympatho-vagal balance and decreased complexity, consistent with the occurrence of more active fetal behavioral states. These findings suggest that there are neurodevelopment differences between fetuses in cephalic and breech presentation.
Keywords: Breech presentation; Development; entropy; Fetal behavior; Heart rate; Spectral analysis

Fetal Behavioral Dynamics in Cephalic Versus Breech Presentations - Goncalves, Hernani; Ayres-de-Campos, Diogo; Bernardes, Joao (Developmental Psychobiology, 2014)

Fetal QRS detection and heart rate estimation: a wavelet-based approach - Almeida, Rute; Goncalves, Hernani; Bernardes, Joao; Rocha, Ana Paula (Physiological Measurement, 2014)

Field dimension and skill level constrain team tactical behaviours in small-sided and conditioned games in football - Silva, Pedro; Duarte, Ricardo; Sampaio, Jaime; Aguiar, Paulo; Davids, Keith; Araujo, Duarte; Garganta, Julio (Journal of Sports Sciences, 2014)

Fluorescent bionanoprobes based on quantum dot-chitosan-O-phospho-L-serine conjugates for labeling human bone marrow stromal cells - Salgado, Christiane L.; Mansur, Alexandra A. P.; Mansur, Herman S.; Monteiro, Fernando J. M. (Rsc Advances, 2014)

Formulation and delivery of anti-HIV rectal microbicides: Advances and challenges - Nunes, Rute; Sarmento, Bruno; das Neves, Jose (Journal of Controlled Release, 2014)

Ganciclovir-resistant cytomegalovirus infection in renal transplantation - Vaz, R.; Barros, F.; Tavares, I.; Bustorff, M.; Ferreira, I.; Pestana, M. (Clinical Kidney Journal, 2014)
Keywords: cytomegalovirus infection; ganciclovir resistance

HA/TCP Scaffolds Obtained by Sucrose Crystal Leaching Method: Preliminary in vitro Evaluation - Rodrigues, Leonardo Ribeiro; Laranjeira, Marta de Sousa; Fernandes, Maria Helena; Monteiro, Fernando Jorge; de Carvalho Zavaglia, Cecilia Amelia (Materials Research-Ibero-American Journal of Materials, 2014)

Hippo pathway effectors control cardiac progenitor cell fate by acting as dynamic sensors of substrate mechanics and nanostructure - Mosqueira, D.; Pagliari, S.; Uto, K; Ebara, M; Romanazzo, S.; Escobedo-Lucea, C; Nakanishi, J; Taniguchi, A; Franzese, O; Di Nardo, P.; Goumans, MJ; Traversa, E; et al. (ACS Nano, 2014)
Stem cell responsiveness to extracellular matrix (ECM) composition and mechanical cues has been the subject of a number of investigations so far, yet the molecular mechanisms underlying stem cell mechano-biology still need full clarification. Here we demonstrate that the paralog proteins YAP and TAZ exert a crucial role in adult cardiac progenitor cell mechano-sensing and fate decision. Cardiac progenitors respond to dynamic modifications in substrate rigidity and nanopattern by promptly changing YAP/TAZ intracellular localization. We identify a novel activity of YAP and TAZ in the regulation of tubulogenesis in 3D environments and highlight a role for YAP/TAZ in cardiac progenitor proliferation and differentiation. Furthermore, we show that YAP/TAZ expression is triggered in the heart cells located at the infarct border zone. Our results suggest a fundamental role for the YAP/TAZ axis in the response of resident progenitor cells to the modifications in microenvironment nanostructure and mechanics, thereby contributing to the maintenance of myocardial homeostasis in the adult heart. These proteins are indicated as potential targets to control cardiac progenitor cell fate by materials design. © 2014 American Chemical Society.
Keywords: adult cardiac progenitor cell; cardiac differentiation; mechano- transduction; substrate nanotopography; YAP/TAZ

Human umbilical cord tissue-derived mesenchymal stromal cells attenuate remodeling after myocardial infarction by proangiogenic, antiapoptotic, and endogenous cell-activation mechanisms - Nascimento, D.S.; Mosqueira, D.; Sousa, L.M.; Teixeira, M.; Filipe, M.; Resende, TP; Araújo, A.F.; Valente, M.; Almeida, J.; Martins, J.P.; Santos, J.M.; Bárcia, R.N.; et al. (Stem Cell Research and Therapy, 2014)
Introduction. Among the plethora of cells under investigation to restore a functional myocardium, mesenchymal stromal cells (MSCs) have been granted considerable interest. However, whereas the beneficial effects of bone marrow MSCs (BM-MSCs) in the context of the diseased heart are widely reported, data are still scarce on MSCs from the umbilical cord matrix (UCM-MSCs). Herein we report on the effect of UCM-MSC transplantation to the infarcted murine heart, seconded by the dissection of the molecular mechanisms at play. Methods. Human umbilical cord tissue-derived MSCs (UCX®), obtained by using a proprietary technology developed by ECBio, were delivered via intramyocardial injection to C57BL/6 females subjected to permanent ligation of the left descending coronary artery. Moreover, medium produced by cultured UCX® preconditioned under normoxia (CM) or hypoxia (CMH) was collected for subsequent in vitro assays. Results: Evaluation of the effects upon intramyocardial transplantation shows that UCX® preserved cardiac function and attenuated cardiac remodeling subsequent to myocardial infarction (MI). UCX® further led to increased capillary density and decreased apoptosis in the injured tissue. In vitro, UCX®-conditioned medium displayed (a) proangiogenic activity by promoting the formation of capillary-like structures by human umbilical vein endothelial cells (HUVECs), and (b) antiapoptotic activity in HL-1 cardiomyocytes subjected to hypoxia. Moreover, in adult murine cardiac Sca- 1§ssup§+§esup§ progenitor cells (CPCs), conditioned medium enhanced mitogenic activity while activating a gene program characteristic of cardiomyogenic differentiation. Conclusions: UCX® preserve cardiac function after intramyocardial transplantation in a MI murine model. The cardioprotective effects of UCX® were attributed to paracrine mechanisms that appear to enhance angiogenesis, limit the extent of the apoptosis, augment proliferation, and activate a pool of resident CPCs. Overall, these results suggest that UCX® should be considered an alternative cell source when designing new therapeutic approaches to treat MI. © 2014 Nascimento et al.; licensee BioMed Central Ltd.

Hydrogel depots for local co-delivery of osteoinductive peptides and mesenchymal stem cells - Maia, F.R.; Barbosa, M.; Gomes, D.B.; Vale, N.; Gomes, P.; Granja, P.L.; Barrias, C.C. (Journal of Controlled Release, 2014)
The outcome of cell-based therapies can benefit from carefully designed cell carriers. A multifunctional injectable vehicle for the co-delivery of human mesenchymal stem cells (hMSCs) and osteoinductive peptides is proposed, to specifically direct hMSCs osteogenic differentiation. The osteogenic growth peptide (OGP) inspired the design of two peptides, where the bioactive portion of OGP was flanked by a protease-sensitive linker, or its scrambled sequence, to provide faster and slower release rates, respectively. Peptides were fully characterized and chemically grafted to alginate. Both OGP analogs released bioactive fragments in vitro, at different kinetics, which stimulated hMSCs proliferation and osteogenesis. hMSCs-laden OGP-alginate hydrogels were tested at an ectopic site in a xenograft mouse model. After 4 weeks, OGP-alginate hydrogels were more degraded and colonized by vascularized connective tissue than the control (without OGP). hMSCs were able to proliferate, migrate outward the hydrogels, produce endogenous extracellular matrix and mineralize it. Moreover, OGP-groups stimulated hMSCs osteogenesis, as compared with the control. Overall, the ability of the proposed platform to direct the fate of transplanted hMSCs in loco was demonstrated, and OGP-releasing hydrogels emerged as a potentially useful system to promote bone regeneration. © 2014 Elsevier B.V.
Keywords: Bone Regeneration; Co-delivery systems; Guided differentiation; Injectable alginate hydrogels; Mesenchymal Stem Cells; Osteoinductive peptides

Impact of 3-D printed PLA- and chitosan-based scaffolds on human monocyte/macrophage responses: Unraveling the effect of 3-D structures on inflammation - Almeida, C.R.; Serra, T.; Oliveira, M.I.; Planell, J.A.; Barbosa, M.A.; Navarro, M. (Acta Biomaterialia, 2014)
Recent studies have pointed towards a decisive role of inflammation in triggering tissue repair and regeneration, while at the same time it is accepted that an exacerbated inflammatory response may lead to rejection of an implant. Within this context, understanding and having the capacity to regulate the inflammatory response elicited by 3-D scaffolds aimed for tissue regeneration is crucial. This work reports on the analysis of the cytokine profile of human monocytes/macrophages in contact with biodegradable 3-D scaffolds with different surface properties, architecture and controlled pore geometry, fabricated by 3-D printing technology. Fabrication processes were optimized to create four different 3-D platforms based on polylactic acid (PLA), PLA/calcium phosphate glass or chitosan. Cytokine secretion and cell morphology of human peripheral blood monocytes allowed to differentiate on the different matrices were analyzed. While all scaffolds supported monocyte/macrophage adhesion and stimulated cytokine production, striking differences between PLA-based and chitosan scaffolds were found, with chitosan eliciting increased secretion of tumor necrosis factor (TNF)-α, while PLA-based scaffolds induced higher production of interleukin (IL)-6, IL-12/23 and IL-10. Even though the material itself induced the biggest differences, the scaffold geometry also impacted on TNF-α and IL-12/23 production, with chitosan scaffolds having larger pores and wider angles leading to a higher secretion of these pro-inflammatory cytokines. These findings strengthen the appropriateness of these 3-D platforms to study modulation of macrophage responses by specific parameters (chemistry, topography, scaffold architecture). © 2013 Acta Materialia Inc.
Keywords: 3-D scaffolds; Human macrophages; Inflammation; Rapid prototyping; Tissue engineering

The impact of nanoparticles on the mucosal translocation and transport of GLP-1 across the intestinal epithelium - Araújo, F.; Shrestha, N.; Shahbazi, M.-A.; Fonte, P.; Mäkilä, E.M.; Salonen, J.J.; Hirvonen, J.T.; Granja, P.L.; Santos, H.A.; Sarmento, B. (Biomaterials, 2014)
Glucagon like peptide-1 (GLP-1) is an incretin hormone that is in the pipeline for type 2 diabetes mellitus (T2DM) therapy. However, oral administration of GLP-1 is hindered by the harsh conditions of the gastrointestinal tract and poor bioavailability. In this study, three nanosystems composed by three different biomaterials (poly(lactide-co-glycolide) polymer (PLGA), Witepsol E85 lipid (solid lipid nanoparticles, SLN) and porous silicon (PSi) were developed and loaded with GLP-1 to study their permeability invitro. All the nanoparticles presented a size of approximately 200nm. The nanoparticles' interaction with the mucus and the intestinal cells were enhanced after coating with chitosan (CS). PSi nanosystems presented the best association efficiency (AE) and loading degree (LD), even though a high AE was also observed for PLGA nanoparticles and SLN. Among all the nanosystems, PLGA and PSi were the only nanoparticles able to sustain the release of GLP-1 in biological fluids when coated with CS. This characteristic was also maintained when the nanosystems were in contact with the intestinal Caco-2 and HT29-MTX cell monolayers. The CS-coated PSi nanoparticles showed the highest GLP-1 permeation across the intestinal invitro models. In conclusion, PLGA+CS and PSi+CS are promising nanocarriers for the oral delivery of GLP-1. © 2014 Elsevier Ltd.
Keywords: chitosan; Diabetes; Glucagon like peptide-1; nanoparticles; Oral delivery systems; Triple co-culture

Impact of the introduction of fetal central monitoring on hospital expenses with cardiotocographic paper - Amorim-Costa, C.; Ayres-de-Campos, D.; Costa-Santos, C.; Bernardes, J. (Journal of Obstetrics and Gynaecology, 2014)

In vitro analysis of the antibacterial effect of nanohydroxyapatite-ZnO composites - Grenho, L.; Jorge Monteiro, F.; Pia Ferraz, M. (Journal of Biomedical Materials Research - Part A, 2014)
Hydroxyapatite (HA) is a biocompatible and bioactive synthetic material for biomedical applications as it binds to bone and enhances bone tissue formation. Particularly, nanophased HA can mimic the dimensions of constituent components of natural tissues; can modulate enhanced osteoblast adhesion and resorption with long-term functionality of tissue engineered implants. However, HA does not inhibit bacteria from adhering onto its surface, and this has implications in the bone healing process required for patient recovery, since infection can lead to the implant failure. In the present work a composite that combines the favorable biological characteristics of nanohydroxyapatite (nanoHA) and, simultaneously, possesses antimicrobial activity as expressed by ZnO was synthesized. To determine whether the size of ZnO particles was playing an important role in inhibiting bacterial growth, ZnO particle of different sizes (from the microscale down to the nanoscale) and concentration were incorporated into nanoHA and tested. The composite samples were characterized by SEM, FT-IR, XRD, XPS and zeta potential. The antibacterial activity of the composites was investigated, as well as the biofilm formation, using both Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) microorganisms. The characterization revealed that ZnO particles were dispersed homogeneously within the nanoHA matrix. The composites antibacterial activity increased with decreasing ZnO particle size and increasing concentration. Biofilm formation tests revealed that the nanoHA-ZnO composites exhibit a strong effect against the common pathogens S. aureus and E. coli. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3726-3733, 2014. © 2013 Wiley Periodicals, Inc.
Keywords: Antibacterial; biofilm; Composite; Nanohydroxyapatite; zinc oxide

In vitro intestinal absorption of amino acid mixtures extracted from codfish (Gadus morhua L.) salting wastewater - Ferraro, V.; Ferreira Jorge, R.; Cruz, I.B.; Antunes, F.; Sarmento, B.; Castro, P.M.L.; Pintado, M.E. (International Journal of Food Science and Technology, 2014)
Summary: This study reports on the intestinal permeability of salt-containing mixtures of amino acids extracted from codfish salting wastewater. Permeability was evaluated in vitro using the Caco-2 cell line model; cell integrity during exposure to mixtures of amino acids was estimated by measuring the transepithelial electrical resistance (TEER). The effect of salt (NaCl) on the permeability and on the intestinal cell's integrity was also examined. Permeation rate (i.e. transport) was ≥95% for all amino acids except for creatine, for which it was 6%. Values for apparent permeability coefficients, Papp > 10-5 cm s-1, for mixture with isotonic concentration of NaCl suggest that amino acids are very likely to be absorbed in humans. Mixture with a hypertonic level of NaCl exerts a cytotoxic effect in intestinal cells resulting in a loss of epithelium integrity. Results show that isotonic mixture of amino acids extracted from codfish salting wastewater could be used in food, feed, cosmetic and pharmaceutical formulations. These applications could contribute to the fish industry sustainability. © 2013 Institute of Food Science and Technology.
Keywords: Absorption; Amino acids; Caco-2 cell; Codfish; Small intestine

Influence of nanohydroxyapatite surface properties on Staphylococcus epidermidis biofilm formation - Barros, J.; Grenho, L.; Manuel, C.M.; Ferreira, C.; Melo, L.; Nunes, O.C.; Monteiro, F.J.; Ferraz, M.P. (Journal of Biomaterials Applications, 2014)
Nanohydroxyapatite (nanoHA), due to its chemical properties, has appeared as an exceptionally promising bioceramic to be used as bone regeneration material. Staphylococcus epidermidis have emerged as major nosocomial pathogens associated with infections of implanted medical devices. In this work, the purpose was to study the influence of the nanoHA surface characteristics on S. epidermidis RP62A biofilm formation. Therefore, two different initial inoculum concentrations (Ci) were used in order to check if these would affect the biofilm formed on the nanoHA surfaces. Biofilm formation was followed by the enumeration of cultivable cells and by scanning electron microscopy. Surface topography, contact angle, total surface area and porosimetry of the biomaterials were studied and correlated with the biofilm data. The surface of nanoHA sintered at 830 (nanoHA830) showed to be more resistant to S. epidermidis attachment and accumulation than that of nanoHA sintered at 1000 (nanoHA1000). The biofilm formed on nanoHA830 presented differences in terms of structure, surface coverage and EPS production when compared to the one formed on nanoHA1000 surface. It was observed that topography and surface area of nanoHA surfaces had influence on the bacterial attachment and accumulation. Ci influenced bacteria attachment and accumulation on nanoHA surfaces over time. The choice of the initial inoculum concentration was relevant proving to have an effect on the extent of adherence thus being a critical point for human health if these materials are used in implantable devices. This study showed that the initial inoculum concentration and surface material properties determine the rate of microbial attachment to substrata and consequently are related to biofilm-associated infections in biomaterials. © The Author(s) 2013 Reprints and permissions: sagepub.co.uk/journalsPermissions.nav.
Keywords: biofilm formation; biomaterial roughness; biomaterial surface area; Inoculum concentration; Nanohydroxyapatite

Influence of the stiffness of three-dimensional alginate/collagen-I interpenetrating networks on fibroblast biology - Branco da Cunha, C.; Klumpers, D.D.; Li, W.A.; Koshy, S.T.; Weaver, J.C.; Chaudhuri, O.; Granja, P.L.; Mooney, D.J. (Biomaterials, 2014)
Wound dressing biomaterials are increasingly being designed to incorporate bioactive molecules to promote healing, but the impact of matrix mechanical properties on the biology of resident cells orchestrating skin repair and regeneration remains to be fully understood. This study investigated whether tuning the stiffness of a model wound dressing biomaterial could control the behavior of dermal fibroblasts. Fully interpenetrating networks (IPNs) of collagen-I and alginate were fabricated to enable gel stiffness to be tuned independently of gel architecture, polymer concentration or adhesion ligand density. Three-dimensional cultures of dermal fibroblasts encapsulated within matrices of different stiffness were shown to promote dramatically different cell morphologies, and enhanced stiffness resulted in upregulation of key-mediators of inflammation such as IL-10 and COX-2. These findings suggest that simply modulating the matrix mechanical properties of a given wound dressing biomaterial deposited at the wound site could regulate the progression of wound healing. © 2014 Elsevier Ltd.
Keywords: ECM (extracellular matrix); Inflammation; Interpenetrating networks (IPNs); Mechanical properties; Wound dressing biomaterial; Wound healing

Injectable alginate hydrogels for cell delivery in tissue engineering - Bidarra, S.J.; Barrias, C.C.; Granja, P.L. (Acta Biomaterialia, 2014)
Alginate hydrogels are extremely versatile and adaptable biomaterials, with great potential for use in biomedical applications. Their extracellular matrix-like features have been key factors for their choice as vehicles for cell delivery strategies aimed at tissue regeneration. A variety of strategies to decorate them with biofunctional moieties and to modulate their biophysical properties have been developed recently, which further allow their tailoring to the desired application. Additionally, their potential use as injectable materials offers several advantages over preformed scaffold-based approaches, namely: Easy incorporation of therapeutic agents, such as cells, under mild conditions; minimally invasive local delivery; and high contourability, which is essential for filling in irregular defects. Alginate hydrogels have already been explored as cell delivery systems to enhance regeneration in different tissues and organs. Here, the in vitro and in vivo potential of injectable alginate hydrogels to deliver cells in a targeted fashion is reviewed. In each example, the selected crosslinking approach, the cell type, the target tissue and the main findings of the study are highlighted. © 2013 Acta Materialia Inc.
Keywords: Alginate; Cell delivery; Injectable; Regeneration; Tissue engineering

Injectable MMP-sensitive alginate hydrogels as hMSC delivery systems - Fonseca, K.B.; Gomes, D.B.; Lee, K.; Santos, S.G.; Sousa, A.; Silva, E.A.; Mooney, D.J.; Granja, P.L.; Barrias, C.C. (Biomacromolecules, 2014)
Hydrogels with the potential to provide minimally invasive cell delivery represent a powerful tool for tissue-regeneration therapies. In this context, entrapped cells should be able to escape the matrix becoming more available to actively participate in the healing process. Here, we analyzed the performance of proteolytically degradable alginate hydrogels as vehicles for human mesenchymal stem cells (hMSC) transplantation. Alginate was modified with the matrix metalloproteinase (MMP)-sensitive peptide Pro-Val-Gly-Leu-Iso-Gly (PVGLIG), which did not promote dendritic cell maturation in vitro, neither free nor conjugated to alginate chains, indicating low immunogenicity. hMSC were entrapped within MMP-sensitive and MMP-insensitive alginate hydrogels, both containing cell-adhesion RGD peptides. Softer (2 wt % alginate) and stiffer (4 wt % alginate) matrices were tested. When embedded in a Matrigel layer, hMSC-laden MMP-sensitive alginate hydrogels promoted more extensive outward cell migration and invasion into the tissue mimic. In vivo, after 4 weeks of subcutaneous implantation in a xenograft mouse model, hMSC-laden MMP-sensitive alginate hydrogels showed higher degradation and host tissue invasion than their MMP-insensitive equivalents. In both cases, softer matrices degraded faster than stiffer ones. The transplanted hMSC were able to produce their own collagenous extracellular matrix, and were located not only inside the hydrogels, but also outside, integrated in the host tissue. In summary, injectable MMP-sensitive alginate hydrogels can act as localized depots of cells and confer protection to transplanted cells while facilitating tissue regeneration. © 2013 American Chemical Society.

Injectable pectin hydrogels produced by internal gelation: PH dependence of gelling and rheological properties - Moreira, H.R.; Munarin, F.; Gentilini, R.; Visai, L.; Granja, P.L.; Tanzi, M.C.; Petrini, P. (Carbohydrate Polymers, 2014)
The production of injectable pectin hydrogels by internal gelation with calcium carbonate is proposed. The pH of pectin was increased with NaOH or NaHCO3 to reach physiological values. The determination of the equivalence point provided evidence that the pH can be more precisely modulated with NaHCO3 than with NaOH. Degradation and inability to gel was observed for pectin solutions with pH 5.35 or higher. Therefore, pectin solutions with pH values varying from 3.2 (native pH) to 3.8 were chosen to produce the gels. The increase of the pH for the crosslinked hydrogels, as well as the reduction of the gelling time and their thickening, was dependent upon the amount of calcium carbonate, as confirmed by rheology. Hydrogel extracts were not cytotoxic for L-929 fibroblasts. On the overall, the investigated formulations represent interesting injectable systems providing an adequate microenvironment for cell, drug or bioactive molecules delivery. © 2013 Elsevier Ltd.
Keywords: Biomaterials; Internal gelation; Natural polymers; pectin; Tissue engineering

Kinetochore motors drive congression of peripheral polar chromosomes by overcoming random arm-ejection forces - Barisic, Marin; Aguiar, Paulo; Geley, Stephan; Maiato, Helder (Nature Cell Biology, 2014)

Long-term effects of chronic cocaine exposure throughout adolescence on anxiety and stress responsivity in a Wistar rat model - Alves, C.J.; Magalhães, A.; Melo, P.; De Sousa, L.; Tavares, M.A.; Monteiro, P.R.R.; Summavielle, T. (Neuroscience, 2014)
Adolescents display increased vulnerability to engage in drug experimentation. This is often considered a risk factor for later drug abuse. In this scenario, the permanent effects of cocaine exposure during adolescence on anxiety levels and stress responsivity, which may result in behavioral phenotypes prone to addiction, are now starting to be unveiled. Thus, the purpose of the present study was to evaluate the long-lasting effects of chronic cocaine administration during adolescence, on anxiety-like behavior and on stress response. Adolescent male Wistar rats were daily administered 45-mg cocaine/kg of body weight in three equal intraperitoneal doses with 1-h interval, from postnatal day (PND) 35 to 50. The effects of cocaine administration on anxiety levels, assessed in the Elevated Plus Maze (EPM), and on social stress response, assessed in the resident-intruder paradigm (R/I), were evaluated 10. days after withdrawal, when rats were reaching the adulthood. The underlying dopaminergic activity, and the corticosterone and testosterone levels were determined. Our results showed that cocaine induced long-lasting alterations in the hypothalamus-pituitary-adrenals (HPA) axis function and in testosterone levels. Such alterations resulted in significant and enduring changes in behavioral responses to environmental challenges, such as the EPM and R/I, including the evaluation of potential threats that may lead to high-risk behavior and low-benefit choices. This was further supported by an altered dopaminergic function in the amygdala and hippocampus. The present findings provide new insights into how the use of cocaine during adolescent development may modulate emotional behavior later in life. Compromised ability to recognize and deal with potential threats is an important risk factor to perpetuate compulsive drug seeking and relapse susceptibility. © 2014 IBRO.
Keywords: Adolescence; anxiety; Cocaine; corticosterone; Dopaminergic system; Social stress

Macrophages stimulate gastric and colorectal cancer invasion through EGFR Y 1086, c-Src, Erk1/2 and Akt phosphorylation and smallGTPase activity - Cardoso, A.P.; Pinto, M.L.; Pinto, A.T.; Oliveira, M.I.; Pinto, M.T.; Gonçalves, R.; Relvas, J.B.; Figueiredo, C.; Seruca, R.; Mantovani, A.; Mareel, M.; Barbosa, M.A.; et al. (Oncogene, 2014)
The interactions between cancer cells and their microenvironment are crucial for malignant progression, as they modulate invasion-related activities. Tumor-associated macrophages are generally considered allies in the process of tumor progression in several types of cancer, although their role on gastric and colorectal carcinomas is still poorly understood. In this report, we studied the influence of primary human macrophages on gastric and colorectal cancer cells, considering invasion, motility/migration, proteolysis and activated intracellular signaling pathways. We demonstrated that macrophages stimulate cancer cell invasion, motility and migration, and that these effects depend on matrix metalloproteinase (MMP) activity and on the activation of epidermal growth factor receptor (EGFR) (at the residue Y 1086), PLC-γ (phospholipase C-gamma) and Gab1 (GRB2-associated binding protein-1), as evidenced by siRNA (small interference RNA) experiments. Epidermal growth factor (EGF)-immunodepletion impaired macrophage-mediated cancer cell invasion and motility, suggesting that EGF is the pro-invasive and pro-motile factor produced by macrophages. Macrophages also induced gastric and colorectal cancer cell phosphorylation of Akt, c-Src and ERK1/2, and led to an increase of RhoA and Cdc42 activity. Interestingly, whereas macrophage-mediated cancer cell c-Src and ERK1/2 phosphorylation occurred downstream EGFR activation, Akt phosphorylation seems to be a parallel event, taking place in an EGFR-independent manner. The involvement of EGF, EGFR-downstream signaling partners and MMPs in macrophage-mediated invasion provides novel insights into the molecular crosstalk established between cancer cells and macrophages, opening new perspectives for the design of new and more efficient therapeutic strategies to counteract cancer cell invasion. © 2014 Macmillan Publishers Limited.
Keywords: cancer cell invasion; colon cancer; Gastric cancer; invasion-related signaling pathways; Macrophages; tumor microenvironment

Mad2 checkpoint gene silencing using epidermal growth factor receptor-targeted chitosan nanoparticles in non-small cell lung cancer model - Nascimento, A.V.; Singh, A.; Bousbaa, H.; Ferreira, D.; Sarmento, B.; Amiji, M.M. (Molecular Pharmaceutics, 2014)
RNA interference has emerged as a powerful strategy in cancer therapy because it allows silencing of specific genes associated with tumor progression and resistance. Mad2 is an essential mitotic checkpoint component required for accurate chromosome segregation during mitosis, and its complete abolition leads to cell death. We have developed an epidermal growth factor receptor (EGFR)-targeted chitosan system for silencing the Mad2 gene as a strategy to efficiently induce cell death in EGFR overexpressing human A549 non-small cell lung cancer cells. Control and EGFR-targeted chitosan nanoparticles loaded with small interfering RNAs (siRNAs) against Mad2 were formulated and characterized for size, charge, morphology, and encapsulation efficiency. Qualitative and quantitative intracellular uptake studies by confocal imaging and flow cytometry, respectively, showed time-dependent enhanced and selective intracellular internalization of EGFR-targeted nanoparticles compared to nontargeted system. Targeted nanoparticles showed nearly complete depletion of Mad2 expression in A549 cells contrasting with the partial depletion in the nontargeted system. Accordingly, Mad2-silencing-induced apoptotic cell death was confirmed by cytotoxicity assay and flow cytometry. Our results demonstrate that EGFR-targeted chitosan loaded with Mad2 siRNAs is a potent delivery system for selective killing of cancer cells.
Keywords: chitosan nanoparticles; Epidermal growth factor receptor; Mad2 gene; non-small cell lung cancer; RNA interference; tumor targeting

Magnetic Bioinspired Hybrid Nanostructured Collagen-Hydroxyapatite Scaffolds Supporting Cell Proliferation and Tuning Regenerative Process - Tampieri, Anna; Iafisco, Michele; Sandri, Monica; Panseri, Silvia; Cunha, Carla; Sprio, Simone; Savini, Elisa; Uhlarz, Marc; Herrmannsdoerfer, Thomas (Acs Applied Materials & Interfaces, 2014)

Matrix-driven formation of mesenchymal stem cell-extracellular matrix microtissues on soft alginate hydrogels - Maia, F.R.; Fonseca, K.B.; Rodrigues, G.; Granja, P.L.; Barrias, C.C. (Acta Biomaterialia, 2014)
Mesenchymal stem cells (MSCs) can be made to rearrange into microtissues in response to specific matrix cues, a process that depends on a balance between cell-matrix and cell-cell interactions. The effect of such cues, and especially their interplay, is still not fully understood, particularly in three-dimensional (3-D) systems. Here, the behaviour of human MSCs cultured within hydrogel matrices with tailored stiffness and composition was evaluated. MSC aggregation occurred only in more compliant matrices (G′ ≤ 120 Pa), when compared to stiffer ones, both in the presence and in the absence of matrix-bound arginine-glycine-aspartic acid cell-adhesion ligands (RGD; 0, 100 and 200 μM). Fibronectin assembly stabilized cell-cell contacts within aggregates, even in non-adhesive matrices. However, MSCs were able to substantially contract the artificial matrix only when RGD was present. Moreover, compliant matrices facilitated cell proliferation and provided an environment conducive for MSC osteogenic differentiation, even without RGD. Cell interactions with the original matrix became less important as time progressed, while the de novo-produced extracellular matrix became a more critical determinant of cell fate. These data provide further insights into the mechanisms by which MSCs sense their microenvironment to organize into tissues, and provide new clues to the design of cell-instructive 3-D matrices. © 2014 Published by Elsevier Ltd. on behalf of Acta Materialia Inc.
Keywords: cell aggregation; Cell traction; Cell-matrix interactions; Hydrogels; Viscoelastic properties

Microfluidics co-culture systems for studying tooth innervation - Pagella, Pierfrancesco; Neto, Estrela; Jimenez-Rojo, Lucia; Lamghari, Meriem; Mitsiadis, Thimios A. (Frontiers in Physiology, 2014)

Modified-chitosan/siRNA nanoparticles downregulate cellular CDX2 expression and cross the gastric mucus barrier - Sadio, A.; Gustafsson, J.K.; Pereira, B.; Gomes, C.P.; Hansson, G.C.; David, L.; Pêgo, A.P.; Almeida, R. (PLoS ONE, 2014)
Development of effective non-viral vectors is of crucial importance in the implementation of RNA interference in clinical routine. The localized delivery of siRNAs to the gastrointestinal mucosa is highly desired but faces specific problems such as the stability in gastric acidity conditions and the presence of the mucus barrier. CDX2 is a transcription factor critical for intestinal differentiation being involved in the initiation and maintenance of gastrointestinal diseases. Specifically, it is the trigger of gastric intestinal metaplasia which is a precursor lesion of gastric cancer. Its expression is also altered in colorectal cancer, where it may constitute a lineage-survival oncogene. Our main objective was to develop a nanoparticle-delivery system of siRNA targeting CDX2 using modified chitosan as a vector. CDX2 expression was assessed in gastric carcinoma cell lines and nanoparticles behaviour in gastrointestinal mucus was tested in mouse explants. We show that imidazolemodified chitosan and trimethylchitosan/siRNA nanoparticles are able to downregulate CDX2 expression and overpass the gastric mucus layer but not colonic mucus. This system might constitute a potential therapeutic approach to treat CDX2-dependent gastric lesions. © 2014 Sadio et al.

Modulation of human dermal microvascular endothelial cell and human gingival fibroblast behavior by micropatterned silica coating surfaces for zirconia dental implant applications - Laranjeira, M.S.; Carvalho, Â.; Pelaez-Vargas, A.; Hansford, D.; Ferraz, M.P.; Coimbra, S.; Costa, E.; Santos-Silva, A.; Fernandes, M.H.; Monteiro, F.J. (Science and Technology of Advanced Materials, 2014)
Dental ceramic implants have shown superior esthetic behavior and the absence of induced allergic disorders when compared to titanium implants. Zirconia may become a potential candidate to be used as an alternative to titanium dental implants if surface modifications are introduced. In this work, bioactive micropatterned silica coatings were produced on zirconia substrates, using a combined methodology of sol-gel processing and soft lithography. The aim of the work was to compare the in vitro behavior of human gingival fibroblasts (HGFs) and human dermal microvascular endothelial cells (HDMECs) on three types of silica-coated zirconia surfaces: flat and micropatterned (with pillars and with parallel grooves). Our results showed that cells had a higher metabolic activity (HGF, HDMEC) and increased gene expression levels of fibroblast-specific protein-1 (FSP-1) and collagen type I (COL I) on surfaces with pillars. Nevertheless, parallel grooved surfaces were able to guide cell growth. Even capillary tube-like networks of HDMEC were oriented according to the surface geometry. Zirconia and silica with different topographies have shown to be blood compatible and silica coating reduced bacteria adhesion. All together, the results indicated that microstructured bioactive coating seems to be an efficient strategy to improve soft tissue integration on zirconia implants, protecting implants from peri-implant inflammation and improving long-term implant stabilization. This new approach of micropatterned silica coating on zirconia substrates can generate promising novel dental implants, with surfaces that provide physical cues to guide cells and enhance their behavior. © 2014 National Institute for Materials Science.
Keywords: bacteria adhesion; Biomaterials; hemolysis; human dermal microvascular endothelial cells (HDMECs); human gingival fibroblasts (HGFs); Micropatterning; Soft lithography

Mucoadhesive polymers in the design of nano-drug delivery systems for administration by non-parenteral routes: A review - Sosnik, Alejandro; das Neves, Jose; Sarmento, Bruno (Progress in Polymer Science, 2014)

A Multicompartment Holder for Spinner Flasks Improves Expansion and Osteogenic Differentiation of Mesenchymal Stem Cells in Three-Dimensional Scaffolds - Teixeira, Graciosa Q.; Barrias, Cristina C.; Lourenco, Ana H.; Goncalves, Raquel M. (Tissue Engineering Part C-Methods, 2014)

Nanoparticle-based drug delivery to improve the efficacy of antiretroviral therapy in the central nervous system - Gomes, M.J.; Das Neves, J.; Sarmento, B. (International Journal of Nanomedicine, 2014)
Antiretroviral drug therapy plays a cornerstone role in the treatment of human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome patients. Despite obvious advances over the past 3 decades, new approaches toward improved management of infected individuals are still required. Drug distribution to the central nervous system (CNS) is required in order to limit and control viral infection, but the presence of natural barrier structures, in particular the blood-brain barrier, strongly limits the perfusion of anti-HIV compounds into this anatomical site. Nanotechnology-based approaches may help providing solutions for antiretro-viral drug delivery to the CNS by potentially prolonging systemic drug circulation, increasing the crossing and reducing the efflux of active compounds at the blood-brain barrier, and providing cell/tissue-targeting and intracellular drug delivery. After an initial overview on the basic features of HIV infection of the CNS and barriers to active compound delivery to this anatomical site, this review focuses on recent strategies based on antiretroviral drug-loaded solid nanoparticles and drug nanosuspensions for the potential management of HIV infection of the CNS. © 2014 Gomes et al.
Keywords: Blood-brain barrier; drug targeting; Efflux transporters; HIV/AIDS; Protease inhibitors

Natriuretic peptide system modulation in uninephrectomized rats - Santos-Araújo, C.; Roncon-Albuquerque Jr., R.; Moreira-Rodrigues, M.; Henriques-Coelho, T.; Quelhas-Santos, J.; Faria, B.; Sampaio-Maia, B.; Leite-Moreira, A.F.; Pestana, M. (Experimental and Clinical Cardiology, 2014)
BACKGROUND: Cardiac activation of the natriuretic peptide (NP) system plays a major role in the renal adaptations to volume, expansion (VE). However, its role after uninephrectomy (Unx) remains to be elucidated. In the present study, we evaluated cardiac hemodynamics, plasma NP-Type B (BNP) levels nd NP receptor A (NPR-A) and C (NPR-C) expression in the renal cortex (RC) and medulla (RM) of Sham and Unx rats. METHODS: Male Wistar-Han rats (n=42) were randomly assigned to Unx or Sham surgery. Non-invasive blood pressure (BP), invasive left ventricular (LV) hemodynamics and natriuretic response to VE were performed and plasma was collected for BNP determination, 2, 10 and 26 weeks after surgery. In addition, samples from RC and RM were obtained for NPR-A and -C quantification (RT-PCR and western-blot). RESULTS: In Unx, blood pressure elevation and reduced natriuretic response to VE were observed. Although plasma BNP levels increased overtime, no LV dysfunction or myocardial BNP gene activation was observed in Unx. NPR-A mRNA in RC and RM were significantly increased in Unx at 26 weeks. This was accompanied by decreased NPR-C mRNA in the RM in Unx at 10 and 26 weeks, with no differences detected in the RC. CONCLUSIONS: In our experimentalmodel of Unx, progressive BP elevation and reduced natriuretic response to VE were accompanied by modulation of NPR-A and -C expression, in both the RC and RM, in the absence of cardiac activation of the NP system. Our results suggest a local renal modulation of the NP system after Unx. © 2013 et al.; licensee Cardiology Academic Press.
Keywords: BNP; Hypertension; Natriuretic peptide receptor; Uninephrectomy

Neonatal human dermal fibroblasts immobilized in RGD-alginate induce angiogenesis - Guerreiro, S.G.; Oliveira, M.J.; Barbosa, M.A.; Soares, R.; Granja, P.L. (Cell Transplantation, 2014)
Promoting angiogenesis in a damaged tissue is a major challenge for tissue regeneration. Recent findings in tissue engineering suggest that fibroblasts (FBs) play an important role in orchestrating the angiogenic process. Fibroblasts maintain the structural integrity of connective tissue by continuously secreting growth factors and extracellular matrix precursors, which are essential for endothelial cell (EC) adhesion and spreading, thus playing a crucial role in angiogenesis. We hypothesized that FBs immobilized in alginate gels grafted with the RGD peptidic sequence could influence the recruitment of ECs to improve vascularization. In this work, the modulation of immobilized human FBs within the 3D synthetic extracellular matrix was assessed. Experiments using cocultures of ECs and FBs in indirect contact as well as angiogenic assays were performed to assess the influence of FBs immobilized in RGD-alginate in ECs' viability, stabilization, sprouting, and assembly into capillary-like structures. This study demonstrates the ability of FBs immobilized within RGD-alginate microspheres to modulate and support capillary-like structures' assembly. These findings indicate that the microenvironment created by these stromal cells in the scaffold modulates capillary morphogenesis, thus stimulating angiogenesis in situ and can potentially be used in regenerative medicine in clinical scenarios where vascularization is essential. © 2014 Cognizant Comm. Corp.
Keywords: Alginate; angiogenesis; Endothelial cells (ECs); Fibroblasts (FBs); RGD peptide: Injectable biomaterials

Optimization of the production of solid Witepsol nanoparticles loaded with rosmarinic acid - Campos, D.A.; Madureira, A.R.; Gomes, A.M.; Sarmento, B.; Pintado, M.M. (Colloids and Surfaces B: Biointerfaces, 2014)
During the last decade there has been a growing interest in the formulation of new food and nutraceutical products containing compounds with antioxidant activity. Unfortunately, due to their structure, certain compounds such as polyphenols, in particular rosmarinic acid (RA) are not stable and may interact easily with matrices in which they are incorporated. To overcome such limitations, the formulation of loaded polyphenols nanoparticles can offer an efficient solution to protect such compounds. Based on this rationale, the aim of this study was to prepare solid lipid nanoparticles (SLNs) loaded with RA using a hot melt ultrasonication method, where Witepsol H15 was used as lipid and Polysorbate 80 (Tween 80) as surfactant, following a 32 fractional factorial design, resulting in the use of 3 different percentages of surfactant (viz. 1, 2 and 3%, v/v) and lipid (0.5, 1.0 and 1.5%, w/v). The stability of the nanoparticles systems were tested during 28d in aqueous solution stored at refrigeration temperature (ca. 5°C), tracking the mean particle size of different formulations by photon correlation spectroscopy. To confirm RA entrapment, thermal analyses of the nanoparticles by DSC and FTIR were performed. The association efficiencies percentages (AE%) were determined using HPLC to quantitatively assess the RA in supernatants. Results showed that Witepsol H15 produced nanoparticles with initial mean diameters between 270 and 1000nm, yet over time, a slight increase occurred, but without occurrence of aggregation. The AE% showed a high percentage of encapsulation (ca. 99%), which reveals low polyphenol releases from SLNs throughout storage time. In general, results showed a successful production of SLNs with properties that can be used to food applications. © 2013 Elsevier B.V.
Keywords: Optimization; Rosmarinic acid; SLNs; Witepsol

A PEX7-Centered Perspective on the Peroxisomal Targeting Signal Type 2-Mediated Protein Import Pathway - Rodrigues, Tony A.; Alencastre, Ines S.; Francisco, Tania; Brites, Pedro; Fransen, Marc; Grou, Claudia P.; Azevedo, Jorge E. (Molecular and Cellular Biology, 2014)

Plasma and urine renalase levels and activity during the recovery of renal function in kidney transplant recipients - Quelhas-Santos, J.; Soares-Silva, I.; Fernandes-Cerqueira, C.; Simões-Silva, L.; Ferreira, I.; Carvalho, C.; Coentrão, L.; Vaz, R.; Sampaio-Maia, B.; Pestana, M. (Experimental Biology and Medicine, 2014)
Renalase is a recently described enzyme secreted by the kidney into both plasma and urine, where it was suggested to degrade catecholamines contributing to blood pressure control. While there is a controversy regarding the relationship between renal function and plasma renalase levels, there is virtually no data in humans on plasma renalase activity as well as on both urine renalase levels and activity. We prospectively examined the time course of plasma and urine renalase levels and activity in 26 end-stage renal disease (ESRD) patients receiving a cadaver kidney transplant (cadaver kidney recipients [CKR]) before surgery and during the recovery of renal function up to day 90 post transplant. The relationship with sympathetic and renal dopaminergic activities was also evaluated. The recovery of renal function in CKR closely predicted decreases in plasma renalase levels (r = 0.88; P < 0.0001), urine renalase levels (r = 0.75; P < 0.0001) and urine renalase activity (r = 0.56; P < 0.03), but did not predict changes in plasma renalase activity (r = -0.02; NS). Plasma norepinephrine levels positively correlated with plasma renalase levels (r = 0.64, P < 0.002) as well as with urine renalase levels and activity (r = 0.47 P < 0.02; r = 0.71, P < 0.0005, respectively) and negatively correlated with plasma renalase activity (r = -0.57, P < 0.002). By contrast, plasma epinephrine levels positively correlated with plasma renalase activity (r = 0.67, P < 0.0001) and negatively correlated with plasma renalase levels (r = -0.62, P < 0.003). A significant negative relationship was observed between urine dopamine output and urine renalase levels (r = -0.48; P < 0.03) but not with urine renalase activity (r = -0.33, NS). We conclude that plasma and urine renalase levels closely depend on renal function and sympathetic nervous system activity. It is suggested that epinephrine-mediated activation of circulating renalase may occur in renal transplant recipients with good recovery of renal function. The increase in plasma renalase activity observed in ESRD patients and renal transplant recipients can be explained on the basis of reduced inhibition of the circulating enzyme. © 2014 by the Society for Experimental Biology and Medicine.
Keywords: catecholamines; CKD; renal function; renal transplant; renalase

Plasma Renalase in Chronic Kidney Disease: Differences and Similarities between Humans and Rats - Quelhas-Santos, Janete; Pestana, Manuel (Current hypertension reviews, 2014)

Poly(trimethylene carbonate-co-ε-caprolactone) promotes axonal growth - Rocha, D.N.; Brites, P.; Fonseca, C.; Pêgo, A.P. (PLoS ONE, 2014)
Mammalian central nervous system (CNS) neurons do not regenerate after injury due to the inhibitory environment formed by the glial scar, largely constituted by myelin debris. The use of biomaterials to bridge the lesion area and the creation of an environment favoring axonal regeneration is an appealing approach, currently under investigation. This work aimed at assessing the suitability of three candidate polymers - poly(ε-caprolactone), poly(trimethylene carbonate-co-ε-caprolactone) (P(TMC-CL)) (11:89 mol%) and poly(trimethylene carbonate) - with the final goal of using these materials in the development of conduits to promote spinal cord regeneration. Poly(L-lysine) (PLL) coated polymeric films were tested for neuronal cell adhesion and neurite outgrowth. At similar PLL film area coverage conditions, neuronal polarization and axonal elongation was significantly higher on P(TMC-CL) films. Furthermore, cortical neurons cultured on P(TMC-CL) were able to extend neurites even when seeded onto myelin. This effect was found to be mediated by the glycogen synthase kinase 3β (GSK3β) signaling pathway with impact on the collapsin response mediator protein 4 (CRMP4), suggesting that besides surface topography, nanomechanical properties were implicated in this process. The obtained results indicate P(TMC-CL) as a promising material for CNS regenerative applications as it promotes axonal growth, overcoming myelin inhibition. © 2014 Rocha et al.

The potential utility of chitosan micro/nanoparticles in the treatment of gastric infection - Gonçalves, I.C.; Henriques, P.C.; Seabra, C.L.; Martins, M.C.L. (Expert Review of Anti-Infective Therapy, 2014)
Gastric infections are mainly caused by Helicobacter pylori (H. pylori), a bacterium that colonizes the gastric mucosa of over 50% of the world's population. Chronic H. pylori infection has been associated with gastric diseases such as chronic gastritis, peptic ulcer and gastric adenocarcinoma. Current eradication treatment relies on antibiotic-based therapies that are unsuccessful in approximately 20% of the patients. Chitosan, a natural and cationic polysaccharide has been investigated in the treatment of H. pylori infection. Due to its mucoadhesive properties, it has been used in the form of micro/nanoparticles, polyelectrolyte complexes or coatings as antibiotic encapsulation systems for gastric delivery, but alternative molecules may also be incorporated. It has been recently proposed that chitosan can also be used for H. pylori binding and scavenging from the host stomach due to its antimicrobial/binding properties. In this manuscript, a brief description of the use of chitosan in H. pylori treatment is reviewed. © Informa UK, Ltd.
Keywords: Biomaterials; chitosan; Crosslinking; Drug delivery; Gastric cancer; Helicobacter pylori; Microspheres; mucoadhesion; nanoparticles; Polyelectrolytes

The predominance of M2-polarized macrophages in the stroma of low-hypoxic bladder tumors is associated with BCG immunotherapy failure - Lima, L.; Oliveira, D.; Tavares, A.; Amaro, T.; Cruz, R.; Oliveira, M.J.; Ferreira, J.A.; Santos, L. (Urologic Oncology: Seminars and Original Investigations, 2014)
Objective: Bacillus Calmette-Guérin (BCG) immunotherapy is the gold standard treatment for superficial bladder tumors with intermediate/high risk of recurrence or progression. However, approximately 30% of patients fail to respond to the treatment. Effective BCG therapy needs precise activation of the type 1 helper cells immune pathway. Tumor-associated macrophages (TAMs) often assume an immunoregulatory M2 phenotype and may directly interfere with the BCG-induced antitumor immune response. Thus, we aim to clarify the influence of TAMs, in particular of the M2 phenotype in stroma and tumor areas, in BCG treatment outcome. Patients and methods: The study included 99 patients with bladder cancer treated with BCG. Tumors resected before treatment were evaluated using immunohistochemistry for CD68 and CD163 antigens, which identify a lineage macrophage marker and a M2-polarized specific cell surface receptor, respectively. CD68+ and CD163+ macrophages were evaluated within the stroma and tumor areas, and high density of infiltrating cells spots were selected for counting. Hypoxia, an event known to modulate macrophage phenotype, was also assessed through hypoxia induced factor (HIF)-1α expression. Results: Patients in whom BCG failed had high stroma-predominant CD163+ macrophage counts (high stroma but low tumor CD163+ macrophages counts) when compared with the ones with a successful treatment (71% vs. 47%, P = 0.017). Furthermore, patients presenting this phenotype showed decreased recurrence-free survival (log rank, P = 0.008) and a clear 2-fold increased risk of BCG treatment failure was observed in univariate analysis (hazard ratio = 2.343; 95% CI: 1.197-4.587; P = 0.013). Even when adjusted for potential confounders, such as age and therapeutic scheme, multivariate analysis revealed 2.6-fold increased risk of recurrence (hazard ratio = 2.627; 95% CI: 1.340-5.150; P = 0.005). High stroma-predominant CD163+ macrophage counts were also associated with low expression of HIF-1α in tumor areas, whereas high counts of CD163+ in the tumor presented high expression of HIF-1α in tumor nests. Conclusions: TAMs evaluation using CD163 is a good indicator of BCG treatment failure. Moreover, elevated infiltration of CD163+ macrophages, predominantly in stroma areas but not in the tumor, may be a useful indicator of BCG treatment outcome, possibly owing to its immunosuppressive phenotype. © 2014 Elsevier Inc.
Keywords: BCG immunotherapy; Bladder cancer; CD163; CD68; Tumor-associated macrophages

Primary bone marrow mesenchymal stromal cells rescue the axonal phenotype of twitcher mice - Miranda, C.O.; Teixeira, C.A.; Sousa, V.F.; Santos,TE; Liz, M.A.; Marques,AM; Pinto-Do-Ó, P.; Sousa, M.M. (Cell Transplantation, 2014)
Krabbe's disease (KD) is a demyelinating disorder caused by the deficiency of lysosomal galactocerebrosidase (GALC), affecting both the central (CNS) and the peripheral nervous system (PNS). A current therapy, hematopoietic stem cell transplantation (HSCT), is ineffective at correcting the PNS pathology. We have previously shown that systemic delivery of immortalized bone marrow-derived murine mesenchymal stromal cells (BM-MSCs) diminishes the neuropathology of transplanted Twitcher mice, a murine model of KD. In this study, to move one step closer to clinical application, the effectiveness of a systematic delivery of primary BM-MSCs to promote recovery of the Twitcher PNS was assessed. Primary BM-MSCs grafted to the Twitcher sciatic nerve led to increased GALC activity that was not correlated to decreased psychosine (the toxic GALC substrate) accumulation. Nevertheless, BM-MSC transplantation rescued the axonal phenotype of Twitcher mice in the sciatic nerve, with an increased density of both myelinated and unmyelinated axons in transplanted animals. Whereas no increase in myelination was observed, upon transplantation an increased proliferation of Schwann cell precursors occurred. Supporting these findings, in vitro, BM-MSCs promoted neurite outgrowth of Twitcher sensory neurons and proliferation of Twitcher Schwann cells. Moreover, BM-MSCs expressed nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) and promoted increased BDNF synthesis by neighboring Schwann cells. Besides their action in neurons and glia, BM-MSCs led to macrophage activation in Twitcher sciatic nerves. In summary, primary BM-MSCs diminish the neuropathology of Twitcher sciatic nerves by coordinately affecting neurons, glia, and macrophages. © 2014 Cognizant Comm. Corp.
Keywords: Axonal degeneration; Bone marrow-derived mesenchymal stromal cells (BM-MSCs); Krabbe's disease (KD); Twitcher mice

Production, characterization and biocompatibility of marine collagen matrices from an alternative and sustainable source: The sea urchin Paracentrotus lividus - Di Benedetto, C.; Barbaglio, A.; Martinello, T.; Alongi, V.; Fassini, D.; Cullorà, E.; Patruno, M.; Bonasoro, F.; Barbosa, M.A.; Carnevali, M.D.C.; Sugni, M. (Marine Drugs, 2014)
Collagen has become a key-molecule in cell culture studies and in the tissue engineering field. Industrially, the principal sources of collagen are calf skin and bones which, however, could be associated to risks of serious disease transmission. In fact, collagen derived from alternative and riskless sources is required, and marine organisms are among the safest and recently exploited ones. Sea urchins possess a circular area of soft tissue surrounding the mouth, the peristomial membrane (PM), mainly composed by mammalian-like collagen. The PM of the edible sea urchin Paracentrotus lividus therefore represents a potential unexploited collagen source, easily obtainable as a food industry waste product. Our results demonstrate that it is possible to extract native collagen fibrils from the PM and produce suitable substrates for in vitro system. The obtained matrices appear as a homogeneous fibrillar network (mean fibril diameter 30-400 nm and < 2 μm) and display remarkable mechanical properties in term of stiffness (146 ± 48 MPa) and viscosity (60.98 ± 52.07 GPa·s). In vitro tests with horse pbMSC show a good biocompatibility in terms of overall cell growth. The obtained results indicate that the sea urchin P. lividus can be a valuable low-cost collagen source for mechanically resistant biomedical devices.
Keywords: Biocompatibility; Collagen matrix; Mesenchimal stromal cells; Native fibril; Sea urchin collagen; Tissue regeneration

Prolonged saltatory fetal heart rate pattern leading to newborn metabolic acidosis - Nunes, I.; Ayres-de-Campos, D.; Kwee, A.; Rosen, K. G. (Clinical and Experimental Obstetrics & Gynecology, 2014)

Propolis varnish: Antimicrobial properties against cariogenic bacteria, cytotoxicity, and sustained-release profile - De Luca, M.P.; Franca, J.R.; Macedo, F.A.F.F.; Grenho, L.; Cortes, M.E.; Faraco, A.A.G.; Moreira, A.N.; Santos, V.R. (BioMed Research International, 2014)
Varnishes are preparations that differ in the polymeric matrix and therapeutical agents. In dentistry they are used to prevent caries. In this study we developed a propolis varnish, considering propolis properties against cariogenic bacteria. To a chitosan polymeric base (CHV) was added ethanolic propolis extract in different concentrations: PV1 (5%), PV2 (10%), and PV3 (15%). Antimicrobial activity was carried out against Streptococcus mutans (SM), Streptococcus sanguinis (SG), Streptococcus salivarius (SS), and Lactobacillus casei (LC) through agar diffusion method. The three propolis concentrations incorporated were effective in inhibiting the growth of all microorganisms, but without significant difference between the zones of inhibition observed. Cytotoxicity assay was done by MTT method. Data were analyzed by one-way ANOVA and Bonferroni test. None of the varnishes were cytotoxic, keeping 80% of viable cells, while CHV allowed cellular proliferation (120%). Sustained-release test was carried out by applying 40 μL of each varnish in the buccal surface of bovine teeth and kept in an ethanol/water solution removed in regular times. According to the "independent model approach," the release profiles were distinct from each varnish and the most prolonged was PV3 (8 weeks). Varnish formulations had satisfactory antimicrobial activity against cariogenic bacteria and have a low cytotoxicity (<50%). © 2014 Mariana P. De Luca et al.

Quality by Design: Discussing and Assessing the Solid Dispersions Risk - Chaves, Luise L.; Vieira, Alexandre C. C.; Reis, Salette; Sarmento, Bruno; Ferreira, Domingos C. (Current Drug Delivery, 2014)

Rescue of wild-type E-cadherin expression from nonsense-mutated cancer cells by a suppressor-tRNA - Bordeira-Carriço, R.; Ferreira, D.; Mateus, D.D.; Pinheiro, H.; Pêgo, A.P.; Santos, M.A.S.; Oliveira, C. (European Journal of Human Genetics, 2014)
Hereditary diffuse gastric cancer (HDGC) syndrome, although rare, is highly penetrant at an early age, and is severe and incurable because of ineffective screening tools and therapy. Approximately 45% of HDGC families carry germline CDH1/E-cadherin alterations, 20% of which are nonsense leading to premature protein truncation. Prophylactic gastrectomy is the only recommended approach for all asymptomatic CDH1 mutation carriers. Suppressor-tRNAs can replace premature stop codons (PTCs) with a cognate amino acid, inducing readthrough and generating full-length proteins. The use of suppressor-tRNAs in HDGC patients could therefore constitute a less invasive therapeutic option for nonsense mutation carriers, delaying the development of gastric cancer. Our analysis revealed that 23/108 (21.3%) of E-cadherin-mutant families carried nonsense mutations that could be potentially corrected by eight suppressor-tRNAs, and arginine was the most frequently affected amino acid. Using site-directed mutagenesis, we developed an arginine suppressor-tRNA vector to correct one HDGC nonsense mutation. E-cadherin-deficient cell lines were transfected with plasmids carrying simultaneously the suppressor-tRNA and wild-type or mutant CDH1 mini-genes. RT-PCR, western blot, immunofluorescence, flow cytometry and proximity ligation assay (PLA) were used to establish the model, and monitor mRNA and protein expression and function recovery from CDH1 vectors. Cells expressing a CDH1 mini-gene, carrying a nonsense mutation and the suppressor-tRNA, recovered full-length E-cadherin expression and its correct localization and incorporation into the adhesion complex. This is the first demonstration of functional recovery of a mutated causative gene in hereditary cancer by cognate amino acid replacement with suppressor-tRNAs. Of the HDGC families, 21.3% are candidates for correction with suppressor-tRNAs to potentially delay cancer onset. © 2014 Macmillan Publishers Limited. All rights reserved.
Keywords: hereditary diffuse gastric cancer (HDGC); nonsense suppression; Premature termination codon (PTC); Suppressor-tRNA

Resveratrol as a Natural Anti-Tumor Necrosis Factor-alpha Molecule: Implications to Dendritic Cells and Their Crosstalk with Mesenchymal Stromal Cells - Silva, Andreia M.; Oliveira, Marta I.; Sette, Laura; Almeida, Catarina R.; Oliveira, Maria J.; Barbosa, Mario A.; Santos, Susana G. (Plos One, 2014)

Role of protein environment and bioactive polymer grafting in the S. epidermidis response to titanium alloy for biomedical applications - Vasconcelos, D.M.; Falentin-Daudré, C.; Blanquaert, D.; Thomas, D.; Granja, P.L.; Migonney, V. (Materials Science and Engineering C, 2014)
Joint implant-related infections, namely by Staphylococci, are a worldwide problem, whose consequences are dramatic. Various methods are studied to fight against these infections. Here, the proposed solution consists in grafting a bioactive polymer on joint implant surfaces in order to allow the control of the interactions with the living system. In this study, sodium styrene sulfonate, bearing sulfonate groups, was grafted on the surface of titanium alloys. Scanning Electron Microscopy, colorimetric method, Fourier-transformed infrared spectroscopy and contact angle measurements were applied to characterize the surfaces. Bacterial adhesion studies were studied on poly(sodium styrene sulfonate) grafted Ti6Al4V and Ti6Al4V surfaces previously adsorbed by proteins involved in the bacteria adhesion process. Fibrinogen and fibronectin were demonstrated to increase staphylococcal adhesion on Ti6Al4V surfaces. Ti6Al4V grafted sodium styrene sulfonate surfaces inhibited the adhesion of Staphylococcus epidermidis in 37% and 13% on pre-adsorbed surfaces with fibrinogen and fibronectin, respectively. The mechanism of the observed inhibiting bacteria adhesion properties is related to the differences of proteic conformations induced by poly(sodium styrene sulfonate) grafting.
Keywords: Bacterial adhesion; Bioactive polymer; Poly(sodium styrene sulfonate) (polyNaSS); Protein adsorption; Surface modification; Titanium alloy

Role of sparc in bone remodeling and cancer-related bone metastasis - Ribeiro, N.; Sousa, S.R.; Brekken, R.A.; Monteiro, F.J. (Journal of Cellular Biochemistry, 2014)
There is a growing socioeconomic recognition that clinical bone diseases such as bone infections, bone tumors and osteoporotic bone loss mainly associated with ageing, are major issues in today's society. SPARC (secreted protein, acidic and rich in cysteine), a matricellular glycoprotein, may be a promising therapeutic target for preventing or treating bone-related diseases. In fact, SPARC is associated with tissue remodeling, repair, development, cell turnover, bone mineralization and may also participate in growth and progression of tumors, namely cancer-related bone metastasis. Yet, the function of SPARC in such biological processes is poorly understood and controversial. The main objective of this work is to review the current knowledge related to the activity of SPARC in bone remodeling, tumorigenesis, and bone metastasis. Progress in understanding SPARC biology may provide novel strategies for bone regeneration and the development of anti-angiogenic, anti-proliferative, or counter-adhesive treatments specifically against bone metastasis. © 2013 Wiley Periodicals, Inc. © 2013 Wiley Periodicals, Inc.
Keywords: BONE METASTASIS; bone remodeling; SPARC; TUMORIGENESIS

Sca-1+cardiac progenitor cells and heart-making: A critical synopsis - Valente, M.; Nascimento, D.S.; Cumano, A.; Pinto-Do-Ó, P. (Stem Cells and Development, 2014)
The identification, in the adult, of cardiomyocyte turnover events and of cardiac progenitor cells (CPCs) has revolutionized the field of cardiovascular medicine. However, the low rate of CPCs differentiation events reported both in vitro and in vivo, even after injury, raised concerns on the biological significance of these subsets. In this Comprehensive Review, we discuss the current understanding of cardiac Lin-Sca-1+cells in light of what is also known for cellular compartments with similar phenotypes in other organs. The Lin-Sca-1+heart subset is heterogeneous and displays a mesenchymal profile, characterized by a limited ability to generate cardiomyocytes in vitro and in vivo, even after injury. There is no evidence for Sca-1 expression in embryonic cardiovascular progenitors. In other organs, Sca-1 expression is mainly observed on mesoderm-derived cells, although it is not restricted to stem/progenitor cell populations. It is urgent to determine, at a single cell level, to which extent cardiac Lin-Sca-1+cells overlap with the fibroblast compartment.

Selective albumin-binding surfaces modified with a thrombin-inhibiting peptide - Freitas, S.C.; Maia, S.; Figueiredo, A.C.; Gomes, P.; Pereira, P.J.B.; Barbosa, M.A.; Martins, M.C.L. (Acta Biomaterialia, 2014)
Blood-contacting medical devices have been associated with severe clinical complications, such as thrombus formation, triggered by the activation of the coagulation cascade due to the adsorption of certain plasma proteins on the surface of biomaterials. Hence, the coating of such surfaces with antithrombotic agents has been used to increase biomaterial haemocompatibility. Biomaterial-induced clotting may also be decreased by albumin adsorption from blood plasma in a selective and reversible way, since this protein is not involved in the coagulation cascade. In this context, this paper reports that the immobilization of the thrombin inhibitor D-Phe-Pro-D-Arg-D-Thr-CONH 2 (fPrt) onto nanostructured surfaces induces selective and reversible adsorption of albumin, delaying the clotting time when compared to peptide-free surfaces. fPrt, synthesized with two glycine residues attached to the N-terminus (GGfPrt), was covalently immobilized onto self-assembled monolayers (SAMs) having different ratios of carboxylate-hexa(ethylene glycol)- and tri(ethylene glycol)-terminated thiols (EG6-COOH/EG3) that were specifically designed to control GGfPrt orientation, exposure and density at the molecular level. In solution, GGfPrt was able to inactivate the enzymatic activity of thrombin and to delay plasma clotting time in a concentration-dependent way. After surface immobilization, and independently of its concentration, GGfPrt lost its selectivity to thrombin and its capacity to inhibit thrombin enzymatic activity against the chromogenic substrate n-p-tosyl-Gly-Pro-Arg-p-nitroanilide. Nevertheless, surfaces with low concentrations of GGfPrt could delay the capacity of adsorbed thrombin to cleave fibrinogen. In contrast, GGfPrt immobilized in high concentrations was found to induce the procoagulant activity of the adsorbed thrombin. However, all surfaces containing GGfPrt have a plasma clotting time similar to the negative control (empty polystyrene wells), showing resistance to coagulation, which is explained by its capacity to adsorb albumin in a selective and reversible way. This work opens new perspectives to the improvement of the haemocompatibility of blood-contacting medical devices. © 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Albumin; Blood compatibility; Clotting; Surface modification; Thrombin

Sensory neurons and osteoblasts: Close partners in a microfluidic platform - Neto, E.; Alves, C.J.; Sousa, D.M.; Alencastre, I.S.; Lourenço, A.H.; Leitão, L.; Ryu, H.R.; Jeon, N.L.; Fernandes, R.; Aguiar, P.; Almeida, R.D.; Lamghari, M. (Integrative Biology (United Kingdom), 2014)
Innervation has proven to be critical in bone homeostasis/regeneration due to the effect of soluble factors, produced by nerve fibers, associated with changes in the activity of bone cells. Thus, in this study, we have established and characterized a coculture system comprising sensory neurons and osteoblasts to mimic the in vivo scenario where nerve fibers can be found in a bone microenvironment. Embryonic or adult primary dorsal root ganglion (DRG) and MC3T3-E1 osteoblastic cells were cocultured in compartmentalized microfluidic platforms and morphological and functional tests were performed. The time of adhesion and readout of axonal outgrowth were improved by the alignment of DRG with the axis of microgrooves, which showed to be a crucial step for the designed experiments. Cocultures of entire DRG from adult origin with osteoblasts were performed, showing extended DRG projections towards the axonal compartment, reaching osteoblastic cells. Immunocytochemistry showed that the neurites present within the osteoblastic compartment were immunoreactive to synapsin and calcitonin gene-related peptide suggesting the presence of specialized structures involved in this crosstalk. This evidence was further confirmed by electron microscopy where varicosities were detected as well as electron dense structures in neurite membranes. Aiming to mimic the properties of tissue extracellular matrices, MC3T3-E1 cells were seeded in the axonal side upon laminin, collagen or within 3D functionalized alginate matrices and axonal outgrowth was clearly observed. In order to analyze and quantify data with reproducible image analysis, a semi-automated algorithm was also developed. The collagen and laminin substrates displayed a higher amount of axons reaching the axonal side. Overall, the established method revealed to be a suitable tool to study the interaction between the peripheral nervous system and bone cells in different contexts mimicking the in vivo scenario. © 2014 the Partner Organisations 2014.

Splice-correcting oligonucleotides restore BTK function in X-linked agammaglobulinemia model - Bestas, B.; Moreno, P.M.D.; Blomberg, K. E. M.; Mohammad, D. K.; Saleh, A. F.; Sutlu, T.; Nordin, J. Z.; Guterstam, P.; Gustafsson, M. O.; Kharazi, S.; Piatosa, B.; Roberts, T. C.; et al. (Journal of Clinical Investigation, 2014)

Stability study perspective of the effect of freeze-drying using cryoprotectants on the structure of insulin loaded into PLGA nanoparticles - Fonte, P.; Soares, S.; Sousa, F.; Costa, A.; Seabra, V.; Reis, S.; Sarmento, B. (Biomacromolecules, 2014)
This work aimed to evaluate the influence of a freeze-drying process using different cryoprotectants on the structure of insulin loaded into poly(lactic-co-glycolic acid) (PLGA) nanoparticles and to assess the stability of these nanoparticles upon 6 months of storage following ICH guidelines. Insulin-loaded PLGA nanoparticles with a size around 450 nm were dehydrated using a standard freeze-drying cycle, using trehalose, glucose, sucrose, fructose, and sorbitol at 10% (w/v) as cryoprotectants. All formulations, except those nonadded of cryoprotectant and added with trehalose, collapsed after freeze-drying. The addition of cryoprotectants increased the nanoparticles stability upon storage. FTIR results showed that insulin maintained its structure after encapsulation in about 88%, decreasing to 71% after freeze-drying. The addition of cryoprotectants prior to freeze-drying increased insulin structural stability an average of up to 79%. Formulations collapsed after freeze-drying showed better protein stabilization upon storage, in special sorbitol added formulation, preserving 76, 80, and 78% of insulin structure at 4 °C, 25 °C/60% RH, and 40 °C/75% RH, respectively. Principal component analysis also showed that the sorbitol-added formulation showed the most similar insulin structural modifications among the tested storage conditions. These findings suggested that regarding nanoparticles stability, cryoprotectants are versatile to be used in a standard freeze-drying, however they present different performances on the stabilization of the loaded protein. Thus, on the freeze-drying of the nanoparticles field, this work gives rise to the importance of the process of optimization, searching for a balance between a good obtainable cake with an optimal structural stabilization of the loaded protein.

Stable phenotype and function of immortalized Lin-Sca-1 + cardiac progenitor cells in long-term culture: A step closer to standardization - Freire, AG; Nascimento, D.S.; Forte, G.; Valente, M.; Resende, TP; Pagliari, S.; Abreu, C; Carvalho, I; Nardo, P.D.; Pinto-Do-Ó, P. (Stem Cells and Development, 2014)
Putative cardiac progenitor cells (CPCs) have been identified in the myocardium and are regarded as promising candidates for cardiac cell-based therapies. Although two distinct populations of CPCs reached the clinical setting, more detailed studies are required to portray the optimal cell type and therapeutic setting to drive robust cell engraftment and cardiomyogenesis after injury. Owing to the scarcity of the CPCs and the need for reproducibility, the generation of faithful cellular models would facilitate this scrutiny. Here, we evaluate whether immortalized Lin-Sca-1+ CPCs (iCPC Sca-1) represent their native-cell counterpart, thereby constituting a robust in vitro model system for standardized investigation in the cardiac field. iCPCSca-1 were established in vitro as plastic adherent cells endowed with robust self-renewal capacity while preserving a stable phenotype in long-term culture. iCPCSca-1 differentiated into cardiomyocytic-, endothelial-, and smooth muscle-like cells when subjected to appropriate stimuli. The cell line consistently displayed features of Lin -Sca-1+ CPCs in vitro, as well as in vivo after intramyocardial delivery in the onset of myocardial infarction (MI). Transplanted iCPCSca-1 significantly attenuated the functional and anatomical alterations caused by MI while promoting neovascularization. iCPCSca-1 are further shown to engraft, establish functional connections, and differentiate in loco into cardiomyocyte- and vasculature-like cells. These data validate iCPCSca-1 as an in vitro model system for Lin-Sca-1+ progenitors and for systematic dissection of mechanisms underlying CPC subsets engraftment/differentiation in vivo. Moreover, iCPCSca-1 can be regarded as a ready-to-use CPCs source for pre-clinical bioengineering studies toward the development of novel strategies for restoration of the damaged myocardium. © Copyright 2014, Mary Ann Liebert, Inc. 2014.

Study of the isoflavone content of different extracts of Medicago spp. as potential active ingredient - Rodrigues, F.; Almeida, I.; Sarmento, B.; Amaral, M.H.; Oliveira, M.B.P.P. (Industrial Crops and Products, 2014)
This study focuses on the isoflavones composition of different extracts of Medicago species (M. minima, M. tornata, M. truncatula, M. rigidula, M. scutelata, M. segitalis and M. sativa), a leguminous crop used as animal feeding. There are some research studies on the isoflavones composition of Medicago sativa, but no comprehensive profile of isoflavones has been reported for these other six species. In this work, two glycosides (daidzin and genistin) and six aglycones (daidzein, glycitein, genistein, formononetin, prunetin and biochanin A) were determined by high performance liquid chromatography (HPLC/DAD) in three different extracts of these species: aqueous, hydroalcoholic and alcoholic. In all samples genistin, daidzein and genistein were the most abundant isoflavone compounds. The highest concentration of genistin was observed in the extracts of M. scutelata (5.2 and 9.6. mg/kg. db, respectively, for hydroalcoholic and alcoholic extract), in amounts 2-4.5-fold higher than the other samples evaluated. Daidzein is also present in high amounts in M. scutelata (19.2. mg/kg. db, alcoholic extract). Genistein is detected in several species at concentrations ranging from 0.7 (aqueous extract of M. tornata) to 16.1. mg/kg. db (alcoholic extract of M. scutelata). In terms of total isoflavones content per species, results showed significant differences between M. rigidula and M. sativa, considering all type of solvents, being the highest and the lowest one, respectively. In a general way, the extractability of compounds significantly increased from aqueous to alcoholic extracts. The study demonstrates that some Medicago species possess an excellent potential as a source of these health promoting bioactive compounds. © 2014 Elsevier B.V.
Keywords: By-product; Daidzein; Genistein; Genistin; Isoflavones; Medicago

Therapeutic antisense oligonucleotides against cancer: hurdling to the clinic - Moreno, Pedro M. D.; Pego, Ana P. (Frontiers in chemistry, 2014)

Timing embryo segmentation: Dynamics and regulatory mechanisms of the vertebrate segmentation clock - Resende, TP; Andrade, R.P.; Palmeirim, I. (BioMed Research International, 2014)
All vertebrate species present a segmented body, easily observed in the vertebrate column and its associated components, which provides a high degree of motility to the adult body and efficient protection of the internal organs. The sequential formation of the segmented precursors of the vertebral column during embryonic development, the somites, is governed by an oscillating genetic network, the somitogenesis molecular clock. Herein, we provide an overview of the molecular clock operating during somite formation and its underlying molecular regulatory mechanisms. Human congenital vertebral malformations have been associated with perturbations in these oscillatory mechanisms. Thus, a better comprehension of the molecular mechanisms regulating somite formation is required in order to fully understand the origin of human skeletal malformations. © 2014 Tatiana P. Resende et al.

Tools for address georeferencing - limitations and opportunities every public health professional should be aware of - Ribeiro, Ana Isabel; Olhero, Andreia; Teixeira, Hugo; Magalhaes, Alexandre; Pina, Maria Fatima (PloS one, 2014)

Translating chitosan to clinical delivery of nucleic acid-based drugs - Gomes, C.P.; Lopes, C.D.F.; Moreno, P.M.D.; Varela-Moreira, A.; Alonso, M.J.; Pego, A. P. (Mrs Bulletin, 2014)

What do Portuguese women prefer regarding vaginal products? Results from a cross-sectional web-based survey - Palmeira-de-Oliveira, R.; Duarte, P.; Palmeira-de-Oliveira, A.; Das Neves, J.; Amaral, M.H.; Breitenfeld, L.; Martinez-de-Oliveira, J. (Pharmaceutics, 2014)
Therapeutic outcomes of vaginal products depend not only on their ability to deliver drugs to or through the vagina but also on acceptability and correct use. Women’s preferences, in turn, may vary according to age and cultural backgrounds. In this work, an anonymous online survey was completed by 2529 Portuguese women to assess their preferences for physical characteristics and mode of application of vaginal products, according to age. Additionally, intention to use and misconceptions about these issues were assessed. The majority of women of all age groups would use vaginal products to treat or prevent diseases, upon medical prescription. Women preferred vaginal products to be odorless and colorless gels, creams and ointments composed by natural origin drugs/excipients and applied by means of an applicator. Although the majority of women would prefer not to insert any product in the vagina, intention to use for self and recommendation to use for others was associated with previous experiences with vaginal products. General concerns and misconceptions related to use of vaginal products were rare. These data may contribute to the development of products that women are more prone to use.
Keywords: Acceptability; Vaginal dosage forms; Vaginal products; Women’s preferences

What do portuguese women prefer regarding vaginal products? Results from a cross-sectional web-based survey - Palmeira-de-Oliveira, Rita; Duarte, Paulo; Palmeira-de-Oliveira, Ana; das Neves, Jose; Amaral, Maria Helena; Breitenfeld, Luiza; Martinez-de-Oliveira, Jose (Pharmaceutics, 2014)

Adsorbed fibrinogen leads to improved bone regeneration and correlates with differences in the systemic immune response - Santos, S.G.; Lamghari, M.; Almeida, C.R.; Oliveira, M.I.; Neves, N.; Ribeiro, A.C.; Barbosa, J.N.; Barros, R.; Maciel, J.; Martins, M.C.L.; Gonçalves, R.M.; Barbosa, M.A. (Acta Biomaterialia, 2013)

Adult stem cells and biocompatible scaffolds as smart drug delivery tools for cardiac tissue repair - Pagliari, S.; Romanazzo, S.; Mosqueira, D.; Pinto-Do-Ó, P.; Aoyagi, T.; Forte, G. (Current Medicinal Chemistry, 2013)

Advanced biofabrication strategies for skin regeneration and repair - Pereira, R.F.; Barrias, C.C.; Granja, P.L.; Bartolo, P.J. (Nanomedicine, 2013)

An overview of central fetal monitoring systems in labour - Nunes, Inês; Ayres-de-Campos, Diogo; Figueiredo, Catarina; Bernardes, João %@ 1619-3997 (2013)

Assessing the physical-chemical properties and stability of dapivirine-loaded polymeric nanoparticles - Das Neves, J.; Amiji, M.; Bahia, M.F.; Sarmento, B. (International Journal of Pharmaceutics, 2013)

Automatic lane segmentation in TLC images using the continuous wavelet transform - Moreira, B.; Sousa, A.; Mendonça, A.M.; Campilho, A. (Computational and Mathematical Methods in Medicine, 2013)

Automatic localization of the optic disc by combining vascular and intensity information - Mendonça, A.M.; Sousa, A.; Mendonça, L.; Campilho, A. (Computerized Medical Imaging and Graphics, 2013)

Bacterial-binding chitosan microspheres for gastric infection treatment and prevention - Gonçalves, I.C.; Magalhães, A.; Fernandes, M.; Rodrigues, I.V.; Reis, C.A.; Martins, M.C.L. (Acta Biomaterialia, 2013)

Biocompatibility of poly(lactic acid) with incorporated graphene-based materials - Pinto, A.M.; Moreira, S.; Gonçalves, I.C.; Gama, F.M.; Mendes, A.M.; Magalhães, F.D. (Colloids and Surfaces B: Biointerfaces, 2013)

Bioengineered surfaces promote specific protein-glycan mediated binding of the gastric pathogen Helicobacter pylori - Parreira, P.; Magalhães, A.; Reis, C.A.; Borén, T.; Leckband, D.; Martins, M.C.L. (Acta Biomaterialia, 2013)

Brain targeting effect of camptothecin-loaded solid lipid nanoparticles in rat after intravenous administration - Martins, S.M.; Sarmento, B.; Nunes, C.; Lúcio, M.; Reis, S.; Ferreira, D.C. (European Journal of Pharmaceutics and Biopharmaceutics, 2013)

Cetuximab conjugated O-carboxymethyl chitosan nanoparticles for targeting EGFR overexpressing cancer cells - Maya, S.; Kumar, L.G.; Sarmento, B.; Sanoj Rejinold, N.; Menon, D.; Nair, S.V.; Jayakumar, R. (Carbohydrate Polymers, 2013)

Characterization of human NLZ1/ZNF703 identifies conserved domains essential for proper subcellular localization and transcriptional repression - Pereira-Castro, I.; Costa, Â.M.S.; Oliveira, M.J.; Barbosa, I.; Rocha, A.S.; Azevedo, L.; Da Costa, L.T. (Journal of Cellular Biochemistry, 2013)

Co-expression network analysis and genetic algorithms for gene prioritization in preeclampsia - Tejera, E.; Bernardes, J.; Rebelo, I. (BMC Medical Genomics, 2013)

Comparison of different methods of heart rate entropy analysis during acute anoxia superimposed on a chronic rat model of pulmonary hypertension - Gonçalves, H.; Henriques-Coelho, T.; Rocha, A.P.; Lourenço, A.P.; Leite-Moreira, A.; Bernardes, J. (Medical Engineering and Physics, 2013)

Comparison of real beat-to-beat signals with commercially available 4 Hz sampling on the evaluation of foetal heart rate variability - Gonçalves, H.; Costa, A.; Ayres-de-Campos, D.; Costa-Santos, C.; Rocha, A.P.; Bernardes, J. (Medical and Biological Engineering and Computing, 2013)

Could moderate earthquakes also trigger cardiac events? - Ribeiro, A.I.; De Fátima De Pina, M. (European Journal of Epidemiology, 2013)

Development and validation method for simultaneous quantification of phenolic compounds in natural extracts and nanosystems - Da Silva, S.B.; Oliveira, A.; Ferreira, D.; Sarmento, B.; Pintado, M. (Phytochemical Analysis, 2013)

Development of bis-locked nucleic acid (bisLNA) oligonucleotides for efficient invasion of supercoiled duplex DNA - Moreno, P.M.D.; Geny, S.; Pabon, Y.V.; Bergquist, H.; Zaghloul, E.M.; Rocha, C.S.J.; Oprea, I.I.; Bestas, B.; Andaloussi, S.E.; Jørgensen, P.T.; Pedersen, E.B.; Lundin, K.E.; et al. (Nucleic Acids Research, 2013)

Development of PLGA-mannosamine nanoparticles as oral protein carriers - Alonso-Sande, M.; Des Rieux, A.; Fievez, V.; Sarmento, B.; Delgado, A.; Evora, C.; Remuñán-López, C.; Préat, V.; Alonso, M.J. (Biomacromolecules, 2013)

E-cadherin and adherens-junctions stability in gastric carcinoma: Functional implications of glycosyltransferases involving N-glycan branching biosynthesis, N-acetylglucosaminyltransferases III and v - Pinho, S.S.; Figueiredo, J.; Cabral, J.; Carvalho, S.; Dourado, J.; Magalhães, A.; Gärtner, F.; Mendonça, A.M.; Isaji, T.; Gu, J.; Carneiro, F.; Seruca, R.; et al. (Biochimica et Biophysica Acta - General Subjects, 2013)

Effect of freeze-drying, cryoprotectants and storage conditions on the stability of secondary structure of insulin-loaded solid lipid nanoparticles - Soares, S.; Fonte, P.; Costa, A.; Andrade, J.; Seabra, V.; Ferreira, D.; Reis, S.; Sarmento, B. (International Journal of Pharmaceutics, 2013)

Effect of gastric environment on Helicobacter pylori adhesion to a mucoadhesive polymer - Nogueira, F.; Gonçalves, I.C.; Martins, M.C.L. (Acta Biomaterialia, 2013)

Effects of density of anisotropic microstamped silica thin films on guided bone tissue regeneration - In vitro study - Pelaez-Vargas, A.; Gallego-Perez, D.; Carvalho, A.; Fernandes, M.H.; Hansford, D.J.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part B Applied Biomaterials, 2013)

Endothelialization of chitosan porous conduits via immobilization of a recombinant fibronectin fragment (rhFNIII7-10) - Amaral, I.F.; Neiva, I.; Ferreira da Silva, F.; Sousa, S.R.; Piloto, A.M.; Lopes, C.D.F.; Barbosa, M.A.; Kirkpatrick, C.J.; Pêgo, A.P. (Acta Biomaterialia, 2013)

Engineering of a 3D nanostructured scaffold made of functionalized self-assembling peptides and encapsulated neural stem cells - Cunha, C.; Panseri, S.; Gelain, F. (Methods in Molecular Biology, 2013)

Enzymatic, physicochemical and biological properties of MMP-sensitive alginate hydrogels - Fonseca, K.B.; Maia, F.R.; Cruz, F.A.; Andrade, D.; Juliano, M.A.; Granja, P.L.; Barrias, C.C. (Soft Matter, 2013)

Establishment of a triple co-culture in vitro cell models to study intestinal absorption of peptide drugs - Antunes, F.; Andrade, F.; Araújo, F.; Ferreira, D.; Sarmento, B. (European Journal of Pharmaceutics and Biopharmaceutics, 2013)

Expression of ST3GAL4 Leads to SLex Expression and Induces c-Met Activation and an Invasive Phenotype in Gastric Carcinoma Cells - Gomes, C.; Osório, H.; Pinto, M.T.; Campos, D.; Oliveira, M.J.; Reis, C.A. (PLoS ONE, 2013)

Fibrinogen promotes resorption of chitosan by human osteoclasts - Torres, A.L.; Santos, S.G.; Oliveira, M.I.; Barbosa, M.A. (Acta Biomaterialia, 2013)

Functionalization of biomaterials with small osteoinductive moieties - Maia, F.R.; Bidarra, S.J.; Granja, P.L.; Barrias, C.C. (Acta Biomaterialia, 2013)

Gender-specific heart rate dynamics in severe intrauterine growth-restricted fetuses - Gonçalves, H.; Bernardes, J.; Ayres-de-Campos, D. (Early Human Development, 2013)

Graphene-based materials biocompatibility: A review - Pinto, A.M.; Gonçalves, I.C.; Magalhães, F.D. (Colloids and Surfaces B: Biointerfaces, 2013)

High biocompatibility and improved osteogenic potential of novel Ca-P/titania composite scaffolds designed for regeneration of load-bearing segmental bone defects - Cunha, C.; Sprio, S.; Panseri, S.; Dapporto, M.; Marcacci, M.; Tampieri, A. (Journal of Biomedical Materials Research - Part A, 2013)

Highly focalised thermotherapy using a ferrimagnetic cement in the treatment of a melanoma mouse model by low temperature hyperthermia - Portela, A.; Vasconcelos, M.; Fernandes, M.H.; Garcia, M.; Silva, A.; Gabriel, J.; Gartner, F.; Amorim, I.; Cavalheiro, J. (International Journal of Hyperthermia, 2013)

Hyaluronic acid / chitosan multilayer coatings on neuronal implants for localized delivery of siRNA nanoplexes - Hartmann, H.; Hossfeld, S.; Schlosshauer, B.; Mittnacht, U.; Pêgo, A.P.; Dauner, M.; Doser, M.; Stoll, D.; Krastev, R. (Journal of Controlled Release, 2013)

Hydrolyzed galactomannan-modified nanoparticles and flower-like polymeric micelles for the active targeting of rifampicin to macrophages - Moretton, M.A.; Chiappetta, D.A.; Andrade, F.; Das Neves, J.; Ferreira, D.; Sarmento, B.; Sosnik, A. (Journal of Biomedical Nanotechnology, 2013)

The importance of antimicrobial peptides and their potential for therapeutic use in ophthalmology - Silva, N.C.; Sarmento, B.; Pintado, M. (International Journal of Antimicrobial Agents, 2013)

In vitro and Ex Vivo evaluation of polymeric nanoparticles for vaginal and rectal delivery of the anti-HIV drug dapivirine - Das Neves, J.; Araújo, F.; Andrade, F.; Michiels, J.; Ariën, K.K.; Vanham, G.; Amiji, M.; Bahia, M.F.; Sarmento, B. (Molecular Pharmaceutics, 2013)

Information-based measure of disagreement for more than two observers: A useful tool to compare the degree of observer disagreement - Henriques, T.; Antunes, L.; Bernardes, J.; Matias, M.; Sato, D.; Costa-Santos, C. (BMC Medical Research Methodology, 2013)

Keratins and lipids in ethnic hair - Cruz, C.F.; Fernandes, M.M.; Gomes, A.C.; Coderch, L.; Martí, M.; Méndez, S.; Gales, L.; Azoia, N.G.; Shimanovich, U.; Cavaco-Paulo, A. (International Journal of Cosmetic Science, 2013)

Loss of WNK2 expression by promoter gene methylation occurs in adult gliomas and triggers Rac1-mediated tumour cell invasiveness - Moniz, S.; Martinho, O.; Pinto, F.; Sousa, B.; Loureiro, C.; Oliveira, M.J.; Moita, L.F.; Honavar, M.; Pinheiro, C.; Pires, M.; Lopes, J.M.; Jones, C.; et al. (Human Molecular Genetics, 2013)

Macrophage polarization following chitosan implantation - Vasconcelos, D.P.; Fonseca, A.C.; Costa, M.; Amaral, I.F.; Barbosa, M.A.; Águas, A.P.; Barbosa, J.N. (Biomaterials, 2013)

Macrophages stimulate gastric and colorectal cancer invasion through EGFR Y1086, c-Src, Erk1/2 and Akt phosphorylation and smallGTPase activity - Cardoso, A.P.; Pinto, M.L.; Pinto, A.T.; Oliveira, M.I.; Pinto, M.T.; Gonçalves, R.; Relvas, J.B.; Figueiredo, C.; Seruca, R.; Mantovani, A.; Mareel, M.; Barbosa, M.A.; et al. (Oncogene, 2013)

Medicago spp. extracts as promising ingredients for skin care products - Rodrigues, F.; Palmeira-de-Oliveira, A.; Das Neves, J.; Sarmento, B.; Amaral, M.H.; Oliveira, M.B. (Industrial Crops and Products, 2013)

Minimum error entropy classification - Marques De Sá, J.P.; Silva, L.M.A.; Santos, J.M.F.; Alexandre, L.A. (Studies in Computational Intelligence, 2013)

A model for educational simulation of the effect of oxytocin on uterine contractions - Lobo, M.F.; Bastos, L.F.; van Meurs, W.L.; Ayres-de-Campos, D. (Medical Engineering and Physics, 2013)

Modulation of stability and mucoadhesive properties of chitosan microspheres for therapeutic gastric application - Fernandes, M.; Gonçalves, I.C.; Nardecchia, S.; Amaral, I.F.; Barbosa, M.A.; Martins, M.C.L. (International Journal of Pharmaceutics, 2013)

Month of birth and risk of multiple sclerosis in a Portuguese population - Barros, P.; De Sá, J.M.; Sá, M.J. (Clinical Neurology and Neurosurgery, 2013)

Nanotechnology and pulmonary delivery to overcome resistance in infectious diseases - Andrade, F.; Rafael, D.; Videira, M.; Ferreira, D.; Sosnik, A.; Sarmento, B. (Advanced Drug Delivery Reviews, 2013)

Neuropeptide y modulates fracture healing through Y1 receptor signaling - Sousa, D.M.; McDonald, M.M.; Mikulec, K.; Peacock, L.; Herzog, H.; Lamghari, M.; Little, D.G.; Baldock, P.A. (Journal of Orthopaedic Research, 2013)

A novel bioactive peptide: Assessing its activity over murine neural stem cells and its potential for neural tissue engineering - Caprini, A.; Silva, D.; Zanoni, I.; Cunha, C.; Volontè, C.; Vescovi, A.; Gelain, F. (New Biotechnology, 2013)

Novel resveratrol nanodelivery systems based on lipid nanoparticles to enhance its oral bioavailability - Neves, A.R.; Lúcio, M.; Martins, S.; Lima, J.L.C.; Reis, S. (International Journal of Nanomedicine, 2013)

Osteoporotic hip fractures: Bisphosphonates sales and observed turning point in trend. A population-based retrospective study - Alves, S.M.; Economou, T.; Oliveira, C.; Ribeiro, A.I.; Neves, N.; Goméz-Barrena, E.; Pina, M.F. (Bone, 2013)

Overexpression of tumour-associated carbohydrate antigen sialyl-Tn in advanced bladder tumours - Ferreira, J.A.; Videira, P.A.; Lima, L.; Pereira, S.; Silva, M.; Carrascal, M.; Severino, P.F.; Fernandes, E.; Almeida, A.; Costa, C.; Vitorino, R.; Amaro, T.; et al. (Molecular Oncology, 2013)

An overview of central fetal monitoring systems in labour - Nunes, I.; Ayres-de-Campos, D.; Figueiredo, C.; Bernardes, J. (Journal of Perinatal Medicine, 2013)

Physical activity-friendly neighbourhood among older adults from a medium size urban setting in Southern Europe - Ribeiro, A.I.; Mitchell, R.; Carvalho, M.S.; De Pina, M.D.F. (Preventive Medicine, 2013)

Preparation and characterization of collagen-nanohydroxyapatite biocomposite scaffolds by cryogelation method for bone tissue engineering applications - Rodrigues, S.C.; Salgado, C.L.; Sahu, A.; Garcia, M.P.; Fernandes, M.H.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part A, 2013)

Protective effects of Lavandula viridis L'Hér extracts and rosmarinic acid against H2O2-induced oxidative damage in A172 human astrocyte cell line - Costa, P.; Sarmento, B.; Gonçalves, S.; Romano, A. (Industrial Crops and Products, 2013)

Response of monocultured and co-cultured human microvascular endothelial cells and mesenchymal stem cells to macroporous granules of nanostructured- hydroxyapatite agglomerates - Laranjeira, M.S.; Fernandes, M.H.; Monteiro, F.J. (Journal of Biomedical Nanotechnology, 2013)

Should European perinatal indicators be revisited? - Santos, J.V.; Correia, C.; Cabral, F.; Bernardes, J.; Costa-Pereira, A.; Freitas, A. (European Journal of Obstetrics Gynecology and Reproductive Biology, 2013)

The smart connective tissue of echinoderms: A materializing promise for biotech applications - Barbaglio, A.; Tricarico, S.; Di Benedetto, C.; Fassini, D.; Lima, A.P.; Ribeiro, A.R.; Ribeiro, C.C.; Sugni, M.; Bonasoro, F.; Wilkie, L.; Barbosa, M.; Candia Carnevali, M.D. (Cahiers de Biologie Marine, 2013)

Sociodemographic determinants of prevalence and incidence of helicobacter pylori infection in portuguese adults - Bastos, J.; Peleteiro, B.; Barros, R.; Alves, L.; Severo, M.; de Fátima Pina, M.; Pinto, H.; Carvalho, S.; Marinho, A.; Guimarães, J.T.; Azevedo, A.; La Vecchia, C.; et al. (Helicobacter, 2013)

Stable phenotype and function of immortalized Lin-Sca-1+ cardiac progenitor cells in long-term culture: a step closer to standardization. - Freire, AG; Nascimento, D.S.; Forte, G.; Valente, M.; Resende, TP; Pagliari, S.; Abreu, C; Carvalho, I; Di Nardo, P.; Pinto-Do-Ó, P. (Stem Cells Dev, 2013)

Taking tissue adhesives to the future: From traditional synthetic to new biomimetic approaches - Bré, L.P.; Zheng, Y.; Pêgo, A.P.; Wang, W. (Biomaterials Science, 2013)

Taking tissue adhesives to the future: from traditional synthetic to new biomimetic approaches - Bré, Lígia Pereira; Zheng, Yu; Pêgo, Ana Paula; Wang, Wenxin (Royal Society of Chemistry, 2013)

Towards the characterization of an in vitro triple co-culture intestine cell model for permeability studies - Araújo, F.; Sarmento, B. (International Journal of Pharmaceutics, 2013)

Adhesion of Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa onto nanohydroxyapatite as a bone regeneration material - Grenho, L.; Manso, M.C.; Monteiro, F.J.; Ferraz, M.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2012)
In orthopedics due to the enormous number of surgical procedures involving invasive implant biomaterials, infections have a huge impact in terms of morbidity, mortality, and medical costs. In this study the initial adhesion of several strains namely Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa, to nanohydroxyapatite, previously heat-treated at 725°C and 1000°C was assessed. Adherent cells were evaluated by scanning electron microscopy and quantified by confocal laser scanning microscopy and as colony forming units after being released by sonication. The wettability and roughness of samples surfaces were assessed by contact angle measurements and atomic force microscopy, respectively. Nanohydroxyapatite heat-treated at 1000°C appeared to be more resistant to bacterial adhesion, over time, in five of the six tested strains while the clinical strains isolated from orthopedic infections presented superior ability to adhere, as well as better capacity to produce slime. The increase in materials sintering temperature resulted in increased hydrophobicity and roughness; however, other surface features such as the decrease in surface area and on porosity as well as the decrease on zeta potential may be the aspects that contributed to a lower bacterial adhesion on the materials sintered at 1000°C. © 2012 Wiley Periodicals, Inc.
Keywords: Adherent cells; Adhesion; article; Atomic force microscopy; Bacteria; Bacterial adhesion; bacterium adherence; Biocompatible Materials; Biological materials; biomaterial; Biomaterials; Bone; bone infection; Bone Regeneration; Bone regeneration materials; Clinical strains; Colony Count, Microbial; colony forming unit; Colony forming units; confocal laser microscopy; Confocal laser scanning microscopy; confocal microscopy; Contact angle; Durapatite; hydrophobicity; Microscopy, Confocal; Microscopy, Electron, Scanning; Nano-hydroxyapatite; Nanohydroxyapatite; nanoparticles; nonhuman; porosity; Pseudomonas aeruginosa; Scanning electron microscopy; Sintering; Sintering temperatures; Staphylococcus aureus; Staphylococcus epidermidis; Surface area; Surface feature; surface property; Surface roughness; Surgical procedures; temperature; ultrasound; unclassified drug; wettability; Zeta potential

Automatic assessment of Leishmania infection indexes on in vitro macrophage cell cultures - Leal, P.; Ferro, L.; Marques, M.; Romão, S.; Cruz, T.; Tomá, A.M.; Castro, H.; Quelhas, P. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
Evaluation of parasite infection indexes on in vitro cell cultures is a practice commonly employed by biomedical researchers to address biological questions or to test the efficacy of novel anti-parasitic compounds. In the particular case of Leishmania infantum, a unicellular parasite that parasitizes macrophages, infection indexes are usually determined either by visual inspection of cells directly under the microscope or by counting digital images using appropriate software. In either case assessment of infection indexes is time consuming, thus motivating the creation of automatic image analysis approaches that allow large scale studies of Leishmania-infected macrophage cultures. We propose a fully automated method for automatic evaluation of parasite infection indexes through the segmentation of individual macrophages nucleus and cytoplasm, as well as the segmentation and co-localization of the parasites in the image. To perform such analysis with robustness and increased performance we propose the use of local image filters tuned to the specific size of the objects to detect, in conjunction with image segmentation approaches. The objects size estimation is then improved through a learning feedback loop. Cytoplasm is detected by seeded watershed segmentation. Our approach obtains, for 86 images from 4 experiments, an average parasite infection index evaluation error of 2.3%. © 2012 Springer-Verlag.
Keywords: Automated methods; Automatic assessment; Automatic evaluation; Automatic image analysis; Cell culture; Cell nuclei detection; cell nucleus; Colocalization; Digital image; Enzyme inhibition; Feed-back loop; Image analysis; Image filters; Image segmentation; In-vitro; Leishmania; Leishmania infantum; Macrophage cells; Macrophage culture; Macrophages; microscopy image segmentation; Microscopy images; Parasite infection; Parasite-; Size estimation; Visual inspection; Watershed segmentation

Automatic lane detection in chromatography images - Moreira, B.M.; Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
This paper proposes a method for automating the detection of lanes in Thin-Layer Chromatography images. Our approach includes a preprocessing step to detect the image region of interest, followed by background estimation and removal. This image is then projected onto the horizontal direction to integrate the information into a one-dimensional profile. A smoothing filter is applied to this profile and the outcome is the input of the lane detection process, which is performed in three phases. The first one aims at obtaining an initial set of candidate lanes that are further validated or removed in the second phase. The last phase is a refinement step that allows the inclusion of lanes that are not clearly distinguishable in the profile and that were not included in the initial set. The method was evaluated in 66 chromatography images and achieved values of recall, precision and F β -measure of 97.0%, 99.4% and 98.2%, respectively. © 2012 Springer-Verlag.
Keywords: Background estimation; Bio-medical image processing; Biomedical image processing; Chromatography; Chromatography images; Computer aided diagnosis; Image analysis; Image regions; Lane detection; Pre-processing step; Refinement step; Second phase; Smoothing filters; Three phasis

Automatic localization of the optic disc in retinal images based on the entropy of vascular directions - Mendonça, A.M.; Cardoso, F.; Sousa, A.V.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
This paper proposes an automatic method for estimating the location of the optic disc in color images of the retina. The proposed methodology is founded in a new concept, the entropy of vascular directions, which proved to be a reliable measure for assessing the convergence of vessels around an image point. To improve the robustness of the method, the search for the maximum value of entropy is restricted to image areas with high intensity. This new method was evaluated in two publicly available databases, containing both normal and pathological images, and was able to obtain a valid location for the optic disc in 115 out of the 121 images of the two datasets. © 2012 Springer-Verlag.
Keywords: Automatic localization; Automatic method; Color images; Data sets; entropy; High intensity; Image analysis; Image points; Maximum values; Ophthalmology; optic disc; Pathological images; Retinal image; Retinal image analysis; vessel segmentation

Automatic myocardial infarction size extraction in an experimental murine model using an anatomical model - Esteves, T.; Valente, M.; Nascimento, D.S.; Pinto-Do-Ó, P.; Quelhas, P. (Proceedings - International Symposium on Biomedical ImagingIEEE Comput. Soc. Conf. Comput. Vis. Pattern Recogn., 2012)
Experimental rodent models of induced ischemic injury have been extensively used in biomedical research to study molecular, cellular and histological alterations following myocar-dial infarction. These models are increasingly employed to assess the potential of newly developed therapies for functional restoration of the damaged heart. Such studies are based on myocardial infarction induction followed by different therapeutic interventions and subsequent analysis of the infarct size. This analysis is used to evaluate the extent to which such interventions meet recovery of the lost myocardial tissue. Infarct size is defined as the percentage of the left ventricle affected by coronary artery occlusion. The infarct size is traditionally estimated manually delineating the infarcted and normal tissue areas in the left ventricle of the excised heart. However, this is a time-consuming, arduous and prone to bias process. Herein, we developed an anatomic model, adapted through expectation maximization, which allows for fully automatic analysis of the data. Experimental validation is performed comparing the proposed approach with manual annotation. The results obtained through anatomical model adaptation were coherent with those manually obtained and the differences where never higher than 10%. © 2012 IEEE.
Keywords: Anatomic models; anatomical model; Anatomical models; Automatic analysis; Biomedical research; Coronary arteries; expectation maximization; Experimental validations; Image segmentation; Infarct size; Ischemic injuries; Left ventricles; Manual annotation; Maximum principle; Medical imaging; Murine model; Myocardial Infarction; Myocardial infarction size; Myocardial tissue; Normal tissue; Rodent models; Therapeutic intervention; Tissue

Automatic myocardial infarction size extraction in an experimental murine model using an anatomical model - Esteves, T.; Valente, M.; Nascimento, D.S.; Pinto-Do-Ó, P.; Quelhas, P. (Proceedings - International Symposium on Biomedical Imaging, 2012)

Bioengineered surfaces to improve the blood compatibility of biomaterials through direct thrombin inactivation - Freitas, S.C.; Cereija, T.B.; Figueiredo, A.C.; Osório, H.; Pereira, P.J.B.; Barbosa, M.A.; Martins, M.C.L. (Acta BiomaterialiaActa Biomater., 2012)
Thrombus formation, due to thrombin generation, is a major problem affecting blood-contacting medical devices. This work aimed to develop a new strategy to improve the hemocompatibility of such devices by the immobilization of a naturally occurring thrombin inhibitor into a nanostructured surface. Boophilin, a direct thrombin inhibitor from the cattle tick Rhipicephalus microplus, was produced as a recombinant protein in Pichia pastoris. Boophilin was biotinylated and immobilized on biotin-terminated self-assembled monolayers (SAM) via neutravidin. In order to maintain its proteinase inhibitory capacity after surface immobilization, boophilin was biotinylated after the formation of a boophilin-thrombin complex to minimize the biotinylation of the residues involved in thrombin-boophilin interaction. The extent of boophilin biotinylation was determined using matrix-assisted laser desorption/ionization-time of flight/time of flight mass spectrometry. Boophilin immobilization and thrombin adsorption were quantified using quartz crystal microbalance with dissipation. Thrombin competitive adsorption from human serum was assessed using 125I-thrombin. Thrombin inhibition and plasma clotting time were determined using spectrophotometric techniques. Boophilin-coated SAM were able to promote thrombin adsorption in a selective way, inhibiting most of its activity and delaying plasma coagulation in comparison with boophilin-free surfaces, demonstrating boophilin's potential to improve the hemocompatibility of biomaterials used in the production of blood-contacting devices. © 2012 Acta Materialia Inc.
Keywords: Coagulation; Hemocompatibility; Protein adsorption; Surface functionalization; Thrombin

Biosynthesis of highly pure poly-γ-glutamic acid for biomedical applications - Pereira, C.L.; Antunes, J.C.; Gonçalves, R.M.; Ferreira-da-Silva, F.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2012)
The remarkable properties of poly-aminoacids, mainly their biocompatibility and biodegradability, have prompted an increasing interest in these polymers for biomedical applications. Poly-γ-glutamic acid (γ-PGA) is one of the most interesting poly-aminoacids with potential applications as a biomaterial. Here we describe the production and characterization of γ-PGA by Bacillus subtilis natto. The γ-PGA was produced with low molecular weight (10-50 kDa), high purity grade (>99 %) and a D-/L-glutamate ratio of 50-60/50-40 %. To evaluate the feasibility of using this γ-PGA as a biomaterial, chitosan (Ch)/γ-PGA nanoparticles were prepared by the coacervation method at pH ranging from 3.0 to 5.0, with dimensions in the interval 214-221 nm with a poly-dispersion index of ca. 0.2. The high purity of γ-PGA produced by this method, which is firstly described here, renders this biopolymer suitable for biomedical applications. Moreover, the Ch/γ-PGA nanocomplexes developed in this investigation can be combined with biologically active substances for their delivery in the organism. The fact that the assembly between Ch and γ-PGA relies on electrostatic interactions enables addition of other molecules that can be released into the medium through changes from acidic to physiological pH, without loss in biological activity. © Springer Science+Business Media, LLC 2012.
Keywords: Amino acids; animal cell; article; Bacillus subtilis; Bacillus subtilis natto; Bioactivity; Biocompatibility; Biocompatible Materials; biodegradability; Biodegradable polymers; Biodegradation; Biologically active substances; biomaterial; Biomedical applications; biomedicine; biosynthesis; chitosan; circular dichroism; complex formation; controlled study; dispersion; Electrophoresis, Polyacrylamide Gel; feasibility study; Functional polymers; gamma polyglutamic acid; Glutamic acid; High purity; Low molecular weight; Medical applications; molecular interaction; molecular weight; Nanocomplexes; nanoparticle; nonhuman; pH; Physiological pH; polyglutamic acid; Potential applications; priority journal; purification; Spectroscopy, Fourier Transform Infrared; static electricity; Stereoisomerism; unclassified drug

Brain delivery of camptothecin by means of solid lipid nanoparticles: Formulation design, in vitro and in vivo studies - Martins, S.; Tho, I.; Reimold, I.; Fricker, G.; Souto, E.; Ferreira, D.; Brandl, M. (International Journal of PharmaceuticsInt. J. Pharm., 2012)
For the purpose of brain delivery upon intravenous injection, formulations of camptothecin-loaded solid lipid nanoparticles (SLN), prepared by hot high pressure homogenisation, were designed. Incorporation of camptothecin in the hydrophobic and acidic environment of SLN matrix was chosen to stabilise the lactone ring, which is essential for its antitumour activity, and for avoiding premature loss of drug on the way to target camptothecin to the brain.A multivariate approach was used to assess the influence of the qualitative and quantitative composition on the physicochemical properties of camptothecin-loaded SLN in comparison to plain SLN. Mean particle sizes of ≤200. nm, homogenous size distributions and high encapsulation efficiencies (>90%) were achieved for the most suitable formulations. In vitro release studies in plasma, showed a prolonged release profile of camptothecin from SLN, confirming the physical stability of the particles under physiological pH. A higher affinity of the SLN to the porcine brain capillary endothelial cells (BCEC) was shown in comparison to macrophages. MTT studies in BCEC revealed a moderate decrease in the cell viability of camptothecin, when incorporated in SLN compared to free camptothecin in solution. In vivo studies in rats showed that fluorescently labelled SLN were detected in the brain after i.v. administration. This study indicates that the camptothecin-loaded SLN are a promising drug brain delivery system worth to explore further for brain tumour therapy. © 2012 Elsevier B.V.
Keywords: Brain capillary endothelial cells (BCEC); Brain delivery; Camptothecin; Multivariate analysis; Solid lipid nanoparticles (SLN); Surfactants

Cancer syndromes and therapy by stop-codon readthrough - Bordeira-Carriço, R.; Pêgo, A.P.; Santos, M.; Oliveira, C. (Trends in Molecular MedicineTrends Mol. Med., 2012)
Several hereditary cancer syndromes are associated with nonsense mutations that create premature termination codons (PTC). Therapeutic strategies involving readthrough induction partially restore expression of proteins with normal function from nonsense-mutated genes, and small molecules such as aminoglycosides and PTC124 have exhibited promising results for treating patients with cystic fibrosis and Duchenne muscular dystrophy. Transgenic expression of suppressor-tRNAs and depleting translation termination factors are, among others, potential strategies for treating PTC-associated diseases. In this review, the potential of using readthrough strategies as a therapy for cancer syndromes is discussed, and we consider the effect of nonsense-mediated decay and other factors on readthrough efficiency. © 2012 Elsevier Ltd.
Keywords: Aminoglycosides; Hereditary cancer syndromes; Nonsense-mediated decay (NMD); Nonsense-suppression; Premature termination codon (PTC); PTC124; Readthrough; Suppressor-tRNA

Cell-based in vitro models for predicting drug permeability - Sarmento, B.; Andrade, F.; Da Silva, S.B.; Rodrigues, F.; Das Neves, J.; Ferreira, D. (Expert Opinion on Drug Metabolism and ToxicologyExpert Opin. Drug Metab. Toxicol., 2012)
In vitro cell models have been used to predict drug permeation in early stages of drug development, since they represent an easy and reproducible method, allowing the tracking of drug absorption rate and mechanism, with an advantageous costbenefit ratio. Such cell-based models are mainly composed of immortalized cells with an intrinsic ability to grow in a monolayer when seeded in permeable supports, maintaining their physiologic characteristics regarding epithelium cell physiology and functionality. Areas covered: This review summarizes the most important intestinal, pulmonary, nasal, vaginal, rectal, ocular and skin cell-based in vitro models for predicting the permeability of drugs. Moreover, the similitude between in vitro cell models and in vivo conditions are discussed, providing evidence that each model may provisionally resemble different drug absorption route. Expert opinion: Despite the widespread use of in vitro cell models for drug permeability and absorption evaluation purposes, a detailed study on the properties of these models and their in vitroin vivo correlation compared with human data are required to further use in order to consider a future drug discovery optimization and clinical development. © 2012 Informa UK, Ltd.
Keywords: Animals; Caco-2 Cells; carcinoma cell; cell differentiation; cell growth; Cell Line; Cell Membrane Permeability; cell models; cell proliferation; cell strain CACO 2; cell type; Cells; conjunctiva; drug absorption; drug bioavailability; drug delivery system; drug penetration; drug screening; drug transport; epithelium cell; Eye; human; Humans; in vitro models; in vitro study; in vitroin vivo correlation; Intestinal Absorption; intestinal mucosa; intestine cell; Intestines; Lung; lung alveolus cell; Models, Biological; molecular weight; nasal cell; nonhuman; ocular cell; permeability; Pharmaceutical Preparations; rectal cell; review; Skin; skin cell; vaginal cell

Chitosan drives anti-inflammatory macrophage polarisation and pro-inflammatory dendritic cell stimulation. - Oliveira, M.I.; Santos, S.G.; Oliveira, M.J.; Torres, A.L.; Barbosa, M.A. (European cells & materialsEur Cell Mater, 2012)
Macrophages and dendritic cells (DC) share the same precursor and play key roles in immunity. Modulation of their behaviour to achieve an optimal host response towards an implanted device is still a challenge. Here we compare the differentiation process and polarisation of these related cell populations and show that they exhibit different responses to chitosan (Ch), with human monocyte-derived macrophages polarising towards an anti-inflammatory phenotype while their DC counterparts display pro-inflammatory features. Macrophages and DC, whose interactions with biomaterials are frequently analysed using fully differentiated cells, were cultured directly on Ch films, rather than exposed to the polymer after complete differentiation. Ch was the sole stimulating factor and activated both macrophages and DC, without leading to significant T cell proliferation. After 10 d on Ch, macrophages significantly down-regulated expression of pro-inflammatory markers, CD86 and MHCII. Production of pro-inflammatory cytokines, particularly TNF-α, decreased with time for cells cultured on Ch, while anti-inflammatory IL-10 and TGF-β1, significantly increased. Altogether, these results suggest an M2c polarisation. Also, macrophage matrix metalloproteinase activity was augmented and cell motility was stimulated by Ch. Conversely, DC significantly enhanced CD86 expression, reduced IL-10 secretion and increased TNF-α and IL-1β levels. Our findings indicate that cells with a common precursor may display different responses, when challenged by the same biomaterial. Moreover, they help to further comprehend macrophage/DC interactions with Ch and the balance between pro- and anti-inflammatory signals associated with implant biomaterials. We propose that an overall pro-inflammatory reaction may hide the expression of anti-inflammatory cytokines, likely relevant for tissue repair/regeneration.
Keywords: antibody specificity; Antigens, CD86; article; Biocompatible Materials; biomaterial; biosynthesis; CD86 antigen; Cell culture; cell differentiation; cell motion; Cell Movement; Cells, Cultured; chitosan; cytology; dendritic cell; Dendritic Cells; drug effect; flow cytometry; Histocompatibility Antigens Class II; HLA antigen class 2; human; Humans; IL10 protein, human; immunology; interleukin 10; Interleukin-10; macrophage; Macrophages; metabolism; monocyte; Monocytes; Organ Specificity; transforming growth factor beta1; tumor necrosis factor alpha; Tumor Necrosis Factor-alpha

Tissue Engineering and Regenerative Medicine - Nascimento D, Silva A, Oliveira MJ Barbosa MA Pinto-do-Ó P. (Tissue Engineering and Regenerative Medicine, 2012)

Dissection and reconstruction of the extracellular matrix - a cardiac regenerative niche - Nascimento D.; Silva A.; Oliveira MJ.; Barbosa MA.; Pinto-do-Ó P. (Journal of Tissue Engineering and Regenerative Medicine, 2012)

E-cadherin dysfunction in gastric cancer - Cellular consequences, clinical applications and open questions - Carneiro, P.; Fernandes, M.S.; Figueiredo, J.; Caldeira, J.; Carvalho, J.; Pinheiro, H.; Leite, M.; Melo, S.; Oliveira, P.; Simões-Correia, J.; Oliveira, M.J.; Carneiro, F.; et al. (FEBS LettersFEBS Lett., 2012)
E-cadherin plays a major role in cell-cell adhesion and inactivating germline mutations in its encoding gene predispose to hereditary diffuse gastric cancer. Evidence indicates that aside from its recognized role in early tumourigenesis, E-cadherin is also pivotal for tumour progression, including invasion and metastization. Herein, we discuss E-cadherin alterations found in a cancer context, associated cellular effects and signalling pathways, and we raise new key questions that will impact in the management of GC patients and families. © 2012 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: Adhesion; Cadherins; cancer growth; cancer invasion; cancer patient; cancer susceptibility; cell adhesion; complex formation; conference paper; E-cadherin; embryo development; endocytosis; epigenetics; epithelial mesenchymal transition; Gastric cancer; gene mutation; gene silencing; genetic susceptibility; Germ-Line Mutation; HDGC; Helicobacter infection; Helicobacter Infections; Helicobacter pylori; histone deacetylase inhibitor; human; Humans; Invasion; metastasis; molecular pathology; nonhuman; priority journal; protein analysis; protein depletion; protein expression; protein function; protein structure; regulatory mechanism; signal transduction; Signalling; stomach cancer; stomach carcinogenesis; Stomach Neoplasms; Tumour; uvomorulin

The effect of adsorbed fibronectin and osteopontin on macrophage adhesion and morphology on hydrophilic and hydrophobic model surfaces - Maciel, J.; Oliveira, M.I.; Gonalves, R.M.; Barbosa, M.A. (Acta BiomaterialiaActa Biomater., 2012)
Macrophages play a crucial role in the host response to biomaterials. Here we investigated the effect of adsorbed fibronectin (FN) and osteopontin (OPN), two important proteins for tissue repair, on macrophage adhesion and morphology. Since cell-biomaterial interactions are modulated via proteins adsorbed onto biomaterial surfaces, FN and OPN were adsorbed on model self-assembled monolayers (SAMs) of alkanethiols on gold with different functional terminal groups (CH 3, OH and tetra(ethylene-glycol)). The initial interaction of inflammatory cells with a biomaterial is crucial for the ensuing phases of an inflammatory reaction. For this reason short-term cultures of primary human macrophages were performed. To account for the competitive adsorption of other proteins serum was added to the culture medium and the effect compared with serum-free medium cultures. In the presence of serum hydrophilic surfaces increased macrophage adhesion. In particular, FN induced a higher cell density, while OPN tended to decrease it. In serum-free medium cell adhesion was greater on hydrophobic surfaces, except for OPN-coated SAMs. Importantly, FN no longer enhanced macrophage adhesion, while OPN maintained its inhibitory effect. Cell polarization studies indicated that macrophage morphology variations induced by surface chemistry are overcome by pre-adsorbed OPN. Taken together our results show that in the presence of serum macrophage adhesion is promoted by FN hydrophilic surfaces, but impaired on OPN-coated surfaces. The effects of inhibited macrophage adhesion on macrophage fusion, and its relevance to the initial stages of the inflammatory response to biomaterials are discussed. © 2012 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: alkane; article; biomaterial; Biomaterials; cell adhesion; cell density; cell interaction; cell structure; controlled study; culture medium; cytoskeleton; Fibronectin; functional group; gold; human; human cell; hydrophilicity; hydrophobicity; inflammatory cell; macrophage; Macrophages; nanomaterial; Osteopontin; priority journal; self assembled monolayer; Self-assembled monolayers; Tetra; thiol; tissue repair

Effect of gastric environment on Helicobacter pylori adhesion to a mucoadhesive polymer - Nogueira, F.; Gonçalves, I.C.; Martins, M.C.L. (Acta BiomaterialiaActa Biomater., 2012)
Helicobacter pylori infection has been associated with several gastric diseases. This bacterium colonizes the gastric mucosa of half of the world's population, and available treatments are unsuccessful in practically one in every five patients. Mucoadhesive polymers, such as chitosan, are being investigated as gastric drug delivery systems. However, since chitosan is also known for its antimicrobial properties, this work aims to evaluate H. pylori interactions with chitosan under simulated gastric environments, namely using various pHs (2.6, 4 and 6), pepsin and urea. To enable the visualization of adherent bacteria, ultrathin chitosan films were produced by spin-coating on gold/glass surfaces, cross-linked with genipin and characterized by Fourier transform infrared reflection absorption spectroscopy, ellipsometry and electrokinetic analysis. Films with homogeneous thickness of 11.7 ± 0.6 nm were produced, and were stable and protonated at all the pHs used. Furthermore, they adsorbed pepsin in all these pHs, in contrast to urea, of which a small adsorption was only observed at pH 6. H. pylori binding to chitosan was higher at pH 2.6 although most of adherent bacteria were dead. The presence of pepsin decreased bacterial adhesion, but increased its viability while in a more stressed morphology (coccoid form). The presence of urea did not affect the amount, morphology or viability of chitosan-adherent bacteria. In suspension, the decrease in pH changed H. pylori zeta potential from negative to positive. Moreover, bacteria were only culturable when incubated in pH 6 with and without urea (without pepsin). This work demonstrates that chitosan has the capacity to bind and kill H. pylori in a range of pHs independently of urea. This opens new perspectives for the application of chitosan-based materials to the elimination of H. pylori gastric colonization, though pepsin might appear to be an obstacle. © 2012 Acta Materialia Inc.
Keywords: Bacterial adhesion; Biomaterials; chitosan; Helicobacter pylori; Thin films

The effect of octadecyl chain immobilization on the hemocompatibility of poly (2-hydroxyethyl methacrylate) - Fischer, M.; Baptista, C.P.; Gonçalves, I.C.; Ratner, B.D.; Sperling, C.; Werner, C.; Martins, C.L.; Barbosa, M.A. (BiomaterialsBiomaterials, 2012)
Albumin-scavenging surfaces decorated with n-alkyl chains represent an established strategy for blood-contacting applications. To evaluate this concept, a set of poly (2-hydroxyethyl methacrylate) (pHEMA) films modified with different amounts of octadecyl isocyanate (C18) was investigated in an in vitro hemocompatibility assay using freshly drawn human whole blood. In addition, the hydrogel materials were thoroughly characterized with respect to changes in wettability and elasticity, which accompanied the gradual chemical modification of pHEMA. An increase of the surface C18 content induced enhanced hydrophobicity and stiffness. Immobilization of C18 chains was found to substantially reduce the coagulation activation and the complement activation by the pHEMA films. Platelet adhesion and degranulation (PF4 release) were similar on the modified and the unmodified pHEMA. Platelet adhesion to pHEMA hydrogels was lower than the polytetrafluoroethylene reference. We conclude that the immobilization of octadecyl chains improved the hemocompatibility of pHEMA materials under conditions that might be encountered in low shear blood flow. © 2012 Elsevier Ltd.
Keywords: Adhesion; Albumin; article; Biological materials; Biomaterials; Blood; Blood flow; Chemical modification; Coagulation; controlled study; Degranulation; Elasticity; Haemocompatibility; Hemocompatibility; human; hydrogel; in vitro study; In-vitro; isocyanate; Octadecyl; octadecyl isocyanate; PHEMA; Platelet adhesion; Platelets; Poly(2-hydroxyethyl methacrylate); PolyHEMA; polymacon; priority journal; Protein adsorption; thrombocyte adhesion; unclassified drug; wettability; Whole blood

Endothelialization of chitosan porous conduits via immobilization of a recombinant fibronectin fragment (rhFNIII 7-10) - Amaral, I.F.; Neiva, I.; Ferreira da Silva, F.; Sousa, S.R.; Piloto, A.M.; Lopes, C.D.F.; Barbosa, M.A.; Kirkpatrick, C.J.; Pêgo, A.P. (Acta BiomaterialiaActa Biomater., 2012)
The present study aimed to develop a pre-endothelialized chitosan (CH) porous hollowed scaffold for application in spinal cord regenerative therapies. CH conduits with different degrees of acetylation (DA; 4% and 15%) were prepared, characterized (microstructure, porosity and water uptake) and functionalized with a recombinant fragment of human fibronectin (rhFNIII 7-10). Immobilized rhFNIII 7-10 was characterized in terms of amount ( 125I-radiolabelling), exposure of cell-binding domains (immunofluorescence) and ability to mediate endothelial cell (EC) adhesion and cytoskeletal rearrangement. Functionalized conduits revealed a linear increase in immobilized rhFNIII 7-10 with rhFNIII 7-10 concentration, and, for the same concentration, higher amounts of rhFNIII 7-10 on DA 4% compared with DA 15%. Moreover, rhFNIII 7-10 concentrations as low as 5 and 20 μg ml
Keywords: Protein conformation; Protein radiolabelling; Spinal cord injury; Surface grafting; Three-dimensional scaffolds

Enhanced mesenchymal stromal cell recruitment via natural killer cells by incorporation of inflammatory signals in biomaterials - Almeida, C.R.; Vasconcelos, D.P.; Gonçalves, R.M.; Barbosa, M.A. (Journal of the Royal Society InterfaceJ. R. Soc. Interface, 2012)
An exacerbated inflammatory response questions biomaterial biocompatibility, but on the other hand, inflammation has a central role in the regulation of tissue regeneration. Therefore, it may be argued that an 'ideal' inflammatory response is crucial to achieve efficient tissue repair/regeneration. Natural killer (NK) cells, being one of the first populations arriving at an injury site, can have an important role in regulating bone repair/regeneration, particularly through interactions with mesenchymal stem/stromal cells (MSCs). Here, we studied how biomaterials designed to incorporate inflammatory signals affected NK cell behaviour and NK cell-MSC interactions. Adsorption of the pro-inflammatory molecule fibrinogen (Fg) to chitosan films led to a 1.5-fold increase in adhesion of peripheral blood human NK cells, without an increase in cytokine secretion. Most importantly, it was found that NK cells are capable of stimulating a threefold increase in human bone marrow MSC invasion, a key event taking place in tissue repair, but did not affect the expression of the differentiation marker alkaline phosphatase (ALP). Of significant importance, this NK cell-mediated MSC recruitment was modulated by Fg adsorption. Designing novel biomaterials leading to rational modulation of the inflammatory response is proposed as an alternative to current bone regeneration strategies. © 2011 The Royal Society.
Keywords: Adhesion; Adsorption; alkaline phosphatase; article; Biocompatibility; biomaterial; Biomaterials; blood cell; Bone; bone marrow cell; Bone Regeneration; Bone repair; cell adhesion; Cell culture; cell differentiation; cell function; cell interaction; cell invasion; Cells; chitosan; Chitosan film; cytokine; Cytokine secretions; Differentiation markers; fibrinogen; gamma interferon; human; Human bone marrow; human cell; Inflammation; Inflammatory response; Mesenchymal Stem Cells; mesenchymal stroma cell; Mesenchymal stromal cells; natural killer cell; Natural killer cells; NK cells; ossification; Pathology; Peripheral blood; Phosphatases; protein expression; Tissue; Tissue regeneration; tissue repair

Epithelial E- and P-cadherins: Role and clinical significance in cancer - Paredes, J.; Figueiredo, J.; Albergaria, A.; Oliveira, P.; Carvalho, J.; Ribeiro, A.S.; Caldeira, J.; Costa, A.M.; Simões-Correia, J.; Oliveira, M.J.; Pinheiro, H.; Pinho, S.S.; et al. (Biochimica et Biophysica Acta - Reviews on CancerBiochim. Biophys. Acta Rev. Cancer, 2012)
E-cadherin and P-cadherin are major contributors to cell-cell adhesion in epithelial tissues, playing pivotal roles in important morphogenetic and differentiation processes during development, and in maintaining integrity and homeostasis in adult tissues. It is now generally accepted that alterations in these two molecules are observed during tumour progression of most carcinomas. Genetic or epigenetic alterations in E- and P-cadherin-encoding genes (CDH1 and CDH3, respectively), or alterations in their proteins expression, often result in tissue disorder, cellular de-differentiation, increased invasiveness of tumour cells and ultimately in metastasis. In this review, we will discuss the major properties of E- and P-cadherin molecules, its regulation in normal tissue, and their alterations and role in cancer, with a specific focus on gastric and breast cancer models. © 2012 Elsevier B.V.
Keywords: antineoplastic activity; antineoplastic agent; Breast; breast cancer; Cancer; cancer chemotherapy; cancer model; cancer survival; drug effect; E-cadherin; Gastric; gene expression regulation; gene function; gene location; gene overexpression; gene structure; genetic association; genetic code; Helicobacter infection; Hereditary diffuse gastric cancer; human; in vivo study; loss of function mutation; lymph node metastasis; malignant neoplastic disease; molecular dynamics; molecular pathology; molecularly targeted therapy; nonhuman; P cadherin; P cadherin gene; P-cadherin; pf 03732010; priority journal; protein expression; protein function; protein inhibitor; protein processing; review; signal transduction; stomach cancer; transcription regulation; tumor gene; unclassified drug; uvomorulin; uvomorulin gene; vasculotropin inhibitor

FTIR analysis and cytotoxicity test of titanium dioxide nanoparticles - Rodrigues, L.R.; Dias, C.G.B.T.; Ceragioli, H.J.; Rodas, A.C.D.; Monteiro, F.J.M.; Zavaglia, C.A.C. (Key Engineering MaterialsKey Eng Mat, 2012)
Titanium dioxide is a material widely used in electronics industry and little explored in the biomedical area, which is the objective of this work. Nowadays one can find surgical instruments coated with thin films that have bactericidal properties when they are activated in the presence of ultraviolet light. For crystalline phase control TiO 2 was calcinated at 500°C. The crystallite mean size for sample calcinated at 500°C was 27nm. With the results of cytotoxicity it is possible to say that biomedical applications are possible. Electron microscopy images showed nanoparticles obtained by sol-gel process and the compounds were identified by FTIR analysis. Raman spectroscopy confirmed the existence of anatase titania phase and X-ray diffraction showed this material to be composed of a crystalline phase. X-ray fluorescence identified chemical contaminants. © (2012) Trans Tech Publications.
Keywords: Anatase titania; Bactericidal properties; Bioceramics; Biomedical applications; Chemical contaminants; Crystalline materials; Crystalline phase; Crystallite size; Cytotoxicity; Cytotoxicity test; Electron microscopy images; Electronics industry; FTIR; FTIR analysis; Gels; Mean size; Medical applications; nanoparticles; Nanotechnology; Oxides; Raman spectroscopy; Scherrer equation; Scherrer equations; Sol-gel process; Sol-gel with sucrose; Sol-gels; Sols; Sugar (sucrose); Surgical equipment; Surgical instrument; TiO; Titanium; Titanium dioxide; Titanium dioxide nanoparticles; Ultra-violet light; Ultraviolet radiation; X ray diffraction; X ray fluorescence

(Gd,Yb,Tb)PO 4 up-conversion nanocrystals for bimodal luminescence-MR imaging - Debasu, M.L.; Ananias, D.; Pinho, S.L.C.; Geraldes, C.F.G.C.; Carlos, L.D.; Rocha, J. (NanoscaleNanoscale, 2012)
Up-conversion (Gd,Yb,Tb)PO 4 materials and their potential for bimodal imaging have received little attention in the literature. Herein, we report the first study on the up-conversion emission of (Gd,Yb,Tb)PO 4 nanocrystals synthesized via a hydrothermal method at 150°C. These materials exhibit ultraviolet, blue and green up-conversion emissions upon excitation with a 980 nm continuous wave laser diode. The intensity of the blue-emission band at 479 nm, ascribed to the cooperative up-conversion emission of a pair of excited Yb 3+ ions, depends on the Yb 3+/Tb 3+ concentration ratio, calcination temperature and particle size. Strong green up-conversion emission of Tb 3+ is observed at 543 nm for the 5D 4 → 7F 5 transition. Relaxometry measurements reveal that the nanocrystals are efficient T 2-weighted (negative) contrast agents which, combined with visible-light emission generated by infrared excitation, affords them considerable potential for being used in bimodal, photoluminescence-magnetic resonance, imaging. © 2012 The Royal Society of Chemistry.
Keywords: Blue-emission; Calcination; Calcination temperature; Concentration ratio; Continuous wave lasers; Contrast agent; Gadolinium; Hydrothermal methods; Infrared excitation; Magnetic resonance; Magnetic resonance imaging; Nanocrystals; Relaxometry; Up-conversion; Up-conversion emission; Visible light; Ytterbium

Gradient convergence filters and a phase congruency approach for in vivo cell nuclei detection - Esteves, T.; Quelhas, P.; Mendonça, A.M.; Campilho, A. (Machine Vision and ApplicationsMach Vision Appl, 2012)
Computational methods used in microscopy cell image analysis have largely augmented the impact of imaging techniques, becoming fundamental for biological research. The understanding of cell regulation processes is very important in biology, and in particular confocal fluorescence imaging plays a relevant role for the in vivo observation of cells. However, most biology researchers still analyze cells by visual inspection alone, which is time consuming and prone to induce subjective bias. This makes automatic cell image analysis essential for large scale, objective studies of cells. While the classic approach for automatic cell analysis is to use image segmentation, for in vivo confocal fluorescence microscopy images of plants, such approach is neither trivial nor is it robust to image quality variations. To analyze plant cells in in vivo confocal fluorescence microscopy images with robustness and increased performance, we propose the use of local convergence filters (LCF). These filters are based in gradient convergence and as such can handle illumination variations, noise and low contrast.We apply a range of existing convergence filters for cell nuclei analysis of the Arabidopsis thaliana plant root tip. To further increase contrast invariance, we present an augmentation to local convergence approaches based on image phase information. Through the use of convergence index filters we improved the results for cell nuclei detection and shape estimation when compared with baseline approaches. Using phase congruency information we were able to further increase performance by 11% for nuclei detection accuracy and 4% for shape adaptation. Shape regularization was also applied, but with no significant gain, which indicates shape estimation was good for the applied filters. © 2011 Springer-Verlag.
Keywords: Arabidopsis thaliana; Biological research; Cell analysis; Cell images; cell nucleus; Cell regulation; Cell segmentation; Cells; Confocal fluorescence imaging; Confocal fluorescence microscopy; Convergence filters; cytology; Detection accuracy; Estimation; Fluorescence microscopy; Illumination variation; Image analysis; Image filtering; Image segmentation; Imaging techniques; In-vivo; Information use; Local Convergence; Local image filtering; Medical applications; Phase congruency; Phase information; Plant cells; Plant roots; Plants (botany); Quality variation; Shape adaptation; Shape estimation; Shape regularization; Visual inspection

Hand detection and tracking using the skeleton of the blob for medical rehabilitation applications - Gil-Jiménez, P.; Losilla-López, B.; Torres-Cueco, R.; Campilho, A.; López-Sastre, R. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
This article presents an image processing application for hand detection and tracking using the 4-connected skeleton of the segmentation mask. The system has been designed to be used with techniques of virtual reality to develop an interactive application for phantom limb pain reduction in therapeutic treatments. One of the major contributions is the design of a fast and accurate skeleton extractor, that has proven to be faster than those available in the literature. The skeleton allows the system to precisely detect the position of all the interest points of the hand (namely the fingers and the hand center). The system, composed of both the hand detector and tracker, and the virtual reality application, can work in real-time, allowing the patient to watch the virtual image of his own hand on a screen. © 2012 Springer-Verlag.
Keywords: blob skeleton; Hand detection; hand detection and tracking; Image analysis; Image processing applications; Interactive applications; Musculoskeletal system; phantom limb pain reduction; Therapeutic treatments; Virtual images; virtual reality

The importance of antimicrobial peptides and their potential for therapeutic use in ophthalmology - Silva, N.C.; Sarmento, B.; Pintado, M. (International Journal of Antimicrobial AgentsInt. J. Antimicrob. Agents, 2012)
The reduced effectiveness of some of the most important antibiotics owing to increasing resistance of microorganisms as well as the absence of new classes of antimicrobial agents have been concerning researchers and clinicians in recent years. Thus, the development and approval of new compounds for clinical applications is of great importance. Among these compounds, antimicrobial peptides (AMPs) appear to be excellent candidates for the development of novel antimicrobial agents. Some AMPs and antimicrobial proteins have been shown to be active against relevant pathogens in ocular infections as well as in biofilm eradication from contact lenses. Thus, they are considered promising in the prevention and management of ocular diseases. This review summarises the main classes and characteristics of AMPs and antimicrobial proteins, in particular those found in ocular structures and fluids. Some AMPs with activity against ocular pathogens and their potential as therapeutic agents to treat and prevent ocular infections are emphasised. © 2012.
Keywords: Antimicrobial peptide; Antimicrobial protein; Ocular infection; Ophthalmology

Interactions of microbicide nanoparticles with a simulated vaginal fluid - Das Neves, J.; Rocha, C.M.R.; Gonçalves, M.P.; Carrier, R.L.; Amiji, M.; Bahia, M.F.; Sarmento, B. (Molecular PharmaceuticsMol. Pharm., 2012)
The interaction with cervicovaginal mucus presents the potential to impact the performance of drug nanocarriers. These systems must migrate through this biological fluid in order to deliver their drug payload to the underlying mucosal surface. We studied the ability of dapivirine-loaded polycaprolactone (PCL)-based nanoparticles (NPs) to interact with a simulated vaginal fluid (SVF) incorporating mucin. Different surface modifiers were used to produce NPs with either negative (poloxamer 338 NF and sodium lauryl sulfate) or positive (cetyltrimethylammonium bromide) surface charge. Studies were performed using the mucin particle method, rheological measurements, and real-time multiple particle tracking. Results showed that SVF presented rheological properties similar to those of human cervicovaginal mucus. Analysis of NP transport indicated mild interactions with mucin and low adhesive potential. In general, negatively charged NPs underwent subdiffusive transport in SVF, i.e., hindered as compared to their diffusion in water, but faster than for positively charged NPs. These differences were increased when the pH of SVF was changed from 4.2 to 7.0. Diffusivity was 50- and 172-fold lower in SVF at pH 4.2 than in water for negatively charged and positively charged NPs, respectively. At pH 7.0, this decrease was around 20- and 385-fold, respectively. The estimated times required to cross a layer of SVF were equal to or lower than 1.7 h for negatively charged NPs, while for positively charged NPs these values were equal to or higher than 7 h. Overall, our results suggest that negatively charged PCL NPs may be suitable to be used as carriers in order to deliver dapivirine and potentially other antiretroviral drugs to the cervicovaginal mucosal lining. Also, they further reinforce the importance in characterizing the interactions of nanosystems with mucus fluids or surrogates when considering mucosal drug delivery. © 2012 American Chemical Society.
Keywords: microbicides; mucin; mucoadhesion; mucosal drug delivery; particle tracking; rheology

Mesenchymal stem cell recruitment by stromal derived factor-1-delivery systems based on chitosan/poly(γ-glutamic acid) polyelectrolyte complexes - Gonçalves, R.M.; Antunes, J.C.; Barbosa, M.A. (European Cells and MaterialsEur. Cells and Mater., 2012)
Human mesenchymal stem cells (hMSCs) have an enormous potential for tissue engineering and cell-based therapies. With a potential of differentiation into multiple lineages and immune-suppression, these cells play a key role in tissue remodelling and regeneration. Here a method of hMSC recruitment is described, based on the incorporation of a chemokine in Chitosan (Ch)/ Poly(γ-glutamic acid) (γ-PGA) complexes. Ch is a nontoxic, cationic polysaccharide widely investigated. γ-PGA is a hydrophilic, non-toxic, biodegradable and negatively charged poly-amino acid. Ch and γ-PGA, being oppositely charged, can be combined through electrostatic interactions. These biocompatible structures can be used as carriers for active substances and can be easily modulated in order to control the delivery of drugs, proteins, DNA, etc. Using the layer-by-layer method, Ch and γ-PGA were assembled into polyelectrolyte multilayers films (PEMs) with thickness of 120 nm. The chemokine stromal-derived factor-1 (SDF-1) was incorporated in these complexes and was continuously released during 120 h. The method of SDF-1 incorporation is of crucial importance for polymers assembly into PEMs and for the release kinetics of this chemokine. The Ch/γ-PGA PEMs with SDF-1 were able to recruit hMSCs, increasing the cell migration up to 6 fold to a maximum of 16.2 ± 4.9 cells/mm 2. The controlled release of SDF-1 would be of great therapeutic value in the process of hMSC homing to injured tissues. This is the first study suggesting Ch/γ-PGA PEMs as SDF-1 reservoirs to recruit hMSCs, describing an efficient method of chemokine incorporation that allows a sustained released up to 5 days and that can be easily scaled-up.
Keywords: adsorption kinetics; article; artificial membrane; Biocompatible Materials; biomaterial; cell differentiation; cell migration; cell motion; Cell Movement; Cell recruitment; chemistry; Chemokine CXCL12; chitosan; controlled study; CXCL12 protein, human; cytology; drug adsorption; drug delivery system; Drug Delivery Systems; drug derivative; drug effect; ellipsometry; enzyme linked immunosorbent assay; human; human cell; human tissue; Humans; in vitro study; isotope labeling; Layer-by-layer; Membranes, Artificial; Mesenchymal stem cell; Mesenchymal Stem Cells; metabolism; methodology; poly(gamma glutamic acid); poly(gamma-glutamic acid); Poly(γ-glutamic acid); polyglutamic acid; Protein delivery; static electricity; stromal cell derived factor 1; sustained drug release

Methamphetamine mimics the neurochemical profile of aging in rats and impairs recognition memory - Melo, P.; Magalhães, A.; Alves, C.J.; Tavares, M.A.; De Sousa, L.; Summavielle, T.; Moradas-Ferreira, P. (NeuroToxicologyNeuroToxicology, 2012)
Brain neurochemistry and cognition performance are thought to decline with age. Accumulating data indicate that similar events occur after prolonged methamphetamine (MA) exposure. Using the rat as a model, the present study was designed to uncover common alteration patterns in brain neurochemistry and memory performance between aging and prolonged MA exposure. To this end, animals were treated with a chronic binge MA administration paradigm (20. mg/kg/day from postnatal day 91 to 100). Three-age control groups received isovolumetric saline treatment and were tested at the MA age-matched period, and at 12 and 20 months. We observed that both MA and aged animals presented a long, but not short, time impairment in novelty preference and an increased anxiety-like behavior. Neurochemical analysis indicated similar MA- and age-related impairments in dopamine, serotonin and metabolites in the striatum, prefrontal cortex and hippocampus. Thus, the present data illustrate that MA may be used to mimic age-related effects on neurotransmitter systems and advocate MA treatment as a feasible animal model to study neuronal processes associated with aging. © 2012 Elsevier Inc.
Keywords: Accelerated aging; Age Factors; aging; animal behavior; animal experiment; animal model; animal tissue; Animalia; Animals; anxiety; article; behavior change; Behavior, Animal; Brain; Brain Chemistry; controlled study; corpus striatum; dopamine; Exploratory Behavior; hippocampus; Hydroxyindoleacetic Acid; long term exposure; male; Memory Disorders; mental performance; Methamphetamine; Neurochemistry; neurotransmission; nonhuman; perinatal drug exposure; prefrontal cortex; priority journal; rat; Rats; Rats, Wistar; Rattus; recognition; Recognition (Psychology); Recognition memory; serotonin; sodium chloride; Time Factors

Micropatterned silica thin films with nanohydroxyapatite micro-aggregates for guided tissue regeneration - Carvalho, A.; Pelaez-Vargas, A.; Gallego-Perez, D.; Grenho, L.; Fernandes, M.H.; De Aza, A.H.; Ferraz, M.P.; Hansford, D.J.; Monteiro, F.J. (Dental MaterialsDent. Mater., 2012)
Surface modification of biomaterials has been shown to improve the biological response to dental implants. The ability to create a controlled micro-texture on the implant via additive surface modification techniques with bioactive nanohydroxyapatite (nanoHA) may positively influence guided tissue regeneration. Objective: The main goal of this study was to produce micro-fabricated SiO 2 surfaces modified with nanohydroxyapatite particles and to characterize their influence on the biological response of Human Dental-Pulp Mesenchymal Stem Cells (hDP-MSCs) and Streptococcus mutans. Materials and methods: A combined methodology of sol-gel and soft-lithography was used to produce micropatterned SiO 2 thin films with different percentages of nanoHA micro-aggregates. The surfaces were characterized by SEM/EDS, FT-IR/ATR, AFM, XPS quantitative elemental percentage and contact angle measurements. Biological characterization was performed using hDP-MSCs cultures, while Streptococcus mutans was the selected microorganism to evaluate the bacterial adhesion on the thin films. Results: Micropatterned SiO 2 surfaces with 0%, 1% and 5% of nanoHA micro-aggregates were successfully produced using a combination of sol-gel and soft-lithography. These surfaces controlled the biological response, triggering alignment and oriented proliferation of hDP-MSCs and significant differences in the adhesion of S. mutans to the different surfaces. Significance: The micropatterned surfaces exhibited biocompatible behavior that induced an oriented adhesion and proliferation of hDP-MSCs while SiO 2 presented low bacterial adhesion. These results show that the combination of sol-gel with soft-lithography is a good approach to create micropatterned surfaces with bioactive nanoparticles for guided tissue regeneration. © 2012 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Adhesion; AFM; Aggregates; Bacteria; Bacterial adhesion; Bioactive nanoparticles; Biological characterization; Biological materials; Biological response; Biomaterials; Cell culture; Contact angle; Dental prostheses; Flowcharting; FTIR/ATR; Guided tissue regeneration; Lithography; Mesenchymal stem cell; Micro patterning; Micro-texture; Microaggregates; Micropatterned; Micropatterned surface; Micropatterning; Nano-HA; Nano-hydroxyapatite; S. mutans; SEM/EDS; Silica; Silica thin films; Soft-lithography; Sol-gel; Sol-gel process; Sol-gels; Streptococcus mutans; Surface modification techniques; Surfaces; Thin films

A model for educational simulation of the evolution of uterine contractions during labor - Bastos, L.F.; van Meurs, W.; Ayres-de-Campos, D. (Computer Methods and Programs in BiomedicineComput. Methods Programs Biomed., 2012)
Electronic fetal monitoring remains an important tool in labor ward settings, providing continuous information on fetal heart rate and maternal uterine contractions. A prompt detection of abnormalities in these signals is essential for the timely resolution of situations that may put both mother and fetus at risk. Uterine contraction signals provide information that is important to evaluate the onset and progress of labor, as well as the significance of certain fetal heart rate abnormalities. We present a model for educational simulation of the spontaneous evolution of uterine contractions during labor, which combines a previously published signal generator with literature-based pre-programmed scripts for educationally relevant scenarios. This model is an essential component of a high-fidelity simulator of intrapartum emergencies, aimed to improve the competency of healthcare providers. Real and simulated tracings were presented to three independent clinical experts who judged simulated signals to be indistinguishable or negligibly different from real tracings. © 2011 Elsevier Ireland Ltd.
Keywords: article; clinical competence; computer memory; computer program; Computer simulation; Computer-Assisted Instruction; controlled study; Educational simulations; Essential component; Female; Fetal heart rate; Fetal monitoring; Health care; Health care providers; High-fidelity simulators; Humans; labor; Labor and delivery; medical education; Medical educational simulation; Models, Biological; Neonatal monitoring; Obstetric Labor Complications; Obstetrics; Pregnancy; Script-controlled simulation; signal detection; Signal generators; Simulated signals; User-Computer Interface; Uterine activities; Uterine activity; Uterine Contraction; Uterine Monitoring; uterus contraction

Neuropeptide Y Y1 receptor antagonism increases bone mass in mice - Sousa, D.M.; Baldock, P.A.; Enriquez, R.F.; Zhang, L.; Sainsbury, A.; Lamghari, M.; Herzog, H. (BoneBone, 2012)
The neuropeptide Y system has emerged as one of the major neural signalling pathways regulating bone homeostasis. Absence of Y1 receptor signalling from bone forming osteoblasts is responsible for an enhancement on bone mass in mice, suggesting that pharmacological blockade of Y1 receptors may offer a novel anabolic treatment option for improving bone mass. Here we show that oral administration of the selective Y1 receptor antagonist BIBO3304 for 8. weeks dose-dependently increases bone mass in mice. Histomorphometric analysis revealed a significant 1.5-fold increase in cancellous bone volume in the femora of mice treated with BIBO3304. Furthermore, bone microarchitecture was improved, with greater trabecular number and trabecular thickness. This increase in bone mass was associated with a significant increase in bone anabolic activity of osteoblasts and, interestingly, was evident despite a coincident increase in bone resorption, as evidenced by an increase in the number of the osteolytic osteoclasts. Changes were also evident in cortical bone, with a significant increase in periosteal mineral apposition rate. Importantly, no adverse extra-skeletal side effects were observed through Y1 receptor antagonism over the 8-week treatment period, with no effects of even the higher BIBO3304 dose on body weight, adiposity, energy metabolism or circulating corticosterone levels. Taken together, this work describes the first NPY-based anabolic treatment for improving bone mass, and highlights the therapeutic potential of blocking Y1 receptor signalling for the prevention of, or recovery from, degenerative skeletal diseases. © 2012 Elsevier Inc.
Keywords: animal experiment; animal tissue; Animals; Arginine; article; body weight; Bone Density; bone mass; bone metabolism; bone strength; cancellous bone; controlled study; cortical bone; corticosterone; corticosterone blood level; dose response; Dose-Response Relationship, Drug; drug effect; drug mechanism; drug megadose; energy metabolism; femur; food intake; glucose; glucose homeostasis; Homeostasis; male; Mice; Mice, Inbred C57BL; morphometrics; mouse; n2 diphenylacetyl n (4 ureidomethylbenzyl)argininamide; neuropeptide Y; Neuropeptide yY; nonhuman; obesity; Oral drug administration; osteoblast; osteoclast activity; Osteogenesis; osteolysis; Osteopenia; Receptors, Neuropeptide Y; signal transduction; trabecular bone; Y1 receptor antagonism

A novel nanoparticle delivery system for in vivo targeting of the sciatic nerve: Impact on regeneration - Gonçalves, N.P.; Oliveira, H.; Pêgo, A.P.; Saraiva, M.J. (NanomedicineNanomedicine, 2012)
Aim: Innovative solutions in the development of drug delivery systems targeting the nerve tissue are awaited. In this regard, a novel system for the delivery of drugs to the sciatic nerve was created using nanomedical principles. Materials & methods: Chitosan was the vehicle material used in the experiment. Heparin bound to growth factors has been administered to enhance peripheral nerve regeneration, and since heparin possesses the appropriate charge to be able to form nanoparticles with chitosan, it appears to be a good candidate to base this new delivery system on. Results: Maximal absorption took place throughout the extracellular matrix at day 15. No major inflammatory response was observed, indicating that this is a safe and biocompatible system for drug delivery to nerves. Sensorimotor performance and nerve regeneration of mice receiving these nanoparticles were superior as compared with controls. Conclusion: Our work demonstrates a versatile nanoparticle delivery system that successfully targets drugs 'in vivo to the sciatic nerve, opening novel avenues in the field of nanomedicine to the design of therapeutic strategies that enhance axonal regeneration. © 2012 Future Medicine Ltd.
Keywords: chitosan; drug delivery system; heparin; nanomedicine; nanoparticles; peripheral nerve regeneration; sciatic nerve

Osteoporotic hip fractures: Bisphosphonates sales and observed turning point in trend. A population-based retrospective study - Alves, Sandra Maria; Economou, Theodoros; Oliveira, Carla; Ribeiro, Ana Isabel; Neves, Nuno; Goméz-Barrena, Enrique; de Pina, Maria de Fátima (Elsevier, 2012)

Poor reliability of visual analysis of fetal heart rate tracings: What should be done about it? - Bernardes, J.; Ayres-de-Campos, D. (American Journal of Obstetrics and GynecologyAm. J. Obstet. Gynecol., 2012)
Keywords: accuracy; Cardiotocography; clinical decision making; clinical practice; computer analysis; fetus blood sampling; fetus electrocardiography; fetus heart rate; Heart Rate, Fetal; human; Humans; letter; medical education; metabolic acidosis; newborn disease; priority journal; reliability; visual acuity

Preparation and characterization of collagen-nanohydroxyapatite biocomposite scaffolds by cryogelation method for bone tissue engineering applications - Rodrigues, S.C.; Salgado, C.L.; Sahu, A.; Garcia, M.P.; Fernandes, M.H.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2012)
Recent efforts of bone repair focus on development of porous scaffolds for cell adhesion and proliferation. Collagen-nanohydroxyapatite (HA) scaffolds (70:30; 50:50; and 30:70 mass percentage) were produced by cryogelation technique using 1-ethyl-3-(3-dimethyl aminopropyl) carbodiimide hydrochloride/N-hydroxysuccinimide as crosslinking agents. A pure collagen scaffold was used as control. Morphology analysis revealed that all cryogels had highly porous structure with interconnective porosity and the nanoHA aggregates were randomly dispersed throughout the scaffold structure. Chemical analysis showed the presence of all major peaks related to collagen and HA in the biocomposites and indicated possible interaction between nanoHA aggregates and collagen molecules. Porosity analysis revealed an enhancement in the surface area as the nanoHA percentage increased in the collagen structure. The biocomposites showed improved mechanical properties as the nanoHA content increased in the scaffold. As expected, the swelling capacity decreased with the increase of nanoHA content. In vitro studies with osteoblasts cells showed that they were able to attach and spread in all cryogels surfaces. The presence of collagen-nanoHA biocomposites resulted in higher overall cellular proliferation compared to pure collagen scaffold. A statistically significant difference between collagen and collagen-nanoHA cryogels was observed after 21 day of cell culture. These innovative collagen-nanoHA cryogels could have potentially appealing application as scaffolds for bone regeneration. © 2012 Wiley Periodicals, Inc.
Keywords: Biomaterials; Bone tissue engineering; Collagen; Cryogels; Nanohydroxyapatite

Proactive engineering - Duarte, C.; Oliveira, H.P.; Magalhaes, F.; Tavares, V.G.; Campilho, A.C.; De Oliveira, P.G. (IEEE Global Engineering Education Conference, EDUCONIEEE Global Eng. Edu. Conf., EDUCON, 2012)
This paper presents two initiatives run by groups of engineering students at the University of Porto: the Microelectronics Students' Group and BioStar. These groups are student-led initiatives that promote different scientific fields through self-guided projects. Both experiences have proven to be very successful in increasing the undergraduate student's interest in science and technology. This work reports the activities, organization and main methodologies employed by these groups, which can be seen as successful approaches to enhance the technical curriculum of students. © 2012 IEEE.
Keywords: Curricula; Engineering education; Microelectronics; Project based learning; project-based learning; Science and Technology; Scientific fields; student-led initiatives; Students; Undergraduate students

Reciprocal induction of human dermal microvascular endothelial cells and human mesenchymal stem cells: Time-dependent profile in a co-culture system - Laranjeira, M.S.; Fernandes, M.H.; Monteiro, F.J. (Cell ProliferationCell Prolif., 2012)
Objectives: Angiogenesis is closely associated with osteogenesis where reciprocal interactions between endothelial and osteoblast cells play an important role in bone regeneration. For these reasons, the aim of this work was to develop a co-culture system to study in detail any time-dependent interactions between human mesenchymal stem cells (HMSC) and human dermal microvascular endothelial cells (HDMEC), co-cultured in a 2D system, for 35 days. Materials and methods: HMSC and HDMEC were co-cultured at a ratio of 1:4, respectively. Single-cell cultures were used as controls. Cell viability/proliferation was assessed using MTT, DNA quantification and calcein-AM assays. Cell morphology was monitored using confocal microscopy, and real time PCR was performed. Alkaline phosphatase activity and histochemical staining were evaluated. Matrix mineralization assays were also performed. Results: Cells were able to grow in characteristic patterns maintaining their viability and phenotype expression throughout culture time, compared to HMSC and HDMEC monocultures. HMSC differentiation seemed to be enhanced in the co-culture conditions, since it was observed an over expression of osteogenesis-related genes, and of ALP activity. Furthermore, presence of calcium phosphate deposits was also confirmed. Conclusions: This work reports in detail the interactions between HMSC and HDMEC in a long-term co-culture 2D system. Endothelial and mesenchymal stem cells cultured in the present co-culture conditions ensured proliferation and phenotype differentiation of cell types, osteogenesis stimulation and over-expression of angiogenesis-related genes, in the same culture system. It is believed that the present work can lead to significant developments for bone tissue regeneration and cell biology studies. © 2012 Blackwell Publishing Ltd.
Keywords: alkaline phosphatase; article; Base Sequence; calcein; calcium phosphate; CD31 antigen; Cell culture; cell differentiation; cell growth; cell interaction; cell nucleus; cell population; cell proliferation; cell structure; cell viability; coculture; Coculture Techniques; confocal microscopy; controlled study; DNA; DNA determination; DNA Primers; Endothelium, Vascular; enzyme histochemistry; F actin; flow cytometry; gene overexpression; human; human cell; Humans; immunohistochemistry; in vitro study; Mesenchymal stem cell; Mesenchymal Stem Cells; Microscopy, Confocal; Microscopy, Electron, Scanning; microvascular endothelial cell; Microvessels; mineralization; nucleotide sequence; osteoblast; phenotype; process development; real time polymerase chain reaction; Real-Time Polymerase Chain Reaction; scanning electron microscope; single cell analysis; Skin

Regenerative medicine for the treatment of spinal cord injury: More than just promises? - Pêgo, A.P.; Kubinova, S.; Cizkova, D.; Vanicky, I.; Mar, F.M.; Sousa, M.M.; Sykova, E. (Journal of Cellular and Molecular MedicineJ. Cell. Mol. Med., 2012)
Spinal cord injury triggers a complex set of events that lead to tissue healing without the restoration of normal function due to the poor regenerative capacity of the spinal cord. Nevertheless, current knowledge about the intrinsic regenerative ability of central nervous system axons, when in a supportive environment, has made the prospect of treating spinal cord injury a reality. Among the range of strategies under investigation, cell-based therapies offer the most promising results, due to the multifactorial roles that these cells can fulfil. However, the best cell source is still a matter of debate, as are clinical issues that include the optimal cell dose as well as the timing and route of administration. In this context, the role of biomaterials is gaining importance. These can not only act as vehicles for the administered cells but also, in the case of chronic lesions, can be used to fill the permanent cyst, thus creating a more favourable and conducive environment for axonal regeneration in addition to serving as local delivery systems of therapeutic agents to improve the regenerative milieu. Some of the candidate molecules for the future are discussed in view of the knowledge derived from studying the mechanisms that facilitate the intrinsic regenerative capacity of central nervous system neurons. The future challenge for the multidisciplinary teams working in the field is to translate the knowledge acquired in basic research into effective combinatorial therapies to be applied in the clinic. © 2012 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Keywords: Biomaterials; Cell therapies; Clinical trials; Conditioning lesion; Gene therapy; Growth factors; Spinal cord injury; Stem cells

Staphylococcus aureus and Staphylococcus epidermidis adhesion to nanohydroxyapatite in the presence of model proteins - Ribeiro, M.; Monteiro, F.J.; Ferraz, M.P. (Biomedical Materials (Bristol)Biomed. Mater., 2012)
Bacterial infections can have adverse effects on the efficacy, lifetime, and safety of an implanted device. The aim of this study was to investigate the initial adhesion of several strains, namely S. aureus and S. epidermidis, on two distinct types of nanohydroxyapatite (nanoHA), sintered at 725°C and 1000°C. A comparison was also made with nanohydroxyapatite having adsorbed fetal bovine serum (FBS), human fibronectin (FN) and human serum albumin (HSA). Adhered bacterial cells were examined by scanning electron microscopy and quantified as colony forming units after being released by sonication. The wettability of the sample surface with and without adsorbed protein was assessed by contact-angle measurements. NanoHA sintered at 1000°C showed lower bacterial adhesion than this heat-treated at 725°C. Adsorption of FBS onto the nanoHA surface caused a decrease in the adhesion of all strains on both materials. The bacterial adhesion patterns in the presence of FN were different for both nanoHA substrates; the adherence of the bacterial strains, except for the clinical strain of S.epidermidis, was significantly higher on nanoHA 1000 in comparison to nanoHA 1000 without protein and the bacterial adhesion on the FN-coated nanoHA 725 was lower in comparison to the bare nanoHA 725. The effect of HSA on bacterial adhesion was concentration and bacterial strain dependent. © 2012 IOP Publishing Ltd.
Keywords: Adhesion; Adsorption; Adverse effect; article; Bacteria; Bacterial adhesion; bacterial cell; Bacterial cells; Bacterial infections; bacterial strain; Bacterial strains; bacterium adherence; Clinical strains; colony forming unit; Colony forming units; Contact angle; Contact-angle measurements; controlled study; Enzyme inhibition; Epidermidis; Fetal bovine serum; Fibronectin; heating; Human fibronectin; human serum albumin; Human serum albumins; hydroxyapatite; Implanted device; materials testing; Model proteins; Nano-HA; Nano-hydroxyapatite; Nanohydroxyapatite; nanoparticle; nonhuman; Proteins; S. aureus; Sample surface; Scanning electron microscopy; serum; Sintering; Staphylococcus aureus; Staphylococcus epidermidis; surface property; ultrasound; unclassified drug; wettability

Supervised content based image retrieval using radiology reports - Ramos, J.; Kockelkorn, T.; Van Ginneken, B.; Viergever, M.A.; Ramos, R.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
Content based image retrieval (CBIR) is employed in medicine to improve radiologists' diagnostic performance. Today effective medical CBIR systems are limited to specific applications, as to reduce the amount of medical knowledge to model. Although supervised approaches could ease the incorporation of medical expertise, its application is not common due to the scarce number of available user annotations. This paper introduces the application of radiology reports to supervise CBIR systems. The concept is to make use of the textual distances between reports to build a transformation in image space through a manifold learning algorithm. A comparison was made between the presented approach and non-supervised CBIR systems, using a Leave-One-Patient-Out evaluation in a database of computer tomography scans of interstitial lung diseases. Supervised CBIR augmented the mean average precision consistently with an increase between 3 to 8 points, which suggests supervision by radiology reports increases CBIR performance. © 2012 Springer-Verlag.
Keywords: CBIR system; Computer tomography; Content based retrieval; Content-Based Image Retrieval; Diagnostic performance; Image analysis; Image space; Interstitial lung disease; Learning algorithms; Manifold learning algorithm; Medical computing; Medical knowledge; Radiation; Radiology; Radiology reports; User annotations

Synthesis of an O-alkynyl-chitosan and its chemoselective conjugation with a PEG-like amino-azide through click chemistry - Oliveira, J.R.; Martins, M.C.L.; Mafra, L.; Gomes, P. (Carbohydrate PolymersCarbohydr Polym, 2012)
N-Phthaloyl-chitosan O-prop-2-ynyl carbamate was prepared as a biopolymer amenable to undergo chemoselective conjugation by azide-alkyne coupling, while allowing upturn of chitosan's amines after dephthaloylation. N-phthaloylchitosan was prepared according to previously described methods and, due to its low solubility in current organic media, subsequent modifications were run in heterogeneous conditions. Activation of hydroxyls with carbonyl-1,1′- diimidazole and coupling to propargylamine yielded N-phthaloyl-chitosan O-prop-2-ynyl carbamate, then coupled to a model PEG-like azide by azide-alkyne coupling, giving the expected triazolyl conjugate. N-Dephthaloylation allowed recovery of the free amines, responsible for chitosan's bioadhesion and tissue-regeneration properties. The structures of all polymers were confirmed by Fourier-transformed infra-red (FT-IR) and X-ray photoelectron (XPS) spectroscopies, as well as by solid-state nuclear magnetic resonance (SSNMR). All chitosan derivatives were poorly soluble in both aqueous and organic media, which makes them suitable for topical applications or for removal of toxic substances from either the gastric intestinal tract or environmental sources. © 2011 Elsevier Ltd. All Rights Reserved.
Keywords: 1 ,3-Dipolarcycloaddition; Acetylene; Amines; Azide-alkyne coupling; Bio-adhesion; Bioadhesion; Biomaterials; chitosan; click chemistry; Cycloaddition; FTIR; Huisgen's 1,3-dipolar cycloaddition; Nuclear magnetic resonance; Nuclear magnetic resonance spectroscopy; Photoelectron spectroscopy; Resonance; Size exclusion chromatography; Size-exclusion chromatography; Solid state NMR; Solid-state NMR; Tissue; X ray photoelectron spectroscopy; XPS

Tumor cell-educated periprostatic adipose tissue acquires an aggressive cancer-promoting secretory profile - Ribeiro, R.J.T.; Monteiro, C.P.D.; Cunha, V.F.P.M.; Azevedo, A.S.M.; Oliveira, M.J.; Monteiro, R.; Fraga, A.M.; Príncipe, P.; Lobato, C.; Lobo, F.; Morais, A.; Silva, V.; et al. (Cellular Physiology and BiochemistryCell. Physiol. Biochem., 2012)
Background/Aims: The microenvironment produces important factors that are crucial to prostate cancer (PCa) progression. However, the extent to which the cancer cells stimulate periprostatic adipose tissue (PPAT) to produce these proteins is largely unknown. Our purpose was to determine whether PCa cell-derived factors influence PPAT metabolic activity. Methods: Primary cultures of human PPAT samples from PCa patients (adipose tissue organotypic explants and primary stromal vascular fraction, SVF) were stimulated with conditioned medium (CM) collected from prostate carcinoma (PC3) cells. Cultures without CM were used as control. We used multiplex analysis and ELISA for protein quantification, qPCR to determine mitochondrial DNA (mtDNA) copy number and zymography for matrix metalloproteinase activity, in order to evaluate the response of adipose tissue explants and SVFs to PC3 CM. Results: Stimulation of PPAT explants with PCa PC3 CM induced adipokines associated with cancer progression (osteopontin, tumoral necrosis factor alpha and interleukin-6) and reduced the expression of the protective adipokine adiponectin. Notably, osteopontin protein expression was 13-fold upregulated. Matrix metalloproteinase 9 activity and mitochondrial DNA copy number were higher after stimulation with cancer CM. Stromovascular cells from PPAT in culture were not influenced by tumor-derived factors. Conclusion: The modulation of adipokine expression by tumor CM indicates the pervasive extent to which tumor cells command PPAT to produce factors favorable to their aggressiveness. © 2012 S. Karger AG, Basel.
Keywords: Adipokines; adiponectin; adipose tissue; adult; article; cancer cell; cancer growth; Cells, Cultured; clinical article; controlled study; Culture Media, Conditioned; culture medium; Cytokines; DNA, Mitochondrial; enzyme activity; enzyme linked immunosorbent assay; explant; gelatinase B; human; human cell; human tissue; Humans; interleukin 6; Interleukin-6; male; Matrix Metalloproteinase 2; Matrix Metalloproteinase 9; Middle Aged; mitochondrial DNA; Osteopontin; Periprostatic adipose tissue; priority journal; Prostate cancer; Prostatic Neoplasms; protein expression; protein induction; protein secretion; quantitative analysis; stroma cell; tissue metabolism; tumor necrosis factor alpha; Tumor Necrosis Factor-alpha

The Arabidopsis D-Type Cyclin CYCD2;1 and the Inhibitor ICK2/KRP2 Modulate Auxin-Induced Lateral Root Formation - Sanz, L.; Dewitte, W.; Forzani, C.; Patell, F.; Nieuwland, J.; Wen, B.; Quelhas, P.; de Jager, S.; Titmus, C.; Campilho, A.; Ren, H.; Estelle, M.; et al. (Plant CellPlant Cell, 2011)
The integration of cell division in root growth and development requires mediation of developmental and physiological signals through regulation of cyclin-dependent kinase activity. Cells within the pericycle form de novo lateral root meristems, and D-type cyclins (CYCD), as regulators of the G 1-to-S phase cell cycle transition, are anticipated to play a role. Here, we show that the D-type cyclin protein CYCD2;1 is nuclear in Arabidopsis thaliana root cells, with the highest concentration in apical and lateral meristems. Loss of CYCD2;1 has a marginal effect on unstimulated lateral root density, but CYCD2;1 is rate-limiting for the response to low levels of exogenous auxin. However, while CYCD2;1 expression requires sucrose, it does not respond to auxin. The protein Inhibitor-Interactor of CDK/Kip Related Protein2 (ICK2/KRP2), which interacts with CYCD2;1, inhibits lateral root formation, and ick2/krp2 mutants show increased lateral root density. ICK2/ KRP2 can modulate the nuclear levels of CYCD2;1, and since auxin reduces ICK2/KRP2 protein levels, it affects both activity and cellular distribution of CYCD2;1. Hence, as ICK2/KRP2 levels decrease, the increase in lateral root density depends on CYCD2;1, irrespective of ICK2/CYCD2;1 nuclear localization. We propose that ICK2/KRP2 restrains root ramification by maintaining CYCD2;1 inactive and that this modulates pericycle responses to auxin fluctuations. © 2011 American Society of Plant Biologists.
Keywords: Arabidopsis; Arabidopsis protein; Arabidopsis Proteins; Arabidopsis thaliana; article; ATP dependent 26S protease; cell cycle; cell cycle protein; Cell Cycle Proteins; cell nucleus; CycD2 protein, Arabidopsis; cycline; Cyclins; gene expression regulation; Gene Expression Regulation, Plant; genetics; growth, development and aging; ICK2 protein, Arabidopsis; indoleacetic acid derivative; Indoleacetic Acids; metabolism; mutation; plant root; Plant roots; proteasome; Proteasome Endopeptidase Complex

Arabidopsis thaliana automatic cell file detection and cell length estimation - Quelhas, P.; Nieuwland, J.; Dewitte, W.; Mendonça, A.M.; Murray, J.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2011)
In plant development biology, the study of the structure of the plant's root is fundamental for the understanding of the regulation and interrelationships of cell division and cellular differentiation. This is based on the high connection between cell length and progression of cell differentiation and the nuclear state. However, the need to analyse a large amount of images from many replicate roots to obtain reliable measurements motivates the development of automatic tools for root structure analysis. We present a novel automatic approach to detect cell files, the main structure in plant roots, and extract the length of the cells in those files. This approach is based on the detection of local cell file characteristic symmetry using a wavelet based image symmetry measure. The resulting detection enables the automatic extraction of important data on the plant development stage and of characteristics for individual cells. Furthermore, the approach presented reduces in more than 90% the time required for the analysis of each root, improving the work of the biologist and allowing the increase of the amount of data to be analysed for each experimental condition. While our approach is fully automatic a user verification and editing stage is provided so that any existing errors may be corrected. Given five test images it was observed that user did not correct more than 20% of all automatically detected structure, while taking no more than 10% of manual analysis time to do so. © 2011 Springer-Verlag.
Keywords: Arabidopsis thaliana; Automatic extraction; Automatic tools; Bio-imaging; BioImaging; cell differentiation; Cell divisions; Cell lengths; cell proliferation; Cells; Cellular differentiation; Experimental conditions; Image analysis; image symmetry; Individual cells; Main structure; Manual analysis; Nuclear state; Plant development; Plant roots; Plants (botany); Reliable measurement; Root structure; Test images; User verification; Wavelet analysis; Wavelet-based images

Automatic and semi-automatic analysis of the extension of myocardial infarction in an experimental murine model - Esteves, T.; Valente, M.; Nascimento, D.S.; Pinto-Do-Ó, P.; Quelhas, P. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2011)
Rodent models of myocardial infarction (MI) have been extensively used in biomedical research towards the implementation of novel regenerative therapies. Permanent ligation of the left anterior descending (LAD) coronary artery is a commonly used method for inducing MI both in rat and mouse. Post-mortem evaluation of the heart, particularly the MI extension assessment performed on histological sections, is a critical parameter for this experimental setting. MI extension, which is defined as the percentage of the left ventricle affected by the coronary occlusion, has to be estimated by identifying the infarcted- and the normal-tissue in each section. However, because it is a manual procedure it is time-consuming, arduous and prone to bias. Herein, we introduce semi-automatic and automatic approaches to perform segmentation which is then used to obtain the infarct extension measurement. Experimental validation is performed comparing the proposed approaches with manual annotation and a total error not exceeding 8% is reported in all cases. © 2011 Springer-Verlag.
Keywords: Extension evaluations; Image analysis; Image segmentation; Infarct extension evaluation; k-means; Mammals; meanshift; otsu; Pattern recognition; region growing; Tissue; watershed

Automatic and semi-automatic analysis of the extension of myocardial infarction in an experimental murine model - Esteves, T.; Valente, M.; Nascimento, D.S.; Pinto-Do-Ó, P.; Quelhas, P. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2011)

Automatic segmentation of chromatographic images for region of interest delineation - Mendonça, A.M.; Sousa, A.V.; Sá-Miranda, M.C.; Campilho, A.C. (Progress in Biomedical Optics and Imaging - Proceedings of SPIEProgr. Biomed. Opt. Imaging Proc. SPIE, 2011)
This paper describes a segmentation method for automating the region of interest (ROI) delineation in chromatographic images, thus allowing the definition of the image area that contains the fundamental information for further processing while excluding the frame of the chromatographic plate that does not contain relevant data for disease identification. This is the first component of a screening tool for Fabry disease, which will be based on the automatic analysis of the chromatographic patterns extracted from the image ROI. Image segmentation is performed in two phases, where each individual pixel is finally considered as frame or ROI. In the first phase, an unsupervised learning method is used for classifying image pixels into three classes: frame, ROI or unknown. In the second phase, distance features are used for deciding which class the unknown pixels belong to. The segmentation result is post-processed using a sequence of morphological operators in order to obtain the final ROI rectangular area. The proposed methodology was successfully evaluated in a dataset of 41 chromatographic images. © 2011 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).
Keywords: Automatic analysis; Automatic segmentations; Chromatographic images; Chromatographic plates; Chromatography; Data sets; Distance feature; Fabry disease; Image pixels; Image segmentation; Imaging systems; Medical imaging; Morphological operator; Pixels; Rectangular area; Region of interest; Region of interest delineation; Screening tool; Second phase; Segmentation methods; Segmentation results; Unsupervised learning; Unsupervised learning method

Bone marrow-derived endothelial progenitors expressing delta-like 4 (Dll4) regulate tumor angiogenesis - Real, C.; Remédio, L.; Caiado, F.; Igreja, C.; Borges, C.; Trindade, A.; Pinto-Do-Ó, P.; Yagita, H.; Duarte, A.; Dias, S. (PLoS ONEPLoS ONE, 2011)
Neo-blood vessel growth (angiogenesis), which may involve the activation of pre-existing endothelial cells (EC) and/or the recruitment of bone marrow-derived vascular precursor cells (BM-VPC), is essential for tumor growth. Molecularly, besides the well established roles for Vascular endothelial growth factor (VEGF), recent findings show the Notch signalling pathway, in particular the ligand Delta-like 4 (Dll4), is also essential for adequate tumor angiogenesis; Dll4 inhibition results in impaired, non-functional, angiogenesis and reduced tumor growth. However, the role of BM-VPC in the setting of Notch pathway modulation was not addressed and is the subject of the present report. Here we show that SDF-1 and VEGF, which are produced by tumors, increase Dll4 expression on recruited BM-VPC. Mechanistically, BM-VPC activated, in a Dll4-dependent manner, a transcriptional program on mature EC suggestive of EC activation and stabilization. BM-VPC induced ICAM-2 and Fibronectin expression on EC, an effect that was blocked by a Dll4-specific neutralizing antibody. In vivo, transplantation of BM-VPC with decreased Dll4 into tumor-bearing mice resulted in the formation of microvessels with decreased pericyte coverage and reduced fibronectin expression. Consequently, transplantation of BM-VPC with decreased Dll4 resulted in impaired tumor angiogenesis, increased tumor hypoxia and apoptosis, and decreased tumor growth. Taken together, our data suggests that Dll4 expression by BM-VPC affects their communication with tumor vessel endothelial cells, thereby modulating tumor angiogenesis by affecting vascular stability. © 2011 Real et al.
Keywords: angiogenesis; animal; animal cell; animal tissue; Animals; apoptosis; article; blood vessel; Blood Vessels; bone marrow; bone marrow cell; Bone Marrow Cells; cell activation; Cell Line, Tumor; cell proliferation; controlled study; cytology; delta like 4 protein; DLL4 protein, mouse; Endothelial Cells; endothelium cell; Female; Fibronectin; gene expression; gene expression regulation; genetics; human; human cell; Humans; hypoxia; in vitro study; in vivo study; intercellular adhesion molecule 2; Intracellular Signaling Peptides and Proteins; membrane protein; Membrane Proteins; metabolism; Mice; mouse; Mus; neoplasm; Neoplasms; neovascularization (pathology); Neovascularization, Pathologic; neutralizing antibody; nonhuman; Notch receptor; Pathology; pericyte; protein expression; signal peptide; solid tumor; stem cell; stem cell transplantation; Stem cells; stromal cell derived factor 1; tumor cell line; tumor growth; unclassified drug; vascularization; vasculotropin

Classification-based segmentation of the region of interest in chromatographic images - Sousa, A.V.; Mendonça, A.M.; Sá-Miranda, M.C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2011)
This paper proposes a classification-based method for automating the segmentation of the region of interest (ROI) in digital images of chromatographic plates. Image segmentation is performed in two phases. In the first phase an unsupervised learning method classifies the image pixels into three classes: frame, ROI or unknown. In the second phase, distance features calculated for the members of the three classes are used for deciding on the new label, ROI or frame, for each individual connected segment previously classified as unknown.The segmentation result is post-processed using a sequence of morphological operators before obtaining the final ROI rectangular area. The proposed methodology, which is the initial step for the development of a screening tool for Fabry disease, was successfully evaluated in a dataset of 58 chromatographic images. © 2011 Springer-Verlag.
Keywords: Chromatographic images; Chromatographic plates; Chromatography; Data sets; Digital image; Distance feature; Fabry disease; Image analysis; Image pixels; Image segmentation; Morphological operator; Rectangular area; Region of interest; Region of interest delineation; Screening tool; Second phase; Segmentation results; Unsupervised learning; Unsupervised learning method

Complexity and categorical analysis may improve the interpretation of agreement studies using continuous variables - Costa-Santos, C.; Bernardes, J.; Antunes, L.; Ayres-de-Campos, D. (Journal of Evaluation in Clinical PracticeJ. Eval. Clin. Pract., 2011)
Rationale Complex clinical scenarios involving a high degree of uncertainty frequently lead to a poor agreement over diagnosis and management. However, inconsistent results can be found with the most widely used measures of agreement for continuous variables - the limits of agreement and the intraclass correlation coefficient. Aims and objectives We aim to improve the interpretation of agreement studies using continues variables. Methods and results Evaluation of agreement may be improved by complexity analysis and by categorization of variables, followed by the use of the proportions of agreement. Conclusions The average never characterizes a complex phenomenon and the methods used to access agreement in continuous variables are based on the mean. For future agreement studies, involving complex continuous variables, we recommend a complexity and categorical analysis. © 2011 Blackwell Publishing Ltd.
Keywords: article; Biomedical research; Cardiotocography; clinical decision making; clinical practice; complexity; Data Interpretation, Statistical; Decision Making; entropy; Female; fetus heart rate; Heart Rate, Fetal; human; Humans; observer variation; Pregnancy; Pregnancy Outcome; priority journal; Reproducibility of Results; statistical data interpretation; Uncertainty

Covalent immobilization of antimicrobial peptides (AMPs) onto biomaterial surfaces - Costa, F.; Carvalho, I.F.; Montelaro, R.C.; Gomes, P.; Martins, M.C.L. (Acta BiomaterialiaActa Biomater., 2011)
Bacterial adhesion to biomaterials remains a major problem in the medical devices field. Antimicrobial peptides (AMPs) are well-known components of the innate immune system that can be applied to overcome biofilm-associated infections. Their relevance has been increasing as a practical alternative to conventional antibiotics, which are declining in effectiveness. The recent interest focused on these peptides can be explained by a group of special features, including a wide spectrum of activity, high efficacy at very low concentrations, target specificity, anti-endotoxin activity, synergistic action with classical antibiotics, and low propensity for developing resistance. Therefore, the development of an antimicrobial coating with such properties would be worthwhile. The immobilization of AMPs onto a biomaterial surface has further advantages as it also helps to circumvent AMPs' potential limitations, such as short half-life and cytotoxicity associated with higher concentrations of soluble peptides. The studies discussed in the current review report on the impact of covalent immobilization of AMPs onto surfaces through different chemical coupling strategies, length of spacers, and peptide orientation and concentration. The overall results suggest that immobilized AMPs may be effective in the prevention of biofilm formation by reduction of microorganism survival post-contact with the coated biomaterial. Minimal cytotoxicity and long-term stability profiles were obtained by optimizing immobilization parameters, indicating a promising potential for the use of immobilized AMPs in clinical applications. On the other hand, the effects of tethering on mechanisms of action of AMPs have not yet been fully elucidated. Therefore, further studies are recommended to explore the real potential of immobilized AMPs in health applications as antimicrobial coatings of medical devices. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Amino Acid Sequence; amoxicillin; ampicillin; Animals; antibiotic agent; antibiotic resistance; Antimicrobial Cationic Peptides; Antimicrobial peptides; Bacteria (microorganisms); Bacterial adhesion; bacterial survival; Biocompatible Materials; biofilm; Biofilms; biomaterial; carbenicillin; cefazolin; Coated Materials, Biocompatible; Cytotoxicity; drug activity; drug half life; drug solubility; drug stability; drug targeting; gentamicin; human; Humans; Immobilized Proteins; Molecular Sequence Data; mouth inflammation; Nanostructured surfaces; nonhuman; penicillin G; polypeptide antibiotic agent; priority journal; review; sepsis; skin infection; soft tissue infection; Surface functionalization; Surface Properties; teicoplanin; tobramycin; vancomycin

The effect of slurry preparation methods on biaxial flexural strength of dental porcelain - Pelaez-Vargas, A.; Dussan, J.A.; Restrepo-Tamayo, L.F.; Paucar, C.; Ferreira, J.A.; Monteiro, F.J. (Journal of Prosthetic DentistryJ. Prosthet. Dent., 2011)
Statement of problem. One-step and incremental mixing procedures are currently used to produce dental ceramic pastes. In the ceramic industry, high quality is obtained using one-step mixing, but in dentistry, the best method has not been yet determined. Purpose. The purpose of this study is to evaluate the effects of 2 mixing techniques on the biaxial flexural strength and microstructure of dental porcelain. Material and methods. Feldspathic porcelain discs (2 × 15 mm in diameter) were produced and divided according to the ceramic paste preparation method, powder-liquid incremental mixing group (n=50) or one-step mixing, as a control group (n=50). Specimens were tested for biaxial flexural strength and characterized using porosimetry, relative humidity, SEM/EDS, XRD, and FT-IR analyses. Statistical analysis was conducted using Weibull statistics. The Weibull modulus, characteristic strength and relative humidity were compared between groups, using Student's t-test and Mann-Whitney U test (α=.05). Results. The powder-liquid incremental mixing group showed significantly higher values (SD) of Weibull modulus (6.74 (0.70), P<.001) and characteristic strength (79.87 (2.01) MPa, P<.001) when compared to the one-step mixing group (4.94 (0.94) and 75.95 (2.61) MPa). Significantly lower mean (SD) relative humidity values (P=.009) were found for powder-liquid incremental mixing group (20% (0.5%)) compared to one-step mixing group (22% (1%)). XRD spectra showed that the one-step mixing group produced higher amounts of the amorphous phase. Conclusions. Specimens produced by the incremental mixing technique showed higher biaxial flexural strength than one-step mixing. © 2011 The Editorial Council of the Journal of Prosthetic Dentistry.
Keywords: article; chemistry; comparative study; Complex Mixtures; Crowns; dental care; Dental Porcelain; Dental Prosthesis Design; Dental Stress Analysis; Dental Veneers; denture; drug mixture; evaluation; materials testing; pliability; tooth crown; tooth prosthesis

Friction and wear behaviour of bacterial cellulose against articular cartilage - Lopes, J.L.; Machado, J.M.; Castanheira, L.; Granja, P.L.; Gama, F.M.; Dourado, F.; Gomes, J.R. (WearWear, 2011)
Bacterial cellulose (BC) is a natural and biocompatible material with unique properties, such as high water holding capacity, ultra-fine fibre network and high strength that makes it an attractive material for the repair of articular cartilage lesions. However, data on the tribological properties of BC is very scarce, particularly if natural articular cartilage is involved in the contact. In this work, unmodified BC pellicles were grown from Gluconacetobacter xylinus in order to be used as tribological samples against bovine articular cartilage (BAC) in the presence of phosphate buffered saline (PBS). The tribological assessment of the sliding pairs was accomplished using reciprocating pin-on-flat tests at 37°C. The reciprocating sliding frequency and stroke length were kept constant at 1Hz and 8mm, respectively. Contact pressures ranging from 0.80 to 2.40MPa were applied. The friction coefficient evolution was continuously monitored during the tests and the release of total carbohydrates into the lubricating solution was followed by means of the phenol-H 2SO 4 method as an attempt to evaluate wear losses. The morphology of worn surfaces was characterized by SEM/EDS and the main wear mechanisms were identified. Low friction coefficient values (∼0.05) combined with the preservation of the mating surfaces (BC and BAC) indicate the potential of BC to be used as artificial cartilage for articular joints. © 2011 Elsevier B.V.
Keywords: Articular cartilage; Articular cartilages; Articular joints; Artificial cartilages; Bacterial cellulose; Bacteriology; Biocompatible Materials; Biological materials; Biotribology; Bovine articular cartilage; Carbohydrates; Cartilage; Cellulose; Contact pressures; Fibre network; Friction; Friction and wear; Friction coefficients; Gluconacetobacter xylinus; High strength; High water; Low friction coefficients; Mating surfaces; Phenols; Phosphate-buffered salines; Pin-on-flat; Reciprocating sliding; SEM/EDS; Stroke length; Total carbohydrates; Tribological properties; Tribology; Wear; Wear loss; Wear mechanisms; Worn surface

Gene delivery into mesenchymal stem cells: A biomimetic approach using rgd nanoclusters based on poly(amidoamine) dendrimers - Pandita, D.; Santos, J.L.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (BiomacromoleculesBiomacromolecules, 2011)
Poly(amidoamine) dendrimers (generations 5 and 6) with amine termini were conjugated with peptides containing the arginine-glycine-aspartic acid (RGD) sequence having in view their application as gene delivery vectors. The idea behind the work was to take advantage of the cationic nature of dendrimers and of the integrin targeting capabilities of the RGD motif to improve gene delivery. Dendrimers were used as scaffolds for RGD clustering and, by controlling the number of peptides (4, 8, and 16) linked to each dendrimer, it was possible to evaluate the effect of RGD density on the gene delivery process. The new vectors were characterized in respect to their ability to neutralize and compact plasmid DNA (pDNA). The complexes formed by the vectors and pDNA were studied concerning their size, zeta potential, capacity of being internalized by cells and ability of transferring genes. Transfection efficiency was analyzed, first, by using a pDNA encoding for Enhanced Green Fluorescent Protein and Firefly Luciferase and, second, by using a pDNA encoding for Bone Morphogenetic Protein-2. Gene expression in mesenchymal stem cells was enhanced using the new vectors in comparison to native dendrimers and was shown to be dependent on the electrostatic interaction established between the dendrimer moiety and the cell surface, as well as on the RGD density of nanoclusters. The use of dendrimer scaffolds for RGD cluster formation is a new approach that can be extended beyond gene delivery applications, whenever RGD clustering is important for modulating cellular responses. © 2011 American Chemical Society.
Keywords: Amino Acid Sequence; Amino acids; animal cell; animal experiment; Animals; Arginine-glycine-aspartic acids; arginylglycylaspartic acid; article; Biomimetics; bone morphogenetic protein 2; Bone morphogenetic protein-2; Cell culture; Cell membranes; cell surface; Cell surfaces; cell survival; Cellular response; Cluster formations; Complexation; controlled study; dendrimer; Dendrimers; Electrostatic interactions; electrostatic precipitation; Encoding (symbols); Enhanced green fluorescent protein; Firefly luciferase; Functional polymers; Gene delivery; Gene delivery vectors; gene expression; gene targeting; Gene therapy; Gene transfer; Gene Transfer Techniques; gene vector; integrin; Integrins; male; Mesenchymal stem cell; Mesenchymal Stem Cells; Molecular Structure; Nanoclusters; Nanostructures; New approaches; nonhuman; Oligopeptides; Organic acids; Peptides; plasmid DNA; Plasmid DNA (pDNA); polyamidoamine; Polyamidoamine dendrimers; Polyamines; priority journal; rat; Rats; Rats, Wistar; RGD motif; Scaffolds; Stem cells; Structure-Activity Relationship; Targeting capability; Transfection efficiency; Vectors; Zeta potential

Interactions of leukocytes and platelets with poly(lysine/leucine) immobilized on tetraethylene glycol-terminated self-assembled monolayers - Martins, M.C.L.; Ochoa-Mendes, V.; Ferreira, G.; Barbosa, J.N.; Curtin, S.A.; Ratner, B.D.; Barbosa, M.A. (Acta BiomaterialiaActa Biomater., 2011)
Surfaces that bind heparin are important for biomaterials for blood deheparinization. In our recent work it was demonstrated that a polypeptide composed of l-lysine and l-leucine (pKL), after immobilization onto tetra(ethylene glycol) terminated self-assembled monolayers (EG4-SAMs), can bind heparin from blood plasma in a selective, concentration-dependent way. During this work the effect of this peptide on platelet adhesion and activation and leukocyte adhesion was studied. The surface charge of these nanostructured surfaces was evaluated in order to correlate the effect of positively charged amine groups and hydrophobic methyl groups on the behavior of platelets and leukocyte adhesion. The results demonstrated that the presence of pKL decreased leukocyte adhesion to EG4-SAMs at all concentrations used. This effect is even more pronounced when surfaces were pre-immersed in heparinized plasma. In contrast, there is an increase in platelet adhesion and activation with increased percentage immobilized pKL. This effect is enhanced when surfaces were pre-immersed in heparinized plasma. However, adsorbed pKL in very low amounts does not induce platelet adhesion and activation compared with EG4, even when pre-immersed in plasma. Since only low pKL amounts are necessary to induce heparin selectivity, these results are promising for the development of heparin-binding biomaterials for blood deheparinization. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: article; Blood Platelets; Cell Communication; Cell Shape; Ethylene Glycol; heparin; heparin binding protein; Humans; hydrophobicity; Imidazoles; Immobilized Proteins; leucine; leukocyte; leukocyte adherence; Leukocytes; methyl group; nanomaterial; plasma; Platelet Adhesiveness; Platelets; Polyethylene Glycols; polylysine; polypeptide; priority journal; Proteins; self assembled monolayer; Self-assembled monolayers; static electricity; Surface charge; Surface Properties; Tetra; thrombocyte; thrombocyte adhesion

Isotropic micropatterned silica coatings on zirconia induce guided cell growth for dental implants - Pelaez-Vargas, A.; Gallego-Perez, D.; Magallanes-Perdomo, M.; Fernandes, M.H.; Hansford, D.J.; De Aza, A.H.; Pena, P.; Monteiro, F.J. (Dental MaterialsDent. Mater., 2011)
Titanium implants are the gold standard in dentistry; however, problems such as gingival tarnishing and peri-implantitis have been reported. For zirconia to become a competitive alternative dental implant material, surface modification techniques that induce guided tissue growth must be developed. Objectives: To develop alternative surface modification techniques to promote guided tissue regeneration on zirconia materials, for applications in dental implantology. Methods: A methodology that combined soft lithography and sol-gel chemistry was used to obtain isotropic micropatterned silica coatings on yttria-stabilized zirconia substrates. The materials were characterized via chemical, structural, surface morphology approaches. In vitro biological behavior was evaluated in terms of early adhesion and viability/metabolic activity of human osteoblast-like cells. Statistical analysis was conducted using one-way ANOVA/Tukey HSD post hoc test. Results: Isotropic micropatterned silica coatings on yttria-stabilized zirconia substrates were obtained using a combined approach based on sol-gel technology and soft lithography. Micropatterned silica surfaces exhibited a biocompatible behavior, and modulated cell responses (i.e. inducing early alignment of osteoblast-like cells). After 7 d of culture, the cells fully covered the top surfaces of pillar microstructured silica films. Significance: The micropatterned silica films on zirconia showed a biocompatible response, and were capable of inducing guided osteoblastic cell adhesion, spreading and propagation. The results herein presented suggest that surface-modified ceramic implants via soft lithography and sol-gel chemistry could potentially be used to guide periodontal tissue regeneration, thus promoting tight tissue apposition, and avoiding gingival retraction and peri-implantitis. © 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Adhesion; article; Biological behavior; biomaterial; biomedical and dental materials; cell adhesion; Cell culture; Cell Line; cell proliferation; Cell response; cell survival; Ceramic implants; ceramics; chemistry; Coated Materials, Biocompatible; Coatings; confocal microscopy; crystallography; Dental implant materials; Dental implantology; Dental Implants; Dental Materials; Dental prostheses; diagnostic agent; dyes, reagents, indicators, markers and buffers; Gels; Gold standards; Growth kinetics; Guided tissue regeneration; Guided Tissue Regeneration, Periodontal; heat; Hot Temperature; human; Human osteoblast-like cells; Humans; In-vitro; Indicators and Reagents; Lithography; materials testing; Micropatterned; Microscopy, Confocal; Microscopy, Electron, Scanning; osteoblast; Osteoblast-like cells; Osteoblastic cell adhesion; Osteoblasts; oxazine derivative; Oxazines; Peri-implantitis; Periodontal tissue; periodontics; phase transition; physiology; Raman spectrometry; resazurin; Scanning electron microscopy; Silica; Silica coatings; Silica film; Silica surface; silicon dioxide; Soft lithography; Sol-gel; Sol-gel chemistry; Sol-gel process; Sol-gel technology; Sol-gels; Sols; Spectrum Analysis, Raman; Stabilized zirconia; Statistical analysis; Surface modification techniques; Surface morphology; Surface Properties; surface property; Surface-modified; Surfaces; time; Time Factors; Tissue; Tissue growth; Titanium; Titanium implants; tooth implantation; Top surface; X ray diffraction; X-Ray Diffraction; xanthene derivative; Xanthenes; yttria stabilized tetragonal zirconia; Yttria stabilized zirconia; yttrium; Yttrium alloys; Zirconia; Zirconia materials; zirconium

Knowledge of adverse neonatal outcome alters clinicians' interpretation of the intrapartum cardiotocograph - Ayres-de-Campos, D.; Arteiro, D.; Costa-Santos, C.; Bernardes, J. (BJOG: An International Journal of Obstetrics and GynaecologyBJOG Int. J. Obstet. Gynaecol., 2011)
Objective: To evaluate the impact of knowledge of neonatal outcome on clinicians' interpretation of the intrapartum cardiotocograph (CTG). Design: Prospective evaluation of pre-recorded cases. Setting: Five maternity hospitals. Population: From a database of intrapartum CTGs acquired with a scalp electrode in singleton near-term fetuses, 20 tracings were sequentially selected from cases with newborn umbilical artery pH < 7.05 and 20 from cases with pH > 7.20. Methods: Five experienced obstetricians practising in different maternity hospitals were asked to analyse the 40 tracings individually, according to the International Federation of Gynaecology and Obstetrics guidelines. In a first round, clinicians were given no information on neonatal outcome. In a second round, carried out 2 months later, clinicians were asked to analyse the same tracings, but the order was randomly altered and information on the newborn's arterial pH was provided. Clinicians were not informed of the purpose of the study or whether the tracings were the same. Main outcome measures: The incidence of individual fetal heart rate feature identification and tracing classification, before and after neonatal outcome was made available. Results: In the group with pH < 7.05, repetitive decelerations and reduced variability were more common in the second round (P < 0.001 and P = 0.001, respectively), as was a pathological classification (P = 0.002); variable decelerations were less common (P = 0.008). In the group with normal pH, less tracings in the second round had prolonged decelerations (P = 0.013) and no accelerations (P = 0.013), but more had pronounced decelerations (P = 0.031) and reduced variability (P = 0.007); there was a reduction in pathological classifications, but this difference failed to reach statistical significance (P = 0.051). Conclusions: A knowledge of adverse neonatal outcome leads to a more severe classification of the intrapartum CTG, which derives mainly from the evaluation of decelerations and variability. © 2011 The Authors BJOG An International Journal of Obstetrics and Gynaecology © 2011 RCOG.
Keywords: adverse outcome; Agreement; article; bradycardia; Cardiotocography; clinical competence; Female; Fetal; Fetal hypoxia; Fetal monitoring; fetus heart rate; fetus outcome; health practitioner; Heart rate; Heart Rate, Fetal; human; Humans; Hydrogen-Ion Concentration; incidence; Infant, Newborn; intrapartum care; Labor, Obstetric; medical practice; pH; practice guideline; Practice Guidelines as Topic; Pregnancy; Pregnancy Outcome; priority journal; Prospective Studies; Questionnaires; Reference Standards; Reproducibility of Results; Research Design; Risk Factors; Sweden; tachycardia; umbilical artery

Layer-by-layer self-assembly of chitosan and poly(γ-glutamic acid) into polyelectrolyte complexes - Antunes, J.C.; Pereira, C.L.; Molinos, M.; Ferreira-da-Silva, F.; Dessi, M.; Gloria, A.; Ambrosio, L.; Gonca̧lves, R.M.; Barbosa, M.A. (BiomacromoleculesBiomacromolecules, 2011)
Chitosan (Ch) is a nontoxic and biocompatible polysaccharide extensively used in biomedical applications. Ch, as a polycation, can be combined with anionic polymers by layer-bylayer (LbL) self-assembly, giving rise to multilayered complexed architectures. These structures can be used in tissue engineering strategies, as drug delivery systems, or artificial matrices mimicking the extracellular microenvironment. In this work, Ch was combined with poly(γ-glutamic acid) (γ-PGA). γ-PGA is a polyanion, which was microbially produced, and is known for its low immunogenic reaction and low cytotoxicity. Multilayered ultrathin films were assembled by LbL, with a maximum of six layers. The interaction between both polymers was analyzed by: ellipsometry, quartz crystal microbalance with dissipation, Fourier transform infrared spectroscopy, atomic force microscopy, and zeta potential measurements. Ch/γ-PGA polyelectrolyte multilayers (PEMs) revealed no cytotoxicity according to ISO 10993-5. Overall, this study demonstrates that Ch can interact electrostatically with γ-PGA forming multilayered films. Furthermore, this study provides a comprehensive characterization of Ch/γ-PGA PEM structures, elucidating the contribution of each layer for the nanostructured films. These model surfaces can be useful substrates to study cell-biomaterial interactions in tissue regeneration. © 2011 American Chemical Society.
Keywords: Amino acids; Anionic polymers; article; Atomic force microscopy; Atomic spectroscopy; Biocompatible Materials; Biocompatible polysaccharides; Biomaterials; Biomedical applications; Cell-biomaterial interactions; chemical interaction; chitosan; controlled study; Cytotoxicity; Drug delivery; drug delivery system; Drug Delivery Systems; Electrolytes; ellipsometry; enzyme activity; Extracellular; Fourier transform infrared spectroscopy; Glutamic acid; immunogenicity; infrared spectroscopy; Layer by layer self assembly; Medical applications; microenvironment; Microenvironments; Microscopy, Atomic Force; Model surface; Models, Molecular; Multi-layered; Multi-layered films; Multilayers; nanofilm; Nanostructured Films; polyanion; Polyanions; Polycations; polyelectrolyte; Polyelectrolyte complexes; Polyelectrolyte multilayer; Polyelectrolytes; Polyethylenes; polyglutamic acid; Polymers; priority journal; Programmed control systems; Quartz; quartz crystal microbalance; Quartz crystal microbalance with dissipation; Self assembly; Tissue; Tissue engineering; Tissue regeneration; Ultrathin films; Viscoelastic Substances; Zeta potential; Zeta potential measurements

The limits of agreement and the intraclass correlation coefficient may be inconsistent in the interpretation of agreement - Costa-Santos, C.; Bernardes, J.; Ayres-de-Campos, D.; Costa, A.; Costa, C. (Journal of Clinical EpidemiologyJ. Clin. Epidemiol., 2011)
Objective: To compare the interpretation of agreement in the prediction of neonatal outcome variables, using the limits of agreement (LA) and the intraclass correlation coefficient (ICC). Study Design and Setting: Three obstetricians were asked to predict neonatal outcomes independently based on the evaluation of intrapartum cardiotocographic tracings. Interobserver agreement was assessed with the LA and the ICC, and the results obtained were interpreted by six clinicians and six statisticians on a scale that established agreement as very poor, poor, fair, good, or very good. Results: Interpretation of the LA results was less consensual than the ICC results, with proportions of agreement of 0.36 (95% confidence interval [CI]: 0.28-0.44) vs. 0.63 (95% CI: 0.54-0.73), respectively. LA results suggested a fair to good agreement among obstetricians, whereas interpretation of ICC results suggested a poor to fair agreement. LA results were more plausible with reality, suggesting that obstetricians predicted neonatal outcomes better than randomly generated values, whereas it was not always the case with the ICC. Conclusions: LA and ICC can provide inconsistent results in agreement studies. Accordingly, in the absence of better strategies to assess agreement, both should be used for this purpose, but their results need to be interpreted with caution keeping their respective limitations in mind. © 2011 Elsevier Inc. All rights reserved.
Keywords: Agreement; Apgar score; Cardiotocography; correlation coefficient; Female; Fetal Blood; human; Humans; Hydrogen-Ion Concentration; Infant, Newborn; intrapartum care; limit of agreement; newborn assessment; normal human; observer variation; Obstetrics; outcome variable; Pregnancy; Pregnancy Outcome; priority journal; reproducibility; Reproducibility of Results; review; statistical data interpretation; statistical parameters; Umbilical Arteries; Umbilical artery blood pH; umbilical cord blood

Low frame rate cell tracking: A Delaunay graph matching approach - Chen, Y.; Quelhas, P.; Campilho, A. (Proceedings - International Symposium on Biomedical ImagingIEEE Comput. Soc. Conf. Comput. Vis. Pattern Recogn., 2011)
Cell tracking is a fundamental problem for studying live cell dynamics. A novel approach for low frame rate cell tracking in fluorescent microscopy image is herein proposed. The method is based on sliding band filter detection and Delaunay triangulation sub-graph matching. With this approach we can track a large amount of small cells without their motion model and not relying on cell motion continuity between consecutive images. The effectiveness and robustness of the method were validated by visual inspection and on a ground truth dataset. © 2011 IEEE.
Keywords: Band filters; cell motion; Cell tracking; Cells; Consecutive images; Data sets; Delaunay graph; Delaunay graph matching; Delaunay triangulation; Fluorescent microscopy; Frame rate; Fundamental problem; Ground truth; Live cell; low frame rate tracking; Medical imaging; Motion models; small target tracking; Small targets; Target tracking; Visual inspection

MIQuant - semi-automation of infarct size assessment in models of cardiac ischemic injury - Nascimento, D.S.; Valente, M.; Esteves, T.; De Fátima De Pina, M.; Guedes, J.G.; Freire, A.; Quelhas, P.; Pinto-Do-Ó, P. (PLoS ONE, 2011)

Molecular recognition force spectroscopy: A new tool to tailor targeted nanoparticles - Oliveira, H.; Rangl, M.; Ebner, A.; Mayer, B.; Hinterdorfer, P.; Pêgo, A.P. (SmallSmall, 2011)
The density of targeting moieties in a nanoparticle-based gene-delivery system has been shown to play a fundamental role in its vectoring performance. Here, molecular recognition force spectroscopy is proposed as a novel screening tool to optimize the density of targeting moieties of functionalized nanoparticles towards attaining cell-specific interaction. By tailoring the nanoparticle formulation, the unbinding event probability between nanoparticles tethered to an atomic force microscopy tip and neuronal cells is directly correlated to the nanoparticle gene-vectoring capacity. Additionally, new insights into protein-receptor interaction are revealed. This novel approach opens new avenues in the field of nanomedicine. A novel screening tool is described to optimize the density of targeting moieties of functionalized nanoparticles towards attaining cell-specific interaction. The unbinding event probability between nanoparticles tethered to an atomic force microscopy tip and neuronal cells is directly correlated to the nanoparticle gene-vectoring capacity. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: article; Atomic force microscopy; Atomic spectroscopy; atomic-force microscopy; chemistry; Event probability; Force spectroscopy; Functionalized nanoparticles; gene technology; Gene-delivery systems; Genes; Medical nanotechnology; medicine; methodology; Microscopy, Atomic Force; Molecular biology; Molecular recognition; molecular recognition force spectroscopy; Nanomedicines; nanoparticle; Nanoparticle formulation; nanoparticles; Nanotechnology; Neuronal cell; Optimization; Receptor interaction; Screening tool; Specific interaction; Targeted nanoparticle

Molecularly designed alginate hydrogels susceptible to local proteolysis as three-dimensional cellular microenvironments - Fonseca, K.B.; Bidarra, S.J.; Oliveira, M.J.; Granja, P.L.; Barrias, C.C. (Acta BiomaterialiaActa Biomater., 2011)
The development of sophisticated three-dimensional (3-D) cell culture microenvironments that recreate some of the complexity of the natural extracellular matrix (ECM) remains a challenging task. Here, the modification of alginate through partial crosslinking with a matrix metalloproteinase (MMP) cleavable peptide (proline-valine-glycine-leucine-isoleucine-glycine, PVGLIG) is described, and its use in the preparation of injectable, in situ crosslinkable hydrogel-like matrices is proposed. PVGLIG-grafted alginates were synthesized by carbodiimide chemistry and characterized. Their biological performance was evaluated by comparing the response of 3-D cultured mesenchymal stem cells (MSCs) to alginate hydrogels containing only cell-adhesion peptides (RGD-alginate) or both peptides (PVGLIG/RGD-alginate). After 1 week, cells remained essentially round within RGD-alginate, while they exhibited an elongated morphology within PVGLIG/RGD-alginate hydrogels, forming cellular networks. This suggests that cells were able to structurally reorganize the matrix, through enzymatic hydrolysis of PVGLIG residues, overcoming biophysical hydrogel resistance. As shown by gelatine-zymography, MSC presented higher activity of MMP-2 when cultured within alginate functionalized with MMP-sensitive peptide, suggesting that the cell's proteolytic phenotype was modulated by the matrix composition. Additionally, PVGLIG/RGD-alginate hydrogels were clearly degraded in cell culture. Taken together, the results demonstrate that the co-incorporation of MMP-labile peptides in cell-adhesive RGD-alginate hydrogels improved their performance as ECM analogues, providing a more dynamic and physiological 3-D cellular microenvironment. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: 3-D Cell culture; Alginate; Alginates; alginic acid; Amino Acid Sequence; article; cell adhesion; cell composition; Cell Count; Cell culture; Cell Culture Techniques; Cell Shape; cell structure; cell survival; cell viability; Cells, Cultured; controlled study; Enzyme Activation; enzyme activity; extracellular matrix; Extracellular matrix (ECM); gelatin; gelatinase A; Glucuronic Acid; Hexuronic Acids; human; human cell; Humans; hydrogel; Hydrogels; hydrolysis; matrix metalloproteinase; Matrix Metalloproteinases; Matrix metalloproteinases (MMPs); Mesenchymal stem cell; Mesenchymal Stem Cells; Molecular Sequence Data; morphology; peptide derivative; Peptides; phenotype; priority journal; prolylvalylglycylleucylisoleucylglycine; Protease-sensitive; protein cleavage; protein degradation; Protein Processing, Post-Translational; Subcellular Fractions; tumor microenvironment; unclassified drug; zymography

New results on minimum error entropy decision trees - De Sá, J.P.M.; Sebastião, R.; Gama, J.; Fontes, T. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2011)
We present new results on the performance of Minimum Error Entropy (MEE) decision trees, which use a novel node split criterion. The results were obtained in a comparive study with popular alternative algorithms, on 42 real world datasets. Carefull validation and statistical methods were used. The evidence gathered from this body of results show that the error performance of MEE trees compares well with alternative algorithms. An important aspect to emphasize is that MEE trees generalize better on average without sacrifing error performance. © 2011 Springer-Verlag.
Keywords: Algorithms; Alternative algorithms; Computer vision; Decision Theory; decision trees; entropy; entropy-of-error; Error entropy; Error performance; Forestry; New results; node split criteria; Real-world datasets; Vision

Non-viral gene delivery to mesenchymal stem cells: Methods, strategies and application in bone tissue engineering and regeneration - Santos, J.L.; Pandita, D.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (Current Gene TherapyCurr. Gene Ther., 2011)
Mesenchymal stem cells (MSCs) can be isolated from several tissues in the body, have the ability to selfrenewal, show immune suppressive properties and are multipotent, being able to generate various cell types. At present, due to their intrinsic characteristics, MSCs are considered very promising in the area of tissue engineering and regenerative medicine. In this context, genetic modification can be a powerful tool to control the behavior and fate of these cells and be used in the design of new cellular therapies. Viral systems are very effective in the introduction of exogenous genes inside MSCs. However, the risks associated with their use are leading to an increasing search for non-viral approaches to attain the same purpose, even if MSCs have been shown to be more difficult to transfect in this way. In the past few years, progress was made in the development of chemical and physical methods for non-viral gene delivery. Herein, an overview of the application of those methods specifically to MSCs is given and their use in tissue engineering and regenerative medicine therapeutic strategies highlighted using the example of bone tissue. Key issues and future directions in non-viral gene delivery to MSCs are also critically addressed. © 2011 Bentham Science Publishers Ltd.
Keywords: Animals; article; artificial chromosome; Bone and Bones; Bone Regeneration; bone tissue; Bone tissue engineering; cell based gene therapy; dendrimer; ex vivo gene transfer; Gene delivery; gene targeting; Gene therapy; Gene Transfer Techniques; gene vector; genetic transfection; human; Humans; in vivo gene transfer; liposome; Mesenchymal stem cell; Mesenchymal Stem Cells; nanomedicine; nanoparticle; Non-viral vectors; nonhuman; nonviral gene delivery system; polymer; protein expression; Regeneration; Regenerative Medicine; Tissue engineering; Tissue regeneration

Novel TiN x-based biosignal electrodes for electroencephalography - Fiedler, P.; Cunha, L.T.; Pedrosa, P.; Brodkorb, S.; Fonseca, C.; Vaz, F.; Haueisen, J. (Measurement Science and TechnologyMeas. Sci. Technol., 2011)
A composition, structural, morphological and electrochemical study of two titanium nitride (TiN x) thin films, sample A and sample B, obtained by dc reactive sputtering on titanium substrates was carried out in this paper. In order to assess their applicability to be used as dry electrodes, several EEG signal acquisition tests were performed using the TiN x electrodes and compared to signals acquired with conventional silver/silver-chloride (Ag/AgCl) electrodes. The two films displayed some compositional differences, as sample B was over-stoichiometric (x = 1.34, x = N/Ti atomic ratio) and sample A was close-stoichiometric (x = 0.94). XRD diffractograms showed that both samples developed a similar fcc crystalline structure (δ-TiN phase). XRD peak fitting showed that sample B (over-stoichiometric) has a more oriented structure (highly [1 1 1] textured), with larger grains. A columnar-type structure with pyramid-like shape at column's top was common to both TiN x films. This morphology, in addition to some columnar disaggregation, gives rise to a rather rough surface and porous structure. Electrochemical impedance spectroscopy results in artificial sweat showed that the electric properties of the samples remain unchanged, even after prolonged contact with sweat. The comparison of EEG signals, simultaneously recorded using the novel TiN x electrodes and conventional Ag/AgCl electrodes, showed very similar results. The root mean square deviation, which was computed for different electrode-electrolyte combinations and signal sequences of 5 s, was in the range of 4.5-9.4 νV and 6.7-20.4 νV for samples A and B, respectively. An additional test with two sets of Ag/AgCl electrodes revealed similar results, thus indicating most of the signal differences are related to the spatial distance of the compared electrodes as well as environmental noise. Therefore, our results lead to the conclusion that the novel TiN x electrodes show promising signal quality for application in EEG biosignal measurements. © 2011 IOP Publishing Ltd.
Keywords: bioelectric; biomedical electrodes; Chlorine compounds; dc magnetron sputtering; Electric properties; Electrochemical impedance spectroscopy; Electrochemical properties; Electrodes; electroencephalography; Electrophysiology; Signal processing; signals; Surface structure; Thin films; Tinning; Titanium; Titanium nitride; titanium nitride thin films

Novel Ti/TiN dry electrodes and Ag/AgCl: A direct comparison in multichannel EEG - Fiedler, P.; Griebel, S.; Fonseca, C.; Vaz, F.; Zentner, L.; Zanow, F.; Haueisen, J. (IFMBE ProceedingsIFMBE Proc., 2011)
With up to 256 silver/silver-chloride (Ag/AgCl) electrodes, research using multichannel electroencephalography (EEG) is nowadays characterized by an increasing number of electrodes. Hence, the preparation gets more and more time-consuming and error-prone. We propose a novel electrode concept based on titanium/titanium nitride (Ti/TiN) electrodes integrated into a novel EEG cap based on fluidicdriven mechanisms. We describe the construction of our electrodes and perform EEG measurements in order to evaluate them in a multichannel setup. Therefore an additional set of conventional Ag/AgCl electrodes was integrated into the Ti/TiN EEG cap, enabling simultaneous recordings with both types of electrodes. In our tests, which included spontaneous EEG like resting state EEG, eye movements, alpha activity, and pattern reversal VEP, we found no considerable differences between compared adjacent electrodes. For the pattern reversal VEP, we found similar potential maps with both types of electrodes. In conclusion, our novel Ti/TiN electrodes have the potential to replace the conventional Ag/AgCl electrodes. © 2011 Springer-Verlag Berlin Heidelberg.
Keywords: Ag/AgCl; Alpha activities; Biomedical Electrode; biomedical electrodes; Chlorine compounds; Concept-based; Dry electrode; EEG Cap; Electric Potential; Electrodes; electroencephalography; Electrophysiology; Error prones; Eye movements; Multi-channel; Multichannel EEG; Nitrides; Potential map; Resting state; Silicone Fluidic- Driven Mechanism; Silicones; Simultaneous recording

Observer reliability and agreement: Differences, difficulties, and controversies - Costa Santos, C.; Bernardes, J.; Ayres-de-Campos, D. (Journal of Clinical EpidemiologyJ. Clin. Epidemiol., 2011)
Keywords: consensus; correlation coefficient; letter; methodology; organization; priority journal; reliability; research; scientific literature; validity

Pectin-based injectable biomaterials for bone tissue engineering - Munarin, F.; Guerreiro, S.G.; Grellier, M.A.; Tanzi, M.C.; Barbosa, M.A.; Petrini, P.; Granja, P.L. (BiomacromoleculesBiomacromolecules, 2011)
A variety of natural polymers and proteins are considered to be 3D cell culture structures able to mimic the extracellular matrix (ECM) to promote bone tissue regeneration. Pectin, a natural polysaccharide extracted from the plant cell walls and having a chemical structure similar to alginate, provides interesting properties as artificial ECM. In this work, for the first time, pectin, modified with an RGD-containing oligopeptide or not, is used as an ECM alternative to immobilize cells for bone tissue regeneration. The viability, metabolic activity, morphology, and osteogenic differentiation of immobilized MC3T3-E1 preosteoblats demonstrate the potential of this polysaccharide to keep immobilized cells viable and differentiating. Preosteoblasts immobilized in both types of pectin microspheres maintained a constant viability up to 29 days and were able to differentiate. The grafting of the RGD peptide on pectin backbone induced improved cell adhesion and proliferation within the microspheres. Furthermore, not only did cells grow inside but also theywere able to spread out from themicrospheres and to organize themselves in 3D structures producing a mineralized extracellular matrix. These promising results suggest that pectin can be proposed as an injectable cell vehicle for bone tissue regeneration. © 2011 American Chemical Society.
Keywords: 3-D Cell culture; 3D Structure; 3T3 Cells; Adhesion; Alginate; animal cell; Animals; arginylglycylaspartic acid; article; Biocompatible Materials; Biopolymers; Bone; Bone and Bones; Bone Regeneration; bone tissue; Bone tissue engineering; Bone tissue regeneration; carbohydrate analysis; cell adhesion; Cell culture; cell differentiation; cell growth; cell metabolism; cell proliferation; cell spreading; cell structure; cell viability; Cells; Chemical modification; Chemical structure; controlled study; Cryoelectron Microscopy; Extracellular matrices; extracellular matrix; gene expression; immobilized cell; Immobilized cells; Injectable biomaterials; Injections; MC3T3-E1; Metabolic activity; Mice; Microscopy, Electron, Scanning; microsphere; Microspheres; Mineralized extracellular matrixes; mouse; Natural polysaccharide; nonhuman; Oligopeptides; osteoblast; osteocalcin; Osteogenic differentiation; pectin; Pectins; Plant cell culture; Plant cell wall; Preosteoblasts; priority journal; RGD peptide; Three dimensional; Tissue engineering

Scientists perception of ethical issues in nanomedicine: A case study - Silva Costa, H.; Sethe, S.; Pêgo, A.P.; Olsson, I.A.S. (NanomedicineNanomedicine, 2011)
Aim: Research and development in nanomedicine has been accompanied by the consideration of ethical issues; however, little is known about how researchers working in this area perceive such issues. This case-study explores scientists attitude towards and knowledge of ethical issues. Method: Data were collected by semi-structured interviews with 22 nanomedicine practitioners and subject to content analysis. Results: We found that scientists reflect with ambiguity on the reputed novelty of nanomedicine and what the ethical issues and risks are in their work. Respondents see no necessity for a paradigm shift in ethical considerations, but view ethical issues in nanomedicine as overlapping with those of other areas of biomedical research. Most respondents discuss ethical issues they faced in scientific work with their colleagues, but expect benefit from additional information and training on ethics. Conclusion: Our findings that scientists are motivated to reflect on ethical issues in their work, can contribute to the design of new strategies, including training programs, to engage scientists in ethical discussion and stimulate their responsibility as nanomedicine practitioners. © 2011 Future Medicine Ltd.
Keywords: adult; ambiguity; article; attitude; case study; clinical article; empirical research; ethics; Female; human; Humans; information; knowledge; male; medical ethics; medical research; Middle Aged; Models, Theoretical; nanomedicine; Nanotechnology; perception; priority journal; professional practice; qualitative study; Research Personnel; responsibility; risks; scientist; scientists perception; semi structured interview; training; Young Adult

Segmentation of ultrasound images of the carotid using RANSAC and cubic splines - Rocha, R.; Campilho, A.; Silva, J.; Azevedo, E.; Santos, R. (Computer Methods and Programs in BiomedicineComput. Methods Programs Biomed., 2011)
A new algorithm is proposed for the semi-automatic segmentation of the near-end and the far-end adventitia boundary of the common carotid artery in ultrasound images. It uses the random sample consensus method to estimate the most significant cubic splines fitting the edge map of a longitudinal section. The consensus of the geometric model (a spline) is evaluated through a new gain function, which integrates the responses to different discriminating features of the carotid boundary: the proximity of the geometric model to any edge or to valley shaped edges; the consistency between the orientation of the normal to the geometric model and the intensity gradient; and the distance to a rough estimate of the lumen boundary.A set of 50 longitudinal B-mode images of the common carotid and their manual segmentations performed by two medical experts were used to assess the performance of the method. The image set was taken from 25 different subjects, most of them having plaques of different classes (class II to class IV), sizes and shapes.The quantitative evaluation showed promising results, having detection errors similar to the ones observed in manual segmentations for 95% of the far-end boundaries and 73% of the near-end boundaries. © 2011 Elsevier Ireland Ltd.
Keywords: Algorithms; article; B scan; B-mode images; Carotid; carotid artery; Carotid Artery Diseases; Carotid Artery, Common; Class II; clinical article; Common carotid artery; Cubic spline; Detection error; echography; Edge map; Female; Gain function; Geometric models; Geometry; human; Humans; Image Interpretation, Computer-Assisted; image processing; Image segmentation; Image sets; Intensity gradients; Longitudinal section; male; Manual segmentation; mathematical model; Medical experts; Medical imaging; Non-linear smoothing; Pattern Recognition, Automated; quantitative analysis; Quantitative evaluation; random sample; Random sample consensus; RANSAC; Semi-automatic segmentation; Splines; Ultrasonic applications; Ultrasonics; Ultrasonography; Ultrasound image; Ultrasound images

Simulations of the NK cell immune synapse reveal that activation thresholds can be established by inhibitory receptors acting locally - Kaplan, A.; Kotzer, S.; Almeida, C.R.; Kohen, R.; Halpert, G.; Salmon-Divon, M.; Köhler, K.; Höglund, P.; Davis, D.M.; Mehr, R. (Journal of ImmunologyJ. Immunol., 2011)
NK cell activation is regulated by a balance between activating and inhibitory signals. To address the question of how these signals are spatially integrated, we created a computer simulation of activating and inhibitory NK cell immunological synapse (NKIS) assembly, implementing either a "quantity-based" inhibition model or a "distance-based" inhibition model. The simulations mimicked the observed molecule distributions in inhibitory and activating NKIS and yielded several new insights. First, the total signal is highly influenced by activating complex dissociation rates but not by adhesion and inhibitory complex dissociation rates. Second, concerted motion of receptors in clusters significantly accelerates NKIS maturation. Third, when the potential of a cis interaction between Ly49 receptors and MHC class I on murine NK cells was added to the model, the integrated signal as a function of receptor and ligand numbers was only slightly increased, at least up to the level of 50% cis-bound Ly49 receptors reached in the model. Fourth, and perhaps most importantly, the integrated signal behavior obtained when using the distance-based inhibition signal model was closer to the experimentally observed behavior, with an inhibition radius of the order 3-10 molecules. Microscopy to visualize Vav activation in NK cells on micropatterned surfaces of activating and inhibitory strips revealed that Vav is only locally activated where activating receptors are ligated within a single NK cell contact. Taken together, these data are consistent with a model in which inhibitory receptors act locally; that is, that every bound inhibitory receptor acts on activating receptors within a certain radius around it. Copyright © 2011 by The American Association of Immunologists, Inc.
Keywords: animal cell; animal experiment; Animals; antigen recognition; article; cell maturation; cell membrane; Computer simulation; controlled study; dissociation; H-2 Antigens; Histocompatibility Antigens Class I; HLA antigen; HLA C antigen; Humans; immunological synapse; Immunological Synapses; intercellular adhesion molecule 1; Intercellular Adhesion Molecule-1; killer cell immunoglobulin like receptor 2DL1; Killer Cells, Natural; lymphocyte activation; lymphocyte function associated antigen 1; Lymphocyte Function-Associated Antigen-1; major histocompatibility antigen class 1; Membrane Microdomains; Mice; Models, Immunological; mouse; natural killer cell; natural killer cell receptor NKG2D; NK Cell Lectin-Like Receptor Subfamily A; NK Cell Lectin-Like Receptor Subfamily K; nonhuman; priority journal; protein assembly; Receptors, KIR; signal transduction; steady state; Vav protein

Systemic delivery of bone marrow-derived mesenchymal stromal cells diminishes neuropathology in a mouse model of Krabbe's disease - Miranda, C.O.; Teixeira, C.A.; Liz, M.A.; Sousa, V.F.; Franquinho, F.; Forte, G.; Di Nardo, P.; Pinto-Do-Ó, P.; Sousa, M.M. (Stem Cells, 2011)

Access to computerised analysis of intrapartum cardiotocographs improves clinicians' prediction of newborn umbilical artery blood pH - Costa, A.; Santos, C.; Ayres-de-Campos, D.; Costa, C.; Bernardes, J. (BJOG: An International Journal of Obstetrics and GynaecologyBJOG Int. J. Obstet. Gynaecol., 2010)
Objective To evaluate the impact of access to computerised cardiotocograph (CTG) analysis on reproducibility and accuracy of clinicians' predictions of umbilical artery blood pH (UAB pH) and 5-minute Apgar score. Design Prospective evaluation of pre-recorded cases. Setting A tertiary-care university hospital. Population From databases of intrapartum CTGs acquired in singleton term pregnancies, 204 tracings with low signal loss and short time interval to delivery were consecutively selected. Methods Tracings were randomly assigned to computer analysis by the Omniview-SisPorto 3.5 ® system (study group n = 104) or to no analysis (control group n = 100). Three experienced clinicians evaluated all tracing printouts independently and were asked to predict the newborns' UAB pH and 5-minute Apgar scores from them. Main outcome measures Interobserver agreement (measured by the intraclass correlation coefficient [ICC]) and accuracy in prediction of neonatal outcomes with 95% CI. Results Agreement on prediction of UAB pH was significantly higher in the study group (ICC = 0.70; 95% CI 0.61-0.77) than in the control group (ICC = 0.43; 95% CI 0.21-0.60), and a trend towards better agreement was also seen in estimation of 5-minute Apgar scores (ICC = 0.55; 95% CI 0.38-0.68 versus ICC = 0.43; 95% CI 0.25-0.57). Observers predicted UAB pH values correctly within a 0.10 margin in 70% of cases in the study group (95% CI 0.61-0.79) versus 46% in the control group (95% CI 0.35-0.56). They predicted 5-minute Apgar scores within a margin of one in 81% of cases in the study group (95% CI 0.73-0.88) and in 70% of cases in the control group (95% CI 0.61-0.79). Conclusions Prediction of UAB pH is more reproducible and accurate when clinicians have access to computerised analysis of CTGs. © RCOG 2010 BJOG An International Journal of Obstetrics and Gynaecology.
Keywords: access to information; Apgar score; arterial pH; article; Cardiotocography; clinical competence; computer analysis; computerised analysis; controlled study; delivery; Diagnosis, Computer-Assisted; diagnostic accuracy; Female; Fetal Blood; Fetal heart rate; Fetal monitoring; Gestational Age; human; Humans; Hydrogen-Ion Concentration; Infant, Newborn; male; neonatal acidaemia; Neonatology; newborn; observer variation; outcome assessment; prediction; Pregnancy; priority journal; Prospective Studies; prospective study; reproducibility; Umbilical Arteries; umbilical artery; university hospital

Adhesion of human leukocytes on mixtures of hydroxyl- and methyl-terminated self-assembled monolayers: Effect of blood protein adsorption - Barbosa, J.N.; Martins, M.C.L.; Freitas, S.C.; Gonçalves, I.C.; Águas, A.P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
The adhesion of human leukocytes to nanostructured surfaces with different chemical properties and the effect of protein adsorption were investigated. Selfassembled monolayers (SAMs) prepared with mixtures of methyl- and hydroxyl-terminated alkanethiols in different percentages on gold were used. The surfaces were preimmersed in distinct protein solutions (human serum albumin, human fibrinogen, and autologous plasma). Adherent leukocytes were analyzed both by light and SEM. SAMs submitted to pre-immersion in plasma presented higher numbers of adherent leukocytes in the pure OH-terminated SAM, whereas methyl-terminated surfaces accounted for the lowest number of adherent cells. We observed a general increase in the number of adherent human leukocytes as the percentage of OH groups on the surface of the SAMs increased for all the pre-immersion conditions investigated. The number of adherent human leukocytes is highly influenced by the pre-immersion conditions used, and this observation is particularly relevant in the case of the methyl-terminated SAMs. The results obtained demonstrate that surface chemistry has a major influence in leukocyte adhesion to biomaterials, and that pre-immersion in protein solutions has a determinant effect in leukocyte adhesion. © 2009 Wiley Periodicals, Inc.
Keywords: Adherent cells; Adhesion; Adsorption; Alkanethiols; article; Biological materials; biomaterial; Blood protein adsorption; Blood Proteins; cell adhesion; Cell Count; Chemical properties; gold; human; human cell; Human leukocytes; Human serum albumins; Humans; hydroxyl group; Hydroxyl Radical; Hydroxyl-terminated; immersion; Inflammatory response; leukocyte adherence; Leukocyte adhesion; Leukocytes; Nanostructured materials; Nanostructured surface; Nanostructured surfaces; OH group; Protein adsorption; protein blood level; Protein solution; Proteins; Sams; Scanning electron microscopy; Self assembled monolayers; Self-assembled monolayers; SEM; Surface chemistry; Surface Properties

Analysis of heart rate variability in a rat model of induced pulmonary hypertension - Gonçalves, H.; Henriques-Coelho, T.; Bernardes, J.; Rocha, A.P.; Brandão-Nogueira, A.; Leite-Moreira, A. (Medical Engineering and PhysicsMed. Eng. Phys., 2010)
Monocrotaline (MCT) is commonly used to experimentally induce pulmonary hypertension (PH), which might lead to chronic heart failure. In this study, linear and non-linear heart rate (HR) dynamics were weekly assessed in MCT-treated and non-treated Wistar rats.The HR of 10 adult Wistar rats injected with MCT (MCT group) and of 10 similar rats injected with vehicle (non-MCT group), anesthetized with Ketamine, was weekly recorded during 4 weeks. The first four segments of 1-min length of each HR recording were analysed using linear, time and frequency domains, and approximate (ApEn) and sample (SampEn) entropy indices, considering recently proposed values for the threshold parameter of ApEn and SampEn. Statistical analysis was performed using 95% confidence intervals and statistical tests.Along the study period, an overall weekly maintenance of HR indices, or a decrease, namely in weeks 1-2, was manifest, in the MCT group, except for LF and LF/HF, in week 1, denoting a short-term increase in sympathetic activity without any other changes. On the other hand, a maintenance of HR indices, or an increase, namely on week 4, was observed in the non-MCT group, except for LF/HF, denoting a long-term increase of the overall activity of HR control systems, with a parasympathetic like dominance.Studies on long-term HR dynamics should be performed in very carefully controlled experimental settings, as significant weekly changes may occur, both among anesthetized MCT-treated and non-treated rats. © 2010 IPEM.
Keywords: adrenergic activity; Amines; animal experiment; animal model; Animals; article; cholinergic activity; Chronic heart failures; Confidence interval; controlled study; Disease Models, Animal; Electrocardiography; entropy; Female; Frequency domain analysis; Frequency domains; Heart; heart electrophysiology; Heart rate; Heart rate variability; Heart rate variability (HRV); Heart rates; Hypertension, Pulmonary; Injections, Subcutaneous; Ketamine; Maintenance; Monocrotaline; Non-linear; nonhuman; priority journal; Pulmonary hypertension; rat; Rat model; Rats; Rats, Wistar; Statistical analysis; statistical parameters; Sympathetic activities; Threshold parameters; Time and frequency domain analysis; Time domain analysis; Time Factors; Wistar rat; Wistar rats

Anti-adhesion and antiproliferative cellulose triacetate membrane for prevention of biomaterial-centred infections associated with Staphylococcus epidermidis - Extremina, C.I.; Fonseca, A.F.d.; Granja, P.L.; Fonseca, A.P. (International Journal of Antimicrobial AgentsInt. J. Antimicrob. Agents, 2010)
The initial step in preventing biomaterial-associated infections consists of preventing bacterial adhesion to the device surface. One possible approach is the design of antibiotic-releasing biomaterials. Cellulose triacetate (CTA) membranes with the antibiotic imipenem (IPM) entrapped (CTA-IPM) were prepared. The material was characterised in terms of surface morphology by scanning electron microscopy, surface free energy of interaction and X-ray photoelectron spectroscopy (XPS). Antibiotic release studies were also performed. In vitro adhesion of Staphylococcus epidermidis RP62A to CTA-IPM was investigated using a modified microtitre plate assay, and the antibacterial activity of the CTA-IPM membrane was assessed by a modified Kirby-Bauer test, which showed effective entrapment of the antibiotic as confirmed by XPS and hydrophilicity assays. Release studies showed that this drug-polymer conjugate serves as an adequate reservoir for sustained release of IPM over a period of 71 h at an effective bacteriostatic concentration. Moreover, bacterial adhesion tests showed a statistically significant decrease in the adhesion of S. epidermidis RP62A to CTA-IPM compared with its adhesion to CTA alone. The present innovative approach is capable of providing a membrane with anti-adhesive and antiproliferative properties, thus encouraging in vivo studies to provide a better simulation of the clinical situation. © 2009 Elsevier B.V. and the International Society of Chemotherapy.
Keywords: Adhesion; Anti-Bacterial Agents; antibacterial activity; Antimicrobial agents; article; Bacterial adhesion; bacterial growth; bacteriostasis; bacterium adherence; Biocompatible Materials; biomaterial; Cellulose; Cellulose triacetate; cilastatin plus imipenem; controlled study; device infection; drug screening; Equipment and Supplies; growth inhibition; Humans; hydrophilicity; Imipenem; in vitro study; infection prevention; Membranes; Microbial Sensitivity Tests; microtiter plate assay; nonhuman; priority journal; Prosthesis-Related Infections; Scanning electron microscopy; Staphylococcus epidermidis; surface property; sustained drug release; X ray photoelectron spectroscopy

Assessment of Disagreement: A New Information-Based Approach - Costa-Santos, C.; Antunes, L.; Souto, A.; Bernardes, J. (Annals of EpidemiologyAnn. Epidemiol., 2010)
Purpose: Disagreement on the interpretation of diagnostic tests and clinical decisions remains an important problem in medicine. As no strategy to assess agreement seems to be fail-safe to compare the degree of agreement, or disagreement, we propose a new information-based approach to assess disagreement. Methods: The sum over all logarithms of possible outcomes of a variable is a valid measure of the amount of information contained in the variable. The proposed measure is based on the amount of information contained in the differences between two observations. This measure is normalized and satisfies the flowing properties: it is a metric, scaled invariant and it has differential weighting. Results: Two real examples and a simulation were used to illustrate the usefulness of the proposed measure to compare the degree of disagreement. Conclusions: Used as complement to the existing methods, we believe our approach can be useful to compare the degree of disagreement among different populations. © 2010 Elsevier Inc.
Keywords: analysis of variance; Apgar score; article; Blood Pressure Determination; blood pressure measurement; correlation coefficient; human; Humans; information science; Information Theory; intermethod comparison; mathematical computing; measurement error; medical research; metric system; Models, Statistical; observer variation; priority journal; probability; process model; reliability; Reproducibility of Results; scale up; standard; Statistical analysis; statistical model; statistics; Statistics as Topic; systolic blood pressure; validity; variance

Bioactivity of immobilized EGF on self-assembled monolayers: Optimization of the immobilization process - Gonçalves, R.; Martins, M.C.L.; Oliveira, M.J.; Almeida-Porada, G.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
Last trends in Biomaterials focus the mimic of cellular environments capable to control cellular responses. Epidermal growth factor (EGF) is a pleiotropic cytokine known to regulate cell proliferation, differentiation, and death. This study aims to optimize the immobilization of EGF on 11-mercapto-1-undecyl-tetra(ethylene)glycol (EG4) - self-assembled monolayers (SAMs) and to establish a new model surface to study EGF-mediated signaling. Gold substrates were modified with a monolayer of EG4 and N,N′- carbonyldiimidazole (CDI) was used to activate hydroxyl terminated groups of EG4-SAMs. EGF was then immobilized on activated EG4-SAMs at pH 7.4, 4°C, and 100 rpm. Different immobilization reaction times were tested as well as different CDI concentrations to optimize the reaction conditions and obtain a range of immobilized EGF concentrations on the surfaces. Surface characterization of EGF-SAMs was performed using radiolabeling, water contact angle measurements, X-ray photoelectron spectroscopy, and ELISA. Phosphorylation of EGFR on BT-20 breast cancer cell line by EGF-SAMs was tested by immunostaining. EGF was successfully immobilized on EG4-SAMs, at 4°C and pH 7.4 in a range of concentrations from 3.6 ± 0.8 to 17.6 ± 1.5 ng/cm 2. The concentration of EGF increases with immobilization time and with the CDI concentration reaching the maximum for surfaces activated with 30 mg/mL of CDI after 48 h. The bioactivity of EGF-SAMs was confirmed by immunostaining of phospho-EGFR of BT-20 cells. This study described EGF immobilization on EG4-SAMs at different concentrations, which could be important surface models to study specific protein interactions at the molecular level evolving EGF-family of proteins. © 2010 Wiley Periodicals, Inc. J.
Keywords: Adsorption; Angle measurement; article; Biocompatible Materials; Biological materials; Breast cancer cells; cancer cell culture; Carbonyldiimidazole; Cell culture; Cell immobilization; Cell Line, Tumor; cell proliferation; Cellular environment; Cellular response; Concentration (process); Concentration of; Contact angle; controlled study; Cytokines; EGF; Electron energy levels; enzyme linked immunosorbent assay; Enzyme-Linked Immunosorbent Assay; epidermal growth factor; Epidermal growth factors; Ethylene; Glycols; gold; Gold substrates; human; human cell; Humans; Hydroxyl-terminated; Imidazoles; Immobilization process; Immobilization reaction; immunofluorescence; immunohistochemistry; Immunostaining; Molecular levels; Nanostructured materials; Nanostructured surface; Nanostructured surfaces; New model; Optimization; Phosphorylation; Photoelectron spectroscopy; Polyethylene Glycols; Protein adsorption; protein immobilization; protein interaction; protein phosphorylation; Proteins; Radiolabeling; Radioligand Assay; Reaction conditions; reaction optimization; Receptor, Epidermal Growth Factor; Sams; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; Sulfhydryl Compounds; Surface characterization; Surface functionalization; Surface models; Surface Properties; Water contact angle measurement; X ray photoelectron spectroscopy

Biocompatibility and calcification of bovine pericardium employed for the construction of cardiac bioprostheses treated with different chemical crosslink methods - Jorge-Herrero, E.; Fonseca, C.; Barge, A.P.; Turnay, J.; Olmo, N.; Fernández, P.; Lizarbe, M.A.; García Páez, J.M. (Artificial OrgansArtif. Organs, 2010)
The use of biological materials in the construction of bioprostheses requires the application of different chemical procedures to improve the durability of the material without producing any undesirable effects. A number of crosslinking methods have been tested in biological tissues composed mainly of collagen. The aim of this study was to evaluate the in vitro biocompatibility, the mechanical properties, and in vivo calcification of chemically modified bovine pericardium using glutaraldehyde acetals (GAAs) in comparison with glutaraldehyde (GA) treatment. Homsy's tests showed that the most cytotoxic treatment is GA whereas GAA treatments showed lower cytotoxicity. Regarding the mechanical properties of the modified materials, no significant differences in stress at rupture were detected among the different treatments. Zeta-Potential showed higher negative values for GA treatment (-4.9 ± 0.6 mV) compared with GAA-0.625% (-2.2 ± 0.5 mV) and GAA-1% (-2.2 ± 0.4 mV), which presented values similar to native tissue. Similar results were obtained for calcium permeability coefficients which showed the highest values for GA treatment (0.12 ± 0.02 mm 2/min), being significantly lower for GAA treatments or non-crosslinked pericardium. These results confirmed the higher propensity of the GA-treated tissues for attraction of calcium cations and were in good agreement with the calcification degree obtained after 60 days implantation into young rats, which was significantly higher for the GA group (22.70 ± 20.80 mg/g dry tissue) compared with GAA-0.625% and GAA-1% groups (0.49 ± 0.28 mg/g dry tissue and 3.51 ± 3.27 mg/g dry tissue, respectively; P < 0.001). In conclusion, GAA treatments can be considered a promising alternative to GA treatment. © 2010, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: acetal derivative; animal cell; animal experiment; animal tissue; Animals; article; Biocompatibility; Bioprostheses; Bioprosthesis; Bovinae; Calcification; Calcification, Physiologic; Calcium; cation; Cattle; Chemical modification; controlled study; Cross-Linking Reagents; Crosslinking; Cytotoxicity; Glutaral; glutaraldehyde; heart valve bioprosthesis; Heart, Artificial; in vitro study; materials testing; mechanical stress; nonhuman; pericardium; permeability; priority journal; rat; Rats; Rattus; Subcutaneous implantation; Tissue engineering; Zeta potential

Cell nuclei and cytoplasm joint segmentation using the sliding band filter - Quelhas, P.; Marcuzzo, M.; Mendonça, A.M.; Campilho, A. (IEEE Transactions on Medical ImagingIEEE Trans. Med. Imaging, 2010)
Microscopy cell image analysis is a fundamental tool for biological research. In particular, multivariate fluorescence microscopy is used to observe different aspects of cells in cultures. It is still common practice to perform analysis tasks by visual inspection of individual cells which is time consuming, exhausting and prone to induce subjective bias. This makes automatic cell image analysis essential for large scale, objective studies of cell cultures. Traditionally the task of automatic cell analysis is approached through the use of image segmentation methods for extraction of cells' locations and shapes. Image segmentation, although fundamental, is neither an easy task in computer vision nor is it robust to image quality changes. This makes image segmentation for cell detection semi-automated requiring frequent tuning of parameters. We introduce a new approach for cell detection and shape estimation in multivariate images based on the sliding band filter (SBF). This filter's design makes it adequate to detect overall convex shapes and as such it performs well for cell detection. Furthermore, the parameters involved are intuitive as they are directly related to the expected cell size. Using the SBF filter we detect cells' nucleus and cytoplasm location and shapes. Based on the assumption that each cell has the same approximate shape center in both nuclei and cytoplasm fluorescence channels, we guide cytoplasm shape estimation by the nuclear detections improving performance and reducing errors. Then we validate cell detection by gathering evidence from nuclei and cytoplasm channels. Additionally, we include overlap correction and shape regularization steps which further improve the estimated cell shapes. The approach is evaluated using two datasets with different types of data: a 20 images benchmark set of simulated cell culture images, containing 1000 simulated cells; a 16 images Drosophila melanogaster Kc167 dataset containing 1255 cells, stained for DNA and actin. Both image datasets present a difficult problem due to the high variability of cell shapes and frequent cluster overlap between cells. On the Drosophila dataset our approach achieved a precision/recall of 95%/69% and 82%/90% for nuclei and cytoplasm detection respectively and an overall accuracy of 76%. © 2010 IEEE.
Keywords: actin; Actins; animal; Animals; article; Band filters; Biological research; cell aggregation; Cell analysis; Cell culture; Cell detection; Cell images; cell nucleus; Cell segmentation; Cell Shape; Cell shapes; Cell size; Cells; chemistry; Computer vision; Convergence filters; Convex shapes; cytoplasm; Data sets; Databases, Factual; Digital image storage; DNA; Drosophila melanogaster; factual database; Fluorescence; Fluorescence microscopy; Fundamental tools; High variability; Image analysis; Image datasets; image processing; image processing in biology; Image Processing, Computer-Assisted; Image quality; Image segmentation; Imaging systems; Improving performance; Individual cells; Joint segmentation; Location; methodology; Microscopy, Fluorescence; Multivariate analysis; multivariate image processing; New approaches; Nuclear detection; Overlap correction; reproducibility; Reproducibility of Results; Semi-automated; Shape estimation; Shape regularization; ultrastructure; Visual communication; Visual inspection

Ceramics for dental restorations - an introduction - Santander, S.A.; Vargas, A.P.; Escobar, J.S.; Monteiro, F.J.; Tamayo, L.F.R. (Una perspectiva de las cerámicas para restauraciones dentalesDYNADYNA, 2010)
Dental ceramics are the preferred materials for oral restoration due to some characteristics, such as adequate esthetics, high fracture strength and chemical stability. Currently, dental professionals have a large amount of ceramic systems to choose from, all of them having small differences regarding their chemistry, processing temperatures, mechanical strength and clinical applications. These differences lead to classification systems that are difficult to understand by professionals outside the dental field. The aim of this work is to review the current dental ceramic systems and present them from a compositional perspective to assure the comprehension of these materials by professionals who belong to the Biomedical Engineering field. A great effort was made to avoid classification methods imposed by manufacturers and to obtain a quick compilation of available information from the literature allowing the reader to have a general view of the stateoftheart on dental ceramics.
Keywords: Ceramic systems; Feldspathic porcelain; Glassceramics; Leucite; Mechanical and physical properties; Zirconium oxide

Characterization of polymeric solutions as injectable vehicles for hydroxyapatite microspheres - Oliveira, S.M.; Almeida, I.F.; Costa, P.C.; Barrias, C.C.; Ferreira, M.R.P.; Bahia, M.F.; Barbosa, M.A. (AAPS PharmSciTechAAPS PharmSciTech, 2010)
A polymeric solution and a reinforcement phase can work as an injectable material to fill up bone defects. However, the properties of the solution should be suitable to enable the transport of that extra phase. Additionally, the use of biocompatible materials is a requirement for tissue regeneration. Thus, we intended to optimize a biocompatible polymeric solution able to carry hydroxyapatite microspheres into bone defects using an orthopedic injectable device. To achieve that goal, polymers usually regarded as biocompatible were selected, namely sodium carboxymethylcellulose, hydroxypropylmethylcellulose, and Na-alginate (ALG). The rheological properties of the polymeric solutions at different concentrations were assessed by viscosimetry before and after moist heat sterilization. In order to correlate rheological properties with injectability, solutions were tested using an orthopedic device applied for minimal invasive surgeries. Among the three polymers, ALG solutions presented the most suitable properties for our goal and a non-sterile ALG 6% solution was successfully used to perform preliminary injection tests of hydroxyapatite microspheres. Sterile ALG 7.25% solution was found to closely match non-sterile ALG 6% properties and it was selected as the optimal vehicle. Finally, sterile ALG 7.25% physical stability was studied at different temperatures over a 3-month period. It was observed that its rheological properties presented minor changes when stored at 25°C or at 4°C. © 2010 American Association of Pharmaceutical Scientists.
Keywords: Alginate; alginic acid; article; Biocompatibility; Biocompatible Materials; Capsules; Carboxymethylcellulose; Drug Compounding; Durapatite; Excipients; hydroxyapatite; Hydroxypropylmethylcellulose; Injectability; injection; Injections; instrument sterilization; microsphere; Microspheres; minimally invasive surgery; molecular weight; orthopedic equipment; Polymers; priority journal; Solutions; Vehicles; viscometry

Characterization of two DLC coatings for joint prosthesis: The role of albumin on the tribological behavior - Carapeto, A.P.; Serro, A.P.; Nunes, B.M.F.; Martins, M.C.L.; Todorovic, S.; Duarte, M.T.; André, V.; Colaço, R.; Saramago, B. (Surface and Coatings TechnologySurf. Coat. Technol., 2010)
A commonly used strategy for reduction of wear and friction of the sliding surfaces in prosthetic pairs is the use of hard coatings. DLCs (diamond like carbons) offer a promising solution, because these coatings, already used in other biomedical applications, exhibit a unique combination of chemical inertness, mechanical and tribological properties. In the present work we investigated the role of albumin, the most abundant protein in the periprosthetic fluid, on the tribological behavior of two DLCs with different compositions, against ultra-high molecular weight polyethylene (UHMWPE). The results are compared with those obtained with uncoated stainless steel surfaces. We have characterized the coatings by atomic force microscopy, X-ray diffraction, Raman spectroscopy, ultramicrohardness and wettability measurements. The adsorption of albumin onto the surfaces was investigated by ellipsometry and using a quartz crystal microbalance. Both DLCs adsorb a larger amount of protein than stainless steel. The tribological tests were performed in microtribometer aiming for a deeper understanding of the tribological mechanisms which occur at the submicrometric contact scale. Results showed no significant differences between the tribological behavior of the two coatings. Under the tested conditions, the tribological performance does not improve significantly with the application of the DLCs. Moreover, the presence of albumin on the lubricant leads to higher friction of the polymer against all counterfaces. This effect was attributed to the formation of bridges between the two sliding surfaces by the denaturated protein. The significant differences in the adsorbed amounts of protein onto the stainless steel and the two types of DLCs did not affect considerably the tribological behavior of these materials. © 2010 Elsevier B.V.
Keywords: Adsorbed amount; Adsorption; Albumin adsorption; Atomic force microscopy; Atomic spectroscopy; Biomedical applications; Chemical inertness; Corrosion resistant alloys; Diamond like carbon; DLC coatings; Friction; Hard coatings; Joint prostheses; Mechanical and tribological properties; Mechanical properties; Microtribology; Microtribometer; Nonmetallic matrix composites; Oxide minerals; Polyethylenes; Proteins; Quartz; Raman spectroscopy; Scanning electron microscopy; Sliding surface; Stainless steel; Stainless steel surface; Steel corrosion; Surfaces; Tribological behaviors; Tribological mechanism; Tribological performance; Tribological tests; Tribology; UHMW-PE; UHMWPE; Ultramicrohardness; Wear and friction; Wettability measurements; X ray diffraction

Chitosan-based gene delivery vectors targeted to the peripheral nervous system - Oliveira, H.; Pires, L.R.; Fernandez, R.; Martins, M.C.L.; Simões, S.; Pêgo, A.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
A non-toxic, targeted, simple and efficient system that can specifically transfect peripheral sensorial neurons can pave the way towards the development of new therapeutics for the treatment of peripheral neuropathies. In this study chitosan (CH), a biodegradable polymer, was used as the starting material in the design of a multicomponent vector targeted to the peripheral nervous system (PNS). Polycation-DNA complexes were optimized using imidazole-and thiol-grafted CH (CHimiSH), in order to increase transfection efficiency and allow the formation of ligand conjugated nanocomplexes, respectively. The 50 kDa non-toxic fragment from the tetanus toxin (HC), shown to interact specifically with peripheral neurons and undergo retrograde transport, was grafted to the binary complex via a bi-functional poly(ethylene glycol) (HC-PEG) reactive for the thiol moieties present in the complex surface. The targeting of the developed nanocomplexes was assessed by means of internalization and transfection studies in the ND7/23 (neuronal) vs. NIH 3T3 (fibroblast) cell lines. Targeted transfection was further confirmed in dorsal root ganglion dissociated primary cultures. A versatile, multi-component nanoparticle system that successfully targets and transfects neuronal cell lines, as well as dorsal root ganglia (DRG) primary neuron cultures was obtained for the 1.0 (w/w) HC-PEG/DNA formulation. © 2010 Wiley Periodicals, Inc.
Keywords: animal cell; Animals; article; Binary complexes; Biodegradable polymers; Carbohydrate Conformation; Carbohydrate Sequence; Cations; Cell culture; Cell lines; cell population; Cells, Cultured; Chitin; chitosan; Complex surface; DNA; DNA complex; Dorsal root ganglia; Efficient systems; embryo; Ethylene; Ethylene Glycol; Female; Ganglia, Spinal; Gene delivery; gene delivery system; Gene delivery vectors; Gene therapy; Gene transfer; Gene Transfer Techniques; genetic transfection; Genetic Vectors; Grafting (chemical); Humans; imidazole; macrogol; materials testing; Mice; Molecular Sequence Data; Molecular Structure; mouse; Multicomponents; Nanocomplexes; Nanoparticle systems; nanoparticles; nerve cell culture; Neuron culture; Neuronal cell; NIH 3T3 Cells; nonhuman; Nontoxic fragment of tetanus toxin; Peripheral nervous system; Peripheral neuropathy; Polycations; Polyethylene Glycols; Polyethylene oxides; Pregnancy; Primary culture; rat; Rats; Rats, Wistar; spinal ganglion; Starting materials; Targeted; Tetanus toxin; Toxic materials; Transfection; Transfection efficiency

Chitosan/siRNA nanoparticles biofunctionalize nerve implants and enable neurite outgrowth - Mittnacht, U.; Hartmann, H.; Hein, S.; Oliveira, H.; Dong, M.; Pêgo, A.P.; Kjems, J.; Howard, K.A.; Schlosshauer, B. (Nano LettersNano Lett., 2010)
Microstructured 20 μm thick polymer filaments used as nerve implants were loaded with chitosan/siRNA nanoparticles to promote nerve regeneration and ensure local delivery of nanotherapeutics. The stable nanoparticles were rapidly internalized by cells and did not affect cell viability. Target mRNA was successfully reduced by 65-75% and neurite outgrowth was enhanced even in an inhibitory environment. This work, thus, supports the application of nanobiofunctionalized implants as a novel approach for spinal cord and nerve repair. © 2010 American Chemical Society.
Keywords: animal; Animals; article; Cell Line; cell viability; chemistry; Chitin; chitosan; cytology; Drug delivery; genetic transfection; genetics; Local delivery; metabolism; Microstructured; nanobiofunctionalized implants; nanoparticle; nanoparticles; nerve cell; nerve regeneration; Nerve repair; neurite; Neurite outgrowth; Neurites; Neurons; Polymer filaments; Prostheses and Implants; prostheses and orthoses; rhoA GTP-Binding Protein; RhoA guanine nucleotide binding protein; RNA; RNA, Small Interfering; siRNA; small interfering RNA; Spinal cords; Transfection; ultrastructure

Comparison of a computer system evaluation of intrapartum cardiotocographic events and a consensus of clinicians. - Costa, M.A.; Ayres-de-Campos, D.; Machado, A.P.; Santos, C.C.; Bernardes, J. (Journal of perinatal medicineJ Perinat Med, 2010)
AIMS: To compare between computer analysis of intrapartum cardiotocography (CTG) features by the Omniview-SisPorto 3.5 and a consensus of clinicians. METHODS: Agreement study using 50 consecutively acquired tracings (206 h of signals) with >60 min duration, <10% signal loss and recorded in labor at term by internal fetal heart rate (FHR) monitoring. Tracings were divided into 10-min segments and independently analyzed by three experienced clinicians, in order to estimate the FHR baseline and identify periodic events. A consensus was reached using a three round Delphi procedure. Results were compared with the analysis provided by the Omniview-SisPorto 3.5 system. RESULTS: For baseline estimation, agreement between the computer and the consensus was high [intraclass correlation coefficient (ICC)=0.85; 95% confidence interval (CI) 0.46-0.93], with a mean difference of 3.7 bpm (limits of agreement -4.4-11.9 bpm), and 99% of differences under 15 bpm. A concordant identification was observed in 71% of accelerations (95% CI: 69%-73%), 68% of decelerations (95% CI: 66%-70%), and 87% of uterine contractions (95% CI: 85%-89%). CONCLUSIONS: A high agreement was observed between the Omniview-SisPorto 3.5 and a consensus of clinicians in evaluation of intrapartum CTG baseline, accelerations, decelerations and uterine contractions.
Keywords: algorithm; Algorithms; article; Cardiotocography; comparative study; computer assisted diagnosis; Diagnosis, Computer-Assisted; Female; Fetal Heart; Fetal monitoring; fetus heart; fetus monitoring; human; Humans; instrumentation; methodology; physician; Physicians; physiology; Pregnancy

De novo expression of CD44 variants in sporadic and hereditary gastric cancer - Da Cunha, C.B.; Oliveira, C.; Wen, X.; Gomes, B.; Sousa, S.; Suriano, G.; Grellier, M.; Huntsman, D.G.; Carneiro, F.; Granja, P.L.; Seruca, R. (Laboratory InvestigationLab. Invest., 2010)
CD44 is the major ubiquitously expressed cell surface receptor for hyaluronate. The CD44 gene encodes several protein isoforms due to extensive alternative splicing and post-translational modifications. Some of these CD44 variable isoforms have been foreseen as key players in malignant transformation and their expression is highly restricted and highly specific, unlike the canonical CD44 standard isoform. In this study, we aimed at dissecting the mRNA splicing pattern of CD44 in normal stomach and gastric cancer (GC) cell lines (n9) using cloning and quantitative mRNA amplification assays. Moreover, we assessed the RNA levels and protein expression pattern of relevant splicing forms in distinct premalignant and malignant gastric lesions (sporadic (n43) and hereditary (n3) forms) using real-time RT-PCR and immunohistochemistry. We also explored the association of CD44 and E-cadherin expression by immunohistochemistry, as E-cadherin has a pivotal functional role in GC. We established the pattern of CD44 variant forms in normal stomach and gastric malignancy. We observed that although exon v6-containing isoforms were rarely expressed in normal gastric mucosa, they became increasingly expressed both in gastric premalignant (hyperplastic polyps, complete and incomplete intestinal metaplasia, low- and high-grade dysplasia) and malignant lesions (cell lines derived from GCs, primary sporadic GCs and hereditary diffuse GCs (HDGCs)). Moreover, we verified that whenever E-cadherin expression was absent, exon v6-containing CD44 isoforms were overexpressed. The lack of expression of CD44 isoforms containing exon v6 in the surface and foveolar epithelia of normal stomach and, its de novo expression in premalignant, as well as in sporadic and hereditary malignant lesions of the stomach, pinpoint CD44 v6-containg isoforms as potential biomarkers for early transformation of the gastric mucosa. Further, our results raise the hypothesis of using CD44v6 as a marker of early invasive intramucosal carcinoma in HDGC CDH1 mutation carriers that lack CDH1 expression in their tumors. © 2010 USCAP, Inc All rights reserved.
Keywords: Alternative Splicing; Antigens, CD44; article; Cadherins; CD44; CD44v6; CD44v6 antigen; CD44v7 antigen; Cell Line, Tumor; clinical article; controlled study; E-cadherin; familial cancer; Gastric Mucosa; Germ-Line Mutation; HDGC; Hermes antigen; human; human tissue; Humans; immunohistochemistry; intestine metaplasia; messenger RNA; Neoplasm Metastasis; priority journal; protein expression; real time polymerase chain reaction; reverse transcription polymerase chain reaction; RNA splicing; RNA, Messenger; splicing; sporadic GC; stomach; stomach cancer; stomach mucosa; Stomach Neoplasms; stomach polyp; tumor marker; unclassified drug; uvomorulin

Dynamic cell-cell interactions between cord blood haematopoietic progenitors and the cellular niche are essential for the expansion of CD34 +, CD34 +CD38 - Da Silva, C.L.; Gonçalves, R.; Dos Santos, F.; Andrade, P.Z.; Almeida-Porada, G.; Cabral, J.M.S. (Journal of Tissue Engineering and Regenerative MedicineJ. Tissue Eng. Regenerative Med., 2010)
Most clinical applications of haematopoietic stem/progenitor cells (HSCs) would benefit from their ex vivo expansion to obtain a therapeutically significant amount of cells from the available donor samples. We studied the impact of cellular interactions between umbilical cord blood (UCB) haematopoietic cells and bone marrow (BM)-derived mesenchymal stem cells (MSCs) on the ex vivo expansion and differentiative potential of UCB CD34 +-enriched cells. UCB cells were cultured: (a) directly in contact with BM MSC-derived stromal layers (contact); (b) separated by a microporous membrane (non-contact); or (c) without stroma (no stroma). Highly dynamic culture events occurred in HSC-MSC co-cultures, involving cell-cell interactions, which preceded HSC expansion. Throughout the time in culture [18 days], total cell expansion was significantly higher in contact (fold increase of 280 ± 37 at day 18) compared to non-contact (85 ± 25). No significant cell expansion was observed in stroma-free cultures. CD34 + cell expansion was also clearly favoured by direct contact with BM MSCs (35 ± 5- and 7 ± 3-fold increases at day 18 for contact and non-contact, respectively). Moreover, a higher percentage of CD34 +CD38
Keywords: Antigens, CD34; Antigens, CD38; Antigens, CD7; article; Bone marrow microenvironment; CD34 antigen; CD38 antigen; CD7 antigen; cell adhesion; Cell Communication; cell contact; Cell culture; cell differentiation; cell interaction; cell proliferation; Cells, Cultured; cellular distribution; clonogenic assay; coculture; Coculture Techniques; Colony-Forming Units Assay; controlled study; Ex vivo expansion; ex vivo study; Fetal Blood; flow cytometry; Haematopoietic stem/progenitor cells; hematopoietic stem cell; Hematopoietic Stem Cells; human; human cell; Humans; Lymphocytes; lymphoid cell; Mesenchymal stem cell; Mesenchymal Stem Cells; Microscopy, Electron, Scanning; phenotype; priority journal; Scanning electron microscopy; somatic gene therapy; stem cell expansion; Stem Cell Niche; stroma cell; Suspensions; umbilical cord blood

Early spreading and propagation of human bone marrow stem cells on isotropic and anisotropic topographies of silica thin films produced via microstamping - Pelaez-Vargas, A.; Gallego-Perez, D.; Ferrell, N.; Fernandes, M.H.; Hansford, D.; Monteiro, F.J. (Microscopy and MicroanalysisMicrosc. Microanal., 2010)
While there has been rapid development of microfabrication techniques to produce high-resolution surface modifications on a variety of materials in the last decade, there is still a strong need to produce novel alternatives to induce guided tissue regeneration on dental implants. High-resolution microscopy provides qualitative and quantitative techniques to study cellular guidance in the first stages of cell-material interactions. The purposes of this work were (1) to produce and characterize the surface topography of isotropic and anisotropic microfabricated silica thin films obtained by sol-gel processing, and (2) to compare the in vitro biological behavior of human bone marrow stem cells on these surfaces at early stages of adhesion and propagation. The results confirmed that a microstamping technique can be used to produce isotropic and anisotropic micropatterned silica coatings. Atomic force microscopy analysis was an adequate methodology to study in the same specimen the sintering derived contraction of the microfabricated coatings, using images obtained before and after thermal cycle. Hard micropatterned coatings induced a modulation in the early and late adhesion stages of cell-material and cell-cell interactions in a geometry-dependent manner (i.e., isotropic versus anisotropic), as it was clearly determined, using scanning electron and fluorescence microscopies. © Microscopy Society of America 2010.
Keywords: AFM; Atomic force microscopy; audiovisual equipment; cell adhesion and proliferation; Cell Culture Techniques; cell proliferation; conference paper; culture technique; cytology; Fluorescence microscopy; Guided tissue regeneration; human; Humans; Microscopy, Atomic Force; Microscopy, Electron, Scanning; Microscopy, Fluorescence; microstamping; Motion Pictures as Topic; myeloid progenitor cell; Myeloid Progenitor Cells; Scanning electron microscopy; SEM; silica sol-gel films; silicon dioxide; Soft lithography; Surface Properties; surface property; Tissue regeneration; tissue scaffold; Tissue Scaffolds

The effect of immobilization of thrombin inhibitors onto self-assembled monolayers on the adsorption and activity of thrombin - Freitas, S.C.; Barbosa, M.A.; Martins, M.C.L. (BiomaterialsBiomaterials, 2010)
Thrombus formation is the major problem associated with biomaterials for blood contact medical devices. The immobilization of inhibitors to thrombin, a serine protease that plays a central role on the coagulation system, on the surface of biomaterials should be a good strategy to avoid blood clotting and increase their hemocompatibility. The aim of this work is the design of a nanostructured surface with capacity to adsorb and inactivate thrombin. The pentapeptide sequence d-Phenylalanine-Proline-Arginine-Proline-Glycine (fPRPG), that was described as a thrombin inhibitor, was immobilized onto tetra(ethylene glycol) terminated self-assembled monolayers (EG4-SAMs). Surface containing different amounts of fPRPG were prepared using different concentrations of N,N′-Carbonyldiimidazole (CDI) during immobilization. The efficiency of fPRPG immobilization was followed using ellipsometry, contact angle measurements, Infrared reflection absorption spectroscopy (IRRAS) and X-ray photoelectron spectroscopy (XPS). Thrombin adsorption was quantified using radiolabelled thrombin and its activity in solution and after adsorption on the developed surfaces was assessed using a chromogenic assay. It was found that, although the immobilization of fPRPG on to EG4-SAMs does not increase its selectivity to thrombin, the activity of the adsorbed thrombin was inhibited in a peptide concentration dependent way. We concluded that SAMs with fPRPG immobilized in high amounts can be used as thrombin-inhibitor surfaces, which is a good step on the development of new surfaces for blood contact devices. © 2010 Elsevier Ltd. All rights reserved.
Keywords: Absorption spectroscopy; Adsorption; adsorption kinetics; Albumins; Amino Acid Sequence; Amino acids; Angle measurement; article; Biomaterials; Blood; Blood clotting; Blood contact; Carbonyldiimidazole; Coagulation; Coagulation system; concentration (parameters); Concentration-dependent; Contact angle; D-phenylalanine; ellipsometry; Ethylene; Ethylene Glycol; ethylene glycol derivative; gold; Hemocompatibility; Humans; imidazole derivative; Immobilized Proteins; Infrared reflection absorption spectroscopy; infrared spectroscopy; Iodine Radioisotopes; isotope labeling; Medical Devices; monolayer culture; nanoanalysis; Nanostructured surface; peptide; Peptide immobilization; Peptides; phenylalanylprolylarginylprolylglycine; Phosphatases; priority journal; Protein adsorption; protein assembly; protein function; protein immobilization; quantitative study; Sams; Self assembled monolayers; Self-assembled monolayers; Serine protease; Solubility; Solutions; Spectroscopy, Fourier Transform Infrared; Surface functionalization; Surface Properties; Tetra; tetra(ethylene glycol); Thrombin; thrombin inhibitor; Thrombin inhibitors; Thrombus formation; unclassified drug; X ray photoelectron spectroscopy

Effect of nanoscale topography on fibronectin adsorption, focal adhesion size and matrix organisation - González-García, C.; Sousa, S.R.; Moratal, D.; Rico, P.; Salmerón-Sánchez, M. (Colloids and Surfaces B: BiointerfacesColloids Surf. B Biointerfaces, 2010)
Phase separation of PLLA/PS (50/50, w/w) solutions during a spin-casting process gives rise to well-defined nanotopographies of 14, 29 and 45. nm deep pits depending on the concentration of the solution. Their influence on the biological activity of fibronectin (FN) was investigated. FN adsorption was quantified by radiolabelling the protein. The amount of adsorbed FN was higher on the 14. nm deep pit nanotopography than on the other two surfaces. FN distribution between valleys and peaks was investigated by AFM combined with image analysis. FN tends to adsorb preferentially on the valleys of the nanotopography only for the 14. nm system and when adsorbed from solutions of concentration lower than 10μg/ml. Higher concentration of the FN solution leads to evenly distribution of the protein throughout the surface; moreover, there is no difference in the distribution of the protein between valleys and peaks for the other two systems (29 and 45. nm) irrespective of the concentration of the FN solution. The biological activity of the adsorbed protein layer was assessed by investigating MC3T3 osteoblast-like cells adhesion, FN reorganisation and late matrix formation on the different substrates. Even if initial cell adhesion is excellent for every substrate, the size of the focal adhesion plaques increases as the size of the pits in the nanotopography does. This is correlated to FN reorganisation, which only takes places on the 29 and 45. nm deep pits surfaces, where enhanced late matrix production was also found. © 2010 Elsevier B.V.
Keywords: 3T3 Cells; Adhesion; Adsorption; AFM; animal cell; Animals; article; Atomic force microscopy; Bioactivity; Biological activities; biological activity; Casting process; cell adhesion; Cell Line; concentration (parameters); Concentration (process); Concentration of; Deep pit; Different substrates; Electric currents; extracellular matrix; Fibronectin; Fibronectin adsorption; Fibronectins; focal adhesion; Focal adhesion plaques; Focal adhesions; Humans; Image analysis; Image Processing, Computer-Assisted; isotope labeling; Landforms; matrix; Matrix formation; Mice; Microscopy, Atomic Force; nanomaterial; Nanoscale topography; Nanotechnology; Nanotopographies; Nanotopography; nonhuman; osteoblast; Osteoblast-like cells; Osteoblasts; Phase separation; polylactic acid; polystyrene; priority journal; Protein adsorption; Protein layers; protein localization; Proteins; Radiolabelling; Reorganisation; Substrates; Surface Properties

Evaluation of the effect of the degree of acetylation on the inflammatory response to 3D porous chitosan scaffolds - Barbosa, J.N.; Amaral, I.F.; Águas, A.P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
The effect of the degree of acetylation (DA) of 3D chitosan (Ch) scaffolds on the inflammatory reaction was investigated. Chitosan porous scaffolds with DAs of 4 and 15% were implanted using a subcutaneous air-pouch model of inflammation. The initial acute inflammatory response was evaluated 24 and 48 h after implantation. To characterize the initial response, the recruitment and adhesion of inflammatory cells to the implant site was studied. The fibrous capsule formation and the infiltration of inflammatory cells within the scaffolds were evaluated for longer implantation times (2 and 4 weeks). Chitosan with DA 15% attracted the highest number of leukocytes to the implant site. High numbers of adherent inflammatory cells were also observed in this material. For longer implantation periods Ch scaffolds with a DA of 15% induced the formation of a thick fibrous capsule and a high infiltration of inflammatory cells within the scaffold. Our results indicate that the biological response to implanted Ch scaffolds was influenced by the DA. Chitosan with a DA of 15% induce a more intense inflammatory response when compared with DA 4% Ch. Because inflammation and healing are interrelated, this result may provide clues for the relative importance of acetyl and amine functional groups in tissue repair and regeneration. © 2009 Wiley Periodicals, Inc.
Keywords: acetic acid derivative; Acetylation; Acute inflammatory response; amine; Amine functional groups; animal cell; animal experiment; animal tissue; Animals; article; Biological materials; Biological response; Biomaterials; cell adhesion; cell infiltration; Chitin; chitosan; Chitosan scaffold; Degree of acetylation; Fibrous capsule; Fibrous capsule formation; freeze drying; Functional groups; Hydrogels; implant; implantation; Implantation periods; Implants, Experimental; Inflammation; Inflammatory cells; Inflammatory reaction; Inflammatory response; leukocyte count; Leukocytes; male; Mice; Mice, Inbred BALB C; Microscopy, Electron, Scanning; mouse; nonhuman; Pathology; porosity; Porous scaffold; Prosthesis Implantation; Relative importance; Scaffolds; Subcutaneous Tissue; Surface Properties; Three dimensional; Tissue regeneration; tissue repair; Tissue response; Tissue responses; Tissue Scaffolds

Functionalization of poly(amidoamine) dendrimers with hydrophobic chains for improved gene delivery in mesenchymal stem cells - Santos, J.L.; Oliveira, H.; Pandita, D.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (Journal of Controlled ReleaseJ. Control. Release, 2010)
A new family of gene delivery vectors is synthesized consisting of a medium-size generation PAMAM dendrimer (generation 5, with amine termini) core randomly linked at the periphery to hydrophobic chains that vary in length (12 to 16 carbon alkyl chains) and number (from 4.2 to 9.7 in average). The idea subjacent to the present work is to join the advantages of the cationic nature of the dendrimer with the capacity of lipids to interact with biological membranes. Unlike other amphiphilic systems designed for the same purpose, where the hydrophobic and hydrophilic moieties coexist in opposite sides, the present vectors have a hydrophilic interior and a hydrophobic corona. The vectors are characterized in respect to their ability to neutralize, bind and compact plasmid DNA (pDNA). The complexes formed between the vectors and pDNA are analyzed concerning their size, ζ-potential, resistance to serum nucleases, capacity of being internalized by cells and transfection efficiency. These new vectors show a remarkable capacity for mediating the internalization of pDNA with minimum cytotoxicity, being this effect positively correlated with the -CH 2- content present in the hydrophobic corona. Gene expression in MSCs, a cell type with relevancy in the regenerative medicine clinical context, is also enhanced using the new vectors but, in this case, the higher efficiency is shown by the vectors containing the smallest hydrophobic chains. © 2010 Elsevier B.V.
Keywords: amphophile; animal cell; animal experiment; article; Biological membranes; Biomedical applications; cation; Cations; Cell culture; cell membrane transport; cell type; Cellular uptake; controlled study; Cytotoxicity; dendrimer; Dendrimers; DNA; DNA binding; Dyes; Functional polymers; Gene delivery; gene delivery system; gene expression; Gene therapy; Gene transfer; Gene Transfer Techniques; gene vector; Genes; genetic transfection; Genetic Vectors; Humans; Hydrocarbons; hydrophilicity; hydrophobicity; internalization; lipid; Lipids; male; Mesenchymal stem cell; Mesenchymal Stem Cells; nonhuman; nuclease; Nucleic acids; plasmid DNA; Plasmids; Poly(amidoamine) dendrimers; polyamidoamine; Polyamidoamine dendrimers; priority journal; rat; Regenerative Medicine; Stem cells; Transfection; Vectors; Zeta potential

Heparinized hydroxyapatite/collagen three-dimensional scaffolds for tissue engineering - Teixeira, S.; Yang, L.; Dijkstra, P.J.; Ferraz, M.P.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2010)
Currently, in bone tissue engineering research, the development of appropriate biomaterials for the regeneration of bony tissues is a major concern. Bone tissue is composed of a structural protein, collagen type I, on which calcium phosphate crystals are enclosed. For tissue engineering, one of the most applied strategies consists on the development and application of three dimensional porous scaffolds with similar composition to the bone. In this way, they can provide a physical support for cell attachment, proliferation, nutrient transport and new bone tissue infiltration. Hydroxyapatite is a calcium phosphate with a similar composition of bone and widely applied in several medical/dentistry fields. Therefore, in this study, hydroxyapatite three dimensional porous scaffolds were produced using the polymer replication method. Next, the porous scaffolds were homogeneously coated with a film of collagen type I by applying vacuum force. Yet, due to collagen degradability properties, it was necessary to perform an adequate crosslinking method. As a result, N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) was employed as an efficient and non-toxic crosslinking method in this research. The composites were characterized by means of SEM, DSC and TNBS. Furthermore, heparin was incorporated in order to accomplish sustained delivery of a growth factor of interest namely, bone morphogenetic proteins (BMP-2). BMP-2 binding and release of non-heparinized and heparinized scaffolds was evaluated at specific time points. The incorporation of heparin leads to a reduced initial burst phase when compared to the non heparinized materials. The results show a beneficial effect with the incorporation of heparin and its potential as a localized drug delivery system for the sustained release of growth factors. © 2010 Springer Science+Business Media, LLC.
Keywords: Achilles Tendon; Animals; Apatite; article; Beneficial effects; Binding and release; Biocompatible Materials; Biological materials; Biomaterials; Bone; Bone and Bones; bone morphogenetic protein 2; Bone morphogenetic proteins; Bone Substitutes; bone tissue; Bone tissue engineering; Bony tissue; Calcium; calcium phosphate; Calcium phosphate crystals; Cattle; Cell attachments; Collagen; collagen degradation; collagen type 1; Collagen type I; controlled study; cross linking; Cross-Linking Reagents; Crosslinking; cyanamide; Degradability; differential scanning calorimetry; Drug delivery; drug delivery system; Durapatite; Grafts; Growth factor; heparin; Hydrogels; hydroxyapatite; Microscopy, Electron, Scanning; n (3 dimethyllaminopropyl) n' ethylcarbodiimide; n hydroxysuccinimide; N-hydroxysuccinimide; Nutrient transport; Peptides; polymer; Polymer replication; Polymers; Polysaccharides; porosity; Porous scaffold; priority journal; protein binding; Scaffolds; Scanning electron microscopy; SEM; Specific time; Structural proteins; Sustained release; Three dimensional; Three-dimensional porous scaffolds; Three-dimensional scaffolds; Tissue engineering; tissue scaffold; Tissue Scaffolds; trinitrobenzenesulfonic acid; unclassified drug; vacuum; Vacuum force

Immobilization of human mesenchymal stem cells within RGD-grafted alginate microspheres and assessment of their angiogenic potential - Bidarra, S.J.; Barrias, C.C.; Barbosa, M.A.; Soares, R.; Granja, P.L. (BiomacromoleculesBiomacromolecules, 2010)
In this work, human mesenchymal stem cells (hMSC) immobilized in RGD-coupled alginate microspheres, with a binary composition of high and low molecular weight alginate, were investigated. Cells immobilized within RGD-alginate microspheres (during 21 days) showed metabolic activity, with an overall viability higher than 90%, short cell extensions, and, when induced, they were able to differentiate into the osteogenic lineage. In osteogenic conditions (comparing to basal conditions), immobilized cells presented alkaline phosphatase (ALP) activity and an upregulation of ALP, collagen type I, and Runx 2 expression. Moreover, mineralization was also detected in immobilized cells under osteogenic stimulus. In addition, it was demonstrated for the first time that MSCs immobilized in this 3D matrix were able to enhance the ability of neighboring endothelial cells to form tubelike structures. Overall, these findings represent a step forward in the development of injectable stem cell carriers for bone tissue engineering. © 2010 American Chemical Society.
Keywords: Alginate; Alginates; alginic acid; alkaline phosphatase; Alkaline phosphatase activity; angiogenesis; arginylglycylaspartic acid; article; Basal conditions; Base Sequence; Binary composition; bone development; Bone tissue engineering; Cell culture; cell differentiation; Cell extension; Cell immobilization; cell metabolism; cell structure; cell viability; collagen type 1; Collagen type I; controlled study; DNA Primers; Endothelial Cells; endothelium cell; enzyme activity; human; human cell; Human mesenchymal stem cells; Humans; immobilized cell; Immobilized cells; Low molecular weight; matrix; Mesenchymal stem cell; Mesenchymal Stem Cells; Metabolic activity; Microscopy, Electron, Scanning; microsphere; Microspheres; molecular weight; Neovascularization, Physiologic; nucleotide sequence; Oligopeptides; osteoblast; Osteogenic; Phosphatases; priority journal; protein expression; quantitative analysis; Reverse Transcriptase Polymerase Chain Reaction; stem cell; Stem cells; three dimensional imaging; Tissue engineering; transcription factor RUNX2; umbilical vein; Up-regulation; upregulation

An improved collagen scaffold for skeletal regeneration - Oliveira, S.M.; Ringshia, R.A.; Legeros, R.Z.; Clark, E.; Yost, M.J.; Terracio, L.; Teixeira, C.C. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
Bone repair and regeneration is one of the most extensively studied areas in the field of tissue engineering. All of the current tissue engineering approaches to create bone focus on intramembranous ossification, ignoring the other mechanism of bone formation, endochondral ossification. We propose to create a transient cartilage template in vitro, which could serve as an intermediate for bone formation by the endochondral mechanism once implanted in vivo. The goals of the study are (1) to prepare and characterize type I collagen sponges as a scaffold for the cartilage template, and (2) to establish a method of culturing chondrocytes in type I collagen sponges and induce cell maturation. Collagen sponges were generated from a 1% solution of type I collagen using a freeze/dry technique followed by UV light crosslinking. Chondrocytes isolated from two locations in chick embryo sterna were cultured in these sponges and treated with retinoic acid to induce chondrocyte maturation and extracellular matrix deposition. Material strength testing as well as microscopic and biochemical analyzes were conducted to evaluate the properties of sponges and cell behavior during the culture period. We found that our collagen sponges presented improved stiffness and supported chondrocyte attachment and proliferation. Cells underwent maturation, depositing an abundant extracellular matrix throughout the scaffold, expressing high levels of type X collagen, type I collagen and alkaline phosphatase. These results demonstrate that we have created a transient cartilage template with potential to direct endochondral bone formation after implantation. © 2010 Wiley Periodicals, Inc.
Keywords: alkaline phosphatase; animal cell; animal tissue; Animals; article; Biocompatible Materials; Body fluids; Bone; Bone and Bones; Bone Regeneration; Cartilage; cartilage cell; Cattle; Cell culture; cell maturation; chick embryo; Chondrocytes; Collagen; collagen implant; collagen type 1; collagen type 10; Compressive Strength; controlled study; embryo; enchondral ossification; Endochondral ossification; extracellular matrix; freeze drying; Humans; immunohistochemistry; Ligaments; materials testing; Microscopy, Electron, Scanning; nonhuman; Phosphatases; protein cross linking; Protein Isoforms; retinoic acid; Scaffolds; Scanning electron microscopy; Stress, Mechanical; Tissue engineering; tissue scaffold; Type I collagen; Type X collagen; Ultraviolet radiation

In vitro study of the proliferation and growth of human bone marrow cells on apatite-wollastonite-2M glass ceramics - Magallanes-Perdomo, M.; De Aza, A.H.; Mateus, A.Y.; Teixeira, S.; Monteiro, F.J.; De Aza, S.; Pena, P. (Acta BiomaterialiaActa Biomater., 2010)
This study concerns the preparation and in vitro characterization of an apatite-wollastonite-2M bioactive glass ceramic which is intended to be used for the regeneration of hard tissue (i.e. in dental and craniomaxillofacial surgery). This bioglass ceramic has been obtained by appropriate thermal treatment through the devitrification (crystallization) of a glass with a stoichiometric eutectic composition within the Ca 3(PO 4)2-CaSiO 3 binary system. Crack-free specimens of the bioglass ceramic were immersed in human bone marrow cell cultures for 3, 7, 14 and 21 days, in order to study biocompatibility. Cell morphology, proliferation and colonization were assessed by scanning electron microscopy and confocal laser scanning microscopy. A total protein content assay was used to evaluate the viability and proliferation of cultured bone marrow cells. The results showed that the cells were able to adhere and proliferate on the designed material due to the essentiality of silicon and calcium as accessory factors for cell activity stimulation. © 2009 Acta Materialia Inc. All rights reserved.
Keywords: Apatite; Apatites; article; Bioceramics; Biocompatibility; bone marrow cell; bone prosthesis; Bone Substitutes; Calcium Compounds; calcium derivative; calcium phosphate; calcium silicate; cell activity; cell adhesion; Cell culture; cell differentiation; cell enlargement; cell growth; cell proliferation; cell structure; cell viability; Cells, Cultured; ceramics; chemistry; confocal laser microscopy; crystal structure; Crystallization; cytology; glass; Glass ceramics; human; human cell; Humans; in vitro study; materials testing; Mesenchymal stem cell; Mesenchymal Stem Cells; methodology; osteoblast; Osteoblasts; physiology; priority journal; protein content; Scanning electron microscopy; silicate; Silicates; Surface Properties; surface property; Tissue regeneration; Wollastonite; X ray fluorescence

In vivo evaluation of highly macroporous ceramic scaffolds for bone tissue engineering - Teixeira, S.; Fernandes, H.; Leusink, A.; Van Blitterswijk, C.; Ferraz, M.P.; Monteiro, F.J.; De Boer, J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
During the last decades, different materials of both natural and synthetic origin have been developed with the aim of inducing and controlling osteogenic differentiation of mesenchymal stem cells (MSCs). In order for that to happen, it is necessary that the material to be implanted obey a series of requirements, namely: osteoconduction, biocompatibility, and biodegradability. Additionally, they must be low-priced, easy to produce, shape, and store. Hydroxyapatite (HA) is a well known ceramic with a composition similar to the mineral component of bone and is highly biocompatible and easy to obtain and/or process. On the other hand, collagen is the main structural protein present in the human body and bone. In this study, a polymer replication method was applied and a highly porous HA scaffold was produced. Collagen was later incorporated to improve the biological properties of the scaffold while resembling the bone composition. The scaffolds were characterized by means of scanning electron microscopy, Fourier transform infrared spectroscopy and energy dispersive spectroscopy. In vitro and in vivo testing was performed in all scaffolds produced. The goal of this study was to evaluate the in vivo osteogenic potential of MSCs from two different species seeded on the different HA based porous scaffolds with collagen type I. The results indicate that all scaffolds exhibit relevant bone formation, being more prominent in the case of the HA scaffolds. © 2009 Wiley Periodicals, Inc.
Keywords: animal cell; animal experiment; animal model; Animals; article; Biocompatibility; Biocompatible Materials; Biodegradation; Bone; Bone and Bones; Bone formation; bone tissue; Calcium; Calcium alloys; calcium phosphate; Calcium phosphates; Cell Count; Cell culture; Cell Culture Techniques; Cells, Cultured; cellular distribution; Ceramic materials; ceramics; Collagen; collagen type 1; Durapatite; Energy dispersive spectroscopy; Flowcharting; Fourier transform infrared spectroscopy; Humans; hydroxyapatite; Hydroxylation; in vitro study; In vivo bone formation; in vivo study; In-vivo; infrared spectroscopy; Macroporous; Macroporous scaffolds; male; materials testing; Mesenchymal stem cell; Mesenchymal Stem Cells; Mice; Microscopy, Electron, Scanning; nonhuman; ossification; Osteogenesis; porous polymer; rat; Rats; Rats, Wistar; Scaffolds; Scanning electron microscopy; Spectroscopy, Fourier Transform Infrared; Stem cells; Tissue engineering; tissue scaffold; Tissue Scaffolds

Influence of crystallite size of nanophased hydroxyapatite on fibronectin and osteonectin adsorption and on MC3T3-E1 osteoblast adhesion and morphology - Ribeiro, N.; Sousa, S.R.; Monteiro, F.J. (Journal of Colloid and Interface ScienceJ. Colloid Interface Sci., 2010)
The characteristic topographical features (crystallite dimensions, surface morphology and roughness) of bioceramics may influence the adsorption of proteins relevant to bone regeneration. This work aims at analyzing the influence of two distinct nanophased hydroxyapatite (HA) ceramics, HA725 and HA1000 on fibronectin (FN) and osteonectin (ON) adsorption and MC3T3-E1 osteoblast adhesion and morphology. Both substrates were obtained using the same hydroxyapatite nanocrystals aggregates and applying the sintering temperatures of 725°C and 1000°C, respectively. The two proteins used in this work, FN as an adhesive glycoprotein and ON as a counter-adhesive protein, are known to be involved in the early stages of osteogenesis (cell adhesion, mobility and proliferation). The properties of the nanoHA substrates had an important role in the adsorption behavior of the two studied proteins and clearly affected the MC3T3-E1 morphology, distribution and metabolic activity. HA1000 surfaces presenting slightly larger grain size, higher root-mean-square roughness (Rq), lower surface area and porosity, allowed for higher amounts of both proteins adsorbed. These substrates also revealed increased number of exposed FN cell-binding domains as well as higher affinity for osteonectin. Regarding the osteoblast adhesion results, improved viability and cell number were found for HA1000 surfaces as compared to HA725 ones, independently of the presence or type of adsorbed protein. Therefore the osteoblast adhesion and metabolic activity seemed to be more sensitive to surfaces morphology and roughness than to the type of adsorbed proteins. © 2010 Elsevier Inc.
Keywords: Adhesion; Adhesive proteins; Adsorption; Adsorption behavior; Animals; Apatite; article; Bioceramics; Biological materials; Biomaterials; bone development; Bone Regeneration; cell adhesion; Cell Count; cell metabolism; cell motility; Cell number; cell proliferation; cell strain 3T3; cell structure; Cell-binding domain; Cells, Cultured; cellular distribution; ceramics; controlled study; Crystallite dimension; Crystallite size; Crystallization; Durapatite; Fibronectin; Fibronectin adsorption; Fibronectins; glycoprotein; grain; Grain size; human; human cell; hydroxyapatite; Hydroxyapatite nanocrystals; MC3T3-E1; Metabolic activity; metabolism; Mice; morphology; Nano-HA; nanocrystal; nanoparticles; Nanophased hydroxyapatite; osteoblast; Osteoblast adhesion; Osteoblast morphology; Osteoblasts; Osteogenesis; osteonectin; Osteonectin adsorption; Particle Size; porosity; priority journal; protein; Proteins; Root mean square roughness; Sintering; Sintering temperatures; Surface area; Surface Properties; surface property; Surface roughness; temperature; Topographical features

Innovative macroporous granules of nanostructured-hydroxyapatite agglomerates: Bioactivity and osteoblast-like cell behaviour - Laranjeira, M.S.; Fernandes, M.H.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
To modulate the biological response of implantable granules, two types of bioactive porous granules composed of nanostructured-hydroxyapatite (HA) agglomerates and microstructured-HA, respectively, were prepared using a polyurethane sponge impregnation and burnout method. The resulting granules presented a highly porous structure with interconnected porosity. Both types of granules were characterized using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and mercury intrusion porosimetry. Results showed that nanostructed-HA granules presented higher surface area and porosity than microstructured-HA granules. In vitro testing using MG63 human osteoblast-like cells showed that on both types of surfaces cells were able to adhere, proliferate, and migrate through the macropores, and a higher growth rate was achieved on nanostructured-HA granules than on microstructured-HA granules (76 and 40%, respectively). In addition, these cells maintained similar expression levels of osteoblastic-associated markers namely collagen type I, alkaline phosphatase, bone morphogenetic protein-2, macrophage colony-stimulating factor, and osteoprotegerin. These innovative nanostructured-HA granules may be considered as promising bioceramic alternative matrixes for bone regeneration and drug release application. © 2010 Wiley Periodicals, Inc.
Keywords: Agglomeration; alkaline phosphatase; Apatite; article; Bioceramics; Biocompatible Materials; Biological Markers; Biological materials; Biological response; Biomaterials; Bone; bone morphogenetic protein 2; Bone morphogenetic protein-2; Bone Regeneration; cell adhesion; cell function; cell granule; cell migration; cell proliferation; Cells, Cultured; collagen type 1; Collagen type I; colony stimulating factor 1; Colony-stimulating factor; drug activity; Drug release; Durapatite; Expression levels; Fourier transform infrared spectroscopy; Fourier transforms; Granulation; Granules; growth rate; human; human cell; Human osteoblast-like cells; Humans; hydroxyapatite; In-vitro; infrared spectroscopy; Interconnected porosity; Macro-porosity; Macropores; Macroporosity; Macroporous; materials testing; matrix; Mercury (metal); Mercury intrusion porosimetry; Microscopy, Electron, Scanning; Microstructured; Nano-materials; Nano-structured; nanomaterial; Nanomaterials; Nanostructured materials; Nanostructures; osteoblast; Osteoblast response; Osteoblast-like cells; Osteoblasts; Osteoprotegerin; Phosphatases; polyurethan; Polyurethane sponge; Polyurethanes; porosity; Porous structures; Reverse Transcriptase Polymerase Chain Reaction; Scanning electron microscopy; SEM; Spectroscopy, Fourier Transform Infrared; Surface area; surface property; X ray diffraction; X-Ray Diffraction

An intrauterine pressure generator for educational simulation of labour and delivery - Bastos, L.F.; Lobo, M.F.; van Meurs, W.L.; Ayres-de-Campos, D. (Medical Engineering and PhysicsMed. Eng. Phys., 2010)
Simulation provides a risk free and controllable environment for training of healthcare providers. The limited realism of available simulators and training programs impedes immersive training in obstetric emergencies. In developed countries, intrapartum monitoring in high-risk cases involves continuous evaluation of foetal heart rate and uterine contractions signals. We present an essential component of a high-fidelity simulator for normal and critical situations in labour and delivery, namely an intrauterine pressure generator. The signal model behind the generator consists of a truncated Gaussian curve with the programmable features: amplitude, frequency, duration, and resting tone. Through analysis of 44. h of physiological data, we demonstrate that the natural variability of these features and of the baseline pressure can be approximated by deterministic trends and stationary stochastic processes. Signal parameters can be controlled by simulation instructors, scripts, or other models to reflect different patients, pathologies, and evolving clinical situations. Twelve 40-min tracings reflecting three different patients in labour were presented to three clinical experts, who attributed similar realism scores to simulated and to real tracings. © 2010 IPEM.
Keywords: article; Clinical situations; Computer simulation; delivery; Delivery, Obstetric; Developed countries; Educational simulations; Essential component; Female; Fetal monitoring; Gaussian curves; generator; Health care providers; Heart Rate, Fetal; Heart rates; High-fidelity simulators; Humans; Immersive; intrauterine pressure; labor; Labor, Obstetric; Labour and delivery; medical education; Medical educational simulation; muscle tone; Natural variability; normal distribution; Obstetrics; Physiological data; Pregnancy; Prenatal Diagnosis; Pressure; Pressure generators; priority journal; Random processes; Risk free; Signal generator; Signal generators; Signal models; Signal parameters; Signal Processing, Computer-Assisted; simulation; Stationary stochastic process; statistical model; statistical parameters; statistics; Stochastic Processes; Time Factors; Training program; Uterine activities; Uterine activity; Uterine Contraction; Uterine Monitoring; uterus contraction

Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics): Preface - Campilho, A.; Kamel, M. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2010)

The MEE principle in data classification: A perceptron-based analysis - Silva, L.M.; Marques de Sá, J.; Alexandre, L.A. (Neural ComputationNeural Comp., 2010)
This letter focuses on the issue of whether risk functionals derived from information-theoretic principles, such as Shannon or Rényi's entropies, are able to cope with the data classification problem in both the sense of attaining the risk functional minimum and implying the minimum probability of error allowed by the family of functions implemented by the classifier, here denoted by min Pe. The analysis of this so-called minimization of error entropy (MEE) principle is carried out in a single perceptron with continuous activation functions, yielding continuous error distributions. In spite of the fact that the analysis is restricted to single perceptrons, it reveals a large spectrum of behaviors that MEE can be expected to exhibit in both theory and practice. In what concerns the theoretical MEE, our study clarifies the role of the parameters controlling the perceptron activation function (of the squashing type) in often reaching the minimum probability of error. Our study also clarifies the role of the kernel density estimator of the error density in achieving the minimum probability of error in practice. © 2010 Massachusetts Institute of Technology.
Keywords: algorithm; Algorithms; artificial intelligence; artificial neural network; automated pattern recognition; Computer simulation; entropy; letter; Mathematical Concepts; mathematical phenomena; Models, Statistical; Neural Networks (Computer); Pattern Recognition, Automated; standard; statistical model

A model for educational simulation of hemodynamic transitions at birth - Sá-Couto, C.D.; Andriessen, P.; van Meurs, W.L.; Ayres-de-Campos, D.; Sá-Couto, P.M. (Pediatric ResearchPediatr. Res., 2010)
Birth is characterized by swift and complex transitions in hemodynamic and respiratory variables. Unrecognized pathologies or incidents may quickly become fatal or cause permanent damage. This article introduces an essential component of an acute perinatal care simulator, namely a model for educational simulation of normal hemodynamic transitions seen during and shortly after birth. We explicitly formulate educational objectives and adapt a preexisting model for the simulation of neonatal cardiovascular physiology to include essential aspects of fetal hemodynamics. From the scientific literature, we obtain model parameters that characterize these aspects quantitatively. The fetal model is controlled by a time-and event-based script of changes occurring at birth, such as onset of breathing and cord clamping, and the transitory phase up to 24 h after birth. Comparison of simulation results with published target data confirms that realistic simulated hemodynamic vital signs are achieved. Copyright © 2010 International Pediatric Research Foundation, Inc.
Keywords: article; artificial ventilation; biological model; birth; Blood flow; blood flow velocity; blood pressure; breathing; breathing mechanics; cardiovascular function; clamp; comparative study; Computer simulation; Constriction; education; evaluation; fetus; hemodynamics; human; Humans; Infant, Newborn; ligation; Models, Cardiovascular; newborn; Parturition; perinatal care; priority journal; Regional Blood Flow; reproducibility; Reproducibility of Results; Respiration, Artificial; Respiratory Mechanics; scientific literature; simulator; stimulation; time; Time Factors; umbilical cord; vascularization; vital sign

Monitoring incremental histogram distribution for change detection in data streams - Sebastião, R.; Gama, J.; Rodrigues, P.P.; Bernardes, J. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2010)
Histograms are a common technique for density estimation and they have been widely used as a tool in exploratory data analysis. Learning histograms from static and stationary data is a well known topic. Nevertheless, very few works discuss this problem when we have a continuous flow of data generated from dynamic environments. The scope of this paper is to detect changes from high-speed time-changing data streams. To address this problem, we construct histograms able to process examples once at the rate they arrive. The main goal of this work is continuously maintain a histogram consistent with the current status of the nature. We study strategies to detect changes in the distribution generating examples, and adapt the histogram to the most recent data by forgetting outdated data. We use the Partition Incremental Discretization algorithm that was designed to learn histograms from high-speed data streams. We present a method to detect whenever a change in the distribution generating examples occurs. The base idea consists of monitoring distributions from two different time windows: the reference window, reflecting the distribution observed in the past; and the current window which receives the most recent data. The current window is cumulative and can have a fixed or an adaptive step depending on the distance between distributions. We compared both distributions using Kullback-Leibler divergence, defining a threshold for change detection decision based on the asymmetry of this measure. We evaluated our algorithm with controlled artificial data sets and compare the proposed approach with nonparametric tests. We also present results with real word data sets from industrial and medical domains. Those results suggest that an adaptive window's step exhibit high probability in change detection and faster detection rates, with few false positives alarms. © 2010 Springer-Verlag Berlin Heidelberg.
Keywords: Adaptive Cumulative Windows; Change detection; Data communication systems; Data reduction; Data stream; Data streams; Graphic methods; Learning histograms; Learning systems; Machine learning; Machine-learning; Monitoring; Monitoring data distribution; Sensors; signal detection; Statistical methods

Neuropeptide y and osteoblast differentiation - The balance between the neuro-osteogenic network and local control: Review Article - Franquinho, F.; Liz, M.A.; Nunes, A.F.; Neto, E.; Lamghari, M.; Sousa, M.M. (FEBS JournalFEBS J., 2010)
Accumulating evidence has contributed to a novel view in bone biology: bone remodeling, specifically osteoblast differentiation, is under the tight control of the central and peripheral nervous systems. Among other players in this neuro-osteogenic network, the neuropeptide Y (NPY) system has attracted particular attention. At the central nervous system level, NPY exerts its function in bone homeostasis through the hypothalamic Y2 receptor. Locally in the bone, NPY action is mediated by its Y1 receptor. Besides the presence of Y1, a complex network exists locally: not only there is input of the peripheral nervous system, as the bone is directly innervated by NPY-containing fibers, but there is also input from non-neuronal cells, including bone cells capable of NPY expression. The interaction of these distinct players to achieve a multilevel control system of bone homeostasis is still under debate. In this review, we will integrate the current knowledge on the impact of the NPY system in bone biology, and discuss the mechanisms through which the balance between central and the peripheral NPY action might be achieved. © 2010 FEBS.
Keywords: Animals; Bone and Bones; bone cell; bone innervation; bone mass; cell differentiation; Homeostasis; Humans; immunoreactivity; leptin; Nerve Net; neuropeptide Y; neuropeptide Y receptor; neuropeptide Y2 receptor; nonhuman; NPY; NPY receptors; osteoblast; Osteoblasts; phenotype; priority journal; protein expression; protein interaction; Protein Isoforms; Receptors, Neuropeptide Y; review

Neuropeptide y expression and function during osteoblast differentiation - Insights from transthyretin knockout mice - Nunes, A.F.; Liz, M.A.; Franquinho, F.; Teixeira, L.; Sousa, V.; Chenu, C.; Lamghari, M.; Sousa, M.M. (FEBS JournalFEBS J., 2010)
To better understand the role of neuropeptide Y (NPY) in bone homeostasis, as its function in the regulation of bone mass is unclear, we assessed its expression in this tissue. By immunohistochemistry, we demonstrated, both at embryonic stages and in the adult, that NPY is synthesized by osteoblasts, osteocytes, and chondrocytes. Moreover, peptidylglycine α-amidating monooxygenase, the enzyme responsible for NPY activation by amidation, was also expressed in these cell types. Using transthyretin (TTR) KO mice as a model of augmented NPY levels, we showed that this strain has increased NPY content in the bone, further validating the expression of this neuropeptide by bone cells. Moreover, the higher amidated neuropeptide levels in TTR KO mice were related to increased bone mineral density and trabecular volume. Additionally, RT-PCR analysis established that NPY is not only expressed in MC3T3-E1 osteoblastic cells and bone marrow stromal cells (BMSCs), but is also detectable by RIA in BMSCs undergoing osteoblastic differentiation. In agreement with our in vivo observations, in vitro, TTR KO BMSCs differentiated in osteoblasts had increased NPY levels and exhibited enhanced competence in undergoing osteoblastic differentiation. In summary, this work contributes to a better understanding of the role of NPY in the regulation of bone formation by showing that this neuropeptide is expressed in bone cells and that increased amidated neuropeptide content is related to increased bone mass. © 2009 FEBS.
Keywords: 3T3 Cells; alpha amidating enzyme; Amidated neuropeptide; amidation; Amides; animal cell; animal tissue; Animals; article; Base Sequence; Bone Density; bone development; bone marrow cell; Bone Marrow Cells; Bone marrow stromal cells; bone mass; cartilage cell; cell differentiation; Cells, Cultured; Chondrocytes; controlled study; developmental stage; DNA Primers; embryo; embryo development; Homeostasis; immunohistochemistry; male; Mice; Mice, Knockout; mouse; Mus; neuropeptide Y; nonhuman; NPY; ossification; osteoblast; Osteoblastic differentiation; Osteoblasts; osteocyte; Osteocytes; peptide synthesis; prealbumin; priority journal; protein expression; protein function; radioimmunoassay; regulatory mechanism; reverse transcription polymerase chain reaction; RNA, Messenger; stroma cell; Stromal Cells; trabecular bone

Novel TiN-based dry EEG electrodes: Influence of electrode shape and number on contact impedance and signal quality - Fiedler, P.; Brodkorb, S.; Fonseca, C.; Vaz, F.; Zanow, F.; Haueisen, J. (IFMBE ProceedingsIFMBE Proc., 2010)
Usability of conventional wet electrodes for electroencephalography (EEG) is depending on a set of requirements, including time consuming and complex preparation of the skin of a subject, thus limiting possible application. A new class of "dry" electrodes without the need for electrolyte gels or pastes is being investigated. The dry application scenario of these novel electrodes requires a stable and reliable contact with the subject's skin. In order to develop an electrode shape with large contact surface for low electrode-skin impedance while also ensuring a sufficient hair layer penetration, several studies were performed. In this paper a distinct titanium electrode substrate shape for titanium nitride (TiN) coated electrodes was analyzed regarding influences of the number of interconnected electrodes and contact surface on electrodeskin impedance and biosignal quality. As a result 10 interconnected TiN pins had the lowest impedance values of 14 to 55 kΩ (depending on signal frequency) in comparison to 2 to 44 kΩ using conventional Ag/AgCl electrodes. Also the mean average deviation (MAD) of 5 seconds long EEG episodes were computed. The lowest MADs of 2.00 to 2.25 μV were determined using three interconnected TiN pins. In comparison to MADs of 2.13 to 2.54 μV, using a second set of Ag/AgCl electrodes, this leads to the conclusion that most of the error was related to spatial distance. This first step in optimization of electrode shape for dry TiN based electrodes showed very promising results and enable their use for EEG acquisition. © 2010 International Federation for Medical and Biological Engineering.
Keywords: Ag/AgCl; Application scenario; Average deviation; Biochemical engineering; Bioelectric phenomena; bioelectric signals; biomedical electrodes; Biosignals; Coated electrodes; Coated wire electrodes; Contact impedance; Contact surface; electrochemical characterization; Electrochemical characterizations; Electrode shape; Electrode-skin impedance; Electrodes; electroencephalography; Electrophysiology; Medical computing; Signal frequencies; Signal quality; Spatial distance; Titanium; Titanium electrodes; Titanium nitride

Optical flow based Arabidopsis thaliana root meristem cell division detection - Quelhas, P.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2010)
The study of cell division and growth is a fundamental aspect of plant biology research. In this research the Arabidopsis thaliana plant is the most widely studied model plant and research is based on in vivo observation of plant cell development, by time-lapse confocal microscopy. The research herein described is based on a large amount of image data, which must be analyzed to determine meaningful transformation of the cells in the plants. Most approaches for cell division detection are based on the morphological analysis of the cells' segmentation. However, cells are difficult to segment due to bad image quality in the in vivo images. We describe an approach to automatically search for cell division in the Arabidopsis thaliana root meristem using image registration and optical flow. This approach is based on the difference of speeds of the cell division and growth processes (cell division being a much faster process). With this approach, we can achieve a detection accuracy of 96.4%. © 2010 Springer-Verlag.
Keywords: Arabidopsis thaliana; Biology; Biology image processing; cell division detection; Cell divisions; cell proliferation; confocal microscopy; Detection accuracy; Growth process; Image data; Image quality; Image segmentation; Imaging systems; In-vivo; In-vivo images; Metadata; Morphological analysis; Optical data processing; Optical flows; Plant biology; Plant cells; research; Root meristem

Plasma surface modification of polycarbonate and poly(propylene) substrates for biomedical electrodes - Pedrosa, P.; Chappé, J.-M.; Fonseca, C.; Machado, A.V.; Nóbrega, J.M.; Vaz, F. (Plasma Processes and PolymersPlasma Processes Polym., 2010)
The effects of surface plasma treatments on the properties of PP and PC substrates were studied. Main results showed that the 0.48 Pa Ar treatment promoted the most favorable changes: roughness increased from 15 to 17 nm for PC and from 12 to 30 nm for PP, while the CA lowered from 95° to 59° and from 87° to 35° for PC and PP, respectively. The effects of the activation treatment on adhesion were checked by depositing a thin layer of TiN on both untreated and 0.48 Pa Ar plasma treated PC samples, and the adhesion to both substrates compared using the standard X-cut tape test. The Ar activated samples displayed better adhesion of the TiN film than the untreated ones, confirming the benefits of the surface changes induced by the plasma treatments. (Figure Presented) © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Activation treatment; Adhesion; Ar plasmas; biomedical electrodes; Deposition; Electrodes; Functional polymers; Plasma surface modifications; Plasma treatment; Plasma treatments; Plasmas; Polymers; Propylene; Surface changes; Surface modification; Surface plasma treatment; Thin layers; TiN films; Titanium nitride

Proliferation and mineralization of bone marrow cells cultured on macroporous hydroxyapatite scaffolds functionalized with collagen type I for bone tissue regeneration - Teixeira, S.; Fernandes, M.H.; Ferraz, M.P.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
This study concerns the preparation and in vitro characterization of functionalized hydroxyapatite (HA) porous scaffolds, which are intended to be used as drug-delivery systems and bone-regeneration matrices. Hydroxyapatite scaffolds were prepared using the polymer replication method, and, after being submitted to a specific sintering cycle, collagen Type I was incorporated on the surface. After the coating procedure, collagen was crosslinked using the N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) conjugation method. In this study, hydroxyapatite scaffolds with uncrosslinked and cross-linked Type I collagen were evaluated. Cell morphology and deposition of extracellular matrix were assessed by scanning electron microscopy, whereas cell distribution was visualized by means of methylene blue staining. MTS and total DNA quantification assays were used to evaluate the viability and proliferation of human bone marrow cells cultured on all the materials for 28 days. Results showed that the cells were able to adhere, proliferate, and form a mineralized matrix on the surface of all the materials. Furthermore, the cells were able to spread from one pore to another and form cell clusters. The results show that these scaffolds are good candidates to serve as drug delivery vehicles and for tissue engineering purposes. © 2010 Wiley Periodicals, Inc.
Keywords: 1 (3 dimethylaminopropyl) 3 ethylcarbodiimide; adult; Animal cell culture; Apatite; article; Automobile exhibitions; Bone; bone marrow cell; Bone Marrow Cells; bone matrix; bone mineralization; Bone Regeneration; bone tissue; Bone tissue regeneration; Calcification, Physiologic; cell adhesion; Cell clusters; Cell culture; Cell distribution; Cell morphology; cell proliferation; cell structure; cell viability; Cells, Cultured; cellular distribution; Ceramic materials; chemistry; Coating procedures; Collagen; collagen type 1; Collagen type I; conjugation; controlled study; cross linking; cross linking reagent; Cross-Linking Reagents; Crosslinked; cytology; Cytotoxicity; DNA; DNA quantification; drug conjugation; Drug delivery; drug delivery system; Drug delivery vehicles; drug effect; Drug-delivery systems; Durapatite; Extracellular matrices; extracellular matrix; Functionalized; human; Human bone marrow cells; human cell; Humans; hydroxyapatite; in vitro study; In-vitro; Macroporous; Macroporous ceramics; male; matrix; metabolism; methylene blue; Methylene blue staining; Microscopy, Electron, Scanning; molecular scaffold; n hydroxysuccinimide; N-hydroxysuccinimide; polymer; Polymer replication; porosity; Porous scaffold; Scaffolds; Scanning electron microscopy; Sintering; Sintering cycles; spectrometry; Spectrometry, X-Ray Emission; Tissue engineering; tissue scaffold; Tissue Scaffolds; Type I collagen; Young Adult

Protein matrices for improved wound healing: Elastase inhibition by a synthetic peptide model - Vasconcelos, A.; Pêgo, A.P.; Henriques, L.; Lamghari, M.; Cavaco-Paulo, A. (BiomacromoleculesBiomacromolecules, 2010)
The unique properties of silk fibroin were combined with keratin to develop new wound-dressing materials. Silk fibroin/keratin (SF/K) films were prepared to reduce high levels of elastase found on chronic wounds. This improved biological function was achieved by the incorporation of a small peptide synthesized based on the reactive-site loop of the Bowman-Birk Inhibitor (BBI) protein. In vitro degradation and release were evaluated using porcine pancreatic elastase (PPE) solution as a model of wound exudate. It was found that biological degradation and release rate are highly dependent on film composition. Furthermore, the level of PPE activity can be tuned by changing the film composition, thus showing an innovative way of controlling the elastase-antielastase imbalance found on chronic wounds. © 2010 American Chemical Society.
Keywords: animal cell; Animals; article; Atomic force microscopy; Biodegradation; Biological degradation; Biological functions; biomaterial; Bombyx; Bowman Birk inhibitor; Bowman-Birk inhibitors; cell proliferation; Chronic wounds; controlled study; Cytotoxicity test; Degradation; Elastase; elastase inhibitor; enzyme activity; Enzyme inhibition; Fibroins; Film composition; In-vitro; keratin; Keratins; mass spectrometry; materials testing; Mice; Microscopy, Atomic Force; NIH 3T3 Cells; nonhuman; pancreatic elastase; Peptide Fragments; Peptides; priority journal; protein binding; Protein matrices; Release rate; Silk; Silk fibroin; Spectrometry, Mass, Electrospray Ionization; Sus; Swine; Synthetic peptide; Trypsin Inhibitor, Bowman-Birk Soybean; Trypsin Inhibitors; wound fluid; Wound healing

Receptor-mediated gene delivery using PAMAM dendrimers conjugated with peptides recognized by mesenchymal stem cells - Santos, J.L.; Pandita, D.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Balian, G.; Tomás, H. (Molecular PharmaceuticsMol. Pharm., 2010)
As mesenchymal stem cells (MSCs) can differentiate into multiple cell types, the delivery of exogenous genes to this type of cell can be an important tool in tissue regeneration and engineering. However transfection of MSCs using nonviral gene delivery vectors is difficult, the development of more efficient and safe DNA vehicles being necessary. Moreover, specific transfection of MSCs may be required to avoid unwanted side effects in other tissues. In this study, a novel family of gene delivery vectors based on poly(amidoamine) (PAMAM) dendrimers functionalized with peptides displaying high affinity toward MSCs was prepared. The vectors were characterized with respect to their ability to neutralize, bind and compact plasmid DNA (pDNA). The complexes formed between the vectors and pDNA were analyzed concerning their size, -potential, capacity of being internalized by cells and transfection efficiency. These new vectors exhibited low cytotoxicity, receptor-mediated gene delivery into MSCs and transfection efficiencies superior to those presented by native dendrimers and by partially degraded dendrimers. © 2010 American Chemical Society.
Keywords: animal cell; animal experiment; animal tissue; Animals; article; asparaginylserylmethionylisoleucylalanylhistidylasparaginyllysylthreonylarginylmethionylhistidylglycylglycylglycylserylcysteine; Cell recognition; cell survival; Cells, Cultured; controlled study; Cytotoxicity; dendrimer; Dendrimers; DNA; DNA binding; Electrophoresis, Agar Gel; flow cytometry; Gene delivery; gene targeting; Gene Transfer Techniques; gene vector; genetic transfection; Genetic Vectors; Green Fluorescent Proteins; male; Mesenchymal stem cell; Mesenchymal Stem Cells; Models, Theoretical; multigene family; nonhuman; PAMAM dendrimers; peptide; Peptides; plasmid DNA; polyamidoamine; priority journal; rat; Rats; Rats, Wistar; serylglycylhistidylglutaminylleucylleucylleucylasparaginyllysylmethionylprolylasparaginylglycylglycylglycylserylcysteine; unclassified drug; Zeta potential

Segmentation of the carotid intima-media region in B-mode ultrasound images - Rocha, R.; Campilho, A.; Silva, J.; Azevedo, E.; Santos, R. (Image and Vision ComputingImage Vision Comput, 2010)
This paper proposes a new approach for the segmentation of both near-end and far-end intima-media regions of the common carotid artery in ultrasound images. The method requires minimal user interaction and is able to segment the near-end wall in arteries with large, hypoechogenic and irregular plaques, issues usually not considered previously due to the increased segmentation difficulty. The adventitia is detected by searching for the best fit of a cubic spline to edges having features compatible with the adventitia boundary. The algorithm uses a global smoothness constraint and integrates discriminating features of the adventitia to reduce the attraction by other edges. Afterwards, using the information of the adventitia location, the lumen boundary is detected by combining dynamic programming, smooth intensity thresholding surfaces and geometric snakes. Smooth contours that correctly adapt to the intima are produced, even in the presence of deep concavities. Moreover, unlike balloon-based snakes, the propagation force does not depend on gradients and does not require a predefined direction. An extensive statistical evaluation is computed, using a set of 47 images from 24 different symptomatic patients, including several classes, sizes and shapes of plaques. Bland-Altman plots of the mean intima-media thickness, for manual segmentations of two medical experts, show a high intra-observer and inter-observer agreement, with mean differences close to zero (mean between -0.10 mm and 0.18 mm) and with the large majority of differences within the limits of agreement (standard deviation between 0.10 mm and 0.12 mm). Similar plots reveal a good agreement between the automatic and the manual segmentations (mean between -0.07 mm and 0.11 mm and standard deviation between 0.11 mm and 0.12 mm). © 2009 Elsevier B.V. All rights reserved.
Keywords: Acoustic waves; B-mode ultrasound images; Best fit; Carotid; Common carotid artery; Cubic spline; Digital image storage; Dynamic programming; Edge detection; End-wall; Function evaluation; Geometric snake; Geometric snakes; Image segmentation; Intima-media thickness; Manual segmentation; Medical experts; New approaches; Smoothness constraints; Standard deviation; Statistical evaluation; statistics; Thresholding; Ultrasonics; Ultrasound image; Ultrasound images; User interaction

Simulation for teaching normal delivery and shoulder dystocia to midwives in training - Reynolds, A.; Ayres-de-Campos, D.; Pereira-Cavaleiro, A.; Ferreira-Bastos, L. (Education for Health: Change in Learning and PracticeEduc. Health, 2010)
Introduction and objective: The cognitive impact of using simulation sessions in midwifery training has not been the subject of previous research. The aim of this study was to compare the effect on students' knowledge of a simulation session versus an image-based lecture, for teaching routine management of normal delivery and resolution of shoulder dystocia to midwives in training. Methods: Sixty students were enrolled three weeks after a "labour and delivery" class, and randomly assigned to two groups. Ten were subsequently excluded as they were not able to attend the whole session and/or did not complete the tests. In the simulation group (n=26), students were divided into pairs and attended a 30-minute hands-on session in the simulation centre. In the lecture group (n=24), students participated in a 30-minute image-based interactive lecture. A ten-question multiple-choice test was taken before (pre-test) and after (post-test) both sessions, to evaluate students' knowledge of labour and delivery and shoulder dystocia. Learner satisfaction was evaluated by adding a six question Likert scale questionnaire to the post-test. Independent t-test, paired samples t-test, and Mann-Whitney test were used for statistical analysis, setting significance at p<0.05. Results: The simulation group showed a significantly higher mean post-test score (6.38 vs. 5.16; p=0.003) and a significantly greater inter-test score progression (p<0.0001). Overall learner satisfaction was also higher in this group (p=0.0001). Conclusions: A significantly higher short-term reinforcement of knowledge and greater learner satisfaction was obtained using simulation sessions compared to image-based lectures when teaching routine management of normal delivery and resolution of shoulder dystocia to midwives in training. © A Reynolds, D Ayres-de-Campos, A Pereira-Cavaleiro, L Ferreira-Bastos, 2010.
Keywords: Labour and delivery; Midwifery training; Patient simulators; Shoulder dystocia

The stability of self-assembled monolayers with time and under biological conditions - Maciel, J.; Martins, M.C.L.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
The stability of self-assembled monolayers (SAMs) of different functionalities (CH 3
Keywords: Animals; article; Binding energy; Biological conditions; Biological studies; Body fluids; Cattle; Cell culture; Culture Media; Ethanol; Female; Fetal bovine serum; In-cell; materials testing; measurement; molecular stability; Nitrogen chamber; nonhuman; Organic polymers; Oxidation; Oxidation-Reduction; Oxidized sulfur; Photodegradation; Photoelectron spectroscopy; Sams; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; Stability; Storage condition; Sulfhydryl Compounds; Sulfur; Surface Properties; Water; wettability; X ray photoelectron spectroscopy; XPS; XPS spectra

Synthesis and characterization of HAp nanorods from a cationic surfactant template method - Coelho, J.M.; Moreira, J.A.; Almeida, A.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2010)
Hydroxyapatite (HAp) [Ca 10(PO 4) 6(OH) 2] nanorods were synthesized using a surfactant templating method, with cetyltrimethylammonium bromide (CTAB) micelles acting as template for HAp growth. The effects of the sintering temperature on the morphological and crystallographic characteristics and on chemical composition of the "as-prepared" structures are discussed. The experimental results show that low heat-treatment temperatures are preferred in order to obtain high quality nanorods, with diameters ranging between 20 and 50 nm. High heat-treatment temperatures enhance the thermal decomposition of HAp into other calcium phosphate compounds, and the sintering of particles into micrometer ball-like structures. The stability of aqueous suspensions of HAp nanorods is also discussed. © 2010 Springer Science+Business Media, LLC.
Keywords: Ammonium compounds; Aqueous suspensions; article; Bromine compounds; Calcium; calcium phosphate; cationic surfactant; Cationic surfactants; Cations; Cetrimonium Compounds; Cetyltrimethylammonium bromide; chemical composition; Chemical compositions; Chemical structure; Crystallographic characteristics; Dyes; Heat treatment temperature; High quality; hydroxyapatite; Microscopy, Electron, Scanning; Microscopy, Electron, Transmission; nanorod; Nanorods; Nanotubes; Phosphate compounds; priority journal; Pyrolysis; Scanning electron microscopy; Sintering; Sintering temperatures; Surface-Active Agents; Surfactant template method; Surfactant templating; Suspensions (fluids); synthesis; Synthesis and characterizations; Thermal decompositions; X-Ray Diffraction

Targeted gene delivery into peripheral sensorial neurons mediated by self-assembled vectors composed of poly(ethylene imine) and tetanus toxin fragment c - Oliveira, H.; Fernandez, R.; Pires, L.R.; Martins, M.C.L.; Simões, S.; Barbosa, M.A.; Pêgo, A.P. (Journal of Controlled ReleaseJ. Control. Release, 2010)
A simple, safe and efficient system that can specifically transfect peripheral sensorial neurons can bring new answers to address peripheral neuropathies. A multi-component non-viral gene delivery vector targeted to peripheral nervous system cells was developed, using poly(ethylene imine) (PEI) as starting material. A binary DNA/polymer complex based on thiolated PEI (PEISH) was optimized, considering complex size and zeta potential and the ability to transfect a sensorial neuron cell line (ND7/23). The 50. kDa non-toxic fragment from tetanus toxin (HC), which has been previously shown to interact specifically with peripheral neurons and to undergo retrograde transport, was grafted to the complex core via a bifunctional PEG (HC-PEG) reactive for the thiol moieties present in the complex surface. Several formulations of HC-PEG ternary complexes were tested for targeting, by assessing the extent of cellular internalization and levels of transfection, in both the ND7/23 and NIH 3 T3 (fibroblast) cell lines. Targeted gene transfer to the neuronal cell line was observed for the complex formulations containing 5 and 7.5. Μg of HC-PEG. Finally, our results demonstrate that the developed ternary vectors are able to transfect primary cultures of dorsal root ganglion dissociated neurons in a targeted manner and elicit the expression of a relevant neurotrophic factor. © 2010 Elsevier B.V.
Keywords: Aberrations; animal cell; Animals; article; Bifunctional; Cell culture; Cell Line, Tumor; Cell lines; cell strain 3T3; Cells, Cultured; Cellular internalization; Chemical modification; Complex cores; Complex formulations; Complex surface; controlled study; DNA; DNA protein complex; Dorsal root ganglia; Efficient systems; embryo; Ethylene; Female; Gene transfer; genetic transfection; Imines; internalization; macrogol; Mice; mouse; Multicomponents; nanoparticle; nanoparticles; neuroblastoma cell; Neuronal cell; Neurons; neurotrophic factor; Neurotrophic factors; NIH 3T3 Cells; Nitrogen compounds; Non-viral; Non-viral gene delivery; nonhuman; Nonviral; nonviral gene delivery system; Nucleic acids; Particle Size; Peptide Fragments; Peripheral nervous system; Peripheral neuropathy; Plasmids; Polyethylene Glycols; Polyethylene oxides; Polyethyleneimine; Polyethylenes; Primary culture; priority journal; process optimization; protein expression; rat; Rats; Rats, Wistar; Regenerative Medicine; Self-assembled; sensory nerve cell; spinal ganglion; Starting materials; Targeted; Targeted gene delivery; Ternary complex; Ternary vectors; Tetanus toxin; tetanus toxin fragment c; Transfection; unclassified drug; Zeta potential

TNF-α regulates the effects of irradiation in the mouse bone marrow microenvironment - Cachaço, A.S.; Carvalho, T.; Santos, A.C.; Igreja, C.; Fragoso, R.; Rio, C.O.; Ferreira, M.; Serpa, J.; Correia, S.; Pinto-Do-Ó, P.; Dias, S. (PLoS ONEPLoS ONE, 2010)
Background: Secondary bone marrow (BM) myelodysplastic syndromes (MDS) are increasingly common, as a result of radio or chemotherapy administered to a majority of cancer patients. Patients with secondary MDS have increased BM cell apoptosis, which results in BM dysfunction (cytopenias), and an increased risk of developing fatal acute leukemias. In the present study we asked whether TNF-α, known to regulate cell apoptosis, could modulate the onset of secondary MDS. Principal Findings:We show that TNF-α is induced by irradiation and regulates BM cells apoptosis in vitro and in vivo. In contrast to irradiated wild type (WT) mice, TNF-α deficient (TNF-α KO) mice or WT mice treated with a TNF-α-neutralizing antibody were partially protected from the apoptotic effects of irradiation. Next we established a 3-cycle irradiation protocol, in which mice were sub-lethally irradiated once monthly over a 3 month period. In this model, irradiated WT mice presented loss of microsatellite markers on BM cells, low white blood cell (WBC) counts, reduced megakaryocyte (MK) and platelet levels (thrombocytopenia) and macrocytic anemia, phenoypes that suggest the irradiation protocol resulted in BM dysfunction with clinical features of MDS. In contrast, TNF-α KO mice were protected from the irradiation effects: BM cell apoptosis following irradiation was significantly reduced, concomitant with sustained BM MK numbers and absence of other cytopenias. Moreover, irradiated WT mice with long term (≥5 months) BM dysfunction had increased BM angiogenesis, MMPs and VEGF and NFkB p65, suggestive of disease progression. Conclusion:Taken together, our data shows that TNF-α induction following irradiation modulates BM cell apoptosis and is a crucial event in BM dysfunction, secondary MDS onset and progression. © 2010 Cachaço et al.
Keywords: angiogenesis; animal; animal cell; animal experiment; animal model; animal tissue; Animals; Antibodies, Neutralizing; apoptosis; article; Blood; blood cell count; Blotting, Western; bone marrow; bone marrow cell; Bone Marrow Cells; C57BL mouse; Cell Line; clinical feature; controlled study; cytokine production; disease course; drug effect; Enzyme Activation; flow cytometry; genetics; immunology; in vitro study; in vivo study; irradiation; leukocyte; leukocyte count; Leukocytes; macrocytic anemia; male; matrix metalloproteinase; Matrix Metalloproteinases; megakaryocyte; Megakaryocytes; metabolism; Mice; Mice, Inbred C57BL; Mice, Knockout; microenvironment; microsatellite marker; mouse; mouse mutant; Mus; myelodysplastic syndrome; neovascularization (pathology); Neovascularization, Pathologic; neutralizing antibody; nonhuman; Pathology; phenotype; protein expression; radiation dose; radiation exposure; Reverse Transcriptase Polymerase Chain Reaction; reverse transcription polymerase chain reaction; thrombocytopenia; transcription factor RelA; tumor necrosis factor alpha; tumor necrosis factor alpha antibody; Tumor Necrosis Factor-alpha; Vascular Endothelial Growth Factor A; vascularization; vasculotropin; vasculotropin A; Western blotting; zymography

Automated Arabidopsis plant root cell segmentation based on SVM classification and region merging - Marcuzzo, M.; Quelhas, P.; Campilho, A.; Maria Mendonça, A.; Campilho, A. (Computers in Biology and MedicineComput. Biol. Med., 2009)
To obtain development information of individual plant cells, it is necessary to perform in vivo imaging of the specimen under study, through time-lapse confocal microscopy. Automation of cell detection/marking process is important to provide research tools in order to ease the search for special events, such as cell division. In this paper we discuss an automatic cell detection approach for Arabidopsis thaliana based on segmentation, which selects the best cell candidates from a starting watershed-based image segmentation and improves the result by merging adjacent regions. The selection of individual cells is obtained using a support vector machine (SVM) classifier, based on a cell descriptor constructed from the shape and edge strength of the cells' contour. In addition we proposed a novel cell merging criterion based on edge strength along the line that connects adjacent cells' centroids, which is a valuable tool in the reduction of cell over-segmentation. The result is largely pruned of badly segmented and over-segmented cells, thus facilitating the study of cells. When comparing the results after merging with the basic watershed segmentation, we obtain 1.5% better coverage (increase in F-measure) and up to 27% better precision in correct cell segmentation. © 2009 Elsevier Ltd. All rights reserved.
Keywords: accuracy; Arabidopsis; Arabidopsis plant; Arabidopsis thaliana; article; artificial intelligence; automation; Bioinformatics; Biological cells; Biomedical image processing; Cell detection; Cell divisions; Cell membranes; Cell merging; cell proliferation; Cell segmentation; Cell Shape; Cell Wall; Computer simulation; confocal microscopy; controlled study; Descriptor; F-measure; Image analysis; image processing; Image Processing, Computer-Assisted; Image segmentation; Imaging systems; In-Vivo imaging; Individual cells; Landforms; Merging; Models, Biological; nonhuman; Over segmentation; Plant cells; plant root; Plant roots; Plants (botany); priority journal; Region-merging; Research tools; root morphology; Segmented cell; signal noise ratio; support vector machine; Support vector machines; SVM classification; Watershed segmentation; Watersheds

Cancer cell angiogenic capability is regulated by 3D culture and integrin engagement - Fischbach, C.; Hyun, J.K.; Hsiong, S.X.; Evangelista, M.B.; Yuen, W.; Mooney, D.J. (Proceedings of the National Academy of Sciences of the United States of AmericaProc. Natl. Acad. Sci. U. S. A., 2009)
Three-dimensional culture alters cancer cell signaling; however, the underlying mechanisms and importance of these changes on tumor vascularization remain unclear. A hydrogel system was used to examine the role of the transition from 2D to 3D culture, with and without integrin engagement, on cancer cell angiogenic capability. Three-dimensional culture recreated tumor microenvironmental cues and led to enhanced interleukin 8 (IL-8) secretion that depended on integrin engagement with adhesion peptides coupled to the polymer. In contrast, vascular endothelial growth factor (VEGF) secretion was unaffected by 3D culture with or without substrate adhesion. IL-8 diffused greater distances and was present in higher concentrations in the systemic circulation, relative to VEGF. Implantation of a polymeric IL-8 delivery system into GFP bone marrow-transplanted mice revealed that localized IL-8 up-regulation was critical to both the local and systemic control of tumor vascularization in vivo. In summary, 3D integrin engagement within tumor microenvironments regulates cancer cell angiogenic signaling, and controlled local and systemic blockade of both IL-8 and VEGF signaling may improve antiangiogenic therapies. © 2009 by The National Academy of Sciences of the USA.
Keywords: animal experiment; animal model; Animals; arginylglycylaspartic acid; article; bone marrow transplantation; cancer cell; cancer cell culture; Cell Culture Techniques; concentration (parameters); controlled study; cytokine release; Diffusion; Drug delivery; ECM; Humans; hydrogel; Hydrogels; IL-8; implantation; in vivo study; integrin; Integrins; interleukin 8; Interleukin-8; Mice; microenvironment; Models, Biological; mouse; Mus; Neoplasms; Neovascularization, Pathologic; nonhuman; polymer; priority journal; signal transduction; systemic circulation; Tumor vascularization; upregulation; Vascular Endothelial Growth Factor A; vasculotropin

Cancer invasion and metastasis: Interacting ecosystems - Mareel, M.; Oliveira, M.J.; Madani, I. (Virchows ArchivVirchows Arch., 2009)
Malignant tumors invade and metastasize. They consist of cancer cells, evolving through genetic and epigenetic modulation, mixed with tumor-associated host cells, emerging from resident or bone marrow-derived precursors. These cells establish ecosystems to activate cellular programs for local invasion and distant metastasis. Characteristic of such malignancy-related activities is communication inside ecosystems between cells, ligands, receptor protein complexes, and signaling pathways as well as between ecosystems comprising the primary tumor, lymph node and distant metastasis, bone marrow and blood and lymph circulation. Complexity is another characteristic, resulting from: heterogeneity of the cell populations; the numbers of promoter and suppressor genes, their levels of regulation, and the pleiotropic activities of their products; biological redundancy of the molecular mechanisms underpinning invasion-related activities. Clinical attention is paid to putative new targets, namely host cells, individual molecules and their signaling pathways, as well as the effects of current treatment on invasion and metastasis. © 2009 Springer-Verlag.
Keywords: bone marrow; cancer cell; cancer invasion; carcinogenesis; cell activity; Circulation; ecosystem; epigenetics; extracellular matrix; gene control; host cell; human; Humans; lymph node metastasis; metastasis; Metastatic site; microarray analysis; Molecular biology; molecular imaging; Neoplasm Invasiveness; Neoplasm Metastasis; Neoplasms; nonhuman; pleiotropy; primary tumor; priority journal; Promoter and suppressor genes; promoter region; review; signal transduction; suppressor gene; Therapy guidance; Tumor-associated host cells

Cationic liposome-DNA complexes as gene delivery vectors: Development and behaviour towards bone-like cells - Oliveira, A.C.; Ferraz, M.P.; Monteiro, F.J.; Simões, S. (Acta BiomaterialiaActa Biomater., 2009)
Modulation of the biological pathways responsible for fracture repair and osteogenisis may accelerate regeneration. Gene therapy is an alternative method for the release of osteogenisis-stimulating proteins into tissues. The development of vectors for gene release is still a problem in terms of ethics and techniques. In this work we evaluated whether cationic liposomes constitute a valuable strategy for the release of genetic material into bone tissue cells as non-viral vectors. Liposomes were prepared with 1,2-dioleoyl-3-trimethylammonium propane (DOTAP)-2-dioleoyl-sn-glycero-3-phosphatidylethanolamine and DOTAP-cholesterol, and characterized according to their size, zeta potential, DNA protection capacity and cytotoxicity. Transfection studies were also carried out using pCMVβ-gal plasmid in two osteoblastic cell lines (MG63 and MC3T3-E1) and in the 294T line, varying the charge ratio and the applied DNA dose. Inclusion of transferrin to increase the expression was also tested. The results suggest that there is great dependency between the transfection activity and the lipid formulation, the charge ratios of the complexes, the applied DNA dose and the cell type. There were even some differences concerning both osteoblastic lines under study. The cells of the MC3T3-E1 line present greater expression levels than the cells of the MG-63 line. The conjugation of the transferrin with the complexes contributes to the increase in transfection levels, possibly due to an increase in internalization of complexes. It is thus a good strategy for inducing the expression of specific genes in osteoblast-like cells. © 2009 Acta Materialia Inc.
Keywords: 1,2 dioleoyl 3 trimethylammoniopropane; animal cell; Animals; article; bone cell; bone development; bone tissue; Cationic liposomes; Cell Line; cell type; complex formation; controlled study; Cytotoxicity; DNA; drug mechanism; gene expression regulation; Gene therapy; Gene transfer; genetic transfection; Genetic Vectors; human; human cell; internalization; lipoplex; liposome; Liposomes; materials testing; Mice; nonhuman; nonviral gene delivery system; osteoblast; Osteoblasts; Osteogenesis; Particle Size; plasmid; priority journal; Transfection; transferrin; Zeta potential

Cell division detection on the arabidopsis thaliana root - Marcuzzo, M.; Guichard, T.; Quelhas, P.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2009)
The study of individual plant cells and their growth structure is an important focus of research in plant genetics. To obtain development information at cellular level, researchers need to perform in vivo imaging of the specimen under study, through time-lapse confocal microscopy. Within this research field it is important to understand mechanisms like cell division and elongation of developing cells. We describe a tool to automatically search for cell division in the Arabidopsis thaliana using information of nuclei shape. The nuclei detection is based on a convergence index filter. Cell division detection is performed by an automatic classifier, trained through cross-validation. The results are further improved by a stability criterion based on the Mahalanobis distance of the shape of the nuclei through time. With this approach, we can achieve a correct detection rate of 94.7%. © 2009 Springer Berlin Heidelberg.
Keywords: A-stability; Arabidopsis thaliana; Automatic classifiers; Bioinformatics; Cell divisions; Cell membranes; cell proliferation; Cellular levels; confocal microscopy; Cross validation; Detection rates; Growth structures; Image analysis; In-plants; In-Vivo imaging; Mahalanobis distances; Pattern recognition; Plant cells; research; Research fields; Stability criteria

Cellular alignment induction during early in vitro culture stages using micropatterned glass coatings produced by sol-gel process - Pelaez-Vargas, A.; Ferrell, N.; Fernandes, M.H.; Hansford, D.J.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2009)
Cell behaviour such as adhesion, morphology, proliferation and functional activity are highly influenced by surface properties including hydrophobicity, roughness, texture and morphology. These surface properties may be controlled using a mixture of additive coating techniques to produce glass coatings by sol-gel process and soft lithography on dental ceramics. The purpose of this work was to compare cell adhesion and early orientation of Human Bone Marrow (HBM) cells cultured on micro-patterned (micro-PGC) and on flat glass coatings (FGC) produced by sol-gel processing. Spin coating was used to apply SiO 2 flat coatings on glass substrates as model surfaces. Photolithography was applied to produce master patterns with microscale dimensions. A moulding technique was used to print micropatterned SiO 2 glass coatings produced by a sol-gel process. The coatings were then sintered, sterilized and cultured with HBM cells derived from primary cultures, using a standardized protocol, for 1 and 7 days. Cell morphology and orientation were observed using scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). Flat and MPGC with line shaped features were produced. Cells presented a typical osteoblastic morphology on flat surfaces while slimmer, preferentially oriented and more elongated morphologies could be seen on line micro-patterned surfaces. HBM cells cultured on flat glass coatings showed increased tendency to spread and to assume more randomized proliferation when compared to the cells on the micro-patterned glass coatings. Micro-patterned glass coatings showed higher orientation control and smaller delay in the rate of proliferation, in early stages of in vitro culture as compared to flat coatings. These preliminary studies revealed that Micro-PGC induce significant morphological changes and controlled orientation of HBM cells during early stages of cell proliferation.
Keywords: Adhesion; cell adhesion; Cell behaviours; Cell culture; Cell morphologies; cell proliferation; Cells; Coatings; Colloids; Confocal laser scanning microscopies; confocal microscopy; Contact guidance; Controlled orientations; cytology; Dental ceramics; Dental Materials; Flat glass; Flat surfaces; Functional activities; Gelation; Gels; glass; Glass ceramics; Glass coatings; Glass substrates; In-vitro; Micro-patterned; Micro-patterned surfaces; Micro-scale; Micromachining; Micropatterning; Model surfaces; Morphological changes; morphology; Nanostructured materials; Orientation controls; Primary cultures; Scanning; Scanning electron microscopy; Scanning electrons; SEM; Silicon compounds; Soft lithographies; Sol-gel; Sol-gel process; Sol-gel processing; Sol-gels; Sols; Surface Properties; Thermal spraying; Trace analysis

Chromatographic pattern recognition using optimized one-class classifiers - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2009)
This paper presents a method for automating the selection of the rejection rate of one-class classifiers aiming at optimizing the classifier performance. These classifiers are used in a new classification approach to deal with class imbalance in Thin-Layer Chromatography (TLC) patterns, which is due to the huge difference between the number of normal and pathological cases, as a consequence of the rarity of Lysosomal Storage Disorders (LSD) diseases. The classification is performed in two decision stages, both implemented using optimized one-class classifiers: the first stage aims at recognizing most of the normal samples; the outliers of this first decision level are presented to the second stage, which is a multiclassifier prepared to deal with both pathological and normal patterns. The results that were obtained proved that the proposed methodology is able to overcome some of the difficulties associated with the choice of the rejection rate of one-class classifiers, and generally contribute to the minimization of the imbalance problem in TLC pattern classification. © 2009 Springer Berlin Heidelberg.
Keywords: Chromatographic analysis; Class imbalance; Classification approach; Classifier performance; Classifiers; Decision levels; Image analysis; Imbalance problem; Learning systems; Lysosomal storage disorder; Multi-classifier; One-class classifier; Optimization; Pathological case; Pattern classification; Pattern recognition; Rejection rates; Thin layer chromatography

Contextual classification of image patches with latent aspect models - Monay, F.; Quelhas, P.; Odobez, J.-M.; Gatica-Perez, D. (Eurasip Journal on Image and Video ProcessingEurasip J. Image Video Process., 2009)
We present a novel approach for contextual classification of image patches in complex visual scenes, based on the use of histograms of quantized features and probabilistic aspect models. Our approach uses context in two ways: (1) by using the fact that specific learned aspects correlate with the semantic classes, which resolves some cases of visual polysemy often present in patch-based representations, and (2) by formalizing the notion that scene context is image-specificwhat an individual patch represents depends on what the rest of the patches in the same image are. We demonstrate the validity of our approach on a man-made versus natural patch classification problem. Experiments on an image collection of complex scenes show that the proposed approach improves region discrimination, producing satisfactory results and outperforming two noncontextual methods. Furthermore, we also show that co-occurrence and traditional (Markov random field) spatial contextual information can be conveniently integrated for further improved patch classification.

Corrected and improved model for educational simulation of neonatal cardiovascular pathophysiology - Zijlmans, M.; Sá-Couto, C.D.; van Meurs, W.L.; Goodwin, J.A.; Andriessen, P. (Simulation in HealthcareSimul. Healthc., 2009)
We identified errors in the software implementation of the mathematical model presented in: Sá Couto CD, van Meurs WL, Goodwin JA, Andriessen P. A model for educational simulation of neonatal cardiovascular pathophysiology. Simul Healthcare 2006;1:4-12. Simulation results obtained with corrected code are presented for future reference. All but one of the simulation results do not differ by more than 9% from the previously published results. The heart rate response to acute loss of 30% of blood volume, simulated with corrected code is stronger than published target data. This modeling error was masked by errors in code implementation. We improved this response and the model by adjusting the gains and adding thresholds and saturations in the baroreflex model. General considerations on identification of model and code errors and model validity are presented. Copyright © 2009 Society for Simulation in Healthcare.
Keywords: aorta coarctation; article; Baroreflex; bleeding; blood pressure; blood volume; Cardiac Output; cardiovascular disease; Cardiovascular Diseases; Cardiovascular physiology; computer program; Computer simulation; Congenital heart defect; congenital heart malformation; diastolic blood pressure; Education, Medical; Erratum; Fallot tetralogy; great vessels transposition; heart output; Heart rate; heart right ventricle pressure; human; Humans; Infant, Newborn; lung pressure; mathematical model; mean arterial pressure; medical education; medical error; methodology; Neonate; Neonatology; newborn; patent ductus arteriosus; pathophysiology; physiology; pressoreceptor reflex; priority journal; simulation; Software Design; systolic blood pressure; Validation; validity; vascular resistance; Verification; vital sign

The correlation between the adsorption of adhesive proteins and cell behaviour on hydroxyl-methyl mixed self-assembled monolayers - Barrias, C.C.; Martins, M.C.L.; Almeida-Porada, G.; Barbosa, M.A.; Granja, P.L. (BiomaterialsBiomaterials, 2009)
The objective of this study was to compare the biological effects of two key cell-adhesive proteins, fibronectin (FN) and vitronectin (VN), upon adsorption onto molecularly-designed model surfaces. Single-component and mixed self-assembled monolayers (SAMs) of alkanethiols on gold with OH and CH 3 terminal groups were prepared at 100%, 65%, 36% and 0% of OH at the surface, to generate a range of surfaces with a simple chemistry and a wettability gradient. FN and VN were adsorbed under non-competitive (single-protein solutions) and competitive (multi-protein solutions) conditions, and compared at different levels: adsorbed amount (radiolabelling), elution, functional presentation of cell-binding domains (ELISA), and role in mediating cell adhesion (antibody-based assay). The observed trends were related to mesenchymal stem cell response in terms of adhesion and overall cell morphology. Under non-competitive conditions, adsorption of both proteins increased with surface hydrophobicity. The presence of competitive proteins significantly decreased the adsorbed amounts, although both proteins were still detected in all SAMs. Adsorption of FN followed a trend similar to that of non-competitive conditions, while adsorption of VN was higher on 100%OH-SAMs. Concerning elution, retention of adsorbed VN was always higher than that of FN. For both proteins, functional presentation of cell-binding domains was more effective on the more hydrophilic 100%OH-SAMs. This fact, coupled to the ability of this type of SAMs to selectively recruit and retain VN in the presence of competitive serum proteins, seems to correlate with the better cell response observed on these surfaces, as compared with hydrophobic 0%OH(100%CH 3)-SAMs. © 2008 Elsevier Ltd. All rights reserved.
Keywords: Adhesion; Adhesiveness; Adsorption; alkane; Animals; article; Biocompatible Materials; Biological Assay; bone marrow; Cattle; cell adhesion; Cell culture; Cell Movement; Cells; Cells, Cultured; cytology; cytoskeleton; Electric currents; Electron energy levels; enzyme linked immunosorbent assay; Fibronectin; Fibronectins; Focal adhesions; Functional groups; Functionalization; gold; human; human cell; Humans; hydrophilicity; hydrophobicity; Hydroxylation; isotope labeling; Mesenchymal stem cell; Mesenchymal Stem Cells; Microscopy, Confocal; Missile bases; Molecular interactions; monoclonal antibody; priority journal; Protein adsorption; protein analysis; protein binding; Protein Structure, Tertiary; Proteins; Self assembled monolayers; Self-assembled monolayers; stem cell; Stem cells; Surface Properties; thiol derivative; Vitronectin

Cytotoxicity evaluation of nanocrystalline diamond coatings by fibroblast cell cultures - Amaral, M.; Gomes, P.S.; Lopes, M.A.; Santos, J.D.; Silva, R.F.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2009)
The cytotoxicity profile of nanocrystalline diamond (NCD) coatings on a Si 3N 4 ceramic was investigated. This material is envisaged to have biomedical dental applications such as burrs and surgical instruments. Two fibroblast cell culture systems were used to address the cytotoxicity of NCD-coated samples: L929 cells (a mouse permanent cell line) and human gingival fibroblasts. Cell behavior was evaluated in terms of cell adhesion, cell viability/proliferation (mitochondrial function, MTT assay) and the pattern of cell growth. Fibroblast cell behavior on standard polystyrene culture plates was used as control, as Si 3N 4 substrates have previously been shown to be biocompatible. NCD coatings provided a suitable surface for cell attachment, spreading and proliferation. Human gingival cells showed a homogeneous cytoplasm spreading, a flattened elongated morphology and a typical parallel alignment on confluent cultures. In comparison, L929 cells denoted a lower cytoplasm expansion, a heterogeneous spreading but a higher proliferation rate. For both cells, after few days, the NCD coating was completely covered with continuous cell layers. As compared to standard polystyrene culture plates, no deleterious or cytotoxic responses were observed with L929 and human fibroblast cell cultures, and in both a slight enhancement in cell proliferation was observed. In addition, the seeded NCD film allowed reproduction of the typical features of the two cell culture systems tested, further suggesting the lack of cytotoxicity of this coating. © 2008 Acta Materialia Inc.
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; animal cell; Animals; article; Biocompatibility; Biomedical dental applications; biomedicine; cell adhesion; Cell Division; cell function; cell growth; Cell Line; cell proliferation; cell spreading; cell structure; cell surface; cell survival; cell viability; ceramics; controlled study; Culture Media; cytoplasm; Cytotoxicity; dentistry; diamond; Fibroblast cell cultures; fibroblast culture; Fibroblasts; gingiva; human; human cell; Humans; material coating; Mice; Microscopy, Electron, Scanning; mitochondrial respiration; mouse; nanocrystal; Nanocrystalline diamond coating; Nanostructures; nonhuman; polystyrene; priority journal; Silicon nitride; Surgical instrument

Decision trees using the minimum Entropy-of-error principle - De Sá, J.P.M.; Gama, J.; Sebastião, R.; Alexandre, L.A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2009)
Binary decision trees based on univariate splits have traditionally employed so-called impurity functions as a means of searching for the best node splits. Such functions use estimates of the class distributions. In the present paper we introduce a new concept to binary tree design: instead of working with the class distributions of the data we work directly with the distribution of the errors originated by the node splits. Concretely, we search for the best splits using a minimum entropy-of-error (MEE) strategy. This strategy has recently been applied in other areas (e.g. regression, clustering, blind source separation, neural network training) with success. We show that MEE trees are capable of producing good results with often simpler trees, have interesting generalization properties and in the many experiments we have performed they could be used without pruning. © 2009 Springer Berlin Heidelberg.
Keywords: Binary decision trees; Binary trees; Blind source separation; Class distributions; decision trees; Electronic medical equipment; entropy; entropy-of-error; Generalization properties; Image analysis; Minimum entropy; Neural network training; Neural networks; New concept; node split criteria; Univariate

The effect of the co-immobilization of human osteoprogenitors and endothelial cells within alginate microspheres on mineralization in a bone defect - Grellier, M.; Granja, P.L.; Fricain, J.-C.; Bidarra, S.J.; Renard, M.; Bareille, R.; Bourget, C.; Amédée, J.; Barbosa, M.A. (BiomaterialsBiomaterials, 2009)
Bone regeneration seems to be dependant on cell communication between osteogenic and endothelial cells arising from surrounding blood vessels. This study aims to determine whether endothelial cells can regulate the osteogenic potential of osteoprogenitor cells in vitro and in vivo, in a long bone defect, when co-immobilized in alginate microspheres. Alginate is a natural polymer widely used as a biomaterial for cell encapsulation. Human osteoprogenitors (HOP) from bone marrow mesenchymal stem cells were immobilized alone or together with human umbilical vein endothelial cells (HUVEC) inside irradiated, oxidized and RGD-grafted alginate microspheres. Immobilized cells were cultured in dynamic conditions and cell metabolic activity increased during three weeks. The gene expression of alkaline phosphatase and osteocalcin, both specific markers of the osteoblastic phenotype, and mineralization deposits were upregulated in co-immobilized HOPs and HUVECs, comparing to the immobilization of monocultures. VEGF secretion was also increased when HOPs were co-immobilized with HUVECs. Microspheres containing co-cultures were further implanted in a bone defect and bone formation was analysed by μCT and histology at 3 and 6 weeks post-implantation. Mineralization was observed inside and around the implanted microspheres containing the immobilized cells. However, when HOPs were co-immobilized with HUVECs, mineralization significantly increased. These findings demonstrate that co-immobilization of osteogenic and endothelial cells within RGD-grafted alginate microspheres provides a promising strategy for bone tissue engineering. © 2009 Elsevier Ltd. All rights reserved.
Keywords: adult; aged; Alginate; Alginates; alginic acid; alkaline phosphatase; animal tissue; Animals; arginylglycylaspartic acid; article; Bioactivity; Biopolymers; Blood vessel prostheses; Blood Vessels; Bone; Bone and Bones; bone defect; Bone defects; Bone formations; Bone marrow mesenchymal stem cells; bone mineralization; Bone Regeneration; Bone regenerations; bone tissue; Bone tissue engineerings; Calcification, Physiologic; Cell communications; Cell culture; Cell encapsulations; cell function; cell growth; Cell immobilization; Cell membranes; cell metabolism; Cells, Cultured; Co immobilizations; Co-culture; coculture; computer assisted tomography; controlled study; Defects; Dynamic conditions; Endothelial Cells; endothelium cell; gene expression; gene expression regulation; Glucuronic Acid; Grafting (chemical); Hexuronic Acids; histology; human; human cell; Human umbilical vein endothelial cells; Humans; Humulus; immobilized cell; Immobilized cells; in vitro study; in vivo study; In-vitro; In-vivo; irradiation; long bone; Long bones; Mesenchymal stem cell; Metabolic activities; Mice; Mice, Nude; microsphere; Microspheres; Middle Aged; Mineralogy; monoculture; mouse; nonhuman; osteoblast; osteocalcin; Osteogenic; Osteogenic potentials; Osteoprogenitor cells; Osteoprogenitors; Oxidation; Peptides; phenotype; Post implantations; priority journal; Self assembly; Sodium compounds; stem cell transplantation; Stem cells; Tissue engineering; umbilical vein; upregulation; Vascular endothelial growth factor (VEGF); X ray analysis; Young Adult

Engineering endochondral bone: In vitro studies - Oliveira, S.M.; Amaral, I.F.; Barbosa, M.A.; Teixeira, C.C. (Tissue Engineering - Part ATissue Eng. Part A, 2009)
Chitosan scaffolds have been shown to possess biological and mechanical properties suitable for tissue engineering and clinical applications. In the present work, chitosan sponges were evaluated regarding their ability to support cartilage cell proliferation and maturation, which are the first steps in endochondral bone formation. Chitosan sponges were seeded with chondrocytes isolated from chicken embryo sterna. Chondrocyte/chitosan constructs were cultured for 20 days, and treated with retinoic acid (RA) to induce chondrocyte maturation and matrix synthesis. At different time points, samples were collected for microscopic, histological, biochemical, and mechanical analyses. Results show chondrocyte attachment, proliferation, and abundant matrix synthesis, completely obliterating the pores of the sponges. RA treatment caused chondrocyte hypertrophy, characterized by the presence of type X collagen in the extracellular matrix and increased alkaline phosphatase activity. In addition, hypertrophy markedly changed the mechanical properties of the chondrocyte/chitosan constructs. In conclusion, we have developed chitosan sponges with adequate pore structure and mechanical properties to serve as a support for hypertrophic chondrocytes. In parallel studies, we have evaluated the ability of this mature cartilage scaffold to induce endochondral ossification. © Copyright 2009, Mary Ann Liebert, Inc. 2009.
Keywords: alkaline phosphatase; Alkaline phosphatase activity; animal; animal cell; animal tissue; Animals; article; biomechanics; Body fluids; Bone; Bone and Bones; Bone formation; Cartilage; cartilage cell; Cell culture; cell damage; cell hypertrophy; cell isolation; cell maturation; Cell membranes; cell proliferation; Cells, Cultured; chick embryo; Chicken embryo; Chitin; chitosan; Chitosan scaffold; Chondrocyte; Chondrocyte maturation; Chondrocytes; Clinical application; collagen type 10; Collagen Type X; controlled study; cytology; DNA; drug effect; embryo; enchondral ossification; Endochondral ossification; enzyme activity; enzymology; Extracellular matrices; extracellular matrix; gene expression profiling; Hypertrophic chondrocytes; in vitro study; In-vitro; Ligaments; Matrix synthesis; Mechanical analysis; Mechanical properties; metabolism; methodology; nonhuman; Pathology; physiology; Porifera; porosity; priority journal; retinoic acid; Retinoic acids; Scaffolds; sponge (Porifera); Sterna; sternum; synthesis; Time points; Tissue engineering; tissue scaffold; Tissue Scaffolds; Tretinoin; Type X collagen

Engineering endochondral bone: In vivo studies - Oliveira, S.M.; Mijares, D.Q.; Turner, G.; Amaral, I.F.; Barbosa, M.A.; Teixeira, C.C. (Tissue Engineering - Part ATissue Eng. Part A, 2009)
The use of biomaterials to replace lost bone has been a common practice for decades. More recently, the demands for bone repair and regeneration have pushed research into the use of cultured cells and growth factors in association with these materials. Here we report a novel approach to engineer new bone using a transient cartilage scaffold to induce endochondral ossification. Chondrocyte/chitosan scaffolds (both a transient cartilage scaffold- experimental-and a permanent cartilage scaffold-control) were prepared and implanted subcutaneously in nude mice. Bone formation was evaluated over a period of 5 months. Mineralization was assessed by Faxitron, micro computed tomography, backscatter electrons, and Fourier transform infrared spectroscopy analyses. Histological analysis provided further information on tissue changes in and around the implanted scaffolds. The deposition of ectopic bone was detected in the surface of the experimental implants as early as 1 month after implantation. After 3 months, bone trabeculae and bone marrow cavities were formed inside the scaffolds. The bone deposited was similar to the bone of the mice vertebra. Interestingly, no bone formation was observed in control implants. In conclusion, an engineered transient cartilage template carries all the signals necessary to induce endochondral bone formation in vivo. © Copyright 2009, Mary Ann Liebert, Inc. 2009.
Keywords: animal; animal experiment; animal tissue; Animals; article; Biological materials; Biomaterials; Bone; Bone and Bones; Bone formation; bone marrow; bone mineralization; Bone repair; bone transplantation; Calcification, Physiologic; Cartilage; cartilage cell; chick embryo; chitosan; Chondrocytes; Computerized tomography; controlled study; Cultured cell; cytology; drug effect; Ectopic bones; ectopic tissue; electron; enchondral ossification; Endochondral ossification; Fourier transform infrared spectroscopy; Growth (materials); Growth factor; Histological analysis; histology; implantation; in vivo study; In-control; In-vivo; infrared spectroscopy; Ligaments; male; metabolism; methodology; Mice; Mice, Nude; micro-computed tomography; Microcomputed tomography; Microscopy, Electron, Scanning; mineral; Minerals; mouse; Mus; Mus musculus; nonhuman; Nude mice; nude mouse; ossification; physiology; priority journal; Prosthesis Implantation; Scaffolds; Scanning electron microscopy; Spectroscopic analysis; Spectroscopy; Spectroscopy, Fourier Transform Infrared; Tissue changes; Tissue engineering; tissue scaffold; Tissue Scaffolds; Tomography; trabecular bone; vertebra

Evaluation of symmetry enhanced sliding band filter for plant cell nuclei detection in low contrast noisy fluorescent images - Marcuzzo, M.; Quelhas, P.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2009)
The study of cell nuclei is fundamental for plant cell Biology research. To obtain information at cellular level, researchers image cells' nuclei which were modified with fluorescence proteins, through laser scanning confocal microscopy. These images are normally noisy and suffer from high background fluorescence, making grey-scale segmentation approaches inadequate for a usable detection. To obtain a successful detection even at low contrast we investigate the use of a particular convergence filter, the Symmetric Sliding Band filter (SSBF), for cell detection. This filter is based on gradient convergence and not intensity. As such it can detect low contrast cell nuclei which otherwise would be lost in the background noise. Due to the characteristics of cell nuclei morphology, a symmetry constrain is integrated in the filter which corrects some inadequate detections and results in a filter response that is more discriminative. We evaluate the use of this filter for cell nuclei detection on the Arabidopsis thaliana root tip, where the nuclei were stained using yellow fluorescence protein. The resulting cell nuclei detection precision is 89%. © 2009 Springer Berlin Heidelberg.
Keywords: Arabidopsis thaliana; Background noise; Band filters; Bioinformatics; Biology imaging; Cell detection; Cell membranes; cell nucleus; Cellular levels; confocal microscopy; Convergence filters; cytology; Filter response; Fluorescence; Fluorescence proteins; Fluorescent images; Image analysis; Laser scanning confocal microscopy; Low contrast; Plant cell culture; Plant cells; Positron emission tomography; Root tip; Yellow fluorescence proteins

Fibronectin-mediated endothelialisation of chitosan porous matrices - Amaral, I.F.; Unger, R.E.; Fuchs, S.; Mendonça, A.M.; Sousa, S.R.; Barbosa, M.A.; Pêgo, A.P.; Kirkpatrick, C.J. (BiomaterialsBiomaterials, 2009)
Chitosan (Ch) porous matrices were investigated regarding their ability to be colonized by human microvascular endothelial cells (HPMEC-ST1.6R cell line) and macrovascular endothelial cells namely HUVECs. Specifically we assessed if previous incubation of Ch in a fibronectin (FN) solution was effective in promoting endothelial cell (EC) adhesion to Ch matrices with different degrees of acetylation (DAs). Upon FN physiadsorption, marked differences were found between the two DAs investigated, namely DA 4% and 15%. While cell adhesion was impaired on Ch with DA 15%, ECs were able to not only adhere to Ch with DA 4%, but also to spread and colonize the scaffolds, with retention of the EC phenotype and angiogenic potential. To explain the observed differences between the two DAs, protein adsorption studies using 125I-FN and immunofluorescent labelling of FN cell-binding domains were carried out. In agreement with the higher cell numbers found, scaffolds with DA 4% revealed a higher number of exposed FN cell-binding domains as well as greater ability to adsorb FN and to retain and exchange adsorbed FN in the presence of competitive proteins. These findings suggest that the DA is a key parameter modulating EC adhesion to FN-coated Ch by influencing the adsorbed protein layer. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Acetylation; Adhesion; Adsorption; angiogenesis; article; Biocompatible Materials; Blood vessel prostheses; cell adhesion; Cell culture; cell invasion; Cell Line; Cell lines; Cell membranes; Cell number; cell proliferation; Cell size; cell spreading; cell survival; Cell-binding domain; Chitin; Chitin/chitosan; chitosan; colony formation; controlled study; Degrees of acetylation; Electric conductivity measurement; Electric currents; Endothelial cell; Endothelial Cells; Endothelialisation; endothelium; endothelium cell; epithelization; Fibronectin; Fibronectins; human; human cell; Human microvascular endothelial cells; Humans; immunofluorescence test; Key parameters; Labels; materials testing; Matrix algebra; Neovascularization, Physiologic; phenotype; porosity; Porous matrixs; priority journal; Protein adsorption; Protein layers; Scaffold; Scaffolds; Self assembly; Tissue engineering; tissue scaffold; umbilical vein

Improving chitosan-mediated gene transfer by the introduction of intracellular buffering moieties into the chitosan backbone - Moreira, C.; Oliveira, H.; Pires, L.R.; Simões, S.; Barbosa, M.A.; Pêgo, A.P. (Acta BiomaterialiaActa Biomater., 2009)
Chitosan was functionalized with imidazole moieties (CHimi) with the aim of improving its buffering capacity and promoting the endosomal escape ability of chitosan-DNA complexes, ultimately increasing their transfection efficiency. 5.6%, 12.9% and 22.1% of the glucosamine residues of chitosan were substituted. Complexes with different molar ratios of primary amines to DNA phosphate anion (N/P) were prepared by a coacervation method. For an N/P > 3, CHimi polymers are able to complex electrostatically with DNA and condense it into positively charged nanostructures (average size 260 nm and zeta potential +16 mV at pH 5.5). In the concentration range 2.5-100 μg ml
Keywords: article; beta galactosidase; Biocompatible Materials; Buffers; Cell Line; cell transport; Chemical structure; chitosan; coacervation; complex formation; controlled study; Cytotoxicity; Diffusion; DNA; Drug Carriers; Drug Compounding; endosome; Gene delivery; Gene transfer; genetic transfection; human; human cell; Humans; imidazole; Kidney; materials testing; nanomaterial; nanoparticle; priority journal; protein expression; proton transport; Tissue engineering; Transfection

In vitro biological characterization of macroporous 3D Bonelike ® structures prepared through a 3D machining technique - Laranjeira, M.S.; Dias, A.G.; Santos, J.D.; Fernandes, M.H. (Materials Science and Engineering CMater. Sci. Eng. C, 2009)
3D bioactive macroporous structures were prepared using a 3D machining technique. A virtual 3D structure model was created and a computer numerically controlled (CNC) milling device machined Bonelike ® samples. The resulting structures showed a reproducible macroporosity and interconnective structure. Macropores size after sintering was approximately 2000 μm. In vitro testing using human bone marrow stroma showed that cells were able to adhere and proliferate on 3D structures surface and migrate into all macropore channels. In addition, these cells were able to differentiate, since mineralized globular structures associated with cell layer were identified. Results obtained showed that 3D structures of Bonelike ® successfully allow cell migration into all macropores, and allow human bone marrow stromal cells to proliferate and differentiate. This innovative technique may be considered as a step-forward preparation for 3D interconnective macroporous structures that allow bone ingrowth while maintaining mechanical integrity. © 2008 Elsevier B.V. All rights reserved.
Keywords: 3-D structures; 3D machining techniques; Biological characterizations; Bone; Bone ingrowths; Bone marrow stroma cells; Bone substitute; Bonelike; Cell layers; Cell migrations; Computer control systems; cytology; Globular structures; Human bone marrow stromal cells; Human bone marrows; In-vitro; Machining; Macro porosities; Macro-pores; Macroporous; Macroporous structures; Mechanical integrities; Porous materials; Sintering; Surface testing; Three dimensional; ®

Induction of notch signaling by immobilization of jagged-1 on self-assembled monolayers - Gonçalves, R.M.; Martins, M.C.L.; Almeida-Porada, G.; Barbosa, M.A. (BiomaterialsBiomaterials, 2009)
Notch signaling is a key mechanism during mammal development and stem cell regulation. This study aims to target and control Notch signaling by ligands immobilization using self-assembled monolayers (SAMs) as model surfaces. Non-fouling substrates were prepared by immersion of gold substrates in (1-Mercapto-11-undecyl)tetra(ethylene glycol) thiol solutions. These surfaces were activated with N,N′-carbonyldiimidazole (CDI) at different concentrations (0, 0.03, 0.3, 3 and 30 mg/ml) and an anti-human IgG, Fc specific fragment antibody (Ab) was covalently bound to EG4-SAMs to guarantee the correct exposure of the Notch ligand Jagged-1/Fc chimera (Jag-1). The presence of Ab and Jag-1 was confirmed by radiolabeling, X-ray photoelectron spectroscopy (XPS), ellipsometry and ELISA. The biological activity of Jag-1-Ab-SAMs was assessed by real-time PCR for Hes-1 family gene expression, a Notch pathway target gene, in HL-60 cell line. Results have shown an increase of the amount of immobilized Ab with increasing surface activator concentrations. Jag-1 concentration also increases with Ab concentration. Interestingly, a higher Jagged-1 exposure and fold increase in Hes-1 expression were obtained for surfaces activated with the lowest concentration of CDI (0.03 mg/ml). These results illustrate the great importance of ligands orientation and exposure, when compared with density. This investigation brings new insights into Notch signaling mechanisms. In particular, Jag-1-Ab-SAMs have shown to be adequate model surfaces to study Notch pathway activation and may provide a basis to develop new interfaces in biomaterials to control Notch mechanism in different cell systems. © 2009 Elsevier Ltd.
Keywords: Activator concentration; Adequate models; Adsorption; Animals; article; Bioactivity; Biological activities; Biological materials; biomaterial; Calcium-Binding Proteins; Carbonyldiimidazole; Cell culture; Cell Line; Cell membranes; cell strain HL 60; Cell system; Chemical activation; Concentration (process); Concentration of; controlled study; Covalently bound; Ethylene; Ethylene Glycol; gene expression; gold; Gold substrates; HL-60 cell line; human; human cell; Human IgG; Humans; Immunoassay; immunoglobulin Fc fragment; Immunoglobulin G; immunoglobulin G antibody; Intercellular Signaling Peptides and Proteins; Jagged1; Ligands; Mammalia; Membrane Proteins; Model surface; Molecular Structure; Nanostructured materials; Nanostructured surfaces; Nonfouling; Notch receptor; Notch signaling; Photoelectron spectroscopy; priority journal; Protein adsorption; protein immobilization; Radiolabeling; Real-time PCR; Receptors, Fc; Receptors, Notch; Recombinant Fusion Proteins; Sams; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; signal transduction; Signaling; stem cell; Surface Properties; Target genes; Tetra; transcription factor HES 1; X ray photoelectron spectroscopy

Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide - Martins, M.C.L.; Curtin, S.A.; Freitas, S.C.; Salgueiro, P.; Ratner, B.D.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2009)
Systemic heparinization, used during haemodialysis to prevent blood clotting on the extracorporeal circuit, leads to a high incidence of hemorrhagic complications. The adverse reactions associated with heparin neutralization using protamine sulphate justify the development of an alternative system for blood deheparinization. The main objective of this work is to design nanostructured surfaces with the capacity to bind heparin from blood in a selective way. A heparin-binding polypeptide, composed of L-lysine and L-leucine (pKL), was synthesized and immobilized, in different concentrations, onto self-assembled monolayers (SAMs) terminated with tetra(ethylene-glycol) (EG4 SAMs). Immobilization was performed using a fixed concentration of pKL after surface activation to different degrees using a range of CDI (N,N′-carbonyldiimidazole) concentrations. Results demonstrated that the presence of pKL increases heparin adsorption to EG4-SAMs, independently of the pKL concentration and the way of immobilization (adsorption or covalent bound). Selectivity towards heparin was successfully achieved on SAMs with low concentrations of immobilized pKL (9-17% of pKL). Surfaces were characterized using ellipsometry, contact angle measurements, Fourier transform infrared reflection absorption spectroscopy (IRAS), atomic force microscopy, and X-ray photoelectron spectroscopy. Heparin adsorption was assessed using IRAS and N-sulphonate- 35S-heparin. Therefore, this study could give a good contribution for the design of blood deheparinization devices. © 2008 Wiley Periodicals, Inc.
Keywords: Absorption spectroscopy; Adsorption; Alternative systems; Amines; Amino acids; Angle measurement; article; Atomic force microscopy; Atomic forces; Atomic spectroscopy; Binding peptides; Blood; Blood clotting; Carbonyl diimidazole; Carbonyldiimidazole; Contact angle; deheparinization; device; Dialysis; Electron energy levels; ellipsometry; Ethylene; Ethylene Glycol; Fourier Transform Infrared; Fourier transforms; Glycols; Haemodialysis; heparin; heparin binding protein; Heparinization; High incidences; Humans; imidazole; immobilization; infrared spectroscopy; leucine; Low concentrations; lysine; Methods; Missile bases; Monolayers; nanomaterial; Nanostructured surfaces; Nanostructures; Peptide immobilization; Peptides; Photoelectron spectroscopy; Polysaccharides; Protein adsorption; protein binding; Renal Dialysis; Self assembled monolayers; Self-assembled monolayers; Sulphate; Surface activations; Surface functionalization; Surface Properties; surface property; tetraethylene glycol; unclassified drug; X ray photoelectron spectroscopy; X-ray photoelectron spectroscopies

Morphology and mechanical properties of injectable ceramic microspheres - Oliveira, S.M.; Barrias, C.C.; Ribeiro, C.C.; Almeida, I.F.; Bahia, M.F.; Barbosa, M.A. (Key Engineering MaterialsKey Eng Mat, 2009)
The aim of this study was to analyze the effect of starting powder granulometry and sintering conditions on the morphological structure and mechanical properties of injectable hydroxyapaptite (HAp) microspheres. The mechanical properties of the microspheres were evaluated, to investigate if their integrity could be maintained during the injection process. To obtain microspheres, HAp powders were dispersed in a sodium alginate solution and spherical particles were prepared by droplet extrusion under a co-axial air stream, coupled with ionotropic gelation in the presence of Ca 2+. This was followed by a sintering process at various temperatures and times. The morphology of microspheres was observed under SEM, diameter measurements were performed in an optical microscope and the compression strength was evaluated using a texture analyzer. Finally, microspheres prepared using lower granulometry HAp powders and sintered at 1200°C for 1 hour presented the best properties and were selected as the most suitable for the envisaged application.
Keywords: Air streams; Apatite; Calcium; Ceramic microspheres; Co-axial; Coagulation; Compression strengths; Diameter measurements; Gelation; Granulometry; hydroxyapatite; Injectable; Injection process; Ionotropic gelations; Mechanical properties; Microspheres; Morphological structures; Morphology and mechanical properties; Optical microscopes; Powders; SEM; Sintering; Sintering conditions; Sintering process; Sodium; Sodium alginates; Spherical particles; Starting powders; Texture analyzers

Neural cell growth on TiO 2 anatase nanostructured surfaces - Collazos-Castro, J.E.; Cruz, A.M.; Carballo-Vila, M.; Lira-Cantú, M.; Abad, L.; del Pino, Á.P.; Fraxedas, J.; San Juan, A.; Fonseca, C.; Pêgo, A.P.; Casañ-Pastor, N. (Thin Solid FilmsThin Solid Films, 2009)
Titanium oxides have anti-inflammatory activity and tunable electrochemical properties that make them attractive materials for biomedical applications. This work investigated the compatibility of nanometric coatings of low-temperature phases of TiO 2 with neurons in 4-day and 10-day cultures, using different cell densities to quantify cell survival and neurite extension. TiO 2 films were prepared by sol-gel and thermal treatment (250-450 °C) of hydrolyzed titanium tetra-isopropoxide on electrically conducting or insulating slides. The conducting substrates were not passivated by the nanometric oxide layer and could be used as electrodes. Characterization of the films showed nano-structured TiO 2 containing exclusively Ti +4 valence in anatase and amorphous phases. When coated with polylysine, all films permitted good neuron attachment and survival for at least ten days in culture. However, they generally reduced neurite growth compared to cell culture borosilicate glass, with dendrites more affected than axons. The analyses of surface topography, hydrophilicity, charge and chemical composition revealed that TiO 2 chemistry was the main factor responsible for neurite inhibition. © 2009 Elsevier B.V. All rights reserved.
Keywords: Amorphous phasis; Anatase; Anti-inflammatory activity; Biomedical applications; Borosilicate glass; Cell culture; cell density; Cell membranes; cell survival; Chemical compositions; Coatings; Conducting substrates; Conductive films; Electrochemical properties; Gelation; Growth kinetics; Heat treatment; Iso-propoxide; Low temperature phasis; Nano-structured; Nanometrics; Nanostructured surface; Nanostructures; Neural cell; Neural cells; Neurite extension; Neurite growth; Neurites; Neurons; Oxide layer; polylysine; Surface topography; Thermal treatment; TiO; Titanium; Titanium dioxide; Titanium oxide; Titanium oxides

A new method for the detection of singular points in fingerprint images - Magalhães, F.; Oliveira, H.P.; Campilho, A.C. (2009 Workshop on Applications of Computer Vision, WACV 2009Workshop Appl. Comput. Vis., WACV, 2009)
Automatic biometric identification based on fingerprints is still one of the most reliable identification method in criminal and forensic applications. A critical step in fingerprint analysis without human intervention is to automatically and reliably extract singular points from the input fingerprint images. These singular points (cores and deltas) not only represent the characteristics of local ridge patterns but also determine the topological structure (i.e., fingerprint type) and largely influence the orientation field. Poincaré Index-based methods are one of the most common for singular points detection. However, these methods usually result in many spurious detections. Therefore, we propose an enhanced version of the method presented by Zhou et al. [13] that introduced a feature called DORIC to improve the detection. Our principal contribution lies in the adoption of a smoothed orientation field and in the formulation of a new algorithm to analyze the DORIC feature. Experimental results show that the proposed algorithm is accurate and robust, giving better results than the best reported results so far, with improvements in the range of 5% to 7%. © 2009 IEEE.
Keywords: Algorithms; Biometric identifications; Biometrics; Computer applications; Computer vision; Critical steps; Fingerprint analysis; Fingerprint images; Forensic applications; Human intervention; Identification method; Orientation fields; Poincare; Ridge patterns; Singular points; Structural optimization; Technical presentations; Topological structure

NPY revealed as a critical modulator of osteoblast function in vitro: New insights into the role of Y1 and Y2 receptors - Teixeira, L.; Sousa, D.M.; Nunes, A.F.; Sousa, M.M.; Herzog, H.; Lamghari, M. (Journal of Cellular BiochemistryJ. Cell. Biochem., 2009)
Neuropeptide Y (NPY) has recently emerged as a potential regulator of bone homeostasis. However, the relevance of NPY's role in osteoblast activity and the biological functions involving NPY receptors in bone homeostasis remain to be clarified. Here we report that chronically elevated NPY levels leaded to a modulation of the level of Y2 receptor expression marked with a transient down and upregulation according to the stage of osteoblast differentiation. We also show that NPY is a negative regulator of Y1 receptor expression. The pharmalogical activation of Y2 receptor with its agonist resulted in similar effect. Functional analysis also revealed the osteogenic potential of NPY with osteoblast phenotype markers being significantly enhanced in osteoprogenitor cells stimulated by NPY, probably due to the down-regulation of Y1 receptor. In contrasts, these cells exhibit a reduction in calcium deposition in extracellular matrix most likely mediated via Y2 receptor signalling. Furthermore, we show that NPY modulates receptor activator of nuclear factor kB (NF-kB) (RANK) ligand and osteoprotegerin, two key factors regulating bone remodelling. Specifically, NPY inhibits the transcriptional activity of RANKL promoter in osteoprogenitor cells and enhances OPG expression in osteoblasts at early stages of differentiation. However, NPY effect on OPG seemed to be unrelated to Y2 receptor activation. Taken together the present data supported the contribution of NPY pathway in bone homeostasis via a direct action on osteoblasts cells. © 2009 Wiley-Liss, Inc.
Keywords: alkaline phosphatase; animal cell; animal tissue; Animals; article; Bone; Bone Marrow Cells; bone remodeling; Calcium; cell activity; cell differentiation; cell function; Cell Line; cell stimulation; controlled study; down regulation; extracellular matrix; gene expression regulation; genetic transcription; Homeostasis; immunoglobulin enhancer binding protein; in vitro study; Mice; neuropeptide Y; neuropeptide Y1 receptor; neuropeptide Y2 receptor; nonhuman; NPY; nuclear factor Y; osteoblast; Osteoblasts; osteoclast differentiation factor; Osteoprotegerin; phenotype; priority journal; promoter region; protein expression; RANK Ligand; Receptors, Neuropeptide Y; Reverse Transcriptase Polymerase Chain Reaction; signal transduction; stem cell; Stromal Cells; upregulation; Y1 receptor; Y2 receptor

NPY signalling pathway in bone homeostasis: Y1 receptor as a potential drug target - Sousa, D.M.; Herzog, H.; Lamghari, M. (Current Drug TargetsCurr. Drug Targets, 2009)
Neuropeptide (NPY) is a neurotransmitter widely distributed in central and peripheral nervous system that has been implicated in several physiological processes through activation of five different Y receptors: Y1, Y2, Y4, Y5, and y6. NPY system has been extensively studied for the last decades due to its implications in a wide variety of physiological processes. For this purpose a diversity of sophisticated animal models and receptors agonists and antagonists has been developed to better understand its actions throughout body homeostasis. Consequently, NPY and its receptors have recently emerged as a potential regulator of bone homeostasis. This is supported by the demonstration of an increase of bone mass in mice lacking Y1 or Y2 receptor genes. Recent findings revealed Y1 receptor as a potential drug target candidate for prevention and treatment of bone loss. Indeed, it has been demonstrated that osteoblasts express Y1 receptor while no other Y receptor was detected in these cells, implicating Y1 receptor signalling in the local control of bone turnover. In this review, we have summarized the findings obtained from studies on NPY system in skeletogenesis focusing on Y1 receptor. © 2009 Bentham Science Publishers Ltd.
Keywords: 1 [1 [3 [(3 piperidyl)]]propyl] 2 [[(4 chlorophenoxyl)methyl]indol 3 yl] 2 (4 piperidylpiperidyl)ethan 1 one; 2 [1 (3 chloro 5 isopropoxycarbonylaminophenyl)ethylamino] 6 [2 (5 ethyl 4 methyl 2 thiazolyl)ethyl] 4 morpholinopyridine; 2 [1 (3 chloro 5 isopropyloxycarbonylaminophenyl)ethylamino] 6 [2 (5 ethyl 4 methyl 1,3 thiazol 2 yl)ethyl] 4 morpholinopyridine; Amino Acid Sequence; animal; Animals; bone development; bone mass; bone remodeling; Bone remodelling; bone turnover; Brain; drug antagonism; drug effect; drug potentiation; drug targeting; genetics; gi 264879a; gr 231118; Homeostasis; human; Humans; ligand; Ligands; ly 357897; metabolism; molecular genetics; Molecular Sequence Data; n alpha [3,3 bis(1 naphthyl)propionyl]dextro arginine n [1 benzyl 2 methoxyethyl]amide; n [1 [4 [[[[4 [(dimethylamino)methyl]cyclohexyl]methyl]amino]iminomethyl]benzyl] 2 oxo 2 (1 pyrrolidinyl)ethyl] alpha [(2 naphthalenylsulfonyl)amino]benzenepropanamide; n2 diphenylacetyl n (4 ureidomethylbenzyl)argininamide; nalpha (diphenylacetyl) n (4 hydroxybenzyl) dextro argininamide; neuropeptide Y; neuropeptide Y receptor; neuropeptide Y receptor agonist; neuropeptide Y receptor antagonist; neuropeptide Y [25 dextro arginine]; neuropeptide Y [26 dextro histidine]; neuropeptide Y [31 leucine 34 proline]; neuropeptide Y [6 arginine 34 proline]; neuropeptide Y [7 phenylalanine 34 proline]; neuropeptide Y1 receptor; neuropeptide Y2 receptor; neuropeptide Y4 receptor; neuropeptide Y5 receptor; neuropeptide Y6 receptor; nonhuman; osteoblast; osteoclast; osteolysis; peptide YY; peptide YY [31 leucine 34 proline]; peptide YY [34 proline]; pharmacological blocking; physiology; protein binding; protein expression; protein family; protein isolation; receptor intrinsic activity; Receptors, Neuropeptide Y; review; signal transduction; unclassified drug; Y1 receptor

Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene delivery vectors - Santos, J.L.; Oramas, E.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (Journal of Controlled ReleaseJ. Control. Release, 2009)
This paper reports the use of different generations of polyamidoamine (PAMAM) dendrimers for the in vitro transfection of mesenchymal stem cells (MSCs). A systematic study was carried out on the transfection efficiency achieved by the PAMAM dendrimers using a β-galactosidase reporter gene system. Transfection results were shown to be dependent upon the generation of dendrimers, the amine to phosphate group ratio and the cell passage number. In all cases, the transfection efficiency was very low. Nevertheless, it was hypothesized that a low transfection level could be sufficient to promote the in vitro differentiation of MSCs towards the osteoblastic lineage. To address this possibility, dendrimers carrying the human bone morphogenetic protein-2 (hBMP-2) gene-containing plasmid were used. All quantitative (alkaline phosphatase activity, osteocalcin secretion and calcium deposition) and qualitative (von Kossa staining) osteogenic markers were significantly stronger in transfected cells when compared to non-transfected ones. This study not only clearly demonstrates that a low transfection level can be sufficient for inducing in vitro differentiation of MSCs to the osteoblast phenotype but also highlights the importance of focusing research on the development of gene delivery vectors in the concrete application. © 2008 Elsevier B.V. All rights reserved.
Keywords: alkaline phosphatase; amine; Amines; animal cell; Animals; article; beta galactosidase; beta-Galactosidase; Bone; Bone morphogenetic protein; bone morphogenetic protein 2; Bone Regeneration; Calcium; Cell culture; cell differentiation; Cell Line; cell lineage; cell survival; Cells; Cells, Cultured; controlled study; dendrimer; Dendrimers; embryo; enzyme activity; Flowcharting; gene expression; Gene transfer; Gene Transfer Techniques; gene vector; Genes, Reporter; genetic transfection; human; human cell; Humans; in vitro study; Kidney; male; Mesenchymal stem cell; Mesenchymal Stem Cells; nonhuman; Nonviral gene delivery; nonviral gene delivery system; Nucleic acids; osteoblast; osteocalcin; Osteogenesis; PAMAM dendrimers; phosphate; plasmid; Plasmids; polyamidoamine; Polyamines; priority journal; protein secretion; Proteins; qualitative analysis; quantitative analysis; rat; Rats; Rats, Wistar; reporter gene; staining

Physical characterization of hydroxyapatite porous scaffolds for tissue engineering - Teixeira, S.; Rodriguez, M.A.; Pena, P.; De Aza, A.H.; De Aza, S.; Ferraz, M.P.; Monteiro, F.J. (Materials Science and Engineering CMater. Sci. Eng. C, 2009)
The present study refers to the preparation and characterization of porous hydroxyapatite scaffolds to be used as matrices for bone regeneration or as specific release vehicles. Ceramics are widely used for bone tissue engineering purposes and in this study, hydroxyapatite porous scaffolds were produced using the polymer replication method. Polyurethane sponges were used as templates and impregnated with a ceramic slurry at different ratios, and sintered at 1300 °C following a specific thermal cycle. The characteristics of the hydroxyapatite porous scaffolds and respective powder used as starting material, were investigated by using scanning electron microscopy, particle size distribution, X-ray diffraction, Fourier transformed infrared spectroscopy and compressive mechanical testing techniques. It was possible to produce highly porous hydroxyapatite scaffolds presenting micro and macropores and pore interconnectivity. © 2008 Elsevier B.V. All rights reserved.
Keywords: Apatite; Bone; Bone regenerations; Bone tissue engineerings; Ceramic materials; Ceramic slurries; Fourier-transformed infrared spectroscopies; hydroxyapatite; infrared spectroscopy; Macro-pores; Mechanical testing; Physical characterizations; Polymer blends; Polymer replications; Polymers; Polyurethane sponges; Pore interconnectivity; Porous hydroxyapatites; Porous scaffolds; Scaffolds; Scanning electron microscopy; Spectroscopic analysis; Starting materials; Thermal cycles; Tissue engineering; X- ray diffractions

Physical, chemical and in vitro biological profile of chitosan hybrid membrane as a function of organosiloxane concentration - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Costa, M.A.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2009)
We attempted to prepare chitosan-silicate hybrid for use in a medical application and evaluated the physico-chemical properties and osteocompatibility of the hybrids as a function of γ-glycidoxypropyltrimethoxysilane (GPTMS) concentration. Chitosan-silicate hybrids were synthesized using GPTMS as the reagent for cross-linking of the chitosan chains. Fourier transform infrared spectroscopy, 29Si CP-MAS NMR spectroscopy and the ninhydrin assay were used to analyze the structures of the hybrids, and stress-strain curves were recorded to estimate their Young's modulus. The swelling ability, contact angle and cytocompatibility of the hybrids were investigated as a function of the GPTMS concentration. A certain fraction of GPTMS in each hybrid was linked at the epoxy group to the amino group of chitosan, which was associated with the change in the methoxysilane group of GPTMS due to hybridization. The cross-linking density was around 80% regardless of the volume of GPTMS. As the content of GPTMS increased, the water uptake decreased and the hydrophilicity of the hybrids increased except when the content exceeded amolar ratio of 1.5, when it caused a decrease. The values of the mechanical parameters assessed indicated that significant stiffening of the hybrids was obtained by the addition of GPTMS. The adhesion and proliferation of the MG63 osteoblast cells cultured on the chitosan-GPTMS hybrid surface were improved compared to those on the chitosan membrane, regardless of the GPTMS concentration. Moreover, human bone marrow osteoblast cells proliferated on the chitosan-GPTMS hybrid surface and formed a fibrillar extracellular matrix with numerous calcium phosphate globular structures, both in the presence and in the absence of dexamethasone. Therefore, the chitosan-GPTMS hybrids are promising candidates for basic materials that can promote bone regeneration because of their controllable composition (chitosan/GPTMS ratio). © 2008 Acta Materialia Inc.
Keywords: (3 glycidyloxypropyl)trimethoxysilane; article; assay; Biocompatibility; Bone Marrow Cells; calcium phosphate; cell adhesion; Cell Line, Tumor; cell proliferation; cell survival; cell viability; Chemical analysis; chitosan; concentration (parameters); controlled study; cross linking; Cross-Linking Reagents; extracellular matrix; human; human cell; Humans; hydrophobicity; in vitro study; infrared spectroscopy; Magnetic Resonance Spectroscopy; Microscopy, Electron, Scanning; molecular hybridization; Nuclear magnetic resonance spectroscopy; Organic-inorganic hybrid; osteoblast; Osteoblasts; Osteocompatibility; physical chemistry; priority journal; Silanes; silicate; siloxane; Siloxanes; Spectrophotometry, Ultraviolet; Spectroscopy, Fourier Transform Infrared; stress strain relationship; structure analysis; surface property; Tissue engineering; unclassified drug; water transport; γ-Glycidoxypropyltrimethoxysilane (GPTMS)

Prediction of neonatal acidemia by computer analysis of fetal heart rate and ST event signals - Costa, A.; Ayres-de-Campos, D.; Costa, F.; Santos, C.; Bernardes, J. (American Journal of Obstetrics and GynecologyAm. J. Obstet. Gynecol., 2009)
Objective: The objective of the study was to evaluate the accuracy of computer analysis of fetal heart rate (FHR) and ST event signals in prediction of neonatal acidemia. Study Design: One hundred forty-eight FHR tracings were evaluated to identify red alerts provided by the system, based on automated analysis of FHR and ST event signals, and compared with the occurrence of umbilical artery acidemia (pH ≤7.05). Results: The presence of red alerts obtained sensitivity of 1.00 (95% confidence interval [CI], 0.56-1.00), specificity of 0.94 (95% CI, 0.89-0.97), positive predictive value (PPV) of 0.47 (95% CI, 0.22-0.72), negative predictive value (NPV) of 1 (95% CI, 0.96-1.00), positive likelihood ratio (PLR) of 17.6 (95% CI, 9.0-34.5), and negative likelihood ratio (NLR) of 0. When limiting analysis to red alerts that did not include ST data, sensitivity was 0.57 (95% CI, 0.20-0.88), specificity was 0.97 (95% CI, 0.92-0.99), PPV was 0.50 (95% CI, 0.17-0.82), NPV was 0.98 (95% CI, 0.93-0.99), PLR was 20.14 (95% CI, 6.3-64.2), and NLR was 0.44 (95% CI, 0.19-1.04). Conclusion: Computer analysis of FHR and ST event signals provide higher accuracy in predicting neonatal academia. © 2009 Mosby, Inc. All rights reserved.
Keywords: acidemia; Acidosis; article; autoanalysis; Cardiotocography; computer analysis; computer assisted; computer prediction; Diagnosis, Computer-Assisted; diagnostic value; Electrocardiography; Female; Fetal heart rate; Fetal hypoxia; Fetal monitoring; fetus electrocardiography; fetus heart rate; Heart Rate, Fetal; human; Humans; Infant, Newborn; major clinical study; male; newborn; newborn acidosis; observational study; pH; Predictive Value of Tests; priority journal; Prospective Studies; prospective study; Reproducibility of Results; sensitivity and specificity; signal transduction; ST segment; umbilical artery

Protein adsorption and clotting time of pHEMA hydrogels modified with C18 ligands to adsorb albumin selectively and reversibly - Gonçalves, I.C.; Martins, M.C.L.; Barbosa, M.A.; Ratner, B.D. (BiomaterialsBiomaterials, 2009)
This work intended to create a nanostructured biomaterial that would bind albumin in a selective and reversible way in order to inhibit the adsorption of other blood proteins and therefore minimize activation of coagulation. Different levels of C18 ligand have been immobilized on poly(2-hydroxyethyl methacrylate) (pHEMA). We hypothesize that samples with intermediate amounts of C18 ligand would allow albumin to recognize them and bind through its hydrophobic pockets specific for long chain fatty acids. Surface characterization has confirmed increasing amounts of C18 ligand on pHEMA as the percentage of C18 in solution increases, with maximum coverage achieved in 10% C18 samples. Adsorption from pure albumin solution revealed a small decrease in albumin adsorption from pHEMA to 1% C18 and 2.5% C18 samples, but on surfaces with 5% or higher C18 the amount of adsorbed albumin increased as the percentage of C18 increased. Competitive adsorption studies in the presence of both albumin and fibrinogen, and in the presence of all plasma proteins showed that 1% C18 and 2.5% C18 were the only surfaces selective for albumin, and that the presence of all plasma proteins may even potentiate albumin adsorption. Reversibility studies demonstrated that both 2.5% C18 and 5% C18 samples exchange 125I-albumin selectively in the presence of both unlabeled albumin and plasma, but 2.5% C18 samples presented higher exchangeability rates (58%). Clotting times using recalcified plasma revealed that samples with none or small amounts of C18 (pHEMA to 5% C18) did not shorten the clotting time compared to the negative control (polystyrene), indicating low activation of the intrinsic coagulation cascade. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Adsorption; article; Biocompatible Materials; Biomaterials; blood clotting time; Blood Coagulation Tests; Body fluids; Clotting time; Coagulation; Coated Materials, Biocompatible; concentration response; controlled study; Fatty acids; fibrinogen; human serum albumin; hydrogel; Hydrogels; hydrophilicity; Ligands; long chain fatty acid; materials testing; Plasmas; PolyHEMA; Polyhydroxyethyl Methacrylate; polymacon; Polymer blends; polystyrene; Polystyrenes; priority journal; Protein adsorption; protein binding; Proteins; Serum Albumin; Surface modification; surface property; Surface treatment

The role of composition, morphology and crystalline structure in the electrochemical behaviour of TiN x thin films for dry electrode sensor materials - Cunha, L.T.; Pedrosa, P.; Tavares, C.J.; Alves, E.; Vaz, F.; Fonseca, C. (Electrochimica ActaElectrochim Acta, 2009)
A morphological, structural and electrochemical study of titanium nitride (TiN x) thin films, obtained by DC reactive sputtering on titanium substrates, was carried out for a wide range of compositions (0 < x < 1.34) aiming a selection of the best coatings for dry biomedical electrodes. The films displayed a columnar-type structure, with morphologies strongly dependent on the composition: a compact and smooth surface was found for the Ti-rich films, (x < 1), whereas the N-rich films, (x ≥ 1) displayed a rough and porous structure. The electrochemical study of the TiN x films was performed in synthetic sweat, aiming at simulating the contact with the skin. The voltammetric analysis showed anodic currents higher for TiN x films than for titanium for low and medium polarization potentials, whereas for potentials beyond 2 V the blocking behaviour of the TiN x films allowed them to display lower current values. The passive dissolution currents in the sub-μA/cm 2 range and the charge transfer resistances of the order of the MΩ proved the excellent stability of all films in sweat conditions. Finally, the electrochemical noise analysis showed that the near-stoichiometric and N-rich films display the lowest noise, being therefore the most suitable for electrode applications, where signals in the microvolt range, such as the electroencephalographic (EEG) signals, are to be monitored. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Anodic currents; Bioelectric phenomena; Biomedical devices; biomedical electrodes; Blocking behaviour; Charge transfer; Charge transfer resistance; Chemical analysis; Crystalline structure; DC reactive sputtering; Dissolution; Dry electrode; EIS; Electrochemical behaviour; Electrochemical corrosion; Electrochemical electrodes; Electrochemical Noise Analysis; Electrochemical studies; Electroencephalographic signals; Ion exchange; morphology; Polarization potential; Porous structures; Selection of the best; Sensor materials; Smooth surface; Sputtering; Thin films; Titanium; Titanium nitride; Titanium substrates; Type structures; Voltammetric analysis

Role of vascular endothelial growth factor in the communication between human osteoprogenitors and endothelial cells - Grellier, M.; Ferreira-Tojais, N.; Bourget, C.; Bareillke, R.; Guillemot, F.; Amédée, J. (Journal of Cellular BiochemistryJ. Cell. Biochem., 2009)
Proper bone remodeling requires an active process of angiogenesis which in turn supplies the necessary growth factors and stem cells. This tissue cooperation suggests a cross-talk between osteoblasts and endothelial cells. This work aims to identify the role of paracrine communication through vascular endothelial growth factor (VEGF) in co-culture between osteoblastic and endothelial cells. Through a well defined direct contact co-culture model between human osteoprogenitors (HOPs) and human umbilical vein endothelial cells (HUVECs), we observed that HUVECs were able to migrate along HOPs, inducing the formation of specific tubular-like structures. VEGF 165 gene expression was detected in the HOPs, was up-regulated in the co-cultured HOPs and both Fit-1 and KDR gene expression increased in co- cultured HUVECs. However, the cell rearrangement observed in co-culture was promoted by a combination of soluble chemoattractive factors and not by VEGF 165 alone. Despite having no observable effect on endothelial cell tubular-like formation, VEGF appeared to have a crucial role in osteoblastic differentiation since the inhibition of its receptors reduced the co-culture-stimulated osteoblastic phenotype. This co-culture system appears to enhance both primary angiogenesis events and osteoblastic differentiation, thus allowing for the development of new strategies in vascularized bone tissue engineering. © 2009 Wiley-Liss, Inc.
Keywords: angiogenesis; article; Cell Communication; cell contact; Cell culture; cell differentiation; cell migration; cell motion; Cell Movement; Cells, Cultured; Co-culture; coculture; Coculture Techniques; controlled study; cytology; Endothelial Cells; endothelium cell; Enzyme Activation; gene expression; gene expression regulation; genetics; human; human cell; Human stem cells; human tissue; Humans; Humulus; messenger RNA; metabolism; Microscopy, Electron, Scanning; Migration; nucleotide sequence; osteoblast; Osteoblasts; Osteogenesis; paracrine signaling; phenotype; priority journal; Receptors, Vascular Endothelial Growth Factor; RNA, Messenger; Scanning electron microscopy; secretion; stem cell; umbilical cord; umbilical vein; upregulation; Vascular Endothelial Growth Factor A; vasculotropin 165; vasculotropin A; vasculotropin receptor; vasculotropin receptor 1; vasculotropin receptor 2; Vegf

Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands - Gonçalves, I.C.; Martins, M.C.L.; Barbosa, M.A.; Naeemi, E.; Ratner, B.D. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2009)
This study focuses on the selective binding of albumin to a nanostructured surfaces to inhibit other blood proteins from adsorbing thereby reducing platelet adhesion and activation. Tetra (ethylene-glycol)-terminated self- assembled monolayers (EG4 SAMs) with different percentages of CI 8 ligands on the surface were characterized by contact angle measurements, X-ray photoelectron microscopy, infrared reflection-absorption spectroscopy, and ellipsometry. A specific surface (2.5% C18 SAM) was found to be selective for human serum albumin (HSA) in the presence of both albumin and fibrinogen (HFG). The importance of this concentration of C18 ligands was stressed in reversibility studies since that surface exchanged almost all the preadsorbed HSA by HSA in solution, but not by HFG. The effect of protein adsorption in the subsequent adhesion and activation of platelets was studied by pre-immersing the surfaces in albumin and plasma before contact with platelets. Scanning electron microscopy and glutaraldehyde induced fluorescence technique images showed that as surfaces got more hydrophobic due to the immobilization of C18 ligands, the number of adherent platelets increased and their morphology changed from round to fully spread. Pre-immersion in HSA led to an 80°/o decrease in platelet adhesion and reduction of activation. Pre-immersion in 1% plasma was only relevant in 2.5% CI 8 SAMs since this was the only surface that demonstrated less adhesion of platelets comparing with buffer pre-immersion. However, they still adsorb more platelets then when HSA was preadsorbed. This was confirmed in competition studies between HSA and plasma that suggested that other plasma proteins were also adsorbing to this surface. © 2008 Wiley Periodicals, Inc.
Keywords: Absorption spectroscopy; Acoustic microscopes; Adhesion; Adsorption; Albumin; Aldehydes; Angle measurement; article; Biological materials; Biomaterials; Blood Platelets; Blood protein; Blood substitutes; Carbon; Cell Shape; chemical composition; Concentration of; Contact angle; controlled study; Ethylene; Ethylene Glycol; ethylene glycol derivative; fibrinogen; Fluorescence technique; glutaraldehyde; gold nanoparticle; human; human serum albumin; Human serum albumins; Humans; hydrophobicity; Infrared reflection absorption spectroscopy; infrared spectroscopy; ligand; Ligands; Nanostructured surface; normal human; Oligo(ethylene glycol); Photoelectron spectroscopy; plasma; Plasma diagnostics; Plasma protein; Plasmas; Platelet adhesion; Platelet Adhesiveness; Platelets; Protein adsorption; protein binding; Proteins; Sams; Scanning electron microscopy; Selective binding; Selective protein adsorption; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; Serum Albumin; Specific surface; Spectrophotometry, Infrared; Surface Properties; surface property; thrombocyte activation; thrombocyte adhesion; thrombocyte shape; X ray photoelectron spectroscopy; X-ray photoelectron microscopy

Sex differences in linear and complex fetal heart rate dynamics of normal and acidemic fetuses in the minutes preceding delivery - Bernardes, J.; Gonçalves, H.; Ayres-de-Campos, D.; Rocha, A.P. (Journal of Perinatal MedicineJ. Perinat. Med., 2009)
Aim: To assess linear and complex heart rate dynamics in relation to fetal gender in normal and acidemic fetuses during the minutes preceding delivery. Methods: Linear and non-linear fetal heart rate indices, namely mean FHR, long-term irregularity index, short-term variability, low and high frequency spectral indices, approximate and sample entropy, were assessed in 36 female and 30 male fetuses, adjusted for gestational age and weight, during the minutes preceding delivery. Analysis was performed in the initial and final minutes of each tracing in fetuses with umbilical artery blood pH at delivery ≥7.20, 7.11-7.19 and ≤7.10. Results: Progression of labor was associated with a significant decrease in non-linear indices and an increase in almost all linear indices, both in female and male fetuses, but changes were more marked in female fetuses. Non-acidemic females showed higher mean FHR in the final minutes of labor, compared with males. Acidemic females had higher linear indices when compared to similar male fetuses. Conclusions: During the minutes preceding delivery, female fetuses express higher linear indices than male fetuses, suggesting greater activation of the autonomic nervous system, while maintaining similar complexity indices, which suggests different reaction and adaptation capabilities to stress and distress. © 2009 by Walter de Gruyter.
Keywords: acidemia; Acidemic fetuses; article; autonomic nervous system; Birth Weight; blood pH; Cross-Sectional Studies; delivery; Delivery, Obstetric; entropy; Entropy and spectral analysis; Female; Fetal Heart; fetus; fetus heart rate; Gestational Age; Heart Rate, Fetal; human; Humans; Hydrogen-Ion Concentration; Intrapartum; labor; Labor, Obstetric; male; Pregnancy; priority journal; Retrospective Studies; Sex Characteristics; sex difference; Umbilical Arteries; umbilical artery

Skin adhesive versus subcuticular suture for perineal skin repair after episiotomy - A randomized controlled trial - Mota, R.; Costa, F.; Amaral, A.; Oliveira, F.; Santos, C.C.; Ayres-de-Campos, D. (Acta Obstetricia et Gynecologica ScandinavicaActa Obstet. Gynecol. Scand., 2009)
Objective. Surgical repair of perineal lesions after delivery is frequently associated with pain and discomfort, interfering with the normal activities of the puerperium. The aim of this study was to compare perineal skin repair after episiotomy with adhesive glue versus a subcuticular suture, regarding the incidence of pain and wound complications. Study design. Randomized clinical trial. Setting. Tertiary care university hospital. Material and methods. One hundred women having mediolateral episiotomy at vaginal delivery were enrolled. They were randomized to receive skin adhesive (n = 53) or subcuticular suture (n = 47) for closure of perineal skin. The main outcome measure was self-evaluated pain in the 30 days following delivery. Secondary outcome measures were technical difficulties reported with the procedure, duration of surgical repair, wound complications observed at 42-68 hours post-partum and re-initiation of sexual activity by 30 days post-partum. Results. No significant differences were observed between the two groups in incidence of technical difficulties and failed procedures, pain during the procedure, wound complications at hospital discharge, self-evaluated measures of pain at 7 and 30 days or re-initiation of sexual activity by 30 days post-partum. The skin adhesive group had a significantly shorter mean duration of the procedure (four minutes less). Conclusion. Perineal skin closure using adhesive glue is faster than subcuticular suture, and associated with a similar incidence of complications and pain in the first 30 days.
Keywords: adult; article; clinical trial; comparative study; controlled clinical trial; controlled study; cyanoacrylic acid octyl ester; edema; episiotomy; Episiotomy closure; Female; granuloma; human; Humans; injury; major clinical study; obstetric care; pain; pain assessment; Perineal repair; perineum; perineum injury; polyglactin; priority journal; questionnaire; randomized controlled trial; sexual intercourse; Skin; Skin adhesive; suture; Suture Techniques; suturing method; Tissue adhesive; Tissue Adhesives; treatment outcome; vaginal delivery; wound closure; wound dehiscence; Wounds and Injuries

3-D biomodelling technology for maxillofacial reconstruction - Oliveira, M.; Sooraj Hussain, N.; Dias, A.G.; Lopes, M.A.; Azevedo, L.; Zenha, H.; Costa, H.; Santos, J.D. (Materials Science and Engineering CMater. Sci. Eng. C, 2008)
Biomodel is a product of rapid prototyping process that represents a new approach for surgical planning and simulation. Biomodels were found to be particularly effective to locate an exact defect with good measurement accuracy and without any risk to the patients' health. These models could provide surgeons a realistic impression of complex structures before surgical intervention, allowing a define diagnosis and a precise preoperative simulation of skeleton modifying interventions. This work reports on the application of innovative 3-D biomodelling technology in the maxillofacial reconstruction. This technology allows for the calculation of the exact contours, angulations, length and general morphology of iliac crest and fibula flaps for maxillofacial reconstruction in a total of 28 clinical cases. Clinical results have shown that by using this technique, much better facial symmetry and improved functionality were achieved after surgery, which resulted in enormous benefits for treated patients. © 2008 Elsevier B.V. All rights reserved.
Keywords: 3D Biomodelling; Biomodels; Complex structures; Concurrent engineering; Facial symmetries; Free flap designing; Health risks; Job analysis; Maxillofacial reconstruction; Measurement accuracies; New approaches; Process engineering; Prototyping processes; Rapid prototyping; Repair; Restoration; Surgical interventions; Surgical planning; Three dimensional

Automatic cell segmentation from confocal microscopy images of the Arabidopsis root - Marcuzzo, M.; Quelhas, P.; Campilho, A.; Mendonça, A.M.; Campilho, A. (2008 5th IEEE International Symposium on Biomedical Imaging: From Nano to Macro, Proceedings, ISBIIEEE Int. Symp. Biomed. Imaging: Nano Macro, Proc., ISBI, 2008)
In vivo observation and tracking of cell division in the Arabidopsis thaliana root meristem, by time-lapse confocal microscopy, is central to biology research. The research herein described is based on large amount of image data, which must be analyzed to determine the location and state of cells. The possibility of automating the process of cell detection/marking is an important step to provide research tools to the biologists in order to ease the search for a special event as cell division. This paper discusses an automatic cell segmentation method, which selects the best cell candidates from a starting watershed based image segmentation. The selection of individual cells is obtained using a Support Vector Machine (SVM) classifier, based on the shape and edge strength of the cells' contour. The resulting segmentation is largely pruned of badly segmented cells, which can reduce the false positive detection of cell division. This is a good result on its own and a starting point for improvement of cell segmentation methodology. ©2008 IEEE.
Keywords: Biological cells; Biomedical image processing; Cell divisions; cell proliferation; Cell segmentation; Cells; confocal microscopy; image processing; Image segmentation; Microscopic examination; Support vector machines; Technical presentations

Biocompatibility evaluation of DLC-coated Si 3N 4 substrates for biomedical applications - Salgueiredo, E.; Vila, M.; Silva, M.A.; Lopes, M.A.; Santos, J.D.; Costa, F.M.; Silva, R.F.; Gomes, P.S.; Fernandes, M.H. (Diamond and Related MaterialsDiamond Relat. Mat., 2008)
DLC coatings are of enormous interest for biotribological applications due to their biocompatibility, auto-lubricious, and non-stick properties. The most demanding implant is the hip joint. Alternative materials to metal alloys are being increasingly investigated aiming low wear debris volume, in any case innocuous wear particles. Silicon nitride (Si 3N 4) ceramics are light, tough, mechanical resistant, inert materials, turning them suitable for high-load medical applications. In this study, Si 3N 4 polished substrates were coated with adherent DLC coatings grown by DC magnetron sputtering to reduce of the friction forces against any antagonist material. Surface characterization results showed that the developed material is quite hydrophobic, with a total surface tension of 45.7 mN/m (polar component: 9.1 mN/m; dispersive component: 36.6 mN/m), and a zeta potential of - 35.0 ± 1.3 mV. In vitro testing using an acellular simulated body fluid (SBF) showed no apatite layer formation ability, as confirmed by SEM observation and analysis of the solution ions concentration with immersion time. MG63 osteoblast-like cells showed poor adhesion on the DLC films but the adherent cells displayed a normal morphology and, as compared to standard polystyrene tissue culture plates, exhibited a higher cell growth rate, suggesting no indication of cytotoxicity. Results suggested that the novel DLC-coated Si 3N 4 biomaterial should be adequate to be used for articular prostheses medical application. © 2007 Elsevier B.V. All rights reserved.
Keywords: Biocompatibility; Biomedical applications; Cell cultures; Coatings; Diamond like carbon films; DLC coatings; Hip joint; hydrophobicity; Magnetron sputtering; Medical applications; Metal alloys; Simulated body fluid (SBF); Tribology; Wear of materials

Biocompatibility of highly macroporous ceramic scaffolds: Cell adhesion and morphology studies - Teixeira, S.; Ferraz, M.P.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2008)
Hydroxyapatite porous scaffolds can be used for tissue engineering applications since they can serve as templates for cell adhesion, proliferation and ultimately for tissue repair. One way to address this issue is to evaluate the cell adhesion using several characterization techniques namely, cytotoxicity assays and cell visualization. On the other hand, when using highly macroporous scaffolds some techniques may not be adequate for evaluation, such as MTT. In this work, cytotoxicity assay (MTS), scanning electron microscopy (SEM) and Confocal laser scanning microscopy (CLSM) were used to evaluate cell adhesion in highly macroporous hydroxyapatite scaffolds. It was possible to observe that some techniques were not suitable to evaluate cell adhesion. In addition, it was shown that for this kind of scaffolds, confocal laser scanning microscopy is a powerful tool for cell adhesion and proliferation evaluation. © 2007 Springer Science+Business Media, LLC.
Keywords: article; Bioassay; Biocompatibility; Biocompatible Materials; cell adhesion; Cell Line, Tumor; cell proliferation; cell structure; Ceramic materials; ceramics; confocal laser microscopy; controlled study; Cytotoxicity; Cytotoxicity assay; Durapatite; human; human cell; Humans; hydroxyapatite; Macroporous ceramic scaffolds; Microscopy, Confocal; Microscopy, Electron, Scanning; Osteoblasts; priority journal; Scanning electron microscopy; Tissue engineering; Tissue Scaffolds

Biodegradable chitosan-silicate porous hybrids for drug delivery - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A. (Key Engineering MaterialsKey Eng Mat, 2008)
Porous chitosan-silicate hybrids were prepared by freeze-drying the precursor sol solutions synthesized from chitosan and 3- glycidoxypropyltrimethoxysilane (GPTMS). Degradability of and the release of cytochrome C in to phosphate buffer saline solution (PBS) were examined as a function of the GPTMS content. The hybrids were less degradable with larger GPTMS contents, and the cytochrome C release profile was so controllable as to give either burst release or slow one due to the GPTMS content. Thus, the present porous chitosan-silicate hybrids were considered applicable to drug delivery systems.
Keywords: biodegradability; Buffer saline solution; chitosan; Chitosan silicate hybrid; Chitosan-silicate hybrid; Drug delivery; Porous materials; Proteins; Silicates; Synthesis (chemical)

Bone ingrowth in macroporous Bonelike ® for orthopaedic applications - Gutierres, M.; Lopes, M.A.; Sooraj Hussain, N.; Lemos, A.F.; Ferreira, J.M.F.; Afonso, A.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Acta BiomaterialiaActa Biomater., 2008)
The aim of this study was to evaluate the biological behaviour of porous scaffold structures of Bonelike ® which is suitable for either direct clinical use or tissue engineering applications. Porous cylindrical specimens 8 × 10 mm were implanted in the lateral aspect of the tibia of 13 patients (mean age 54 years), during osteotomy surgery for the treatment of medial compartment osteoarthritis of the knee. Implanted cylinders were retrieved at the same time as the removal of the blade plates at 3, 6, 9 and 12 months. Scanning electron microscopy and histological evaluations were performed to observe the biological responses of human bone tissue to porous Bonelike ®. The penetration depth was determined for all implantation periods, and after 6 months it was already possible to see new bone in the centre of the implanted cylinders, which gives 100% of penetration depth for all implantations periods except for 3 months when bone could only be seen in the peripherical region. Regarding the percentage of the area covered by new bone calculated from two-dimensional histological sections, values of 53 ± 15, 76 ± 12 and 88 ± 9% were achieved for 6, 9 and 12 months, respectively. Due to its structural features porous Bonelike ® permitted effective vascularization and bone ingrowth, and therefore was fully osteointegrated as shown in the histological surveys. A slow biomaterial degradation with implantation time is envisaged since the material has displayed surface degradation. Bonelike ® scaffolds show potential for complete ingrowth of osseous tissue and restoration of vascularization throughout the defected site. © 2007.
Keywords: adult; aged; article; biomaterial; bone defect; Bone graft; bone growth; Bone Regeneration; Bone Substitutes; bone tissue; Bonelike; clinical article; controlled study; Female; histology; human; human tissue; Humans; implant; knee osteoarthritis; male; materials testing; Microscopy, Electron, Scanning; Middle Aged; molecular scaffold; Orthopaedic; orthopedics; Osseointegration; Osteoarthritis; osteotomy; porosity; Porous materials; priority journal; Prostheses and Implants; Scanning electron microscopy; tibia; Time Factors; Tissue engineering; tissue section; vascularization; ®

Cell-induced response by tetracyclines on human bone marrow colonized hydroxyapatite and Bonelike ® - Gomes, P.S.; Santos, J.D.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2008)
Semi-synthetic tetracyclines are commonly used antibiotics that also seem to play an important role in the modulation of the immuno-inflammatory imbalance, verified in several bone diseases. The association of a therapeutic agent (that prevents bacterial infection and induces tissue formation) to a biomaterial aiming to repair/regenerate bone defects could contribute to a more predictable clinical outcome. The present study intends to evaluate the proliferation and functional activity of osteoblast-induced human bone marrow cells, cultured on the surface of hydroxyapatite (HA) and Bonelike ®, in the presence of therapeutic concentrations of doxycycline and minocycline. First passage bone marrow cells were cultured for 35 days on the surface of HA and Bonelike ® discs, in the absence or presence of 1 μg ml
Keywords: adult; alkaline phosphatase; alkaline phosphatase bone isoenzyme; antimicrobial activity; article; Bacteria (microorganisms); bone infection; bone marrow cell; Bone Marrow Cells; Bone Substitutes; Bonelike; Calcium; calcium phosphate; Cell culture; cell function; cell proliferation; cell survival; cell viability; Cells, Cultured; concentration response; controlled study; Culture Media; culture medium; doxycycline; Durapatite; enzyme activity; extracellular matrix; glass; human; human cell; Humans; hydroxyapatite; implant; Microscopy, Electron, Scanning; Middle Aged; Minerals; minocycline; osteoblast; Osteoblasts; priority journal; Scanning electron microscopy; stroma cell; Tetracycline; tetracycline derivative; Tetracyclines; X-Ray Diffraction

Changes in detrended fluctuation indices with aging in healthy and congestive heart failure subjects - Barquero-Pérez, Ó.; De Sá, J.M.; Rojo-Álvarez, J.L.; Goya-Esteban, R. (Computers in CardiologyComput Cardiol, 2008)
Detrended Fluctuation Analysis (DFA) aims to quantify the fractal correlation properties in nonstationary time series, and it has successfully been applied in the assessment of the Heart Rate Variability (HRV) for cardiac risk stratification purposes. However the physiological meaning of DFA indices and its relation with aging have not yet been completely established. Given that a loss of complexity in the physiological regulation of elderly subjects has been reported in the literature, we hypothesized that DFA indices could be modified by aging. In this work we computed the Hurst exponent (estimated using DFA method) and DFA indices α 1 and α 2 to assess the HRV in healthy and Congestive Heart Failure (CHF) subjects, and we studied the dependence of these indices on aging for both healthy and CHF subjects. We found that only α2 and Hurst exponent, and only in the case of healthy subjects, have significant discrimination capability to distinguish between young and elderly groups, and also that these indices have a steady increase with aging. Therefore, we can conclude that the loss of complexity due to aging can be quantified by changes in the values of α 2 and Hurst exponent.
Keywords: Cardiology; Congestive heart failures; Correlation properties; Detrended fluctuation analysis; DFA methods; Healthy subjects; Heart rate variabilities; Heart valve prostheses; Hurst exponents; Non-stationary time series; Risk analysis; Risk perception; Risk stratifications; Table lookup; Time series; Time series analysis

Characterization of heart rate variability loss with aging and heart failure using sample entropy - Goya-Esteban, R.; De Sá, J.P.M.; Rojo-Álvarez, J.L.; Barquero-Pérez, O. (Computers in CardiologyComput Cardiol, 2008)
Entropy based measures, such as Sample Entropy (SampEn), have been widely used for quantifying the Heart Rate Variability (HRV) for cardiac risk stratification purposes, with the hypothesis that decreasing entropy points to a perturbation of the complex physiological mechanisms or disease. However, in the literature, higher entropy values have been reported for some pathologies than for healthy subjects, which could be due to the use of a threshold value r tuned relative to the signal standard deviation. In the present paper we apply SampEn to assess the variability of the RR time series from healthy subjects and subjects with Congestive Heart Failure (CHF) in order to discriminate between both groups, as well as to characterize the variability loss due to aging. We conclude that the use of a fixed threshold value r in the SampEn algorithm instead of its conventional setting (as a percentage of the standard deviation of each data series), improves the discrimination capabilities between healthy and CHF subjects, and it allows to quantify the loss of HRV due to aging in healthy subjects.
Keywords: Cardiology; Congestive heart failures; Data series; entropy; Entropy values; Fixed thresholds; Healthy subjects; Heart failures; Heart rate variabilities; Heart valve prostheses; Physiological mechanisms; Risk stratifications; Sample entropies; Signal standard deviations; Standard deviations; Table lookup; Time series

Chromatographic pattern classification - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (IEEE Transactions on Biomedical EngineeringIEEE Trans. Biomed. Eng., 2008)
In this paper, we propose and evaluate methodologies for the classification of images from thin-layer chromatography. Each individual sample is characterized by an intensity profile that is further represented into a feature space. The first steps of this process aim at obtaining a robust estimate of the intensity profile by filtering noise, reducing the influence of background changes, and by fitting a mixture of Gaussians. The resulting profiles are represented by a set of appropriate features trying to characterize the state of nature, here spread out over four classes, one for normal subjects and the other three corresponding to lysosomal diseases, which are disorders responsible for severe nerve degeneration. For classification purposes, a novel solution based on a hierarchical structure is proposed. The main conclusion of this paper is that an automatically generated decision tree presents better results than more conventional solutions, being able to deal with the natural imbalance of the data that, as consequence of the rarity of lysosomal disorders, has very few representative cases in the disease classes when compared with the normal population. © 2008 IEEE.
Keywords: Acoustic variables control; Algorithms; article; Chromatographic analysis; Chromatographic pattern features; Chromatographic profiles; Chromatography; Chromatography, Thin Layer; Classification; Diagnosis, Computer-Assisted; Gaussian noise (electronic); Hierarchical classifier; Humans; Hydrolases; imaging; Lysosomal Storage Diseases; lysosome storage disease; mathematical analysis; nerve degeneration; noise; normal distribution; Pattern recognition; Pattern Recognition, Automated; Reproducibility of Results; sensitivity and specificity; Urinalysis

A clinical report of bone regeneration in maxillofacial surgery using bonelike® synthetic bone graft - Sousa, R.C.; Lobato, J.V.; Maurício, A.C.; Hussain, N.S.; Botelho, C.M.; Lopes, M.A.; Santos, J.D. (Journal of Biomaterials ApplicationsJ. Biomater. Appl., 2008)
The objective of this study is to evaluate the osteoconductivity and bioactivity of the Bonelike® graft in repairing surgical cystic bone defects. Bonelike® is implanted in 11 patients, aged between 24 and 53 years with a mean age of 36 years, consisting of 5 men and 6 women. According to the standard follow up protocols, radiological examinations are performed and Bonelike® /bone retrieved samples have been analyzed histologically using non-decalcified sections obtained perpendicular to bone length axis. Radiographic examination and histological results clearly demonstrate an extensive new bone formation apposed on Bonelike® granules with a significant degree of maturation. These clinical applications in maxillary bone defects indicate perfect bone bonding between new bone formed and Bonelike® granules, along with partial surface biodegradation. This quick and effective osteoconductive response from Bonelike® may reduce the time needed to reconstruct the bone defected area of patients. © 2008 Sage Publications.
Keywords: adult; article; Bioactivity; Bone; bone prosthesis; Bone Regeneration; Bone Substitutes; bone transplantation; Bonelike®; clinical trial; facial bone; Facial Bones; Female; Histological studies; histology; human; Humans; Implants (surgical); instrumentation; male; Maxillofacial surgery; methodology; Middle Aged; oral surgery; Pathology; Radiography; Radiology; Regeneration; Surgery; Surgery, Oral; Synthetic bone graft; treatment outcome

Comparative study of nanohydroxyapatite microspheres for medical applications - Mateus, A.Y.P.; Barrias, C.C.; Ribeiro, C.; Ferraz, M.P.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
This study concerns the preparation, physical, and in vitro characterization of two different types of hydroxyapatite (HA) microspheres, which are intended to be used as drug-delivery systems and bone-regeneration matrices. Hydroxyapatite nanoparticles (HA-1 and HA-2) were prepared using the chemical precipitation synthesis with H 3PO 4, Ca(OH) 2, and a surfactant, SDS (sodium dodecyl sulfate), as starting reagents. The HA powders were dispersed in a sodium alginate solution, and spherical particles were obtained by droplet extrusion coupled with ionotropic gelation in the presence of Ca 2+. These were subsequently sintered to produce HA-1 and HA-2 microspheres with a uniform size and interconnected microporosity. Both powders and microspheres were characterized using FTIR and X-ray diffraction. Moreover, SEM and mercury intrusion porosimetry were used to analyze the microspheres, and TEM was used to analyze the powders. Results showed that pure HA and mixtures of HA/β-TCP in the nanometer range and needlelike shape were obtained for HA-1 and HA-2 powders, respectively. Neutral Red, scanning electron microscopy and confocal microscopy were used to evaluate the behavior of osteoblastic-like MG-63 cells cultured on HA microspheres surfaces for 7 days. Results showed that good adhesion and proliferation of osteoblasts on the HA microspheres surface. Cells built bridges between adjacent microspheres, forming microspheres-cells clusters in both types of materials. © 2007 Wiley Periodicals, Inc.
Keywords: alginic acid; analytic method; Apatite; article; Biocompatible Materials; Biological materials; biomaterial; Bone Regeneration; Calcium; calcium hydroxide; calcium phosphate; cell adhesion; Cell Line; cell proliferation; Chemical precipitation; Chemotherapy; Comparative studies; comparative study; controlled study; dodecyl sulfate sodium; Drug delivery; Drug delivery system (DDS); Drug Delivery Systems; Drug dosage; Durapatite; Gelation; human; human cell; Humans; hydroxyapatite; Hydroxyapatite (HAP); Hydroxylation; In vitro characterization; in vitro study; infrared spectroscopy; materials testing; Medical applications; Mercury intrusion porosimetry; microsphere; Microspheres; Nano-hydroxyapatite (n-HA); Nanohydroxyapatite; nanoparticle; nanoparticles; neutral red; osteoblast; Osteoblasts; Particle Size; phosphoric acid; porosity; powder; Powders; precipitation; Precipitation (chemical); reagent; Regeneration (renovating); Scanning electron microscopy; surfactant; synthesis; Synthesis (chemical); X ray diffraction

Data classification with multilayer perceptrons using a generalized error function - Silva, L.M.; Marques de Sá, J.; Alexandre, L.A. (Neural NetworksNeural Netw., 2008)
The learning process of a multilayer perceptron requires the optimization of an error function E (y, t) comparing the predicted output, y, and the observed target, t. We review some usual error functions, analyze their mathematical properties for data classification purposes, and introduce a new one, E Exp, inspired by the Z-EDM algorithm that we have recently proposed. An important property of E Exp is its ability to emulate the behavior of other error functions by the sole adjustment of a real-valued parameter. In other words, E Exp is a sort of generalized error function embodying complementary features of other functions. The experimental results show that the flexibility of the new, generalized, error function allows one to obtain the best results achievable with the other functions with a performance improvement in some cases. © 2008 Elsevier Ltd. All rights reserved.
Keywords: algorithm; Algorithms; analytical error; article; calculation; Classification; Complementary features; Cybernetics; data analysis; Data classification; Data classifications; Data Interpretation, Statistical; Electric loads; entropy; Error functions; learning; Learning processes; mathematical analysis; Mathematical properties; Models, Statistical; Multilayer neural networks; Multilayer perceptron; Multilayer perceptrons; Multilayers; Neural networks; Neural Networks (Computer); Pattern recognition systems; perceptron; Performance improvements; priority journal; Probability density function

Dissimilarity-based classification of chromatographic profiles - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Pattern Analysis and ApplicationsPattern Anal. Appl., 2008)
This paper proposes a non-parametric method for the classification of thin-layer chromatographic (TLC) images from patterns represented in a dissimilarity space. Each pattern corresponds to a mixture of Gaussian approximation of the intensity profile. The methodology comprises various phases, including image processing and analysis steps to extract the chromatographic profiles and a classification phase to discriminate among two groups, one corresponding to normal cases and the other to three pathological classes. We present an extensive study of several dissimilarity-based approaches analysing the influence of the dissimilarity measure and the prototype selection method on the classification performance. The main conclusions of this paper are that, Match and Profile-difference dissimilarity measures present better results, and a new prototype selection methodology achieves a performance similar or even better than conventional methods. Furthermore, we also concluded that simplest classifiers, such as k-NN and linear discriminant classifiers (LDCs), present good performance being the overall classification error less than 10% for the four-class problem. © 2008 Springer-Verlag London Limited.
Keywords: Chromatographic images; Dissimilarity representation; Nearest neighbour classifiers; Prototype selection

Frequency domain and entropy analysis of fetal heart rate: Appealing tools for fetal surveillance and pharmacodynamic assessment of drugs - Gonçalves, H.; Rocha, A.P.; Ayres-de-Campos, D.; Bemardes, J. (Cardiovascular and Hematological Disorders - Drug TargetsCardiovasc. Hematol. Disord. Drug Targets, 2008)
Recently, frequency domain and entropy analysis of fetal heart rate (FHR) have been assessed in several studies, providing new insights into physiologic regulatory mechanisms, constituting appealing tools for pharmacodynamic assessment, namely during fetal life. There is evidence that entropy and frequency domain analysis convey information on cortical and autonomic nervous system activities, respectively. Use of internal versus external FHR acquisition sensors and the signal sampling frequency may dramatically affect results. Most FHR frequency domain indices are significantly increased with rising fetal activity, namely during active wakefulness and active sleep, whereas the opposite occurs with nonlinear indices. This is in favour of increased activity of the autonomous nervous system and decreased activity of the central nervous system complexity control systems, during periods of fetal activity. Progression of labor is associated with a significant increase in FHR frequency domain indices, whereas entropy indices are significantly decreased. This denotes activation of the autonomic nervous system in the final minutes of labour, associated with decreased central nervous system activity. The emerging knowledge on FHR frequency domain and entropy analysis substantiates a continued interest of these methods in evaluation of the fetal pathophysiologic regulatory mechanisms, and opens new perspectives for clinical and pharmacodynamic assessment. © 2008 Bentham Science Publishers Ltd.
Keywords: acidemia; adrenergic receptor stimulating agent; alpha adrenergic receptor blocking agent; anticonvulsive agent; article; atropine; autonomic nervous system function; beta adrenergic receptor blocking agent; betamethasone; Cardiotocography; central depressant agent; central nervous system function; cholinergic receptor blocking agent; chronotropism; Computerized analysis; drug effect; drug mechanism; electronic sensor; entropy; External and internal monitoring; Female; Fetal behavioral states; Fetal heart rate (FHR); Fetal monitoring; fetus; fetus heart rate; fetus monitoring; frequency analysis; Frequency domain and entropy analysis; gestation period; Heart rate variability; Heart Rate, Fetal; human; Humans; instrumentation; labor; lidocaine; local anesthetic agent; magnesium sulfate; mathematical computing; methodology; nonhuman; opiate; pharmacodynamics; physiology; Pregnancy; prenatal screening; propranolol; pulse rate; review; salbutamol; signal detection

Hip fractures cluster in space: An epidemiological analysis in Portugal - De Pina, M.F.; Alves, S.M.; Barbosa, M.; Barros, H. (Osteoporosis InternationalOsteoporosis Int., 2008)
Summary: Using Portuguese hospital registers (2000-2002) we calculated age-standardized incidence rates of hip fractures. Spatial clusters of high incidence rates were found, with annual averages (per 100,000 inhabitants) varying from 154.4 to 572.2 and 77.3 to 231.5 for women and men, respectively. Geographic inequalities in the occurrence of hip fractures were also found. Introduction: The aim of this study was to identify spatial patterns in the incidence of hip fracture in Portugal during the period 2000 to 2002. Methods: From the National Hospital Discharge Register, admissions of patients (50 years of age or more) with low-energy hip fracture were selected. Age-standardized incidence rates in relation to the municipality of the patients' place of residence were calculated. Empirical Bayes estimators were used to smooth the local risk and spatial statistics methods were used to identify spatial clusters. Results: Of 25,634 hip fractures in individuals aged 50 years or more caused by low or moderate impact, 19,759 occurred in women (age, mean±SD, 80.6±8.6 years) and 5,875 in men (age 77.7±10.0 years). Incidence rates increased exponentially with age, being higher in women nation-wide (female to male ratio from 1.5 to 5.1). Significant geographic differences were found: the incidence rates (95% CI) varied from 154.4 (153.6-155.3) to 572.2 (569.5-575.0) in women and 77.3 (76.64-78.05) to 231.5 (229.9-233.0) in men per 100,000 inhabitants. Spatial autocorrelation values (Moran index) were 0.56 and 0.45 for women and men, respectively. Conclusion: Spatial clusters (p<0.0001) of high incidences were identified. Geographic differences in incidence rates were about threefold. Some regions had incidence rates as high as some north European countries. The geographic inequalities could be due to environmental or socioeconomic factors, but further investigation needs to be done to confirm this hypothesis. © 2008 International Osteoporosis Foundation and National Osteoporosis Foundation.
Keywords: adult; Age Distribution; aged; Aged, 80 and over; article; Bayes Theorem; Bone Density; Cluster Analysis; Databases, Factual; falling; Female; fracture; geographic information system; Geographic information systems; hip fracture; Hip fractures; human; Humans; incidence; international classification of diseases; major clinical study; male; Middle Aged; Osteoporosis; Portugal; priority journal; Risk Factors; sex difference; Sex Distribution; Space-Time Clustering; Spatial analysis; Spatial clusters; Spatial dependency

A hybrid approach for arabidopsis root cell image segmentation - Marcuzzo, M.; Quelhas, P.; Campilho, A.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
In vivo observation and tracking of the Arabidopsis thaliana root meristem, by time-lapse confocal microscopy, is important to understand mechanisms like cell division and elongation. The research herein described is based on a large amount of image data, which must be analyzed to determine the location and state of cells. The automation of the process of cell detection/marking is an important step to provide research tools for the biologists in order to ease the search for special events, such as cell division. This paper discusses a hybrid approach for automatic cell segmentation, which selects the best cell candidates from a starting watershed-based image segmentation and improves the result by merging adjacent regions. The selection of individual cells is obtained using a Support Vector Machine (SVM) classifier, based on the shape and edge strength of the cells' contour. The merging criterion is based on edge strength along the line that connects adjacent cells' centroids. The resulting segmentation is largely pruned of badly segmented and over-segmented cells, thus facilitating the study of cell division. © 2008 Springer-Verlag Berlin Heidelberg.
Keywords: Arabidopsis (Arabidopsis thaliana); Arabidopsis thaliana (ELIP); Cell divisions; Cell image segmentation; cell proliferation; Cell segmentation; Cells; confocal microscopy; Digital image storage; Heidelberg (CO); Hybrid approaches; Image analysis; Image data; image processing; Image segmentation; Imaging techniques; In vivo observation; Individual (PSS 544-7); International conferences; Merging; Microscopic examination; Research tools; Root meristem; Strength (IGC: D5/D6); Support Vector Machine (SVM); Support vector machines; Time lapse confocal microscopy

Hybrid chitosan membranes tested in sheep for guided tissue regeneration - Cortez, P.P.; Shirosaki, Y.; Botelho, C.M.; Simões, M.J.; Gartner, F.; Da Costa, R.M.G.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Maurício, A.C. (Key Engineering MaterialsKey Eng Mat, 2008)
Previous in vitro studies confirmed an improved cytocompatibility of chitosan-silicate hybrid membranes over chitosan membranes. The main goal of this study was to assess the in vivo histocompatibility of both membranes through subcutaneous implantations at different time periods, 1 week, 1, 2 and 3 months, using a sheep model. Chitosan membranes elicited an exuberant inflammatory response and were consequently rejected. The hybrid chitosan membranes were not rejected and the degree of inflammatory response decreased gradually until the third month of implantation. Histological evaluation also showed that these membranes can be resorbed in vivo. This study demonstrates that the incorporation of silicate into the chitosan solution improves its histocompatibility, indicating that the hybrid chitosan-silicate membranes are suitable candidates to be used in clinical applications.
Keywords: biodegradability; Biodegradable membrane; Biodegradable membranes; chitosan; Chitosan-silicate hybrid; Guided tissue regeneration (GTR); histology; in vivo study; Membranes; Silicates; Tissue culture

The influence of the risk functional in data classification with MLPs - Silva, L.M.; Embrechts, M.; Santos, J.M.; De Sá, J.M. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
We investigate the capability of multilayer perceptrons using specific risk functionals attaining the minimum probability of error (optimal performance) achievable by the class of mappings implemented by the multilayer perceptron (MLP). For that purpose we have carried out a large set of experiments using different risk functionals and datasets. The experiments were rigorously controlled so that any performance difference could only be attributed to the different risk functional being used. Statistical analysis was also conducted in a careful way. From the several conclusions that can be drawn from our experimental results it is worth to emphasize that a risk functional based on a specially tuned exponentially weighted distance attained the best performance in a large variety of datasets. As to the issue of attaining the minimum probability of error we also carried out classification experiments using non-MLP classifiers that implement complex mappings and are known to provide the best results until this date. These experiments have provided evidence that at least in many cases, by using an adequate risk functional, it will be possible to reach the optimal performance. © Springer-Verlag Berlin Heidelberg 2008.
Keywords: Backpropagation; Complex mapping; Data classification; Data sets; Electric loads; Experiments; Functionals; Minimum probability of error; MLP classifiers; Multi layer perceptron; Multi-layer perceptrons; Multilayer neural networks; Multilayers; Optimal performance; Pattern recognition systems; Probability density function; risks; Statistical analysis; Weighted distance

Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gel-forming ability - Oliveira, S.M.; Barrias, C.C.; Almeida, I.F.; Costa, P.C.; Pena Ferreira, M.R.; Bahia, M.F.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part B Applied BiomaterialsJ. Biomed. Mater. Res. Part B Appl. Biomater., 2008)
The aim of this study was to test the injectability of a bone filler system based on the combination of ceramic microspheres with a gel-like vehicle, for noninvasive surgery. Porous hydroxyapatite microspheres with a uniform size and an average diameter of 535 ± 38 μm were prepared, and their compression strength and friability were tested. The sodium-alginate solution with a concentration of 7.25% (w/v) was used as the vehicle. To promote its in situ gelation, calcium carbonate and D-gluconic-δ-lactone were added to the solution. Microspheres were mixed with the vehicle at different percentages (20-40 wt %). Gelation times in the range of 8-20 min, were obtained, depending on the formulation. Mixtures of HAp microspheres with alginate solution at 7.25% originating a gel in 11 min present an adequate handling time to perform an injection. Their injectability was evaluated using an injection device commonly employed in vertebroplasty surgical procedures, coupled to a texturometer in compression mode. Using an extrusion rate of 0.1 mm/s, the force required to extrude any of the mixtures tested was lower than 100 N. For an extrusion rate of 1 mm/s mixtures with 40 wt % of microspheres were very difficult to inject. Mixtures with 35 wt % of microspheres presented the best compromise between injectability and compression strength of the gelled system. MicroCT analysis revealed a homogeneous distribution of the microspheres inside the vehicle, as well as full interconnection of the intra-microspheres spaces. The compression strength for the gelled systems ranged from 80 kPa (gel itself) to 600 kPa (composite with 40 Wt % of microspheres). © 2008 Wiley Periodicals, Inc.
Keywords: Alginate; alginic acid; Apatite; article; Average diameter; bioengineering; Bone; bone filler system; Bone Substitutes; Calcium; Calcium carbonate; Ceramic; Ceramic microspheres; Coagulation; Colloids; compression; Compression mode; Compression strengths; Compressive Strength; Computerized tomography; Concentration (process); Data compression; Durapatite; Extrusion; Extrusion rates; Fillers; Forming; Gel-forming ability; Gelation; Gels; gluconolactonase; Handling time; Homogeneous distribution; hydrogel; hydroxyapatite; In situ gelation; in situ hybridization; In-situ; Injectability; injection; Injection (oil wells); Micro-CT; microsphere; Microspheres; Mixtures; non invasive procedure; Particle Size; Porous hydroxyapatite; Sodium; Surgery; Surgical procedures; Uniform size; Vehicles; Vertebroplasty

Jaw avascular osteonecrosis after treatment of multiple myeloma with zoledronate - Lobato, J.V.; Maurício, A.C.; Rodrigues, J.M.; Cavaleiro, M.V.; Cortez, P.P.; Xavier, L.; Botelho, C.; Hussain, N.S.; Santos, J.D. (Journal of Plastic, Reconstructive and Aesthetic SurgeryJ. Plast. Reconstr. Aesthetic Surg., 2008)
Purpose: Multiple myeloma, the second most common haematopoietic cancer, which represents the collection of plasma-cell neoplasms that invariably becomes fatal when self-renewing myeloma cells begin unrestrained proliferation. The major clinical manifestation of multiple myeloma is related to the loss of bone through osteolysis. This can lead to pathologic fractures, spinal cord compression, hypercalcaemia, and pain. It is also a major cause of morbidity and mortality in these patients, who frequently require radiation therapy, surgery and analgesic medications. Bisphosphonates are specific inhibitors of osteoclastic activity, and are currently used to prevent bone complications and to treat malignant hypercalcaemia in patients with multiple myeloma, or bone metastases from breast and prostate cancers. Hence, osteonecrosis of the mandible has been reported in three patients from Centro Hospitalar de Vila Nova de Gaia (CHVNG) with multiple myeloma treated for over 18-48 months with intravenous zoledronate, commonly prescribed for multiple myeloma therapy. Although, this report alerts clinicians about the potential complication of bone necrosis in patients receiving bisphosphonate therapy, many questions remain concerning the underlying pathogenesis of this process. Patients and methods: The medical and dental records of three patients with multiple myeloma, who were treated in CHVNG in the past 4 years, were reviewed. These three patients presented exposed bone and osteonecrosis of the mandible, and shared one common clinical feature: all of them were treated with bisphosphonate zoledronate, administered intravenously for long periods. Sequential orthopantomograms (OPGs) and histological evaluation have been analysed from the biopsies of the non healing dental extraction sites of these patients. Results: After a routine dental extraction, these patients developed avascular osteonecrosis of the mandible and secondary bone infection with Actinomyces israelii (actinomycotic osteomyelitis), with no evidence of metastatic disease evaluated by biopsy. In these three described clinical cases, surgical debridment without flap elevation, intensive antibiotherapy and the suspension of the zoledronate treatment allowed a partial recovery of the patients. The purpose of this clinical report is to point out that patients suffering from multiple myeloma can develop bone osteonecrosis induced by treatment with bisphosphonates. Research to determine the mechanism of this dental phenomenon is needed to fully validate and substantiate the possible link between bisphosphonate treatment of multiple myeloma or other cancer diseases and avascular osteonecrosis of the jaws. Until then, clinicians involved in the care of patients at risk should consider this possible complication. © 2006 British Association of Plastic, Reconstructive and Aesthetic Surgeons.
Keywords: Actinomyces israelii; adult; aged; amoxicillin; antibiotic therapy; article; avascular necrosis; Avascular osteonecrosis; biopsy; Bisphosphonates; Bone Density Conservation Agents; case report; clinical feature; cyclophosphamide; cyclosporin; dexamethasone; Diphosphonates; drug induced disease; drug inhibition; drug withdrawal; erythropoietin; Female; histology; human; Humans; hypercalcemia; Imidazoles; Jaw; jaw avascular osteonecrosis; male; Mandibular Diseases; morbidity; mortality; Multiple myeloma; osteolysis; Osteonecrosis; pain; panoramic radiography; pathologic fracture; priority journal; Radiography, Panoramic; risk assessment; spinal cord compression; thalidomide; tooth extraction; zoledronic acid

Joint detection of the carotid boundaries in longitudinal B-mode images - Rocha, R.; Campilho, A.; Silva, J. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
This paper proposes a new approach for the automatic segmentation of the carotid adventitia in longitudinal B-scans, with and without the presence of plaque. The top and bottom adventitia contours are jointly detected with a 3D dynamic programing scheme that searches for the best pair of boundaries according to a specified fuzzy cost function. Some discriminating features of the adventitia in B-mode images are used to reduce the attraction by other edges. The final contours are filtered with a smoothing spline fitting. The proposed approach was quantitatively evaluated in a set of 38 images. In order to avoid high correlation of the results, a maximum of two images was selected from each patient. The carotid boundaries manually traced by a medical expert were used as the ground truth. Several statistics show that the proposed algorithm gives good results in most of the cases, including many poor quality images. Examples of the detected contours are presented and compared with the ground truth. © 2008 Springer-Verlag Berlin Heidelberg.
Keywords: Automatic segmentations; B-Mode imaging; Edge detection; Fuzzy costs; Ground truth; Heidelberg (CO); Image analysis; Image enhancement; Imaging techniques; International conferences; Joint detection (JD); Medical experts; New approaches; Regression analysis; Smoothing splines

LEGClust - A clustering algorithm based on layered entropic subgraphs - Santos, J.M.; De Sá, J.M.; Alexandre, L.A. (IEEE Transactions on Pattern Analysis and Machine IntelligenceIEEE Trans Pattern Anal Mach Intell, 2008)
Hierarchical clustering is a stepwise clustering method usually based on proximity measures between objects or sets of objects from a given data set. The most common proximity measures are distance measures. The derived proximity matrices can be used to build graphs, which provide the basic structure for some clustering methods. We present here a new proximity matrix based on an entropic measure and also a clustering algorithm (LEGClust) that builds layers of subgraphs based on this matrix, and uses them and a hierarchical agglomerative clustering technique to form the clusters. Our approach capitalizes on both a graph structure and a hierarchical construction. Moreover, by using entropy as a proximity measure we are able, with no assumption about the cluster shapes, to capture the local structure of the data, forcing the clustering method to reflect this structure. We present several experiments on artificial and real data sets that provide evidence on the superior performance of this new algorithm when compared with competing ones. © 2007 IEEE.
Keywords: algorithm; Algorithms; article; artificial intelligence; automated pattern recognition; Cluster Analysis; Clustering; Clustering algorithms; computer assisted diagnosis; Distance measurement; Entropic subgraphs; entropy; Graph theory; Graphs; Hierarchical clustering; Hierarchical systems; Image enhancement; Image Interpretation, Computer-Assisted; Imaging, Three-Dimensional; methodology; Pattern Recognition, Automated; reproducibility; Reproducibility of Results; sensitivity and specificity; three dimensional imaging

Linear and complex heart rate dynamics vary with sex in relation to fetal behavioural states - Bernardes, J.; Gonçalves, H.; Ayres-de-Campos, D.; Rocha, A.P. (Early Human DevelopmentEarly Hum. Dev., 2008)
Background: A better understanding of gender influences on fetal heart rate can help to improve analysis of the latter and perhaps elucidate the increased risk of perinatal death that occurs in males. Aim: To assess differences in linear and complex heart rate dynamics according to fetal sex, in the antepartum period of normal term pregnancies, for patterns associated with fetal behavioural states. Study design and subjects: One hundred and eighty seven fetal heart rate segments of 10-minute duration, acquired with a system for computerized analysis of cardiotocograms and classified into fetal behavioural patterns A, B, C or D were analysed. They had been acquired from 24 female and 23 male term fetuses, with uneventful perinatal outcomes. Four different comparative studies between female and male fetuses were conducted, considering different adjustments for gestational age, weight and FHR pattern. Outcome measures: Indices of linear and nonlinear fetal heart rate variability, namely, long-term irregularity index, very low, low and high frequency spectral indices, approximate entropy and sample entropy. Results: Pattern B was the most frequent, both in female and male fetuses. Pattern A was more likely to be associated to female than male fetuses, whereas the opposite occurred with patterns C and D. Linear indices were significantly higher in male than in female fetuses, whereas the opposite occurred with nonlinear indices. Conclusions: Male fetuses exhibited significantly more linear and significantly less complex fetal heart rate activity than female fetuses, expressing signs of a more active autonomous nervous system and of less active complexity control systems. These aspects may need to be considered when interpreting FHR tracings. © 2007 Elsevier Ireland Ltd. All rights reserved.
Keywords: article; Behavior; Cardiotocography; comparative study; Computerized analysis; Entropy and spectral analysis; Female; Fetal behavioural states and sex; Fetal heart rate; Fetal monitoring; Fetal Movement; fetus; fetus heart rate; Gestational Age; heart hemodynamics; Heart Rate, Fetal; human; Humans; male; normal human; Pregnancy; Pregnancy Outcome; Sex Characteristics; sex difference; SisPorto

Linear and nonlinear heart-rate analysis in a rat model of acute anoxia - Gonçalves, H.; Henriques-Coelho, T.; Bernardes, J.; Rocha, A.P.; Nogueira, A.; Leite-Moreira, A. (Physiological MeasurementPhysiol. Meas., 2008)
The objective of this study was the assessment of heart-rate (HR) dynamics with linear and nonlinear methods during episodes of mechanical ventilation and acute anoxia in rats. Namely, to assess whether linear and nonlinear HR analysis was able to discriminate acute anoxia from baseline in rats and if this was consistent with human foetal and adult studies. Five HR segments of 1 min duration, during baseline recording, mechanical ventilation and first, second and third minutes of induced acute anoxia, were analysed in ten adult Wistar rats. Linear time and frequency domain and nonlinear methods were used, namely mean HR (mHR), long-term irregularity (LTI), interval index (II), low frequency (LF) and high frequency (HF), approximate entropy (ApEn) and sample entropy (SampEn). New parameters for the entropy indices are proposed for the analysis of rats' HR. Bootstrap percentile confidence intervals and nonparametric statistical tests were used in the evaluation of the differences between segments. During mechanical ventilation a clear spectral band was detectable at the ventilation rate, but mHR, II and the 'new' entropy indices were the only significantly changed indices. In the transition from baseline-mechanical- ventilation to mechanical-ventilation-induced anoxia, a statistically significant decrease of mHR, II and entropy indices was observed, clearly discriminating these two instances, whereas most linear indices increased. With continued anoxia, most linear indices decreased significantly, whereas entropy remained stably low. These results are consistent with other foetal human and non-human studies and evidence that the rat model may be used for further research on linear and nonlinear analysis of heart-rate dynamics. The transition from baseline to acute anoxia was encompassed by signs of increased activation of the autonomic nervous system sympathetic branch, and decreased or blunted activity of the HR complexity regulatory centres. © 2008 Institute of Physics and Engineering in Medicine.
Keywords: acute disease; animal experiment; animal model; Animals; Anoxia; article; artificial ventilation; bootstrapping; controlled study; entropy; Female; Fetal monitoring; frequency analysis; Heart rate; Heart rate variability; Humans; Linear analysis; linear system; lung ventilation; Models, Cardiovascular; nonhuman; nonlinear system; priority journal; rat; Rats; Rats, Wistar; Rattus; Rattus norvegicus; Respiration, Artificial; Statistical analysis; Variability; Wistar rat; Wistar rats

A list scheduling algorithm for scheduling multi-user jobs on clusters - Barbosa, J.; Monteiro, A.P. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
This paper addresses the problem of scheduling multi-user jobs on clusters, both homogeneous and heterogeneous. A user job is composed by a set of dependent tasks and it is described by a direct acyclic graph (DAG). The aim is to maximize the resource usage by allowing a floating mapping of processors to a given job, instead of the common mapping approach that assigns a fixed set of processors to a user for a period of time. The simulation results show a better cluster usage. The scheduling algorithm minimizes the total length of the schedule (makespan) of a given set of parallel jobs, whose priorities are represented in a DAG. The algorithm is presented as producing static schedules although it can be adapted to a dynamic behavior as discussed in the paper. © 2008 Springer Berlin Heidelberg.
Keywords: Cluster computing; Dynamic behaviors; Electric load shedding; High performance liquid chromatography; List scheduling; Paper addresses; Parallel algorithms; Parallel task; Resource usage; Scheduling; Scheduling algorithms; Simulation results; Static and dynamic scheduling; Total length

Microstructure, mechanical properties and chemical degradation of brazed AISI 316 stainless steel/alumina systems - Paiva, O.C.; Barbosa, M.A. (Materials Science and Engineering AMater. Sci. Eng. A, 2008)
The main aims of the present study are simultaneously to relate the brazing parameters with: (i) the correspondent interfacial microstructure, (ii) the resultant mechanical properties and (iii) the electrochemical degradation behaviour of AISI 316 stainless steel/alumina brazed joints. Filler metals on such as Ag-26.5Cu-3Ti and Ag-34.5Cu-1.5Ti were used to produce the joints. Three different brazing temperatures (850, 900 and 950 °C), keeping a constant holding time of 20 min, were tested. The objective was to understand the influence of the brazing temperature on the final microstructure and properties of the joints. The mechanical properties of the metal/ceramic (M/C) joints were assessed from bond strength tests carried out using a shear solicitation loading scheme. The fracture surfaces were studied both morphologically and structurally using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and X-ray diffraction analysis (XRD). The degradation behaviour of the M/C joints was assessed by means of electrochemical techniques. It was found that using a Ag-26.5Cu-3Ti brazing alloy and a brazing temperature of 850 °C, produces the best results in terms of bond strength, 234 ± 18 MPa. The mechanical properties obtained could be explained on the basis of the different compounds identified on the fracture surfaces by XRD. On the other hand, the use of the Ag-34.5Cu-1.5Ti brazing alloy and a brazing temperature of 850 °C produces the best results in terms of corrosion rates (lower corrosion current density), 0.76 ± 0.21 μA cm
Keywords: Active metal brazing; Alumina; Bond strength (materials); Brazing; Electrochemical degradation; Filler metals; fracture; Interface composition; Metal/ceramic joining; Metallic matrix composites; morphology; Processing parameters; Shear strength; Stainless steel

Minimizing the imbalance problem in chromatographic profile classification with one-class classifiers - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
This paper presents a new classification approach to deal with class imbalance in TLC patterns, which is due to the huge difference between the number of normal and pathological cases as a consequence of the rarity of LSD diseases. The proposed architecture is formed by two decision stages: the first is implemented by a one-class classifier aiming at recognizing most of the normal samples; the second stage is a hierarchical classifier which deals with the remaining outliers that are expected to contain the pathological cases and a small percentage of normal samples. We have also evaluated this architecture by a forest of classifiers, using the majority voting as a rule to generate the final classification. The results that were obtained proved that this approach is able to overcome some of the difficulties associated with class imbalance. © 2008 Springer-Verlag Berlin Heidelberg.
Keywords: Class imbalances; Classification (of information); Classification approach; Classifiers; Heidelberg (CO); Hierarchical classifiers; Image analysis; Imaging techniques; Imbalance problems; International conferences; Learning systems; Majority voting; Pathological cases

Molecular epidemiology of pseudomonas aeruginosa clinical isolates from Portuguese Central Hospital - Fonseca, A.P.; Correia, P.; Extremina, C.I.; Sousa, J.C.; Tenreiro, R.; Barros, H. (Folia MicrobiologicaFolia Microbiol., 2008)
The relatedness between clinical isolates of P. aeruginosa obtained from patients during their stay in a Portuguese Central Hospital was evaluated. Genotypic fingerprinting (M13-PCR), phenotypic methods (biotyping and antibiotyping) and epidemiological information (spatial and temporal links) were used to evaluate the relatedness between 88 clinical isolates (68 patients), selected randomly out of 189. Sixty-two M13 types were found, 12 of them containing isolates from more than one patient. Thirty-four antibiotypes were found, as well as a significant association (p < 0.05) between epidemic isolates and multiresistance patterns. The nosocomial transmission of P. aeruginosa strains may be limited since M13 typing demonstrated a high degree of diversity among all the isolates, suggesting the occurrence of mainly independent infectious episodes. The results show the possible occurrence of cross-acquisition, cross-colonization and cross-infection and suggest an epidemic population structure for P. aeruginosa in this hospital.
Keywords: antibiotic resistance; article; bacterial DNA; cross infection; disease transmission; DNA, Bacterial; Drug Resistance, Microbial; Electrophoresis, Gel, Pulsed-Field; epidemiology; genetics; genotype; Hospitals, Teaching; human; Humans; isolation and purification; microbiology; polymerase chain reaction; Portugal; Pseudomonas aeruginosa; Pseudomonas infection; Pseudomonas Infections; pulsed field gel electrophoresis; Sampling Studies; statistics; teaching hospital

Nanocrystalline diamond as a coating for joint implants: Cytotoxicity and biocompatibility assessment - Amaral, M.; Gomes, P.S.; Lopes, M.A.; Santos, J.D.; Silva, R.F.; Fernandes, M.H. (Journal of NanomaterialsJ. Nanomater., 2008)
Nanocrystalline diamond (NCD) coatings combine a very low surface roughness with the outstanding diamond properties, such as superlative hardness, low self-friction coefficient, high wear and corrosion resistance, and biotolerance, which are ideal features for applications in medicine (knee and hip replacement) and surgical tools. The present work presents a comprehensive study of the cytotoxicity and biocompatibility of NCD films grown by hot-filament chemical vapour deposition (HFCVD) technique, aiming such future applications. Cytotoxicity was evaluated in vitro by seeding human gingival fibroblasts on the NCD surface for 14 days, while specific biocompatibility was assessed on samples seeded with human bone marrow-derived osteoblasts during 21 days. The NCD coatings proved to be noncytotoxic in the preliminary human gingival fibroblast cell cultures, as denoted by a notable sequence of cell attachment, spreading, and proliferation events. In the specific biocompatibility assay envisaging bone tissue applications, NCD coatings induced human osteoblast proliferation and the stimulation of differentiation markers, compared to standard polystyrene tissue culture plates. Copyright © 2008.

Nanocrystalline diamond: In vitro biocompatibility assessment by MG63 and human bone marrow cells cultures - Amaral, M.; Dias, A.G.; Gomes, P.S.; Lopes, M.A.; Silva, R.F.; Santos, J.D.; Fernandes, M.H. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
Nanocrystalline diamond (NCD) has a great potential for prosthetic implants coating. Nevertheless, its biocompatibility still has to be better understood. To do so, we employed several materials characterization techniques (SEM, AFM, micro-Raman spectroscopy) and cell culture assays using MG63 osteoblast-like and human bone marrow cells. Biochemical routines (MTT assays, Lowry's method, ALP activity) supported by SEM and confocal microscopy characterization were carried out. We used silicon nitride (Si 3N 4) substrates for NCD coatings based on a previous demonstration of the superior adhesion and tribological performance of these NCD coated ceramics. Results demonstrate an improved human osteoblast proliferation and the stimulation of differentiated markers, like ALP activity and matrix mineralization, compared with standard polystyrene tissue culture plates. The nanometric featuring of NCD, associated to its chemical affinity are key points for bone regeneration purposes. © 2007 Wiley Periodicals, Inc.
Keywords: adult; alkaline phosphatase; ALP activity; Animal cell culture; Architectural acoustics; article; Atomic force microscopy; Biocompatibility; Bone; bone marrow cell; Bone Marrow Cells; Bone Regeneration; Cell culture; cell proliferation; cell survival; Cells; Cells, Cultured; ceramics; Cladding (coating); Coated Materials, Biocompatible; confocal microscopy; controlled study; diamond; Diamonds; enzyme activity; extracellular matrix; human; Human bone marrow cells; human cell; Humans; Imaging techniques; Implants (surgical); In vitro biocompatibility; in vitro selection; Joint replacement; male; Materials characterization; materials testing; Micro-Raman spectroscopy; Microscopic examination; Microscopy, Atomic Force; Microscopy, Confocal; Microscopy, Electron, Scanning; mineralization; MTT assaying; Nano-crystalline diamond; nanocrystal; Nanocrystalline alloys; Nanocrystalline materials; nanoparticles; Nanostructured materials; Nitrides; Nonmetals; osteoblast; Osteoblasts; polystyrene; Prostheses and Implants; Raman spectrometry; Scanning electron microscopy; Secondary emission; Silicon; Silicon compounds; Silicon nitride; Spectrum Analysis, Raman; Surface Properties; Tissue engineering

Omniview-SisPorto® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis - Ayres-de-Campos, D.; Sousa, P.; Costa, A.; Bernardes, J. (Journal of Perinatal MedicineJ. Perinat. Med., 2008)
Visual analysis of cardiotocograms is poorly reproducible and is currently recognized as the main weakness of the STAN® methodology. The Omniview-SisPorto® 3.5 program is the most recent version of a central monitoring system that provides visual and sound alerts, based on computer analysis of cardiotocographic and ST event features. This paper describes the program's main characteristics and provides an overview of the system's online alerts. Omniview-SisPorto® 3.5 is the first central monitoring system to incorporate computerized analysis of cardiotocographic and ST event features, providing health professionals with online alerts for minor and major changes in monitored signals. The system is currently undergoing extensive clinical evaluation. © 2008 by Walter de Gruyter.
Keywords: article; Cardiotocography; computer program; Computer-assisted; Electrocardiography; Female; Fetal; Fetal hypoxia; Fetal monitoring; fetus hypoxia; fetus monitoring; Heart rate; human; Humans; instrumentation; online system; Pregnancy; priority journal; Signal processing; ST segment

Osteoblast adhesion and morphology on TiO 2 depends on the competitive preadsorption of albumin and fibronectin - Sousa, S.R.; Lamghari, M.; Sampaio, P.; Moradas-Ferreira, P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
This study aims at assessing the influence of the competitive preadsorption of human serum albumin (HSA) and human plasma fibronectin (FN) from binary solutions and 10% plasma on MC3T3-E1 osteoblast adhesion and morphology on two types of TiO 2 substrates. One was commercially pure titanium with a titanium oxide layer formed in an H 2O 2 solution and the other TiO 2 sputtered on Si (Sousa et al., Langmuir 2004; 20:9745-9754.). The strategy applied in the present investigation was to compare osteoblast adhesion to surfaces preadsorbed with HSA, FN, HSA/FN = 1, HSA/FN = 200, and 10% plasma. The adsorption of proteins was evaluated measuring the amount and the effectiveness of binding with radiolabeled proteins, 125I-FN and 125I-HSA. Our results indicated that MC3T3-E1 osteoblast adhesion correlates well with the amounts of FN and HSA adsorbed on TiO 2 surfaces. Also, we found that fewer osteoblasts adhered to both substrates preadsorbed with HSA, HSA/FN = 200, and 10% plasma, after 4 and 24 h, than to the surfaces preadsorbed with FN and HSA/FN = 1. For the latter, FN was able to compensate the inhibitory effect of HSA on osteoblast adhesion. Therefore, the presence of lower amounts of coadsorbed albumin may improve presentation of FN in a more integrin-recognized conformation, suggesting that some degree of molecular packing prevents loss of integrin-binding activity. FN reversibility does not seem to be dependent on the HSA/FN adsorption mass ratio in solution, suggesting that FN competitively adsorbs to TiO 2 in a favorable conformation and does not suffers subsequent conformational changes allowing exchange with other FN molecules in solution. © 2007 Wiley Periodicals, Inc.
Keywords: 2; 3T3 Cells; Adsorption; Albumins; animal cell; Animals; article; binding kinetics; cell adhesion; Coloring Agents; Competitive protein adsorption; controlled study; cytoskeleton; Data Interpretation, Statistical; Fibronectin; Fibronectins; FN; HSA; human serum albumin; hydrogen peroxide; iodine 125; Iodine Radioisotopes; isotope labeling; Mice; Microscopy, Confocal; mouse; neutral red; nonhuman; osteoblast; Osteoblast adhesion; Osteoblasts; Protein radiolabeling; Proteins; Radiology; Solutions; Sterilization; surface property; TiO; Titanium; Titanium dioxide

PLD bioactive ceramic films: The influence of CaO-P 2O 5 glass additions to hydroxyapatite on the proliferation and morphology of osteblastic like-cells - Oliveira, G.M.; Ferraz, M.P.; González, P.G.; Serra, J.; Leon, B.; Pèrez-Amor, M.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2008)
This work consists on the evaluation of the in vitro performance of Ti6Al4V samples PLD (pulsed laser deposition) coated with hydroxyapatite, both pure and mixed with a CaO-P 2O 5 glass. Previous studies on immersion of PLD coatings in SBF, showed that the immersion apatite films did not present the usual cauliflower morphology but replicated the original columnar structure and exhibited good bioactivity. However, the influence of glass associated to hydroxyapatite concerning adhesion, proliferation and morphology of MG63 cells on the films surface was unclear. In this study, the performance of these PLD coated samples was evaluated, not only following the physical-chemical transformations resulting from the SBF immersion, but also evaluating the cytocompatibility in contact with osteoblast-like MG63 cells. SEM and AFM confirmed that the bioactive ceramic PLD films reproduce the substrate's surface topography and that the films presented good adherence and uniform surface roughness. Physical-chemical phenomena occurring during immersion in SBF did not modify the original columnar structure. In contact with MG63 cells, coated samples exhibited very good acceptance and cytocompatibility when compared to control. The glass mixed with hydroxyapatite induced higher cellular proliferation. Cells grown on these samples presented many filipodia and granular structures, typical features of osteoblasts. © 2007 Springer Science+Business Media, LLC.
Keywords: Apatite; Apatite films; Bioactive ceramic films; Bioactive glass; Bioactivity; Bioceramics; Biocompatible Materials; Biofilms; Brassica oleracea var. botrytis; Calcium Compounds; calcium oxide; Cauliflower morphology; cell adhesion; cell proliferation; cell structure; cell survival; ceramics; Columnar structure; conference paper; controlled study; Durapatite; glass; human; human cell; Humans; hydroxyapatite; Lasers; materials testing; Microscopy, Atomic Force; Microscopy, Electron, Scanning; morphology; osteoblast; Osteoblasts; oxide; Oxides; phosphorous pentoxide; Phosphorus Compounds; Polystyrenes; priority journal; Pulsed laser deposition; unclassified drug

Region and graph-based motion segmentation - Monteiro, F.C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
This paper describes an approach for integrating motion estimation and region clustering techniques with the purpose of obtaining precise multiple motion segmentation. Motivated by the good results obtained in static segmentation we propose a hybrid approach where motion segmentation is achieved within a region-based clustering approach taken the initial result of a spatial pre-segmentation and extended to include motion information. Motion vectors are first estimated with a multiscale variational method applied directly over the input images and then refined by incorporating segmentation results into a region-based warping scheme. The complete algorithm facilitates obtaining spatially continuous segmentation maps which are closely related to actual object boundaries. A comparative study is made with some of the best known motion segmentation algorithms. © 2008 Springer-Verlag Berlin Heidelberg.
Keywords: Clustering approach; Comparative studies; Conformal mapping; Estimation; Flow of solids; Graph-based; Heidelberg (CO); Hybrid approaches; Image analysis; Image segmentation; Imaging techniques; Input Images; International conferences; Maps; Motion estimation; Motion information; Motion segmentation; Motion vector (MV); Multi scaling; Multiple motion segmentation; Object boundaries; Region clustering; Region-based; Segmentation maps; Segmentation results; Static segmentation; Variational methods

Structural studies of Na 2O-TiO 2-CaO-P 2O 5 system glasses investigated by FTIR and FT-Raman - Li, Y.; Weng, W.; Santos, J.D.; Lopes, A.M. (Physics and Chemistry of Glasses: European Journal of Glass Science and Technology Part BPhys. Chem. Glasses Euro. J. Glass Sci. Technol. Part B, 2008)
CaO-P 2O 5 based glasses are widely used as biomaterials due to their various chemical compositions, excellent bioactivity, adjustable biodegradation and suitable mechanical properties. The structures of Na 2O-TiO 2-CaO-P 2O 5 system glasses were investigated by FTIR and FT-Raman spectroscopies. The calcium phosphate glasses have chain-like structures based on Ti-O-P linkages containing [P 2O 7] 4- groups and [PO 4] 3- groups. Some amount of TiO 2 enters into the glass network, in which [TiO 4] tetrahedra connect with [PO 4] tetrahedra through the P-O-Ti bonds, the remaining TiO 2 exists into interspaces of [PO 4] tetrahedra. CaO connects the two linkages in the form of Ca-O-P bonds.

Surface characterization and cell response of a PLA/CaP glass biodegradable composite material - Navarro, M.; Engel, E.; Planell, J.A.; Amaral, I.; Barbosa, M.; Ginebra, M.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
Bioabsorbable materials are of great interest for bone regeneration applications, since they are able to degrade gradually as new tissue is formed. In this work, a fully biodegradable composite material containing polylactic acid (PLA) and calcium phosphate (CaP) soluble glass particles has been characterized in terms of surface properties and cell response. Cell cultures were performed in direct contact with the materials and also with their extracts, and were evaluated using the MTT assay, alkaline phosphatase activity, and osteocalcin measurements. The CaP glass and PLA were used as reference materials. No significant differences were observed in cell proliferation with the extracts containing the degradation by-products of the three materials studied. A relation between the materials wettability and the material-cell interactions at the initial stages of contact was observed. The most hydrophilic material (CaP glass) presented the highest cell adhesion values as well as an earlier differentiation, followed by the PLA/glass material. The incorporation of glass particles into the PLA matrix increased surface roughness. SEM images showed that the heterogeneity of the composite material induced morphological changes in the cells cytoskeleton. © 2007 Wiley Periodicals, Inc.
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; Absorbable Implants; alkaline phosphatase; article; Biodegradable composite materials; biodegradable implant; Biodegradation; Bone; Bone Regeneration; Bone Substitutes; calcium phosphate; Calcium phosphates; cell adhesion; Cell culture; cell function; cell interaction; Cell Line; cell proliferation; Cell response; Composite materials; cytoskeleton; glass; human; human cell; Humans; hydrophilicity; hydrophobicity; In vitro test; Lactic Acid; materials testing; Osteoblasts; osteocalcin; polylactic acid; Polymers; scanning electron microscope; Surface analysis; Surface Properties; wettability

Synthesis and cytocompatibility of porous chitosan-silicate hybrids for tissue engineering scaffold application - Shirosaki, Y.; Okayama, T.; Tsuru, K.; Hayakawa, S.; Osaka, A. (Chemical Engineering JournalChem. Eng. J., 2008)
Chitosan-silicate hybrids with 3D porous structures were prepared with freeze-drying precursor solutions derived from chitosan and γ-glycidoxypropyltrimethoxysilane (GPTMS). They were formed easily in any shape, such as sheets, pellets, disks, granules, and even roll-cakes. The pore size was strongly dependent on the freezing temperature: lower freezing temperature resulted smaller pores, about 110 μm for the hybrids frozen at -20 °C, and about 50 μm for those at -85 °C. The pore size was little dependent on the GPTMS content. In contrast, the GPTMS content affected porosity a littlie: ∼80% for chitosan, and ∼90% for the GPTMS-containing hybrids. Thus, their porous microstructure was controllable due to the freezing temperature and composition. MG63 osteoblastic cells were cultured up to 7 days on the porous hybrids. The cells adhered on the pore walls, proliferated, and migrated deep into the pore structure. It was thus concluded that the present chitosan-silicate hybrids were promising for tissue engineering scaffold applications. © 2007 Elsevier B.V. All rights reserved.
Keywords: chitosan; Cytocompatibility; GPTMS; Organic-inorganic hybrid; Osteoblastic cell MG63; Osteoblasts; Pore size; Pore structure; Scaffold; Silicates; Tissue engineering; γ-Glycidoxypropyltrimethoxysilane (GPTMS)

Three dimensional macroporous calcium phosphate scaffolds for bone tissue engineering - Teixeira, S.; Oliveira, S.; Ferraz, M.P.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2008)
Calcium phosphate ceramics are widely used as bone substitutes since they are biocompatible and bioactive. Having a chemical composition close to natural bone, calcium phosphate ceramics are promising bone substitute materials in orthopaedics, maxillofacial surgery and dentistry. Hydroxyapatite (HA) and tricalcium phosphate (TCP) are the most commonly used calcium phosphates, because their calcium/phosphorus (Ca/P) ratios are close to that of natural bone and they are relatively stable in physiological environment. HA is a major constituent of bone materials and is resorbed after a long time of residence in the body. In this work, highly porous hydroxyapatite scaffolds were produced by polymer replication method and their properties evaluated by Scanning Electron Microscopy (SEM) and micro computerized tomography (μ-CT).
Keywords: Biocompatibility; Bone; calcium phosphate; Calcium phosphates; Computerized tomography; Maxillofacial prostheses; Maxillofacial surgery; Micro computerized tomography; Porous; Scaffolds; Scanning electron microscopy; Tissue engineering

Tracking of Arabidopsis thaliana root cells in time-lapse microscopy - Marcuzzo, M.; Quelhas, P.; Mendonça, A.M.; Campilho, A. (Proceedings - International Conference on Pattern RecognitionProc. Int. Conf. Pattern Recognit., 2008)
In vivo observation of cells in the Arabidopsis thaliana root, by time-lapse confocal microscopy, is central to biology research. The research herein described is based on large amount of image data, which must be analyzed to determine the location and state of individual cells. Automating the process of cell tracking is an important step to create tools which will facilitate the analysis of cells' evolution through time. Here we introduce a confocal tracking system designed in two stages. At the image acquisition stage, we track the area under analysis based on point-to-point correspondences and motion estimation. After image acquisition, we compute cell-to-cell correspondences through time. The final result is a temporal structured information about each cell. © 2008 IEEE.
Keywords: Arabidopsis thaliana; Bioinformatics; Cell tracking; confocal microscopy; Image acquisition; Image data; In-vivo; Individual cells; Motion estimation; Pattern recognition; Point correspondence; Root cells; Structured information; Time-lapse microscopy; Tracking system; Two stage

Watershed framework to region-based image segmentation - Monteiro, F.C.; Campilho, A. (Proceedings - International Conference on Pattern RecognitionProc. Int. Conf. Pattern Recognit., 2008)
This paper proposes a new framework to image segmentation which combines edge- and region-based information with spectral techniques through the morphological algorithm of watersheds. A pre-processing step is used to reduce the spatial resolution without losing important image information. An initial partitioning of the image into primitive regions is set by applying a rainfalling watershed algorithm on the image gradient magnitude. This initial partition is the input to a computationally efficient region segmentation process which produces the final segmentation. The latter process uses a region-based similarity graph representation of the image regions. The experimental results clearly demonstrate the effectiveness of the proposed approach to produce simpler segmentations and to compare favourably with state-of-the-art methods. © 2008 IEEE.
Keywords: Computationally efficient; Edge detection; Graph representation; Image gradients; Image information; Image regions; Image segmentation; Landforms; Pre-processing step; Process use; Rainfalling watershed; Region segmentation; Region-based; Spatial resolution; Spectral techniques; State-of-the-art methods; Watersheds

Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation - Amaral, I.F.; Cordeiro, A.L.; Sampaio, P.; Barbosa, M.A. (Journal of Biomaterials Science, Polymer EditionJ. Biomater. Sci. Polym. Ed., 2007)
Chitosan (Ch) is being actively investigated as a non-protein template for the growth of an increasing number of anchorage-dependent cells, including chondrocytes and bone cells. In the present work, Ch films with degrees of N-acetylation (DAs) in the range of 4 to 49% were evaluated with respect to the attachment, spreading and short-term proliferation of osteoblasts, using human osteoblastic MG-63 cells. The films were characterized in terms of surface morphology and surface charge by atomic force microscopy and streaming potential measurements, respectively. Cell attachment was assessed after 3 and 24 h of cell culture. After 24 h of incubation, cell attachment was found to be dependent on the DA, lower DAs favouring cell adhesion. With time, cell spreading and cytoskeleton organization were only attained for DAs ≤ 13%. Regarding cell proliferation, cells grown on films with the lowest DA (4%) revealed a higher specific growth rate as compared to those grown on films with higher DAs. Films with a DA of 49% failed to sustain cell proliferation. In addition, a longer lag-phase was observed on Ch, as compared to TCPS, in accordance to an observed delay of cell spreading. The present findings revealed that differences in the DA as small as 9% may be critical in terms of the osteoblast response to two-dimensional Ch-based matrices. © 2007 VSP.
Keywords: Acetylation; AFM; article; Atomic force microscopy; Biocompatible Materials; biofilm; Biofilms; biomaterial; bone cell; cartilage cell; cell adhesion; cell anchorage; Cell culture; cell growth; Cell Line, Tumor; cell proliferation; Cell Shape; cell spreading; cell survival; Chemical structure; chemistry; Chitin; chitosan; comparative study; controlled study; cytoskeleton; Degree of acetylation; drug effect; Growth kinetics; human; human cell; Humans; incubation time; metabolism; Microscopy, Atomic Force; osteoblast; Osteoblast-like cells; Osteoblasts; Pathology; priority journal; Surface charge; Surface Properties; surface property; Surface treatment; tumor cell line; Zeta potential

Automatic vertebra detection in x-ray images - Moura, D.C.; Correia, M.V.; Barbosa, J.G.; Reis, A.M.; Laranjeira, M.; Gomes, E. (Proceedings of the International Symposium CompIMAGE 2006 - Computational Modelling of Objects Represented in Images: Fundamentals, Methods and ApplicationsProc. Int. Symp. CompIMAGE - Comput. Model. Objects Represent. Images: Fundam., Methods Appl., 2007)
In this paper we will describe our experiments with x-ray image analysis for vertebra detection in juvenile/adolescent patients with idiopathic scoliotic spines. We will focus on detecting vertebrae location in a anterior-posterior x-ray image in a fully automatic way. For accomplishing this, we propose a set of techniques for (i) isolating the spine by removing other bone structures (e.g. ribs), (ii) detecting vertebrae location along the spine using an hierarchical and progressive threshold analysis, and (iii) detecting vertebrae lateral boundaries. © 2007 Taylor & Francis Group.
Keywords: Anterior posteriors; Bone structures; Image analysis; Lateral boundaries; Mammals; Threshold analysis; X ray analysis; X ray apparatus; X-ray images

Characterization of hydroxyapatite sputtered films doped with titanium - Ribeiro, A.R.; Piedade, A.P.; Ribeiro, C.C.; Vieira, M.T.; Barbosa, M.A. (Key Engineering MaterialsKey Eng Mat, 2007)
In the present work, thin films of hydroxyapatite (HAp), titanium, and hydroxyapatite doped with different titanium concentrations were obtained by sputtering and characterized using several analytical techniques. These films are intended to be used as model surfaces on protein adsorption studies in order to better understand the role of titanium ions in biological processes.
Keywords: Adsorption; Biofilms; Doping (additives); hydroxyapatite; Hydroxyapatite sputtered films; Model surfaces; Proteins; Sputtering; Titanium; Titanium ions

Degradation studies of some polymeric biomaterials: Polypropylene PP and polyvinylidene difluoride (PVDF) - Silva, R.A.; Silva, P.A.; Carvalho, M.E. (Materials Science ForumMater Sci Forum, 2007)
Degradation studies of PP and PVDF monofilaments were carried out using a special chamber for several periods of time. One set of the samples was exposed to a 0.9 % NaCl solution and to ultraviolet radiation at 83° C and the other set involved the exposition in air under the same conditions of irradiation and temperature. Scanning Electron Microscopy (SEM) analysis showed direct evidence of PP degradation. Meanwhile, the PVDF monofilaments showed no apparent evidence of degradation under the same conditions. Differential Thermal Analysis (DTA) curves, FTIR spectra and Oxidation Induction Time experiments confirmed the results of SEM Analysis.
Keywords: Biomaterials; Degradation; Degradation of polypropylene and polyvinylidene difiuoride; Fourier transform infrared spectroscopy; FTIR spectroscopy; Monofilament sutures; Monofilaments; Oxidation induction time; Polypropylenes; Redox reactions; Thermal analysis; Thermoanalysis

Detection of lung nodule candidates in chest radiographs - Pereira, C.S.; Fernandes, H.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2007)
This paper presents an automated method for the selection of a set of lung nodule candidates, which is the first stage of a computeraided diagnosis system for the detection of pulmonary nodules. An innovative operator, called sliding band filter (SBF), is used for enhancing the lung field areas. In order to reduce the influence of the blood vessels near the mediastinum, this filtered image is multiplied by a mask that assigns to each lung field point an a priori probability of belonging to a nodule. The result is further processed with a watershed segmentation method that divides each lung field into a set of non-overlapping areas. Suspicious nodule locations are associated with the regions containing the highest regional maximum values. The proposed method, whose result is an ordered set of lung nodule candidate regions, was evaluated on the 247 images of the JSRT database with very promising results. © Springer-Verlag Berlin Heidelberg 2007.
Keywords: Blood Vessels; Computer aided diagnosis; Database systems; Lung nodule candidates; Non-overlapping areas; Pulmonary diseases; Pulmonary nodules; Radiography; Sliding band filter (SBF)

Efficient approximation of the mahalanobis distance for tracking with the Kalman filter - Pinho, R.R.; Tavares, J.M.R.S.; Correia, M.V. (Proceedings of the International Symposium CompIMAGE 2006 - Computational Modelling of Objects Represented in Images: Fundamentals, Methods and ApplicationsProc. Int. Symp. CompIMAGE - Comput. Model. Objects Represent. Images: Fundam., Methods Appl., 2007)
We address the problem of tracking efficiently feature points along image sequences. To estimate the undergoing movement we use an approach based on Kalman filtering which performs the prediction and correction of the features movement in every image frame. In this paper measured data is incorporated by optimizing the global correspondence set based on efficient approximations of the Mahalanobis distances (MD). We analyze the difference between using the MD and its efficient approximation in the tracking results, and also examine the related computational costs. Experimental results which validate our approach are presented. © 2007 Taylor & Francis Group.
Keywords: Computational costs; Control theory; Feature points; Image frames; Image sequences; Kalman filters; Kalman-filtering; Mahalanobis distances; Measured datum

Efficient approximation of the mahalanobis distance for tracking with the Kalman filter - Pinho, R.R.; Tavares, J.M.R.S.; Correia, M.V. (International Journal of Simulation ModellingInt. J. Simul. Model., 2007)
In this paper, we address the problem of tracking feature points along image sequences efficiently. Thus, to estimate the undergoing movement we use an approach based on Kalman filtering, which performs the prediction and correction of the features' movement in every image frame. Measured data is incorporated by optimizing the global association set built on efficient approximations of the Mahalanobis distance (MD). We analyze the difference between the usage in the tracking results of the original MD formulation and its more efficient approximation, as well as the related computational costs. Experimental results which validate our approach are presented.
Keywords: Computational vision; Data association; Kalman filter; Mahalanobis distance; Tracking

Epidemiology of femur fractures in Portugal - Alves, S.F.; Pina, M.D.F.; Barbosa, M. (Epidemiologia das fracturas do fémur em Portugal: Fracturas do colo do fémur versus fracturas de outras localizações não especificadas do fémurArquivos de MedicinaArq. Med., 2007)
Fractures related to osteoporosis have been increasing in many countries. Femoral neck fractures have been widely studied, however little is known about other femur fractures and its relationship with osteoporosis. The main objective of this study is the comparison between the incidence of neck fractures attributed to osteoporosis with the ones that occurs in other places of femur other than the neck, in the same conditions. It was used a national database, under the regulation of a governmental institute, with registers from 2000 to 2002. From the total number of femural fractures the authors selected the registers corresponding to individuals with more than fifty years of age and due to low impact, it were analysed separately the femoral neck fractures (International Classification of Diseases codes, 9 th Revision, Clinical Modification, ICD9-CM codes 820 and derivates) from the fractures that occurred in other locations in the femur (ICD9-CM codes 821 and derivates). Case fatality rates and the incidence rates were calculated for that period of time, and an analysis of the variables age, days and costs of hospital admission as well as of the variable destination after discharge. Only 7.6% of the femural fractures were coded as 821.x, all the others were coded as 820.x. In both groups the fractures were more frequent in women (above 75%) and showed an exponential increase with age. The costs were higher in the 820.x fractures which also presented higher case fatality rates. ©ArquiMed, 2007.
Keywords: adult; aged; article; Female; femur; femur fracture; fracture; hip fracture; human; incidence; Low impact; male; Osteoporosis; outcome assessment; Portugal; risk assessment; survival

Evaluation of contrast enhancement filters for lung nodule detection - Pereira, C.S.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2007)
The aim of this paper is to evaluate and compare the performance of three convergence index (CI) filters when applied to the enhancement of chest radiographs, aiming at the detection of lung nodules. One of these filters, the sliding band filter (SBF), is the proposal of an innovative operator, while the other two CI class members, the iris filter (IF) and the adaptive ring filter (ARF), are already known in this application. To demonstrate the adequacy of the new filter for the enhancement of chest x-ray images, we calculated several figures of merit with the goal of comparing (i) the contrast enhancement capability of the filters, and (ii) the behavior of the filters for the detection of lung nodules. The results obtained for 154 images with nodules of the JSRT database show that the SBF outperforms both the IF and ARF. The proposed filter demonstrated to be a promising enhancement method, thus justifying its use in the first stage of a computer-aided diagnosis system for the detection of lung nodules. © Springer-Verlag Berlin Heidelberg 2007.
Keywords: Adaptive systems; Contrast enhancement filters; Database systems; Image segmentation; Iris filter (IF); Medical imaging; Radiography; X rays

Face detection based on skin color in video images with dynamic background - Ferreira, A.M.; Correia, M.V. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2007)
Face detection is a problem in image processing that has been extensively studied in the last decades. This fact is justified due to the innumerous applications this subject has in computer vision. In this paper we present a technique to detect a face in an image where several persons may be. The images were recorded from news broadcasts from different networks. First, a model based on normalized RGB color space was built to define a skin color model: skin regions were selected from several face images and extracted statistical characteristics. Second, each pixel of the image was classified in two categories: skin and not skin. Third, the face region was identified. A MATLAB function was created to detect faces of any size, achieving high detection rates. © Springer-Verlag Berlin Heidelberg 2007.
Keywords: Color; Color segmentation; Computer vision; Face detection; Face recognition; MATLAB; Skin; Skin color model; Skin detection

A Gait Analysis Laboratory for rehabilitation of patients with musculoskeletal impairments - Sousa, D.S.S.; Tavares, J.M.R.S.; Correia, M.V.; Barbosa, J.G.; Chã, C.V.; Mendes, E. (Proceedings of the International Symposium CompIMAGE 2006 - Computational Modelling of Objects Represented in Images: Fundamentals, Methods and ApplicationsProc. Int. Symp. CompIMAGE - Comput. Model. Objects Represent. Images: Fundam., Methods Appl., 2007)
This paper describes the technology (software & hardware) used in the Gait Analysis Laboratory of CRPG - Centro de Reabilitação Projissional de Gaia. This laboratory is mainly intended to support CRPG with quantitative data for clinical rehabilitation of patients with musculoskeletal pathologies, namely in the lower limbs. Usually, for the gait analysis is considered data obtained from several acquisition sensors, such as: image cameras, electromyographic devices, pressure devices and force plates. This paper also presents briefly how quantitative motion analysis can be used for a clinical point of view and it presents the influence of image algorithms in gait rehabilitation. © 2007 Taylor & Francis Group.
Keywords: Acquisition sensors; Electromyographic; Force plates; Gait analysis; Gait rehabilitations; Image algorithms; Lower limbs; Motion analysis; Patient rehabilitation; Pressure devices; Quantitative datum

An improved management model for tracking missing features in computer vision long image sequences - Pinho, R.R.; Tavares, J.M.R.S.; Correia, M.V. (WSEAS Transactions on Information Science and ApplicationsWSEAS Trans. Inf. Sci. Appl., 2007)
In this paper we present a management model to deal with the problem of tracking missing features during long image sequences using Computational Vision. Some usual difficulties related with missing features are that they may be temporarily occluded or might even have disappeared definitively, and the computational cost involved should always be reduced to the strictly necessary. The proposed Net Present Value (NPV) model, based on the economic Theory of Capital, considers the tracking of each missing feature as an investment. Thus, using the NPV criterion, with adequate receipt and outlay functions, each occluded feature may be kept on tracking or it may be excluded of the tracking process depending on its historical behavior. This approach may be applied to any tracking system as long as the tracking results may be evaluated in each temporal step, and it can deal with the appearance, occlusion and disappearance of features especially useful for tracking in long image sequences. Experimental results, both on synthetic and real image sequences, which validate our model, will be also presented.
Keywords: Automatic target recognition; Computer vision; Feature extraction; Long image sequences; Management; Mathematical models; Missing features; Motion estimation; Net Present Value (NPV); Occlusion; Tracking

Laser surface treatment of hydroxyapatite for enhanced tissue integration: Surface characterization and osteoblastic interaction studies - Teixeira, S.; Monteiro, F.J.; Ferraz, M.P.; Vilar, R.; Eugénio, S. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2007)
Biocompatibility has long been associated with surface microtopography, microtexture, and microchemistry. The surface topography eventually affects the nature and the intensity of the interactions that occur at biomaterial- biological interface (cell adhesion, mobility, spreading, and proliferation). Therefore, it is necessary to produce and work with controlled microtopographical surfaces that present reproducible microdomains of a dimension similar to that of the biological elements of interest (in this case, osteoblasts). There are a number of substrates that already have been studied in terms of surface topography; however, few studies are related to hydroxyapatite (HA) substrates. As it is well established, HA is a well-known ceramic that is extremely used in medical applications, namely implants and coatings. In this work, the surface topography of dense HA substrates was altered by using KFr excimer laser. The surface was characterized by atomic force microscopy and contact angle measurements, while the cell distribution and morphology was assessed by scanning electron microscopy and confocal laser scanning microscopy. Results revealed that the surface is characterized by a homogeneous columnar structure with high specific area. Moreover, cells were able to attach and spread on the surface of the samples, and gradually grow into nearly confluent monolayers. © 2007 Wiley Periodicals, Inc.
Keywords: article; Atomic force microscopy; Biocompatibility; biomaterial; cell adhesion; Cell Communication; Cell Line, Tumor; cell motility; cell proliferation; cell spreading; cellular distribution; ceramic prosthesis; ceramics; chemistry; confocal laser microscopy; controlled study; Durapatite; Excimer laser; Excimer lasers; human; human cell; Humans; hydroxyapatite; laser; Lasers; material coating; Microchemistry; Microscopy, Atomic Force; Microscopy, Confocal; Microscopy, Electron, Scanning; Microtexture; monolayer culture; osteoblast; Osteoblasts; reproducibility; Scanning electron microscopy; Surface microtopography; Surface modification; Surface Properties; surface property; Surface topography; Surface treatment; Tissue engineering

Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period - Gonçalves, H.; Bernardes, J.; Paula Rocha, A.; Ayres-de-Campos, D. (Early Human DevelopmentEarly Hum. Dev., 2007)
Background: Fetal behavioral states are important indicators of fetal physiology and pathology associated to typical fetal heart rate (FHR) patterns. Aim: To provide linear and nonlinear analysis of FHR patterns associated with fetal behavioral states regarding a better understanding of these states and patterns. Study design and subjects: Fifty FHR tracings from normal term pregnancies with a median duration of 40.3 min were acquired with the SisPorto® 2.01 system for computerized analysis of cardiotocograms. Each tracing was divided into consecutive 10-minute segments and each segment was classified by two experts as pattern A, B, C or D. Outcome measures: Linear and nonlinear indices were computed in each segment, namely mean FHR, long-term irregularity index (LTI), very low (VLF), low (LF) and high (HF) frequency spectral indices, approximate entropy (ApEn) and sample entropy (SampEn). Kappa statistic (κ) and proportions of agreement (Pa) were used for assessment of inter-observer agreement. Bootstrap percentile confidence intervals and nonparametric statistical tests were calculated for statistical inference. Results: Overall agreement between experts in pattern classification was good to excellent with values for κ and Pa of 0.74 (95% CI: 0.64-0.94) and 0.94 (95% CI: 0.92-0.96), respectively. Most linear domain indices increased significantly with rising fetal activity whereas the opposite occurred with nonlinear indices, except for SampEn(2, 0.1). LF/(MF + HF) ratio also significantly increased with fetal activity, denoting an increased sympatho-vagal balance. Conclusions: Results support the hypothesis that entropy and linear variability indices measure different FHR features. FHR patterns associated with active sleep (B) and active wakefulness (D) evidenced more signs of autonomous nervous system activity, with sympatho-vagal imbalance, and less signs related to complexity or irregularity control systems than patterns associated with calm sleep (A) and calm wakefulness (C). © 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: adult; article; behavior change; Cardiotocography; Computerized analysis; controlled study; entropy; Female; Fetal behavioral states; Fetal heart rate; Fetal monitoring; fetus; fetus heart rate; fetus monitoring; Heart Rate, Fetal; human; Humans; Image Interpretation, Computer-Assisted; Linear Models; Nonlinear Dynamics; Pregnancy; SisPorto; Spectral analysis; vagus nerve stimulation

Mesenchymal stem cell proliferation and morphological analysis on interconnected macroporous structures - Teixeira, S.; Fernandes, H.M.; De Boer, J.; Ferraz, M.P.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2007)
Calcium phosphate ceramics are widely used as bone substitutes since they are biocompatible and bioactive. Given that their chemical composition is close to natural bone, calcium phosphate ceramics are promising bone substitute materials in orthopaedics, maxillofacial surgery and dentistry. Hydroxyapatite (HA) and tricalcium phosphate (TCP) are the most commonly used calcium phosphates, because their calcium/phosphorus (Ca/P) ratios are close to that of natural bone and they are relatively stable in physiological environment. Furthermore, other critical parameters must be accomplished when designing a biomaterial for bone regeneration, namely: pore size, shape and interconnectivity [1]. Porosity is one of the most important factors since it influences the adhesion, migration nutrient supply and ultimately, proliferation of mesenchymal stem cells. In this study, HA scaffolds with controlled porosity were obtained and their capacity to support human and rat mesenchymal stem cells attachment and proliferation was evaluated.
Keywords: Biomaterials; Calcium Compounds; cell adhesion; cytology; hydroxyapatite; Macroporous ceramics; Mesenchymal Stem Cells; orthopedics; Phase composition; Physiological models; porosity; Tricalcium phosphate (TCP)

Microspheres based on hydroxyapatite nanoparticles aggregates for bone regeneration - Pataquiva Mateus, A.Y.; Ferraz, M.P.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2007)
This study concerns the preparation and characterisation of microspheres associating alginate and two different types of hydroxyapatite (HA), which are intended to be used as drug delivery systems and bone regeneration matrices. Hydroxyapatite nanoparticles (HA-1 and HA-2) were prepared using a chemical precipitation synthesis based on H3PO4, Ca(OH)2 and a surfactant, SDS (sodium dodecylsulphate), as starting reagents. These two powders of nanoHA and alginate were used to prepare two different types of microspheres. Both powders and microspheres were characterised using FTIR, TEM, SEM, mercury porosimetry analysis and X-ray diffraction Results show that pure hydroxyapatite (HA) and mixtures of HA/β-TCP in the nanometre range were obtained from both HA syntheses. Microspheres with different characteristics were obtained from these two types of hydroxyapatite.
Keywords: Alginate; Bone; Bone Regeneration; Chemical precipitation; Controlled drug delivery; Fourier transform infrared spectroscopy; hydroxyapatite; Microspheres; Microstructure; nanoparticles; Nanostructured materials; Scanning electron microscopy; Surface active agents; transmission electron microscopy

Nanohydroxyapatite microspheres as delivery system for antibiotics: Release kinetics, antimicrobial activity, and interaction with osteoblasts - Ferraz, M.P.; Mateus, A.Y.; Sousa, J.C.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2007)
Severe periodontitis treatment, where massive alveolar bone loss occurs, involves bone defect filling and intensive systemic log-term antibiotics administration. This study aims at developing novel injectable drug delivery systems (nanohydroxyapatite microspheres) with the drug releasing capability for periodontitis treatment and simultaneously initiating the osteointegration process. Materials were characterized by XRD, SEM, inverted stand optical microscope analysis, and mercury porosimetry method. Amoxicillin, amoxicillin + clavulanic acid, and erythromycin were the antibiotics used. Release properties during 28 days from the hydroxyapatite (HA) granules, and two types of nanoHA microspheres were investigated. Biocompatibility was assessed by cytotoxicity assays. HA granules were inadequate, releasing all antibiotic during the first hours. The concentration of antibiotics released in the first days from HA-2 was higher than from HA-1 microspheres, because of the increased porosity and surface area. The release profiles (fast initial release followed by long-term sustained release) of effective doses of antibiotics make these systems good alternatives for antibiotics delivery. Osteoblasts proliferated well on both types of microspheres, being cell growth enhanced in the presence of antibiotics. Erythromycin presented the most beneficial effect. Combining the sustained antibiotic release with the osteoconduction, resorbability, and potential use as injectable bone filling material of porous HA microspheres, these systems provided a forth fold beneficial effect. © 2007 Wiley Periodicals, Inc.
Keywords: alveolar bone; amoxicillin; amoxicillin plus clavulanic acid; Anti-Bacterial Agents; Antibacterial; antibiotic agent; antibiotic resistance; Antibiotics administration; antimicrobial activity; article; Bacteria; Cell Communication; Cell Death; cell growth; cell kinetics; Cell Line; cell proliferation; clindamycin; concentration response; controlled study; Cytotoxicity; Drug delivery; drug delivery system; Drug Delivery Systems; Drug release; Durapatite; erythromycin; Escherichia coli; human; human cell; Humans; hydroxyapatite; Kinetics; materials testing; metronidazole; Microbial Sensitivity Tests; microsphere; Microspheres; minocycline; Nanohydroxyapatite; nanoparticle; nanoparticles; nonhuman; Optical microscope analysis; osteoblast; Osteoblasts; osteolysis; periodontitis; porosity; Staphylococcus aureus; surface property; sustained drug release; Tetracycline; unclassified drug; X ray diffraction

A novel dry active electrode for EEG recording - Fonseca, C.; Silva Cunha, J.P.; Martins, R.E.; Ferreira, V.M.; Marques De Sá, J.P.; Barbosa, M.A.; Martins Da Silva, A. (IEEE Transactions on Biomedical EngineeringIEEE Trans. Biomed. Eng., 2007)
The design and testing of a "dry" active electrode for electroencephalographic recording is described. A comparative study between the EEG signals recorded in human volunteers simultaneously with the classical Ag-AgCl and "dry" active electrodes was carried out and the reported preliminary results are consistent with a better performance of these devices over the conventional Ag-AgCl electrodes. © 2007 IEEE.
Keywords: article; Biocompatible Materials; Bioelectric phenomena; Bioelectric signal recording; bioenergy; biomedical electrodes; Biomedical engineering; Data recording; Dry electrodes; Electric Impedance; Electrochemical electrodes; electrode; Electrodes; electroencephalogram; Electroencephalographic recording; electroencephalography; Equipment Design; Equipment Failure Analysis; Feasibility Studies; Pilot Projects; signal transduction; Silver compounds; Titanium

Opening wedge high tibial osteotomy using 3D biomodelling Bonelike® macroporous structures: Case report - Gutierres, M.; Dias, A.G.; Lopes, M.A.; Hussain, N.S.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2007)
Two synthetic calcium phosphates in porous wedge shape, Bonelike® and a commercial HA/β-TCP biphasic material, were used as an alternative to bone autografts and allografts in the treatment of medial compartment osteoarthritis of varus knees. The structure of Bonelike® has a 3D architecture that is computer controlled, and a composition that mimics the mineral composition of natural bone. The HA/β-TCP biphasic material used as a control material in this study was prepared using conventional foaming based methods. No signs of inflammatory reactions were observed post-operatively for both materials. After 4 months signs of fusion at the osteotomy site and good integration of the implanted wedges were observed, showing good mechanical resistance. Concerning the final correction attained, the left knee revealed a satisfactory valgus of 10°, but the right one only had a final value of 6°. The clinical evaluation using International Knee Score (IKS) showed good outcome in all parameters with complete range of motion in both knees and climbing stairs without crutches with only slight pain. © 2007 Springer Science+Business Media, LLC.
Keywords: adult; article; Biological organs; Biomodeling; Bone; bone allograft; Bone graft; bone mineral; Bone Substitutes; calcium phosphate; Calcium phosphates; case report; climbing; clinical evaluation; Computer simulation; Grafts; human; Humans; hydroxyapatite; Hydroxyapatites; Imaging, Three-Dimensional; knee; knee pain; Macroporous structures; male; Mechanical properties; Middle Aged; Osteoarthritis; Osteoarthritis, Knee; Osteoblasts; osteotomy; pain assessment; porosity; Porous wedge shapes; priority journal; Prostheses and Implants; range of motion; structure analysis; tibia; tibia osteotomy; Tibial osteotomy; Valgus; valgus knee

Physicochemical degradation studies of calcium phosphate glass ceramic in the CaO-P 2O 5-MgO-TiO 2 system - Dias, A.G.; Gibson, I.R.; Santos, J.D.; Lopes, M.A. (Acta BiomaterialiaActa Biomater., 2007)
The aim of this work was to evaluate the in vitro degradation behaviour of a 45CaO-37P 2O 5-5MgO-13TiO 2 (mol.%) glass ceramic, under two different simulated physiological conditions: normal physiological pH 7.4, and pH 3.0, which was designed to simulate the acidic conditions produced by osteoclast cells. The in vitro testing was carried out at 37 °C for up to 42 days for the pH 7.4 solution and for up to 1 day for the pH 3.0 solution. The incorporation of TiO 2 into the glass structure leads to the precipitation of specific crystalline phases in the glass matrix, namely α- and β-Ca 2P 2O 7, TiP 2O 7 and CaTi 4(PO 4) 6. The degradation testing at pH 3.0 showed a higher weight loss compared with degradation testing at pH 7.4; the weight loss under the acidic condition after 1 day (24 h) was about 10 times higher than the weight loss after 42 days of immersion at pH 7.4. The ionic release profile of Ca 2+, PO 4 3 -, Mg 2+ and Ti 4+ showed a continuous increase in concentration over all immersion times for both testing solutions. After 1 day of immersion at pH 3.0, the concentration levels of Mg 2+, Ca 2+, PO 4 3 - were about six times higher than the levels achieved after 42 days of immersion at pH 7.4. The glass ceramic showed similar degradation to hydroxyapatite, and therefore has potential to be used in certain clinical applications where relatively slow resorption of the implant and replacement by bone is required, e.g. cranioplasty. © 2006 Acta Materialia Inc.
Keywords: acidity; article; Biocompatible Materials; Biomaterials; Bone; Bone and Bones; bone prosthesis; Calcium Compounds; calcium ion; calcium phosphate ceramic; Calcium phosphates; ceramics; Chemical structure; concentration response; controlled study; cranioplasty; Crystallization; Degradation; glass; Hydrogen-Ion Concentration; hydroxyapatite; In vitro biodegradation; in vitro study; Magnesium Oxide; materials testing; Microscopy, Electron, Scanning; Models, Statistical; osteoclast; Oxides; pH; phosphate; Phosphorus Compounds; physical chemistry; priority journal; prosthesis material; simulation; Spectrum Analysis, Raman; structure analysis; temperature; Time Factors; Titanium; weight reduction

Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix - Evangelista, M.B.; Hsiong, S.X.; Fernandes, R.; Sampaio, P.; Kong, H.-J.; Barrias, C.C.; Salema, R.; Barbosa, M.A.; Mooney, D.J.; Granja, P.L. (BiomaterialsBiomaterials, 2007)
There is a need for new therapeutic strategies to treat bone defects caused by trauma, disease or tissue loss. Injectable systems for cell transplantation have the advantage of allowing the use of minimally invasive surgical procedures, and thus for less discomfort to patients. In the present study, it is hypothesized that Arg-Gly-Asp (RGD)-coupled in a binary (low and high molecular weight) injectable alginate composition is able to influence bone cell differentiation in a three-dimensional (3D) structure. Viability, metabolic activity, cytoskeleton organization, ultrastructure and differentiation (alkaline phosphatase (ALP), von Kossa, alizarin red stainings and osteocalcin quantification) of immobilized cells were assessed. Cells within RGD-modified alginate microspheres were able to establish more interactions with the synthetic extracellular matrix as visualized by confocal laser scanning microscope and transmission electron microscopy imaging, and presented a much higher level of differentiation (more intense ALP and mineralization stainings and higher levels of osteocalcin secretion) when compared to cells immobilized within unmodified alginate microspheres. These findings demonstrate that peptides covalently coupled to alginate were efficient in influencing cell behavior within this 3D system, and may provide adequate preparation of osteoblasts for cell transplantation. © 2007 Elsevier Ltd. All rights reserved.
Keywords: 3T3 Cells; Alginate; Alginates; alginic acid; alkaline phosphatase; animal cell; Animals; arginylglycylaspartic acid; article; Bone; bone cell; Bone Regeneration; calvaria; cell adhesion; cell differentiation; Cell encapsulation; Cell immobilization; cell metabolism; cell proliferation; cell survival; cell ultrastructure; cell viability; confocal laser microscopy; controlled study; cytology; cytoskeleton; DNA; DNA content; ECM (extracellular matrix); enzyme activity; extracellular matrix; Glucuronic Acid; Hexuronic Acids; hydrogel; immobilized cell; metabolism; Mice; Microscopy, Confocal; Microscopy, Electron, Transmission; microsphere; Microspheres; nonhuman; Oligopeptides; osteoblast; Osteoblasts; osteocalcin; Patient treatment; priority journal; rat; RGD peptide; structure analysis; three dimensional imaging; Tissue engineering; transmission electron microscopy; Transplantation (surgical)

31P MAS-NMR studies of CaO-P 2O 5 glass ceramics - Dias, A.G.; Lopes, M.A.; Tsuru, K.; Hayakawa, S.; Santos, J.D.; Osaka', A. (Key Engineering MaterialsKey Eng Mat, 2006)
This work reports the structure of two glass ceramics prepared in the calcium phosphate system, MK5B and MT13B, using 31P MAS-NMR technique. The results obtained showed that the network of MK5B consisted mainly of Q 1 and Q 2 groups. Besides these two groups, MT13B material also present Q 3 units. The Q n groups detected in both glass ceramics seem to be correlated to the crystalline phases present in their microstructure.
Keywords: Biomaterials; calcium phosphate; Crystalline materials; Crystalline phases; Glass ceramics; Lime; MAS-NMR technique; Microstructure; NMR; Nuclear magnetic resonance spectroscopy

Absorption and emission properties of Ho 3+ doped lead-zinc-borate glasses - Sooraj Hussain, N.; Ali, N.; Dias, A.G.; Lopes, M.A.; Santos, J.D.; Buddhudu, S. (Thin Solid FilmsThin Solid Films, 2006)
This paper reports on the affect of lead content on the absorption and emission spectra of the Ho 3+ ion doped lead-zinc-borate glasses in the composition (mol%) of (20 - x)PbO-20ZnO-(59 + x)B 2O 3-1.0Ho 2O 3 where x = 0, 5,10,15 of PbO content with λ exc = 405 nm. The experimental absorption band energies have satisfactorily been correlated with the theoretical results with an r.m.s deviation of zero with the following correction factors obtained by a least square fit analysis: ΔE 1 = 348.495936 cm
Keywords: Band energies; Doping (additives); Energy gap; glass; Glasses; Holmium; Holmium glasses; Light absorption; Luminescence; Luminescences; Luminescent transitions; Optical properties; Stimulated emission

Adsorption of albumin on prosthetic materials: Implication for tribological behavior - Serro, A.P.; Gispert, M.P.; Martins, M.C.L.; Brogueira, P.; Colaço, R.; Saramago, B. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
The orthopedic prosthesis used to substitute damaged natural joints are lubricated by a pseudosynovial fluid that contains biological macromolecules with potential boundary lubrication properties. Proteins are some of those macromolecules whose role in the lubrication process is not yet completely understood. In a previous work, we investigated the influence of the presence of albumin, the major synovial protein, upon the tribological behavior of three of the most used pairs of artificial joint materials: ultra high molecular weight polyethylene (UHMWPE) against counterfaces of alumina, CoCrMo alloy, and 316L stainless steel. Albumin was found to cause a significant decrease in the friction coefficient when the counterfaces were metallic because transfer of UHMWPE was avoided, but this effect was much weaker in the case of alumina. The objective of the present work was to look for an explanation for these differences in tribological behavior in terms of albumin adsorption. With this goal, studies on adsorption of bovine serum albumin (BSA) on the counterface materials, from a biological model fluid (Hanks' balanced salt solution), were carried out using radiolabeled albumin ( 125I-BSA), X-ray photoelectron spectroscopy, and atomic force microscopy. The conclusion from all techniques is that the driving force for albumin adsorption is higher on the metals than on alumina. These results confirm that the greater the amount of protein adsorbed on the counterface, the more efficient is the protection against the transfer of polymeric film to the counterface. © 2006 Wiley Periodicals, Inc.
Keywords: Adsorption; Albumin; Albumin adsorption; Albumins; Alumina; aluminum oxide; article; Atomic force microscopy; balanced salt solution; Biocompatible Materials; Body fluids; bovine serum albumin; chromium derivative; Cobalt alloy; Cobalt alloys; cobalt derivative; force; Friction; iodine 125; isotope labeling; joint fracture; Joints (anatomy); lubrication; macromolecule; metal; molecular weight; molybdenum; orthopedic prosthesis; orthopedics; Polyethylenes; polymer; Prostheses and Implants; prosthesis material; Prosthetics; protein; Proteins; Pseudosynovial fluid; Stainless steel; Thermodynamics; Tribology; ultra high molecular weight polyethylene; Ultra high molecular weight polyethylene (UHMWPE); X ray photoelectron spectroscopy

Assessment of Bonelike® graft with a resorbable matrix using an animal model - Lobato, J.V.; Hussain, N.S.; Botelho, C.M.; Maurício, A.C.; Afonso, A.; Ali, N.; Santos, J.D. (Thin Solid FilmsThin Solid Films, 2006)
Synthetic bone grafts have been developed to provide an alternative to autografts and allografts. Bonelike® is a patented synthetic osteoconductive bone graft that mimics the mineral composition of natural bone. In the present preliminary animal studies a user-friendly version of synthetic bone graft Bonelike® have been developed by using a resorbable matrix, Floseal®, as a vehicle and raloxifene hydrochloride as a therapeutic molecule, that is known to decrease osteoclast activity and therefore enhanced bone formation. From histological and scanning electron microscopy evaluations, the use of Bonelike® associated with Floseal® and raloxifene hydrochloride showed that new bone was rapidly apposed on implanted granules and also that the presence of the matrix and therapeutic molecule does not alter the proven highly osteoconductivity properties of Bonelike®. Therefore, this association may be one step-forward for the clinical applications of Bonelike® scaffolds since it is much more easy-to-handle when compared to granular materials. © 2006 Elsevier B.V. All rights reserved.
Keywords: animal model; Bone; Bonelike®; FloSeal®; Grafting (chemical); Histological analysis; Mathematical models; Raloxifene hydrochloride; Scanning electron microscopy

Calcium phosphate microspheres for localised delivery of a therapeutic enzyme - Barrias, C.C.; Ribeiro, C.C.; Martins, M.C.L.; Barbosa, M.A.; Rodrigues, D.; Miranda, M.C.S. (Key Engineering MaterialsKey Eng Mat, 2006)
The ability of calcium titanium phosphate (CTP) and hydroxyapatite (HAp) microspheres to reversibly adsorb the enzyme glucocerebrosidase (GCR) while preserving its biological activity, and efficiently deliver it to Gaucher disease (GD) fibroblasts was investigated. CTP microspheres adsorbed ca. 3.6-fold more GCR than HAp microspheres. The activity of adsorbed GCR was higher than the free enzyme in the case of CTP microspheres and lower when HAp was used. GCR release from both types of microspheres was characterized by the initial elution of a large percentage of enzyme followed by a delayed release that extended for at least 30 days. Released GCR was internalized by GD fibroblasts increasing their intracellular enzymatic activity. In cells treated with the same amount of GCR-loaded CTP microspheres or free-GCR a higher intracellular activity was detected in the former case, suggesting an improved efficacy.
Keywords: Adsorption; Biocompatibility; biological activity; Biomaterials; Calcium Compounds; Calcium titanium phosphate; Calcium titanium phosphate (CTP); Cells; Enzyme adsorption; Enzymes; hydroxyapatite; Microspheres

Cellulose phosphates as biomaterials. In vitro biocompatibility studies - Granja, P.L.; Jéso, B.D.; Bareille, R.; Rouais, F.; Baquey, C.; Barbosa, M.A. (Reactive and Functional PolymersReact Funct Polym, 2006)
Grafting of phosphate groups has been investigated as a means to render biomedical polymers able to induce the formation of an apatite layer. In the present investigation, regenerated cellulose hydrogels were surface modified by phosphorylation using a previously reported method. The in vitro biocompatibility of materials with varying phosphate contents was evaluated in cultured human bone marrow stromal cells (HBMSC), in terms of cytotoxicity, cell attachment, proliferation and immunohistochemistry. Negatively charged cellulose phosphates were neutralized in the form of the calcium salt before contact with cells. Cellulose phosphates were not cytotoxic, independently of the phosphate content. Unmodified regenerated cellulose hydrogels showed good rates of HBMSC attachment and proliferation. On the contrary, negatively charged, highly hydrophilic, phosphorylated surfaces showed poor HBMSC attachment and proliferation, as well as poor alkaline phosphatase-specific activity and expression of osteocalcin and type I collagen. Differences found are discussed in terms of surface chemical functionality, hydrophilicity and charge. © 2005 Elsevier B.V. All rights reserved.
Keywords: Biocompatibility; Biomaterials; Cell attachment; Cell culture; Cellulose; Cellulose derivatives; Cellulose phosphates; Cytotoxicity; Grafting (chemical); Human bone marrow stromal cells; Hydrogels; hydrophilicity; immunohistochemistry; In vitro; Phosphorylation; Proliferation; Regenerated cellulose hydrogels; toxicity

Characterization of fetal heart rate irregularity using approximate entropy and wavelet filtering - Magalhães, F.; Marques De Sá, J.P.; Bernardes, J.; Ayres-de-Campos, D. (Computers in CardiologyComput Cardiol, 2006)
Approximate Entropy (ApEn) has been used by several researchers as a means to characterize the irregularity of fetal heart rate (FHR), a major contributor to fetal risk assessment. The present work starts by analyzing the influence of accelerative and decelerative (AD) components of the FHR signal in the computation of ApEn. Having shown that the AD components may completely distort the ApEn evaluation we proceed to present two methods of eliminating the influence of the AD components: wavelet filtering; AD detection using specific algorithms based on well-established physiological criteria. We obtained good results with the first method when applied to simulated signals; however it proved unreliable in the practical application of discriminating normal from pathological fetal FHR. With the second method we were able to achieve this discrimination with high statistical significance.
Keywords: Approximate entropy; Cardiology; Fetal heart rate; Neonatal monitoring; Occupational risks; Physiological models; risk assessment; Risk management; Safety engineering; Simulated signals; Statistical significance; Wavelet filtering

The class imbalance problem in TLC image classification - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2006)
The paper presents the methodology developed to solve the class imbalanced problem that occurs in the classification of Thin-Layer Chromatography (TLC) images. The proposed methodology is based on resampling, and consists in the undersampling of the majority class (normal class), while the minority classes, which contain Lysosomal Storage Disorders (LSD) samples, are oversampled with the generation of synthetic samples. For image classification two approaches are presented, one based on a hierarchical classifier and another uses a multiclassifier system, where both classifiers are trained and tested using balanced data sets. The results demonstrate a better performance of the multiclassifier system using the balanced sets. © Springer-Verlag Berlin Heidelberg 2006.
Keywords: Chromatographic analysis; Class imbalanced problem; Classification (of information); Hierarchical systems; Lysosomal Storage Disorders (LSD); Medical imaging; Multiclassifier system; Problem solving; Thin-Layer Chromatography (TLC) images

Cultivation of human embryonic stem cells without the embryoid body step enhances osteogenesis in vitro - Karp, J.M.; Ferreira, L.S.; Khademhosseini, A.; Kwon, A.H.; Yeh, J.; Langer, R.S. (Stem CellsStem Cells, 2006)
Osteogenic cultures of embryonic stem cells (ESCs) are predominately derived from three-dimensional cell spheroids called embryoid bodies (EBs). An alternative method that has been attempted and merits further attention avoids EBs through the immediate separation of ESC colonies into single cells. However, this method has not been well characterized and the effect of omitting the EB step is unknown. Herein, we report that culturing human embryonic stem cells (hESCs) without the EB stage leads to a sevenfold greater number of osteogenic cells and to spontaneous bone nodule formation after 10-12 days. In contrast, when hESCs were differentiated as EBs for 5 days followed by plating of single cells, bone nodules formed after 4 weeks only in the presence of dexamethasone. Furthermore, regardless of the inclusion of EBs, bone matrix formed, including cement line matrix and mineralized collagen, which displayed apatitic mineral (PO 4) with calcium-to-phosphorous ratios similar to those of hydroxyapatite and human bone. Together these results demonstrate that culturing hESCs without an EB step can be used to derive large quantities of functional osteogenic cells for bone tissue engineering. ©AlphaMed Press.
Keywords: alkaline phosphatase; Apatite; article; bone development; bone growth; bone matrix; bone mineralization; Bone tissue engineering; Calcium; calcium phosphate; Calcium phosphates; Cell Culture Techniques; cell differentiation; cell separation; Collagen; collagen synthesis; culture technique; cytology; dexamethasone; embryo; embryo culture; Embryoid bodies; embryonic stem cell; extracellular matrix; human; human cell; human embryo; Human embryonic stem cells; Humans; hydroxyapatite; in vitro study; Matrix characterization; metabolism; methodology; ossification; osteocalcin; Osteogenesis; Osteogenic cell frequency; phosphorus; spheroid cell; Tissue engineering; totipotent stem cell; Totipotent Stem Cells

Differentiation of mononuclear precursors into osteoclasts on the surface of Si-substituted hydroxyapatite - Botelho, C.M.; Brooks, R.A.; Spence, G.; McFarlane, I.; Lopes, M.A.; Best, S.M.; Santos, J.D.; Rushton, N.; Bonfield, W. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
In healthy bone, resorption and synthesis are in perfect coordination. In previous studies we demonstrated that the incorporation of silicon into the hydroxyapatite (HA) lattice enhances the proliferation and differentiation of human osteoblasts. Therefore, the aim of this study was to demonstrate the effect of silicon-substituted HA (0.8 and 1.5 wt % Si-HA) on the differentiation of mononuclear cells into osteoclasts, using two different starting cultures, peripheral blood mononuclear cells (PBMC) and monocytes expressing the CD14 antigen (CD14 +). Through this study, it was possible to demonstrate that Si-HA allows the differentiation of mononuclear cells into mature osteoclasts, independent of the starting culture, PBMC or CD14 +. Most of the cells on the surface of the materials expressed osteoclastic markers: actin rings, several nuclei, positivity for tartrate-resistant acid phosphatase (TRAP), and vitronectin receptor. In the presence of osteoclasts, a higher release of calcium and phosphate into the medium from the 1.5 wt % Si-HA substrate was detected when compared to the HA substrate; therefore, these results indicate higher osteoclastic resorptive activity on the 1.5 wt % Si-HA surface. Si-HA can be resorbed by cellular mechanisms and have a stimulatory effect on osteoclasts, although the underlying mechanism is still poorly understood. © 2006 Wiley Periodicals, Inc.
Keywords: acid phosphatase tartrate resistant isoenzyme; actin; Antigens, CD14; article; Biomarkers; Calcium; CD14 antigen; cell differentiation; Cells; controlled study; Differentiation; Durapatite; human; human cell; hydroxyapatite; Microscopy, Fluorescence; monocyte; Monocytes; Monocytes CD14 positive; Osteoblasts; osteoclast; Osteoclasts; osteolysis; peripheral blood mononuclear cell; Peripheral blood mononuclear cells; phosphate; Silicon; Silicon-substituted hydroxyapatite; Sorption; Substitution reactions; Substrates; surface property; Synthesis (chemical); vitronectin receptor

Effect of surface treatments on anodic oxide film growth and electrochemical properties of tantalum used for biomedical applications - Silva, R.A.; Silva, I.P.; Rondot, B. (Journal of Biomaterials ApplicationsJ. Biomater. Appl., 2006)
Self-expandable nitinol (nickel-titanium) alloys and 316L stainless steel are the most commonly used materials in the production of coronary stents. However, tantalum (Ta) has already been used to make stents for endovascular surgery and may constitute an alternative to other materials because of its better electrochemical performance, namely its higher corrosion resistance, as well as its radio-opacity. The characterization of wet polished, chemically polished, wet polished anodized, and chemically polished anodized Ta electrodes has been performed in a 0.15 M NaCl solution (simulated body fluid) using U corr=f(t) measurements, anodic polarizations, capacity measurements, anodic oxidations, and atomic force microscopy (AFM) imaging. Anodic polarization curves have shown that the abnormal current density peak with a maximum value around 1.65 V (critical applied potential, U c) disappeared for the anodized electrodes indicating a probable relationship between the surface states and the film growth. These results are confirmed by capacity measurements. The behavior of wet polished and chemically polished electrodes during anodic oxidations seemingly indicated that for these particular treatments the film growth is different. The AFM images and roughness measurements have shown that chemical polishing produced smoother electrodes, a fact probably related to the differences in film growth. © 2006 Sage Publications.
Keywords: AFM; Anodic films; Anodic oxide film growth; Anodic polarization; article; artificial membrane; Atomic force microscopy; Biocompatible Materials; biomaterial; Biomedical applications; Biomedical engineering; Chemical polishing; chemistry; Coronary stents; Corrosion resistance; Crystallization; Current density; electric conductivity; Electrochemical properties; electrochemistry; electrode; Electrodes; materials testing; Membranes, Artificial; methodology; oxidation reduction reaction; Oxidation-Reduction; oxide; Oxides; Polarization; Surface Properties; surface property; Surface treatment; Tantalum; Tantalum electrodes

Error entropy in classification problems: A univariate data analysis - Silva, L.M.; Felgueiras, C.S.; Alexandre, L.A.; Marques de Sá, J. (Neural ComputationNeural Comp., 2006)
Entropy-based cost functions are enjoying a growing attractiveness in unsupervised and supervised classification tasks. Better performances in terms both of error rate and speed of convergence have been reported. In this letter, we study the principle of error entropy minimization (EEM) from a theoretical point of view. We use Shannon's entropy and study univariate data splitting in two-class problems. In this setting, the error variable is a discrete random variable, leading to a not too complicated mathematical analysis of the error entropy. We start by showing that for uniformly distributed data, there is equivalence between the EEM split and the optimal classifier. In a more general setting, we prove the necessary conditions for this equivalence and show the existence of class configurations where the optimal classifier corresponds to maximum error entropy. The presented theoretical results provide practical guidelines that are illustrated with a set of experiments with both real and simulated data sets, where the effectiveness of EEM is compared with the usual mean square error minimization. © 2006 Massachusetts Institute of Technology.
Keywords: article; Classification; entropy; methodology; Models, Theoretical; normal distribution; theoretical model

Error entropy minimization for LSTM training - Alexandre, L.A.; Marques De Sá, J.P. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2006)
In this paper we present a new training algorithm for the Long Short-Term Memory (LSTM) recurrent neural network. This algorithm uses entropy instead of the usual mean squared error as the cost function for the weight update. More precisely we use the Error Entropy Minimization approach, were the entropy of the error is minimized after each symbol is present to the network. Our experiments show that this approach enables the convergence of the LSTM more frequently than with the traditional learning algorithm. This in turn relaxes the burden of parameter tuning since learning is achieved for a wider range of parameter values. The use of EEM also reduces, in some cases, the number of epochs needed for convergence. © Springer-Verlag Berlin Heidelberg 2006.
Keywords: Algorithms; Convergence of numerical methods; Cost function; entropy; Error Entropy Minimization; Errors; Long Short-Term Memory (LSTM); Neural networks; Optimization

Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers - Rodrigues, S.N.; Gonçalves, I.C.; Martins, M.C.L.; Barbosa, M.A.; Ratner, B.D. (BiomaterialsBiomaterials, 2006)
The effect of surface wettability on fibrinogen adsorption, platelet adhesion and platelet activation was investigated using self-assembled monolayers (SAMs) containing different ratios of longer chain methyl- and shorter chain hydroxyl-terminated alkanethiols (C15CH3 vs. C11OH) on gold. Protein adsorption studies were performed using radiolabeled human fibrinogen (HFG). Platelet adhesion and activation studies with and without pre-adsorbed fibrinogen, albumin and plasma were assessed using scanning electron microscopy (SEM) and a glutaraldehyde-induced fluorescence technique (GIFT). Results demonstrated a linear decrease of HFG adsorption with the increase of OH groups on the monolayer (increase of the hydrophilicity). Platelet adhesion and activation also decrease with increase of hydrophilicity of surface. Concerning SAMs pre-immersed in proteins, fibrinogen adsorption was related with high platelet adhesion and activation. The passivant effect of albumin on platelet adhesion and activation was only demonstrated on SAMs contained C11OH. When all the blood proteins are present (plasma) platelet adhesion was almost absent on SAMs with 65% and 100% C11OH. This could be explained by the higher albumin affinity of the SAMs with 65% C11OH and the lower total protein adsorption associated with SAMs with 100% C11OH. © 2006 Elsevier Ltd. All rights reserved.
Keywords: Adsorption; Albumin; alkane derivative; Alkanes; article; binding affinity; Biocompatible Materials; Blood Platelets; Cells, Cultured; Chemical reactions; controlled study; Crystallization; fibrinogen; Fluorescence; fluorescence analysis; glutaraldehyde; gold; human; human cell; Humans; hydrophilicity; Hydroxides; hydroxyl group; materials testing; methyl group; Methylation; monolayer culture; Monolayers; normal human; Organic compounds; plasma; Plasma protein; Platelet activation; Platelet adhesion; Platelet Adhesiveness; priority journal; Protein adsorption; protein binding; Proteins; Radiolabeled human fibrinogen (HFG); Scanning electron microscopy; Self assembled; SEM; Sulfhydryl Compounds; surface property; thiol derivative; thrombocyte adhesion; wettability

Functionalization of chitosan membranes through phosphorylation: Atomic force microscopy, wettability, and cytotoxicity studies - Amaral, I.F.; Granja, P.L.; Melo, L.V.; Saramago, B.; Barbosa, M.A. (Journal of Applied Polymer ScienceJ. Appl. Polym. Sci., 2006)
Grafting negatively charged groups such as phosphates is a well-known strategy for inducing the deposition of apatite-like layers under simulated physiological conditions. In this investigation, chitosan was phosphorylated in an attempt to enhance its osteoconduction. Chitosan membranes were phosphorylated at 30°C with the H 3PO 4/ Et 3PO 4/P 2O 5/butanol reaction system for periods up to 48 h. This method is an alternative to the phosphoric acid/ urea/dimethylformamide phosphorylation method, which involves the use of much higher temperatures. In this study, the effects of the phosphorylation reaction time on the surface morphology and surface free energy of phosphorylated membranes were investigated with atomic force microscopy and static-contact-angle measurements, respectively. In addition, the modified membranes were evaluated with respect to their cytotoxiciry toward bone cells through the incubation of human osteoblastic cells with extracts of the materials for two different periods: 24 and 120 h. The results revealed a reduction of the average surface roughness at the nanometer scale with increasing phosphorylation reaction time. Wettability studies showed an increase in the polar component of the surface free energy with increasing reaction time as a result of the increase in the phosphate surface concentration. Cytotoxicity studies revealed no cytotoxic effect of phosphorylated membranes on osteoblastic cells, regardless of the incubation period. © 2006 Wiley Periodicals, Inc.
Keywords: Atomic force microscopy; Atomic force microscopy (AFM); Biocompatibility; Biological applications; Biological applications of polymers; Biomaterials; Chitin; chitosan; Chitosan membranes; grafting; Grafting (chemical); Osteoblastic cells; Phosphorylation; Polymeric membranes; polysaccharide; Polysaccharides; surface property; toxicity; Urea

Histological and scanning electron microscopy analyses of bone/implant interface using the novel Bonelike® synthetic bone graft - Gutierres, M.; Hussain, N.S.; Lopes, M.A.; Alfonso, A.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Journal of Orthopaedic ResearchJ. Orthop. Res., 2006)
Synthetic bone grafts provide an alternative to autografts and allografts. Bonelike® is a patented synthetic bone graft that mimics the mineral composition of bone. The aim of the present work was to assess the biological behavior of Bonelike® graft in humans, before using the material in orthopedic applications of bone regeneration, for example, in opening wedge high tibial osteotomies for medial knee osteoarthritis. Bonelike® granules were implanted in cortical bone of 11 patients undergoing osteotomies, and new bone formation, osteoconductive properties, and resorption characteristics of the granules were analyzed. The granules ranged from 500 to 1000 μm and were implanted in the lateral aspect of the tibia. The patients' mean age was 59 years (range 48 to 70 years); there were eight women and three men, all suffering from medial compartment osteoarthritis of the knee. At surgery, a 1 × 1 × 1-cm cortical defect was created 3 cm distal to the entry point of the screws, in line with the long axis of tibia. The implanted Bonelike® graft sample was extracted for analysis during removal of the metallic prosthesis after implantation times of 6, 9, and 12 months. Radiological follow-up, scanning electron microscopy, histological analysis, and histomorphometric measurements were conducted on the retrieved samples to assess bone regeneration in the defect area. Osteoconductive capacity was demonstrated by extensive mature bone formation around the implanted granules and high levels of percentage bone-to-graft contact (from 67-84%). Bonelike® acted as an excellent bioactive scaffold, allowing the migration, proliferation, and differentiation of bone cells on its surface, and therefore regeneration of the defects was achieved in a rapid, controlled manner. Our results suggest that Bonelike® graft is an excellent candidate for orthopedic applications where rapid new bone formation is a fundamental requirement. © 2006 Orthopaedic Research Society. Published by Wiley Periodicals, Inc.
Keywords: adult; aged; article; Bone; Bone and Bones; bone cell; bone conduction; bone development; Bone graft; bone prosthesis; bone radiography; Bone Regeneration; bone screw; Bone Substitutes; bone transplantation; Bonelike®; cell differentiation; cell migration; cell proliferation; Clinical applications; clinical article; controlled study; Female; follow up; Histological analysis; histology; human; Humans; knee osteoarthritis; male; Microscopy, Electron, Scanning; Middle Aged; morphometrics; orthopedics; ossification; Osteoconduction; Osteogenesis; osteolysis; Pathology; priority journal; Prostheses and Implants; prostheses and orthoses; prosthesis material; Scanning electron microscopy; surgical technique; Synthetic bone graft; tibia osteotomy; ultrastructure

Human osteoblast response to silicon-substituted hydroxyapatite - Botelho, C.M.; Brooks, R.A.; Best, S.M.; Lopes, M.A.; Santos, J.D.; Rushton, N.; Bonfield, W. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
Human osteoblasts were cultured on hydroxyapatite (HA), 0.8 wt % silicon substituted hydroxyapatite (Si-HA) and 1.5 wt % Si-HA discs. The influence of these substrates on cell behaviour in vitro was assessed by measuring total protein in the cell lysate and the production of several phenotypic markers: collagen type I (COL 1), alkaline phosphatase (ALP), osteocalcin (OC), and the formation of bone mineral. After 7 days, β-glycerophosphate and physiological levels of hydrocortisone were added to the culture medium to stimulate cell differentiation and mineral production. There was a significantly higher production of ALP on 1.5 wt % Si-HA at day 7 following which, the addition of hydrocortisone promoted the differentiation of cells on the other two substrates. Hydrocortisone addition also decreased the production of OC. During the period, when hydrocortisone was present, no significant difference in behavior was seen between cells on Si-HA and HA; however, following removal of hydrocortisone, cells responded to 0.8 wt % Si-HA with a significant increase in protein production. Using fluorescence microscopy, nodular structures labeled with tetracycline were observed on the surface of all substrates after 21 days. These structures were deposited on areas of high cell density but were not related to the presence or level of silicon in the substrate. These results indicate that human osteoblasts are affected by the presence of silicon in the HA substrate and that the timing of these effects may be dependent upon the level of silicon substitution. © 2006 Wiley Periodicals, Inc.
Keywords: alkaline phosphatase; article; Biomarkers; bone mineral; cell activity; Cell culture; cell density; cell differentiation; cell function; cell lysate; cell marker; cell protein; Cells; Cells, Cultured; collagen type 1; Collagen type I; culture medium; Durapatite; Fluorescence microscopy; glycerol 2 phosphate; hormone determination; human; human cell; Human osteoblasts; Humans; Hydrocortisone; hydroxyapatite; in vitro study; Minerals; Nodular mineral formation; osteoblast; Osteoblasts; osteocalcin; Osteocalcin (OC); phenotype; Phosphoric Diester Hydrolases; protein analysis; protein synthesis; Pyrophosphatases; Silicon; Substitution reactions; Substrates; Tetracycline; β-glycerophosphate

An improved management model for tracking multiple features in long image sequences - Pinho, R.R.; Tavares, J.M.R.S.; Correia, M.V. (WSEAS Transactions on Information Science and ApplicationsWSEAS Trans. Inf. Sci. Appl., 2006)
In this paper we present a management model to deal with the problem of tracking a large number of features during long image sequences. Some usual difficulties are related to this problem: features may be temporarily occluded or might even have disappeared definitively; the computational cost involved should always be reduced to the strictly necessary. The proposed Net Present Value (NPV) model, based on the economic Theory of Capital, considers the tracking of each missing feature as an investment. Thus, using the NPV criterion, with adequate receipt and outlay functions, each occluded feature may be kept on tracking or it may be excluded of the tracking process depending on its historical behavior. This methodology may be applied to any tracking system as long as the tracking results may be evaluated in each temporal step. Experimental results, both on synthetic and real image sequences, which validate our model, will be also presented.
Keywords: Computer vision; Costs; Feature extraction; Image sequences; Imaging systems; Management; Management model; Motion estimation; Net Present Value (NPV); Occlusion; Tracking; Tracking (position); Tracking multiple features

In vivo performance of biodegradable calcium phosphate glass ceramics using the rabbit model: Histological and SEM observation - Dias, A.G.; Lopes, M.A.; Santos, J.D.; Afonso, A.; Tsuru, K.; Osaka, A.; Hayakawa, S.; Takashima, S.; Kurabayashi, Y. (Journal of Biomaterials ApplicationsJ. Biomater. Appl., 2006)
Two MK5 (45CaO-45P 2O 5-5MGO-5K 2O, in mol% and MT13 (45CaO-37P 2O 5-5MgO-13TiO 2, in mol%) glasses are prepared in the meta- and pyrophosphate regions and crystallized to obtain MK5B and MT13B, respectively. MK5B was obtained by controlled crystallization, and MT13B by powder sintering. As a result of these heat treatment processes, the crystalline phases precipitated in the glassy matrix are KCa(PO 3) 3, β-Ca(PO 3) 2, β-Ca 2P 2O 7 and Ca 4P 6O 19 phases for MK5B and CaTi 4(PO 4) 6, TiP 2O 7, α- and β-Ca 2P 2O 7 phases for MT13B. To assess the in vivo biological behavior of these glass ceramics, a mixed granulometry in the range 250-355 μm and 355-425 μm with a ratio of 1/1 was implanted for 2, 4, and 12 weeks in the tibiae of Japanese white rabbits. The results showed that the in vivo behavior was strongly affected by their solubility. All implanted materials, MK5B and MT13B, and β-tricalcium phosphate (β-TCP) as control material, showed signs of degradation in vivo. However, the levels of degradation were quite different throughout the implantation periods. The highest degradation was observed for MK5B glass ceramic and the lowest for MT13B with β-TCP in-between. All implanted materials allow for new bone formation in the bone defect area. At the longest implantation period (12 weeks), the MT13B and β-TCP materials were almost completely surrounded by new bone tissue, whereas MK5B showed some unfilled spaces. This behavior is discussed in terms of the high degradation observed in previous studies. © 2006 SAGE Publications.
Keywords: Absorbable Implants; animal; Animals; article; Biodegradable glass ceramics; biodegradable implant; Biodegradation; bone prosthesis; Bone Substitutes; bone tissue; Calcium Compounds; calcium phosphate; Calcium phosphates; ceramics; chemistry; disease model; Disease Models, Animal; glass; Glass ceramics; histology; Imaging techniques; In vivo testing; materials testing; Optical microscopy; Pathology; rabbit; Rabbits; Scanning electron microscopy; tibia fracture; Tibial Fractures; Tissue; treatment outcome; X ray diffraction analysis

The influence of functional groups of self-assembled monolayers on fibrous capsule formation and cell recruitment - Barbosa, J.N.; Madureira, P.; Barbosa, M.A.; Águas, A.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
The contribution of the surface chemistry of an implant to the thickness of the fibrous capsule formed after implantation was herein investigated. For that, self-assembled monolayers (SAMs) of alkanethiols on gold with different terminal functional groups (COOH, OH, and CH 3) were used. These surfaces were implanted in subcutaneous air pouches of BALB/c mice and the ensuing fibrous capsules were evaluated and compared with the initial inflammatory response caused by the implant. The thickness of the fibrous capsules that are under organization around the implant was measured 1 week after implantation by histology. Inflammatory exudates were collected from the air pouches 24 h after the implantation of SAMs and were analyzed by flow cytometry. A significant increase in the thickness of fibrous capsules was seen around implanted CH 3-terminated SAMs, and also in gold surfaces, in comparison with the air pouch wall of sham-operated mice and of COOH- and OH-covered SAMs. The CH 3-coated implants also recruited higher numbers of inflammatory cells; this enhancement involved a significant number of Mac-1 + cells. Our data indicate that implant surfaces coated with CH 3 induce thick fibrous capsules and this may be the result of the stronger inflammatory effect of CH 3 in comparison with COOH or OH chemical groups. © 2005 Wiley Periodicals, Inc.
Keywords: animal; animal cell; animal experiment; animal model; animal tissue; Animals; article; Bagg albino mouse; Biocompatible Materials; biomaterial; chemistry; controlled study; flow cytometry; functional group; gold; histology; implantation; Inflammation; male; Mice; Mice, Inbred BALB C; Monolayers; mouse; nonhuman; Self assembly; Self-assembled monolayers; Sulfhydryl Compounds; Surface chemistry; thiol derivative; tissue reaction; Tissue responses

Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters - Gonçalves, H.; Rocha, A.P.; Ayres-de-Campos, D.; Bernardes, J. (Physiological MeasurementPhysiol. Meas., 2006)
The effect of foetal heart rate (FHR) acquisition mode on linear and nonlinear parameters is still largely unknown. In 33 normal labouring women, FHR signals were acquired simultaneously by an external ultrasound sensor applied to the maternal abdomen and an internal scalp electrode, in the minutes preceding delivery. For each case, the initial and final 5, 10 and 20 min segments were analysed, considering FHR signals at a frequency of 4 Hz (the frequency at which they are transmitted by the majority of commercialized foetal monitors). Several time and frequency domain linear and nonlinear FHR indices were computed in these segments, namely mean FHR, very low frequency (VLF), low frequency (LF), high frequency (HF), approximate entropy (ApEn) and sample entropy (SampEn). Parametric confidence intervals, statistical tests and correlation coefficients were calculated in order to evaluate the effect of internal versus external FHR monitoring modes on the considered indices. The whole evaluation was repeated using FHR signals at a frequency of 2 Hz. Most time domain linear indices were similar with external and internal monitoring in the initial and final segments of the tracings. However, linear frequency domain indices were poorly correlated in the final segments and had significantly different mean values in the initial segments. Nonlinear indices were significantly different in both initial and final segments. The correlation between 4 and 2 Hz sampled parameters was high for both linear and nonlinear indices (most correlation coefficient values ranging between 0.95 and 1) but nonlinear index values were significantly higher at 2 Hz. In conclusion, the mode used to acquire FHR signals and the sampling rate employed can significantly affect most FHR indices. © 2006 IOP Publishing Ltd.
Keywords: abdomen; Algorithms; article; Cardiotocography; commercial phenomena; Confidence interval; controlled study; correlation coefficient; delivery; Diagnosis, Computer-Assisted; Electrocardiography; electrode; entropy; External and internal monitoring; Female; fetus electrocardiography; fetus monitoring; Foetal heart rate (FHR); Frequency domain analysis; Heart; Heart rate; human; intermethod comparison; intrapartum care; Linear and nonlinear analysis; Linear Models; mathematical computing; Nonlinear Dynamics; normal human; priority journal; Reproducibility of Results; sensitivity and specificity; sensor; Signal Processing, Computer-Assisted; Statistical significance; ultrasound; Variability

Leptin effect on RANKL and OPG expression in MC3T3-E1 osteoblasts - Lamghari, M.; Tavares, L.; Camboa, N.; Barbosa, M.A. (Journal of Cellular BiochemistryJ. Cell. Biochem., 2006)
Recent studies have suggested that leptin hormone may play a pivotal role on bone remodeling through a direct effect by modulating positively the OPG/RANKL balance. Here, we investigate the effect of leptin hormone on RANKL and OPG expression in MC3T3-E1 osteoblasts using RT-PCR and ELISA measurements. We have at first identified the expression of Ob-Rb and Ob-Ra leptin receptor isoforms in MC3T3-E1 and observed that these cells respond to mrleptin treatments. We then investigated the effect of mrleptin on RANKL and OPG expression. We show that mrleptin dose-dependently regulated the expression of RANKL mRNA with complete inhibition observed at concentrations higher than 12 ng/ml. This effect was confirmed with sRANKL protein measurements. However, the exposure of MC3T3-E1 to mrleptin had no effect on OPG mRNA. Taken together, these results suggest that leptin modulates positively OPG/RANKL balance by inhibiting the expression of RANKL gene. © 2006 Wiley-Liss, Inc.
Keywords: alkaline phosphatase; animal cell; Animals; article; bone remodeling; Carrier Proteins; Cell Line; enzyme linked immunosorbent assay; gene expression; gene expression regulation; Glycoproteins; hormone action; leptin; leptin receptor; leptin receptor a; leptin receptor b; MC3T3-E1; Membrane Glycoproteins; messenger RNA; Mice; mouse; nonhuman; Ob-Ra; Ob-Rb; OPG; osteoblast; Osteoblasts; osteoclast differentiation factor; Osteoprotegerin; priority journal; protein expression; RANK Ligand; RANKL; Receptor Activator of Nuclear Factor-kappa B; Receptors, Cell Surface; Receptors, Cytoplasmic and Nuclear; Receptors, Tumor Necrosis Factor; reverse transcription polymerase chain reaction; RNA extraction; RNA, Messenger; unclassified drug

Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery - Gonçalves, H.; Rocha, A.P.; Ayres-de-Campos, D.; Bernardes, J. (Medical and Biological Engineering and ComputingMed. Biol. Eng. Comput., 2006)
Linear and nonlinear fetal heart rate (FHR) indices, namely mean FHR, interval index (II), very low, low and high frequencies, approximate (ApEn) and sample entropy (SampEn), were computed, immediately before delivery, in the initial and final FHR tracing segments, from 48 normal, 10 mildly acidemic and 10 moderate-to-severely acidemic fetuses. Progression of labor was associated with a significant increase in linear frequency domain indices whereas nonlinear indices were significantly decreased. Moderate-to-severe fetal acidemia was associated with a significant decrease in nonlinear indices. The best discrimination between moderate-to-severe acidemic fetuses and the remaining cases was obtained combining II and ApEn(2,0.15), with a specificity of 71% and a sensitivity of 80%. These findings support the hypothesis of increased autonomic nervous system activity in the final minutes of labor and of decreased central nervous system activity, both in the final minutes of labor and in moderate-to-severe acidemic fetuses. © International Federation for Medical and Biological Engineering 2006.
Keywords: acidemia; Acidosis; Acids; article; autonomic nervous system; Biological materials; Cardiology; Central nervous system; clinical article; controlled study; delivery; Delivery, Obstetric; Discriminant Analysis; disease severity; entropy; Fetal Diseases; Fetal heart rate; Fetal heart rate (FHR); Fetal monitoring; fetus; fetus heart rate; Frequency domain analysis; Heart Rate, Fetal; human; Humans; hypothesis; labor; Linear and nonlinear indices; linear system; Neurology; newborn; nonlinear system; Prenatal Care; Second stage of labor; sensitivity and specificity; Severity of Illness Index

Lung parenchyma segmentation from CT images based on material decomposition - Vinhais, C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2006)
We present a fully automated method for extracting the lung region from volumetric X-ray CT images based on material decomposition. By modeling the human thorax as a composition of different materials, the proposed method follows a threshold-based, hierarchical voxel classification strategy. The segmentation procedure involves the automatic computation of threshold values and consists on three main steps: patient segmentation and decomposition, large airways extraction and lung parenchyma decomposition, and lung region of interest segmentation. Experimental results were performed on thoracic CT images acquired from 30 patients. The method provides a reproducible set of thresholds for accurate extraction of the lung parenchyma, needed for computer aided diagnosis systems. © Springer-Verlag Berlin Heidelberg 2006.
Keywords: Biological organs; Classification (of information); Computer simulation; Computerized tomography; Image segmentation; Lung parenchyma; Medical imaging; Patient segmentation; Patient treatment; Volumetric X-ray CT images; Voxel classification strategy

A model for educational simulation of neonatal cardiovascular pathophysiology. - Sá Couto, C.D.; van Meurs, W.L.; Goodwin, J.A.; Andriessen, P. (Simulation in healthcare : journal of the Society for Simulation in HealthcareSimul Healthc, 2006)
Full-body patient simulators provide a technological basis for clinical education without risk to real patients. In a previous study, we described a model for educational simulation of infant cardiovascular physiology. Using essentially the same methodology, we derive a mathematical model for the cardiovascular system of a healthy 1-week-old neonate. Computer simulations of this model result in vital signs that are close to target hemodynamic variables. Simulated systemic arterial pressure waveform and left ventricular pressure-volume loop are realistic, and the system reacts appropriately to blood loss. We also adapt the model structure and change its parameters to reflect the congenital heart defects: patent ductus arteriosus, tetralogy of Fallot, complex coarctation of the aorta with patent foramen ovale, and transposition of the great arteries. Simulated vital signs are again close to target hemodynamic variables. The resulting model for neonatal cardiovascular pathophysiology is an essential step in attaining a full-body, model-driven neonatal acute care simulator.
Keywords: article; cardiovascular disease; Cardiovascular Diseases; cardiovascular function; Cardiovascular Physiological Phenomena; cardiovascular system; Computer simulation; congenital heart malformation; Education, Medical, Graduate; educational model; Heart Defects, Congenital; human; Humans; infant welfare; Infant, Newborn; medical education; methodology; Models, Educational; Models, Theoretical; newborn; theoretical model

Modular neural network task decomposition via entropic clustering - Santos, J.M.; Alexandre, L.A.; De Sá, J.M. (Proceedings - ISDA 2006: Sixth International Conference on Intelligent Systems Design and ApplicationsProc. ISDA Sixth Int. Conf. Intelligent Syst. Design Applic., 2006)
The use of monolithic neural networks (such as a multilayer perceptron) has some drawbacks: e.g. slow learning, weight coupling, the black box effect. These can be alleviated by the use of a modular neural network. The creation of a MNN has three steps: task decomposition, module creation and decision integration. In this paper we propose the use of an entropie clustering algorithm as a way of performing task decomposition. We present experiments on several real world classification problems that show the performance of this approach. © 2006 IEEE.
Keywords: Classification (of information); Clustering algorithms; Decision Theory; Entropic clustering; Learning systems; Modular neural network task decomposition; Monolithic neural networks; Neural networks; Weight coupling

A multiclassifier approach for lung nodule classification - Pereira, C.S.; Alexandre, L.A.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2006)
The aim of this paper is to examine a multiclassifier approach to the classification of the lung nodules in X-ray chest radiographs. The approach investigated here is based on an image region-based classification whose output is the information of the presence or absence of a nodule in an image region. The classification was made, essentially, in two steps: firstly, a set of rotation invariant features was extracted from the responses of a multi-scale and multi-orientation filter bank; secondly, different classifiers (multi-layer perceptrons) are designed using different features sets and trained in different data. These classifiers are further combined in order to improve the classification performance. The obtained results are promising and can be used for reducing the false-positives nodules detected in a computer-aided diagnosis system. © Springer-Verlag Berlin Heidelberg 2006.
Keywords: Biological organs; Classification (of information); Computer aided diagnosis; False-positives nodules; Medical imaging; Multi-orientation filter bank; Radiography; X rays; X-ray chest radiographs

New developments of the Z-EDM algorithm - Silva, L.M.; Marques de Sá, J.; Alexandre, L.A. (Proceedings - ISDA 2006: Sixth International Conference on Intelligent Systems Design and ApplicationsProc. ISDA Sixth Int. Conf. Intelligent Syst. Design Applic., 2006)
In this paper we address some open questions on the recently proposed Zero-Error Density Maximization algorithm for MLP training. We propose a new version of the cost function that solves a training problem encountered in previous work and prove that the use of a nonparametric density estimator preserves the optimal solution. Some experiments are reported comparing this cost function to the usual mean-square error and cross entropy cost junctions. © 2006 IEEE.
Keywords: Algorithms; Cost functions; Mean square error; MLP training; Nonparametric density estimators; Optimization; Personnel training; Problem solving; Zero-Error Density Maximization algorithm

The N-terminal half of the peroxisomal cycling receptor Pex5p is a natively unfolded domain - Carvalho, A.F.; Costa-Rodrigues, J.; Correia, I.; Costa Pessoa, J.; Faria, T.Q.; Martins, C.L.; Fransen, M.; Sá-Miranda, C.; Azevedo, J.E. (Journal of Molecular BiologyJ. Mol. Biol., 2006)
Targeting of most newly synthesised peroxisomal matrix proteins to the organelle requires Pex5p, the so-called PTS1 receptor. According to current models of peroxisomal biogenesis, Pex5p interacts with these proteins in the cytosol, transports them to the peroxisomal membrane and catalyses their translocation across the membrane. Presently, our knowledge on the structural details behind the interaction of Pex5p with the cargo proteins is reasonably complete. In contrast, information regarding the structure of the Pex5p N-terminal half (a region containing its peroxisomal targeting domain) is still limited. We have recently observed that the Stokes radius of this Pex5p domain is anomalously large, suggesting that this portion of the protein is either a structured elongated domain or that it adopts a low compactness conformation. Here, we address this issue using a combination of biophysical and biochemical approaches. Our results indicate that the N-terminal half of Pex5p is best described as a natively unfolded pre-molten globule-like domain. The implications of these findings on the mechanism of protein import into the peroxisome are discussed. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Amino acids; amino terminal sequence; article; biogenesis; Calorimetry, Differential Scanning; cell membrane; cell receptor; Chromatography, Gel; circular dichroism; cytosol; differential scanning calorimetry; human; Humans; infrared spectroscopy; matrix protein; Natively unfolded; Peroxisomal protein import; peroxisome; Pex5p; priority journal; Protein conformation; protein degradation; protein domain; protein folding; protein interaction; protein Pex5p; protein structure; Protein Structure, Secondary; Protein Structure, Tertiary; protein transport; pts1 receptor; PTS1-receptor; Receptors, Cytoplasmic and Nuclear; Spectroscopy, Fourier Transform Infrared; unclassified drug

Osteoblast proliferation and morphology analysis on laser modified hydroxyapatite surfaces: Preliminary results - Teixeira, S.; Queiroz, A.C.; Monteiro, F.J.; Ferraz, M.P.; Vilar, R.; Eugénio, S. (Key Engineering MaterialsKey Eng Mat, 2006)
Biocompatibility has long been associated with surface microtopography, microtexture and microchemistry. The surface topography ultimately affects the nature and the strength of the interactions that occur at biomaterial-biological environment (cell adhesion, mobility, spreading and proliferation). Thus, it is necessary to produce and work with controlled microtopographical surfaces that present reproducible microdomains of a dimension similar to that of the biological elements of interest (for instance, cells). [1] There are a number of substrates that already have been studied (such as silicone, polystyrene, poly-L-lactic acid and titanium coated polystyrene) in terms of surface topography. [2] However, few studies are related to hydroxyapatite substrates. As it is well established, hydroxyapatite is a well known ceramic that is extremely used in medical applications, namely implants and coatings. In this work, the surface topography of dense hydroxyapatite substrates was altered by using KFr excimer laser. Excimer lasers produce high-intensity, pulsed ultraviolet radiation and are especially well suited for materials processing due to their large beam cross-section area, which permits using mask projection technologies to process relatively large areas in a single step.[3].
Keywords: Bone; cell adhesion; Cells; Ceramic materials; Excimer laser; Excimer lasers; hydroxyapatite; Microtexture; Microtopography; morphology; Strength of materials; Surface modification; Surface topography; Surface treatment

Silicon addition to hydroxyapatite increases nanoscale electrostatic, van der Waals, and adhesive interactions - Vandiver, J.; Dean, D.; Patel, N.; Botelho, C.; Best, S.; Santos, J.D.; Lopes, M.A.; Bonfield, W.; Ortiz, C. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
The normal intersurface forces between nanosized probe tips functionalized with COO
Keywords: Adhesives; article; Atomic force microscopy; Biocompatible Materials; biomaterial; Biomaterials; Bone; cell adhesion; chemical binding; chemical interaction; derjaguin landau verwey overbeek approximation; Durapatite; electrochemical analysis; Electrostatic; Electrostatics; high resolution force spectroscopy; hydroxyapatite; materials testing; mathematical analysis; Microscopy, Electron, Scanning; Monolayers; Nanomechanics; Nanostructures; Particle Size; Poisson distribution; Polycrystalline materials; Silicon; Silicon-substituted hydroxyapatite; Spectrophotometry; Spectroscopy; Spectroscopy, Fourier Transform Infrared; Stress, Mechanical; Surface charge; surface property; thiol derivative; Van der Waals; Van der Waals forces

Structural analysis of dextran-based hydrogels obtained chemoenzymatically - Ferreira, L.; Figueirecio, M.M.; Gil, M.H.; Ramos, M.A. (Journal of Biomedical Materials Research - Part B Applied BiomaterialsJ. Biomed. Mater. Res. Part B Appl. Biomater., 2006)
This work reports the results of structural analysis in novel dextran-acrylate (dexT70-VA) hydrogels generated chemoenzymatically. Porous structure as well as hydrogel surface and interior morphologies were evaluated by mercury intrusion porosimetry (MIP), nitrogen adsorption (NA), and scanning electron microscopy (SEM) analyses, as a function of the degree of substitution (DS), and initial water content used in the preparation of the hydrogel. MIP analysis showed that the overall networks were clearly macroporous with pore sizes ranging from 0.065 to 10 μm. As expected, the average pore size decreased as DS increased and as initial water content decreased. Moreover, the porosity values ranged from 75 up 90%, which shows that these hydrogels present an interconnected pore structure. Nitrogen adsorption analyses showed that the specific surface area of dexT70-VA hydrogels increased either by increasing the DS or by decreasing the initial water content of the hydrogel. SEM results revealed that the surface of hydrogels with lower DS presented either a porous structure or a polymeric "skin" covering the pores, whereas hydrogels with higher DS were totally porous. Furthermore, the interior morphology varied according to the DS and the initial water content of the hydrogels. Finally, the average pore size was also determined from the swelling of hydrogel using a theoretical model developed by FIory-Rehner. The comparison of the SEM and MIP results with the ones obtained by the equilibrium swelling theory of Flory-Rehner shows that this approach highly underestimates the average pore size. © 2005 Wiley Periodicals, Inc.
Keywords: acrylic acid; article; Biocompatible Materials; Chemical structure; Degree of substitution (DS); dextran; dextran acrylate; Dextrans; enzyme activity; Enzymes; equilibrium swelling theory; Gas adsorption; hydrogel; Hydrogels; materials testing; Mathematical models; Mercury intrusion porosimetry; Microscopy, Electron, Scanning; Molecular Structure; morphology; nitrogen; polymer; porosity; Scanning electron microscopy; Structural characterization; structure analysis; Surface Properties; theoretical model; unclassified drug; Water; water content

Three-dimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation - Amaral, I.F.; Sampaio, P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
In this investigation, the effect of the degree of acetylation (DA) of chitosan on the behavior of human osteoblastic MG-63 cells cultured in three-dimensional chitosan matrices was assessed. Chitosan sponges with DAs in the range of 4 to 49% were prepared and characterized in terms of microstructure, porosity, and pore size. Collagen sponges were used as 3D control. Cell proliferation was determined using the MTT assay while the retention of the osteoblastic phenotype was monitored by assaying alkaline phosphatase activity. Cell morphology, cytoskeletal organization, and viability were assessed using different microscopy techniques. Chitosan sponges showed a similar microstructure regardless the DA, except for the highest DA used, where a more heterogeneous pore distribution was observed. In terms of cell proliferation, alkaline phosphatase activity and cell viability, cells cultured in chitosan scaffolds performed as well as in the 3D control regardless the DA, except for the highest DA used, where an inhibitory effect on cell proliferation was found. However, while in sponges with DAs ≤ 13% cells attached and spread displaying long cell filopodia and numerous cell-to-cell contacts, in sponges with higher DAs cells tended to remain spherical and grow into spheroid-like cellular aggregates. In the present study, the DA played a key role in determining the affinity of osteoblastic cells towards the substrates, possibly by influencing the nature of the initial adsorbed protein layer. © 2005 Wiley Periodicals, Inc.
Keywords: Acetylation; Aggregates; alkaline phosphatase; article; Bone Regeneration; bone tissue; Bone tissue engineering; Cell culture; Cell Culture Techniques; Cell filopodia; cell growth; cell proliferation; Cell Shape; cell structure; cell survival; cell viability; chitosan; Collagen; confocal microscopy; controlled study; Cytoskeletal organization; cytoskeleton; Degree of acetylation (DA); enzyme activity; gel permeation chromatography; human; human cell; Humans; infrared spectroscopy; Microstructure; morphology; osteoblast; Osteoblastic cells; Osteoblasts; Phosphatase activity; porosity; Proteins; Scaffold; Scaffolds; Scanning electron microscopy; Substrates; Tissue engineering

Time-lapse analysis of stem-cell divisions in the Arabidopsis thaliana root meristem - Campilho, A.; Garcia, B.; Toorn, H.V.D.; Wijk, H.V.; Campilho, A.; Scheres, B. (Plant JournalPlant J., 2006)
In the Arabidopsis root, asymmetric stem-cell divisions produce daughters that form the different root cell types. Here we report the establishment of a confocal tracking system that allows the analysis of numbers and orientations of cell divisions in root stem cells. The system provides direct evidence that stem cells have lower division rates than cells in the proximal meristem. It also allows tracking of cell division timing, which we have used to analyse the synchronization of root cap divisions. Finally, it gives new insights into lateral root cap formation: epidermal stem-cell daughters can rotate the orientation of the division plane like the stem cell. © 2006 The Authors.
Keywords: Arabidopsis; Arabidopsis thaliana; article; cell cycle; Cell Division; Cells; cytology; Development; Growth; Growth kinetics; Image analysis; meristem; Photoperiod; photoperiodicity; Plant; plant root; Plant roots; Plants; Plants (botany); Real-time; stem cell; Stem cells; Stem-cell daughters; time; Time Factors

Titanium dental implants coated with Bonelike®: Clinical case report - Lobato, J.V.; Sooraj Hussain, N.; Botelho, C.M.; Maurício, A.C.; Lobato, J.M.; Lopes, M.A.; Afonso, A.; Ali, N.; Santos, J.D. (Thin Solid FilmsThin Solid Films, 2006)
The aim of the study was to evaluate the direct bone bonding and osteointegration of the commercial pure (cp Ti) implants coated with Bonelike® synthetic bone graft by plasma spraying. The Bonelike® coated implant was placed in the mandible of a 40-year-old patient and it was removed after a healing period of 3 months with a trephine of 6 mm diameter. The structure of the coating and new bone/implant interface of retrieved samples were evaluated using scanning electron microscopy (SEM) and histological analysis using light microscopy. In vivo microstructure observations of Bonelike® coated retrieved implants showed excellent bone remnants on its surface without any tissue and inflammatory signs observed. The reported Bonelike® coated (cp Ti) implants improved primary stability, which may increase the lifetime of the implant. Bonelike® coated dental implants proved to be highly bioactive with extensive new bone formation and strongly bonded to Bonelike® coating. © 2005 Elsevier B.V. All rights reserved.
Keywords: Bone; Bone Regeneration; Bone/implant interface; Bonelike® coatings; Clinical applications; Dental Implants; Dental prostheses; Hip prostheses; Medical applications; Optical microscopy; Plasma spraying

The uptake of titanium ions by hydroxyapatite particles - Structural changes and possible mechanisms - Ribeiro, C.C.; Gibson, I.; Barbosa, M.A. (BiomaterialsBiomaterials, 2006)
In order to understand the effect of titanium ions on the molecular structure of hydroxyapatite (HAp), HAp powders were incubated in solutions with different titanium concentrations. After incubation, the powders obtained were analysed using different techniques, namely X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), differential thermal analysis (DTA), X-ray photoelectron spectroscopy (XPS), and energy dispersive spectroscopy (EDS). The results suggest that, depending on the concentration of titanium in solution, two different mechanisms of interaction with HAp occur. For concentrations equal to or smaller than 200 ppm, the titanium uptake by the solid seems to be primarily due to incorporation in the lattice. For higher concentrations, a dissolution-precipitation process seems to occur, leading to formation of a titanium phosphate compound. © 2005 Elsevier Ltd. All rights reserved.
Keywords: article; Biocompatible Materials; concentration response; differential scanning calorimetry; drug mechanism; drug structure; Durapatite; Energy dispersive spectroscopy; Fourier transform infrared spectroscopy; hydroxyapatite; Incubation; infrared spectroscopy; Ions; Lattice constants; particulate matter; powder; Precipitation (chemical); priority journal; Solutions; Spectroscopy; Spectroscopy, Fourier Transform Infrared; temperature; Titanium; Titanium ions; Titanium phosphate; X ray diffraction; X ray diffraction analysis; X ray photoelectron spectroscopy; X-Ray Diffraction

Adsorption isotherm of sodium ampicillin onto dense and porous hydroxyapatite - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2005)
The adsorption behaviour of sodium ampicillin to dense and porous hydroxyapatite as been extensively studied through the obtention of an adsorption isotherm. This isotherm was produced at body temperature, and a wide range of antibiotic solutions were used. The adsorption behaviour was measured by UV spectroscopy. The shape of the isotherm for the two forms of the material,dense and porous, indicates that the adsorption behaviour of the antibiotic seems to be different, however this is due to the adsorption taking place within the pores of the porous material, thus showing a larger amount of antibiotic adsorbed.
Keywords: Adsorption; Adsorption behavior; Adsorption isotherms; ampicillin; Antibiotics; hydroxyapatite; Porous hydroxyapatite; Porous materials; Sodium ampicillin; Sodium compounds; Ultraviolet spectroscopy

Assessment of the potential of Bonelike® graft for bone regeneration by using an animal model - Lobato, J.V.; Hussein, N.S.; Botelho, C.M.; Rodrigues, J.M.; Luís, A.L.; Maurício, A.C.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2005)
Bonelike® graft that mimics the inorganic composition of bone tissue has been developed and characterized over the last decade. To evaluate the osteoconductivity of Bonelike® two granule size ranges, one ranging from 150-250μm and the other from 250-500μm were implanted in the femurs of New Zealand White rabbits, aiming at being clinically used in different medical applications, such as dentistry and orthopaedics. In order to facilitate the medical application of the Bonelike® graft the use of a commercially available polymeric vehicle was also analyzed. Radiological examination, histological studies and scanning electron microscopy (SEM) analyses revealed that the surface of Bonelike® granules was almost completely surrounded by new bone formation after 12 weeks of implantation, which proves its highly osteoconductive behaviour.
Keywords: animal model; Animal models; Animals; Biomaterials; Biomedical engineering; Biomimetic materials; Bone; bone tissue; Bonelike graft; Bonelike® graft; Granular materials; In vivo studies; Scanning electron microscopy

Biocatalytic synthesis of highly ordered degradable dextran-based hydrogels - Ferreira, L.; Gil, M.H.; Cabrita, A.M.S.; Dordick, J.S. (BiomaterialsBiomaterials, 2005)
We have prepared unique macroporous and ordered dextran-based hydrogels using a single-step biocatalytic transesterification reaction between dextran and divinyladipate in neat dimethylsulfoxide. These hydrogels show a unimodal distribution of interconnected pores with average diameters from 0.4 to 2.0 μm depending on the degree of substitution. In addition, the hydrogels show a higher elastic modulus for a given swelling ratio than chemically synthesized dextran-based hydrogels. In vivo studies in rats show that the hydrogel networks are degradable over a range of time scales from 5 to over 40 days, and possess good biocompatibility, as reflected in only a mild inflammatory reaction and minor fibrous capsule formation during the time-frame of subcutaneous implantation. These combined properties may offer competitive advantages in biomedical applications ranging from tissue engineering to controlled drug delivery. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Absorbable Implants; adipic acid derivative; animal experiment; animal tissue; Animals; article; Bacillus subtilis; Biocatalysts; Biocompatibility; Biocompatible Materials; Biodegradation; Biomedical engineering; biosynthesis; catalysis; Controlled drug delivery; controlled study; Cross-linking; dextran; Dextran-based hydrogels; Dextrans; dimethyl sulfoxide; Dimethylsulfoxide; Elastic moduli; Elasticity; Enzyme; Foreign-Body Reaction; hydrogel; Hydrogels; implantation; in vivo study; Inflammation; male; materials testing; nonhuman; Peptide Hydrolases; porosity; priority journal; rat; Rats; Rats, Wistar; substitution reaction; Sulfur compounds; Surface Properties; Swelling; Swelling ratio; synthesis; Tissue; transesterification; Transesterification reactions

Biological behaviour of Bonelike® graft implanted in the tibia of humans - Gutierres, M.; Hussain, N.S.; Afonso, A.; Almeida, L.; Cabral, T.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2005)
This paper reports the ability of Bonelike® to regenerate bone defected areas when implanted in the tibia of 3 patients (average age of 59 years) during a high tibial osteotomy (HTO) to treat medial compartment osteoarthritis of the knee. Bonelike® is a synthetic bone graft designed to mimic the inorganic composition of bone using a patent process that consists of liquid sintering hydroxyapatite in the presence of CaO-P 2O 5 based glass. The preliminary clinical evaluation performed showed that an intimate contact between new formed bone and Bonelike® was established (67±10%), with no fibrous interface. Therefore, Bonelike® is a single-handedly viable osteoconductive synthetic grafting material as it has been demonstrated from the profiles of radiological, histological and scanning electron microscopy analyses for the six months implantation period.
Keywords: Biological behavior; Bone; Bonelike® graft; Clinical trials; histology; hydroxyapatite; Implants (surgical); Radiology; Scanning electron microscopy; Surgery; Synthetic grafting material

Biological evaluation of calcium alginate microspheres as a vehicle for the localized delivery of a therapeutic enzyme - Barrias, C.C.; Lamghari, M.; Granja, P.L.; Sá Miranda, M.C.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
Gaucher disease (GD) is caused by the decreased activity and/or stability of the lysosomal enzyme glucocerebrosidase (GCR). The available treatment consists in the intravenous administration of exogenous GCR, and is effective in reverting most of the symptoms. However, in terms of bone pathology, which is among the most disabling manifestations, a slow and incomplete response is observed, indicating that adjuvant therapies are necessary to consistently restore GCR activity in bone and accelerate regeneration. In this study, calcium alginate microspheres were analyzed as a vehicle for localized GCR delivery to bone. Results demonstrated that the entrapped enzyme retained full activity and exhibited a broader pH-dependent activity profile, compared to that of free-GCR, with improved stability at physiological pH. GCR release profile was established, and it was demonstrated that GCR could be released in a sustained manner. The biological behavior of the system was evaluated by analyzing the uptake of released GCR by GCR-deficient cells from GD patients, using different techniques: GCR activity measurements, radiolabeling, and cellulose acetate electrophoresis. Results demonstrated that GCR was internalized by cells significantly enhancing the residual enzymatic activity. To achieve an activity reconstitution level comparable to that obtained using free-GCR, only half of the dose was required with entrapped-GCR. © 2005 Wiley Periodicals, Inc.
Keywords: Alginates; alginic acid; article; Bone; bone disease; Bone Regeneration; Calcium alginate; Calcium Compounds; catalysis; Cell culture; Cells, Cultured; controlled study; Drug Carriers; drug delivery system; enzyme activity; enzyme assay; enzyme replacement; Enzymes; Enzymes, Immobilized; fibroblast culture; Fibroblasts; Gaucher disease; Gaucher disease (GD); Glucocerebrosidase (GCR); Glucosylceramidase; Glucuronic Acid; Hexuronic Acids; human; human cell; Humans; iodine 125; Localized delivery; lysosome enzyme; lysosome storage disease; microsphere; Microspheres; Pathology; pH effects; physiology; recombinant enzyme; Therapeutic enzyme

Bone substitutes: General concepts and "state of the art" - Gutierres, M.; Ascensão Lopes, M.; Sooraj Hussain, N.; Trigo Cabral, A.; Almeida, L.; Domingos Santos, J. (Substitutos ósseos: Conceitos gerais e estado actualArquivos de MedicinaArq. Med., 2005)
Bone grafts are nowadays the subject of extensive research worldwide, aimed at overcoming limitations associated with the use of autografts or bone banks to fill bone defects. Additionally, the use of osteogenic substances opens new perspectives in the treatment of fractures, pseudarthroses and vertebral arthrodeses. Due to the large amount of information available in the area of bone grafts, this paper aims not only to revise general concepts but also to summarize what has been published recently in the area of bone substitutes for bone regeneration. ©ArquiMed, 2006.
Keywords: Autografts; biomaterial; bone defect; bone demineralization; bone development; Bone graft; Bone growth factors; Bone morphogenetic protein; bone prosthesis; calcium phosphate; calcium sulfate; cortical bone; fibroblast growth factor; fracture; health care facility; health status; human; hydroxyapatite; platelet derived growth factor; pseudarthrosis; publication; review; somatomedin C derivative; spondylarthritis; transforming growth factor

Bonelike®/PLGA hybrid materials for bone regeneration: Preparation route and physicochemical characterisation - Oliveira, J.M.; Miyazaki, T.; Lopes, M.A.; Ohtsuki, C.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2005)
Bonelike®/PLGA hybrid materials have been developed using γ-MPS as silane-coupling agent between the inorganic and organic phases for controlled drug delivery applications. Silanization showed to be more effective when cyclohexane was used as a non-polar solvent (nP method) due to a chemical interaction between Bonelike®, and the silane film, while by using a 95/5 (V/V) methanol/water as a polar solvent (P method), a much thinner film was achieved. Functional groups of PLGA, such as the carbonyl group (C=O), were identified using Raman and FTIR-ATR analysis and therefore these groups may be used to link therapeutic molecules. These novel hybrid materials prepared by combining silanization and post-hybridisation processes are expected to find use in medical applications of bone regeneration and as drug delivery carrier for therapeutic molecules. © 2005 Springer Science + Business Media, Inc.
Keywords: analytic method; article; Biological materials; Bone; Bone Regeneration; carbonyl derivative; chemical bond; chemical interaction; chemical reaction; Chemical reactions; chemistry; Chemistry, Physical; cyclohexane; Drug delivery; drug delivery system; Drug therapy; Durapatite; film; Fourier transform infrared spectroscopy; Hybrid materials; hybridization; hydroxyapatite; infrared spectroscopy; Lactic Acid; methanol; methodology; Microscopy, Electron, Scanning; Molecules; physical chemistry; polyglactin; polyglycolic acid; polylactic acid polyglycolic acid copolymer; polylactic acid-polyglycolic acid copolymer; polymer; Polymers; priority journal; Raman spectrometry; Raman spectroscopy; reaction analysis; Scanning electron microscopy; silane; silane derivative; Silanes; Silanization; solvent effect; Solvents; Spectroscopy, Fourier Transform Infrared; Spectrum Analysis, Raman; synthesis; Water; X ray; X-Rays

Characterization of fetal heart rate using approximate entropy - Marques De Sá, J.P. (Computers in CardiologyComput Cardiol, 2005)
Approximate entropy (ApEn) is an interesting measure for assessing the irregularity of time series and in particular for characterizing heart rate variability. In the present paper we apply ApEn to the characterization of three patterns of fetal heart rate (FHR): calm sleep; calm vigilance; pathological flat-sinusoidal condition. We conclude that ApEn can perfectly discriminate the pathological FS pattern from the normal A and C patterns and is far better for FHR pattern discrimination than classic time-domain variability indexes used in clinical practice. © 2005 IEEE.
Keywords: Approximate entropy (ApEn); Cardiology; Fetal heart rate; Fetal monitoring; Heart rate variability; Pathology; Sleep research; Time domain analysis

Chemical modification of chitosan by phosphorylation: An XPS, FT-IR and SEM study - Amaral, I.F.; Granja, P.L.; Barbosa, M.A. (Journal of Biomaterials Science, Polymer EditionJ. Biomater. Sci. Polym. Ed., 2005)
In the present work, the surface of chitosan membranes was modified using a phosphorylation method carried out at room temperature. Phosphorylation may be of particular interest in materials for orthopaedic applications, due to the cation-exchange properties of phosphate functionalities. Phosphate groups chelate calcium ions, thus inducing the deposition of an apatite-like layer known to improve the osteoconduction of polymer-based implants. Additionally, the negatively charged phosphate functionalities, together with the positively charged amine groups from chitosan, are expected to provide chitosan with an amphoteric character, which may be useful as a combinatorial therapeutic strategy, by simultaneously allowing the immobilization of signalling molecules like growth factors. Phosphorylation was carried out at room temperature using the H 3 PO 4/Et 3 PO 4/P 2O 5/butanol method. Surface characterization was performed by XPS, ATR-FT-IR, and SEM. Cross-sections were analyzed by SEM fitted with EDS. The phosphate content increased with the reaction time, as shown by XPS and ATR-FT-IR, a P/N atomic ratio of 0.73 being obtained after 48 h of treatment. High-resolution XPS spectra regarding C 1s, O 1s, N 1s and P 2p are discussed. The introduction of a neutralization step led to a reduction of P content, which pointed out to the presence of phosphates ionically bound to protonated amines, in addition to phosphate esters. EDS analysis of cross-sections revealed a gradual P reduction up to 50% towards the inner part of the membrane. © VSP 2005.
Keywords: Acetylation; amine; animal; Animals; Apatite; article; bone conduction; butanol; calcium ion; cation exchange; cephalopod; chelate; Chemical modification; chemistry; Chitin; chitosan; comparative study; controlled study; Decapodiformes; Fourier transform infrared spectroscopy; Fourier transform infrared spectroscopy (FT-IR); Growth factor; immobilization; Implants (surgical); infrared spectroscopy; isolation and purification; Microscopy, Electron, Scanning; molecular weight; organophosphate; phosphate; Phosphate groups; Phosphates; Phosphorylation; Phosphorylation method; Plastics applications; priority journal; reflectometry; room temperature; Scanning electron microscopy; SEM-EDS; signal transduction; spectrometry; Spectrometry, X-Ray Emission; Spectroscopy, Fourier Transform Infrared; Surface chemical reaction; Surface Properties; surface property; temperature; time; Time Factors; viscosity; X ray photoelectron spectroscopy; X-rayphotoelectron spectroscopy (XPS)

Data parallel scheduling of operations in linear algebra on heterogeneous clusters - Morais, C.; Barbosa, J.; Tadeu, P. (WSEAS Transactions on ComputersWSEAS Trans. Comput., 2005)
The aim of data and task parallel scheduling for dense linear algebra kernels is to minimize the processing time of an application composed by several linear algebra kernels. The scheduling strategy presented here combines the task parallelism used when scheduling independent tasks and the data parallelism used for linear algebra kernels. This problem has been studied for scheduling independent tasks on homogeneous machines. Here it is proposed a methodology for heterogeneous clusters and it is shown that significant improvements can be achieved with this strategy.
Keywords: Computational complexity; Computer simulation; Heterogeneous clusters; Linear algebra; Mathematical models; Optimization; Parallel algorithms; Parallel processing systems; Parallel tasks; Static scheduling

Development of a system to adsorb drugs onto calcium phosphate materials - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2005)
Several studies were carried out in order to reduce the systemic use of antibiotics due to the high concentration required to provide the minimum inhibitory concentration (MIC) at infected sites. The aim of this study was to develop a system of drug adsorption onto commercial hydroxyapatite (HA, Ca 10(PO 4) 6(OH) 2) and glass reinforced hydroxyapatite (GR-HA) granules. The drug will then be released for the local treatment of periodontitis. The antibiotics used in this study were metronidazole, a specific antibiotic indicated for the systemic treatment of periodontitis, and ampicillin, a wide spectrum antibiotic. UV spectroscopy was used to measure the amount of drug adsorbed onto HA and GR-HA granules. Results showed that metronidazole was unable to adsorb on the material's surface, as opposed to ampicillin which adsorbed both onto HA and GR-HA. Preliminary release kinetics studies were carried out using a flow through dissolution system. Results are discussed in terms of the influence of the different surface characteristics of the materials on the adsorption processes. © 2005 Springer Science + Business Media, Inc.
Keywords: Adsorption; ampicillin; Anti-Infective Agents; Antibiotics; article; Calcium Compounds; calcium phosphate; Calcium phosphates; Coated Materials, Biocompatible; concentration response; Delayed-Action Preparations; Diffusion; Dissolution; drug absorption; drug adsorption; Drug Carriers; Drug release; drug stability; glass; Glass reinforced hydroxyapatie (GR-HA); human; Humans; hydroxyapatite; Kinetics; Material's surface; Materials science; materials testing; metronidazole; minimum inhibitory concentration; Minimum inhibitory concentration (MIC); periodontitis; priority journal; Reaction kinetics; reduction; surface property; Ultraviolet spectroscopy

Effect of calcium phosphate addition to alginate microspheres: modulation of enzyme release kinetics and improvement of cell adhesion - Barrias, C.C.; Ribeiro, C.C.; Rodrigues, D.; Miranda, M.C.S.; Barbosa, M.A. (Key Engineering MaterialsKey Eng Mat, 2005)
In this study, the addition of calcium phosphate powders to an alginate matrix was evaluated as a strategy to modulate enzyme release-kinetics from alginate microspheres and, simultaneously, to improve cell adhesion to the polymer. Pre-adsorption of the enzyme to the ceramic powders resulted in a more adequate release pattern. The ratio of ceramic-to-polymer had a pronounced effect on osteoblast adhesion to microspheres. Cells were only able to spread on microspheres with the highest percentage of ceramic (0.4 w/w using a 1.5% w/v alginate solution).
Keywords: Alginate; Bioceramics; calcium phosphate; Calcium titanium phosphate; cell adhesion; Enzyme kinetics; Enzyme release; hydroxyapatite; Microspheres; Osteoblasts

Feature extraction for classification of thin-layer chromatography images - Sousa, A.V.; Mendonça, A.M.; Campilho, A.; Aguiar, R.; Sá Miranda, C. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2005)
Thin-Layer Chromatography images are used to detect and identify the presence of specific oligosaccharides, expressed by the existence, at different positions, of bands in the gel image. ID gaussian deconvolution, commonly used for band detection, does not produce good results due to the large curvature observed in the bands. To overcome this uncertainty on the band position, we propose a novel feature extraction methodology that allows an accurate modeling of curved bands. The features are used to classify the data into two different classes, to differentiate normal from pathologic cases. The paper presents the developed methodology together with the analysis and discussion of the results. © Springer-Verlag Berlin Heidelberg 2005.
Keywords: Edge detection; Feature extraction; Image analysis; Image segmentation; Oligosaccharides; Thin layer chromatography; Thin-Layer Chromatography images

Genetic model-based segmentation of chest X-ray images using free form deformations - Vinhais, C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2005)
A method is proposed to segment digital posterior-anterior chest X-ray images. The segmentation is achieved through the registration of a deformable prior model, describing the anatomical structures of interest, to the X-ray image. The deformation of the model is performed using a deformation grid. A coarse matching of the model is done using anatomical landmarks automatically extracted from the image, and maps of oriented edges are used to guide the deformation process, optimized with a probabilistic genetic algorithm. The method is applied to extract the ribcage and delineate the mediastinum and diaphragms. The segmentation is needed for defining the lungs region, used in computer-aided diagnosis systems. © Springer-Verlag Berlin Heidelberg 2005.
Keywords: Computer aided analysis; Diaphragms; Feature extraction; Free Form Deformation; Gabor Filters; Genetic Algorithms; Image segmentation; Model-based Image Segmentation; Optimization; Pattern matching; X ray analysis

Improving the adhesion of poly(ethylene terephthalate) fibers to poly(hydroxyethyl methacrylate) hydrogels by ozone treatment: Surface characterization and pull-out tests - Ferreira, L.; Evangelista, M.B.; Martins, M.C.L.; Granja, P.L.; Esteves, J.L.; Barbosa, M.A. (PolymerPolymer, 2005)
This work reports a methodology to improve the adhesion between poly(ethylene terephthalate) (PET) fibers and poly(hydroxyethyl methacrylate) (pHEMA) hydrogels by treating PET with ozone. The surface chemistry of PET was examined by water contact angle measurements, X-ray photoelectron spectroscopy (XPS), infrared reflection absorption spectroscopy (IRAS) and attenuated total reflectance infrared spectroscopy (ATR-IR) yielding information about the chemical functionalities at depths upon 0.6 μm. Ozone treatment introduces several polar groups in the surface of PET through oxidation and chain scission resulting in increased wettability. These groups include mostly carboxylic and anhydride groups and in small extent hydroxyl groups. Atomic force microscopy (AFM) analysis shows that the surface of ozone-treated PET films is fully covered with spherical particles that are removed after washing the film with water. During the washing step carboxylic functionalities were removed preferentially, as demonstrated by XPS and IR analysis. According to pull-out tests, PET monofilaments and bundles treated by ozone had a higher adhesion to pHEMA hydrogels than untreated ones. The apparent interfacial shear strength is 65% higher on pHEMA hydrogel containing an ozonated than an untreated PET monofilament. In addition, the force to pull-out an ozone-treated PET bundle from pHEMA hydrogel is ca. 81% higher than the one observed for the untreated bundle. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Adhesion; Atomic force microscopy; Contact angle; hydrogel; Hydrogels; infrared spectroscopy; Oxidation; Ozone; ozone treatment; Ozone treatments; Poly(ethylene terephthalate); polyethylene terephthalate fiber; Polyethylene terephthalates; Polymethyl methacrylates; pull-out; Pull-out tests; Surface characterization; Surface chemistry; surface property; X ray photoelectron spectroscopy

In situ thermal and structural characterization of bioactive calcium phosphate glass ceramics containing TiO 2 and MgO oxides: High temperature - XRD studies - Dias, A.G.; Skakle, J.M.S.; Gibson, I.R.; Lopes, M.A.; Santos, J.D. (Journal of Non-Crystalline SolidsJ Non Cryst Solids, 2005)
This study aims to develop glass ceramics in the calcium phosphate system that exhibit suitable properties to be used for biomedical applications. Calcium phosphate glasses with the incorporation of small additions of MgO and TiO 2 oxides were prepared in the pyro-and orthophosphate regions. The glass ceramics were prepared by a controlled powder sintering process through heat-treatment at different temperatures, as defined by results from differential thermal analysis (DTA). The composition of the crystalline phases precipitated in the glassy matrix as a result of heat treatments at different temperatures, ranging from 681 to 725 °C, was determined from X-ray diffraction data. The sequence of phase crystallization in the mother glass was also studied in situ using high temperature X-ray diffraction (HT-XRD) analysis. Results showed that the first phases that precipitated in the glass matrix were α- and β-Ca 2P 2O 7 at 620 °C. A small amount of CaTi 4(PO 4) 6 appeared at 630 °C. At 650 °C the three phases α-Ca 2P 2O 7, β-Ca 2P 2O 7 and CaTi 4(PO 4) 6 were clearly presented with a small amount of TiP 2O 7 and finally at 660 °C all four phases were observed. Glass ceramics were also characterized using Raman and X-ray photoelectron spectroscopy. This study demonstrates that, by altering the heat treatment cycle, it is possible to prepare glass ceramics in the calcium phosphate system that contains different bioactive and biocompatible phases. © 2005 Published by Elsevier B.V.
Keywords: Biocompatibility; Calcium Compounds; Calcium phosphate systems; Cavity fillers; Computer software; Crystallinity; Differential thermal analysis; Fourier transform infrared spectroscopy; Glass ceramics; Magnesia; Phase analysis; Raman spectroscopy; Titanium dioxide; X ray diffraction analysis; X ray photoelectron spectroscopy

In vitro analysis of protein adhesion to phase pure hydroxyapatite and silicon substituted hydroxyapatite - Botelho, C.M.; Brooks, R.A.; Kawai, T.; Ogata, S.; Ohtsuki, C.; Best, S.M.; Lopes, M.A.; Santos, J.D.; Rushton, N.; Bonfield, W. (Key Engineering MaterialsKey Eng Mat, 2005)
The adhesion of bovine collagen type I, bovine serum albumin, bovine IgG, 1 % and 10 % (v/v) human serum to hydroxyapatite (HA), silicon-substituted hydroxyapatite (Si-HA) and tissue culture plastic were studied. The materials were incubated at 37°C for 30 minutes, after which the protein solution was removed and analyzed. The adsorbed protein was evaluated by electrophoresis and immunoassay after extraction from the materials. The degree of adhesion was higher for collagen, followed by IgG and albumin on all materials. However there was no difference in the amount of collagen adsorbed onto the surface of each material and this was also the finding with albumin and IgG. These results suggest that the increased bioactivity seen with Si-HA is not due to the degree of protein adhesion, but may possibly be due to changes in the conformation of the bound proteins.
Keywords: Adsorption; Bioactivity; Bovine collagen type I; Bovine collagens; Bovine serum proteins; Collagen; Human serum proteins; hydroxyapatite; Immunoglobulin G (IgG); immunology; Silicon-substituted hydroxyapatite; Substitution reactions; Tissue culture

In vitro biodegradability of chitosan-organosiloxane hybrid membrane - Tsuru, K.; Shirosaki, Y.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Fernandas, M.H. (Key Engineering MaterialsKey Eng Mat, 2005)
Chitosan-silicate hybrid membranes were prepared using γ- glycidoxypropyltrimethoxysilane (GPSM) through a sol-gel process. The amino groups of chitosan chains were reacted with the epoxy groups of GPSM and GPSM have a function as the agent to cross-link the chitosan chains. The cross-linking degree of the hybrid membranes was determined by ninhydrin assay. Fourier-transform infrared (FT-IR) spectroscopy and 29Si cross-polarization (CP) magic-angle spinning (MAS)-NMR spectroscopy were used to assess the structure of the hybrid membranes. The biodegradability of the hybrid membranes in phosphate-buffered saline solution or lysozyme solution was investigated as a function of the GPSM concentration.
Keywords: biodegradability; Biological membranes; chitosan; Chitosan chains; Chitosan inorganic hybrid membranes; Chitosan-lnorganlc hybrid; Crosslinking; Fourier transform infrared spectroscopy; Nuclear magnetic resonance spectroscopy; R- glycidoxypropyltrimethoxysilane GPSM; Reaction kinetics; Silicates; Sol-gel process

In vitro cytocompatibility of MG63 cells on chitosan-organosiloxane hybrid membranes - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (BiomaterialsBiomaterials, 2005)
Chitosan-silicate hybrids were synthesized using γ- glycidoxypropyltrimethoxysilane (GPSM) as the agent for cross-linking the chitosan chains. CaCl 2 was introduced in the hybrids in expectation that it would improve cell adhesion and differentiation of the hybrid surfaces. Fourier-transform infrared (FT-IR) spectroscopy and 29Si CP-MAS NMR spectroscopy were used to analyze the structures of the hybrids. Cytocompatibility of the hybrids was investigated in terms of proliferation of an osteoblastic cell line, MG63. The adhesion and proliferation of the osteoblastic cells cultured on the surface of a chitosan-GPSM hybrid without calcium were similar to those on a control culture plate, and were better than those on a chitosan membrane. The ALP activity of the cells cultured on this hybrid was higher than that on the chitosan membrane. Contrary to expectations, the incorporation of calcium ions into the hybrids did not improve cell attachment and proliferation on their surfaces. © 2004 Elsevier Ltd. All rights reserved.
Keywords: alkaline phosphatase; article; artificial membrane; Biocompatibility; Biocompatible Materials; Bone Neoplasms; Calcium; calcium chloride; cell adhesion; Cell attachments; Cell culture; cell differentiation; Cell Division; Cell Line, Tumor; chitosan; chitosan derivative; controlled study; cross linking; Cross-Linking Reagents; Crosslinking; Cytocompatibility; Fourier transform infrared spectroscopy; human; human cell; Humans; hybrid; infrared spectroscopy; Magnetic Resonance Spectroscopy; materials testing; Membranes, Artificial; MG63 osteoblastic cells; Microscopy, Electron, Scanning; Neoplasm Proteins; Nuclear magnetic resonance spectroscopy; Organic-inorganic hybrid; osteoblast; Osteoblasts; Osteosarcoma; priority journal; Silanes; Silicates; siloxane; Spectroscopy, Fourier Transform Infrared; structure analysis; surface property; Synthesis (chemical); wettability; γ-Glycidoxypropyltrimethoxysilane (GPSM)

In vitro degradation behavior of a novel bioresorbable composite material based on PLA and a soluble CaP glass - Navarro, M.; Ginebra, M.P.; Planell, J.A.; Barrias, C.C.; Barbosa, M.A. (Acta BiomaterialiaActa Biomater., 2005)
Poly(α-hydroxy acids), and in particular polylactic acid (PLA), are nowadays amongst the most used bioabsorbable materials. However, this polymer may not meet some application requirements due to inadequate mechanical properties and or its degradation characteristics. A possible strategy to tackle this problem is the incorporation of an inorganic phase into the polymeric matrix. In this work a new fully biodegradable composite material made with PLA and calcium phosphate soluble glass particles has been developed. The behaviour of the PLA/ glass composite has been analysed during its degradation in simulated physiological conditions by means of weight loss, molecular weight and thermal properties analysis and electron microscopy observation. The results showed that the incorporation of phosphate glass particles into the polymer significantly accelerated the degradation of the PLA and induced the formation of calcium phosphate precipitates at the composite surface. © 2005 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Absorbable Implants; Absorption; article; biodegradability; Biodegradable composite; Biomimetic materials; Body fluids; Bone Regeneration; Bone Substitutes; calcium phosphate; Calcium phosphates; composite material; Degradation; electron microscopy; glass; In vitro degradation; in vitro study; Lactic Acid; materials testing; molecular weight; observation; Phosphate glass; polylactic acid; Polymers; precipitation; priority journal; reaction analysis; simulation; Solubility; Surface Properties; surface property; temperature; weight reduction

In vitro studies of calcium phosphate glass ceramics with different solubility with the use of human bone marrow cells - Dias, A.G.; Lopes, M.A.; Trigo Cabral, A.T.; Santos, J.D.; Fernandes, M.H. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
Two glass ceramics in the CaO-P 2O 5-MgO system with the incorporation of K 2O or TiO 2 oxides were prepared with the goal of using them as potential bone graft substitutes. The incorporation of TiO 2 and K 2O led to the preparation of specific crystalline phases in the structure of the glass ceramics, which show different degrees of biodegradation. In fact, the 45CaO-45P 2O 5-5MgO-5K 2O has been previously demonstrated to be much more soluble in aqueous solutions than the 45CaO-37P 2O 5-5MgO-13TiO 2 glass ceramic. The in vitro biological activity of the two calcium phosphate glass ceramics was studied with the use of human bone marrow osteoblast cell cultures maintained for 28 days, and seeded materials were assessed for cell proliferation and function. The Ti-containing glass ceramic showed a stable surface throughout the culture time, on macroscopic and SEM observation. Osteoblast cells proliferated gradually, especially during the third week, with a high alkaline phosphatase activity and formation of a mineralized matrix. On SEM observation, attached cells appeared with a spreadpolygonal morphology typical of the osteoblast cells, with extensive cell-to-cell contact. Cell behavior on the seeded material was similar to that found on cultures performed on tissue-culture-grade polystyrene; except for the presence of lower cell numbers during the first 2 weeks. By contrast, the K-containing glass ceramic showed a highly instable surface with dissolution/precipitation processes occurring throughout the culture time. Few cells adhered to the material surface, and subsequent proliferation was also hindered, especially from the first week onwards. Cell numbers were significantly lower than those observed in the Ti-containing glass ceramic during most of the incubation time. Results suggest that the different in vitro biological behavior of these two glass ceramics is mainly due to the significant differences in the surface degradation rate, which is directly correlated to the chemical composition of the mother glass. © 2005 Wiley Periodicals, Inc.
Keywords: alkaline phosphatase; aqueous solution; article; Biodegradation; Bone; Bone graft; bone marrow cell; Bone Marrow Cells; bone mineralization; bone prosthesis; Calcium Compounds; calcium phosphate; Calcium phosphate glass ceramic; Calcium phosphate glass ceramics; Calcium phosphates; cell contact; Cell culture; cell proliferation; Cells; ceramics; chemical composition; controlled study; crystal structure; Dissolution; enzyme activity; extracellular matrix; glass; Glass ceramics; human; Human bone marrow cells; human cell; Humans; in vitro study; In vitro testing; Magnesia; magnesium derivative; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; polystyrene; Precipitation (chemical); Scanning electron microscopy; Solubility; Spectrum Analysis; Surface treatment; Titanium dioxide

Inflammatory cell recruitment and adhesion to methyl-terminated self-assembled monolayers: Effect of implantation time - Barbosa, J.N.; Barbosa, M.A.; Águas, A.P. (Microscopy Research and TechniqueMicrosc. Res. Tech., 2005)
The contribution of methyl groups in implant-triggered inflammation was investigated in vivo using self-assembled monolayers (SAMs) of alkanethiols on gold. The CH 3-coated implants were inserted in an air-pouch cavity induced in BALB/c mice. The in situ inflammatory response was monitored 24, 48, and 72 hours later. Inflammatory cells recovered from the air pouches were counted and observed by light microscopy. The cellularity of the implant surfaces was defined by scanning electron microscopy (SEM). In comparison with gold implants, the CH 3-coated SAMs recruited a significantly higher number of inflammatory cells. Polymorphonuclear leukocytes (PMN) were more numerous than mononuclear cells (Mo) in the exudates recovered from the air pouches with CH 3-coated SAMs. The opposite PMN/Mo proportion was observed in air pouches of the two control groups (mice receiving gold implants or sham-operated animals). A low density of adherent cells was seen on CH 3-coated implants, with no significant quantitative differences during the time course of the study. In contrast, the gold-coated surfaces were covered with numerous cells during all of the 3 days of the inflammation. In conclusion, implants with CH 3 surfaces are likely to induce PMN-dominated local acute inflammation but these surfaces are not associated with a significant adherence of leukocytes to the implant. © 2005 Wiley-Liss, Inc.
Keywords: Air-pouch model; animal experiment; animal model; Animalia; Animals; article; biomaterial; cell adhesion; Cell Count; cell density; cell surface; Cell-surface interactions; Coated Materials, Biocompatible; Contact angle; controlled study; gold; implantation; Implants, Experimental; Inflammation; inflammatory cell; Inflammatory responses; leukocyte adherence; Leukocytes; male; materials testing; methyl group; Mice; Microscopy, Electron, Scanning; mononuclear cell; mouse; neutrophil; nonhuman; priority journal; Scanning electron microscopy; Self-assembled monolayers; Surface Properties; thiol derivative; Time Factors

The influence of pre-incubation treatment in the in vitro biological performance of degradable CaO-P 2O 5 glass ceramics - Dias, A.G.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (Key Engineering MaterialsKey Eng Mat, 2005)
Based upon the CaO-P 2O 5 glass system, two glass ceramics were prepared in the meta-, pyro- and orthophosphate regions. The present work describes results concerning the biological activity of MT13B (45CaO-37P 2O 5-5MgO-13TiO 2, in mol %) and MK5B (45CaO-45P 2O 5-5MgO-5K 2O, in mol %) using MG63 osteoblast-like cells cultured for 6 days. The influence of a 24h pretreatment with culture medium before cell culture was also evaluated (MT13Bi; MK5Bi). Both "as-received" and pre-treated material samples supported cell growth, which increased with the culture time. Pre-treatment resulted in an increase of adhered cells on both materials (day 1). Throughout the culture time (days 3 and 6), MT13Bi presented higher cell numbers than that of MT13B, but no differences were found between MK5Bi and MK5B. In addition, cell growth was significantly lower in the K-containing glass ceramic in both experimental situations comparing with Ti-containing glass ceramic. SEM and confocal microscopy observation showed that cell adhesion and spreading were hampered on MK5B samples. Evident macroscopic and microscopic surface instability was observed on this material with simultaneous dissolution/precipitation processes. By contrast, MT13B presented a relatively stable surface throughout the culture time. Results suggest that the pre-incubation with culture medium improves the adhesion of the osteoblast cells to both glass ceramics and that the high degradation rate of MK5B hinders the in vitro biological performance of this material.
Keywords: Bioactivity; biodegradability; Biodegradable glass ceramics; Calcium Compounds; Cell culture; cell growth; Glass ceramics; MG63 osteoblast-like cells; Orthophosphate; Osteoblasts; Pretreatment

A method for simultaneously precipitating and dispersing nano-sized calcium phosphate suspensions - Lemos, A.F.; Rebelo, A.H.S.; Rocha, J.H.G.; Ferreira, J.M.F. (Key Engineering MaterialsKey Eng Mat, 2005)
Stable and relatively concentrated aqueous suspensions of nano-sized stoichiometric hydroxyapatite could be prepared by a precipitation method in the presence of suitable surface active agent (SAA). The method includes the precipitation, vacuum filtration and washing of the precipitated powders, followed by re-dispersion. It could be concluded that the added amount of the SAA should be enough to cover the primary particles surface, and that washing should be better carried out using a SAA solution. The method developed enables the precipitation of the powders and the preparation of suspensions, while significantly shortening the overall time required for colloidal processing consuming.
Keywords: calcium phosphate; Calcium phosphates; Colloidal processing; Colloids; hydroxyapatite; Precipitated powders; precipitation; Precipitation (chemical); rheology; Stoichiometry; Surface active agents; Vacuum filtration; Washing

Method for tailoring and control the morphology, size and porosity of calcium phosphate granules - Lemos, A.F.; Rocha, J.H.G.; Ventura, J.M.; Ferreira, J.M.F. (Key Engineering MaterialsKey Eng Mat, 2005)
Hydroxyapatite (HA) is the calcium-phosphate material with composition closest to that of human bone, what makes it suitable for osseous implant purposes, namely as fillers, spacers and bone grafts substitutes. This study is aimed at the development of a method to produce porous spherical hydroxyapatite granules. The process involves the spraying of a suspension with different amounts of a setting agent to a setting media. The tailor and the control of the morphology, size and porosity of the granules were attained by adjusting the nozzle diameter, the pressure of air flow and the distance between the nozzle and the setting media.
Keywords: Air flow; Bioceramics; Bioceramlcs; Bone grafts substitutes; calcium phosphate; Granular materials; Granules; Human bone; hydroxyapatite; Hydroxyapatite granules; Porous materials; Porous structures; Starch

Mineralization of regenerated cellulose hydrogels induced by human bone marrow stromal cells - Granja, P.L.; De Jéso, B.; Bareille, R.; Rouais, F.; Baquey, C.; Barbosa, M.A. (European Cells and MaterialsEur. Cells and Mater., 2005)
The proliferation of cultured human bone marrow stromal cells (HBMSC) on regenerated cellulose hydrogels was assessed. Regenerated cellulose hydrogels showed good rates of HBMSC proliferation, the cells exhibiting a flattened morphology, and after 22 days in culture, the cells had homogeneously colonized the surface of the materials. Moreover, since the early days in culture, between the surface of the materials and attached cells a continuous granulated hydroxyapatite layer was formed. It has been previously demonstrated in vitro, but without cells, that these materials did not mineralize. Hence, it seems that HBMSC promoted the mineralization of the surface.
Keywords: article; bone marrow cell; Bone Marrow Cells; bone mineralization; Calcification, Physiologic; Calcium phosphates; Cell culture; cell proliferation; cell regeneration; Cells, Cultured; Cellulose; hematopoietic stem cell; human; Human bone marrow stromal cells; human cell; Humans; hydrogel; Hydrogels; hydroxyapatite; in vitro study; mineralization; Regenerated cellulose hydrogels; Regeneration; Spectroscopy, Fourier Transform Infrared; stroma cell; Stromal Cells; Time series analysis

Neural network classification: Maximizing zero-error density - Silva, L.M.; Alexandre, L.A.; De Sá, J.M. (Lecture Notes in Computer ScienceLect. Notes Comput. Sci., 2005)
We propose a new cost function for neural network classification: the error density at the origin. This method provides a simple objective function that can be easily plugged in the usual backpropagation algorithm, giving a simple and efficient learning scheme. Experimental work shows the effectiveness and superiority of the proposed method when compared to the usual mean square error criteria in four well known datasets. © Springer-Verlag Berlin Heidelberg 2005.
Keywords: Algorithms; Backpropagation; Backpropagation algorithm; Classification (of information); Costs; Error analysis; Function evaluation; Learning systems; Mean square error; Neural network classification; Neural networks; Zero-error density

Neural networks trained with the EEM algorithm: Tuning the smoothing parameter - Santos, J.M.; Marques de Sá, J.; Alexandre, L.A. (WSEAS Transactions on SystemsWSEAS Trans. Syst., 2005)
The training of Neural Networks and particularly Multi-Layer Perceptrons (MLP's) is made by minimizing an error function usually known as "cost function". In our previous works, we apply the Error Entropy Minimization (EEM) algorithm in classification and its optimized version using, as cost function, the entropy of the errors between the outputs and the desired targets of the neural network. One of the difficulties in implementing the EEM algorithm is the choice of the smoothing parameter, also known as window size, in the Parzen Window probability density function estimation for the computation of the entropy and its gradient. We present here a formula yielding the value of the smoothing parameter, depending on the number of data samples and on the neural network output dimension. Several experiments with real data sets were made in order to show the validity of the proposed formula.
Keywords: Cost function; entropy; Error entropy minimization (EEM) algorithm; Learning algorithms; Learning systems; Neural networks; Optimization; Parzen; Probability density function; Smoothing parameter

Polysaccharides as scaffolds for bone regeneration - Barbosa, M.A.; Granja, P.L.; Barrias, C.C.; Amaral, I.F. (ITBM-RBMITBM-RBM, 2005)
This review is concerned with the use of polysaccharides for bone regeneration. Cellulose, alginate and chitosan have been chosen as examples of the formidable potential of this class of materials. Many others could be cited but our experience and research interests dictated the choice. As in many areas of research we know how they started but we cannot see how and if they will end. Modification of cellulose was our entrance to the world of polysaccharides and a lot of what we know we owe to Charles Baquey, to whom we would like to express our immense gratitude. This chapter is dedicated to him, for his cooperation, unlimited enthusiasm and friendship. © 2005 Elsevier SAS. All rights reserved.
Keywords: Alginate; alginic acid; Amino Acid Sequence; arginylglycylaspartic acid; biomaterial; biotechnology; bone cell; bone prosthesis; Bone Regeneration; Cellulose; chitosan; enzyme degradation; polysaccharide; Polysaccharides; review; Tissue engineering

Porous HA scaffolds for drug releasing - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2005)
Dense and porous hydroxyapatite materials aimed at being used in controlled drug delivery, were characterised and studied in order to evaluate their ability to adsorb and release sodium ampicillin in a controlled manner, as a model for a drug delivery system, potentially applicable associated to surgery for the treatment of bone defects. These porous materials should also have adequate mechanical strength to withstand manipulation and sculpturing in surgery room. Adsorption and release profiles were obtained for a range of porous materials, leading to higher adsorption rates and more adequate release profiles than for dense materials.
Keywords: Adsorption; ampicillin; Controlled drug delivery; Drug release; hydroxyapatite; orthopedics; Porous hydroxyapatite; Porous hydroxyapatites; Porous materials; Scaffolds; Sodium ampicillin; Surgery; Surgery rooms

Proliferation, activity, and osteogenic differentiation of bone marrow stromal cells cultured on calcium titanium phosphate microspheres - Barrias, C.C.; Ribeiro, C.C.; Lamghari, M.; Sá Miranda, C.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
In this study, the behavior of bone marrow stromal cells cultured on calcium titanium phosphate (CTP) microspheres was analyzed. Cell adhesion and proliferation were estimated by the neutral red assay and by total DNA quantification. Morphology and deposition of extracellular matrix were assessed by confocal laser scanning microscopy and/or scanning electron microscopy. The expression of the osteoblastic phenotype was evaluated by monitoring alkaline phosphatase activity and osteocalcin secretion. Results revealed that cells were able to attach and spread on the surface of CTP microspheres, and gradually grow into nearly confluent monolayers. Moreover, cells were able to bridge adjacent microspheres forming microsphere-cell clusters. Cells produced an abundant amount of fibrillar extracellular matrix that covered the substrate surface. Alkaline phosphatase activity peaked around days 7-14 and then decreased until day 21. Cells secreted osteocalcin, with higher levels being detected at day 14 than at day 21. Taken together, these results suggest that CTP microspheres are appropriate scaffolds for the growth and differentiation of cells along the osteoblastic lineage. © 2004 Wiley Periodicals, Inc.
Keywords: alkaline phosphatase; animal cell; Animals; article; Bioassay; Bone; bone marrow cell; Bone Marrow Cells; bone marrow stromal cell; Bone marrow stromal cells; Calcium; Calcium Compounds; calcium phosphate; Calcium titanium phosphate; cell adhesion; Cell culture; cell differentiation; cell growth; cell lineage; cell proliferation; cell structure; Confluent monolayers; confocal laser microscopy; Confocal laser scanning microscopy; controlled study; Deposition; DNA determination; enzyme activity; Enzyme kinetics; extracellular matrix; Microscopy, Electron; microsphere; Microspheres; nonhuman; osteoblast; osteocalcin; Osteogenesis; Osteogenic differentiation; phenotype; protein expression; protein secretion; rat; Rats; Scanning electron microscopy; Stromal Cells; surface property; Tissue culture; Tissue engineering; Titanium; unclassified drug

Rat bone marrow stromal cell osteogenic differentiation and fibronectin adsorption on chitosan membranes: The effect of the degree of acetylation - Amaral, I.F.; Lamghari, M.; Sousa, S.R.; Sampaio, P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
Cell adhesion, migration, and proliferation of a few anchorage-dependent cells cultured on chitosan (Ch) matrices are influenced by the degree of N-acetylation (DA) of Ch. In the present work, we examined the influence of the DA on the attachment, spreading, proliferation, and osteogenic differentiation of rat bone marrow stromal cells (rBM-SCs). Ch membranes were characterized in terms of surface morphology, roughness, and wettability, and in terms of adsorption of an adhesive protein, fibronectin (Fn). Chs with DAs in the range of 4 to 49% were used. Among the Ch samples, the DA of 4% led to the highest Fn surface concentration, both from single protein solution and from diluted serum. Furthermore, the levels of Fn adsorbed from serum found for this DA were threefold higher than for the tissue culture polystyrene control, indicating that in the presence of competitive proteins Ch is more specific toward Fn adsorption than tissue culture polystyrene. rBMSCs cultured on Ch carrying a DA of 4% were able to spread, proliferate, and differentiate, reaching a higher level of osteogenic differentiation than on the control, despite the lower cell attachment observed for all Ch samples. Because the Ch sample with a DA of 4% showed the highest Fn adsorption from serum, we suggest that cell adhesion, spreading, and osteogenic differentiation of rBMSCs on Ch may be mediated by the adsorbed layer of Fn. © 2005 Wiley Periodicals, Inc.
Keywords: Acetylation; Adhesion; Adsorption; animal cell; Animals; article; artificial membrane; binding affinity; binding competition; Bone; bone development; bone marrow cell; Bone Marrow Cells; Bone marrow stomal cells; Bone marrow stromal cells; cell adhesion; cell anchorage; Cell culture; cell differentiation; Cell membranes; cell migration; cell proliferation; Cell Shape; cell spreading; chitosan; Coated Materials, Biocompatible; controlled study; cytoskeleton; Degree of acetylation; Fibronectin; Fibronectins; male; materials testing; morphology; nonhuman; polystyrene; Proteins; rat; Rats; Rats, Wistar; roughness; stroma cell; Stromal Cells; Surface Properties; surface property; Tissue culture; wettability

Recombinant glucocerebrosidase uptake by Gaucher disease human osteoblast culture model - Lamghari, M.; Barrias, C.C.; Sá Miranda, C.; Barbosa, M.A. (Blood Cells, Molecules, and DiseasesBlood Cells Mol. Dis., 2005)
Bone lesions are a major cause of morbidity in Gaucher disease (GD) type I. Enzyme replacement therapy (ERT) has been successful in treating many symptoms of type I GD but skeletal response lags behind. Local exogenous glucocerebrosidase supplementation in bone lesions via a drug delivery system may overcome this limitation. Although local enzyme supplementation aims to target lipid-engorged macrophages (Gaucher Cells) in bone compartment, enzyme uptake by osteoblasts is not excluded. To investigate the ability of human osteoblasts to internalize recombinant glucocerebrosidase (rGCR), we have used an artificial GD human osteoblasts cell culture system. MG63 human osteoblasts were treated with conduritol B epoxide (CBE) to induce complete and prolonged inhibition of endogenous glucocerebrosidase activity of cells. rGCR uptake by glucocerebrosidase-inactivated osteoblasts was examined using 125I-radiolabelling, Western blot analysis and measurement of glucocerebrosidase activity. Analysis of radiolabeled enzyme uptake by CBE treated osteoblasts showed 67.9% of internalized protein in cell extract. Enzyme internalization was also observed by Western blot analysis where the amount of mature form of glucocerebrosidase protein recognized by the glucocerebrosidase antibody was increased following the administrations of rGCR. Moreover, enzymatic activity measurement showed 23.9% of glucocerebrosidase activity of control cells. The rGCR internalization by MG63 osteoblast seems to be partially mediated by mannose receptors. These data provide evidence that MG63 human osteoblasts are able to internalize rGCR. © 2005 Elsevier Inc. All rights reserved.
Keywords: article; Cell culture; cell extract; Cells, Cultured; conduritol b epoxide; controlled study; drug activity; drug uptake; enzyme activity; enzyme antibody; Enzyme inhibition; Enzyme uptake; epoxide; Gaucher disease; Glucocerebrosidase; Glucosylceramidase; human; human cell; Humans; imiglucerase; Inositol; internalization; iodine 125; isotope labeling; mannose receptor; osteoblast; Osteoblasts; priority journal; Recombinant Proteins; unclassified drug; Western blotting

Segmentation of ultrasonic images of the carotid - Rocha, R.; Campilho, A.; Silva, J. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2005)
A new algorithm for an effective and automatic segmentation of the carotid wall in ultrasonic images is proposed. It combines the speed of thresholding algorithms with the accuracy, flexibility and robustness of a successful geometric active contour model which incorporates an optimal image segmentation model in a level set framework. Due to the multiphase nature of these images, a sequential minimum cross entropy thresholding is used to get a first approximation of the segments, reducing the problem to a two phase segmentation. This thresholding solution is then used as a starting point for a two phase piecewise constant version of a geometric active contour model to reduce noise, smooth contours, improve their position accuracy and close eventual gaps in the carotid wall. © Springer-Verlag Berlin Heidelberg 2005.
Keywords: Active contour model; Algorithms; Approximation theory; Carotid wall; Image segmentation; Image segmentation model; Mathematical models; Optimization; Ultrasonic imaging

Spectral methods in image segmentation: A combined approach - Monteiro, F.C.; Campilho, A.C. (Lecture Notes in Computer ScienceLect. Notes Comput. Sci., 2005)
Grouping and segmentation of images remains a challenging problem in computer vision. Recently, a number of authors have demonstrated a good performance on this task using spectral methods that are based on the eigensolution of a similarity matrix. In this paper, we implement a variation of the existing methods that combines aspects from several of the best-known eigenvector segmentation algorithms to produce a discrete optimal solution of the relaxed continuous eigensolution. © Springer-Verlag Berlin Heidelberg 2005.
Keywords: Algorithms; Computer vision; Discrete optimal solution; Eigensolution; Eigenvalues and eigenfunctions; Image segmentation; Matrix algebra; Problem solving; Similarity matrix; Spectral methods

Synthesis and characterization of new injectable and degradable dextran-based hydrogels - Maia, J.; Ferreira, L.; Carvalho, R.; Ramos, M.A.; Gil, M.H. (PolymerPolymer, 2005)
Injectable and degradable hydrogels are very interesting networks for drug delivery and cell transplantation applications since they can be administered in the human body in a minimally invasive way. In most cases, the crosslinking reaction occurs by photopolymerisation or free radical polymerisation; however, the use of chemical initiators may promote cell death. In the current work, injectable and degradable dextran-based hydrogels were prepared without the use of initiators. Dextran, a natural glucose-containing polysaccharide, was oxidized with sodium periodate (dexOx) and the derivatives characterized by NMR and FTIR spectroscopy's as well as by colorimetric techniques. The oxidized derivatives were crosslinked with adipic acid dihydrazide (AAD), forming a gel within 2-4 min. The obtained hydrogels were characterized by their mechanical properties, swelling and degradation behavior under physiologic conditions. In addition, the hydrogel interior morphology as well as porous structure was evaluated by scanning electron microscopy (SEM) and mercury intrusion porosimetry (MIP). MIP analysis showed that dexOx hydrogels crosslinked with 10% of AAD were macroporous with pore sizes ranging from 0.32 to 0.08 μm. As expected, the average pore size increased during hydrogel degradation as confirmed by SEM and MIP studies. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Cell Death; Cell transplantation; Colorimetry; Crosslinking; Degradation; Drug delivery; Drug dosage; Fourier transform infrared spectroscopy; Free radical polymerization; hydrogel; Hydrogels; Mercury intrusion porosimetry (MIP); morphology; Nuclear magnetic resonance spectroscopy; Photopolymerization; Polysaccharides; Pore size; Porosimeters; Scanning electron microscopy; Synthesis (chemical)

TiO 2 type influences fibronectin adsorption - Sousa, S.R.; Moradas-Ferreira, P.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2005)
Human fibronectin (FN) plays a key role in the biointegration of implants as the success depends on adsorption of proteins like FN [1]. Indeed FN can be an intermediary between the biomaterial surface and cells. The adsorption of human fibronectin (FN) on commercially pure titanium with a titanium oxide layer formed in a H 2O 2 solution (TiO 2 cp) and TiO 2 sputtered on Si (TiO 2 sp) was studied. Adsorption isotherms and the work of adhesion were assessed by wettability studies, X-ray photoelectron spectroscopy (XPS), and by radiolabelling of FN with 125I, 125I-FN. Exchangeability of bound FN by free FN, was also evaluated by the radiolabelling technique. Contact angle determinations have shown that FN displays higher affinity for the TiO 2 cp surface than for the TiO 2 sp. As expected from the surface free energy values, the work of adhesion of FN is higher for the TiO 2 cp substrate, the more hydrophilic one, and lower for the TiO 2 sp substrate, the more hydrophobic one. The adsorption isotherms were evaluated by two different techniques: radiolabelling of FN ( 125I-FN) and XPS. TiO 2 cp adsorbs more FN than the TiO 2 sp surfaces as shown by the radiolabelling data. FN molecules are also more strongly attached to the former surface as indicated by the work of adhesion and by the exchangeability studies. Results using 125I-FN also suggests that FN adsorbs as a multilayer for FN concentrations in solution higher than 100 μg/mL. © 2005 Springer Science + Business Media, Inc.
Keywords: Adsorption; adsorption kinetics; article; binding affinity; Biointegration; Biomaterials; Cells; chemistry; conference paper; Contact angles; Fibronectin; Fibronectins; human; Human fibronectin (FN); Humans; hydrogen peroxide; hydrophilicity; hydrophobicity; Implants (surgical); iodine 125; isotherm; Isotherms; isotope labeling; physical chemistry; priority journal; protein binding; Proteins; Radiolabelling; solution and solubility; Solutions; surface property; Titanium; Titanium dioxide; wettability; X ray photoelectron spectroscopy

Automatic delimitation of lung fields on chest radiographs - Mendonça, A.M.; Da Silva, J.A.; Campilho, A. (2004 2nd IEEE International Symposium on Biomedical Imaging: Macro to NanoIEEE Int. Symp. Biomed. Imaging Macro Nano, 2004)
The purpose of the research herein presented is the automatic delimitation of lung fields in posterior-anterior digital chest radiographs. In a computer-aided diagnosis system the precise location of the lungs is important as it allows the reduction of the region under analysis, decreasing the computation time and facilitating data compression. Furthermore, it allows the delimitation of the search area, easing the selective tuning of the abnormalities detection algorithms. The results produced by the automatic method were validated by comparison with manual contours traced by experienced radiologists. Two programs with friendly interfaces were developed for this purpose. © 2004 IEEE.
Keywords: Algorithms; Chest radiographs; Computer aided diagnosis; Contour detection; Data compression; Edge detection; Image segmentation; Lung fields; Pulmonary diseases; Radiography; X ray analysis; X ray imaging

Automatic lane and band detection in images of thin layer chromatography - Sousa, A.V.; Aguiar, R.; Mendonca, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
This work aims at developing an automatic method for the analysis of TLC images for measuring a set of features that can be used for the characterization of the distinctive patterns that result from the separation of oligosaccharides contained in human urine. This paper describes the methods developed for the automatic detection of the lanes contained in TLC images, and for the automatic separation of bands for each detected lane. The extraction of quantitative information related with each band was accomplished with two methods: the EM expectation-maximization and nonlinear least squares trustregion algorithms. The results of these methods, as well as additional quantitative information related with each band, are also presented. © Springer-Verlag 2004.

Biocompatibility of chemoenzymatically derived dextran-acrylate hydrogels - Ferreira, L.; Rafael, A.; Lamghari, M.; Barbosa, M.A.; Gil, M.H.; Cabrita, A.M.S.; Dordick, J.S. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2004)
The biocompatibility of chemoenzymatically generated dextran-acrylate hydrogels has been evaluated in vitro, using human foreskin fibroblasts, and in vivo, by subcutaneous and intramuscular implantation in Wistar rats for up to 40 days. In vitro tests show that hydrogel extracts only minimally reduced (<10%) the mitochondrial metabolic activity of fibroblasts. Direct contact of the hydrogels with cells induced a cellular proliferation inhibition index (CPII) of 50-80%, compared with a control, whereas through indirect contact, the CPII values were <16%, suggesting that the high CPII values achieved in the direct assay test were likely due to mechanical stress or limitations in oxygen diffusion. Hence, the hydrogels were noncytotoxic. Moreover, cell-material interaction studies show that these hydrogels were nonadhesive. Finally, histologic evaluation of tissue response to subcutaneous and intramuscular implants showed acceptable levels of biocompatibility, as characterized by a normal cellular response and the absence of necrosis of the surrounding tissues of the implant. In the first 10 days, the foreign-body reaction in the intramuscular implantation was more severe than in subcutaneous implantation, becoming identical after 30 days. In both cases, dextran hydrogels did not show signs of degradation 6 weeks postimplantation and were surrounded by a thin fibrous capsule and some macrophages and giant cells. This response is typical with a number of nondegradable biocompatible materials. These results indicate that dextran hydrogels are biocompatible, and may have suitable applications as implantable long-term peptide/protein delivery systems or scaffolds for tissue engineering. © 2004 Wiley Periodicals, Inc.
Keywords: Acrylates; acrylic acid; animal experiment; animal model; animal tissue; Animals; article; Biocatalytic polyester; Biocompatibility; Biocompatible Materials; Biodegradation, Environmental; Biodiversity; Biomaterials; cell adhesion; Cell Division; cell interaction; cell proliferation; Cells, Cultured; Coenzymes; controlled study; Cytotoxicity; dextran; dextran acrylate; dextran acrylate hydrogel; dextran hydrogel; Dextrans; drug delivery system; Enzymes; fibroblast; Fibroblasts; Fibrous capsules; foreign body reaction; Foreign-Body Reaction; giant cell; human; human cell; Humans; hydrogel; Hydrogels; implantation; Implants (surgical); Implants, Experimental; in vitro study; in vivo study; macrophage; male; materials testing; mechanical stress; Mechanical stresses; metabolism; Mitochondria; mitochondrial respiration; nonhuman; oxygen diffusion; prepuce; rat; Rats; Rats, Wistar; Tissue; Tissue engineering; unclassified drug

Biological Activity of Two Glass Ceramics in the Meta- and Pyrophosphate Region: A Comparative Study - Dias, A.G.; Costa, M.A.; Lopes, M.A.; Santos, J.D.; Fernandas, M.H. (Key Engineering MaterialsKey Eng Mat, 2004)
Based upon the CaO-P 2O 5 glass system, two glass ceramics were prepared in the metaand pyrophosphate regions. The present work describes preliminary results concerning the biological activity of MK5B (45CaO-45P 2O 5-5MgO-5K20, in mol %) and MT13B (45CaO-37P 2O 55-5MgO-13TiO 2, in mol %) using MG63 osteoblast-like cells. Both materials supported cell growth and proliferation which increased with the incubation time. However, cell growth was significantly lower on seeded MK5B samples. SEM observation showed that cell adhesion and spreading were hampered on this material. Evident degradation of the material surface was observed with simultaneous cell proliferation and material precipitation. By contrast, MT13B presented a relatively stable surface throughout the culture time. Results suggest that the in vitro biological behaviour of MK5B and MT13B is related with differences in the degradation rates of the two materials during the culture time.
Keywords: Adhesion; Biodegradable glass ceramics; Biodegradation; Bone; cell proliferation; Cells; Crystallization; Degradation; Glass ceramics; incubation time; MG63 osteoblast-like cells; Scanning electron microscopy; X ray diffraction

Bonelike®/PLGA hybrid materials for bone regeneration: In vivo evaluation - Oliveira, J.M.; Kawai, T.; Lopes, M.A.; Ohtsuki, C.; Santos, J.D.; Afonso, A. (Materials Science ForumMater Sci Forum, 2004)
The biocompatibility and osteoconductive potential of Bonelike® and Bonelike®/PLGA hybrid materials were evaluated through subcutaneous and tibiae implantations for a 4 week period. Qualitative histology was performed to evaluate new bone formation and characterise bone-implant interface and results showed that Bonelike®/PLGA hybrid materials promote extensive bone growth. After the 4 week implantation period, Bonelike® resorption was recognized, which may be due to the presence of resorbable β and α-tricalcium phosphate phases.
Keywords: Bacteria; Biodegradation; Bone; Bonelike resorption; Bonelike®; Histological studies; histology; Hybrid materials; hydroxyapatite; In vivo; physiology; PLGA; Polymers; Surgery; Tissue

Bounds for the Average Generalization Error of the Mixture of Experts Neural Network - Alexandre, L.A.; Campilho, A.; Kamel, M. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
In this paper we derive an upper bound for the average-case generalization error of the mixture of experts modular neural network, based on an average-case generalization error bound for an isolated neural network. By doing this we also generalize a previous bound for this architecture that was restricted to special problems. We also present a correction factor for the original average generalization error, that was empirically obtained, that yields more accurate error bounds for the 6 data sets used in the experiments. These experiments illustrate the validity of the derived error bound for the mixture of experts modular neural network and show how it can be used in practice. © Springer-Verlag 2004.
Keywords: Generalization error bounds; Mixture of experts; Modular neural networks

Calcium phosphate-alginate microspheres as enzyme delivery matrices - Ribeiro, C.C.; Barrias, C.C.; Barbosa, M.A. (BiomaterialsBiomaterials, 2004)
The present study concerns the preparation and initial characterisation of novel calcium titanium phosphate-alginate (CTP-alginate) and hydroxyapatite-alginate (HAp-alginate) microspheres, which are intended to be used as enzyme delivery matrices and bone regeneration templates. Microspheres were prepared using different concentrations of polymer solution (1% and 3%w/v) and different ceramic-to-polymer solution ratios (0.1, 0.2 and 0.4w/w). Ceramic powders were characterised using X-ray diffraction, laser granulometry, Brunauer, Emmel and Teller (BET) method for the determination of surface area, zeta potential and Fourier transform infrared spectroscopy (FT-IR). Alginate was characterised using high performance size exclusion chromatography. The methodology followed in this investigation enabled the preparation of homogeneous microspheres with a uniform size. Studies on the immobilisation and release of the therapeutic enzyme glucocerebrosidase, employed in the treatment of Gaucher disease, were also performed. The enzyme was incorporated into the ceramic-alginate matrix before gel formation in two different ways: pre-adsorbed onto the ceramic particles or dispersed in the polymeric matrix. The two strategies resulted in distinct release profiles. Slow release was obtained after adsorption of the enzyme to the ceramic powders, prior to preparation of the microspheres. An initial fast release was achieved when the enzyme and the ceramic particles were dispersed in the alginate solution before producing the microspheres. The latter profile is very similar to that of alginate microspheres. The different patterns of enzyme release increase the range of possible applications of the system investigated in this work. © 2003 Elsevier Ltd. All rights reserved.
Keywords: Absorption; Adsorption; Alginate; Alginates; article; Biomaterials; Bone; Calcium Compounds; Calcium phosphates; Calcium titanium phosphate; calcium titanium phosphate alginate; ceramics; Drug Carriers; Drug Delivery Systems; Enzyme delivery; Enzyme-delivery; Enzymes; Enzymes, Immobilized; Fourier transform infrared spectroscopy; Glucosylceramidase; Glucuronic Acid; Hexuronic Acids; High performance liquid chromatography; hydroxyapatite; hydroxyapatite alginate; laser; methodology; microsphere; Microspheres; Molecular Conformation; Particle Size; Powders; priority journal; surface property; unclassified drug; X ray diffraction

CaO-P 2O 5 Glass-Hydroxyapatite Thin Films Obtained by Laser Ablation: Characterisation and In Vitro Bioactivity Evaluation - Ferraz, M.P.; Monteiro, F.J.; Gião, D.; Leon, B.; Gonzalez, P.; Liste, S.; Serra, J.; Arias, J.; Perez-Amor, M. (Key Engineering MaterialsKey Eng Mat, 2004)
Hydroxyapatite (HA) coatings have been applied to improve adhesion of non-cemented implants to host bone. Plasma spraying is the most common technique leading to thick calcium phosphate films (>120μm). Pulse laser deposition (PLD), is a possible alternative method to obtain thin (<10 μm), well adherent hydroxyapatite (HA) films. Similarly to synthetic HA, biological apatites contain Ca 2+, PO 4 3- and OH
Keywords: 2O; 5 glass; Adhesion; Bioactivity; Bone; Calcium Compounds; CaO-P; Coatings; Deposition; Energy dispersive spectroscopy; Homogeneous mixtures; Hydroxylapatite thin films; Implants (surgical); In vitro bioactivity; Laser ablation; Plasma spraying; Scanning electron microscopy; Thin films; X ray diffraction

Combining Foaming and Starch Consolidation Methods to Develop Macroporous Hydroxyapatite Implants - Lemos, A.F.; Ferreira, J.M.F. (Key Engineering MaterialsKey Eng Mat, 2004)
Hydroxyapatite (HA) is the calcium-phosphate material with composition closest to that of bone, what makes it suitable for osseous implant purposes. This material was used to produce macroporous structures with pores larger than 100 μm, which are believed to be suitable for allowing bone ingrowth. The macroporous structures were generated and consolidated by combining foaming and starch consolidation methods. The porous structures could be tailored according to the final application by varying the proportion of different foaming agents, foam-bath concentrate (FBC) and sodium lauril sulphate (SLS). Playing with these proportions it was also possible to improve foam stability and model the size of pores and pore interconnections in order to reproduce the pore structure of natural bone.
Keywords: Bioceramics; Biocompatibility; Bone; Composition; Foaming method; hydroxyapatite; Hydroxyapatlte; Implants (surgical); Macroporous structures; Microstructure; Pore size; Porous ceramics; Porous materials; Starch; Starch consolidation

A comparative study of CaO-P 2O 5-SiO 2 gels prepared by a sol-gel method - Hussain, N.S.; Lopes, M.A.; Santos, J.D. (Materials Chemistry and PhysicsMater Chem Phys, 2004)
This paper reports on the results concerning the preparation and systematic analysis of CaO-P 2O 5-SiO 2 gels by a sol-gel process. The concentration of SiO 2 influence on these gels and found the results are very encouraging. Studies have revealed that the concentration of SiO 2 has a marginal influence on the phase formation of these gels. It has appreciable changes from less configured particles at lower values of concentration, with an ultimate growth in a highly crystalline fibrous nature at higher concentrations of SiO 2. The authors have examined the changes in the morphology of these gels by a scanning electron microscope with an energy dispersive analyser (SEM/EDS techniques) and also from the profiles of Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) spectral data and reported the crystalline product containing the fibrous β-Ca(PO 3) 2 as a major phase in the materials studied. © 2004 Elsevier B.V. All rights reserved.
Keywords: Bioactivity; Calcium Compounds; Calcium phosphosilicates; Fourier transform infrared spectroscopy; Gels; morphology; Phase composition; Phase formation; Phosphorus Compounds; Scanning electron microscopy; Silica; Sol-gel process; Sol-gels; X ray diffraction analysis

Crystallisation studies of biodegradable CaO-P 2O 5 glass with MgO and TiO 2 for bone regeneration applications - Dias, A.G.; Tsuru, K.; Hayakawa, S.; Lopes, M.A.; Santos, J.D.; Osaka, A. (Glass TechnologyGlass Technol, 2004)
CaO-P 2O 5 glass ceramics with small additions of MgO and TiO 2 were prepared in the ortho and pyrophosphate regions by powder sintering and crystallisation through heat treatment at different temperatures determined from differential thermal analysis (DTA). The glass ceramics were analysed by x-ray diffraction (XRD) and it was observed that α- and β-Ca 2P 2O 7 were the first phases to precipitate in the parent glass matrix at a temperature of 681°C, followed by CaTi 4(PO 4) 6 and TiP 2O 7 at temperatures between 703 and 725°C. The β-Ca 2P 2O 7 and CaTi 4(PO 4) 6 phases are usually considered as biocompatible and bioactive and, therefore, these glass ceramics seem to show good potential for bone regeneration applications.
Keywords: Biodegradation; Bone Regeneration; Crystallization; Differential thermal analysis; Diffractometers; Glass ceramics; Glass matrix; Glass transition; Laser diffraction; Lime; Magnesia; methanol; Monochromators; Precipitation (chemical); Temperature scanning; Titanium dioxide; X ray powder diffraction

Designing of Bioceramics with Bonelike Structures Tailored for Different Orthopaedic Applications - Lemos, A.F.; Ferreira, J.M.F. (Key Engineering MaterialsKey Eng Mat, 2004)
Innovative methods for the production of porous bioceramics for implants with tailored pore volume fractions, pore sizes, pore size distributions and pore interconnectivity have been developed. The average pore sizes can vary from a few micrometers to more than one millimeter, therefore fulfilling all the needs required for components used in implantology. The methods combine in a suitable way the knowledge coming from different areas in the field of colloid and interface science, namely, on the processing of ceramic materials by traditional colloidal shaping techniques such as slip casting with a number of new direct consolidation techniques, which transform the fluid hydroxyapatite (HA) based suspensions into rigid bodies, and particularly the expertise in the production of porous ceramics by different techniques. Slip casting was preferably used for designing the cortical part of the bone, while direct consolidation techniques were used to "freeze" tailored foamy structures or suspensions containing different kinds of organic inclusions of suitable sizes and amounts that generate pores after burning out.
Keywords: Bioceramics; Biocompatibility; Bone; Cells; Ceramic materials; Consolidation techniques; hydroxyapatite; morphology; orthopedics; Pore size; Porous ceramics; Porous materials; Sintering; Slip casting

Detection of Rib Borders on X-ray Chest Radiographs - Moreira, R.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
The purpose of the research herein presented is the automatic detection of the rib borders in posterior-anterior (PA) digital chest radiographs. In a computer-aided diagnosis system, the precise location of the ribs is important as it allows reducing the false positive in the detection of abnormalities such as nodules, rib lesions and lung lesions. We adopted an edge based approach aiming at detecting the lower border of each rib. For this purpose, the rib geometric model is described as a parabola. For each rib, the upper limit is obtained using the position of the corresponding lower border. © Springer-Verlag 2004.

Effect of the Solvents on the Solution Mixture Derived Polylactide/hydroxyapatite Composites - Li, Y.; Weng, W.; Cheng, K.; Du, P.; Shen, G.; Han, G.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2004)
Polylactide/hydroxyapatite composites were prepared by a solution mixture method. Chloroform and tetrahydrofuran were used as solvents. The effect of the solvents on the polylactide/hydroxyapatite composites was investigated by TEM, mechanical properties, sedimentation time and UV-Vis transmission spectra. The results indicate that the polylactide/hydroxyapatite prepared using tetrahydrofuran as solvent has better dispersion of the hydroxyapatite filler in the matrix and larger bend strength than the one using chloroform as solvent. This is ascribed to the proper interaction between the solvent and hydroxyapatite filler.
Keywords: Bend strength; Composite; Composite materials; dispersion; Dispersions; Fillers; Heat treatment; Hydroxvapatite; hydroxyapatite; Polarity; polylactide; Sedimentation; Solutions; Solvent; Solvents; transmission electron microscopy; Ultraviolet radiation

Effects of some variables on R.F. Magnetron Sputtered Hydroxyapatite Coatings on Titanium - Silva, R.A.; Sousa, M.; Monteiro, F.J.; Barral, R.; Santos, J.D.; Lopes, M.A. (Key Engineering MaterialsKey Eng Mat, 2004)
RF sputtering may be used to produce thin, well adherent bioactive coatings with long term stability to ensure contact with bone tissue. RF Sputtered Hydroxyapatite (HA) coatings were produced onto Ti at 200 and 150 W. S.E.M. analysis indicated that films obtained with 200 W were thicker than those with 150 W. Significant variations were observed, depending on the location of the substrates with respect to the sample holder in the sputtering chamber, with thickness ranging from 1.8 to 3.2 μm. EDS analysis of 200 W films revealed the presence of Ca and P, in ratios typical of HA. XPS of thinner films obtained at 150 W, showed Ca and P, but also some carbonate probably partially substituting OH. Anodic polarisation curves of samples coated at 200 W and 150 W and for different sputtering times, compared to Ti substrate, indicate that HA films were protective and that the degree of protection increased with film thickness, i.e., with power intensity and time of deposition.
Keywords: Bioactive coatings; Bone; Coatings; Corrosion protection; hydroxyapatite; Magnetron sputtering; Plasma spraying; Polarization; RF sputtering; Scanning electron microscopy; Sputter deposition; Sputtering chambers; Thin films; Titanium

Electrochemical behaviour of titanium coated stainless steel by r.f. sputtering in synthetic sweat solutions for electrode applications - Fonseca, C.; Vaz, F.; Barbosa, M.A. (Corrosion ScienceCorros. Sci., 2004)
The r.f. sputtering technique was used to deposit titanium thin films on stainless steel substrates, aiming at the application of the coated samples as skin contact materials for "dry" active electrodes. In this work the electrochemical behaviour of the coated samples was investigated in synthetic sweat solutions and their performance was compared with that of uncoated stainless steel and bulk titanium. The characterisation of the samples was carried out by electrochemical techniques and scanning electron microscopy. The coated samples displayed corrosion resistance values in synthetic sweat solutions much higher than stainless steel samples and of the same order of the values measured for bulk titanium in the same conditions. © 2004 Elsevier Ltd. All rights reserved.
Keywords: A. Sputtered films; A. Stainless steel; A. Titanium; B. EIS; coating; Corrosion resistance; Electrochemical corrosion; Electrochemical techniques; electrochemistry; electrode; Electrodes; Protective coatings; Scanning electron microscopy; Sputtering; Stainless steel; Synthetic sweat solutions; Thin films; Titanium

An electronic instrumentation course for non-electronic engineering students - Campilho, A.; Cardoso, A. (International Journal of Electrical Engineering EducationInt J Electr Eng Educ, 2004)
This paper reports on the implementation of a required course on electronic instrumentation for informatics engineering students. These students had proved in previous years to require a special approach, as their motivation for this subject was low. The course focuses on the basic concepts of Electronic Instrumentation, including analogue-to-digital and digital-to-analogue conversion and introducing the concept of instrument control. The course was organised in a set of lectures coupled with laboratory experiments, and a small project. To foster collaborative learning all the students work on the same laboratory experiments, simultaneously, organised in groups of two. The students' feedback on the course was more positive than in previous years, although not substantially so in terms of results. We feel that a change of attitude took place effectively, and that this could be attributed to the laboratory experiments using LabVIEW.
Keywords: Analog to digital conversion; Analogue-to-digital conversion; Collaborative learning; Collaborative learning (CL); Curricula; Data processing; Electronic instrumentation; Electronics engineering; Engineering education; LabVIEW; Learning systems; Motivation; Project management; Students

Fabrication of alternating polycation and albumin multilayer coating onto stainless steel by electrostatic layer-by-layer adsorption - Ji, J.; Tan, Q.; Fan, D.-Z.; Sun, F.-Y.; Barbosa, M.A.; Shen, J. (Colloids and Surfaces B: BiointerfacesColloids Surf. B Biointerfaces, 2004)
Multilayer films consisting of polyethylenimine (PEI) and albumin were successfully prepared on biomedical 316L stainless steel surface via electrostatic self-assembly of the PEI and albumin. The process of electrostatic self-assembly of PEI/albumin was monitored by 125I radiolabeling, electrochemical impedance spectroscopy (EIS) and atomic force microscopy (AFM). The EIS data revealed that the multilayer coating was stable in Tris-HCl (pH 7.35) buffer solution for 21 days. 125I radiolabeling experiments indicated that less than 10% albumin was eluted by PBS in 45 days. Static platelet adhesion experiments indicated that the PEI/albumin deposited on stainless steel could resist platelet adhesion effectively. Such an easy processing and shape-independent method may have good potential for surface modification of cardiovascular devices. © 2004 Elsevier B.V. All rights reserved.
Keywords: Adhesion; Adsorption; Albumin; Albumins; article; Atomic force microscopy; Cardiovascular devices; Chemical modification; Coatings; Electric Impedance; Electric Potential; Electrochemical impedance spectroscopy; electrochemistry; Electrons; Electrostatics; film coating; iodine 125; isotope labeling; Layer-by-layer; Lipid Bilayers; Microscopy, Atomic Force; Multilayers; Nonthrombogenic; pH effects; Platelet Adhesiveness; Polyamines; polycation; Polycations; Polyethyleneimine; priority journal; Proteins; Self assembly; Spectroscopy; Spectrum Analysis; Stainless steel; Surface modification; Surface Properties; surface property; Surface treatment; thrombocyte adhesion

Fabrication of alternating polycation and albumin multilayer coating by electrostatic layer-by-layer adsorption - Ji, J.; Tan, Q.; Fan, D.-Z.; Sun, Y.-F.; Barbosa, M.A.; Shen, J. (Journal of Materials ScienceJ Mater Sci, 2004)
The construction of albumin multilayers via the electrostatic self-assembly (ESA) method was explored. Based on the results, it was possible to develop a fast, easy processing and shape-independent method for nonthrombogenic coating.
Keywords: Adhesion; Adsorption; Albumin; Biocompatibility; Biological materials; Biopolymers; Blood; Charge transfer; Chemical bonds; Covalent binding; Desorption; Electron transfer; Electron transfer resistance; Electrostatic layer by layer adsorption; Electrostatics; Multilayers; polycation; Positive ions; Spectroscopic analysis; Static platelet adhesion

Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma - Sousa, S.R.; Moradas-Ferreira, P.; Saramago, B.; Viseu Melo, L.; Barbosa, M.A. (LangmuirLangmuir, 2004)
In the present work, the adsorption of human serum albumin (HSA) on commercially pure titanium with a titanium oxide layer formed in a H 2O 2 solution (TiO 2 cp) and on TiO 2 sputtered on Si (TiO 2 sp) was analyzed. Adsorption isotherms, kinetic studies, and work of adhesion determinations were carried out. HSA exchangeability was also evaluated. Surface characterization was performed by atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), and wettability studies. The two TiO 2 surfaces have very distinct roughnesses, the TiO 2 sp having a mean R a value 14 times smaller than the one of TiO 2 cp. XPS analysis revealed consistent peaks representative of TiO 2 on sputtered samples as well as on Ti cp substrate after 48 h of H 2O 2 immersion. Nitrogen was observed as soon as protein was present, while sulfur, present in disulfide bonds in HSA, was observed for concentrations of protein higher than 0.30 mg/mL. The work of adhesion was determined from contact angle measurements. As expected from the surface free energy values, the work of adhesion of HSA solution is higher for the TiO 2 cp substrate, the more hydrophilic one, and lower for the TiO 2 sp substrate, the more hydrophobic one. The work of adhesion between plasma and the substrates assumed even higher values for the TiO 2 cp surface, indicating a greater interaction between the surface and the complex protein solutions. Adsorption studies by radiolabeling of albumin ( 125I-HSA) suggest that rapid HSA adsorption takes place on both surfaces, reaching a maximum value after ~60 min of incubation. For the higher HSA concentrations in solution, a multilayer coverage was observed on both substrates. After the adsorption step from single HSA solutions, the exchangeability of adsorbed HSA molecules by HSA in solution was evaluated. The HSA molecules adsorbed on TiO 2 sp seem to be more easily exchanged by HSA itself than those adsorbed on TiO 2 cp after 24 h. In contrast, after 72 h, nearly all the adsorbed albumin molecules effectively exchange with other albumin molecules.
Keywords: Adsorption; article; Atomic force microscopy; Blood; chemistry; human; Human serum albumin (HSA); Humans; hydrophobicity; Multilayers; plasma; Plasmas; Plastic surgery; Proteins; Radiolabeling; Serum Albumin; solution and solubility; Solutions; Substrates; Surface characterization; Surface Properties; surface property; Titanium; Titanium dioxide; X ray photoelectron spectroscopy

"In vitro" bioactivity evaluation of CaO-P 2O 5 glass-hydroxylapatite thin coatings produced by pulsed laser deposition - Arias, J.L.; Liste, S.; González, P.; Serra, J.; León, B.; Ferraz, M.P.; Monteiro, F.J.; Giao, D.; Pérez-Amor, M. (Transactions - 7th World Biomaterials CongressTrans. World Biomater. Congr., 2004)
The synthesis of coatings based on hydroxyapatites (HA) and glass modified hydroxyapatite targets by pulsed laser deposition, was presented. It was observed that coatings produced from HA targets keep their crystallinity through all their thickness, while there is a loss of crystallinity towards the surface of the HA+1.5G coatings. On immersion in SBF for three days, the coatings produced from HA targets suffered a loss of crystallinity near the surfaces, while the crystallinity of the coatings produced from HA+1.5G targets increased. It was also observed that addition of 1.5wt% of CaO-P 2O 5 glasses to HA thin coatings produced by pulsed laser deposition leads to a significant structural change of the coating surface.
Keywords: Apatites; Bioactivity; Calcium Compounds; Coatings; Crystalline materials; Crystalline phases; hydroxyapatite; Mixtures; Phosphorus Compounds; Pressure effects; Pulsed laser deposition; Scanning electron microscopy; Substrates; Thin coatings; X ray diffraction; X ray photoelectron spectroscopy

In Vitro Cytocompatibility of Osteoblastic Cells Cultured on Chitosan-Organosiloxane Hybrid Membrane - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (Key Engineering MaterialsKey Eng Mat, 2004)
Chitosan-silicate hybrids were synthesized using γ-glycidoxypropyltrimethoxysilane (GPSM) as the agent to cross-link the chitosan chains. Fourier-transform infrared (PT-IR) spectroscopy was used to analyze the structures of the hybrids. The swelling ability and the cytocompatibility of the hybrids were investigated as a function of the GPSM concentration. The swelling of the hybrids was suppressed by addition of GPSM. MG63 human osteoblastic cells were cultured on the hybrids. The adhesion and proliferation of the MG63 cells cultured on the chitosan-GPSM hybrid surface were improved comparing to that on chitosan membrane, regardless the GPSM concentration.
Keywords: Biocompatibility; Biological membranes; biosynthesis; Cell culture; Cells; chitosan; Chitosan-inorganic hybrid; Crosslinking; Cytocompatibility; Fourier transform infrared spectroscopy; Nuclear magnetic resonance spectroscopy; Organic polymers; Osteoblastic cell (MG63); Structural analysis; Synthetic polymers; Tissue; Tissue engineering; γ-Glycidoxypropyltrimethoxysilane (GPSM)

In Vitro Mineralisation of Human Bone Marrow Cells Cultured on Bonelike® - Costa, M.A.; Gutierres, M.; Almeida, L.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (Key Engineering MaterialsKey Eng Mat, 2004)
Bonelike® is a CaO-P 2O 5 based glass-reinforced hydroxyapatite (HA) designed to mimic the inorganic composition of the bone tissue. This work evaluates the response of human bone marrow cells to Bonelike® concerning cell proliferation and osteoblast differentiation. HA was used as control material. Results showed that Bonelike® allowed the proliferation of bone marrow cells and their complete differentiation, as evidenced by the formation of cell-mediated mineralisation. In comparison with HA, Bonelike® had a positive effect on the expression of alkaline phosphatase and also on the formation of a mineralised matrix, two osteoblast markers.
Keywords: Bone; Bonelike®; Cell culture; cell proliferation; Composition; Grafts; Human bone marrow cells; hydroxyapatite; In vitro mineralisation; mineralization; Scanning electron microscopy; Sintering; X ray diffraction

In Vivo Behaviour of Bonelike®/PLGA Hybrid: Histological Analysis and Peripheral Quantitative Computed Tomography (pQ-CT) Evaluation - Oliveira, J.M.; Kawai, T.; Lopes, M.A.; Ohtsuki, C.; Santos, J.D.; Afonso, A. (Key Engineering MaterialsKey Eng Mat, 2004)
The present work consisted in assessing the in vivo biological behaviour of novel Bonelike®/PLGA hybrid materials through subcutaneous and tibiae implantations for a 4 week period using an animal model. No sign of inflammation was observed as a result of subcutaneous implantation, which reveals that these materials were well-tolerated by the soft tissues. pQ-CT analysis demonstrated that the implanted materials were highly osteointegrated in bone tissue. SEM analysis at bone defect area revealed that Bonelike® resorption occurred after 4 weeks of implantation. Although the osteoconductive properties of Bonelike® have been reported in literature, the present work allowed to demonstrate that the silane-coupling agent and the PLGA treatments do not significantly modify the biological performance of Bonelike®. This result is strongly encouraging since Bonelike®/PLGA hybrid materials are being developed for bone tissue healing/regeneration purposes with simultaneous delivery of therapeuthic molecules.
Keywords: Biodegradation; Bonelike®; Computerized tomography; Histological analysis; histology; hydroxyapatite; In vivo studies; Organic polymers; PLGA; pQ-CT; Silanes; Sintering; Synthetic polymers; Tibiae implantations; Tissue

Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethiolates on gold - Barbosa, J.N.; Barbosa, M.A.A.; Águas, A.P. (BiomaterialsBiomaterials, 2004)
The acute inflammatory response and the adhesion of cells to self-assembled monolayers (SAMs) of well-defined surface chemistry was studied in vivo using a rodent air-pouch model of inflammation. SAMs with three different terminal functional groups (OH, COOH and CH 3) were implanted in subcutaneous air pouches induced in BALB/c mice. After 24h, inflammatory cells were recovered from the air pouches and the implants were removed and prepared for observation by scanning electron microscopy (SEM). The implants coated with OH and CH 3, were found to cause the highest recruitment of inflammatory cells into the subcutaneous pouches. Polymorphonuclear neutrophils (PMNs) leukocytes predominated over mononuclear cells in inflammatory exudates of SAMs-coated implants, the opposite being found in uncoated implants (controls). CH 3-coated implants induced the highest number of inflammatory cells and also the largest percentage of PMNs seen in the subcutaneous pouches. Control and OH-covered implants presented the higher densities of attached inflammatory cells detected by SEM. In contrast, the CH 3-coated implants showed a very low density of cells adherent to the implant surface. We conclude that the chemical nature and the degree of hydrophobicity of the surface of implants modulate both the local acute inflammatory reaction and the adhesion of leukocytes. © 2003 Elsevier Ltd. All rights reserved.
Keywords: Air-pouch model; alkane derivative; animal cell; animal experiment; animal model; Animals; article; Biomaterials; cell adhesion; Cell culture; cell density; cell surface; Cell-surface interactions; controlled study; exudate; gold; gold complex; hydrophobicity; implantation; Inflammation; Inflammatory responses; leukocyte; Leukocytes; male; material coating; Mice; Mice, Inbred BALB C; Microscopy, Electron, Scanning; mouse; neutrophil; nonhuman; polymorphonuclear cell; priority journal; Rodentia; Scanning electron microscopy; Self assembly; Self-assembled monolayers; Sulfhydryl Compounds; Surface chemistry; surface property

Influence of characteristics of the starting hydroxyapatite powders and of deagglomeration procedure, on rheological behaviour of HA suspensions - Lemos, A.F.; Santos, J.D.; Ferreira, J.M.F. (Materials Science ForumMater Sci Forum, 2004)
In order to evaluate how the characteristics of starting HA powders affect their dispersion ability, several tests were made, including particle size distribution, particle morphology (SEM) and rheological measurements of the suspensions. To enable the preparation of concentrated suspensions as high as possible, the influence of deagglomeration procedure on rheological behaviour of hydroxyapatite aqueous suspensions was evaluated. The results revealed significant differences in the dispersing ability of the powders and on the maximum achievable solids loading. In fact, the maximum solids volume fraction that was possible to incorporate in the initial suspension of HA R was only 35-vol.%, while with the HA S it has been possible to start from 45-vol.% suspensions. Ball milling revealed to be more efficient than planetary milling in the preparation of HA R suspensions, and enabled to achieve a maximum solids volume fraction of 45-vol.% at the end of long milling period, which included successive incremental additions of powder. The powder HA S exhibited a much better dispersing ability, enabling the preparation of 60-vol.% solids only after two hours of planetary milling.
Keywords: Agglomeration; Bioceramics; crystallography; Deagglomeration; Foaming processes; hydroxyapatite; medicine; morphology; Particle size analysis; Powder characteristics; Powders; rheology; Scanning electron microscopy; Sedimentation; Sintering

Laser surface modification of hydroxyapatite and glass-reinforced hydroxyapatite - Queiroz, A.C.; Santos, J.D.; Vilar, R.; Eugénio, S.; Monteiro, F.J. (BiomaterialsBiomaterials, 2004)
Surface treatment of materials with excimer laser radiation often results in the formation of a rough columnar or cone-shaped surface topography, which leads to a considerable increase in the surface area. As a result, the search for a non-porous bioactive material with adequate mechanical properties and a high surface to volume ratio, similar to porous materials, which could be used for drug delivery in the treatment of periodontitis, justified assessing excimer laser surface treatment to promote controlled roughning of hydroxyapatite (HA) and glass-reinforced hydroxyapatite (GR-HA). A KrF excimer laser with 248nm radiation wavelength and 30ns pulse duration was used for surface modification. The laser treatment was carried out in air, using wide ranges of radiation fluence and number of laser pulses. In order to identify the physico-chemical changes induced by the laser treatment and the column formation mechanisms in these materials, the treated surfaces were characterised by laser profilometry, scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Fourier transform infra-red spectroscopy (FTIR). Laser processing induced the formation of a surface topography consisting of cone-shaped features. The constitution of the surface layer was also modified, as revealed by FTIR, XPS and XRD. This work has shown that laser surface modification increases the surface area of HA and GR-HA and is a promising technique to increase the reactivity and drug delivery capability of both materials. © 2003 Elsevier Ltd. All rights reserved.
Keywords: article; Biocompatible Materials; Biomaterials; drug delivery system; Durapatite; Excimer laser; Excimer lasers; Fourier transform infrared spectroscopy; FTIR; glass; hydroxyapatite; infrared spectroscopy; laser; Lasers; Macromolecular Substances; materials testing; Molecular Conformation; Non-porous bioactive materials; periodontitis; physical chemistry; porosity; priority journal; Profilometry; Radiation Dosage; Reinforcement; Scanning electron microscopy; Surface area; Surface modification; Surface Properties; Surface treatment; topography; X ray diffraction; X ray diffraction analysis; X ray photoelectron spectroscopy; XPS; XRD

Mineralised membranes for bone regeneration - Mesquita, P.; Branco, R.; Afonso, A.; Vasconcelos, M.; Cavalheiro, J. (Key Engineering MaterialsKey Eng Mat, 2004)
Guided bone regeneration can be achieved using filling biomaterials and protective membranes. The aim of this work is to study a new membrane prepared from shrimp shells, without modification of the natural concave shape. The "in vitro" bioactivity was evaluated using a simulated body fluid prepared with substitution of calcium by strontium (SBR-Sr). The bioactivity behaviour was increased using a surface treatment with sodium silicate. The "in vitro" and "in vivo" tests allow to conclude that these membranes are bioactive and can induce bone growth on their surfaces.
Keywords: Biological membranes; biomaterial; Biomaterials; Bone; Bone Regeneration; Calcium; Ceramic materials; Deproteinization; Membrane; Mineralised membranes; Natural material; Optical microscopy; Shear strength; Sodium compounds; Strontium; Substitution reactions

A model for educational simulation of infant cardiovascular physiology - Goodwin, J.A.; van Meurs, W.L.; Sá Couto, C.D.; Beneken, J.E.W.; Graves, S.A. (Anesthesia and AnalgesiaAnesth. Analg., 2004)
Full-body patient simulators provide the technology and the environment necessary for excellent clinical education while eliminating risk to the patient. The extension of simulator-based training into management of basic and critical situations in complex patient populations is natural. We describe the derivation of an infant cardiovascular model through the redefinition of a complete set of parameters for an existing adult model. Specifically, we document a stepwise parameter estimation process, explicit simplifying assumptions, and sources for these parameters. The simulated vital signs are within the target hemodynamic variables, and the simulated systemic arterial pressure wave form and left ventricular pressure volume loop are realistic. The system reacts appropriately to blood loss, and incorporation of aortic stenosis is straightforward. This infant cardiovascular model can form the basis for screen-based educational simulations. The model is also an essential step in attaining a full-body, model-driven infant simulator.
Keywords: aging; Algorithms; Anesthesiology; aorta stenosis; Aortic Valve Stenosis; arterial pressure; article; Baroreflex; biological model; bleeding; Blood Loss, Surgical; cardiovascular function; Cardiovascular physiology; Computer simulation; education; heart ventricle pressure; hemodynamic parameters; Hemodynamic Processes; Humans; Infant; Models, Biological; priority journal; Pulmonary Circulation; simulation; Ventricular Function, Left; Ventricular Function, Right

New Method for the Incorporation of Soluble Bioactive Glasses to Reinforce Porous HA Structures - Lemos, A.F.; Santos, J.D.; Ferreira, J.M.F. (Key Engineering MaterialsKey Eng Mat, 2004)
The most widely used calcium-phosphate ceramic in clinical applications is hydroxyapatite, Ca 10(PO 4) 6(OH) 2, however its dissolution rate in the human body after implantation is too low to achieve good results and it has poor mechanical properties. Recently, glass reinforced hydroxyapatite composites (GR-HA) have been developed, in order to improve the mechanical properties and to increase the similarity between implants and bone. The addition of a P 2O 5 based glass to a hydroxyapatite matrix, promotes the liquid phase sintering, improving the mechanical properties of the final bodies, and enabling the formation of two other calcium-phosphate phases, which have a higher dissolution rate, more compatible with bone regeneration. However, some of these glass compositions are soluble in water, making their incorporation in aqueous slurry impossible. Therefore, the aim of the present work is to study a new alternative method for the incorporation of soluble P 2O 5 based glass into macroporous structures obtained by different methods.
Keywords: Bioactivation; Bioactive glass; Biocompatibility; Bone; Dissolution; glass; hydroxyapatite; Liquid phase sintering; Macroporous structures; Microstructure; Porous materials; Reinforced hydroxyapatite; Sintering; Slurries

Porous Hydroxyapatite and Glass Reinforced Hydroxyapatite for Controlled Release of Sodium Ampicillin - Queiroz, A.C.; Teixeira, S.; Santos, J.D.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2004)
Porous hydroxyapatite (HA) and glass reinforced hydroxyapatite (GRHA) with adequate macro and microporous structure were developed, aiming at being used as drug delivery carrier of antibiotics, for the in situ treatment of periodontitis. Materials were characterised by XRD and FTIR, presenting no changes from similar dense materials. Mercury intrusion porosimetry revealed micropores of less than 1 μm, accounting for 15% of the total porosity. Compression tests have shown close values for HA and GRHA, with the former showing slightly higher values of strength. Ampicillin adsorption was more effective on porous than on dense HA, and was similar for HA and GRHA.
Keywords: Adsorption; Antibiotics; Coatings; Dense materials; Diseases; Drug delivery; Drug dosage; Fourier transform infrared spectroscopy; glass; Glass reinforced hydroxyapatite; hydroxyapatite; Mercury (metal); Porous; Porous materials; Scanning electron microscopy; Sodium; Strength of materials; Ultraviolet spectroscopy; X ray diffraction analysis

Preparation and Characterization of Calcium Phosphate Nanoparticles - Manuel, C.M.; Foster, M.; Monteiro, F.J.; Ferraz, M.P.; Doremus, R.H.; Bizios, R. (Key Engineering MaterialsKey Eng Mat, 2004)
In this work, CaP nanoparticles were prepared by wet chemical precipitation using three different approaches and were characterised and quantified in terms of their composition. Different precipitating, ageing and drying temperatures were applied and affected HA to TCP ratio. Sintering induced formation of large agglomerates and affected the relative composition, specifically, increased concentrations of TCP as proved by SEM, FTIR and XRD. Different reactants also affected chemical final product composition. Contacts with fibroblasts and osteoblasts revealed better adhesion to sintered substrates.
Keywords: Agglomeration; Bioceramics; Biocompatibility; Bone; Calcium Compounds; Cell culture; Cytocompatibility; Fourier transform infrared spectroscopy; hydroxyapatite; nanoparticles; Nanostructured materials; orthopedics; Precipitation (chemical); Scanning electron microscopy; Synthesis (chemical); Tricalcium phosphate; Wet chemical precipitation; X ray diffraction analysis

Production of porous hydroxyapatite with potential for controlled drug delivery - Queiroz, A.C.; Teixeira, S.; Santos, J.D.; Monteiro, F.J. (Materials Science ForumMater Sci Forum, 2004)
Porous hydroxyapatite was prepared in order to be used as a drug carrier and promote bone ingrowth. For this purpose, the microstructure should have interconnective pores and micro as well as macro porosity, for bone cell adhesion and bone ingrowth. The porous hydroxyapatite prepared by the burn-out method exhibits all these features. For measuring porosity, SEM analysis, mercury intrusion porosimetry and BET were used. FT-IR and XRD analysis revealed that only hydroxyapatite phase was present, being this result similar to the one found for dense samples. The morphology obtained appears to be well adapted to bone growth and drug adsorption.
Keywords: Adsorption; Antibiotics; Bioceramics; Controlled drug delivery; Drug Carriers; Drug delivery; Fourier transform infrared spectroscopy; hydroxyapatite; morphology; Polyurethanes; porosity; Porous; Porous materials; Scanning electron microscopy; X ray diffraction analysis

Protein adsorption effect on in vitro acellular biodegradation of CaO-P 2O 5 glass ceramics - Dias, A.G.; Lopes, M.A.; Santos, J.D. (Materials Science ForumMater Sci Forum, 2004)
This work reports the in vitro accelular behaviour of a glass ceramic (45P 2O 5-45CaO-5MgO-5K 2O), which has significant potential for being used as an alloplastic bone graft. Experiments were carried out by immersing granule samples for a period up to 90 days in Trisbuffer solution at pH 7.4, in the presence and absence of a foetal bovine serum (FBS). The release of calcium, phosphorus, and potassium ions as well as the amount of protein adsorbed was followed by several techniques. The results obtained seem to indicate that the adsorption of proteins on the surface of the material, although causing an initial delay in the degradation, does not hamper the ionic exchange and therefore it is not a barrier for the degradation of the glass ceramic.
Keywords: Adsorption; Bioceramics; Biodegradation; Calcium Compounds; Foetal bovine serum (FBS); Glass ceramics; Hard tissue; Ion exchange; Ionic strength; pH effects; Protein adhesion; Proteins; Tissue

Protein electrostatic self-assembly on poly(DL-lactide) scaffold to promote osteoblast growth - Zhu, H.; Ji, J.; Barbosa, M.A.; Shen, J. (Journal of Biomedical Materials Research - Part B Applied BiomaterialsJ. Biomed. Mater. Res. Part B Appl. Biomater., 2004)
The development of protein coating on 3D biodegradable scaffold based on electrostatic self-assembly (ESA) to promote osteoblast growth is reported. Poly (ethylenimine) (PEI) was employed to obtain a stable positively charged surface on poly(DL-lactide) (PDL-LA) substrate. An extracellular-matrix (ECM)-like biomacromolecule, gelatin, was chosen as the polyelectrolyte to deposit on the activated PDL-LA substrate via ESA technique. Osteoblast (MC3T3) was then cultured on unmodified and gelatin-modified PDL-LA scaffolds. Osteoblast testing regarding total intracellular protein content, total DNA content, cell activity, and cell morphology on the ECM-like multilayer-modified PDL-LA scaffold showed that osteoblast growth was promoted. It will be easy to replace the gelatin with osteoinductive proteins or other polyelectrolytes to promote specific osteoblast functions. In comparison with conventional coating methods, polyelectrolyte multilayers are easy and stable to prepare. They may be a good choice for the surface modification of complex biomedical devices, especially for the 3D tissue-engineering scaffold. These very flexible systems allow broad medical applications for drug delivery and tissue engineering. © 2004 Wiley Periodicals, Inc.
Keywords: 3T3 Cells; Absorbable Implants; Activation analysis; animal cell; Animals; article; Biodegradation; Biomedical engineering; cell activity; cell adhesion; Cell Division; cell growth; cell level; cell protein; cell structure; cell surface; Cell-material interactions; Cells; Coating techniques; DNA; DNA content; Drug products; Electrostatics; ethylene derivative; extracellular matrix; gelatin; Gelation; Growth (materials); Kinetics; macromolecule; materials testing; Mice; Microscopy, Confocal; mouse; nonhuman; osteoblast; Osteoblast growth; Osteoblast testing; Osteoblasts; polyelectrolyte; Polyelectrolytes; Polyesters; Polyethyleneimine; polylactide; polymer; protein assembly; Proteins; Surface modification; Tissue; Tissue engineering

Ribcage Boundary Delineation in Chest X-ray Images - Vinhais, C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
We propose a method for segmenting the ribcage boundary of digital postero-anterior chest X-ray images. The segmentation is achieved by first defining image landmarks: the center of the ribcage and, using polar transformation from this point, two initial points belonging to the ribcage. A bank of Gabor filters (in analogy with the simple cells present in the human visual cortex) is used to obtain an orientation edges enhanced image. In this enhanced image, an edge following, starting from the landmarks previously determined, is performed for delineating the left and right sections of the ribcage. The complete segmentation is then accomplished by connecting these sections with the top section of the ribcage, obtained by means of spline interpolation. © Springer-Verlag 2004.
Keywords: Edge following; Gabor Filters; Polar image transform; Probabilistic genetic algorithm; Ribcage boundary segmentation

Scheduling parallel tasks on heterogeneous clusters - Barbosa, J.; Morais, C.; Monteiro, A.P. (Proceedings of the IASTED International Conference on Parallel and Distributed Computing and SystemsProc. IASTED INt. Conf. Parall. Distrib. Comput. Syst., 2004)
Parallel tasks, also called malleable tasks, are tasks that can be executed on any number of processors with its execution time being a function of the number of processors alloted to it. The scheduling of independent parallel tasks on homogeneous machines is a problem that has been extensively studied. For heterogeneous machines, with a diverse CPU capacity, new challenges arise, namely the selection of the set of CPUs that optimizes the processing time of a given task. This paper presents a methodology to determine the best allotment for each task that minimizes its processing time on a given heterogeneous machine. The aim is to improve the global processing time of a complex algorithm composed by several linear algebra kernels, by scheduling a number of parallel tasks in the heterogeneous machine. The results presented compare this approach to the simpler data parallel execution of each task on the heterogeneous cluster, i.e. executing one task at a time using the data parallel programming model.
Keywords: Computational complexity; Computer programming; CPU capacity; Data handling; Directed acyclic graphs (DAG); Graph theory; Heterogeneous clusters; Linear algebra; Parallel algorithms; Parallel processing systems; Parallel/malleable tasks; Program processors; Scheduling

Study of a Silicate Cement for Dental Applications - Pereira, S.; Cavalheiro, J.; Branco, R.; Afonso, A.; Vasconcelos, M. (Key Engineering MaterialsKey Eng Mat, 2004)
Dental cements have a wide field of applications in clinical practice. The use as a base material is a very important one in dentistry. The aim of this study is to assess some relevant properties of a silicate cement (SC) developed for dental applications, comparing it with two other cements already commercialised, a zinc phosphate cement De Trey Zinc Cement Improved® (DT) and ProRootMTA®(MTA). Their compressive strength, dimensional changes and weight variation in water after setting, according to ISO standards were compared. The mean compressive strength of DT, MTA and SC were, respectively, 134MPa, 31MPa and 46MPa. There were no statistically significant differences for the three tested cements at the various time intervals, in respect to their weight variation or dimensional changes. However, there was a little loss of weight for DT (0.15%) and for MTA (3%) and a gain of 3% for the SC. Regarding the dimensional changes, all materials undergo little expansion, more significant in the MTA and in the SC samples of 2,07% and 0,4%, respectively. The new Silicate Cement, presented enough compressive strength, low weight variation, very small dimensional changes and good adaptation to the surface of dental cavity. For these reasons this new cement could be a valuable proposal as a base material for dental applications.
Keywords: Biocompatibility; Body fluids; Ceramic materials; ceramics; Compressive Strength; Dental cement; Dental cements; Dental prostheses; Dimensional stability; Precipitation (chemical); Scanning electron microscopy; Silicate cements; Silicates; Stainless steel; Weight variation

Ultrastructural comparison of dissolution and apatite precipitation on hydroxyapatite and silicon-substituted hydroxyapatite in vitro and in vivo - Porter, A.E.; Botelho, C.M.; Lopes, M.A.; Santos, J.D.; Best, S.M.; Bonfield, W. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2004)
Recent histological studies have demonstrated that the substitution of silicate ions into hydroxyapatite (HA) significantly increases the rate of bone apposition to HA implants. The enhanced bioactivity of silicon-substituted HA (Si-HA) over pure HA has been attributed to the effect of silicate ions in accelerating dissolution. In the present study, high-resolution transmission electron microscopy (HR-TEM) was employed to compare dissolution of HA and Si-HA in an acellular simulated body fluid (SBF) to dissolution in an in vivo model. HR-TEM observations confirmed a difference in morphology of apatite precipitates in vivo and in SBF: apatite deposits were platelike in vivo and nodular in SBF. Compositional mapping suggested that preferential dissolution of silicon from the implant promotes the nucleation of carbonate apatite around the implant. The in vivo findings illustrated an absence of dissolution at the bone-HA or Si-HA interface, whereas dissolution was extensive from within the implant. The amount of dissolution in acellular SBF was similar to dissolution from within the implant, although the site at which the dissolution nucleates was different: dissolution predominates at the crystallite surfaces in SBF, whereas grain boundary dissolution predominates in vivo. These findings suggest that proteins in the in vivo milieu modify the processes of dissolution from the implant. © 2004 Wiley Periodicals, Inc.
Keywords: Apatite; article; Bioactivity; Biocompatible Materials; body fluid; carbonic acid; comparative study; Composition; Dissolution; Durapatite; histology; hydroxyapatite; implant; Implants (surgical); in vitro study; in vivo study; Interfaces (materials); Microscopy, Electron; Microscopy, Electron, Scanning; morphology; precipitation; Precipitation (chemical); Silicon; Simulated body fluid; Simulated body fluids (SBF); simulation; transmission electron microscopy; ultrastructure

The Valences of Egg White for Designing Smart Porous Bloceramics: As Foaming and Consolidation Agent - Lemos, A.F.; Ferreira, J.M.F. (Key Engineering MaterialsKey Eng Mat, 2004)
Porous hydroxyapatite bioceramics were developed by a new direct consolidation method based on the foaming capability of egg white and on its gelling properties on heating, thus acting both as pore former and consolidator agent. The bubble forming capability of fresh egg white, due to the presence of a globular protein - albumen, allows the formation of a stable foam when added to a ceramic suspension. Adding a sufficient amount of the globular protein to the suspension revealed to be crucial to control either the pore volume fraction as well as the gelling behaviour and the rigidity of the green bodies. This consolidation method can be performed in nonporous moulds, enabling materials with controlled porosity to be obtained by varying the egg white content in the slip composition. After drying, burnout and sintering, materials with ultimate porosities close to 75 % were obtained.
Keywords: Bioceramics; Biodegradation; Bone-grafting; Ceramic materials; Consolidation technique; Consolidation techniques; Egg-white; heating; hydroxyapatite; morphology; Pore size; porosity; Porous ceramics; Porous materials; Proteins; Slurries; Solidification

XRD and FT-IR characterisation of hydroxyapatite sputtered films on titanium - Silva, R.A.; Sousa, M.; Monteiro, F.J.; Barrai, R.; Lopes, M.A. (Transactions - 7th World Biomaterials CongressTrans. World Biomater. Congr., 2004)
XRD and FT-IR were used to characterize hydroxyapatite (HA) films, which were prepared using rf sputtering. The morphology of the sample films was analyzed using SEM. From the FT-IR spectrum, sputtered HA films showed structural changes, namely the decrease of the strength of the liberational mode of OH group, indicating the presence of a poorly crystalline phase. XRD results of films obtained at 500 W and 400 W showed that the crystallinity of the 500 W 4h e 2h samples was low, just showing a very incipient degree of crystalline structural structural arrangement, while in the 400 W-4h and 2h samples there was no crystalline structure, with only a slight diffraction of the 002 and 301 HA planes.
Keywords: Absorption bands; Adsorption; Bioactive films; Biomaterials; Bone; crystal structure; Crystallinity; Deposition; Fourier transform infrared spectroscopy; hydroxyapatite; Hydroxyapatite films; morphology; Scanning electron microscopy; Sintering; Sputtering; Surface topography; Thin films; Titanium; X ray diffraction analysis

Adhesion of human leukocytes to biomaterials: An in vitro study using alkanethiolate monolayers with different chemically functionalized surfaces - Barbosa, J.N.; Barbosa, M.A.; Água, A.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2003)
The adhesion of human leukocytes to self-assembled monolayers of well-defined surface chemistry was investigated in vitro. Polymorphonuclear (PMN) and mononuclear leukocytes were isolated from human blood by centrifugation techniques. The effect on adhesion of cell activation produced by pre-incubation of leukocytes with phytohemagglutinin (PHA) and phorbol 12-myristate 13-acetate (PMA) was also studied. Gold substrates were modified by treatment with alkanethiols with three different terminal chemical groups: COOH, OH, and CH 3. After incubation with the two subpopulations of leukocytes, the monolayers were washed, treated with fixative, stained with a Giemsa method, and observed by light microscopy to quantify the number of attached leukocytes. Comparative quantification of the density of leukocyte adhesion to the three types of self-assembled monolayers was determined. The hydrophobic surface expressing CH 3 was found to be the one that induced the highest adhesion density of leukocytes, both of PMN and mononuclear cells. In vitro activation of both mononuclear and PMN leukocytes further increased cell adhesion to the chemically defined monolayers that were used. This enhancement was higher for PHA-activated than for PMA-stimulated mononuclear cells, whereas PMA treatment of neutrophils resulted in a higher rate of adhesion of these cells than PHA stimulation. © 2003 Wiley Periodicals, Inc.
Keywords: alkane derivative; article; Biocompatible Materials; biomaterial; Biomaterials; Blood; carboxyl group; cell adhesion; cell interaction; cell isolation; cell subpopulation; cell surface; Cell-surface interactions; Cells; Centrifugation; controlled study; drug effect; Giemsa stain; gold; human; human cell; Humans; hydrophobicity; hydroxide; in vitro study; Incubation; lectin; Lectins; leukocyte; Leukocyte activation; leukocyte adherence; Leukocyte adhesion; Leukocytes; Leukocytes, Mononuclear; materials testing; methane; microscopy; Monolayers; mononuclear cell; neutrophil; Neutrophils; Optical microscopy; phorbol 12 acetate 13 myristate; phorbol 13 acetate 12 myristate; physiology; phytohemagglutinin; Phytohemagglutinins; polymorphonuclear cell; Self-assembled monolayers; Surface Properties; surface property; Tetradecanoylphorbol Acetate; thiolacid

Albumin adsorption on alkanethiols self-assembled monolayers on gold electrodes studied by chronopotentiometry - Martins, M.C.L.; Fonseca, C.; Barbosa, M.A.; Ratner, B.D. (BiomaterialsBiomaterials, 2003)
Chronopotentiometry was used to study the adsorption of human serum albumin (HSA) to self-assembled monolayers with the following terminal functional groups: CH 3, COOH and OH. Surfaces were characterized by X-ray photoelectron spectroscopy, water contact angle measurements and cyclic voltammetry. HSA coverage of the different SAMs was investigated by chronopotentiometry and the total amount of adsorbed protein was determined using radiolabelled albumin. Both techniques have demonstrated that HSA adsorption to the different SAM-modified electrodes increases in the following order: OH<COOH<CH 3-terminated SAMs. A good correlation between coverage and total amount of HSA adsorbed was observed for long adsorption times (900s). © 2003 Elsevier Science Ltd. All rights reserved.
Keywords: Adsorption; Albumin; Albumin adsorption; Albumins; alkane; Alkanes; article; Biocompatible Materials; biomaterial; Biomaterials; carboxyl group; Chemical modification; Chronopotentiometry; Contact angle; correlation analysis; cyclic potentiometry; Cyclic voltammetry; electrochemistry; electrode; Electron Probe Microanalysis; Functional groups; gold; Humans; hydroxyl group; isotope labeling; methyl group; Monolayers; potentiometry; priority journal; protein analysis; Self assembly; Self-assembled monolayers; Serum Albumin; Sulfhydryl Compounds; Surface modification; Surface Properties; surface property; temperature; thiol derivative; Time Factors; Water; X ray photoelectron spectroscopy

Albumin adsorption on Cibacron Blue F3G-A immobilized onto oligo(ethylene glycol)-terminated self-assembled monolayers - Martins, Ma.C.L.; Naeemi, E.; Ratner, B.D.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2003)
Self-assembled monolayers can be tailored with specific ligands to a certain protein and at the same time prevent the non-specific adsorption of other proteins. Cibacron Blue F3G-A (CB-thiol) was successfully immobilized onto tetra(ethylene glycol)-terminated alkanethiol (CB-thiol). The affinity of human serum albumin (HSA) to immobilized Cibacron Blue F3G-A was studied using mixed thiolate self-assembled monolayers on gold with different n-alkyl chain lengths and functional terminal groups (CH 3-; OH- and tetra(ethylene glycol)). Surfaces were characterized using X-ray photoelectron spectroscopy and water contact angle measurements. Albumin adsorption and exchangeability of the adsorbed albumin molecules with other albumin molecules in solution were evaluated using 125I-radiolabeled HSA. Competitive adsorption between albumin and fibrinogen to the different self-assembled monolayers (SAMs) was also investigated. Results showed that the incorporation of CB-thiol on the monolayers does not increase the HSA adsorption and reversibility on the SAMs. However, although specific adsorption of HSA to the immobilized Cibacron Blue F3G-A was not demonstrated, the presence of CB-thiol decreases the affinity of fibrinogen to the OH-terminated SAMs. © 2003 Kluwer Academic Publishers.
Keywords: Adsorption; Albumin; aqueous solution; article; Cell immobilization; cibacron blue f3ga; Contact angle; controlled study; Drug products; Ethylene Glycol; fibrinogen; functional group; Glycols; gold; human; human serum albumin; iodine 125; isotope labeling; ligand; macrogol; molecule; priority journal; protein assembly; protein binding; protein immobilization; protein structure; Proteins; radioassay; Self assembly; surface property; synthesis; tetra(ethylene glycol) undecanethiol; thiol; thiol derivative; unclassified drug; Water; X ray photoelectron spectroscopy

Albumin and fibrinogen adsorption on Cibacron blue F3G-A immobilised onto PU-PHEMA (polyurethane-poly (hydroxyethylmethacrylate)) surfaces - Martins, M.C.L.; Wang, D.; Ji, J.; Feng, L.; Barbosa, M.A. (Journal of Biomaterials Science, Polymer EditionJ. Biomater. Sci. Polym. Ed., 2003)
In the present work, it is intended to study the effect of Cibacron blue F3G-A (CB) immobilised onto PU-PHEMA (polyurethane-poly(hydroxyethylmethacrylate)) surfaces on protein adsorption and bacterial adhesion. CB immobilisation was carried out by covalent binding between its triazine ring and the hydroxyl groups of the polymer. Characterisation of the films was carried out by attenuated total reflection Fourier transform infrared spectroscopy (ATR-FT-IR), contact angle measurements, X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). CB efficiency was evaluated using radiolabelled albumin and fibrinogen from pure solutions, mixtures of both and plasma. Bacterial adhesion tests before and after albumin pre-coating were also performed. The presence of CB increases albumin and fibrinogen adsorption to PU-PHEMA surfaces. The incorporation of CB onto the PU-PHEMA surface also increases bacterial adhesion. Although albumin pre-coating decreases bacterial adhesion onto PU (67% decrease) and PU-PHEMA-CB (80%), bacterial adhesion is always lower on PU and PU-PHEMA surfaces than on PU-PHEMA-CB. These results demonstrate that, in contrast to what has been described for CB bound to dextran, CB immobilisation on PU-PHEMA surfaces presents low selectivity to albumin and increased bacterial adhesion relatively to PU and PU-PHEMA surfaces.
Keywords: Adsorption; Albumin; Albumins; article; Bacterial adhesion; bacterium adherence; Biocompatible Materials; Chemical structure; Cibacron blue; cibacron blue f3ga; Contact angle; controlled study; covalent bond; dextran; fibrinogen; hydroxyl group; immobilization; infrared spectroscopy; isotope labeling; Membranes, Artificial; Microscopy, Electron, Scanning; nonhuman; PHEMA; Polyhydroxyethyl Methacrylate; polymacon; polyurethan; priority journal; Protein adsorption; Scanning electron microscopy; Spectroscopy, Fourier Transform Infrared; Staphylococcus epidermidis; Surface Properties; triazine derivative; Triazines; X ray photoelectron spectroscopy; XPS

Albumin and fibrinogen adsorption on PU-PHEMA surfaces - Martins, M.C.L.; Wang, D.; Ji, J.; Feng, L.; Barbosa, M.A. (BiomaterialsBiomaterials, 2003)
Materials that adsorb specific proteins may find a variety of applications in the biomedical field. The aim of this study was the preparation of a hydrophilic surface, with low protein adsorption, to be used in the future as a support for the immobilisation of several species, e.g. Cibacron Blue F3G-A, which has been described to induce specific albumin adsorption. Poly(hydroxyethylmethacrylate) (PHEMA) and poly(hydroxyethylacrylate) (PHEA) were chosen as the hydrophilic surface because they can be easily polymerised and possess hydroxyl groups that can be used for the immobilisation of different compounds. Thin films of PHEMA and PHEA were successfully graft polymerised onto the surface of a commercial poly(etherurethane) (PU) using ceric ion as initiator. Grafting polymerisations were followed by mass gain and attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR). Since stability tests demonstrated that only PU-PHEMA was stable in alkaline solutions, a necessary condition to future immobilisations, the investigation was focused on the coating of PU with PHEMA. PU-PHEMA films were characterised in detail using several techniques as mass gain, ATR-FTIR, contact angle measurements, X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). Protein adsorption was evaluated using radiolabelled albumin and fibrinogen from pure solutions and from mixtures of both proteins. PU surfaces modified with PHEMA have demonstrated low protein adsorption, showing their potential use as substrates. This opens the possibly of exploring the advantages of selective adsorption by appropriate immobilisation of specific molecules. © 2003 Elsevier Science Ltd. All rights reserved.
Keywords: acrylic acid ethyl ester; Adsorption; Albumin; Albumins; article; ATR-FTIR; Biocompatible Materials; Chemical modification; Dose-Response Relationship, Drug; fibrinogen; film; Fourier transform infrared spectroscopy; Graft polymerisation; Humans; Hydrogen-Ion Concentration; Hydrophilic surfaces; hydrophilicity; hydroxyl group; infrared spectroscopy; isotope labeling; Microscopy, Electron, Scanning; molecular stability; Pellethane; PHEMA; poly(2 hydroxyethyl acrylate); polyetherurethan; Polyhydroxyethyl Methacrylate; polymacon; Polymerization; priority journal; protein; Protein adsorption; Proteins; Scanning electron microscopy; Spectrometry, X-Ray Emission; Spectroscopy, Fourier Transform Infrared; surface property; Thin films; unclassified drug; Water; X ray photoelectron spectroscopy

Cartographic representation of spatial data - De Pina, M.D.F. (Representação Cartográfica de Dados EspaciaisArquivos de MedicinaArq. Med., 2003)
Keywords: article; cartography; diagram; dot map; epidemiological data; geographic distribution; histogram; population distribution; tuberculosis; visual aid

Constructing thromboresistant surface on biomedical stainless steel via layer-by-layer deposition anticoagulant - Tan, Q.; Ji, J.; Barbosa, M.A.; Fonseca, C.; Shen, J. (BiomaterialsBiomaterials, 2003)
Multilayer films consisting of polyethylenimine (PEI) and heparin were successfully prepared on biomedical 316L stainless steel surface via electrostatic self-assembly (ESA) of the PEI and heparin. The process of ESA of PEI/heparin was monitored by static contact angle, electrochemical impedance spectroscopy (EIS), reflection adsorption spectroscopy and X-ray photoelectron spectroscopy data. The contact angle and EIS data revealed that the multilayer coating was stable in Tris-HCl (pH 7.35) buffer solution for 21 days. The static platelet adhesion and static clotting time experiments indicated that the PEI/heparin-deposited stainless steel could resist the platelet adhesion and prolong the static clotting time effectively. Such an easy processing and shape-independent method may have good potential for surface modification of cardiovascular devices. © 2003 Elsevier Ltd. All rights reserved.
Keywords: 316L stainless steel; Adhesion; Adsorption; anticoagulant agent; Anticoagulants; aqueous solution; article; Biocompatibility; biomaterial; Biomaterials; blood clotting time; Blood Platelets; Blood-compatibility; buffer; Coated Materials, Biocompatible; coating; Coatings; Contact angle; controlled study; Deposition; device; electricity; Electrochemical impedance spectroscopy; electrochemistry; Electrostatics; heparin; human; human cell; Humans; implant; Layer-by-layer; material coating; materials testing; Multilayers; Organic polymers; pH; Platelet Adhesiveness; Polyethyleneimine; priority journal; reflection adsorption spectroscopy; Self assembly; Spectroscopy; Stainless steel; Surface Properties; surface property; Surfaces; thrombocyte adhesion; Thromboresistant surfaces; trometamol; X ray photoelectron spectroscopy

Corrosion behaviour of commercially pure titanium shot blasted with different materials and sizes of shot particles for dental implant applications - Aparicio, C.; Javier Gil, F.; Fonseca, C.; Barbosa, M.; Planell, J.A. (BiomaterialsBiomaterials, 2003)
It is well known that the osseointegration of the commercially pure titanium (c.p. Ti) dental implant is improved when the metal is shot blasted in order to increase its surface roughness. This roughness is colonised by bone, which improves implant fixation. However, shot blasting also changes the chemical composition of the implant surface because some shot particles remain adhered on the metal. The c.p. Ti surfaces shot blasted with different materials and sizes of shot particles were tested in order to determine their topographical features (surface roughness, real surface area and the percentage of surface covered by the adhered shot particles) and electrochemical behaviour (open circuit potential, electrochemical impedance spectroscopy and cyclic polarisation). The results demonstrate that the increased surface area of the material because of the increasing surface roughness is not the only cause for differences found in the electrochemical behaviour and corrosion resistance of the blasted c.p. Ti. Among other possible causes, those differences may be attributed to the compressive residual surface stresses induced by shot blasting. All the materials tested have an adequate corrosion and electrochemical behaviour in terms of its possible use as dental implant material. © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: article; Blast finishing; chemical composition; chemistry; Corrosion; Dental implant; Dental Implants; Dental prostheses; Electric Potential; Electrochemical impedance spectroscopy; electrochemistry; impedance; materials testing; Particle Size; Polarization; priority journal; Shot blasting; Spectroscopy; stress; Surface roughness; Surface topography; Titanium; tooth implantation

Creating maps: The construction of a lecture on the specialties of phenomena - Henrique Castiglione, L.; De Fátima De Pina, M. (Elaborar Mapas: A Construção de um Discurso sobre a Espacialidade dos FenómenosArquivos de MedicinaArq. Med., 2003)
Keywords: audiovisual equipment; geography; information processing; interpersonal communication; medical education; medical specialist; review

Detection and validation of lung field contours on chest radiographs - Mendonça, A.M.; Alves Da Silva, J.; Campilho, A. (Proceedings of the IASTED International Conference on Biomedical EngineeringProc. IASTED Internat. Conf. Biomed. Eng., 2003)
The purpose of the research herein presented is the automatic detection of lung boundaries in posterior-anterior digital chest radiographs. The precise location of the two lungs is important in a computer-aided diagnosis system as it allows the reduction of the region under analysis, decreasing the computation time and facilitating data compression. Furthermore, it allows the delimitation of the search area, easing the selective tuning of the abnormalities detection algorithms. The results produced by the automatic method were validated by comparison with manual contours traced by an experienced radiologist. For this particular purpose, two programs with friendly interfaces were developed. The achieved comparison results demonstrate the good performance of the automatic method.
Keywords: Algorithms; automation; Biological organs; Chest radiographs; Computational time; Computer aided diagnosis; Computer-aided diagnosis; Data compression; Image analysis; Medical image processing; Medical imaging; Radiography; Regions of interest (ROI)

Development of foetal and neonatal simulators at the University of Porto - van Meurs, W.L.; Sá Couto, P.M.; Sá Couto, C.D.; Bernardes, J.F.; Ayres-de-Campos, D. (Medical Education, SupplementMed. Educ. Suppl., 2003)
Background: Human error can be expected to play a significant role in adverse outcomes in perinatal acute care. In acute care of the adult, simulator based training is recommended and used to improve patient safety. Aims: Our general goal is to develop model-driven foetal and neonatal educational simulators and curricula. The specific objectives of this paper are to introduce the reader to the perinatal acute care context and simulator design considerations, as well as to give initial results and describe ongoing developments. A brief description of adult simulators and simulation engines is followed by a more detailed description of a foetal distress simulator (FDS) and of models for a neonatal simulator developed at the University of Porto. Ongoing developments involve the modelling of foetal baroreflexes, the effect of uterine contractions, and an adapted method for estimating foetal heart rate variability parameters. Results: We present FDS simulation results reflecting the changes in oxygen supply to the foetus and the foetal heart rate in response to a reduction in uterine blood flow. We also present a structural diagram of a model for the educational simulation of congenital heart disease and preliminary simulation results reflecting a patent ductus arteriosus. Conclusion: We expect that, after initial clinical and educational validation, the presented models and simulators will play a role in simulator-based educational programmes contributing to increased perinatal safety.
Keywords: article; audiovisual equipment; blackstarPatient simulation; clinical competence; Clinical competence/blackstarstandards/economics; competence; Curriculum; Education, Medical, Undergraduate; Education, medical, undergraduate/blackstarmethods; Equipment Safety; fetus distress; human; Humans; Manikins; medical education; model; oxygen; Patient Simulation; perinatal care; Perinatal care/ blackstarstandards/methods; Portugal; safety; simulator; training

Dissolution studies of hydroxyapatite and glass-reinforced hydroxyapatite ceramics - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J.; Prado da Silva, M.H. (Materials CharacterizationMater Charact, 2003)
In the continuous agitation assays, glass-reinforced hydroxyapatite (GR-HA) was shown to form a calcium phosphate (CaP) layer, but hydroxyapatite (HA) only formed dispersed precipitates. The formation of this layer was first detected on the GR-HA with a 7.5% glass addition (7.5 GR-HA) after only 3 days of immersion in simulated body fluid (SBF). The time required for layer formation decreased as the amount of glass added to the HA increased. The dissolution rate of the materials followed a similar pattern, i.e. the dissolution rate for GR-HA was higher than for HA, and increased with the addition of glass. The immersion of 7.5 GR-HA in water showed almost linear dissolution kinetics over the immersion periods (3, 7, 15, 30 and 60 days). The concentration of calcium ions in solution and the scanning electron microscopy (SEM) analysis of the 7.5 GR-HA specimens immersed in water and in SBF revealed a clear competition between the material dissolution and the precipitation of a CaP phase. Fourier transformed infrared spectroscopy with alternated total reflectance (FTIR-ATR) analysis indicated that the CaP phase that formed during longer immersion times (30 and 60 days) could be a carbonate-substituted CaP precipitate. As expected from previous work, the GR-HA behavior in terms of its in vitro bioactivity is higher than HA because a homogeneous CaP layer is formed and the precipitation occurs faster. From the dissolution test and in accordance with the chemical composition of the samples, GR-HA was more soluble than HA. © 2003 Elsevier Inc. All rights reserved.
Keywords: Ceramic materials; Dissolution; glass; Glass-reinforced hydroxyapatite; hydroxyapatite; Immersion times; Scanning electron microscopy

Effect of heat treatment on relative content of β-Ca 2P 2O 7 crystalline phase in calcium phosphate glass-ceramics - Li, Y.; Weng, W.; Du, P.; Shen, G.; Han, G.; Santos, J.D.; Lopes, A.M. (Kuei Suan Jen Hsueh Pao/ Journal of the Chinese Ceramic SocietyKuei Suan Jen Hsueh Pao, 2003)
The 3Na 2O-12TiO 2-57CaO-28P 2O 5 glass was heat-treated to form glass-ceramics under different conditions. The relationships between the heat-treatment conditions and the content of β-Ca 2P 2O 7 in the glass-ceramics, bioactivity of the glass-ceramics were investigated. The experimental results show that the glass-ceramics contain crystalline phases of β-Ca 2P 2O 7, CaTi 4(PO 4) 6, NaTi 2(PO 4) 3 and TiP 2O 7 after heat-treatment, in which β-Ca 2P 2O 7 crystalline phase is a dominant one; the content of β-Ca 2P 2O 7 crystalline phase in the glass-ceramics increases with the increase of nucleation temperature and time; and the glass-ceramics with more β-Ca 2P 2O 7 crystalline phase has a better bioactivity. The role of heat-treatment in increasing the content of β-Ca 2P 2O 7 crystalline phase in the glass-ceramics is attributed to the crystallization of β-Ca 2P 2O 7 involved in the simultaneous occurrence of the glass phase separation and nucleation processes. Due to the better ability of β-Ca 2P 2O 7 in promoting bioactivity, the glass-ceramics with more β-Ca 2P 2O 7 phase have stronger bioactivity. Therefore, the bioactivity of the glass-ceramics could be changed by heat treatment.
Keywords: Bioactivity; Calcium Compounds; calcium phosphate; Crystalline materials; Crystalline phase; Crystallization; Glass ceramics; Glass-ceramics; Heat treatment; Nucleation; Phase separation; Phosphates

In vitro degradation studies of calcium phosphate glass ceramics prepared by controlled crystallization - Dias, A.G.; Lopes, M.A.; Gibson, I.R.; Santos, J.D. (Journal of Non-Crystalline SolidsJ Non Cryst Solids, 2003)
Calcium phosphate glass ceramics with incorporation of small additions of two nucleating agents, MgO and K 2O were prepared in the metaphosphate and pyrophosphate region, using an appropriate two-step heat treatment of controlled crystallization defined by differential thermal analysis results. Identification and quantification of crystalline phases precipitated from the calcium phosphate glass were performed using X-ray diffraction and Rietveld analysis. The β-Ca 2P 2O 7 (β-DCP), KCa(PO 3) 3, β-Ca(PO 3) 2 and Ca 4P 6O 19 phases were detected in the glass ceramics. In order to evaluate the degradation of the glass ceramics prepared, degradation studies were carried out during 42 days in Tris-HCl solution at 37 °C, pH 7.4, using granules in the range of 355-415 μm. The materials presented a weight loss ranging up to 12%. The ions leached during the immersion mainly originated from the KCa(PO 3) 3 phase, probably due to the presence of K + ion in the calcium metaphosphate, and the residual glassy phase. The structural changes at the surface of materials during degradation have been analyzed by Fourier transform infrared spectroscopy and X-ray diffraction. Results showed that significant surface changes occurred with immersion time, with the decrease of KCa(PO 3) 3, β-Ca 2P 2O 7 and β-Ca(PO 3) 2 phases occurring at different periods of immersion. This study has demonstrated an easy way to prepared calcium phosphate materials with specific calcium phosphate phases and crystallization, and therefore specific degradation rates. © 2003 Elsevier B.V. All rights reserved.
Keywords: Calcium Compounds; Crystallization; Degradation; Differential thermal analysis; Fourier transform infrared spectroscopy; Glass ceramics; Heat treatment; Nucleating agents; Nucleation; X ray diffraction

Optimal detection of symmetry axis in digital chest X-ray images - Vinhais, C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2003)
We present a method for detecting the axis of bilateral symmetry in a digital chest X-ray image and subsequently measuring the degree of symmetry of the image. The detection is achieved by analysing rotated-reflected digital chest X-ray images and it is posed as a global optimization problem solved with a probabilistic genetic algorithm (PGA). The global search is initially based on natural peak orientation information related to the orientation of the symmetry axis. Only a few generations of the PGA are needed to achieve convergence to all the images in the database. This method is applied directly on the intensity input image and does not require any prior segmentation. © Springer-Verlag Berlin Heidelberg 2003.
Keywords: image processing; Probabilistic genetic algorithm; Reflectional Symmetry

A probabilistic model for the cooperative modular neural network - Alexandre, L.A.; Campilho, A.; Kamel, M. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2003)
This paper presents a model for the probability of correct classification for the Cooperative Modular Neural Network (CMNN). The model enables the estimation of the performance of the CMNN using parameters obtained from the data set. The performance estimates for the experiments presented are quite accurate (less than 1% relative difference). We compare the CMNN with a multi-layer perceptron with equal number of weights and conclude that the CMNN is preferred for complex problems. We also investigate the error introduced by one of the CMNN voting strategies. © Springer-Verlag Berlin Heidelberg 2003.

Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers - Martins, M.C.L.; Ratner, B.D.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2003)
The effect of surface composition and wettability on the adsorption of human serum albumin (HSA) was studied. Self-assembled monolayers (SAMs) containing mixtures of longer chain methyl- and shorter chain hydroxyl-terminated alkanethiols on gold were used to produce a range of surfaces with different wettabilities and exposed functional groups. Different SAMs were characterized by X-ray photoelectron spectroscopy, water contact angles, and Fourier transform infrared reflection absorption spectroscopy (IRAS). HSA adsorption onto the different SAMs was evaluated by contact angle measurements (wetting tension determinations), radiolabeling of proteins, and IRAS. Concerning HSA adsorption, all the techniques demonstrated higher HSA adsorption on more hydrophobic surfaces. The wetting tension measurements and IRAS suggested a gradual decrease of the HSA adsorption with increases of surface hydrophilicity. Radiolabeled albumin measurements also demonstrated a significant decrease of HSA adsorption on the pure hydroxyl-terminated SAMs. However, no significant differences were detected between mixed and pure methyl-terminated SAMs. Studies of HSA exchangeability with human fibrinogen have suggested that an ideal percentage of hydroxyl groups on the surface may increase albumin affinity without fibrinogen adsorption. © 2003 Wiley Periodicals, Inc.
Keywords: Absorption spectroscopy; Adsorption; article; Biocompatible Materials; Contact angle; Contact angles; fourier transform infrared reflection absorption spectroscopy; Fourier transform infrared spectroscopy; Functional groups; gold; human serum albumin; hydrophilicity; hydrophobicity; IRAS; isotope labeling; measurement; Mixtures; monolayer culture; Monolayers; Protein adsorption; Proteins; Self-assembled monolayers; Spectrum Analysis; Sulfhydryl Compounds; surface property; tension; thiol derivative; Time Factors; wettability; X ray photoelectron spectroscopy; XPS

Surface engineering of poly(DL-lactide) via electrostatic self-assembly of extracellular matrix-like molecules - Zhu, H.; Ji, J.; Tan, Q.; Barbosa, M.A.; Shen, J. (BiomacromoleculesBiomacromolecules, 2003)
We report the development of new biomacromolecule coatings on biodegradable biomaterials based on electrostatic assembly of extracellular matrix-like molecules. Poly(ethylene imine) (PEI) was employed to engineer poly(DL-lactide) (PDL-LA) substrate to obtain a stable positively charged surface. An extracellular matrix- (ECM-) like biomacromolecule, gelatin, was selected as the polyelectrolyte to deposit on the activated PDL-LA substrate via the electrostatic assemble technique. The extracellular matrix-like multilayer on the PDL-LA substrate was investigated by attenuated total reflection (ATR-FTIR), X-ray photoelectron spectrscopy (XPS), contact angle, and atomic force microscopy (AFM). The gradual buildup of the protein layer was investigated by UV-vis spectra, and it was further given a quantitative analysis of the protein layer on the PDL-LA substrate via the radioiodination technique. The stability of the protein layer under aqueous condition was also tested by the radiolabeling method. Chondrocyte was selected as the model system for testing the cell behavior and morphology on modified PDL-LA substrates. The chondrocyte test about cell attachment, proliferation, cell activity and cell morphology by SEM, and confocal laser scanning microscopy (CLSM) investigation on extracellular matrix-like multilayer modified PDL-LA substrate was shown to promote chondrocyte attachment and growth. Comparing conventional coating methods, polyelectrolyte multiplayers are easy and stable to prepare. It may be a good choice for the modification of 3-D scaffolds used in tissue engineering. These very flexible systems allow broad medical applications for drug delivery and tissue engineering.
Keywords: animal cell; Animalia; Animals; article; Atomic force microscopy; biodegradability; biomaterial; cartilage cell; cell activity; cell adhesion; cell function; cell growth; cell proliferation; cell structure; Cells, Cultured; Chondrocytes; confocal laser microscopy; controlled study; Electron Probe Microanalysis; Electrostatics; extracellular matrix; Fourier transform infrared spectroscopy; gelatin; macromolecule; Macromolecules; Microscopy, Atomic Force; nonhuman; polyelectrolyte; Polyesters; Polyethyleneimine; Polyethylenes; polylactide; priority journal; protein analysis; protein stability; quantitative analysis; Rabbits; radioiodination; Scanning electron microscopy; Self assembly; Spectrophotometry, Ultraviolet; Spectroscopy, Fourier Transform Infrared; Surface charge; Surface engineering; Surface Properties; Tissue engineering; Ultraviolet spectroscopy; X ray photoelectron spectroscopy

Synthesis of hydroxyapatite and tricalcium phosphate nanoparticles - Preliminary studies - Manuel, C.M.; Ferraz, M.P.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2003)
The wet mechanochemical process (MC) and chemical precipitation (CP) used to prepare hydroxyapatite (HA) and tricalcium phosphate (TCP) nanoparticles proved to be successful. In mechanochemical treatment, water and ethanol were used as a solvent but the last one improved particles agglomeration and decreased HA formation. This effect was also observed when aging temperature was decreased in wet chemical precipitation.
Keywords: Agglomeration; Calcium Compounds; Chemical precipitation; hydroxyapatite; Mechanochemical treatment; nanoparticles; Nanostructured materials; Precipitation (chemical); Synthesis (chemical); Tricalcium phosphate

The use of geographic information systems in health data analysis - De Pina, M.D.F. (O uso dos sistemas de informação geográfica na análise de dados de saúdeArquivos de MedicinaArq. Med., 2003)
Keywords: article; data analysis; geographic distribution; geographic information system; health survey; information system; Statistical analysis

Cellulose phosphates as biomaterials. In vivo biocompatibility studies - Fricain, J.C.; Granja, P.L.; Barbosa, M.A.; De Jéso, B.; Barthe, N.; Baquey, C. (BiomaterialsBiomaterials, 2002)
Femoral implantation of regenerated cellulose hydrogels revealed their biocompatibility, but a complete osseointegration could not be observed. Phosphorylation was therefore envisaged as the means to enhance cellulose bioactivity. In vitro studies showed that regenerated cellulose hydrogels promote bone cells attachment and proliferation but do not mineralize in acellular simulated physiological conditions. On the contrary, phosphorylated cellulose has shown an opposite behavior, by inducing the formation of a calcium phosphate layer in simulated physiological conditions, but behaving as a poor substrate for bone cells attachment and proliferation. In order to investigate the in vivo behavior of these materials, and assess the influence of mineralization induction ability vs. bone cells compatibility, unmodified and phosphorylated cellulose hydrogels were implanted in rabbits for a maximum period of 6 months and bone regeneration was investigated. Despite the difficulties arising from the retraction of cellulose hydrogels upon dehydration during the preparation of retrieved implants, histological observations showed no inflammatory response after implantation, with bone intra-spongious regeneration of cells and the integration of the unmodified as well as the phosphorylated cellulose implants. After a maximum implantation period of 6 months, histological observations, histomorphometry and the measurement of the amount of 45Ca incorporated in the surrounding tissue indicated a slightly better osseointegration of phosphorylated cellulose, although no significant differences between the two materials were found. © 2001 Elsevier Science Ltd. All rights reserved.
Keywords: animal experiment; Animal implantation; animal tissue; Animalia; Animals; article; Biocompatibility; Biocompatible Materials; biomaterial; Biomaterials; Bone; bone cell; bone mineralization; Bone Regeneration; Calcium; calcium 45; Calcium Compounds; calcium phosphate; Calcium Radioisotopes; cell adhesion; cell proliferation; Cells; Cellulose; Cellulose phosphate; Chemical modification; controlled study; Dehydration; histology; hydrogel; Hydrogels; implant; in vivo study; Inflammation; materials testing; Microscopy, Electron, Scanning; morphometrics; nonhuman; Oryctolagus cuniculus; Osseointegration; Phosphates; Phosphorylation; priority journal; Prostheses and Implants; rabbit; Rabbits; Regenerated cellulose hydrogels

Densification route and mechanical properties of Si 3N 4-bioglass biocomposites - Amaral, M.; Lopes, M.A.; Silva, R.F.; Santos, J.D. (BiomaterialsBiomaterials, 2002)
The processing route and the final microstructural and mechanical characteristics of a novel biomaterial composite are described. This new material is composed of 70 wt% Si 3N 4 ceramic phase and 30 wt% bioglass, the later performing as a liquid sintering aid system and simultaneously providing bioactivity characteristics to the composite. The conditions for fabrication of an almost fully dense material (∼98% of relative density) were pursued. Optimised parameters were 1350°C-40min-30 MPa by hot-pressing technique. The very fast densification rate of the process avoided the crystallisation of the bioglass intergranular phase and therefore its intrinsic properties were maintained. Also, the large amount of glassy phase assured the densification by liquid phase assisted grain rearrangement without Si 3N 4 phase transformation. The final mechanical properties of the Si 3N 4-bioglass were as follows: fracture toughness, K IC = 4.4 MPa m 1/2; Vickers hardness, H V = 10.3 GPa; Young's modulus, E = 197 GPa; bending strength, σ R = 383 MPa; Weibull modulus, m = 8.3. These values provide an attractive set of properties among other bioactive materials, namely by upgrading the main drawback of bioceramics and bioglasses for high-load medical applications, which is the lack of satisfactory fracture toughness. © 2001 Elsevier Science Ltd. All rights reserved.
Keywords: 3N; 4-bioglass composites; article; Bending strength; Biocompatible Materials; biomaterial; Biomaterial composites; Biomaterials; Ceramic materials; ceramics; Composite Resins; Crystallization; Densification; Densification behaviour; density; Elastic moduli; Fracture toughness; glass; hardness; heat; Hot pressing; Hot-pressing; Kinetics; Mechanical properties; phase transition; Phase transitions; priority journal; Si; Silicon compounds; silicon derivative; Sintering; strength; Stress, Mechanical; technique; Thermodynamics; Vickers hardness testing; X-Ray Diffraction; young modulus

Electrochemical and microstructural studies of tantalum and its oxide films for biomedical applications in endovascular surgery - Silva, R.A.; Walls, M.; Rondot, B.; Da Cunha Belo, M.; Guidoin, R. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2002)
The most popular coronary stents are made of 316L stainless steel and self-expandable Nitinol. Nevertheless, Ta has already been used to make stents for endovascular surgery and may constitute a good alternative to the other materials because of its higher corrosion resistance and radio-opacity property, which may facilitate the follow-up of stent catheterization. The characterization of Ta and its natural passive oxide films has been performed in a 0.15M NaCl solution (simulated body fluid - SBF) using anodic polarizations, electrochemical impedance spectroscopy and photoelectrochemical techniques. Changes in microstructure have been observed by atomic force microscopy (AFM). Polarization curves show the existence of a current density increase between 1.40 and 1.80V. Bode complex plots show that some perturbation of the film occurred in this potential interval which may be associated with a decrease in polarization resistance, Rp, indicating that the film may be less resistant to corrosive attack. Mott-Schottky capacity measurements show that the density of donors, Nd, varies with polarization. The optical band gap, E g, which is equal to 4.1 eV did not show variations in our experiments. The localized formation on the electrode surface, in the above potential interval of a Ta compound (possibly an oxide-hydroxide) was observed by AFM, and this may explain the appearance of the current density peak and capacity behavior at those potentials. © 2002 Kluwer Academic Publishers.
Keywords: article; Atomic force microscopy; body fluid; coronary stent; Corrosion; Corrosion resistance; Current density; Electric Potential; electrochemical analysis; Electrochemical impedance spectroscopy; electrochemistry; electrode; endovascular surgery; Energy gap; film; heart catheterization; hydroxide; Materials science; metal oxide; Metallic films; Microstructure; nitinol; optical density; Oxide films; Polarization; priority journal; simulation; sodium chloride; Stainless steel; structure analysis; Surgery; Tantalum; Tantalum compounds; tantalum oxide; unclassified drug

Mathematical model for educational simulation of the oxygen delivery to the fetus - Sá Couto, P.M.; van Meurs, W.L.; Bernardes, J.F.; Marques De Sá, J.P.; Goodwin, J.A. (Control Engineering PracticeControl Eng. Pract., 2002)
Critical situations in obstetrics and anesthesia of the pregnant woman are rare and associated with a high risk to the woman and fetus involved. Therefore, simulation is a valuable tool in teaching the diagnostic and therapeutic skills in this context. We derive a mathematical model for the oxygen supply to the fetus that was specifically designed for educational simulations. The model reflects the hemodynamics and the oxygen transport. Parameter values for human patients are derived from the literature data. We validate the response of the model, with parameters reflecting the fetal lamb, to various reductions of the uterine and umbilical blood flow. © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Anesthesiology; Blood; Computer simulation; control; Diagnosis; education; Fetal monitoring; fetus; hemodynamics; mathematical model; Mathematical models; medical application; Obstetrics; oxygen; Oxygen supply; simulator; Therapeutic skills

A novel urethane containing copolymer as a surface modification additive for blood contact materials - Ji, J.; Barbosa, M.A.; Feng, L.; Shen, J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2002)
Surface modification to develop a biomolecules-presenting surface is of interest, both from a scientific and an industrial point of view. In this research, a penta-block-coupling polymer of warfarin-PEO-MDI-PEO-warfarin was specially designed as the surface modifying additive (SMA). The warfarin-modified polyurethane surfaces were then prepared by dip-coating method. Attenuated total reflection fourier transform infra-red (ATR-FTIR) spectra revealed that the urethane segments in the SMA could penetrate into the hard block of segmented polyurethane (SPU) via intermolecular hydrogen bonds. The X-ray photoelectron spectroscopy (XPS) results indicated that the intermolecular hydrogen bonds were strong enough to form stable warfarin-PEO composite surfaces in an aqueous environment. Fibrinogen and albumin adsorption onto unmodified and SMA-modified SPU was investigated by the 125l-labeled method. The surface for attracting and reversibly binding albumin, which was proved to suppress the platelet adhesion and prolong the clotting time, has been developed by the simple coating of the novel SMA in SPU. © 2002 Kluwer Academic Publishers.
Keywords: Adhesion; Adsorption; Albumin; article; Attenuation; biomaterial; Block copolymers; Blood; blood clotting time; Chemical modification; Coatings; copolymer; fibrinogen; Fourier transform infrared spectroscopy; human; human cell; hydrogen bond; Hydrogen bonds; infrared spectroscopy; iodine 125; material coating; Polyurethanes; priority journal; Surface modifying additives (SMA); surface property; Surface treatment; synthesis; thrombocyte adhesion; urethan; warfarin; X ray photoelectron spectroscopy

Porous glass reinforced hydroxyapatite materials produced with different organic additives - Prado da Silva, M.H.; Lemos, A.F.; Gibson, I.R.; Ferreira, J.M.F.; Santos, J.D. (Journal of Non-Crystalline SolidsJ Non Cryst Solids, 2002)
In the present study three different organic additives were used to produce porous structures of a CaO-P 2O 5 glass reinforced hydroxyapatite potato starch, almond crust and wax spheres. The produced samples were analysed by scanning electron microscopy, X-ray diffraction with Rietveld refinement, differential thermal analysis and mercury porosimetry. The techniques used in this study enabled the production of glass reinforced hydroxyapatite samples with various pore diameters. Two different techniques were used to produce porous glass reinforced hydroxyapatite samples: a dry method using wax spheres as pore formers and a wet method in alcoholic suspension, where almond crust and potato starch were used as pore formers. The final microstructure consists of hydroxyapatite, α-tricalcium phosphate and β-tricalcium phosphate. X-ray diffraction and scanning electron microscopy analysis revealed different percentages of phases when comparing dense and porous glass reinforced hydroxyapatite specimens. These hard materials are intended to be used as bone defect fillers. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: Additives; Differential thermal analysis; Fillers; glass; hydroxyapatite; Microstructure; Porosimeters; Porous glasses; Porous materials; Scanning electron microscopy; Suspensions (fluids); X ray diffraction analysis

Preparation of albumin preferential surfaces on poly(vinyl chloride) membranes via surface self-segregation - Ji, A.; Feng, L.; Shen, J.; Barbosa, M.A. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 2002)
Poly(vinyl chlorides)-graft-[w-stearyl-poly(ethylene oxide)] (PVC-g-SPEO), which has a poly(vinyl chloride) (PVC) backbone, poly(ethylene oxide) (PEO) side chain, and stearyl end groups, has been synthesized. Self-organizing blends of the amphiphilic comb polymer in poly-(vinyl chlorides) have been examined as a means to create albumin preferential surfaces on polymer films. X-ray photoelectron spectroscopy (XPS) analysis indicates substantial surface segregation of the PVC-g-SPEO. A surface concentration of 59.9 EO wt % is achieved by the solution casting and heat treatment of a film with a bulk concentration of only 3.78 EO wt %. In the aqueous environment, the surface rearrangement of PVC-g-SPEO/PVC blend film is limited and presents a high interfacial energy and high depolar component of interfacial energy due to the "tail-like" SPEO side chain. Protein adsorption tests confirm that PVC-g-SPEO/PVC blend films absorb high levels of albumin and dramatically resist fibrinogen adsorption. Surfaces to attract and reversibly bind albumin, which might diminish the occurrence of thrombosis, inflammation, and infection, are developed by self-organizing blends of the amphiphilic comb polymer in poly(vinyl chlorides). © 2002 Wiley Periodicals, Inc.
Keywords: Adsorption; Albumin; Amphiphilic copolymer; amphophile; aqueous solution; article; artificial membrane; Biocompatible Materials; cell separation; cell surface; chemical binding; combinatorial chemistry; concentration response; conference paper; dimerization; energy resource; film; human; Humans; infection; Inflammation; Inflammations; macrogol; macrogol derivative; membrane structure; Membranes, Artificial; metabolism; Plastic films; Polyethylene Glycols; polymer; Polymeric membranes; Polyvinyl Chloride; Polyvinyl chlorides; polyvinylchloride; protein binding; Serum Albumin; Stearates; stearic acid derivative; stearyl poly(ethylene oxide); Surface modification; Surface Properties; surface property; Surface segregation; Synthesis (chemical); thrombosis; X ray analysis; X ray photoelectron spectroscopy

Production of porous biomaterials based on glass-reinforced hydroxyapatite composites - Prado da Silva, M.H.; Lemos, A.F.; Ferreira, J.M.F.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2002)
In this study, porous GR-HA composites were produced using a calcium-phosphate glass with the composition, in mol%, 75P 2O 5-15CaO-10CaF 2. The composites were obtained by wet mixing 4.0% (w/w) of the glasses with hydroxyapatite (HA) powder (batch P120) (Plasma Biotal; Tideswell, U.K.), pressing and sintering. Two different organic additives were used as pore formers: potato starch and almond crust. This processing route was effective in producing a homogeneous microstructure of equiaxed grains. The bulk density of the samples decreased with the volume fraction increase in the content of pore formers. Scanning electron microscopy and mercury porosimetry analyses showed to be complementary techniques in characterising the pore size and distribution.
Keywords: Biomaterials; Composite materials; glass; Glass-reinforced hydroxyapatite composites; GR-HA Composites; hydroxyapatite; Macroporous Bioceramics; Mercury (metal); Microstructure; Organic Additives; Pore size; Porous materials; Powders; Pressing (forming); Scanning electron microscopy; Sintering; Starch

Real-time implementation of an optical flow algorithm - Correia, M.V.; Campilho, A.C. (Proceedings - International Conference on Pattern RecognitionProc. Int. Conf. Pattern Recognit., 2002)
This paper presents the implementation of an optical flow algorithm on a pipeline image processor. The overall optical flow computation method is presented and evaluated on a common set of image sequences. Results are compared to other implementations according to two different error measures. Due to its deterministic architecture, this implementation achieves very low computation delays that allow it to operate at standard video frame-rate and resolutions. It compares favorably to recent implementations in parallel hardware. © 2002 IEEE.
Keywords: Algorithms; Computational methods; Image analysis; Image processors; Image sequences; Optical flow algorithm; Optical flows; Real time systems; Video frame-rate; Video signal processing

Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells - Amaral, M.; Costa, M.A.; Lopes, M.A.; Silva, R.F.; Santos, J.D.; Fernandes, M.H. (BiomaterialsBiomaterials, 2002)
The in vitro osteocompatibility of a novel Si 3N 4-bioglass composite (70-30% weight proportion) with improved mechanical properties (fracture toughness=4.4MPam 1/2; bending strength=383±47MPa) is reported. Immersion of the composite samples in culture medium (30min to 7 days) resulted in rapid protein adsorption to the surface and, also, dissolution of the intergranular phase of bioglass (time-dependent process) with the formation of different size cavities. "As-received" and pre-treated material samples presented a similar behaviour concerning the proliferation of MG63 osteoblast-like cells, evaluated during a 5-day culture period. Seeded materials showed a higher cell growth rate as compared to cultures performed on the standard plastic culture plates. To assess the osteogenic potential of the composite, "as-received" material samples were seeded with human bone marrow cells and cultured for 35 days in experimental conditions that favour the development of the osteoblastic phenotype. The cell adhesion process was similar to that observed in control cultures. Cells successfully adapted to the irregularities of the surface and were able to grow towards inside the cavities; in addition, osteogenic differentiation occurred with the formation of abundant cell-mediated mineralised deposits. Results suggest that this Si 3N 4-bioglass composite seems to be a promising candidate for high-stress medical applications. © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: 3N; 4-bioglass composite; Adhesion; Adsorption; alkaline phosphatase; article; Biocompatibility; Bioglass; Biomaterials; bone marrow cell; Bone Marrow Cells; Calcium; cell adhesion; Cell Culture Techniques; cell differentiation; Cell Division; cell growth; cell proliferation; composite material; controlled study; culture medium; Dissolution; glass; Growth kinetics; human; Human bone marrow cells; human cell; Humans; immersion; in vitro study; Mechanical properties; MG63 osteoblast-like cells; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; Osteocompatibility; Osteogenic differentiation; phenotype; phosphorus; priority journal; Proteins; rigidity; Si; Silicon compounds; silicon derivative; surface property; tensile strength; Time Factors

Silicon and iron levels in tissues of animals treated with a "ferrimagnetic ceramic" with oncotherapeutic potential (anti-tumor) value - Almeida, T.; Soares, M.E.; Cavalheiro, J.; Bastos, M.D.L. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 2002)
The stability in a biological environment of an injectable cement with oncotherapeutic potential - consisting of a glass powder of SiO 2 (35.6%), CaO (42.4%), P 2O 5 (17%), Na 2O (5%) and 30% of its weight of Fe 3O 4 dissolved in (NH 4) 2HPO 4 plus NH 4H 2PO 4 - was evaluated referring to the release of silicon and iron. The experimental model was the rat, and organs (liver, kidney, spleen, lung, heart, and brain) of the implanted and control animals were collected for quantification of these elements by electrothermal atomization atomic absorption spectrometry methods. In most of the analysed organs no significant difference in the contents of silicon and iron between the implanted and the control animals was found.
Keywords: animal model; animal tissue; Animalia; Animals; article; atomic absorption spectrometry; Biocompatible Materials; calcium oxide; cancer therapy; cement; ceramics; controlled study; experimental model; Ferrimagnetic ceramic; heat; Humans; implant; Iron; Magnetics; materials testing; Neoplasms; nonhuman; Oncotherapy; phosphorus pentoxide; powder; priority journal; Prostheses and Implants; rat; Rats; Reproducibility of Results; Silicon; silicon dioxide; tissue distribution; Tissue Extracts

Soluble silk-like organic matrix in the nacreous layer of the bivalve Pinctada maxima: A new insight in the biomineralization field - Pereira-Mouriès, L.; Almeida, M.-J.; Ribeiro, C.; Peduzzi, J.; Barthélemy, M.; Milet, C.; Lopez, E. (European Journal of BiochemistryEur. J. Biochem., 2002)
Nacre organic matrix has been conventionally classified as both 'water-soluble' and 'water-insoluble', based on its solubility in aqueous solutions after decalcification with acid or EDTA. Some characteristics (aspartic acid-rich, silk-fibroin-like content) were specifically attributed to either one or the other. The comparative study on the technique of extraction (extraction with water alone vs. demineralization with EDTA) presented here, seems to reveal that this generally accepted classification may need to be reconsidered. Actually, the nondecalcified soluble organic matrix, extracted in ultra-pure water, displays many of the characteristics of what until now has been called 'insoluble matrix'. We present the results obtained on this extract and on a conventional EDTA-soluble matrix, with various characterization methods: fractionation by size-exclusion and anion-exchange HPLC, amino acid analysis, glycosaminoglycan and calcium quantification, SDS/PAGE and FTIR spectroscopy. We propose that the model for the interlamellar matrix sheets of nacre given by Nakahara [In: Biomineralization and Biological Metal Accumulation, Westbroek, P. & deJong, E.W., eds, (1983) pp. 225-230. Reidel, Dordrecht, Holland] and Weiner and Traub [Phil. Trans. R. Soc. Lond. B (1984) 304, 425-434] may no longer be valid. The most recent model, proposed by Levi-Kalisman et al. [J. Struct. Biol. (2001) 135, 8-17], seemed to be more in accordance with our findings.
Keywords: amino acid analysis; Amino acids; Animals; anion exchange chromatography; article; Biochemistry; biomineralization; bivalve; Bivalvia; Calcium; Chemical Fractionation; Chromatography, High Pressure Liquid; controlled study; demineralization; edetic acid; EDTA-soluble matrix; Electrophoresis, Polyacrylamide Gel; Extracellular Matrix Proteins; extraction; fractionation; gel permeation chromatography; glycosaminoglycan; Glycosaminoglycans; High performance liquid chromatography; hydrophobicity; infrared spectroscopy; Insect Proteins; model; Nacre; nonhuman; Ostreidae; Pinctada; Pinctada maxima; polyacrylamide gel electrophoresis; priority journal; Silk; Silk-fibroin-like-proteins; Solubility; Spectroscopy, Fourier Transform Infrared; Undecalcified soluble matrix; Water

Structural analysis of Si-substituted hydroxyapatite: Zeta potential and X-ray photoelectron spectroscopy - Botelho, C.M.; Lopes, M.A.; Gibson, I.R.; Best, S.M.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2002)
The aim of this study was to determine the effect of the incorporation of silicon on the surface charge of hydroxyapatite (HA) and to assess surface structural changes of HA and Si-HA induced by dissolution in both static and dynamic systems. X-ray photoelectron spectroscopy (XPS) analysis showed that SiO 4 4- groups were substituted for PO 4 3- groups in the silicon-hydroxyapatite (Si-HA) lattice according to a previously proposed substitution mechanism without the formation of other crystalline phases, such as tricalcium phosphate or calcium oxide. The substituted silicon induced a decrease in the net surface charge and the isoelectric point of HA as determined by zeta potential (ZP) measurements. At physiological pH = 7.4 the surface charge of Si-HA was significantly lowered compared to unmodified HA, i.e. -50 ±5 to - 71 ± 5 eV, caused by the presence of silicate groups in the HA lattice, which may account for a faster in vitro apatite formation using SBF testing. XPS results indicated that silicon seems to be preferentially leached out from Si-HA surface compared to other ionic species after dissolution studies in tris-buffer using a dynamic system. © 2002 Kluwer Academic Publishers.
Keywords: calcium oxide; calcium phosphate; Chemical modification; conference paper; crystal structure; Dissolution; Electric Potential; electricity; hydroxyapatite; in vitro study; isoelectric point; Lime; molecular dynamics; pH; pH measurement; phase transition; phosphate; Phosphorus Compounds; priority journal; reaction analysis; Silicon; Silicon compounds; silicon derivative; structure analysis; surface property; X ray photoelectron spectroscopy; Zeta potential

Wettability and surface charge of Si 3N 4-bioglass composites in contact with simulated physiological liquids - Amaral, M.; Lopes, M.A.; Santos, J.D.; Silva, R.F. (BiomaterialsBiomaterials, 2002)
Wettability and surface charge studies were performed on a novel Si 3N 4-30wt% bioglass biocomposite. Contact angle and surface tension variation with time were determined at 25°C, respectively, by the sessile and pendant drop techniques, for distinct testing liquids: water, diiodomethane, simulated body fluid (SBF) and bovine serum albumin (BSA) dissolved in SBF solution. This biocomposite revealed a hydrophilic character (θ=26.6±2.0°) and a surface tension value (66.6mJm
Keywords: 3N; 4-bioglass composites; Adsorption; aqueous solution; article; Biocomposites; Biomaterials; body fluid; Body fluids; Bovinae; bovine serum albumin; cation; Cattle; ceramics; chemistry; conformation; Conformations; Contact angle; electrochemistry; enthalpy; entropy; glass; Glass ceramics; Hydrogen-Ion Concentration; hydrophilicity; liquid; methyl iodide; methylene iodide; pH; Physiological models; priority journal; Serum Albumin; Serum Albumin, Bovine; Si; Silicon compounds; silicon derivative; Silicon nitride; simulation; Support, Non-U.S. Gov't; Surface charge; Surface chemistry; Surface Properties; surface property; Surface tension; temperature; time; unclassified drug; Water; wettability; Wetting; Zeta potential

Adsorption and release studies of sodium ampicillin from hydroxyapatite and glass-reinforced hydroxyapatite composites - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J.; Gibson, I.R.; Knowles, J.C. (BiomaterialsBiomaterials, 2001)
As a potential therapy for periodontitis, sodium ampicillin, a broad spectrum antibiotic, was adsorbed onto hydroxyapatite (HA) and glass-reinforced hydroxyaptite (GR-HA) composites, and was subsequently released in vitro. The sodium ampicillin, was adsorbed more on HA compared to the GR-HA composites. X-ray diffraction (XRD) and Rietveld analysis were used to identify and quantify the levels of HA and β-tricalcium phosphate (β-TCP) in the microstructure of the GR-HA composites. Lattice parameters changes were observed for the β-TCP phase dependant on the amount of glass added. The release kinetics were shown to be divided into three stages, the first of which where a large amount of sodium ampicillin is released, followed by a slower release rate and then a final stage where the release amount approaches zero, until no more sodium ampicillin was present. X-ray photoeletron spectroscopy (XPS) studies were carried out in order to ensure that the entire antibiotic adsorbed onto the materials had been released. These kinetics studies have indicated the possibility of using these materials as possible carriers for drug delivery. Copyright © 2001 Elsevier Science Ltd.
Keywords: Adsorption; ampicillin; Antibiotics; article; calcium phosphate; composite material; controlled study; drug adsorption; Drug delivery; drug delivery system; Drug release; Durapatite; glass; Glass-reinforced hydroxyapatite; hydroxyapatite; Kinetics; Microstructure; Penicillins; periodontitis; priority journal; Reinforcement; Rietveld analysis; roentgen spectroscopy; Sodium ampicillin; Sodium compounds; structure analysis; unclassified drug; X ray diffraction; X ray diffraction analysis; X ray photoelectron spectroscopy; X-Ray Diffraction

Affinity of hydroxyapatite to metal cations - a study on the composition and structure of phosphates formed in the presence of titanium and aluminum - Ribeiro, C.C.; Barbosa, M.A. (Key Engineering MaterialsKey Eng Mat, 2001)
The purpose of this study was to contribute to the understanding of the effect of titanium, aluminium and titanium/aluminium on the Hap structure and to investigate if a synergistic effect between the two cations exists. The effect of the metal ion concentration was studied. The solids were analysed by X-ray diffraction, Fourier transform infrared spectroscopy, FT-Raman spectroscopy and energy dispersive X-ray analysis.
Keywords: Aluminum; Energy dispersive spectroscopy; Fourier transform infrared spectroscopy; Hap structure; hydroxyapatite; Positive ions; Raman spectroscopy; Structure (composition); Synergistic effect; Titanium; X ray diffraction analysis

CaO-P 2O 5 glass ceramics containing bioactive phases: crystallisation and in vitro bioactivity studies - Zhang, Y.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2001)
CaO-P 2O 5 glass ceramics were prepared using a two-step heat treatment of nucleation and crystal growth using TiO 2 and Na 2O as nucleating agents. X-ray diffraction analysis demonstrated that bioactive and bioresorbable crystalline phases were precipitated in the microstructure, depending upon the relative content of the additives and of the CaO/P 2O 5 ratio of the glass. Ca 2P 2O 7 (β-DCP) was the main crystalline phase however β-Ca 3(PO 4) 2 (β-TCP), could also be formed by increasing the content of TiO 2 and the CaO/P 2O 5 ratio. Na and Ti-containing phases, CaTi 4(PO 4) 6, and/or NaTi 2(PO 4) 3, could also be assigned in the XRD spectra. In vitro testing in simulated body fluid (SBF) has proved the in vitro bioactivity of these glass ceramics with the formation of Ca-deficient apatite crystals, as demonstrated by Scanning Electron Microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) analyses.
Keywords: Bioactivity; Biomaterials; Ceramic materials; Crystal growth; Crystal microstructure; Crystalline materials; Crystalline phase; Crystallization; glass; Lime; Nucleating agents; Nucleation; Phosphates; Scanning electron microscopy; Simulated body fluid; X ray diffraction analysis; X ray photoelectron spectroscopy

Cellulose phosphates as biomaterials. I. Synthesis and characterization of highly phosphorylated cellulose gels - Granja, P.L.; Pouysgu, L.; Ptraud, M.; De Jso, B.; Baquey, C.; Barbosa, M.A. (Journal of Applied Polymer ScienceJ. Appl. Polym. Sci., 2001)
The present study concerns the investigation of a material expected to be biocompatible and able to promote bone regeneration. For this purpose, cellulose was chemically modified by phosphorylation. Once implanted, phosphorylated cellulose could promote the formation of calcium phosphates, thus having closer resemblance to bone functionality. In a previous investigation, the obtention and the preliminary characterization of cellulose phosphate gels were reported. In the present study, the synthesis by the H 3PO 4/P 2O 5/Et 3PO 4/hexanol method was optimized in terms of reaction parameters. The structure of materials was investigated by FTIR, Raman, and solid-state 31P- and 13C-NMR spectroscopic studies, and X-ray diffraction. Water swelling and stability to sterilization by gamma-radiation were also assessed. It was demonstrated that the present method allows highly phosphorylated cellulose derivatives to be obtained. Cellulose triphosphates gels are described here for the first time. Products obtained were poorly crystallized monoesters, apparently not significantly affected by gamma sterilization and showed a high water swelling capability. Chemical bonding was confirmed by FTIR, Raman, and both 31P- and 13C-NMR spectroscopies. It was also shown that the H 3PO 4/P 2O 5/Et 3PO 4/hexanol method provides a versatile and interesting alternative route to some of the more widely used techniques for the phosphorylation of cellulose. © 2001 John Wiley & Sons, Inc. J. Appl. Polym. Sci.
Keywords: 13C-NMR; 2O; 3PO; 4/hexanol method; 4/P; 5/Et; Biomaterials; Cellulose derivatives; Cellulose gels; Cellulose triphosphates; Chemical bonds; Fourier transform infrared spectroscopy; Gels; H; medical textile; Nuclear magnetic resonance spectroscopy; Phosphorylation; Raman scattering; Sterilizers; Synthesis (chemical); X ray diffraction analysis

Cellulose phosphates as biomaterials. II. Surface chemical modification of regenerated cellulose hydrogels - Granja, P.L.; Pouysgu, L.; Ptraud, M.; De Jso, B.; Baquey, C.; Barbosa, M.A. (Journal of Applied Polymer ScienceJ. Appl. Polym. Sci., 2001)
Cellulose regenerated by the viscose process was previously investigated as an implantable material in orthopedic surgery. It was envisaged to take advantage not only of its good matching with mechanical properties of bone but also of its hydroexpansivity, therefore allowing a satisfactory fixation to hard tissue. Both the osteoconduction and the lack of ostcoinduction of this material were demonstrated. Grafting of phosphate groups was then envisaged as the means to render cellulose more suitable for orthopedic applications by enhancing its bioactivity. In the present work, the previously optimized phosphorylation reaction was successfully adapted to the surface modification of regenerated cellulose. Modified materials were characterized by XPS, FTIR, and 31P MAS NMR spectroscopic studies, and contact angle measurements, revealing the chemical bond between phosphate groups and cellulose, as well as the hydrophilic nature of phosphorylated materials, which increases with increasing phosphate contents. Water swelling and resistance to gamma sterilization were assessed as well, showing that phosphorylated materials swell considerably in water and were not affected when sterilization was carried out under a nitrogen atmosphere. The increase in surface roughness attributed to chemical modification was demonstrated through laser rugosimetry measurements. © 2001 John Wiley & Sons, Inc. J. Appl. Polym. Sci.
Keywords: 2O; 3PO; 4/hexanol method; 4/P; 5/Et; Biomaterials; Cellulose derivatives; Cellulose phosphates; Chemical bonds; Chemical modification; Energy dispersive spectroscopy; Fourier transform infrared spectroscopy; H; Hydrogels; Phosphorylation; Regenerated cellulose hydrogels; Sterilization (cleaning); Surface modification; Surface roughness; X ray photoelectron spectroscopy

On combining classifiers using sum and product rules - Alexandre, L.A.; Campilho, A.C.; Kamel, M. (Pattern Recognition LettersPattern Recogn. Lett., 2001)
This paper presents a comparative study of the performance of arithmetic and geometric means as rules to combine multiple classifiers. For problems with two classes, we prove that these combination rules are equivalent when using two classifiers and the sum of the estimates of the a posteriori probabilities is equal to one. We also prove that the case of a two class problem and a combination of two classifiers is the only one where such equivalence occurs. We present experiments illustrating the equivalence of the rules under the above mentioned assumptions. © 2001 Elsevier Science B.V. All rights reserved.
Keywords: artificial neural network; Classification; Classifier fusion; Combinatorial mathematics; Combining classifiers; Equivalence classes; Estimation; K nearest-neighbours; Multiple classifiers; Neural networks; Pattern recognition; probability

Comparative effects of nacre water-soluble matrix and dexamethasone on the alkaline phosphatase activity of MRC-5 fibroblasts - Almeida, M.J.; Pereira, L.; Milet, C.; Haigle, J.; Barbosa, M.; Lopez, E. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 2001)
In this study we demonstrate, for the first time, that dexamethasone and BMP-2 stimulated alkaline phosphatase (ALP) activity in MRC-5 fibroblasts, a cell line derived from human fetal lung. Previously we reported that the water-soluble matrix (WSM) of nacre obtained from the inner shell layer of the oyster Pinctada maxima, promoted an increase in ALP activity that was dose-dependent. In this work, we show that the effect of WSM is also time-dependent. As a comparison, the effect of WSM was also tested in bone marrow stromal cells because marrow and other bone surface-derived osteoblast stem cells have the inherent direct potential for osteogenesis. WSM promotes cell proliferation and ALP activity when tested with bone marrow cells in concentrations between 135 and 540 μg protein/mL. The effect of WSM on ALP activity of bone marrow stromal cells is similar to that obtained by dexamethasone. These results imply that MRC-5 fibroblasts respond to differentiating factors that promote osteoblastic phenotype in bone-derived cell cultures. © 2001 John Wiley & Sons, Inc.
Keywords: alkaline phosphatase; Animals; article; Biomedical engineering; BMP-2; Bone; bone development; bone marrow; Bone Marrow Cells; Bone morphogenetic proteins; Cell culture; Cell Line; cell proliferation; Cells; concentration response; dexamethasone; differentiation inducing factor; dose response; Dose-Response Relationship, Drug; enzyme activity; fibroblast; Fibroblasts; Glucocorticoids; human; human cell; Humans; male; MRC-5 fibroblasts; Nacre; natural product; osteoblast; Ostreidae; oyster; phenotype; Proteins; Pulmonary diseases; Rats; Rats, Wistar; Solubility; stroma cell; time; Time Factors; Transforming Growth Factor beta; unclassified drug; Water; Water-soluble matrix

Corrosion behaviour of titanium in biofluids containing H 2O 2 studied by electrochemical impedance spectroscopy - Fonseca, C.; Barbosa, M.A. (Corrosion ScienceCorros Sci, 2001)
This work aims at studying the electrochemical behaviour of titanium in the presence of an artificial biofluid containing H 2O 2, mimicing the situation, where the metal is implanted in the human body and hydrogen peroxide is generated by an inflammatory reaction. A phosphate buffered saline (PBS) solution and two PBS/H 2O 2 solutions containing 50 and 150 mM of H 2O 2 were used to simulate the body fluids. The behaviour of the metal was monitored as a function of time by electrochemical impedance spectroscopy (EIS) for three weeks. After one week, the PBS/H 2O 2 solutions were replaced by fresh PBS solutions in order to simulate the end of the inflammatory process and recovery of the system. All the experiments were carried out at a constant temperature of 37 °C. From the simulation of the experimental EIS spectra, it was concluded that the corrosion resistance of titanium is strongly affected by the presence of H 2O 2 and when the peroxide is removed, the metal displays a sharp resistance increase. Furthermore, the oxides formed in H 2O 2 are rougher and display higher ionic conductivities than the oxides formed in the absence of peroxide. The study was complemented with potentiostatic experiments and scanning electron microscopy observation of the metal surfaces.
Keywords: Biomaterials; Body fluids; Corrosion resistance; Electrochemical corrosion; electrochemical process; hydrogen peroxide; impedance technique; Implants (surgical); Phosphate buffered saline; Solutions; Spectroscopy; Titanium

Effect of chemical composition on hydrophobicity and zeta potential of plasma sprayed HA/CaO-P 2O 5 glass coatings - Ferraz, M.P.; Monteiro, F.J.; Serro, A.P.; Saramago, B.; Gibson, I.R.; Santos, J.D. (BiomaterialsBiomaterials, 2001)
Multilayered plasma sprayed coatings on the surface of Ti-6Al-4V alloys have been prepared, which were composed of an underlayer of HA and a surface layer of a CaO-P 2O 5 glass-HA composite, with 2 or 4 wt% of glass. Contact angle and surface tension variation with time, for both water and a protein solution, were determined by the sessile and pendent drop methods respectively using the ADSA-P software. Wettability studies showed that hydrophobicity of the coatings increase with the glass addition. The work of adhesion of albumin was also altered in a controlled manner by the addition of the CaO-P 2O 5 glass, being lower on the composite coatings than on HA. Zeta potential (ZP) results showed that composite coatings presented a higher net negative charge than HA coatings and that ZP values were also influenced by the content of the glass. This study demonstrated that the surface properties of those coatings may be modified by the addition of CaO-P 2O 5 glass. © 2001 Published by Elsevier Science Ltd.
Keywords: Adhesion; alloy; analytic method; article; bovine serum albumin; Calcium Compounds; calcium oxide; chemical composition; Chemical modification; Coatings; Composition; computer program; Contact angle; Durapatite; glass; hydrophobicity; hydroxyapatite; Hydroxyapatite glass composites; oxide; Oxides; pentoxide; Phosphorus Compounds; priority journal; protein; Serum Albumin, Bovine; Sprayed coatings; Surface charge; Surface Properties; Surface tension; Surface tension zeta potential; time; unclassified drug; Water; wettability; Wetting; X-Ray Diffraction; Zeta potential

HA and double-layer HA-P 2O 5/CaO glass coatings: Influence of chemical composition on human bone marrow cells osteoblastic behavior - Ferraz, M.P.; Fernandes, M.H.; Santos, J.D.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2001)
Human osteoblastic bone marrow derived cells were cultured for 28 days onto the surface of a glass reinforced hydroxyapatite (HA) composite and a commercial type HA plasma sprayed coatings, both in the "as-received" condition and after an immersion treatment with culture medium during 21 days. Cell proliferation and differentiation were analyzed as a function of the chemical composition of the coatings and the immersion treatment. Cell attachment, growth and differentiation of osteoblastic bone marrow cells seeded onto "as-received" plasma sprayed coatings were strongly affected by the time-dependent variation of the surface structure occurring during the first hours of culture. Initial interactions leading to higher amounts of adsorbed protein and zeta potential shifts towards negative charges appeared to result in surface structures with better biological performance. Cultures grown onto the pretreated coatings showed higher rate of cell proliferation and increased functional activity, as compared to those grown onto the corresponding "as-received" materials. However, the cell behavior was similar in the glass composite and HA coatings. The results showed that the glass composites present better characteristics for bone cell growth and function than HA. In addition, this work also provide evidence that the biological performance of the glass composites can be modulated and improved by manipulations in the chemical composition, namely in the content of glass added to HA. © 2001 Kluwer Academic Publishers.
Keywords: Adsorption; alkaline phosphatase; article; Biomedical engineering; Bone; bone marrow; bone marrow cell; Calcium; calcium oxide; cell adhesion; Cell culture; cell differentiation; cell growth; cell proliferation; chemical composition; Coatings; controlled study; culture medium; enzyme activity; glass; Growth kinetics; human; human cell; hydroxyapatite; immersion; osteoblast; oxygen; performance; phosphorus; priority journal; protein binding; protein content; Proteins; Scanning electron microscopy; Surface charge; surface property; time; X ray diffraction

Histological studies of double layer HA/CaO-P 2O 5 glass plasma sprayed coatings using Rabbit model - Ferraz, M.P.; Santos, J.D.; Afonso, A.; Vasconcelos, M.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2001)
The in vivo biological performance of a double layer HA/CaO-P 2O 5 glass and HA plasma sprayed coatings was assessed, using cylindrical implants that were placed in rabbits tibiae and histologically characterised after 2, 4, 8 and 16 weeks of implantation. For both types of coatings, long-term histological results indicated successful contact between implanted materials and bone, with organised new bone established at the interface. The main difference between the two coatings corresponded to the shorter implantation periods, where the composite coating induced faster osteointegration than HA coating. The faster formation of organised bone for composite coatings is discussed in terms of the presence of phase composition in the coatings structure.
Keywords: Bond strength (materials); Bone; Double layer coatings; hydroxyapatite; Implants (surgical); In vivo evaluation; Interfaces (materials); morphology; Phase composition; Phosphates; Plasma sprayed coatings; Rabbit model; Scanning electron microscopy; Sprayed coatings; X ray diffraction analysis

Microstructural characterization and in vitro apatite formation in CaO-P 2O 5-TiO 2-MgO-Na 2O glass-ceramics - Zhang, Y.; Santos, J.D. (Journal of the European Ceramic SocietyJ Eur Ceram Soc, 2001)
Bulk calcium phosphate glass and glass-ceramic with CaO/P 2O 5 molar ratio = 1.25 were prepared through introducing small amounts of Na 2O, MgO, and TiO 2 into the glass. Using XRD analysis, biocompatible β-Ca 2P 2O 7 (β-DCP) and more soluble Ca and Na-containing phases were clearly identified in the microstructure. In vitro bioactivity was assessed by immersion testing in SBF-simulated body fluid and apatite crystals were formed after 4 and 8 weeks of soaking. Porous microstructure was produced through dissolution of soluble phases and desirable porous structure may be achieved by controlling size and distribution of these phases and the leaching process. Therefore, this glass-ceramic is expected to be used as bone repair and regeneration implants and drug delivery carrier.
Keywords: Apatite; Bioactivity; Calcium phosphate glass; Ceramic materials; Crystal microstructure; Crystallization; dissociation; glass; Glass ceramics; Leaching; Lime; Magnesia; Phosphorus Compounds; Porous materials; Sodium compounds; Solubility; Titanium dioxide

Mineralization of regenerated cellulose hydrogels - Granja, P.L.; Ribeiro, C.C.; De Jéso, B.; Baquey, C.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2001)
Due to their high water swelling, regenerated cellulose hydrogels and sponges were pre-incubated in a Ca-containing solution, and their mineralization was investigated. Results obtained demonstrate that a simple pre-incubation treatment in a Ca containing solution can induce mineralization in materials with limited or no tendency to mineralize. The minerals formed had an apatitic carbonated and poorly crystalline structure, resembling carbonated hydroxyapatite found in bone mineral. The apatitic layer formed showed a relatively accelerated growth using this technique, exhibiting nodules in their macroscopic structure, which seem to indicate lateral growth. The porous structure of regenerated cellulose sponges was also homogeneously mineralized using this technique. © 2001 Kluwer Academic Publishers.
Keywords: Apatite; article; Bone; bone mineral; Calcification (biochemistry); Calcium; Carbon; Cellulose; crystal; hydrogel; Hydrogels; hydroxyapatite; Incubation; infrared spectroscopy; mineralization; porosity; priority journal; Scanning electron microscopy; surface property; Swelling; Water

Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits - Lopes, M.A.; Santos, J.D.; Monteiro, F.J.; Ohtsuki, C.; Osaka, A.; Kaneko, S.; Inoue, H. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 2001)
In vitro and in vivo bioactivity studies were performed to assess the biocompatibility of CaO-P 2O 5 glass-reinforced hydroxyapatite (GR-HA) composites. The ability to form an apatite layer by soaking in simulated body fluid (SBF) was examined and surfaces were characterized using FTIR reflection and thin-film X-ray diffraction analyses. Qualitative histology, histomorphometric measurements, and push-out testing were performed in a rabbit model for characterizing bone/implant bonding. Under the in vitro conditions using SBF, an apatite layer could not be formed on GR-HA composites within 8 weeks. Results of push-out testing showed bonding between the composites and bone, ranging from 130-145 N after 2 weeks of implantation. After the longest implantation period, 16 weeks, the GR-HA composite prepared with the higher content of CaO-P 2O 5 glass showed the highest bonding force, 606 ± 45 N, compared to 459 ± 30 N for sintered HA. Development of immature bone and modifications in the turnover of a more mature bone on the surface of GR-HA composites were similar to those on sintered HA. © 2000 John Wiley & Sons, Inc. In vitro and in vivo bioactivity studies were performed to assess the biocompatibility of CaO-P 2O 5 glass-reinforced hydroxyapatite (GR-HA) composites. The ability to form an apatite layer by soaking in simulated body fluid (SBF) was examined and surfaces were characterized using FTIR reflection and thin-film X-ray diffraction analyses. Qualitative histology, histomorphometric measurements, and push-out testing were performed in a rabbit model for characterizing bone/implant bonding. Under the in vitro conditions using SBF, an apatite layer could not be formed on GR-HA composites within 8 weeks. Results of push-out testing showed bonding between the composites and bone, ranging from 130-145 N after 2 weeks of implantation. After the longest implantation period, 16 weeks, the GR-HA composite prepared with the higher content of CaO-P 2O 5 glass showed the highest bonding force, 606 ± 45 N, compared to 459 ± 30 N for sintered HA. Development of immature bone and modifications in the turnover of a more mature bone on the surface of GR-HA composites were similar to those on sintered HA. © 2000 John Wiley & Sons, Inc.
Keywords: animal experiment; animal tissue; Animals; article; Biocompatibility; Body fluids; Bonding; Bone; Bone Substitutes; bone turnover; Ceramic materials; Composite Resins; Durapatite; Fiber reinforced materials; Fourier transform infrared spectroscopy; glass; Glass reinforced hydroxyapatite composites; Glass-reinforced hydroxyapatite composites; Histological studies; histology; Histomorphometric measurements; hydroxyapatite; implant; implantation; Implants (surgical); In vitro bioactivity; In vivo evaluation; Interfaces (materials); male; nonhuman; orthopedic equipment; ossification; Prosthesis Implantation; Push out testing; Push-out testing; rabbit; Rabbits; Spectroscopy, Fourier Transform Infrared; Stress, Mechanical; Surgical equipment; tibia; Time Factors; X ray diffraction; X ray diffraction analysis

Silicon nitride - bioglass composite for biomedical applications - Santos, J.D.; Amaral, M.; Oliveira, S.M.; Lopes, M.A.; Silva, R.F. (Key Engineering MaterialsKey Eng Mat, 2001)
This study aimed at preparing novel highly toughened bioactive ceramic composite composed of Si 3N 4 matrix and Bioglass using a hot pressing technique. Densification rate, hardness and fracture toughness of this novel composite were assessed as well as in vitro bioactivity using a simulated body fluid (SBF). A fracture toughness of 5.2±0.3 MPa.m. 1/2 was achieved for fully densified samples, which complies with K 1c value reported for cortical bone. This novel composite, which can be used in high load medical applications, seems to overcome the drawback of low fracture toughness presented by most currently available bioactive ceramics.
Keywords: Bioactive ceramic composite; Bioglass; Biomaterials; Body fluids; Bone; Ceramic matrix composites; cortical bone; Densification; Fracture toughness; Glass ceramics; Hot pressing; Medical applications; Silicon nitride; Simulated body fluid

Starch based copolymers as biomaterials in vivo biocompatibility study - Souillac, V.; Fricain, J.C.; Bareille, R.; Reis, R.L.; Chauveaux, D.; Baquey, C. (Key Engineering MaterialsKey Eng Mat, 2001)
This report is a preliminary study of a starch-based copolymer that was used as a bone substitute. The interest of this study was to evaluate the possibility of using a hydrophilic material as a bone substitute. We studied this copolymer alone, after phosphorylation, and after hydroxyapatite coating.
Keywords: Biocompatibility; Bone; Bone substitute; Copolymers; Ethanol; Ethylene; hydroxyapatite; Hydroxyapatite coating; Implants (surgical); orthopedics; Phosphates; phosphoric acid; Phosphorylation; Starch; Substitution reactions; Vinyl resins

Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin - Ji, J.; Feng, L.; Barbosa, M.A. (BiomaterialsBiomaterials, 2001)
An ideal surface for many biomedical applications would resist non-specific protein adsorption while at the same time triggering a specific biological pathway. Based on the approach of selectively binding albumin to free fatty acids, stearyl groups were immobilized onto poly(styrene) backbone via poly(ethylene oxide) side chains. X-ray photoelectron spectroscopy (XPS) analysis indicates substantial surface enrichment of the stearyl poly(ethylene oxide) (SPEO). In an aqueous environment, the surface rearrangement is limited, as proved by dynamic contact angle tests. The comb-like copolymer presents a special hydrophobic surface with high SPEO surface density, which may be due to the 'tail like' SPEO architecture at the copolymer/water interface. Protein adsorption tests confirm that the comb-like surfaces adsorb high levels of albumin and resist fibrinogen adsorption very significantly. The surfaces prepared in this research attract and reversibly bind albumin due to the synergistic action of the PEO chains and the stearyl end groups. Copyright © 2001 Elsevier Science Ltd.
Keywords: Adsorption; Albumin; Amphiphilic copolymer; article; Biocompatible Materials; Biomedical engineering; Catalyst selectivity; Cell immobilization; Contact angle; copolymer; Copolymers; density; Electron Probe Microanalysis; fibrinogen; Grafting (chemical); Humans; hydrophobicity; Ligands; macrogol; macrogol derivative; materials testing; Polyethylene Glycols; Polystyrenes; priority journal; Protein adsorption; protein binding; Proteins; roentgen spectroscopy; Serum Albumin; Stearates; Stearyl end groups; Surface Properties; surface property; Ultraviolet spectroscopy; X ray photoelectron spectroscopy

Brazing parameters determine the degradation and mechanical behaviour of alumina/titanium brazed joints - Paiva, O.C.; Barbosa, M.A. (Journal of Materials ScienceJ Mater Sci, 2000)
The main aims of the present study are simultaneously to relate tho brazing parameters with the correspondent interfacial microstructure, the resultant mechanical properties and the electrochemical degradation behaviour of commercially pure titanium/alumina brazed joints. A filler metal on the Ag-26.5Cu-3Ti system has been used. Three different brazing temperatures (850, 900 and 950 °C) and three holding times (0.3, 1.2, 2.4 ks) were tested, in order to understand the influence of each combination of brazing temperature holding times, over the final microstructure and properties of the joints. The mechanical properties of the M/C joints were assessed on the basis of bond strength tests carried out using a shear solicitation scheme. The fracture surfaces were studied morphologically and structurally using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and X-ray diffraction analysis (XRD). The degradation behaviour of the M/C joints was assessed by means of electrochemical techniques. It was found that a brazing temperature of 850 °C and a holding time of 2.4 ks, produces the best results in terms of bond strength, 130±16 MPa. The mechanical properties obtained could be explained on the basis of the different compounds identified on the fracture surfaces by XRD. On the other hand, a brazing temperature of 950 °C produces the best results in terms of corrosion rates (lower corrosion current), 3.44±0.73 μA cm
Keywords: Alumina; Aluminum copper titanide; Brazing filler metals; Ceramic matrix composites; Degradation; Energy dispersive spectroscopy; fracture; Joints (structural components); Scanning electron microscopy; Silver alloys; Titanium; X ray diffraction analysis

Classification of breast tissue by electrical impedance spectroscopy - Estrela Da Silva, J.; Marques De Sá, J.P.; Jossinet, J. (Medical and Biological Engineering and ComputingMed. Biol. Eng. Comput., 2000)
Electrical impedance spectroscopy is a minimally invasive technique that has clear advantages for living tissue characterisation owing to its low cost and ease of use. The present paper describes how this technique can be applied to breast tissue classification and breast cancer detection. Statistical analysis is used to derive a set of rules based on features extracted from the graphical representation of electrical impedance spectra. These rules are used hierarchically to discriminate several classes of breast tissue. Results of statistical classification obtained from a data set of 106 cases representing six classes of excised breast tissue show an overall classification efficiency of ~92% with carcinoma discrimination > 86%.Electrical impedance spectroscopy is a minimally invasive technique that has clear advantages for living tissue characterization owing to its low cost and ease of use. The present paper describes how this technique can be applied to breast tissue classification and breast cancer detection. Statistical analysis is used to derive a set of rules based on features extracted from the graphical representation of electrical impedance spectra. These rules are used hierarchically to discriminate several classes of breast tissue. Results of statistical classification obtained from a data set of 106 cases representing six classes of excised breast tissue show an overall classification efficiency of approximately 92% with carcinoma discrimination >86%.
Keywords: article; Breast; breast cancer; Breast Neoplasms; cancer classification; Data classification; Discriminant Analysis; Electric Impedance; Electrical impedance spectroscopy; Electrodiagnosis; Feature extraction; Female; human; Humans; impedance; Impedance spectroscopy; major clinical study; Medical imaging; Signal Processing, Computer-Assisted; Spectroscopy; Statistical analysis; Statistical methods; Tissue; Tissue characterisation

A computational model of visual cortex receptive fields using spatio-temporal filters - Milanova, M.G.; Elmaghraby, A.S.; Wachowiak, M.P.; Campilho, A. (Proceedings of the IEEE/EMBS Region 8 International Conference on Information Technology Applications in Biomedicine, ITABProc IEEE EMBS Reg 8 Int Conf Inf Technol Appl Biomed ITAB, 2000)
It is known that neurons in the primary visual cortex are characterized by receptive fields that are selective for specific spatial orientations. It is believed that the sense of object motion and velocity are also related to these fields, as objects in natural scenes are represented by a sparse set of statistically independent components, such as edges. Currently, computational models of receptive fields consider only spatial components, and thus cannot account for time-varying sensory stimuli. In this paper, a model based on independent components analysis and cellular neural networks is proposed. This approach extends existing models to incorporate temporal aspects of sequences of images of natural scenes.
Keywords: Cellular neural networks; Computational methods; ICA; Independent component analysis; Mathematical models; Neurology; Receptive fields; Receptive fields (RF); Spatial filters; Spatio-temporal filters; Visual modeling

Concept, design and fabrication of smart orthopedic implants - Burny, F.; Donkerwolcke, M.; Moulart, F.; Bourgois, R.; Puers, R.; Van Schuylenbergh, K.; Barbosa, M.; Paiva, O.; Rodes, F.; Bégueret, J.B.; Lawes, P. (Medical Engineering and PhysicsMed. Eng. Phys., 2000)
Extensive clinical experience has been built up using orthopaedic implants instrumented with strain gauges connected to a Wheatstone bridge by means of percutaneous leads. This research showed the medical relevance of the monitoring of the deformation of implants as a powerful tool to evaluate nursing and rehabilitation exercises, for tracing dangerous overloads and anticipating implant failure and also to observe the healing process. The IMPACT 3500 project focuses on the instrumentation of femoral implants with on board sensors: regular Benoist-Girard implants have been modified, to contain a 'sensing cell', and thoroughly tested in vitro and in vivo. The implant deformations are measured with resistive strain gauges, and the signal is transferred to a personal computer for processing and display, via a hard wired connection, or via a telemetry system. Two fully implantable wireless designs, called Linkstrain and Sealstrain, are powered from the outside by magnetic induction. As Sealstrain contains the whole telemetric system in its cavity, the highest miniaturization was required; this seriously deteriorates the efficiency of the inductive power link. © 2001 IPEM.
Keywords: article; atomic absorption spectrometry; Biocompatible Materials; biomechanics; body movement; Bone Plates; ceramics; compression; Corrosion; Failure of implants; Femoral Fractures; femur; Fracture healing; healing; Humans; materials testing; metal; metal implantation; Metals; microcomputer; Microscopy, Electron, Scanning; Monitoring, Physiologic; Orthopedic implants; orthopedic surgery; priority journal; Prostheses and Implants; Prosthesis Design; prosthesis failure; Rehabilitation; Scanning electron microscopy; sensor; Sensors; Smart implants; Spectrum Analysis; Stainless steel; strain gauge transducer; Strain measurements; Stress, Mechanical; Telemetry; Weight-Bearing

Crystallization and microstructure analysis of calcium phosphate-based glass ceramics for biomedical applications - Zhang, Y.; Santos, J.D. (Journal of Non-Crystalline SolidsJ Non Cryst Solids, 2000)
Calcium phosphate glasses and glass ceramics (CaO/P 2O 5 = 1.25 in molar ratio) modified by small amounts of additives such as Na 2O, MgO, TiO 2 and ZrO 2 were prepared after appropriate heat treatment for nucleation and crystallization. Based upon differential thermal analysis (DTA) results, a two-step heat treatment was used for crystal nucleation and growth. X-ray diffraction (XRD) analysis demonstrated that bioresorbable β-Ca 2P 2O 7 (β-DCP), β-Na 2CaP 2O 7, Na 2Mg(PO 3) 4 phases were formed in the glass matrix depending upon the relative contents of the additives. By adding higher contents of Na 2O and TiO 2 and using CaO/P 2O 5 = 1.5-2.0, crystallization of β-DCP and Ca 3(PO 4) 2 (β-TCP), and the formation of a dense structure in the glass ceramics were obtained. The precipitation of these crystals could be well distinguished at a magnification of 4000× and phases were dispersed in areas of micron size. A porous structure may be easily formed after the soluble phases are dissolved in physiological media. These glass ceramics with high CaO/P 2O 5 ratio, modified by the above mentioned additives are expected to find use as implants for bone replacement/regeneration and drug delivery carriers synergistically, because the soluble phases may act as drug delivery carriers and the porous structure will allow for bone ingrowth.
Keywords: Additives; Biomaterials; Calcium Compounds; calcium phosphate; Ceramic materials; Crystal microstructure; Crystallization; Differential thermal analysis; glass; Glass ceramics; Nucleation; Phosphates; Porous materials; Precipitation (chemical); Sodium dioxide; X ray crystallography

Direct and indirect effects of P 2O 5 glass reinforced-hydroxyapatite composites on the growth and function of osteoblast-like cells - Lopes, M.A.; Knowles, J.C.; Santos, J.D.; Monteiro, F.J.; Olsen, I. (BiomaterialsBiomaterials, 2000)
Human osteoblast-like cells were plated on hydroxyapatite and P 2O 5-glass reinforced hydroxyapatite composite discs. They were also cultured in the presence of media obtained by incubating the discs in the absence of cells. The effects of these direct and indirect interactions were examined by measuring cell proliferation and the expression of certain key extracellular matrix antigens. One composite was found to initially delay cell growth, while the extract of a different composite appeared to down-regulate DNA synthesis. Flow cytometry analysis showed that growth directly on the discs had little effect on collagen type I, but reduced fibronectin and osteocalcin levels. The extracts of the materials generally had less effect, although one extract obtained from the glass-reinforced hydroxyapatite significantly down-regulated fibronectin. These in vitro studies thus suggest that there were only few differences overall in the growth of the cells directly on the glass-reinforced compared with the hydroxyapatite discs and also only relatively small effects of the extracts on the cells. However, the flow cytometry results suggest that both the materials and the extracts may have a potentially important influence on connective tissue production, and that these effects are both material- and antigen-specific. Copyright (C) 2000 Elsevier Science Ltd. Human osteoblast-like cells were plated on hydroxyapatite and P 2O 5-glass reinforced hydroxyapatite composite discs. They were also cultured in the presence of media obtained by incubating the discs in the absence of cells. The effects of these direct and indirect interactions were examined by measuring cell proliferation and the expression of certain key extracellular matrix antigens. One composite was found to initially delay cell growth, while the extract of a different composite appeared to down-regulate DNA synthesis. Flow cytometry analysis showed that growth directly on the discs had little effect on collagen type I, but reduced fibronectin and osteocalcin levels. The extracts of the materials generally had less effect, although one extract obtained from the glass-reinforced hydroxyapatite significantly down-regulated fibronectin. These in vitro studies thus suggest that there were only few differences overall in the growth of the cells directly on the glass-reinforced compared with the hydroxyapatite discs and also only relatively small effects of the extracts on the cells. However, the flow cytometry results suggest that both the materials and the extracts may have a potentially important influence on connective tissue production, and that these effects are both material- and antigen-specific.
Keywords: Animal cell culture; antigen expression; Antigens; article; Biocompatibility; Biocompatible Materials; Biomaterials; Bone; Bone cells; cell antigen; Cell culture; Cell Division; cell function; cell growth; Cell Line; cell proliferation; cell structure; collagen type 1; controlled study; DNA; DNA Replication; DNA synthesis; extracellular matrix; Fibronectin; flow cytometry; glass; Glass fibers; Glass-reinforced hydroxyapatite; Growth kinetics; human; human cell; Humans; hydroxyapatite; Hydroxyapatites; immunofluorescence; In vitro; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; osteocalcin; Phosphate minerals; Phosphates; phosphorus pentoxide; priority journal; Proteins; Reinforcement; Scanning electron microscopy

Fetal heart rate baselines in twins: Interobserver agreement in antepartum estimation - Bernardes, J.; Costa-Pereira, A.; Calejo, L.; Ayres-de-Campos, D.; Patrício, B.; Pereira-Leite, L. (Journal of Reproductive Medicine for the Obstetrician and GynecologistJ. Reprod. Med. Obstet. Gynecol., 2000)
OBJECTIVE: To assess interobserver agreement in antepartum estimation of fetal heart rate (FHR) baselines in twins. STUDY DESIGN: Two residents and one specialist in obstetrics and gynecology, all with special interest in FHR monitoring, independently estimated baselines in 162 consecutive antepartum FHR tracings recorded in 24 twins. Tracings were obtained with a dual-channel fetal monitor for the simultaneous recording of both twins' heart rates. Baselines were estimated, as single values corresponding to the mean of the lowest stable FHR segment, in the absence of fetal movements and uterine contractions, within physiologic limits (110-150 beats per minute [bpm]). If these criteria were not met, the possibility of persistent bradycardia or tachycardia was considered, and if this was confirmed in a tracing with at least 40 minutes, a baseline < 110 or > 150 bpm was chosen. Interobserver agreement was assessed by the proportions of agreement (PA), kappa statistic (K) and intraclass correlation coefficient (ICCC), with 95% confidence intervals (CIs). RESULTS: Interobserver agreement was excellent, with a PA of 0.90 (95% CI: 0.89-0.91), K of 0.88 (95% CI: 0.84-0.92) and ICCC of 0.91 (95% CI: 0.88-0.94). CONCLUSION: Interobserver agreement in antepartum estimation of fetal heart rate baselines in twins was excellent with the baseline concept used in this study.
Keywords: adult; article; clinical article; Electrocardiography; Female; Fetal heart rate; Fetal monitoring; fetus; fetus heart rate; fetus monitoring; Heart rate variability; Heart Rate, Fetal; human; Humans; Internship and Residency; observer variation; Obstetrics; Pregnancy; Prenatal Care; priority journal; Professional Competence; Twins

Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma-sprayed coatings - Ferraz, M.P.; Knowles, J.C.; Olsen, I.; Monteiro, F.J.; Santos, J.D. (BiomaterialsBiomaterials, 2000)
Multilayered coatings composed of mixtures of HA and P 2O 5-based bioactive glasses are of potential clinical benefit in orthopaedic and dental surgery. Pre-immersion of these materials has been reported to further enhance their efficacy in vivo, although the precise biological effects of this treatment are not yet known. In this study we have therefore prepared double-layer plasma-sprayed coatings and evaluated the effects of pre-immersion on the growth and function of human osteosarcoma cells in vitro, using the MTT assay and flow cytometry analysis, respectively. The results showed that the increase in numbers of viable cells was the same or elevated following incubation on the pre-immersed HA and glass-reinforced HA coatings compared with the non-immersed materials. In addition, the expression of bone sialoprotein and fibronectin, two key connective tissue antigens, was up-regulated in cultures grown on the pre-immersed surfaces compared with the non-treated materials. Moreover, cell numbers and antigen expression both improved as the proportion of glass increased, particularly in the pre-immersed samples. Our findings thus suggest that the immersion treatment of these materials appeared to improve the response of these bone-like cells. Copyright (C) 2000 Elsevier Science Ltd. Multilayered coatings composed of mixtures of HA and P 2O 5-based bioactive glasses are of potential clinical benefit in orthopaedic and dental surgery. Pre-immersion of these materials has been reported to further enhance their efficacy in vivo, although the precise biological effects of this treatment are not yet known. In this study we have therefore prepared double-layer plasma-sprayed coatings and evaluated the effects of pre-immersion on the growth and function of human osteosarcoma cells in vitro, using the MTT assay and flow cytometry analysis, respectively. The results showed that the increase in numbers of viable cells was the same or elevated following incubation on the pre-immersed HA and glass-reinforced HA coatings compared with the non-immersed materials. In addition, the expression of bone sialoprotein and fibronectin, two key connective tissue antigens, was up-regulated in cultures grown on the pre-immersed surfaces compared with the non-treated materials. Moreover, cell numbers and antigen expression both improved as the proportion of glass increased, particularly in the pre-immersed samples. Our findings thus suggest that the immersion treatment of these materials appeared to improve the response of these bone-like cells.
Keywords: antigen expression; article; Bioactive glasses; Biocompatibility; Biocompatible Materials; Biomaterials; Cell culture; Cell Division; cell growth; cell proliferation; Cell size; Coated Materials, Biocompatible; controlled study; cytology; Cytoplasmic Granules; Dental Materials; drug manufacture; Durapatite; Fibronectin; Fibronectins; flow cytometry; Flow cytometry analysis; glass; Glass fibers; Glass-reinforced hydroxyapatite; Growth kinetics; human; human cell; Humans; hydroxyapatite; in vitro study; materials testing; orthopedics; Osteosarcoma; osteosarcoma cell; Phosphates; Plasma spraying; Pre-immersion; priority journal; protein expression; Proteins; Sialoglycoproteins; sialoprotein; Sprayed coatings; Surface Properties; technique; Tumor Cells, Cultured

Microstructural dependence of Young's and shear moduli of P 2O 5 glass reinforced hydroxyapatite for biomedical applications - Lopes, M.A.; Silva, R.F.; Monteiro, F.J.; Santos, J.D. (BiomaterialsBiomaterials, 2000)
P 2O 5 glass reinforced hydroxyapatite composite materials were prepared through a liquid-phase sintering process. Secondary phases, β- and α- tricalcium phosphate (β-TCP and α-TCP), were formed in the microstructure of the composites, due to the reaction between the liquid glassy phase and the hydroxyapatite matrix. The dynamic Young's modulus (E) and shear modulus (G) of these composites were determined using an impulse excitation method. By applying the Duckworth-Knudsen equation, the elastic property results were correlated with the relative proportion of β-TCP and α-TCP phases and with the porosity percentage present in the microstructure. Glass reinforced hydroxyapatite composites showed lower Young's and shear moduli than unmodified hydroxyapatite, mainly due to presence of β-TCP phase. The Duckworth-Knudsen model demonstrated an exponential dependence of E and G modulus with porosity and mathematical equations were derived for composite materials with porosity correction factors (b) of 4.04 and 4.11, respectively, indicating that porosity largely decreased both E and G moduli. (C) 2000 Elsevier Science Ltd. 2O 5 glass reinforced hydroxyapatite composite materials were prepared through a liquid-phase sintering process. Secondary phases, β- and α-tricalcium phosphates (β-TCP and α-TCP), were formed in the microstructure of the composites, due to the reaction between the liquid glassy phase and the hydroxyapatite matrix. The dynamic Young's modulus (E) and shear modulus (G) of these composites were determined using an impulse excitation method. By applying the Duckworth-Knudsen equation, the elastic property results were correlated with the relative proportion of β-TCP and α-TCP phases and with the porosity percentage present in the microstructure. Glass reinforced hydroxyapatite composites showed lower Young's and shear moduli than unmodified hydroxyapatite, mainly due to the presence of β-TCP phase. The Duckworth-Knudsen model demonstrated an exponential dependence of E and G modulus with porosity and mathematical equations were derived for composite materials with porosity correction factors (b) of 4.04 and 4.11, respectively, indicating that porosity largely decreased both E and G moduli.
Keywords: article; Biocompatible Materials; Ceramic matrix composites; Chemical analysis; chemical composition; composite graft; Duckworth-Knudsen model; Elastic moduli; Elasticity; glass; hydroxyapatite; Hydroxyapatite glass composites; Hydroxyapatites; Implants (surgical); Mathematical models; Microstructure; Molecular Structure; Phosphate minerals; Phosphates; porosity; priority journal; Shear modulus; shear stress; young modulus; Young's modulus

Object recognition in image sequences with cellular neural networks - Milanova, M.; Büker, U. (NeurocomputingNeurocomputing, 2000)
In this paper, the application of CNN associative memories for 3D object recognition is presented. The main idea is to analyse the optical flow in an image sequence of an object. Several features of the optical flow between two succeeding images are calculated and merged to a time series of features for the whole image sequence. These features show several object specific characteristics and are used for a classification step in an object recognition system. Therefore, the feature vectors of an object set are learnt and recalled by an associative memory based on the paradigm of cellular neural networks (CNN). (C) 2000 Elsevier Science B.V.In this paper, the application of CNN associative memories for 3D object recognition is presented. The main idea is to analyze the optical flow in an image sequence of an object. Several features of the optical flow between two succeeding images are calculated and merged to a time series of features for the whole image sequence. These features show several object specific characteristics and are used for a classification step in an object recognition system. Therefore, the feature vectors of an object set are learnt and recalled by an associative memory based on the paradigm of cellular neural networks (CNN).
Keywords: algorithm; artificial neural network; Associative memory; Associative storage; Cellular neural networks; Computational methods; computer system; Image analysis; Image sequences; mathematical computing; Object recognition; Optical flow; Optical flows; Pattern recognition; Pattern recognition systems; priority journal; review; Three dimensional computer graphics; Time series analysis; Vectors

Remote foetal heart rate acquisition and analysis - Marques, P.; Marques de Sa, J.P.; Bernardes, J.; Sousa, P. (Computers in CardiologyComput Cardiol, 2000)
The remote foetal monitoring and analysis is part of INTERCARE project - an integrated healthcare system applied to Electrocardiography and Cardiotocography. Its aim is to provide low cost and wide spread technological infrastructure that supports an integrated healthcare system to users and healthcare providers. This paper illustrates the work done in the cardiotocography area. We have developed a system for remote acquisition and analysis of FHR. The system uses a portable 'foetal detector' which can be used by the pregnant woman to acquire the heart beats. This detector sends a modulated audio signal via the telephone line or a computer connected to Internet. At the processing end the signal received by the telephone can be switched to the computer sound acquisition board. The signal is then processed by an application that reads from the soundcard. Due to the noise added by devices and telephone lines, the signal is filtered using optimal FIR filters and is decimated until its band of interest covers the peaks of the heart sounds. Next the signal is processed by a specially developed adaptive correlation algorithm in order to obtain the heart beat instants. The whole process operates in real time. The adaptive correlation algorithm performs a continuous adjustment of the heart beat template and threshold detection levels.
Keywords: Adaptive algorithms; Adaptive correlation algorithm; Cardiology; Cardiotocography; Client server computer systems; Data acquisition; Data warehouse; Database systems; Electrocardiography; FIR filters; Foetal heart rate; Internet; Patient monitoring; Remote foetal monitoring; Signal filtering and prediction; Sonoscope; Spurious signal noise; Telephone

Self-assembly and surface structure of an amphiphilic graft copolymer, polystyrene-graft-ω-stearyl-poly(ethylene oxide) - Ji, J.; Feng, L.; Qiu, Y.; Yu, X.; Barbosa, M.A. (Journal of Colloid and Interface ScienceJ. Colloid Interface Sci., 2000)
Surface properties of the polystyrene-graft-ω-stearyl-poly(ethylene oxide) (PS-g-SPEO) have been characterized by X-ray photoelectron spectroscopy (XPS), differential scanning calorimetry (DSC), contact angle, and spin probe techniques. The XPS results indicate that the surface and bulk composition of the PS-g-SPEO copolymers differ remarkably from each other. The stearyl and EO components enrich at the copolymer/air interfaces due to the self-assembly of the stearyl groups. At the PS-g-SPEO-72.6 surface (the x in PS-g-SPEO-x indicates the bulk density of the SPEO in wt%), the self- assembly of the hydrophobic stearyl groups is strong enough to form a stable liquid crystalline phase as indicated by DSC. At polymer/water interfaces, PS-g-SPEO-72.6 presents a hydrophilic surface with low PEO mobility, whereas PS-g-SPEO-50.6 and PS-g-SPEO-31.0 present the hydrophobic surface with high PEO mobility. The two different types of the surfaces, with different characters in surface energy, surface mobility of PEO, and surface architecture of SPEO, will be quite valuable as models for detecting the synergistic action of the PEO chains and the stearyl groups (specific ligand for albumin binding) in protein solutions. (C) 2000 Academic Press.
Keywords: Amphiphilic copolymer; article; biomaterial; copolymer; crystal; differential scanning calorimetry; electron microscopy; electron spin resonance; hydrophobicity; macrogol; polystyrene; priority journal; protein assembly; protein binding; protein structure; Self-assembly; stearic acid; Surface structure; X ray analysis

Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement - Lopes, M.A.; Knowles, J.C.; Santos, J.D. (BiomaterialsBiomaterials, 2000)
Phase transformations and interstitial and/or substitution of trace elements during the liquid-phase sintering process of P 2O 5-CaO-MgO glass-reinforced hydroxyapatite (GR-HA) composites were examined by X-ray diffraction and Rietveld analyses. Using the Rietveld method for structure refinement, changes in the lattice parameters of the two main phases of the composites, hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP), as well as changes in several bond lengths and in the occupancy of the hydroxyl oxygen site in the HA phase structure were assessed. The glasses gave rise to formation of between approximately 45 and 50% of β-TCP, with evidence for the Mg 2+ enhancing the formation of β-TCP. Between 1300 and 1350°C, the β-TCP inverts to α-TCP, without further decomposition of the residual HA. The glasses showed evidence for stabilisation of the hydroxyl group located in the hydroxyl channels. This is supported by measurements of the hydroxyl channel radius (R(c)), the Ca 2-OH bond length and the hydroxyl oxygen occupancy (O(occ)). Results showed that the Mg 2+ containing glasses induced the β-TCP phase formation in the structure of GR-HA composites and retarded the β-TCP into α-TCP transformation at higher temperatures. The chemical composition of the P 2O 5 glasses also induces modifications in the lattice parameters of the crystallographic phases present in the microstructure of the composites. This suggests some substitution of Mg 2+-for-Ca 2+ in the β-TCP structure during the liquid-phase sintering process. Copyright (C) 2000 Elsevier Science Ltd. Phase transformations and interstitial and/or substitution of trace elements during the liquid-phase sintering process of P 2O 5-CaO-MgO glass-reinforced hydroxyapatite (GR-HA) composites were examined by X-ray diffraction and Rietveld analyses. Using the Rietveld method for structure refinement, changes in the lattice parameters of the two main phases of the composites, hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP), as well as changes in several bond lengths and in the occupancy of the hydroxyl oxygen site in the HA phase structure were assessed. The glasses gave rise to formation of between approximately 45 and 50% of β-TCP, with evidence for the Mg 2+ enhancing the formation of β-TCP. Between 1300 and 1350 °C, the β-TCP inverts to α-TCP, without further decomposition of the residual HA. The glasses showed evidence for stabilization of the hydroxyl group located in the hydroxyl channels. This is supported by measurements of the hydroxyl channel radius (R c), the Ca 2-OH bond length and the hydroxyl oxygen occupancy (O occ). Results showed that the Mg 2+ containing glasses induced the β-TCP phase formation in the structure of GR-HA composites and retarded the β-TCP into α-TCP transformation at higher temperatures. The chemical composition of the P 2O 5 glasses also induces modifications in the lattice parameters of the crystallographic phases present in the microstructure of the composites. This suggests some substitution of Mg 2+-for-Ca 2+ in the β-TCP structure during the liquid-phase sintering process.
Keywords: article; Biocompatible Materials; Biomedical engineering; Calcium Compounds; calcium phosphate; Calcium phosphates; Chemical bonds; chemical composition; Composition effects; Crystal lattices; Crystal microstructure; crystal structure; Crystallization; decomposition; Fiber reinforced materials; glass; Glass fibers; Glass-reinforced hydroxyapatite; Glass-reinforced hydroxyapatite composites; hydroxyapatite; Hydroxyapatites; Implants (surgical); Liquid-phase sintering; Magnesium; Mg-apatites; Models, Molecular; phase transition; Phase transitions; Phosphate minerals; priority journal; Rietveld refinement; Rietveld refinement analysis; Sintering; spectacles; structure analysis; temperature; Thermodynamics; Trace Elements; Tricalcium phosphate; X ray analysis; X ray crystallography; β-TCP

CaO-P 2O 5 glass hydroxyapatite double-layer plasma-sprayed coating: In vitro bioactivity evaluation - Ferraz, M.P.; Monteiro, F.J.; Santos, J.D. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
Double-layer composite coatings composed of a P 2O 5-based glass/Ca 10(PO 4) 6(OH) 2 (HA) mixture top layer and a simple HA underlayer, on Ti-6AI-4V substrates, were prepared using a plasma-spraying technique. The in vitro bioactivity of these coatings was assessed by immersion testing in simulated body fluid. Both scanning electron microscopy (SEM) analysis and the ionic solution changes followed by atomic absorption spectroscopy and the molybdenum blue method demonstrated that these composite coatings induce a faster surface Ca-P layer formation than the simple HA coatings used as a control. X-ray photoelectron spectroscopy (XPS) analysis demonstrated that the Ca-P layer formed was apatite. The combination of SEM and XPS analyses showed that the apatite layer was a calcium-deficient hydroxyapatite with a Ca/P ranging from 1.3 to 1.4 with CO 3 2- groups contained in the structure. Double-layer composite coatings composed of a P 2O 5-based glass/Ca 10(PO 4) 6(OH) 2 (HA) mixture top layer and a simple HA underlayer, on Ti-6AI-4V substrates, were prepared using a plasma-spraying technique. The in vitro bioactivity of these coatings was assessed by immersion testing in simulated body fluid. Both scanning electron microscopy (SEM) analysis and the ionic solution changes followed by atomic absorption spectroscopy and the molybdenum blue method demonstrated that these composite coatings induce a faster surface Ca-P layer formation than the simple HA coatings used as a control. X-ray photoelectron spectroscopy (XPS) analysis demonstrated that the Ca-P layer formed was apatite. The combination of SEM and XPS analyses showed that the apatite layer was a calcium-deficient hydroxyapatite with a Ca/P ranging from 1.3 to 1.4 with CO 3 2- groups contained in the structure.
Keywords: alloy; Alloys; Apatite; article; Atomic absorption spectroscopy; Atomic spectroscopy; Bioactivity; Biocompatibility; biomaterial; Biomaterials; Biomedical engineering; Body fluids; Calcium; Calcium Compounds; CaO SiO2 P2O5 CaF2 glass; CaO-SiO2-P2O5-CaF2 glass; Chemical analysis; chemical composition; Coated Materials, Biocompatible; Double layer coatings; Double-layer coatings; Durapatite; film; glass; Glass plasma spraying; human; Humans; hydroxyapatite; immersion; implant; in vitro study; Ionic solution changes; Magnesium; materials testing; Molybdenum blue; Multilayers; Particle Size; phosphate; Phosphate minerals; Phosphates; Phosphorus Compounds; phosphorus pentoxide; Plasma spraying; potassium; powder; Powders; resin cement; Resin Cements; Scanning electron microscopy; Sodium; solution and solubility; Solutions; structure analysis; Substrates; Surface Properties; surface property; thickness; Tissue; Titanium; titanium alloy (TiAl6V4); Titanium alloys; X ray photoelectron spectroscopy

ECG noise filtering using wavelets with soft-thresholding methods - Agante Da Silva, P.M.G.; Marques De Sá, J.P. (Computers in CardiologyComput Cardiol, 1999)
In this paper we analyze algorithms for filtering white gaussian noise and 50 Hz power line noise from ECG signals. We used several wavelets to study their effect and efficiency in the filtering process. To deal with these different kinds of noises we used two distinct soft-thresholding techniques: the Donoho's statistical threshold estimator and a method developed by us. This last method exploits one of the wavelet processing main features: time-frequency relation. The de-noising methods led to good filtering results: noise reduction with only minor change of the ECG waveforms as confirmed by the high correlation values between the processed signal and the original one. These good results are due to a wavelet advantage over classical filtering - time-frequency relation - enabling the possibility of filtering noise in the same frequency band of the ECG signal with minimal interference.
Keywords: Algorithms; Electrocardiography; Signal filtering and prediction; Signal interference; Wavelet denoising; White noise

Enhancement of the mechanical properties of a high-density polyethylene - Kalay, G.; Sousa, R.A.; Reis, R.L.; Cunha, A.M.; Bevis, M.J. (Journal of Applied Polymer ScienceJ. Appl. Polym. Sci., 1999)
This paper describes the process optimization in injection molding of high-density polyethylene (HDPE). Both conventional injection molding and shear controlled orientation (SCORIM) were employed in processing. The process optimization was based on design of experiments and complemented with analysis of variance. Mechanical characterization was carried out by tensile testing. Wide-angle X-ray diffraction and differential scanning calorimetry were used for the structural characterization of the moldings. High-density polyethylene exhibits 7.2 GPa Young's modulus and 155 MPa of ultimate tensile strength following the application of SCORIM processing. These results account for a fourfold increase in Young's modulus and a fivefold increase in ultimate tensile strength compared to conventional injection molding. The maintenance of toughness while enhancing stiffness and strength of the SCORIM moldings is attributable to an oriented morphology developed during shear flow, i.e., shish-kebab structure. The frequency of shearing action has the strongest influence on the morphology development. It is also demonstrated that the studied parameters are very much interdependent. It is possible to achieve substantial gains in mechanical properties of HDPE in SCORIM processing without causing a substantial increase in cycle time.
Keywords: differential scanning calorimetry; Elastic moduli; High density polyethylenes; Injection molding; morphology; Optimization; Shear controlled orientation in injection molding; Shear flow; Shish kebab structure; Stiffness; Strength of materials; tensile strength; Tensile testing; Toughness; Wide angle X ray diffraction; X ray diffraction analysis

Flow cytometry analysis of effects of glass on response of osteosarcoma cells to plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings - Ferraz, M.P.; Knowles, J.C.; Olsen, I.; Monteiro, F.J.; Santos, J.D. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
Multilayered coatings composed of mixtures of hydroxyapatite (HA) and P 2O 5-based bioactive glasses offer potential clinical benefits in orthopedic and dental surgery. In this study double-layer plasma-sprayed coatings were prepared and the biological response evaluated in tissue culture using two human osteosarcoma cell lines, MG63 and HOS TE85 (HOS). The cells were cultured on the materials and the effects on cell growth were determined using a spectrophometric assay of a mitochondrial enzyme that is active in viable cells. While none of the materials influenced the growth of the MG63 cells, the HOS cells appeared to undergo less proliferation on all the HA materials. Flow cytometry analysis was carried out using rabbit antibodies against osteonectin, osteopontin, bone sialoprotein, fibronectin, and collagen type I to measure the effects of the materials on key cellular functions. The results showed that the materials downregulated the expression of these extracellular matrix antigens by MG63 cells whereas they had less effect on the HOS cells compared to the same cells incubated on a plastic surface. Notably, with both cell lines the composite with the higher percentage of glass restored the production of connective tissue proteins to levels that were more similar to those present in the control cells. In this study, double-layer plasma-sprayed coatings were prepared and the biological response evaluated in tissue culture using two human osteosarcoma cell lines, MG63 and HOS TE85 (HOS). The materials downregulated the expression of the extracellular matrix antigens by MG63 cells whereas they had less effect on the HOS cells compared to the same cells incubated on a plastic surface. Notably, with both cell lines the composite with the higher percentage of glass restored the production of connective tissue proteins to levels that were more similar to those present in the control cells.
Keywords: Animals; Antibodies; antigen expression; article; Bioassay; Biomaterials; Bone cells; Bone sialoprotein; Bone Substitutes; calcium phosphate; cancer cell culture; Cell Division; cell function; cell granule; cell growth; cell proliferation; Cell size; Cells; Coated Materials, Biocompatible; Collagen; collagen type 1; connective tissue; controlled study; dentistry; enzyme activity; Enzymes; Fibronectin; flow cytometry; Flow cytometry analysis; glass; Growth kinetics; human; human cell; Humans; hydroxyapatite; Hydroxyapatite-glass; Hydroxyapatites; Incubation; Mitochondrial enzyme; orthopedics; Osteoblasts; osteonectin; Osteopontin; Osteosarcoma; osteosarcoma cell; Osteosarcoma cells; Phosphates; Proliferation; Proteins; Rabbits; sialoprotein; Spectrophometric assay; Tissue culture; Tumor Cells, Cultured

Glass-reinforced hydroxyapatite composites: Fracture toughness and hardness dependence on microstructural characteristics - Lopes, M.A.; Monteiro, F.J.; Santos, J.D. (BiomaterialsBiomaterials, 1999)
Fracture toughness and hardness properties of CaO-P 2O 5 glass-reinforced hydroxyapatite composites have been assessed using indentation techniques and results calculated according to Laugier and Evans' equations. Both properties showed to be dependent upon several microstructural characteristics, namely residual porosity and the percentage of secondary β and α tricalcium phosphate phases in the structure of the composites. Composites presented a Palmqvist-type indentation crack system, which is the specific crack system addressed by Laugier's approach. Fracture toughness determinations according to Evan's equation, which is a universal one and adapted to both median and Palmqvist crack systems, did not correlate well with Laugier determinations. Copyright (C) 1999 Elsevier Science Ltd. Fracture toughness and hardness properties of CaO-P 2O 5 glass-reinforced hydroxyapatite composites have been assessed using indentation techniques and results calculated according to Laugier and Evans' equations. Both properties showed to be dependent upon several microstructural characteristics, namely residual porosity and the percentage of secondary β and α tricalcium phosphate phases in the structure of the composites. Composites presented a Palmqvist-type indentation crack system, which is the specific crack system addressed by Laugier's approach. Fracture toughness determinations according to Evan's equation, which is a universal one and adapted to both median and Palmqvist crack systems, did not correlate well with Laugier determinations.
Keywords: article; Biocompatible Materials; Biomaterials; calcium phosphate; Calcium phosphates; ceramics; Composite materials; Composite Resins; Cracks; Durapatite; Evan's equation; Fracture toughness; glass; hardness; hydroxyapatite; Hydroxyapatite-glass composites; Indentation techniques; Kinetics; Laugier equations; material state; mechanical stress; Microscopy, Electron, Scanning; Microstructure; Palmqvist crack systems; Phosphate minerals; porosity; priority journal; Stress, Mechanical; tensile strength; Tricalcium phosphate

Glass-reinforced hydroxyapatite composites: Secondary phase proportions and densification effects on biaxial bending strength - Lopes, M.A.; Monteiro, F.J.; Santos, J.D. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
CaO-P 2O 5 glasses with additions of MgO and CaF 2 were used as a sintering aid of hydroxyapatite, and glass-reinforced hydroxyapatite composites obtained. Glasses promoted significant changes in the microstructure of the composites, namely with the formation of tricalcium phosphate secondary phases, β and α-TCP. Quantitative phase analysis was performed by the Rietveld method using General Structure Analysis Software. Grain size measurements were carried out on SEM photomicrographs, using a planimetric procedure according to ASTM E 112-88. Flexural bending strength was determined from concentric ring-on-ring testing. Flexural bending strength (FBS) of glass-reinforced hydroxyapatite composites was found to be about twice or three times higher than that of unreinforced hydroxyapatite and tended to depend more on porosity and β and α-TCP secondary phases, rather than on grain size. Traces of α-tricalcium phosphate significantly enhanced the strength of the composites. Using the rule of mixtures to estimate the zero porosity bending strength, the Duckworth-Knudsen model applied to the composites gave a porosity correction factor, b, with a value of 4.02. Weibull statistics were also used to analyze biaxial strength data and the level of reinforcement obtained by comparing failure probability for the composites and for the unreinforced hydroxyapatite. Lower activation energies for grain growth were observed for the composites compared to unreinforced hydroxyapatite, which should be attributed to the presence of a liquid glassy phase that promotes atomic diffusion during the sintering process. CaO-P 2O 5 glasses with additions of MgO and CaF 2 were used as a sintering aid of hydroxyapatite, and glass-reinforced hydroxyapatite composites obtained. Glasses promoted significant changes in the microstructure of the composites, namely with the formation of tricalcium phosphate secondary phases, β and α-TCP. Quantitative phase analysis was performed by the Rietveld method using General Structure Analysis Software. Grain size measurements were carried out on SEM photomicrographs, using a planimetric procedure according to ASTM E 112-88. Flexural bending strength was determined from concentric ring-on-ring testing. Flexural bending strength (FBS) of glass-reinforced hydroxyapatite composites was found to be about twice or three times higher than that of unreinforced hydroxyapatite and tended to depend more on porosity and β and α-TCP secondary phases, rather than on grain size. Traces of α-tricalcium phosphate significantly enhanced the strength of the composites. Using the rule of mixtures to estimate the zero porosity bending strength, the Duckworth-Knudsen model applied to the composites gave a porosity correction factor, b, with a value of 4.02. Weibull statistics were also used to analyze biaxial strength data and the level of reinforcement obtained by comparing failure probability for the composites and for the unreinforced hydroxyapatite. Lower activation energies for grain growth were observed for the composites compared to unreinforced hydroxyapatite, which should be attributed to the presence of a liquid glassy phase that promotes atomic diffusion during the sintering process.
Keywords: article; atom; Bending (deformation); Biocompatibility; Biocompatible Materials; Biomaterials; calcium fluoride; calcium phosphate; Calcium phosphates; Composite materials; Densification; Dental application; dentistry; Duckworth-Knudsen model; glass; Glass reinforced hydroxyapatite; Humans; hydroxyapatite; Hydroxyapatite-glass composites; Hydroxyapatites; Implants (surgical); Magnesium Oxide; mathematical analysis; Mechanical strength; Mechanics; Medical applications; Microstructure; orthopedics; Phase composition; physical chemistry; porosity; Scanning electron microscopy; Strength of materials; tensile strength; Tissue; Tricalcium phosphate

Histological effects of iron accumulation on mice liver and spleen after administration of a metallic solution - Pereira, M.C.; Pereira, M.L.; Sousa, J.P. (BiomaterialsBiomaterials, 1999)
Special attention has been focused on the toxicity of some metallic species released from implanted materials, which accumulate in vital organs over long periods of time. A set of experiments with mice was designed to investigate the individual effects caused by iron in the liver and spleen. Histological features of these organs were evaluated and slight morphological changes were observed during the treatment time suggesting a negative correlation with the duration of the iron treatment. In addition, to associate the histological changes in the organs with iron accumulation an electrochemical method, adsorptive stripping voltammetry, was chosen to quantify the iron levels in these mentioned organs. The accuracy of the proposed method was checked by atomic absorption spectrometry. Both organs showed elevated concentrations of iron, nearly twofold, 7 days after iron administration compared to control organs.Special attention has been focused on the toxicity of some metallic species released from implanted materials, which accumulate in vital organs over long periods of time. A set of experiments with mice was designed to investigate the individual effects caused by iron in the liver and spleen. Histological features of these organs were evaluated and slight morphological changes were observed during the treatment time suggesting a negative correlation with the duration of the iron treatment. In addition, to associate the histological changes in the organs with iron accumulation an electrochemical method, adsorptive stripping voltammetry, was chosen to quantify the iron levels in these mentioned organs. The accuracy of the proposed method was checked by atomic absorption spectrometry. Both organs showed elevated concentrations of iron, nearly twofold, 7 days after iron administration compared to control organs.
Keywords: Absorption spectroscopy; accuracy; Adsorption; Adsorptive stripping voltametry; Adsorptive stripping voltammetry; animal experiment; animal model; animal tissue; Animalia; Animals; article; atomic absorption spectrometry; Atomic spectroscopy; bioaccumulation; biomaterial; controlled study; Corrosion; electrochemistry; histology; histopathology; Implants (surgical); Injections, Subcutaneous; Iron; iron metabolism; Kinetics; Liver; liver toxicity; male; metal implantation; Mice; morphology; mouse; nonhuman; Organ Size; potentiometry; priority journal; quantitative assay; Solutions; Spleen; Stainless steel; tissue distribution; toxicity

Hydrophobicity, surface tension, and zeta potential measurements of glass-reinforced hydroxyapatite composites - Lopes, M.A.; Monteiro, F.J.; Santos, J.D.; Serro, A.P.; Saramago, B. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
Wettability and zeta potential studies were performed to characterize the hydrophobicity, surface tension, and surface charge of P 2O 5-glass- reinforced hydroxyapatite composites. Quantitative phase analysis was performed by the Rietveld method using GSAS software applied to X-ray diffractograms. Surface charge was assessed by zeta potential measurements. Protein adsorption studies were performed using vitronectin. Contact angles and surface tensions variation with time were determined by the sessile and pendent drop techniques, respectively, using ADSA-P software. The highest (- 18.1 mV) and lowest (-28.7 mV) values of zeta potential were found for hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP), respectively, with composite materials presenting values in between. All studied bioceramic materials showed similar solid surface tension. For HA and β-TCP, solid surface tensions of 46.7 and 45.3 mJ/m 2, respectively, were obtained, while composites presented intermediate surface tension values. The dispersive component of surface tension was the predominant one for all materials studied. Adhesion work values between the vitronectin solution and HA and β- TCP were found to be 79.8 and 88.0 mJ/m 2, respectively, while the 4.0 wt % glass composites showed slightly lower values than the 2.5 wt % ones. The presence of β-TCP influenced surface charge, hydrophobicity, and protein adsorption of the glass-reinforced HA composites, and therefore indirectly affected cell-biomaterial interactions. The hydrophobicity, surface tension, and surface charge of P 2O 5-glass-reinforced hydroxyapatite (HA) composites were characterized through wettability and zeta potential studies. The highest and lowest values of zeta potential were found for HA and β-TCP. All studied bioceramic materials showed similar solid surface tension. The presence of β-TCP indirectly affected cell-biomaterial interactions.
Keywords: Adhesion; Adsorption; Algorithms; article; Biocompatible Materials; biomaterial; Biomaterials; Bone; Calcium Compounds; calcium phosphate; Calcium phosphates; Cells; Chemical analysis; Chemistry, Physical; Composite materials; Contact angle; glass; Glass reinforced hydroxyapatite composites; hydrophobicity; hydroxyapatite; Hydroxyapatite-glass composites; Hydroxyapatites; implant; Implants (surgical); Interfacial energy; Phosphorus Compounds; Protein adsorption; Proteins; Surface charge; Surface Properties; surface property; Surface tension; Tricalcium phosphate; Vitronectin; wettability; X-Ray Diffraction; Zeta potential

In vitro growth and differentiation of osteoblast-like human bone marrow cells on glass reinforced hydroxyapatite plasma-sprayed coatings - Ferraz, M.P.; Fernandes, M.H.; Cabral, A.T.; Santos, J.D.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1999)
Human osteoblastic bone marrow cells were cultured far periods of up to 28 days in control conditions and on the surface of a glass reinforced hydroxyapatite composite (HA/G1) and commercial hydroxyapatite (HA) plasma-sprayed coatings, in the 'as-received' condition and after immersion treatment in culture medium for 21 days. Cultures were characterized for total protein content and alkaline phosphatase activity. Scanning electron microscope analyses were performed on control cultures, seeded materials and materials incubated in the absence of cells. Culture media were analyzed for total and ionized calcium and phosphorus concentrations throughout the incubation period. Immersion of HA/G1 and HA coatings in culture medium resulted in significant alterations to the levels of calcium and phosphorus in the medium, leading to surface modifications. However, seeded material samples showed significant differences in the pattern of variation of the levels of these species. Cell proliferation was observed in the 'as-received' HA/G1 composite, but cell mediated formation of mineral deposits was not proved. In contrast, 'as-received' HA hardly supported cell growth. Previously immersed material samples showed cell proliferation and evidence of biological formation of mineral deposits. However, the HA/G1 composite presented better surface characteristics for cell growth as the behavior of bone marrow eel Is was closer to that observed in control cultures.Human osteoblastic bone marrow cells were cultured for periods of up to 28 days in control conditions and on the surface of a glass reinforced hydroxyapatite composite (HA/G1) and commercial hydroxyapatite (HA) plasma-sprayed coatings, in the 'as-received' condition and after immersion treatment in culture medium for 21 days. Cultures were characterized for total protein content and alkaline phosphatase activity. Scanning electron microscope analyses were performed on control cultures, seeded materials and materials incubated in the absence of cells. Culture media were analyzed for total and ionized calcium and phosphorus concentrations throughout the incubation period. Immersion of HA/G1 and HA coatings in culture medium resulted in significant alterations to the levels of calcium and phosphorous in the medium, leading to surface modifications. However, seeded material samples showed significant differences in the pattern of variation of the levels of these species. Cell proliferation was observed in the 'as-received' HA/G1 composite, but cell mediated formation of mineral deposits was not proved. In contrast, 'as-received' HA hardly supported cell growth. Previously immersed material samples cell proliferation and evidence of biological formation of mineral deposits. However, the HA/G1 composite presented better surface characteristics for cell growth as the behavior of bone marrow cells was closer to that observed in control cultures.
Keywords: adult; alkaline phosphatase; article; Bone; bone marrow cell; Bone replacement materials; Calcium; calcium ion; case report; Cell culture; cell differentiation; cell growth; Cells; controlled study; culture medium; enzyme activity; Enzyme kinetics; glass; Growth kinetics; human; Human bone marrow cell; human cell; hydroxyapatite; male; osteoblast; Phosphates; phosphorus; priority journal; protein; protein determination; Proteins; scanning electron microscope; Scanning electron microscopy; Sprayed coatings

In vitro osteoblastic differentiation of human bone marrow cells in the presence of metal ions - Morais, S.; Dias, N.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
For periods up to 21 days human bone marrow was cultured in control conditions that favor the proliferation and differentiation of osteoblastic cells. The effect of AISI 316L corrosion products and the corresponding major separate metal ions (Fe, Cr, and Ni) were studied in three different phases of the culture period in order to investigate the effects of metal ions in cell populations representative of osteoblastic cells in different stages of differentiation. Toxicity consequences of the presence of metal ions in bone marrow cultures were evaluated by biochemical parameters (enzymatic reduction of MTT, alkaline phosphatase activity, and total protein content), histochemical assays (identification of ALP-positive cells and Ca and phosphates deposits), and observation of the cultures by light and scanning electron microscopy. Culture media were analyzed for total and ionized Ca and P and also for metal ions (Fe, Cr, and Ni). The presence of AISI 316L corrosion products and Ni salt in bone marrow cultures during the first and second weeks of culture significantly disturbs the normal behavior of these cultures, interfering in the lag phase and exponential phase of cell growth and ALP expression. However, the presence of these species during the third week of culture, when expression of osteoblastic functions occurs (mineralization process), did not result in any detectable effect. Fe salt also disturbs the behavior of bone marrow cell cultures when present during the lag phase and proliferation phase, and a somewhat compromised response between the normal pattern (control cultures) and intense inhibition (AISI 316L corrosion products and Ni salt-added cultures) was observed. Fe did not affect the progression of the mineralization phase. Osteogenic cultures exposed to Cr salt (Cr 3+) presented a pattern similar to the controls, indicating that this element does not interfere, in the concentration studied, in the osteoblastic differentiation of bone marrow cells. Quantification of metal ions in the culture media showed that Cr (originated from AISI 316L corrosion products but from not Cr 3+ salt) and Ni (originated from AISI 316L corrosion products and Ni salt) appear to be retained by the bone marrow cultures. For periods up to 21 days human bone marrow was cultured in control conditions that favor the proliferation and differentiation of osteoblastic cells. The effect of AISI 316L corrosion products and the corresponding major separate metal ions (Fe, Cr, and Ni) were studied in three different phases of the culture period in order to investigate the effects of metal ions in cell populations representative of osteoblastic cells in different stages of differentiation. Toxicity consequences of the presence of metal ions in bone marrow cultures were evaluated by biochemical parameters (enzymatic reduction of MTT, alkaline phosphatase activity, and total protein content), histochemical assays (identification of ALP-positive cells and Ca and phosphates deposits), and observation of the cultures by light and scanning electron microscopy. Culture media were analyzed for total and ionized Ca and P and also for metal ions (Fe, Cr, and Ni). The presence of AISI 316L corrosion products and Ni salt in bone marrow cultures during the first and second weeks of culture significantly disturbs the normal behavior of these cultures, interfering in the lag phase and exponential phase of cell growth and ALP expression. However, the presence of these species during the third week of culture, when expression of osteoblastic functions occurs (mineralization process), did not result in any detectable effect. Fe salt also disturbs the behavior of bone marrow cell cultures when present during the lag phase and proliferation phase, and a somewhat compromised response between the normal pattern (control cultures) and intense inhibition (AISI 316L corrosion products and Ni salt-added cultures) was observed. Fe did not affect the progression of the mineralization phase. Osteogenic cultures exposed to Cr salt (Cr 3+) presented a pattern similar to the controls, indicating that this element does not interfere, in the concentration studied, in the osteoblastic differentiation of bone marrow cells. Quantification of metal ions in the culture media showed that Cr (originated from AISI 316L corrosion products but from not Cr 3+ salt) and Ni (originated from AISI 316L corrosion products and Ni salt) appear to be retained by the bone marrow cultures.
Keywords: alkaline phosphatase; Alloys; article; Batch cell culture; Biocompatible Materials; biotechnology; Bone; Bone cells; bone marrow cell; Bone Marrow Cells; bone mineralization; bone prosthesis; Calcium; Cell culture; cell differentiation; Cell Division; cell population; Cells, Cultured; Chromium; controlled study; Corrosion; Corrosion products; Cytotoxicity; Differentiation; human; human cell; Human osteoblast-like cells; Humans; Implants (surgical); Ions; Iron; joint prosthesis; materials testing; metal ion; Metal ions; Metals; Nickel; osteoblast; Osteoblasts; phosphorus; Prostheses and Implants; Proteins; Stainless steel; Steel corrosion; Tetrazolium Salts; Thiazoles

Individual study of chromium in the stainless steel implants degradation: An experimental study in mice - Pereira, M.D.C.; Pereira, M.D.L.; Sousa, J.P. (BioMetalsBioMetals, 1999)
To study the accumulation and the histological effects in mice organs caused by hexavalent chromium, one of the corrosion products released from AISI 316L stainless steel implants, mice groups were subcutaneously injected with a metallic solution of chromium during a certain period of time. Similar injections were made with HBSS (Hank's Balanced Salt Solution) in other groups to be used as controls. The levels of chromium found in the liver, kidney and spleen of the control and the treated animals were obtained by atomic absorption spectrometry (AAS) and were compared to those obtained by AdSV (adsorptive stripping voltammetry) to test the accuracy of the results. During the experimental period, the liver and spleen showed a progressive and significant accumulation of chromium whereas in the kidney the significant accumulation found after the first week practically remained unchanged during the four weeks. Apparently, the histological analysis of these tissues did not evidence any relevant morphological alteration induced by the chromium accumulations during the four weeks of treatment.
Keywords: animal experiment; animal tissue; Animalia; Animals; article; atomic absorption spectrometry; Biocompatible Materials; biomaterial; body weight; Chromium; controlled study; Corrosion; histology; histopathology; implant; Injections, Subcutaneous; Kidney; Liver; liver level; male; Mice; Mice organs; Mice, Inbred Strains; mouse; nonhuman; potentiometry; Prostheses and Implants; Spleen; Stainless steel; tissue distribution

Miniaturization and application of the MTT assay to evaluate metabolic activity of protozoa in the presence of toxicants - Dias, N.; Nicolau, A.; Carvalho, G.S.; Mota, M.; Lima, N. (Journal of Basic MicrobiologyJ. Basic Microbiol., 1999)
This paper describes a critical evaluation of a miniaturised colorimetric assay, using MTT (3-[4,5-dimethyl-thiazol-2-yl]-2,5-diphenyl-tetrazolium bromide) reduction, applied to protozoan viability testing. The toxic substances used were copper, zinc, Triton X-100 (a membrane surfactant) and cycloheximide (an inhibitor of the protein synthesis). The viability assay of the ciliate protozoan Tetrahymena pyriformis was optimised in terms of MTT concentration and incubation time. Since protozoa are non adherent cells the MTT assay was modified in order to maintain the medium in the well. MTT proved to be effective in the measurement of Tetrahymena pyriformis viability. Four hours of MTT incubation followed by 30 minutes of incubation with DMSO were found to be the best incubation times for optical density reading. Furthermore, 10 mg/ml of MTT solution was the concentration that gave higher values of optical densities with minor medium interference.
Keywords: Animals; Ciliophora; Colorimetry; Copper; Cycloheximide; MTT assay; Octoxynol; Protozoa; Tetrahymena pyriformis; Tetrazolium Salts; Thiazoles; Zinc

Adhesion and microstructural characterization of plasma-sprayed hydroxyapatite/glass ceramic coatings onto Ti-6Al-4V substrates - Silva, P.L.; Santos, J.D.; Monteiro, F.J.; Knowles, J.C. (Surface and Coatings TechnologySurf. Coat. Technol., 1998)
Commercial hydroxyapatite (HA), Ca 10(PO 4) 6(OH) 2, powders were reinforced with 4% of a CaO-P 2O 5 based glass during its sintering process. Double layered coatings were obtained by Plasma Spraying and composed of 50 μm commercial HA, followed by a 50 μm (HA)/P 2O 5-CaO based glass composite coating. Samples were characterized by X-ray diffraction (XRD) analysis and it was shown that they were constituted of an HA matrix with small traces of tricalcium phosphate (β-TCP) phase. The XRD spectra were quite similar to those of commercial HA coatings. For coating to substrate adhesion two different tests were performed: adhesion tests according to ASTM C 633-79 and ASTM D 1002-83 standards. Higher values were obtained for ASTM C 633-79 than for ASTM D 1002-83, 35 and 15 MPa, respectively. This behavior is discussed in terms of the different stress effort applied to specimens. The results obtained with ASTM C 633-79 show that these double layered satisfy the stress requirements for load bearing biomedical applications. © 1998 Published by Elsevier Science S.A.
Keywords: Adhesion; Ceramic coatings; Characterization; coating; Hydroxyapatite glass ceramic coatings; materials testing; Mechanical properties; Microstructure; Phosphates; Plasma spraying; Stresses; Titanium aluminum vanadium substrates; X ray diffraction analysis; X-Ray Diffraction

Adsorptive stripping measurements of iron accumulation in mice kidney using microelectrodes and histological features - Pereira, M.C.; Pereira, M.L.; Sousa, J.P. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 1998)
The toxic effects caused by iron in kidney was performed on experimental studies with mice following administration of a metallic solution of this specie to simulate the iron corrosion products of a metallic implant. To quantify the total levels of iron present in this organ, an electrochemical method was chosen based on the application of square wave voltammetry using adsorptive collection of iron-catechol on a mercury film microelectrode (MFM). The optimal working conditions to produce a very stable and reproducible iron peak in the digested kidney samples were found to be pH=7.2 provided by 8.0 mmol/L PIPES buffer, catechol concentration of 3.0x10
Keywords: , biomaterials; Adsorptive stripping; animal experiment; animal model; animal tissue; Animals; article; atomic absorption spectrometry; biomaterial; controlled study; electrochemical analysis; electrochemistry; histology; Iron; iron absorption; Kidney; male; Mercury; metal implantation; Mice; microelectrode; Microelectrodes; mouse; nonhuman; potentiometry; priority journal; Toxicology

Chromium determination in osteoblast-like cell culture medium by catalytic cathodic stripping voltammetry with a mercury microelectrode - Morais, S.; De Carvalho, G.S.; Sousa, J.P. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 1998)
A catalytic cathodic stripping voltammetric procedure for the determination of total chromium in osteoblast-like cell culture medium using a mercury film microelectrode (MFM) was optimised. The method is based on the pre-concentration of the Cr(III)-diethylenetriaminepentaacetic acid (DTPA) complex by adsorption at the potential of -1.00 V (vs. Ag/AgCl) in the presence of 10 x 10
Keywords: Acetates; animal cell; Animalia; Animals; article; atomic absorption spectrometry; Bone Marrow Cells; catalysis; Cell culture; Cells, Cultured; Chromium; complex formation; controlled study; Culture Media; culture medium; drug determination; electrochemistry; Electrodes; Hydrogen-Ion Concentration; in vitro study; Kinetics; Mercury; microelectrode; Microelectrodes; Nitrates; nonhuman; osteoblast; Osteoblasts; potentiometry; priority journal; Rabbits; Reproducibility of Results; sensitivity and specificity; Stromal Cells; technique

Classification of foetal heart rate sequences based on fractal features - Felgueiras, C.S.; De Marques Sá, J.P.; Bernardes, J.; Gama, S. (Medical and Biological Engineering and ComputingMed. Biol. Eng. Comput., 1998)
Visual inspection of foetal heart rate (FHR) sequences is an important means of foetal well-being evaluation. The application of fractal features for classifying physiologically relevant FHR sequence patterns is reported. The use of fractal features is motivated by the difficulties exhibited by traditional classification schemes to discriminate some classes of FHR sequence and by the recognition that this type of signal exhibits features on different scales of observation, just as fractal signals do. To characterise the signals by fractal features, two approaches are taken. The first models the FHR sequences as temporal fractals. The second uses techniques from the chaos-theory field and aims to model the attractor based on FHR sequences. The fractal features determined by both approaches are used to design a Bayesian classification scheme. Classification results for three classes are presented; they are quite satisfactory and illustrate the importance of this type of methodology.Visual inspection of foetal heart rate (FHR) sequences is an important means of foetal well-being evaluation. The application of fractal features for classifying physiologically relevant FHR sequence patterns is reported. The use of fractal features is motivated by the difficulties exhibited by traditional classification schemes to discriminate some classes of FHR sequence and by the recognition that this type of signal exhibits features on different scales of observation, just as fractal signals do. To characterise the signals by fractal features, two approaches are taken. The first models the FHR sequences as temporal fractals. The second uses techniques from the chaos-theory field and aims to model the attractor based on FHR sequences. The fractal features determined by both approaches are used to design a Bayesian classification scheme. Classification results for three classes are presented; they are quite satisfactory and illustrate the importance of this type of methodology.
Keywords: article; Bayes Theorem; Cardiology; Chaos techniques; Chaos theory; Classification; Computer aided analysis; Computer simulation; Electrocardiography; Female; Fetal monitoring; fetus; fetus heart rate; FHR classification; FHR sequence; Foetal heart rate sequences; fractal analysis; Fractal features; Fractals; Heart Rate, Fetal; human; Humans; Pattern recognition; Pregnancy; Signal Processing, Computer-Assisted; technique

Decreased consumption of Ca and P during in vitro biomineralization and biologically induced deposition of Ni and Cr in presence of stainless steel corrosion products - Morais, S.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S.; De Bruijn, J.D.; Van Blitterswijk, C.A. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1998)
The purpose of this study was to investigate the effects of 316L stainless steel (SS) corrosion products on the in vitro biomineralization process, because tissue necrosis, bone loss, impaired bone mineralization, and loosening of orthopedic implants are associated with ions and debris resulting from biodegradation. Rat bone marrow cells were cultured in experimental conditions that favored the proliferation and differentiation of osteoblastic cells and were exposed to SS corrosion products obtained by electrochemical means for periods ranging from 1 to 21 days. Quantification of total and ionized Ca and P, as well as Fe, Cr, and Ni, ions in the culture media of control and metal added cultures during the incubation period was performed to study the influence of corrosion products on the Ca and P consumption that occurs during the mineralization process. Control cultures and metal effects on cultures were evaluated concerning DNA content, enzymatic reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), and alkaline phosphatase (ALP) activity. Histochemical detection of ALP, Ca, and phosphate deposition, and examination of the cultures by scanning and transmission electron microscopy (SEM and TEM) were also performed. The presence of SS corrosion products resulted in impairment of the normal behavior of rat bone marrow cultures. Levels of Cr and Ni in the medium of cultures exposed to 316L SS corrosion products decreased throughout the incubation period, suggesting a regular deposition of these species; these results were supported by TEM observation of the cultures. Cultures exposed to the corrosion products presented lower DNA content, MTT reduction, and ALP activity and failed to form mineralized areas. These cultures showed negative staining on histochemical reactions for the identification of calcium and phosphate deposition and SEM and TEM examination did not show mineral globular structures or mineralization foci, respectively, which is characteristic of cultures grown in control conditions. These results suggest that metal ions associated with 316L SS are toxic to osteogenic cells, affecting their proliferation and differentiation.The purpose of this study was to investigate the effects of 316L stainless steel (SS) corrosion products on the in vitro biomineralization process, because tissue necrosis, bone loss, impaired bone mineralization, and loosening of orthopedic implants are associated with ions and debris resulting from biodegradation. Rat bone marrow cells were cultured in experimental conditions that favored the proliferation and differentiation of osteoblastic cells and were exposed to SS corrosion products obtained by electrochemical means for periods ranging from 1 to 21 days. Quantification of total and ionized Ca and P, as well as Fe, Cr, and Ni, ions in the culture media of control and metal added cultures during the incubation period was performed to study the influence of corrosion products on the Ca and P consumption that occurs during the mineralization process. Control cultures and metal effects on cultures were evaluated concerning DNA content, enzymatic reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), and alkaline phosphatase (ALP) activity. Histochemical detection of ALP, Ca, and phosphate deposition, and examination of the cultures by scanning and transmission electron microscopy (SEM and TEM) were also performed. The presence of SS corrosion products resulted in impairment of the normal behavior of rat bone marrow cultures. Levels of Cr and Ni in the medium of cultures exposed to 316L SS corrosion products decreased throughout the incubation period, suggesting a regular deposition of these species; these results were supported by TEM observation of the cultures. Cultures exposed to the corrosion products presented lower DNA content, MTT reduction, and ALP activity and failed to form mineralized areas. These cultures showed negative staining on histochemical reactions for the identification of calcium and phosphate deposition and SEM and TEM examination did not show mineral globular structures or mineralization foci, respectively, which is characteristic of cultures grown in control conditions. These results suggest that metal ions associated with 316L SS are toxic to osteogenic cells, affecting their proliferation and differentiation.
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; alkaline phosphatase; animal cell; Animal cell culture; Animals; article; Biocompatible Materials; Biodegradation; biomineralization; Bioprosthesis; Bone; Bone and Bones; bone atrophy; bone marrow; Calcification, Physiologic; Calcium; calcium ion; Catalyst activity; Cells, Cultured; Chromium; controlled study; Corrosion; Corrosion products; Enzymes; Implants (surgical); metal implantation; mineralization; Nickel; nonhuman; osteoblast; Osteoblast-like cells; phosphate; phosphorus; prosthesis loosening; rat; Rats; Scanning electron microscopy; Stainless steel; Stainless steel corrosion products; Steel; Steel corrosion; tissue necrosis; transmission electron microscopy

Effects of AISI 316L corrosion products in in vitro bone formation - Morais, S.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S.; De Bruijn, J.D.; Van Blitterswijk, C.A. (BiomaterialsBiomaterials, 1998)
Rat bone marrow cells were cultured in experimental conditions that favour the proliferation and differentiation of osteoblastic cells (i.e., 2.52 x 10
Keywords: Absorption spectroscopy; alkaline phosphatase; animal cell; Animal cell culture; Animals; article; ascorbic acid; atomic absorption spectrometry; Bioassay; Biomaterials; bone development; bone marrow cell; Bone Marrow Cells; Calcium; Calcium phosphates; Cell culture; Cell Death; Cells, Cultured; Corrosion; Corrosion products; culture medium; dexamethasone; electrochemical analysis; electrochemistry; Enzymes; glycerophosphate; histochemistry; Histocytochemistry; in vitro study; male; metal ion; Mineralisation; mineralization; nonhuman; ossification; osteoblast; Osteoblast-like cells; Osteoblasts; phosphate; Phosphate minerals; phosphorus; priority journal; rat; Rats; Rats, Wistar; Scanning electron microscopy; Slurries; Stainless steel; Stainless steel 316L; Stainless-steel corrosion products; Steel corrosion

ESR spectroscopy to determine the molecular mobility of poly(ethylene oxide) grafts in amphiphilic graft copolymers - Ji, J.; Feng, L.; Qiu, Y.; Yu, X. (Macromolecular Rapid CommunicationsMacromol. Rapid Commun., 1998)
The ethylene oxide (EO) mobility in polystyrene-graft-[poly(ethylene oxide)] (PS-g-PEO) and polystyrene-graft-[stearyl poly(ethylene oxide)] (PS-g-SPEO) copolymers was evaluated by spin probe techniques. The ESR spectra indicate that 4-hydroxyl-TEMPO (TEMPO = 2,2,6,6-tetramethylpiperidine-N-oxyl) is strongly biased to the PEO phase of the PS-g-(S)PEO membranes. The rotational correlation time τ c can also be employed to assess the PEO mobility in PS-g-(S)PEO membranes. Although τ c of PS-g-(S)PEO usually decreases with increasing surface density of EO, it is of interest that τ c is rather high when the surface within a depth of at least 5 nm is fully occupied by SPEO (sample PS-g-SPEO-72.6).

Evaluation of nickel toxicity on liver, spleen, and kidney of mice after administration of high-dose metal ion - Pereira, M.C.; Pereira, M.L.; Sousa, J.P. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1998)
The toxic effects caused by nickel (Ni) per si were explored by performing in vivo studies on mice following subcutaneous administration of a metallic solution of nickel at 1, 2, 3, and 4 weeks to evaluate the side effects of this metal ion when released from stainless steel implants. Other groups were similarly injected with HBSS and used as controls. Accumulation of Ni ions on liver, spleen, and kidney was assessed by an electrochemical method, adsorptive stripping voltammetry (AdSV) using microelectrodes, and atomic absorption spectrometry (AAS). Alterations of those organs induced by Ni ions were studied, showing that several histological changes had been induced. Chemical analysis and histological features indicate that Ni is partially accumulated in the study organs.The toxic effects caused by nickel (Ni) per si were explored by performing in vivo studies on mice following subcutaneous administration of a metallic solution of nickel at 1, 2, 3, and 4 weeks to evaluate the side effects of this metal ion when released from stainless steel implants. Other groups were similarly injected with HBSS and used as controls. Accumulation of Ni ions on liver, spleen, and kidney was assessed by an electrochemical method, adsorptive stripping voltammetry (AdSV) using microelectrodes, and atomic absorption spectrometry (AAS). Alterations of those organs induced by Ni ions were studied, showing that several histological changes had been induced. Chemical analysis and histological features indicate that Ni is partially accumulated in the study organs.
Keywords: Absorption spectroscopy; Adsorptive stripping voltammetry; animal experiment; animal tissue; Animals; article; atomic absorption spectrometry; biomaterial; body weight; controlled study; Dose-Response Relationship, Drug; electrochemistry; Evaluation Studies; histology; Implants (surgical); Kidney; Liver; liver toxicity; Living systems studies; Mice; Microelectrodes; mouse; nephrotoxicity; Nickel; nonhuman; potentiometry; Spectrophotometry, Atomic; Spleen; spleen injury; Stainless steel; toxicity

Flow cytometry for assessing biocompatibility - Lopes, M.A.; Knowles, J.C.; Kuru, L.; Santos, J.D.; Monteiro, F.J.; Olsen, I. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1998)
Flow cytometry (FCM) was examined as a possible procedure for measuring in vitro the biocompatibility of implant materials for orthopedic and dental surgery. The human osteoblast-like cell line MG63 was grown on hydroxyapatite (HA) and P 2O 5 glass-reinforced HA composite discs and compared with the same cells grown on polystyrene culture dishes. While morphological observation at the light and electron microscopic levels showed no major deleterious effects, FCM indicated that cell size was somewhat reduced, particularly by growth on the HA composite. Moreover, this material also appeared to delay the progression of the cells from the G0/G1 into the S phase of the cell cycle. In addition to this low level of inhibition of cell growth relative to control cultures, FCM analysis also demonstrated that the glass-reinforced HA caused some down-regulation of the expression of osteocalcin and fibronectin, two antigens which play a vital part in the integrity and function of bone and soft connective tissue, respectively. These results thus show, first, that although HA and the HA composite used in these experiments were generally biocompatible, they nevertheless had certain suboptimal effects on the cells; and second, that FCM could be a highly useful procedure for effectively screening and evaluating important biological responses to implant materials. Flow cytometry (FCM) was examined as a possible procedure for measuring in vitro the biocompatibility of implant materials for orthopedic and dental surgery. The human osteoblast-like cell line MG63 was grown on hydroxyapatite (HA) and P 2O 5 glass-reinforced HA composite discs and compared with the same cells grown on polystyrene culture dishes. While morphological observation at the light and electron microscopic levels showed no major deleterious effects, FCM indicated that cell size was somewhat reduced, particularly by growth on the HA composite. Moreover, this material also appeared to delay the progression of the cells from the G0/G1 into the S phase of the cell cycle. In addition to this low level of inhibition of cell growth relative to control cultures, FCM analysis also demonstrated that the glass-reinforced HA caused some down-regulation of the expression of osteocalcin and fibronectin, two antigens which play a vital part in the integrity and function of bone and soft connective tissue, respectively. These results thus show, first, that although HA and the HA composite used in these experiments were generally biocompatible, they nevertheless had certain suboptimal effects on the cells; and second, that FCM could be a highly useful procedure for effectively screening and evaluating important biological responses to implant materials.
Keywords: antigen expression; Antigens; Biocompatibility; Biocompatible Materials; biomaterial; Biomaterials; Biomedical engineering; Bone and Bones; bone prosthesis; Cell culture; cell cycle; cell cycle s phase; Cell Line; Cell size; cell ultrastructure; Cells; Collagen; conference paper; Dental Implants; dentistry; extracellular matrix; Fibronectin; Fibronectins; flow cytometry; Glass fiber reinforced plastics; growth inhibition; human; human cell; Humans; hydroxyapatite; Implants; Implants (surgical); Microscopy, Electron, Scanning; mitosis inhibition; morphology; orthopedics; Osteoblasts; osteocalcin; Polystyrenes; Prostheses and Implants; prosthesis material; Tissue; tooth prosthesis

In situ characterization of the p-Si/NH 4F interface during dissolution in the current oscillations regime - Cattarin, S.; Chazalviel, J.-N.; Da Fonseca, C.; Ozanam, F.; Peter, L.M.; Schlichthörl, G.; Stumper, J. (Journal of the Electrochemical SocietyJ Electrochem Soc, 1998)
Several physicochemical properties of the p-Si/NH 4F interface have been monitored by in situ techniques in the regime of current oscillations. Comparison of evolution of infrared absorption, microwave reflectivity, electrode admittance, hydrogen evolution, and electron injection rate shows interesting correlations. An integrated description of the processes involved is attempted on the basis of the current models for the Si/acidic fluoride interface.
Keywords: Ammonium compounds; Ammonium fluoride; Dissolution; Electric currents; Electric Impedance; Electrochemical electrodes; Electron injection rate; Hydrogen; Interfaces (materials); Microwave reflectivity; Porous silicon

In situ infrared study of the oscillating anodic dissolution of silicon in fluoride electrolytes - Chazalviel, J.-N.; Da Fonseca, C.; Ozanam, F. (Journal of the Electrochemical SocietyJ Electrochem Soc, 1998)
In the far anodic regime, the anodic dissolution of silicon exhibits a resonant behavior, which results from an oscillating behavior on the microscopic scale. The interface has been investigated using in situ infrared spectroscopy in the strong oscillating regime. The interface oxide film varies in thickness by up to a factor of two, and the oxide quality, as determined from a fine analysis of the infrared polarized spectra, is also found to vary periodically during the oscillation. The relative phase of these periodic variations suggests that the origin of the oscillation mechanism lies in a periodic breakdown of the blocking properties of the oxide, which may be initiated by ion permeation in the outer part of the film. The study of oxide dissolution kinetics evidences a stratified structure of the oxide, with layers of "soft" and "strong" oxide. The fast dissolution of the soft oxide is associated with the periodic drop of the oxide thickness.
Keywords: Anodic dissolution; Anodic oxidation; Dissolution; infrared spectroscopy; Interfaces (materials); Oxide films; Oxides; Semiconducting silicon

In vitro biomineralization by osteoblast-like cells I. Retardation of tissue mineralization by metal salts - Morais, S.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S. (BiomaterialsBiomaterials, 1998)
The cytocompatibility of stainless steel 316L (SS 316L) corrosion products was investigated with particular focus on the dose- and time-effect of electrochemically dissolved SS and the corresponding separate metal ions on osteogenic bone marrow derived cells. Type AISI 316L stainless steel (Fe 63.9%, Cr 18.0%, Ni 12.5%, Mo 2.8%, Si 1.2%, Mn 1.6% and C 0.025%, weight for weight) was anodically dissolved in Hank's Balanced Salt Solution (HBSS) and diluted to the following concentrations: 500 μgml
Keywords: Absorption spectroscopy; alkaline phosphatase; animal cell; Animalia; Animals; article; ascorbic acid; atomic absorption spectrometry; balanced salt solution; Bioassay; Biocompatibility; biomaterial; Biomaterials; biomineralization; bone marrow cell; bone mineralization; Bovinae; Calcification, Physiologic; Calcium; calcium phosphate; Carbon; Cations; Cattle; Cell Division; cell proliferation; cell survival; cell viability; Cells, Cultured; Chromium; controlled study; Corrosion; dexamethasone; electrochemistry; enzyme activity; Enzyme kinetics; glycerol 2 phosphate; histochemistry; Iron; Kinetics; manganese; metal ion; Metal ions; Metals; molybdenum; Nickel; nonhuman; Oryctolagus cuniculus; osteoblast; Osteoblast cells; Osteoblast-like cells; Osteoblasts; Phosphates; priority journal; rabbit; Rabbits; serum; Silicon; Stainless steel; Steel corrosion; Tetrazolium Salts; Thiazoles; Tissue culture

In vitro biomineralization by osteoblast-like cells II. Characterization of cellular culture supernatants - Morais, S.; Carvalho, G.S.; Faria, J.L.; Gomes, H.T.; Sousa, J.P. (BiomaterialsBiomaterials, 1998)
The quantification of total calcium, phosphorus, iron, chromium and nickel in cell culture medium by electrochemical or spectroscopic means may require digestion of samples. Nevertheless, when pH adjustment is performed for values higher than about 6.5, the formation of two phases occurs: a white precipitate and a clear solution. Analysing both phases using microelectrodes, atomic absorption spectrometry (AAS), diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy. X-ray dispersive (XRD) analysis, scanning electron microscopy (SEM) and energy dispersive spectroscopic (EDS) analysis, it was oberved that iron, chromium and nickel are not co-precipitating with the white solid phase. If quantification of calcium, phosphorus and magnesium is intended, a ten-fold dilution at least, must be performed to avoid most of these elements going into the precipitate. This knowledge is crucial if a mineralization study is going to be made.The quantification of total calcium, phosphorus, iron, chromium and nickel in cell culture medium by electrochemical or spectroscopic means may require digestion of samples. Nevertheless, when pH adjustment is performed for values higher than about 6.5, the formation of two phases occurs: a white precipitate and a clear solution. Analyzing both phases using microelectrodes, atomic absorption spectrometry (AAS), diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy, X-ray dispersive (XRD) analysis, scanning electron microscopy (SEM) and energy dispersive spectroscopic (EDS) analysis, it was observed that iron, chromium and nickel are not co-precipitating with the white solid phase. If quantification of calcium, phosphorus and magnesium is intended, a ten-fold dilution at least, must be performed to avoid most of these elements going into the precipitate. This knowledge is crucial if a mineralization study is going to be made.
Keywords: Absorption spectroscopy; Animals; article; atomic absorption spectrometry; Biomaterials; bone mineralization; Calcification, Physiologic; Calcium; Cell culture medium; Cells, Cultured; Chromium; Culture Media; culture medium; Diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy; electrochemistry; Energy dispersive spectroscopic analysis; Fourier transform infrared spectroscopy; Hydrogen-Ion Concentration; infrared spectroscopy; Iron; Magnesium; Metals; microelectrode; Microelectrodes; Nickel; nonhuman; osteoblast; Osteoblast cells; Osteoblasts; pH effects; phosphorus; precipitation; Precipitation (chemical); priority journal; Rabbits; Scanning electron microscopy; Spectrophotometry, Atomic; Spectroscopic techniques; Spectroscopy; Stainless steel; supernatant; Supernatants; Tissue culture; X ray analysis; X ray dispersive analysis

In vitro testing of surface-modified biomaterials - Leitão, E.; Barbosa, M.A.; De Groot, K. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1998)
The influence of surface modification treatments such as ion implantation and sputter coating on an in vitro rat bone-marrow cell culture was studied by scanning electron microscopy and X-ray microanalysis. 316 L stainless steel, Ti-6Al-4V and Ti-5Al-2.5Fe were nitrogen ion-implanted with three fluences: 10 15, 10 16 and 10 17 ion cm
Keywords: animal cell; animal tissue; article; biomaterial; Biomaterials; bone marrow culture; Calcium; Carbon; Cell culture; cell suspension; collagen fiber; extracellular matrix; implantation; in vitro study; In vitro testing; Ion implantation; male; materials testing; mineralization; morphology; nitrogen; nonhuman; priority journal; rat; Scanning electron microscopy; Sputtering; Stainless steel; Titanium alloys; Titanium aluminum iron alloy; Titanium aluminum vanadium alloy; X ray analysis; X ray microanalysis

New starch-based thermoplastic hydrogels for use as bone cements or drug-delivery carriers - Pereira, C.S.; Cunha, A.M.; Reis, R.L.; Vázquez, B.; San Román, J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1998)
The development of new biodegradable hydrogels, based on corn starch/cellulose acetate blends, produced by free-radical polymerization with methyl methacrylate monomer (MMA) and/or an acrylic acid monomer (AA), is reported. The polymerization was initiated by a redox system consisting of a benzoyl peroxide and 4-dimethlyaminobenzyl alcohol at low temperature. These hydrogels may constitute an alternative to the materials currently used as bone cements or drug-delivery carriers. Swelling studies were carried out, as a function of pH and temperature, in buffered solutions. The xerogels were further characterized by Fourier transform-infrared spectroscopy. Tensile and compression tests, and dynamic mechanical thermal analysis were used to assess the mechanical performance of the developed materials. The fracture surfaces were observed by scanning electron microscopy. The developed materials are sensitive to the pH, showing a clear reversible transition in a relatively narrow interval of pH, which is just in the range of physiological conditions. These properties make the materials developed in this study very promising for biomedical applications. Fickian-type diffusion is the mechanism predominant in these systems, except for the composition with a higher concentration of AA, that corresponds to the most desirable kinetical behavior for controlled release (case II-transport mechanism). Furthermore, the results obtained in the mechanical tests are in the range of those reported for typical PMMA bone cements, showing that it is possible to develop partially degradable cements with an adequate mechanical behavior.
Keywords: acrylic acid; alcohol; article; benzoyl peroxide; Biodegradation; bone cement; buffer; cellulose acetate; compression; Diffusion; drug delivery system; dynamics; fracture; free radical; hydrogel; infrared spectroscopy; Kinetics; low temperature; mechanical stress; oxidation reduction reaction; pH; poly(methyl methacrylate); Polymerization; priority journal; Scanning electron microscopy; Starch; tensile strength; Thermal analysis

Objective computerized fetal heart rate analysis - Bernardes, J.; Ayres-de-Campos, D.; Costa-Pereira, A.; Pereira-Leite, L.; Garrido, A. (International Journal of Gynecology and ObstetricsInt. J. Gynecol. Obstet., 1998)
Objective: To assess the validity of a computerized methodology for cardiotocogram analysis based on a recently described reproducible visual estimation of the baseline. Methods: Forty-two antepartum and 43 intrapartum cardiotocograms (CTGs) acquired by a personal computer were selected. Antepartum tracings were performed in the 48 h that preceded an elective cesarean section, and intrapartum tracings were performed until delivery. FHR baselines were estimated by an expert, according to an objective and reproducible methodology. Using these baselines, automated detection of accelerations and decelerations and estimation of variability was performed by the personal computer. A quantitative adaptation of the FIGO guidelines for fetal monitoring was used to classify tracings. Perinatal outcome was classified according to the Apgar score and umbilical arterial pH. Validity was then assessed by the proportions of agreement (PA), kappa statistic (κ), sensitivity and specificity, with 95% confidence intervals (95% CI). Cases showing a disagreement between CTG and perinatal classification were reviewed and an adjustment in baseline definition was tested. Results: The initial overall PA and κ between CTG and perinatal classification were, respectively, 0.79 (95% CI: 0.69-0.87) and 0.62 (95% CI: 0.41-0.83). The overall PA and κ, after baseline adjustment were, respectively, 0.89 (95% CI: 0.81-0.95) and 0.78 (95% CI: 0.58-0.98). Sensitivities and specificities ranged between 79% (95% CI: 60-92%) and 100% (95% CI: 95-100%). Conclusions: Good clinical prediction may be possible with an objective methodology for cardiotocogram analysis based on a recently described reproducible baseline estimation.
Keywords: Apgar score; arterial pH; article; Cardiotocography; cesarean section; computer analysis; Computerized analysis; Female; Fetal heart rate; fetus; fetus heart rate; fetus monitoring; Heart Rate, Fetal; human; Humans; Image Processing, Computer-Assisted; practice guideline; Predictive Value of Tests; Pregnancy; priority journal; umbilical artery; validity

Semiautomated ultrasonographic measurement of fetal nuchal translucency using a computer software tool - Bernardino, F.; Cardoso, R.; Montenegro, N.; Bernardes, J.; Marques de Sá, J. (Ultrasound in Medicine and BiologyUltrasound Med. Biol., 1998)
Nuchal translucency (NT) thickness measurement has been recently proposed as a part of routine ultrasound scanning during the late first trimester of pregnancy, for the early screening of chromosomal abnormalities. Manual determination of NT is currently performed using electronic callipers placed by the operator in the middle of two echogenic fines displayed on the screen. Therefore, intraobserver and interobserver repeatability can be questioned. This paper presents a software tool that has been developed for achieving this goal in a semiautomatic way, improving the reproducibility of the method.Nuchal translucency (NT) thickness measurement has been recently proposed as a part of routine ultrasound scanning during the late first trimester of pregnancy, for the early screening of chromosomal abnormalities. Manual determination of NT is currently performed using electronic callipers placed by the operator in the middle of two echogenic lines displayed on the screen. Therefore, intraobserver and interobserver repeatability can be questioned. This paper presents a software tool that has been developed for achieving this goal in a semiautomatic way, improving the reproducibility of the method.
Keywords: article; cervical spine; chromosome aberration; Chromosome Aberrations; Chromosome Disorders; Computer aided diagnosis; computer program; Computer software; computer system; Female; Fetal monitoring; Fetal nuchal translucency; fetus echography; first trimester pregnancy; Humans; Image analysis; Image Processing, Computer-Assisted; Image thresholding; Medical imaging; Neck; observer variation; Pregnancy; Pregnancy Trimester, First; priority journal; reproducibility; Reproducibility of Results; Software; Software package NUCA; Thickness measurement; Ultrasonic imaging; Ultrasonography, Prenatal; ultrasound

Adsorptive Stripping Voltammetric Measurements of Chromium Accumulation in Mice Organs Using Mercury Film Microelectrodes - Pereira, M.C.; Pereira, M.L.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1997)
Chromium is the metallic species of most concern with the use of stainless steel implants. To study the distribution of chromium in mice organs with time, several animals were subcutaneously injected with 2.70 × 10
Keywords: Adsorptive stripping voltammetry; Biomaterials; Chromium; Microelectrodes

Apatite deposition on titanium surfaces - The role of albumin adsorption - Serro, A.P.; Fernandes, A.C.; Saramago, B.; Lima, J.; Barbosa, M.A. (BiomaterialsBIOMATERIALS, 1997)
Titanium implant surfaces are known to spontaneously nucleate apatite layers when in contact with simulated body fluids. However, adsorption of proteins may influence the process of apatite layer formation. In this study the role of bovine serum albumin (BSA) adsorption in the process of apatite deposition on titanium substrates is investigated. Deposition of calcium phosphate was induced by immersing titanium substrates in a Hank's balanced salt solution (HBSS) for times ranging from 1 to 23 days. The resulting substrates were studied by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), wettability measurements and electrochemical impedance determinations. All these methods indicate the presence of a calcium phosphate layer. The same procedure was repeated substituting HBSS with a solution of BSA in HBSS. Although SEM, EDS and electrochemical impedance spectra do not reveal the presence of an apatite layer, XPS analysis strongly indicates that the inhibition of apatite formation by BSA is only partial. The competition between BSA adsorption and apatite deposition seems to lead to a mixed film where the protein co-exists with calcium phosphate. Wettability studies suggest that this surface film is heterogeneous and porous, similar to the thicker films formed in albumin-free HBSS.Titanium implant surfaces are known to spontaneously nucleate apatite layers when in contact with simulated body fluids. However, adsorption of proteins may influence the process of apatite layer formation. In this study the role of bovine serum albumin (BSA) adsorption in the process of apatite deposition on titanium substrates is investigated. Deposition of calcium phosphate was induced by immersing titanium substrates in a Hank's balanced salt solution (HBSS) for times ranging from 1 to 23 days. The resulting substrates were studied by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), wettability measurements and electrochemical impedance determinations. All these methods indicate the presence of a calcium phosphate layer. The same procedure was repeated substituting HBSS with a solution of BSA in HBSS. Although SEM, EDS and electrochemical impedance spectra do not reveal the presence of an apatite layer, XPS analysis strongly indicates that the inhibition of apatite formation by BSA is only partial. The competition between BSA adsorption and apatite deposition seems to lead to a mixed film where the protein co-exists with calcium phosphate. Wettability studies suggest that this surface film is heterogeneous and porous, similar to the thicker films formed in albumin-free HBSS.
Keywords: Adsorption; Albumin; Albumin adsorption; Animals; Apatite; Apatite deposition; Apatites; article; Binding Sites; Bovinae; bovine serum albumin; Calcium Compounds; calcium phosphate; Calcium phosphates; Cattle; Deposition; Electric Impedance; Electrochemical impedance; Energy dispersive spectroscopy; impedance; implant; Isotonic Solutions; Microscopy, Electron, Scanning; priority journal; Prostheses and Implants; Proteins; Scanning electron microscopy; Serum Albumin, Bovine; Spectrometry, X-Ray Emission; Substrates; Surface Properties; surface property; Surfaces; Tissue Preservation; Titanium; wettability; X ray photoelectron spectroscopy

Dissolution and deposition processes at metal/apatite interfaces - Barbosa, M.A. (Anales de Quimica, 1997)
The coating of implant surfaces with an apatite layer has become one of the most widely used methods to improve bonding to bone. The metal/apatite interface is, however, a region of chemical and mechanical weaknesses, which led some Authors to cast doubts on the long-term integrity of apatite coated implants. These concerns arc essentially related to coatings obtained by conventional plasma-spraying techniques. Recently, there have been attempts to produce coatings with better properties, particularly by acting at the surface preparation stages and by using alternative methods of deposition. Apatite deposition in a liquid phase is one of the new routes being explored. This paper attempts to focus on the main chemical processes involved in the stability of the metal/apatite interface, in order to establish the basic principles for further technological developments. © Springer-Verlag Ibérica 1997.

Electrochemical and surface modifications on N +-ion implanted Ti-5Al-2.5Fe immersed in HBSS - Leitão, E.; Silva, R.A.; Barbosa, M.A. (Corrosion ScienceCorros. Sci., 1997)
The electrochemical behaviour of nitrogen ion-implanted Ti-5Al-2.5Fe was studied in HBSS-Hank's balanced salt solution, by open-circuit potential vs time and cyclic polarization techniques. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. All ion-implanted surfaces showed higher corrosion resistance than the non-implanted ones. The corrosion potential of the ion-implanted samples was more noble and their passivation current was lower than the non-implanted ones. X-ray photo-electron spectroscopy showed that the immersion of Ti-5Al-2.5Fe in HBSS produces a Ca- and P-rich surface layer. © 1997 Elsevier Science Ltd. All rights reserved.
Keywords: A. titanium alloys; B. EIS; B. XPS; C. passive films; Corrosion resistance; Cyclic polarization technique; Hank's balanced salt solution (HBSS); Ion implantation; nitrogen; Open circuit potential technique; Passivation; Passive films; Surface treatment; Titanium alloys; X ray photoelectron spectroscopy

Electrochemical and surface modifications on N +-ion-implanted 316L stainless steel - Leitão, E.; Silva, R.A.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1997)
The effect of nitrogen-ion implantation on the electrochemical behaviour of 316L stainless steel in a simulated physiological solution (HBSS-Hank's Balanced Salt Solution) was studied by open-circuit potential versus time and cyclic polarization techniques, with the aim of characterizing the surfaces and choosing the best nitrogen-ion fluence. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. The 10 16 ions/cm 2 N + fluence improves the corrosion resistance of the 316L stainless steel. The effect of nitrogen-ion implantation on the electrochemical behaviour of 316L stainless steel in a simulated physiological solution (HBSS-Hank's Balanced Salt Solution) was studied by open-circuit potential versus time and cyclic polarization techniques, with the aim of characterizing the surfaces and choosing the best nitrogen-ion fluence. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. The 10 16 ions/cm 2 N + fluence improves the corrosion resistance of the 316L stainless steel.
Keywords: article; balanced salt solution; Composition effects; Corrosion; Corrosion resistance; Cyclic polarization technique; Electrochemical corrosion; electrochemistry; implantation; Ion implantation; limb prosthesis; nitrogen; Polarization; priority journal; prosthesis failure; Simulated physiological solutions; Solutions; Stainless steel; Stainless steel 316L; Surface Properties; Surface treatment; time

Electrochemical impedance spectroscopy of nitrogen- and carbon-sputter coated 316 L stainless steel - Leitão, E.; Silva, R.A.; Barbosa, M.A. (Corrosion ScienceCorros. Sci., 1997)
The effect of nitrogen and carbon sputter coatings on the electrochemical behaviour of 316 L stainless steel in a simulated physiological solution (Hank's Balanced Salt Solution) was studied by electrochemical impedance spectroscopy with the aim of characterizing the surfaces and choosing the best coating. Coatings with different thicknesses and structures were tested. The results showed that thicker sputter coatings produce surfaces with higher charge transfer resistance and lower interface capacities. This indicates that these materials probably owe their high corrosion resistance to the formation of more protective films. © 1997 Elsevier Science Ltd. All rights reserved.
Keywords: A. Stainless steel; B. EIS; C. passive films; Carbon; Charge transfer; Coatings; Composition effects; Corrosion resistance; electrochemistry; Films; Hank's balanced salt solution; nitrogen; Passive films; Protective coatings; sodium chloride; Spectroscopy; Sputter deposition; Stainless steel; Surface phenomena

Guided bone regeneration using osteopatite® granules and polytetrafluoroethylene membranes - Vasconcelos, M.; Afonso, A.; Branco, R.; Cavalheiro, J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1997)
Granules of a modified hydroxyapatite, Osteopatite®, were implanted in the right posterior tibiae of adult rabbits. We studied the extent of bone regeneration in bone holes. In the right tibiae, that were filled with granules of this biomaterial covered with a polytetrafluoroethylene (PTFE) membrane using, as a control, uncovered granules. In the left tibia, an empty hole was covered with PTFE membrane and a second hole was left empty to be used as a control. A histomorphometric study was carried out using light microscopy, four and eight weeks after the surgery. The covered granules presented a higher percentage of bone contact than the uncovered ones, and it was also possible to observe a better bone tissue organization, mainly produced by the immobilization action of the PTFE membrane. Empty bone defects covered with PTFE membranes, two months after implantation, presented large areas of Haversian bone and direct bone contact to the PTFE membrane.Granules of a modified hydroxyapatite, Osteopatite, were implanted in the right posterior tibiae of adult rabbits. We studied the extent of bone regeneration in bone holes. In the right tibiae, that were filled with granules of this biomaterial covered with a polytetrafluoroethylene (PTFE) membrane using, as a control, uncovered granules. In the left tibia, an empty hole was covered with PTFE membrane and a second hole was left empty to be used as a control. A histomorphometric study was carried out using light microscopy, four and eight weeks after the surgery. The covered granules presented a higher percentage of bone contact than the uncovered ones, and it was also possible to observe a better bone tissue organization, mainly produced by the immobilization action of the PTFE membrane. Empty bone defects covered with PTFE membranes, two months after implantation, presented large areas of Haversian bone and direct bone contact to the PTFE membrane.
Keywords: animal experiment; Animalia; biomaterial; Bone; bone defect; Bone Regeneration; conference paper; controlled study; haversian canal; hydroxyapatite; Implants (surgical); microscopy; nonhuman; Optical microscopy; Oryctolagus cuniculus; Phosphate minerals; politef; Polymeric membranes; Polytetrafluoroethylenes; priority journal; rabbit; tibia

Influence of substrate material and surface finishing on the morphology of the calcium-phosphate coating - Leitão, E.; Barbosa, M.A.; De Groot, K. (Journal of Biomedical Materials ResearchJ. BIOMED. MATER. RES., 1997)
The formation of an apatite-like layer was achieved by immersing Ti- 6A1-4V, Ti-A1-2.5Fe, and 316 L stainless-steel substrata in Hank's balanced salt solution (HBSS). The layer was characterized by surface analysis techniques, namely, X-ray microanalysis and X-ray diffraction, and the morphology was observed by scanning electron microscopy and atomic force microscopy. The concentrations of Ca and P were monitored as a function of time. The morphology of the precipitate layer seems to be dependent both on the type of metal substrate and its surface finish. Polished Ti-6A1-4V and Ti-A1-2.5Fe surfaces exhibit a plate precipitate morphology, whereas rougher surfaces show scattered crystal-like precipitation. The results suggest that the layer produced by immersion of polished titanium alloys in HBSS is constituted by an amorphous apatite.The formation of an apatite-like layer was achieved by immersing Ti-6Al-4V, Ti-Al-2.5Fe, and 316 L stainless-steel substrata in Hank's balanced salt solution (HBSS). The layer was characterized by surface analysis techniques, namely, X-ray microanalysis and X-ray diffraction, and the morphology was observed by scanning electron microscopy and atomic force microscopy. The concentrations of Ca and P were monitored as a function of time. The morphology of the precipitate layer seems to be dependent both on the type of metal substrate and its surface finish. Polished Ti-6Al-4V and Ti-Al-2.5Fe surfaces exhibit a plate precipitate morphology, whereas rougher surfaces show scattered crystal-like precipitation. The results suggest that the layer produced by immersion of polished titanium alloys in HBSS is constituted by an amorphous apatite.
Keywords: Alloys; Aluminum; Aluminum alloys; article; Biocompatibility; Biocompatible Materials; biomaterial; Calcium Compounds; calcium phosphate; Calcium phosphate coatings; Calcium phosphates; Coatings; Finishing; Humans; hydroxyapatite; Implants (surgical); Iron; Isotonic Solutions; materials testing; metal implantation; Microscopy, Electron, Scanning; morphology; Phosphates; Stainless steel; Surface Properties; surface property; Surface testing; Surface treatment; Time Factors; Titanium; Titanium alloys; X ray diffraction; X ray diffraction analysis

Investigation of the dissolution of the bioceramic hydroxyapatite in the presence of titanium ions using ToF-SIMS and XPS - Leadley, S.R.; Davies, M.C.; Ribeiro, C.C.; Barbosa, M.A.; Paul, A.J.; Watts, J.F. (BiomaterialsBIOMATERIALS, 1997)
Time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS) analyses have been used to investigate the dissolution of hydroxyapatite in the presence of titanium chloride suggesting the substitution of titanium ions for calcium in the hydroxyapatite structure. The surface analytical data suggest that titanium was incorporated within the solid phase as titanium phosphate. Comparison of relative ion intensities in the ToF-SIMS spectra reveals changes in the composition of the surface chemistry of hydroxyapatite. These relative ion intensities show that the maximum surface uptake of titanium occurred at a solution concentration of 500 ppm titanium chloride for a time of incubation of 30 min. These data correlate with that obtained using XPS highlighting the semi-quantitative information which ToF-SIMS can provide.Time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS) analyses have been used to investigate the dissolution of hydroxyapatite in the presence of titanium chloride suggesting the substitution of titanium ions for calcium in the hydroxyapatite structure. The surface analytical data suggest that titanium was incorporated within the solid phase as titanium phosphate. Comparison of relative ion intensities in the ToF-SIMS spectra reveals changes in the composition of the surface chemistry of hydroxyapatite. These relative ion intensities show that the maximum surface uptake of titanium occurred at a solution concentration of 500 ppm titanium chloride for a time of incubation of 30 min. These data correlate with that obtained using XPS highlighting the semi-quantitative information which ToF-SIMS can provide.
Keywords: article; Bioceramic hydroxyapatite; Biocompatible Materials; biomaterial; Biomaterials; Cations; ceramic prosthesis; ceramics; Composition; Dissolution; Durapatite; hydroxyapatite; information processing; mass spectrometry; Phosphates; priority journal; Radiography; Secondary ion mass spectrometry; Spectrometry, Mass, Secondary Ion; Spectrometry, X-Ray Emission; Spectrophotometry; Substitution reactions; Surface chemistry; surface property; Surface structure; Time of flight secondary ion mass spectrometry; Time-of-flight secondary ion mass spectrometry; Titanium; Titanium chloride; X ray photoelectron spectroscopy; X-ray photoelectron spectroscopy

Iron Determination in Osteoblast-Like Cell Culture Medium by Adsorptive Cathodic Stripping Voltammetry with a Mercury Microelectrode - Morais, S.; Carvalho, G.S.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1997)
Mercury film microelectrodes were used to determine iron in osteoblast-like cell culture medium by performing adsorptive cathodic stripping voltammetry in the presence of catechol. The optimized analytical conditions are a catechol concentration of 5.00×10
Keywords: Cell culture medium; Iron; Mercury film microelectrode

Mineralization in serially passaged human alveolar bone cells - Fernandes, M.H.; Costa, M.A.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1997)
Well-characterized human bone cell cultures have been regarded as a useful tool to study bone control mechanisms and also to analyse bone/biomaterials interactions. In the present study, human alveolar bone cells were cultured in a-minimal essential medium (α-MEM) containing 10% foetal bovine serum (FBS), 50 μg/ml ascorbic acid, 10 mM sodium β-glycerophosphate and either in the presence or in the absence of 10 nM dexamethasone (Dexa). Cultures were characterized concerning cell viability/proliferation, alkaline phosphatase (ALP), acid phosphatase (ACP) and tartraric acid resistant phosphatase (TRAP) activities, and formation of mineralized areas. Cell proliferation increased gradually for approximately 20 days. In the presence of Dexa, cells formed isolated or interconnected multilayered clusters that increased with culture time. Histochemical assays revealed strong positive reactions for ALP and calcium and phosphates deposits, mainly in relation to cells associated with the clusters. High levels of ALP activity (biochemical determination) were observed. Cells cultured in the absence of Dexa showed significantly lower ALP activity and no calcium and phosphates deposits were present. Serially passaged cells kept the proliferation rate constant but a decrease in ALP activity was observed either in the presence or in the absence of Dexa. The ability to form mineralized areas (cultures fed with Dexa) also decreased on serial subculture.Well-characterized human bone cell cultures have been regarded as a useful tool to study bone control mechanisms and also to analyse bone/biomaterials interactions. In the present study, human alveolar bone cells were cultured in α-minimal essential medium (α-MEM) containing 10% foetal bovine serum (FBS), 50 μg/ml ascorbic acid, 10 mM sodium β-glycerophosphate and either in the presence or in the absence of 10 nM dexamethasone (Dexa). Cultures were characterized concerning cell viability/proliferation, alkaline phosphatase (ALP), acid phosphatase (ACP) and tartaric acid resistant phosphatase (TRAP) activities, and formation of mineralized areas. Cell proliferation increased gradually for approximately 20 days. In the presence of Dexa, cells formed isolated or interconnected multilayered clusters that increased with culture time. Histochemical assays revealed strong positive reactions for ALP and calcium and phosphates deposits, mainly in relation to cells associated with the clusters. High levels of ALP activity (biochemical determination) were observed. Cells cultured in the absence of Dexa showed significantly lower ALP activity and no calcium and phosphates deposits were present. Serially passaged cells kept the proliferation rate constant but a decrease in ALP activity was observed either in the presence or in the absence of Dexa. The ability to form mineralized areas (cultures fed with Dexa) also decreased on serial subculture.
Keywords: Acid phosphatase; Acid resistance; alkaline phosphatase; alveolar bone; article; ascorbic acid; Bioassay; Biocompatibility; Biomaterials; Bone; bone cell; Bovinae; Cell culture; cell proliferation; Characterization; Chemical reactions; controlled study; culture medium; dexamethasone; Foetal bovine serum; glycerophosphate; Histochemical assays; histochemistry; human; Human alveolar bone cells; human cell; mineralization; Minimal essential medium; Phosphates; priority journal; Proteins; tartaric acid; Tartraric acid resistant phosphatase; Tissue culture

Nickel Determination in Osteoblast-Like Cell Culture Medium by Adsorptive Cathodic Stripping Voltammetry with a Mercury Microelectrode - Morais, S.; Carvalho, G.S.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1997)
The purpose of this study is to investigate the influence of nickel, which is an alloying element in commonly used metallic biomaterials, on the biomaterials mineralization process. An electrochemical method was developed to quantify this metal ion in osteoblast-like cell culture medium (OST) by performing adsorptive cathodic stripping voltammetry (CSV) with dimethylglyoxime (DMG) at a mercury film microelectrode (MFM). The optimized analytical conditions and the square-wave CSV parameters for the analysis are: DMG concentration: 5.00 × 10
Keywords: Cell culture medium; Mercury film microelectrode; Nickel

Nickel Quantification in Mice Organs by Adsorptive Cathodic Stripping Voltammetry Using Mercury Microelectrodes - Pereira, M.C.; Faria, J.L.; Reis, M.L.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1997)
Mercury film microelectrodes (MFMs) were used to quantify trace levels of nickel accumulated in mice organs samples after dosing the mice with a physiological solution containing 150 ppm of Ni ions over a period of time, by performing adsorptive cathodic stripping square wave voltammetry (AdSWV). The residues obtained after digestion of the biological organs with nitric acid which affects the electrochemical response of Ni were investigated by XRD and IR spectrometry and found to be mainly composed by p-nitrobenzoic acid. Electrochemical conditions for the quantification of Niwith MFMs in the biological solutions were optimized. The electrochemical data compared favorably with that obtained by atomic absorption spectrometry.
Keywords: Adsorptive stripping voltammetry; Mice organs; Microelectrodes; Nickel

Preparation and characterization of fluoride-substituted apatites - Jha, L.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1997)
Apatites were prepared with three different fluoride concentrations: 0.0 mM (pure hydroxyapatite) 2.5 mM and 5 mM. Reactions were performed in aqueous medium using a reaction between diammonium orthophosphate and calcium nitrate 4-hydrate and ammonium fluoride at temperatures of 3°, 25°, 60° and 90°C. The effects of reaction temperature and fluoride concentration on the crystal morphology, phase purity and crystallinity of the precipitates were observed, using transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy and ion chromatography. Transmission electron micrographs revealed that the crystallites precipitated at 3°C were spheroidal, but became increasingly acicular with increasing precipitation temperature. X-ray diffraction results indicated that all the materials produced were phase pure and that the crystallinity of apatites prepared at higher precipitation temperatures was higher than those prepared at lower precipitation temperatures. A significant difference in the a-axis dimension of fluoride-substituted apatites was observed, as compared to hydroxyapatite. FTIR spectroscopy revealed a hydroxyl band at 3568 cm
Keywords: Apatites; Chromatographic analysis; Composition effects; crystal structure; Fluorine compounds; Fourier transform infrared spectroscopy; Ion chromatography; Phase composition; Phase purity; Phosphate minerals; Precipitation (chemical); Thermal effects; transmission electron microscopy; X ray diffraction analysis

Processing and in vitro degradation of starch/EVOH thermoplastic blends - Reis, R.L.; Mendes, S.C.; Cunha, A.M.; Bevis, M.J. (Polymer InternationalPolym. Int., 1997)
This paper describes the processing dependence of the mechanical properties of three blends of starch/ethylene vinyl alcohol (EVOH) with potential uses as biomaterials. These blends exhibit a distinct rheological behaviour and mechanical performance. Using shear controlled orientation in injection moulding (Scorim) it was possible to induce anisotropy into the mouldings and to simultaneously enhance stiffness and ductility. Degradation was studied in simulated physiological solutions (Hank's balanced salt solution) with and without added bovine serum. Both the dry weight loss and the changes in mechanical properties were determined for ageing periods up to 80 days. The degradation behaviour proved to be strongly dependent on the formulation of the material studied, and on the addition of proteins. The susceptibility of the starch/EVOH blends to degradation when sterilised with ethylene oxide (EtO) was also studied, and showed that the polymers could stand one EtO sterilisation cycle. However, two consecutive cycles severely degraded the polymer structure and properties.
Keywords: Aging of materials; Anisotropy; Biodegradable polymers; Biodegradation; Biomaterials; Degradation; Ductility; Ethylene oxide; Ethylene vinyl alcohol; Hank's salt solution; Injection molding; Polyethylenes; Polymer blends; Polyvinyl alcohols; Processing; Proteins; rheology; Shear controlled orientation injection molding (Scorim); Starch; Sterilisation; Stiffness

Production, bonding strength and electrochemical behaviour of commercially pure Ti/Al 2O 3 brazed joints - Paiva, O.C.; Barbosa, M.A. (Journal of Materials ScienceJ Mater Sci, 1997)
The brazing of commercially pure titanium to Al 2O 3 has been studied. Two different brazing alloys within the Ag-Cu-Ti system and pure silver were selected as bonding agents. Titanium hydride (TiH 2) additions were also tested, with the aim of improving the wetting of the ceramic surface by the melted brazing alloy. The mechanical and electrochemical behaviour of the produced joints was assessed, and related to chemical and morphological features resulting from an analysis by scanning electron microscopy and energy dispersive spectroscopy. It was possible to produce joints presenting high integrity, good strength and high resistance to corrosion. The best results were obtained when using an Ag-26Cu-3Ti brazing alloy. The addition of TiH 2 increased the mechanical properties, leading to a maximum bonding strength of 80 ± 8 MPa, as determined in three-point bending tests. In most of the cases, for a maximum deflection of 5 mm, there was only a partial detachment of the ceramic/metal joints. The lowest values for the corrosion rates (i corr = 1.38 μA cm
Keywords: Agents; Aluminum compounds; Aluminum trioxide; Bond strength (materials); Bonding; Brazed joints; Brazing; Brazing alloys; Corrosion resistance; Energy dispersive spectroscopy; Interfaces (materials); Joints (structural components); Scanning electron microscopy; Silver alloys; Strength of materials; Titanium; Titanium compounds; Titanium hydride

Structure development and control of injection-molded hydroxylapatite-reinforced starch/EVOH composites - Reis, R.L.; Cunha, A.M.; Allan, P.S.; Bevis, M.J. (Advances in Polymer TechnologyAdv Polym Technol, 1997)
This article reports on the development of novel composites of starch-based polymers reinforced with hydroxylapatite (HA). Two different grades of blends of starch and ethylene vinyl alcohol copolymers were reinforced with up to 30% (wt) of sintered and nonsintered HA. The initial compounding stage was carried out either in a rotating drum or by twin-screw extrusion (TSE). Compounds were injection molded using both conventional molding and a shear-controlled orientation in injection molding (Scorim) technique. It was possible to obtain composites with very good mechanical properties, approaching those of cortical bone. The best results were achieved for 30% sintered HA composites processed by TSE and Scorim, due to the in situ formation of HA fibers, and the development of molecular orientation and more compact microstructures in the moldings. This was confirmed by SEM analysis of the fracture surfaces, x-ray diffraction, and Raman spectroscopy. The biodegradability of the composites was also assessed and was found to be faster than that of the matrix. © 1997 John Wiley & Sons, Inc.
Keywords: Biodegradation; Composition effects; Compounding (chemical); Copolymers; Extrusion molding; hydroxyapatite; Injection molding; Microstructure; Molecular orientation; Phosphate minerals; Polymer blends; Polyvinyl alcohols; Reinforced plastics; Rotating drum extrusion; Starch; Twin screw extrusion

Treatments to induce the nucleation and growth of apatite-like layers on polymeric surfaces and foams - Reis, R.L.; Cunha, A.M.; Fernandes, M.H.; Correia, R.N. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1997)
In this work, a bioactive glass is used as a percusor of calcium-phosphate (Ca-P) film deposition onto several polymer-based materials. Both bioinert (high molecular weight polyethylene, HMWPE), and biodegradable (corn starch-based blends, SEVA-C) polymers, unreinforced or reinforced with hydroxylapatite (HA), were coated by the very simple proposed route. Also polyurethane (PU) foams, with an open-cell structure, were mineralized by the proposed method. In fact, it was possible to induce the growth of the Ca-P films not only at the surface, but also in the bulk of the PU foam. These cellular materials are intended for cancellous bone replacement applications. The morphology of the formed films was strongly dependent on the used substrate, its polar character, and on the presence of HA in its composition, as observed by SEM. Nevertheless, a well defined needle like structure was observed in all samples at high magnifications. The Ca:P ratios of the films were between 1.5 and 1.7, i.e. in the range of tricalcium phosphate-hydroxylapatite. Raman spectroscopy and thin-film x-ray diffraction (XRD) evidenced the formation of mostly amorphous calcium-phosphate films. After scraping the coating from the polymer surface and heat-treating the resulting powder at 1000°C for 1 h, HA and β-tricalcium phosphate (TCP) typical peaks were found on XRD patterns.In this work, a bioactive glass is used as a percussor of calcium-phosphate (Ca-P) film deposition onto several polymer-based materials. Both bioinert (high molecular weight polyethylene, HMWPE), and biodegradable (corn starch-based blends, SEVA-C) polymers, unreinforced or reinforced with hydroxylapatite (HA), were coated by the very simple proposed route. Also polyurethane (PU) foams, with an open-cell structure, were mineralized by the proposed method. In fact, it was possible to induce the growth of the Ca-P films not only at the surface, but also in the bulk of the PU foam. These cellular materials are intended for cancellous bone replacement applications. The morphology of the formed films was strongly dependent on the used substrate, its polar character, and on the presence of HA in its composition, as observed by SEM. Nevertheless, a well defined needle like structure was observed in all samples at high magnifications. The Ca:P ratios of the films were between 1.5 and 1.7, i.e. in the range of tricalcium phosphate-hydroxylapatite. Raman spectroscopy and thin-film x-ray diffraction (XRD) evidenced the formation of mostly amorphous calcium-phosphate films. After scraping the coating from the polymer surface and heat-treating the resulting powder at 1000 °C for 1 h, HA and β-tricalcium phosphate (TCP) typical peaks were found on XRD patterns.
Keywords: Apatite; Bioactivity; Biomaterials; calcium phosphate; cancellous bone; conference paper; Deposition; Film growth; Foamed plastics; glass; Heat treatment; hydroxyapatite; implantation; mineralization; molecular weight; morphology; Nucleation; Phosphate coatings; Phosphate minerals; polyethylene; polymer; polyurethan foam; Polyurethanes; priority journal; Raman spectrometry; Raman spectroscopy; Scanning electron microscopy; X ray diffraction; Zea mays

XPS characterization of surface films formed on surface-modified implant materials after cell culture - Leitão, E.; Barbosa, M.A.; De Groot, K. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1997)
Nitrogen ion-implanted Ti-6AI-4V, Ti-5AI-2.5Fe and 316 L stainless steel and nitrogen or carbon sputter-coated samples were inoculated with rat bone marrow. The interface between the cell layer and the substrata was studied by X-ray photo-electron spectrometry and observed by scanning electron microscopy (SEM). Ca and P were detected on all materials after in vitro cell culture. Titanium appears to be present mainly in the form of TiO 2. Nitrogen ion-implanted Ti-6Al-4V, Ti-5Al-2.5Fe and 316 L stainless steel and nitrogen or carbon sputter-coated samples were inoculated with rat bone marrow. The interface between the cell layer and the substrata was studied by X-ray photo-electron spectrometry and observed by scanning electron microscopy (SEM). Ca and P were detected on all materials after in vitro cell culture. Titanium appears to be present mainly in the form of TiO 2.
Keywords: Animal cell culture; Animalia; article; Bone; bone marrow; Calcium; Carbon; Cell culture; implant; Implants (surgical); Interfaces (materials); Ion implantation; nitrogen; phosphorus; priority journal; Scanning electron microscopy; Stainless steel; Surface films; surface property; Surface treatment; Titanium alloys; Titanium dioxide; X ray spectrometry

Amino acid and metal content of Crassostrea gigas shell infested by Polydora sp. in the prismatic layer insoluble matrix and blister membrane - Almeida, M.J.; Moura, G.; MacHado, J.; Coimbra, J.; Vilarinho, L.; Ribeiro, C.; Soares-Da-Silva, P. (Aquatic Living ResourcesAquatic Living Resour., 1996)
The spionid polychaete Polydora sp. can live and reproduce inside the oysters' shell, excavating a U-shaped burrow the central portion of which is filled with detritus and particles of dissolved shell. The oyster responds by secreting an organic layer, confining the worm, and later covering it with calcitostracum. This process creates a characteristic "mud blister". Crassostrea gigas were analysed for the organic matrix amino acid content and 14 metals of the whole shell of normal oysters and severely Polydora infested ones. Amino acid, DOPA and FT-Raman analyses were also performed on isolated membranes from the characteristic mud blister and on prismatic layer insoluble matrix (PLIM) of infested oysters, with the aim of detecting any differences between the two organic matrices. Membranes and PLIM composition differ from whole normal shell organic matrix by having lower aspartate and glycine and higher levels of virtually all hydrophobic amino acids, especially alanine. There are no significant differences between membranes and PLIM in the ratio of charged to non-polar amino acids, respectively 0.54 and 0.59. L-DOPA content is also similar in the two matrices with 0.45 (±0.18) and 0.57 (±0.30) ng.mg
Keywords: Amino acids; Crassostrea gigas; Metals; Polydora sp.; Shell organic matrix

Characterization of apatite layer formation on P 2O 5-CaO, P 2O 5-CaO- Na 2O, and P 2O 5-CaO-Na - Jha, L.J.; Santos, J.D.; Knowles, J.C. (Journal of Biomedical Materials ResearchJ. BIOMED. MATER. RES., 1996)
P 2O 5-based glass hydroxyapatite (HA) composites denoted HA-2 oxide, HA-3 oxide, and HA-4 oxide, were immersed in Hank's balanced salt solution for a period of 1, 2, 3, and 4 weeks at 37°C in nonagitated condition for in vitro evaluation. A surface layer was precipitated on the composites that was analyzed using scanning electron microscopy (SEM), X-ray photoelecton spectroscopy, and thin film X-ray diffractometry (TF-XRD). SEM micrographs showed complete coverage of the composite surface by crystallites after immersion of 1 week in the solution, which grew thicker with respect to immersion time. The binding energies measured by XPS indicated apatite formation and the presence of carbonate on the composite surface, showing the newly formed layer was a carbonated apatite. Confirmation of the formed apatite layer was obtained by TF-XRD. 2O 5-based glass hydroxyapatite (HA) composites denoted HA-2 oxide, HA-3 oxide, and HA-4 oxide, were immersed in Hank's balanced salt solution for a period of 1, 2, 3, and 4 weeks at 37°C in nonagitated condition for in vitro evaluation. A surface layer was precipitated on the composites that was analyzed using scanning electron microscopy (SEM), X-ray photoelectron spectroscopy, and thin film X-ray diffractometry (TF-XRD). SEM micrographs showed complete coverage of the composite surface by crystallites after immersion of 1 week in the solution, which grew thicker with respect to immersion time. The binding energies measured by XPS indicated apatite formation and the presence of carbonate on the composite surface, showing the newly formed layer was a carbonated apatite. Confirmation of the formed apatite layer was obtained by TF-XRD.
Keywords: Apatite; article; binding affinity; Biomaterials; bone strength; Calcium Compounds; Carbonates; Ceramic materials; Characterization; chemical composition; Composite materials; Crystallites; electron microscopy; glass; Glass hydroxyapatite composites; Hank balanced salt solution; hydroxyapatite; Hydroxyapatites; immersion; Microscopy, Electron, Scanning; Molecular Structure; Oxides; prosthesis material; Scanning electron microscopy; scanning tunneling microscopy; Spectrum Analysis; Thin film X ray diffractometry; Thin films; X ray diffraction; X ray diffraction analysis; X ray photoelectron spectroscopy; X-Ray Diffraction

Crystallinity and structural changes in HA plasma-sprayed coatings induced by cyclic loading in physiological media - Reis, R.L.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
In this study hydroxyapatite plasma-sprayed Ti-6A1-4V was characterized by X-ray diffraction (XRD) after being cyclically loaded, while immersed in two different testing environments: Hank's balanced salt solution (HBSS) and an isotonic saline solution (0.15m NaCl). An original method was developed to test these systems under cyclic bending, while immersed in the testing solution. The crystallinity of the coating was calculated, before and after testing. Crystallinity changes were related to coating dissolution rates, measured by atomic absorption spectroscopy (AAS) and by a photocolourimetric method using ascorbic acid. Structural changes induced either by the plasma-spraying procedure or due to corrosion-fatigue tests, namely a preferential dissolution of the coating's amorphous phase, were also found in X-ray diffraction patterns. Long-term immersion tests, without any applied load, were carried out for assessing cyclic loading effects. An immersion for 2 years in static conditions was found to be equivalent to a cyclic test of 27.8 h in the same solution, as measured by the changes on the coating structure and by the amount of coating material lost to the solution.In this study hydroxyapatite plasma-sprayed Ti-6Al-4V was characterized by X-ray diffraction (XRD) after being cyclically loaded, while immersed in two different testing environments: Hank's balanced salt solution (HBSS) and an isotonic saline solution (0.15M NaCl). An original method was developed to test these systems under cyclic bending, while immersed in the testing solution. The crystallinity of the coating was calculated, before and after testing. Crystallinity changes were related to coating dissolution rates, measured by atomic absorption spectroscopy (AAS) and by a photocolourimetric method using ascorbic acid. Structural changes induced either by the plasma-spraying procedure or due to corrosion-fatigue tests, namely a preferential dissolution of the coating's amorphous phase, were also found in X-ray diffraction patterns. Long-term immersion tests, without any applied load, were carried out for assessing cyclic loading effects. An immersion for 2 years in static conditions was found to be equivalent to a cyclic test of 27.8 h in the same solution, as measured by the changes on the coating structure and by the amount of coating material lost to the solution.
Keywords: Absorption spectroscopy; article; ascorbic acid; atomic absorption spectrometry; Atomic absorption spectroscopy; balanced salt solution; Bending (deformation); Calculations; Characterization; Corrosion fatigue tests; crystal structure; Crystallinity; Cyclic bending; Dissolution; Fatigue testing; Hanks balanced salt solution; hydroxyapatite; Hydroxyapatite plasma sprayed coatings; immersion; implant; Isotonic saline solution; loading test; Long term immersion tests; materials testing; Modification; Photocolourimetric method; photometry; Plasma spraying; priority journal; sodium chloride; Sprayed coatings; Titanium alloys; Titanium aluminum vanadium alloys; X ray crystallography; X ray diffraction

Effect of hydroxyapatite thickness on metal ion release from Ti6Al4V substrates - Sousa, S.R.; Barbosa, M.A. (BiomaterialsBIOMATERIALS, 1996)
The electrochemical dissolution behaviour of Ti6Al4V alloy coated with hydroxyapatite (HA) by plasma spraying was studied in Hank's balanced salt solution (HBSS) and compared with that of polished and grit-blasted passivated surfaces. Two different nominal thicknesses of HA (50 and 200 μm) were used. Taking a polished passivated surface as reference, grit blasting of the substrate increased the electrical charge used in the oxidation of Ti6Al4V alloy at constant potential, as a result of increased surface area. However, only HA coatings with a thickness of 200 μm were capable of reducing the charge to values lower than those measured for polished surfaces. Electrochemical impedance spectroscopy has also shown that only 200 μm thick coatings are effective in reducing the oxidation rate of the substrate. Furthermore, in potentiostatic experiments the 50 μm thick coating detached from the substrate, which did not occur with the 200 μm thick coating. However, after 6 months immersion in HBSS, detachment occurred in some regions of both coatings. No titanium, aluminium or vanadium were detected in solution by electrothermal atomic absorption spectroscopy. These data indicate that HA is an effective barrier to metal ion release, even for the thinner coatings, due to formation of metal phosphates or to incorporation of metal ions in the HA structure.The electrochemical dissolution behaviour of Ti6Al4V alloy coated with hydroxyapatite (HA) by plasma spraying was studied in Hank's balanced salt solution (HBSS) and compared with that of polished and grit-blasted passivated surfaces. Two different nominal thicknesses of HA (50 and 200 μm) were used. Taking a polished passivated surface as reference, grit blasting of the substrate increased the electrical charge used in the oxidation of Ti6Al4V alloy at constant potential, as a result of increased surface area. However, only HA coatings with a thickness of 200 μm were capable of reducing the charge to values lower than those measured for polished surfaces. Electrochemical impedance spectroscopy has also shown that only 200 μm thick coatings are effective in reducing the oxidation rate of the substrate. Furthermore, in potentiostatic experiments the 50 μm thick coating detached from the substrate, which did not occur with the 200 μm thick coating. However, after 6 months immersion in HBSS, detachment occurred in some regions of both coatings. No titanium, aluminium or vanadium were detected in solution by electrothermal atomic absorption spectroscopy. These data indicate that HA is an effective barrier to metal ion release, even for the thinner coatings, due to formation of metal phosphates or to incorporation of metal ions in the HA structure.
Keywords: Absorption spectroscopy; Alloys; Aluminum; article; Atomic spectroscopy; balanced salt solution; Bioactive coatings; Biocompatible Materials; Biomaterials; Calcium Compounds; Dissolution; Durapatite; Electric charge; Electrochemical dissolution; Electrochemical impedance spectroscopy; electrochemistry; Electrothermal atomic absorption spectroscopy; Hank balanced salt solution; hydroxyapatite; Ion release; Ions; metal ion; Metal ion release; Metal phosphates; Microscopy, Electron, Scanning; Oxidation; Plasma spraying; potentiometry; priority journal; Spectrophotometry, Atomic; Spectroscopy; Substrates; thickness; Thickness effect; Time Factors; Titanium; Titanium alloys; vanadium

Effects of Co-Cr corrosion products and corresponding separate metal ions on human osteoblast-like cell cultures - Tomás, H.; Carvalho, G.S.; Fernandes, M.H.; Freire, A.P.; Abrantes, L.M. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
The cytocompatibility of the degradation products of a Co-Cr orthopaedic alloy was investigated with particular focus on the dose-effect of an electrochemically dissolved alloy extract and of the corresponding separate metal ions on human osteogenic bone marrow derived cells. The extract solution contained 15ppm of Co and 8ppm of Cr as analysed by atomic absorption spectroscopy. Stock salt solutions of CoCl 2·6H 2O, CrCl 3·6H 2O and Na 2CrO 4 at corresponding concentrations were also prepared. Several dilutions of the above metallic solutions were tested for a period of 21 days on cells (third subculture) cultured in α-minimal essential medium containing foetal bovine serum and supplemented with antibiotics, dexamethasone ascorbic acid and β-glycerophosphate. The osteoblast response to the presence of metal ions was evaluated by several biochemical parameters: cell viability (MTT reduction by intracellular enzymes), alkaline phosphatase activity (an osteoblast marker) and protein production (both intracellular and extracellular). Co-Cr corrosion products showed opposite effects to their respective metal salts only on day 1. With time the different metal solutions presented a similar pattern of inhibition. These results suggest that impaired bone formation in vitro can occur in the presence of Co-Cr corrosion products. The cytocompatibility of the degradation products of a Co-Cr orthopaedic alloy was investigated with particular focus on the dose-effect of an electrochemically dissolved alloy extract and of the corresponding separate metal ions on human osteogenic bone marrow derived cells. The extract solution contained 15 ppm of Co and 8 ppm of Cr as analyzed by atomic absorption spectroscopy. Stock salt solutions of COCl 2·6H 2O, CrCl 3·6H 2O and Na 2CrO 4 at corresponding concentrations were also prepared. Several dilutions of the above metallic solutions were tested for a period of 21 days on cells (third subculture) cultured in α-minimal essential medium containing foetal bovine serum and supplemented with antibiotics, dexamethasone ascorbic acid and β-glycerophosphate. The osteoblast response to the presence of metal ions was evaluated by several biochemical parameters: cell viability (MTT reduction by intracellular enzymes), alkaline phosphatase activity (an osteoblast marker) and protein production (both intracellular and extracellular). Co-Cr corrosion products showed opposite effects to their respective metal salts only on day 1. With time the different metal solutions presented a similar pattern of inhibition. These results suggest that impaired bone formation in vitro can occur in the presence of Co-Cr corrosion products.
Keywords: Absorption spectroscopy; article; Atomic spectroscopy; Biocompatibility; Bone; Cell culture; Chromium alloys; Cobalt alloys; Corrosion; Corrosion resistance; Cytocompatibility; Enzyme inhibition; human; human cell; Human osteoblasts; Implants (surgical); Orthopaedic alloys; ossification; osteoblast; priority journal; surface property

Fracture toughness of hydroxyapatite reinforced with P 2O 5-CaO glasses containing Na 2O, K 2O and MgO - Silva, P.L.; Santos, J.D.; Knowles, J.C.; Silva, R.F.; Monteiro, F.J. (Transactions of the Annual Meeting of the Society for Biomaterials in conjunction with the International Biomaterials SymposiumTrans Annu Meet Soc Biomater Int Biomater Symp, 1996)
Calcium phosphate materials are widely used in biomedical applications but their poor strength and brittleness limit their use in load bearing applications. To improve their mechanical properties, hydroxyapatite (HA) ceramics were reinforced with P 2O 5-CaO based glasses with additions of Na 2+, Mg 2+ and K + oxides. A composite chemical composition that approaches the inorganic part of bone chemical composition was obtained using HA with calcium phosphate-based glasses. Fracture toughness was significantly enhanced by glass additions, and the decrease in fracture toughness at 1300 and 1350 °C was attributed to grain growth since it significantly increased with sintering temperature.
Keywords: Biomaterials; Bone; Composition effects; Fracture toughness; glass; Grain growth; hardness; Hydroxyapatites; Lime; Magnesia; Phosphate minerals; Potassium compounds; Sodium compounds; Thermal effects

Granules of osteoapatite and glass-reinforced hydroxyapatite implanted in rabbit tibiae - Afonso, A.; Santos, J.D.; Vasconcelos, M.; Branco, R.; Cavalheiro, J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Granules of a modified hydroxyapatite, glass-reinforced hydroxyapatite composite and commercial hydroxyapatite were implanted in rabbit tibiae. Histological studies were carried out after 1 and 2 months implantation periods using light and fluorescence microscopy. A much higher percentage of bone contact was developed for both the glass-reinforced hydroxyapatite composite and the modified hydroxyapatite when compared to commercial hydroxyapatite (89-91% versus 66%) after 2 months implantation. The mechanism of bone formation and growth around implants is discussed in terms of the influence of elements incorporated into these novel materials which are commonly found in bone tissues, such as Na, K and Mg, and the presence of a soluble β-tricalcium phosphate phase in the microstructure of the composite.
Keywords: animal experiment; animal tissue; article; Bone; Bone formation; bone growth; Calcium Compounds; calcium phosphate; Composite materials; Fiber reinforced materials; glass; Glass fibers; Glass reinforced hydroxyapatite; Granular materials; histology; hydroxyapatite; implant; Implants (surgical); Magnesium; Microstructure; Modified hydroxyapatite; nonhuman; Optical microscopy; ossification; Osteoapatite; Oxides; Phosphates; Physiological models; potassium; priority journal; rabbit; Rabbit tibiae; Sodium; tibia; X ray diffraction analysis

Histological evaluation of two bioactive cements - Vasconcelos, M.; Afonso, A.; Branco, R.; Planell, J.; Driessens, F.; Cavalheiro, J. (Transactions of the Annual Meeting of the Society for Biomaterials in conjunction with the International Biomaterials SymposiumTrans Annu Meet Soc Biomater Int Biomater Symp, 1996)
Two bioactive bone cements were compared with poly(methylmethacrylate) (PMMA) cement. Cement A was prepared from precipitated hydroxyapatite and tricalcium phosphate, using an aqueous solution of Na 2HPO 4. Cement B was prepared by crushing a bioactive glass composed of SiO 2, CaO, P 2O 5 and Na 2O. The powder was mixed with NH 4H 2PO 4/(NH 4) 2 PO 4 aqueous solution buffered at pH = 7.4. The bioactive cements exhibited different in vivo behaviors but both performed better than PMMA cement.
Keywords: Bioactive bone cements; bone cement; glass; hydroxyapatite; Ion exchange; Lime; pH; Phosphate minerals; Polymethyl methacrylates; Silica; Sodium compounds; Solutions; Sorption; Tricalcium phosphate

Implant recovery and tissue reaction in growing pigs following implantation of packaging materials for injectable electronic identification and monitoring devices - Janssens, S.; Rocha, L.A.; Bosschaerts, L.; Barbosa, M.A.; Puers, R.; Villé, H.; Geers, R. (Preventive Veterinary MedicinePrev. Vet. Med., 1996)
Different materials were used as cylindrical housings (40 mm × 5 mm) for implantable electronic identification and monitoring tags in livestock. A total of 299 pigs received an implant in the right ear base. Wound healing was complete after 6 weeks in all animals, whereas tissue reaction at the site of the transponder started from the first week with highest levels between 6 and 9 weeks. About 10% of pigs showed visible swelling of the tissue surrounding the implant. Severeness of tissue reaction ante-mortem influenced the recovery rate of implants. Histological sections obtained from the pigs at slaughter show signs of an inflammatory response in most of the pigs which was associated with the implantation duration/body weight effect. Overall recovery of implants was 90%. The unfavourable inflammation and recovery results might be attributed to a sub-optimal injection procedure.
Keywords: implant; Implant recovery; Pig; tissue reaction

In vitro calcium phosphate formation on SiO 2-Na 2O-CaO-P 2O 5 glass reinforced hydroxyapatite composite: A study by XPS analysis - Santos, J.D.; Jha, L.J.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
In-vitro apatite layer formation on the surface of a newly developed glass reinforced hydroxyapatite composite was characterized using X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) equipped with energy dispersive X-ray analysis (EDXA). After 1 week soaking in an acellular simulated body fluid the composite surface was entirely covered by a Ca, P-layer, suggesting a bioactive behaviour. XPS binding energy results revealed that this surface layer was a carbonated and non- stoichiometric apatite with Ca/P ratio of 1.3. This apatite layer was composed of very fine needle-like crystallites. Comparative studies on a commercially available hydroxyapatite showed that a similar apatite layer was also formed on its surface.In-vitro apatite layer formation on the surface of a newly developed glass reinforced hydroxyapatite composite was characterized using X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) equipped with energy dispersive X-ray analysis (EDXA). After 1 week soaking in an acellular simulated body fluid the composite surface was entirely covered by a Ca, P-layer, suggesting a bioactive behaviour. XPS binding energy results revealed that this surface layer was a carbonated and non-stoichiometric apatite with Ca/P ratio of 1.3. This apatite layer was composed of very fine needle-like crystallites. Comparative studies on a commercially available hydroxyapatite showed that a similar apatite layer was also formed on its surface.
Keywords: article; Binding energy; Biocompatibility; Biodegradation; biomaterial; Calcium; calcium phosphate; Characterization; Composite materials; Composition; Energy dispersive x ray analysis; glass; Glass reinforced hydroxyapetite composite; hydroxyapatite; implant; In vitro calcium phosphate formation; Ionic concentration; molecular interaction; Nucleation; Phosphates; phosphorus; priority journal; Scanning electron microscopy; Surfaces; X ray analysis; X ray photoelectron spectroscopy

Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts - Carvalho, G.S.; Castanheira, M.; Diogo, I.; Abreu, A.M.; Sousa, J.P.; Loon, J.A.; Van Blitterswijk, C.A. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Fibroblasts from normal human skin were cultured for a period of 21 days in the absence or in the presence of metal ions. The effects of stainless steel (SS) corrosion products were compared to the effects of iron, chromium and nickel ions used either separately (Fe, Cr, or Ni solutions) or combined (Fe+Cr+Ni solution). At several periods of time (4, 7, 14 and 21 days) the cell cultures were analysed for the following parameters: (a) metal ion accumulation by atomic absorption spectrometry; (b) cell morphology and viability by the neutral red assay; (c) cell proliferation by DNA assessment, and enzyme activity by both (d) MTT reduction and (e) acid phosphatase activity. Results showed that SS-corrosion products and the corresponding metal ions combined at the same concentrations, Fe+Cr+Ni solution, had opposite effects on fibroblast cultures. In fact, SS-corrosion products caused no apparent effects on cell morphology nor on cell proliferation whereas Fe+Cr+Ni solution stimulated both neutral red uptake and cell proliferation. The enzymatic assays showed that SS-corrosion products caused inhibition of both MTT reduction and acid phosphatase activity in contrast to Fe+Cr+Ni solution which stimulated their activity. Furthermore, in all biological parameters studied, a strong association was observed between the effects of Fe+Cr+Ni solution and Cr alone, suggesting that Cr was the metal ion mostly involved in the stimulatory effects of the combined solution.Fibroblasts from normal human skin were cultured for 21 days in the absence, or presence, of metal ions. The effects of stainless steel (SS) corrosion products were compared to the effects of iron, chromium, and nickel ions used either separately or combined. At different periods of time, the cell cultures were analyzed for the following parameters: metal ion accumulation by atomic absorption spectrometry; cell morphology and viability by the neutral red assay; cell proliferation by DNA assessment; and enzyme activity by both MTT reduction and acid phosphatase activity. Results show that SS-corrosion products and the corresponding metal ions combined at the same concentrations, Fe+Cr+Ni solution, have opposite effects on fibroblast cultures.
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; Absorption spectroscopy; Acid phosphatase; article; atomic absorption spectrometry; Atomic spectroscopy; Bioassay; Cell culture; Cell morphology; cell proliferation; cell structure; cell viability; Chromium; controlled study; Corrosion; Corrosion products; cytology; DNA; Enzymatic assays; Enzyme Activation; enzyme activity; Enzyme inhibition; fibroblast; human; human cell; Ions; Iron; metal; Metal ion accumulation; Metal salts; Metals; neutral red; Nickel; priority journal; Salts; Skin; skin fibroblast; Stainless steel; Steel corrosion

Mechanical behavior of injection-molded starch-based polymers - Reis, R.L.; Cunha, A.M.; Allan, P.S.; Bevis, M.J. (Polymers for Advanced TechnologiesPolym. Adv. Technol., 1996)
This work evaluates the mechanical performance of injection-molded starch-based copolymers, 60/40 (mol/ mol) starch/poly(ethylene vinyl alcohol), and the possibility of improving material properties through deliberately induced anisotropy during processing. Different types of samples were produced by conventional and shear-controlled injection molding (Scorim) and tested under tensile and impact loading. The behavior of three distinct grades is discussed in terms of the respective fracture morphology (evaluated by scanning electron microscopy). A comparison is made between the behavior of conventional and Scorim samples. The results show that the mechanical properties of the materials used were significantly improved by the employment of the Scorim process. The stiffness values of the conventional moldings were doubled, without reducing the ductility of the polymer. The impact data showed a material sensitivity, and consequent loss of properties, to the localized shear imposed to the melt during processing. This situation is attributed to very narrow mold gates (in the case of pingated systems) and leads to much reduced impact performance.
Keywords: Anisotropy; Biomaterials; Copolymers; differential scanning calorimetry; Ductility; fracture; Impact performance; Impact testing; Injection molding; Mechanical performance; Melting temperature; morphology; Narrow mold gates; performance; Scanning electron microscopy; Scorim; Scorim process; Starch-based polymers; Starched based polymers; Stiffness; Tensile testing

Potentiometric Determination of Total and Ionized Calcium in Osteoblast-Like Cell Culture Medium - Morais, S.; Carvalho, G.S.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1996)
The effect of the ionic strength and composition of solutions in the direct potentiometric determination of total and ionized calcium content using a calcium selective electrode was investigated. In the presence of a constant complexation buffer (CCB), the addition of sodium chloride and sodium bicarbonate causes a decrease in the limit of detection of the potentiometric response. When the procedure was tested in osteoblast-like cell culture medium no electrode interferences or method interferences were observed by the presence of proteins, i.e., the total and ionized calcium in this medium can be measured by potentiometric means.
Keywords: Cell culture medium; potentiometry; Total and ionized calcium

Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O and MgO - Santos, J.D.; Silva, P.L.; Knowles, J.C.; Talal, S.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Commercial hydroxyapatite was reinforced by adding small amounts (2 and 4 wt%) of P 2O 5-based glasses during its sintering process. The composites prepared had a chemical composition closely related to the mineral part of bone tissues in terms of trace elements usually detected, such as Na, K and Mg. X-ray diffraction analysis (XRD) showed that the glass reinforced-HA composites were composed of a HA matrix and variable amounts of tricalcium phosphate phase, depending on sintering temperature and glass composition. These composites were shown to have much higher biaxial bending strength than sintered HA, 107 MPa for Ha/2% of 35P 2O 5-35CAO-10Na 2O-10K 2O-10MgO glass composite and 28 MPa for sintered HA. The presence of β-tricalcium phosphate in the microstructure of the composites is an important factor in the reinforcement process. Commercial hydroxyapatite was reinforced by adding small amounts (2 and 4 wt%) of P 2O 5-based glasses during its sintering process. The composites prepared had a chemical composition closely related to the mineral part of bone tissues in terms of trace elements usually detected, such as Na, K and Mg. X-ray diffraction analysis (XRD) showed that the glass reinforced-HA composites were composed of a HA matrix and variable amounts of tricalcium phosphate phase, depending on sintering temperature and glass composition. These composites were shown to have much higher biaxial bending strength than sintered HA, 107 MPa for Ha/2% of 35P 2O 5-35CaO-10Na 2O-10K 2O-10MgO glass composite and 28 MPa for sintered HA. The presence of β-tricalcium phosphate in the microstructure of the composites is an important factor in the reinforcement process.
Keywords: article; Bending strength; Bone; chemical composition; Composite materials; Composition; Composition effects; glass; Glass composition; Glass reinforced hydroxapatite composite; hydroxyapatite; implant; Magnesium Oxide; metal oxide; Microstructure; molecular dynamics; Phosphates; potassium derivative; priority journal; Sintering; Sintering temperature; sodium derivative; Thermal effects; Trace Elements; Tricalcium phosphate phase; X ray diffraction

Sintering effects in a glass reinforced hydroxyapatite - Knowles, J.C.; Talal, S.; Santos, J.D. (BiomaterialsBIOMATERIALS, 1996)
Glass was incorporated into hydroxyapatite (HA) to act as a sintering aid in order to improve the mechanical properties. The glass was added at 2 and 4 wt% and the powders compacted uniaxially. The compacts were sintered at a variety of temperatures (1200, 1250, 1300 and 1350°C) and the effects of the glass addition and the firing temperature were studied to determine their effects on the sintering process. It was found that the glass promoted some phase changes, related to the amount of glass added to the composite. At 1200 and 1250°C, some β-tricaicium phosphate (TCP) was found with the residual being HA. However, at 1300 and 1350°C, both β- and α-TCP were formed. The 4 wt% addition, as expected, promoted higher levels of secondary phases in the composite. The flexural bend strength (FBS) showed high values and also significant differences dependent on the amount of glass added. A 2 wt% addition gave a gradual increase in FBS with temperature. With a 4 wt% addition there was an increase in FBS, but above 1300°C there was a rapid decrease. These effects were mirrored in the linear shrinkage. Both the linear shrinkage and the FBS results were attributed to both the phase changes occurring and also change in grain size with increasing firing temperature.Glass was incorporated into hydroxyapatite (HA) to act as a sintering aid in order to improve the mechanical properties. The glass was added at 2 and 4 wt% and the powders compacted uniaxially. The compacts were sintered at a variety of temperatures (1200, 1250, 1300 and 1350°C) and the effects of the glass addition and the firing temperature were studied to determine their effects on the sintering process. It was found that the glass promoted some phase changes, related to the amount of glass added to the composite. At 1200 and 1250°C, some β- tricalcium phosphate (TCP) was found with the residual being HA. However, at 1300 and 1350°C, both β- and α-TCP were formed. The 4 wt% addition, as expected, promoted higher levels of secondary phases in the composite. The flexural bend strength (FBS) showed high values and also significant differences dependent on the amount of glass added. A 2 wt% addition gave a gradual increase in FBS with temperature. With a 4 wt% addition there was an increase in FBS, but above 1300°C there was a rapid decrease. These effects were mirrored in the linear shrinkage. Both the linear shrinkage and the FBS results were attributed to both the phase changes occurring and also change in grain size with increasing firing temperature.
Keywords: article; Bending strength; Biomaterials; calcium phosphate; Chemistry, Physical; Durapatite; glass; Glass reinforced hydroxyapatite; Grain growth; hydroxyapatite; priority journal; Sintering; Sintering aid; temperature; tensile strength; Tricalcium phosphate; X-Ray Diffraction

Computerized fetal heart rate analysis in labour based on 2-s sampling. Can it proceed with confidence? [1] - Bernardes, J.; Garrido, A.; Chang, A.; Sahota, D.S.; Reed, N.N.; James, D.K.; Mohajer, M.P. (European Journal of Obstetrics Gynecology and Reproductive BiologyEUR. J. OBSTET. GYNECOL. REPROD. BIOL., 1995)
Keywords: computer analysis; Computers; Female; Fetal monitoring; fetus; fetus heart rate; Heart Rate, Fetal; human; labor; Labor, Obstetric; letter; measurement; Pregnancy; priority journal; sampling; Time Factors

The effect of hydroxyapatite thickness on metal ion release from stainless steel substrates - Sousa, S.R.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
The corrosion behaviour of 350 stainless steel coated with hydroxyapatite, HA, by plasma spraying was studied in Hank's Balanced Salt Solution, HBSS, and compared with that of polished passivated surfaces. Two different nominal thicknesses, 50 μm and 200 μm, corresponding to what one might consider a thin and a thick coating, respectively, were used. Only HA coatings with a thickness of 200 μm were capable of reducing the electrical charge consumed at constant potential to values lower than those measured for polished surfaces. However, no HA detachment occurred for both thicknesses, as opposed to what has been found in a previous work with Ti6A14V alloy coated with 50 μm HA. No iron, chromium or nickel were detected in solution by Atomic Absorption Spectroscopy with electrothermal atomization (ET-AAS). These elements were also absent from the bulk of the HA coating, both after a 6 month immersion period and electrochemical accelerated tests. The data indicate that in spite of the relatively low corrosion resistance of stainless steel as compared to that of titanium alloys, a thin (50 μm) HA coating prevents the release of metal ions, while remaining adherent to the substrate.The corrosion behaviour of 350 stainless steel coated with hydroxyapatite, HA, by plasma spraying was studied in Hank's Balanced Salt Solution, HBSS, and compared with that of polished passivated surfaces. Two different nominal thicknesses, 50 μm and 200 μm, corresponding to what one might consider a thin and a thick coating, respectively, were used. Only HA coatings with a thickness of 200 μm were capable of reducing the electrical charge consumed at constant potential to values lower than those measured for polished surfaces. However, no HA detachment occurred for both thicknesses, as opposed to what has been found in a previous work [1] with Ti6Al4V alloy coated with 50 μm HA. No iron, chromium or nickel were detected in solution by Atomic Absorption Spectroscopy with electrothermal atomization (ET-AAS). These elements were also absent from the bulk of the HA coating, both after a 6 month immersion period and electrochemical accelerated tests. The data indicate that in spite of the relatively low corrosion resistance of stainless steel as compared to that of titanium alloys, a thin (50 μm) HA coating prevents the release of metal ions, while remaining adherent to the substrate.
Keywords: Absorption spectroscopy; atomic absorption spectrometry; Atomic absorption spectroscopy; Atomic spectroscopy; balanced salt solution; Calcium Compounds; Chromium; comparative study; conference paper; Corrosion; Corrosion behaviour; Electric charge; electrochemistry; Hank balanced salt solution; hydroxyapatite; immersion; Inorganic coatings; Ions; Iron; metal ion; Metal ion release; Nickel; Plasma spraying; priority journal; Stainless steel; Stainless steel substrates; Substrates; thickness; Thickness effect; Titanium; Titanium alloys

Electrochemical and surface modifications on N +-ion implanted Ti-6A1-4V immersed in HBSS - Leitão, E.; Sa, C.; Silva, R.A.; Barbosa, M.A.; Ali, H. (Corrosion ScienceCorros. Sci., 1995)
The effect of nitrogen-ion implantation on the electrochemical behaviour of Ti-6Al-4V in a simulated physiological solution (HBSS-Hank's balanced salt solution) was studied by open-circuit potential versus time and cyclic polarization techniques, with the aim of characterizing better the surface prior to biological testing and to choose the most appropriate nitrogen-ion fluence. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. The 10 16 ions/cm 2 N + fluence produced the lowest corrosion rate under passive conditions. The highest fluence originated a large increase in the corrosion rate and inhibited the formation of a calcium- and phosphate-rich layer on the electrode surface. © 1995.
Keywords: Biological testing; Characterization; Corrosion; Corrosion rate; Cyclic polarization technique; Electrochemical behaviour; electrochemistry; Hank balanced salt solution; Ion implantation; materials testing; Nitrogen ion implanted titanium aluminum vanadium alloy; Nitrogen-ion fluence; Open circuit potential; Passivation; Polarization; Simulated physiological solution; Solutions; Surface modification; Surface treatment; Titanium alloys

In vitro calcification of orthopaedic implant materials - Leitao, E.; Barbosa, M.A.; De Groot, K. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
The formation of an apatite-like layer is achieved by immersing Ti6A14V and TiA12.5Fe substrata in Hank's Balanced Salt Solution (HBSS). The layer was characterized by several techniques, namely X-ray microanalysis, X-ray diffraction and X-ray photoelectron spectroscopy. The results suggest that the layer produced by immersion in HBSS is in the form of an amorphous apatite. The pH and the concentrations of calcium and phosphate were monitored as a function of time. In vitro tests with rat bone marrow were performed in order to mimic the bone/biomaterial interface. They were performed on both immersed and non-immersed samples. The in vitro bone marrow results suggest that the apatite-like layer formed may improve the bone bonding characteristics of the studied titanium alloys.The formation of an apatite-like layer is achieved by immersing Ti6Al4V and TiAl2.5Fe substrata in Hank's Balanced Salt Solution (HBSS). The layer was characterized by several techniques, namely X-ray microanalysis, X-ray diffraction and X-ray photoelectron spectroscopy. The results suggest that the layer produced by immersion in HBSS is in the form of an amorphous apatite. The pH and the concentrations of calcium and phosphate were monitored as a function of time. In vitro tests with rat bone marrow were performed in order to mimic the bone/biomaterial interface. They were performed on both immersed and non-immersed samples. The in vitro bone marrow results suggest that the apatite-like layer formed may improve the bone bonding characteristics of the studied titanium alloys.
Keywords: Amorphous apatite; Amorphous materials; animal cell; Apatite; balanced salt solution; Bone; bone marrow; Calcification; Calcification (biochemistry); Calcium; calcium phosphate; conference paper; Hank balanced salt solution; immersion; implantation; Implants (surgical); metal implantation; Microanalysis; nonhuman; orthopedics; pH; phosphate; Phosphates; priority journal; rat; Spectroscopy; surface property; time; Titanium; Titanium alloys; X ray analysis; X ray diffraction; X ray photoelectron spectroscopy

Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions: Structure and properties of the composites - Santos, J.D.; Reis, R.L.; Monteiro, F.J.; Knowles, J.C.; Hastings, G.W. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
Phosphate- and silicate-based glasses were added to hydroxyapatite in order to improve its mechanical properties and to fabricate composites with different degrees of bioactivity. A strong chemical bonding was obtained between hydroxyapatite and the phosphate-based glasses leading to samples approaching theoretical density, according to density measurements and scanning electron microscopy. Bioglass® additions led to the formation of a complex calcium phosphate silicate which hampered the reinforcement process. The fracture toughness of the hydroxyapatite-glass composites was shown to be within the 1.1-1.2 MPam(1/2) range, which is double that determined for sintered hydroxyapatite. A 2 μm thick apatite layer was observed on the surface of the hydroxyapatite-glass composites after 48 h immersion in a simulated human blood plasma, whereas only a few apatite crystals were detected on sintered hydroxyapatite after 7 days immersion. From the results obtained we anticipate that the composites might show a higher rate of bone bonding, leading to enhanced bioactivity.Phosphate- and silicate-based glasses were added to hydroxyapatite in order to improve its mechanical properties and to fabricate composites with different degrees of bioactivity. A strong chemical bonding was obtained between hydroxyapatite and the phosphate-based glasses leading to samples approaching theoretical density, according to density measurements and scanning electron microscopy. Bioglass (R) additions led to the formation of a complex calcium phosphate silicate which hampered the reinforcement process. The fracture toughness of the hydroxyapatite-glass composites was shown to be within the 1.1-1.2 MPa m 1/2 range, which is double that determined for sintered hydroxyapatite. A 2 μm thick apatite layer was observed on the surface of the hydroxyapatite-glass composites after 48 h immersion in a simulated human blood plasma, whereas only a few apatite crystals were detected on sintered hydroxyapatite after 7 days immersion. From the results obtained we anticipate that the composites might show a higher rate of bone bonding, leading to enhanced bioactivity.
Keywords: Adhesion; article; Bioactivity; Bioglass; Biomaterials; Bone; bone prosthesis; calcium phosphate; chemical binding; Chemical bonds; chemical composition; Chemical structure; Complex calcium phosphate silicate; Composite materials; crystal; density; Density measurement (specific gravity); glass; Human blood plasma; hydroxyapatite; Liquid phase sintering; Mechanical properties; Mechanics; phosphate; Phosphates; plasma; priority journal; Scanning electron microscopy; silicate; Silicates; Sintering; Structure (composition); surface property; thickness

Modifications in the molecular structure of hydroxyapatite induced by titanium ions - Ribeiro, C.C.; Barbosa, M.A.; Machado, A.A.S.C.; Tudor, A.; Davies, M.C. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
The purpose of this study was to contribute to the understanding of the effect of titanium ions released from a metallic substrate on the molecular structure of hydroxyapatite. The effects of pH, time of incubation and concentration of titanium ions were investigated. The solids were analysed by X-ray diffraction, Fourier transform infrared spectroscopy, Fourier transform Raman spectroscopy, energy dispersive X-ray analysis and thermogravimetric analysis. The results clearly indicate the presence of a titanium phosphate, Ti(HPO 4) 2·nH 2O (n = 1-3), which probably has a double layered structure. The formation of this compound is dependent on the titanium concentration and its crystallinity increases with the time of incubation. The purpose of this study was to contribute to the understanding of the effect of titanium ions released from a metallic substrate on the molecular structure of hydroxyapatite. The effects of pH, time of incubation and concentration of titanium ions were investigated. The solids were analysed by X-ray diffraction, Fourier transform infrared spectroscopy, Fourier transform Raman spectroscopy, energy dispersive X-ray analysis and thermogravimetric analysis. The results clearly indicate the presence of a titanium phosphate, Ti(HPO 4) 2·nH 2O (n = 1-3), which probably has a double layered structure. The formation of this compound is dependent on the titanium concentration and its crystallinity increases with the time of incubation.
Keywords: Calcium Compounds; Chemical structure; Coatings; conference paper; Crystallinity; Crystallization; Dissolution; Energy dispersive x ray analysis; Fourier transform infrared spectroscopy; Fourier transform Raman spectroscopy; hydroxyapatite; Implants (surgical); incubation time; infrared spectroscopy; Ions; metal ion; Molecular Structure; pH; pH effects; phosphate; Phosphates; priority journal; Raman spectrometry; Raman spectroscopy; Thermogravimetric analysis; thermogravimetry; time; Titanium; Titanium compounds; X ray analysis; X ray diffraction

Plasma surface treatment and PACVD on Ti alloys for surgical implants - Rie, K.-T.; Stucky, T.; Silva, R.A.; Leitao, E.; Bordji, K.; Jouzeau, J.-Y.; Mainard, D. (Surface and Coatings TechnologySurf. Coat. Technol., 1995)
To improve the poor surface hardness and wear resistance of titanium alloys used for surgical implants undergoing wear TiA16V4 and TiA15Fe2.5 have been plasma nitrided. TiN and other sublayers are formed by plasma nitriding. To increase the thickness of the outermost TiN layer the samples have been coated with TiN by PACVD following plasma nitriding. The produced layers have been characterized in terms of microstructure, layer composition, hardness depth profiles. The evaluation of corrosion resistance and biocompatibility revealed that the good properties of the untreated alloys have been well preserved. © 1995 Elsevier Science S.A.
Keywords: Biocompatibility; Biomaterials; Characterization; Chemical vapor deposition; Corrosion resistance; hardness; Implants (surgical); Microstructure; Nitriding; PACVD; Plasma applications; Plasma assisted chemical vapor deposition; Plasma nitriding; Plasma surface treatment; Surface hardness; Surface treatment; Surfaces; Ti alloys; Titanium alloys; Wear resistance

Stainless steel corrosion products cause alterations on mouse spleen cellular populations - Tracana, R.B.; Pereira, M.L.; Abreu, A.M.; Sousa, J.P.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
Stainless steel is a metallic biomaterial commonly used in orthopaedic surgery. In this study we looked at the effects of stainless steel corrosion products on spleen, in order to evaluate their potential immunotoxicological effects. For this purpose stainless steel, type AISI 316L, was electrochemically dissolved in a physiological salt solution. The final solution, containing 490 μg/ml Fe, 224 μg/ml Cr and 150 μg/ml Ni, was injected subcutaneously in mice. After several periods of time (4, 10 and 14 days) spleens were removed and analysed for: (a) their contents in Fe, Cr and Ni, (b) histological alterations, (c) enumeration of cellular populations. Results showed that stainless steel corrosion products accumulated in spleen, caused histological alterations, and induced changes in cellular populations. When compared to chromium and nickel, iron was the metal ion preferentially accumulated in spleen. The increase of the multinucleated giant cell population was accompanied by depletion of lymphocyte populations. This study indicates that stainless steel corrosion products can spread systemically and accumulate in spleen inducing histological and cellular alterations which may give rise to immunotoxicological consequences.Stainless steel is a metallic biomaterial commonly used in orthopaedic surgery. In this study we looked at the effects of stainless steel corrosion products on spleen, in order to evaluate their potential immunotoxicological effects. For this purpose stainless steel, type AISI 316L, was electrochemically dissolved in a physiological salt solution. The final solution, containing 490 μg/ml Fe, 224 μg/ml Cr and 150 μg/ml Ni, was injected subcutaneously in mice. After several periods of time (4, 10 and 14 days) spleens were removed and analysed for: (a) their contents in Fe, Cr and Ni, (b) histological alterations, (c) enumeration of cellular populations. Results showed that stainless steel corrosion products accumulated in spleen, caused histological alterations, and induced changes in cellular populations. When compared to chromium and nickel, iron was the metal ion preferentially accumulated in spleen. The increase of the multinucleated giant cell population was accompanied by depletion of lymphocyte populations. This study indicates that stainless steel corrosion products can spread systematically and accumulate in spleen inducing histological and cellular alterations which may give rise to immunotoxicological consequences.
Keywords: animal cell; animal experiment; animal tissue; Animalia; article; Biocompatibility; biomaterial; cell population; Cells; Chromium; Chronoamperometry; controlled study; Corrosion; Corrosion products; Dissolution; electrochemistry; giant cell; histology; immunology; immunotoxicity; Immunotoxicological effects; Ions; Iron; Lymphocyte; lymphocyte subpopulation; male; mouse; Nickel; nonhuman; orthopedic surgery; priority journal; sodium chloride; Spleen; spleen cell; Stainless steel; Steel corrosion; subcutaneous drug administration; toxicity

Surface modifications of glass-reinforced hydroxyapatite composites - Santos, J.D.; Jha, L.J.; Monteiro, F.J. (BiomaterialsBIOMATERIALS, 1995)
Surface modifications of glass-reinforced hydroxyapatite composites immersed in a simulated physiological solution were studied using X-ray photoelectron spectroscopy, scanning electron microscopy and energy dispersive X-ray spectroscopy. In the first stages of the apatite formation process, calcium and silicon ions were leached out from the surface of the composites. After 12 days of immersion, apatite crystals were detected on the surface indicating bioactive behaviour. Sodium ions attributed to sodium sulphate were also found in the apatite layer. Bound water on the surface also increased with immersion time.Surface modifications of glass-reinforced hydroxyapatite composites immersed in a simulated physiological solution were studied using X-ray photoelectron spectroscopy, scanning electron microscopy and energy dispersive X-ray spectroscopy. In the first stages of the apatite formation process, calcium and silicon ions were leached out from the surface of the composites. After 12 days of immersion, apatite crystals were detected on the surface indicating bioactive behaviour. Sodium ions attributed to sodium sulphate were also found in the apatite layer. Bound water on the surface also increased with immersion time.
Keywords: Apatite; article; Bioactive glass; Biocompatible Materials; Biomaterials; Calcium; chemical composition; Composite materials; Electron Probe Microanalysis; glass; Glass reinforced hydroxyapatite composites; Hydrogen-Ion Concentration; hydroxyapatite; Hydroxyapatites; immersion; Ions; Leaching; Microscopy, Electron, Scanning; Phosphates; phosphorus; priority journal; Scanning electron microscopy; Silicon; Sodium; sodium chloride; sodium sulfate; Spectrometry, X-Ray Emission; Spectroscopy; Surface modification; Surface Properties; surface property; Surface treatment; Water; X ray; X ray photoelectron spectroscopy; X ray spectroscopy

Mouse inflammatory response to stainless steel corrosion products - Tracana, R.B.; Sousa, J.P.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1994)
Corrosion occurs regularly following long-term implantation of stainless steel. Little is known about the inflammatory and immunological potential of stainless steel corrosion products. AISI 316L stainless steel was anodically dissolved in a physiologically solution, HBSS, through a chronoamperometric process by imposing an external constant current of 0.5 mA. The solution, containing 245 μg of Fe, 112 μg of Cr, 75 μg of Ni and 13 μg of Mo, was injected in the peritoneal cavity of male C57BL/6 mice. Five animals were used per survival period of time: 4, 16, 24, and 48 h, 1, 2, 4, 8 and 16 weeks. Three control mice per survival period of time were injected with HBSS. For each assay, peritoneal samples were analysed not only for the total number of cells but also for the percentages of macrophages, lymphocytes and polymorphonuclear (PMN) cells, which were estimated by differential counting on Wright-stained cytocentrifuge preparations. Our follow-up study showed that stainless steel corrosion products induced an acute inflammatory response for a period of one week as demonstrated by the influx of PMN cells and macrophages. In contrast neither a chronic inflammation nor an immune response was observed indicating that the stainless steel solution caused a minor tissue response.A follow-up study of the changes to mouse peritoneal cell populations, succeeding intraperitoneal injection of stainless steel corrosion products, in order to assess the inflammatory response to such metals was presented. AISI stainless steel was anodically dissolved in a physiologically solution, Hank's balanced salt solution (HBSS), which was injected in the peritoneal cavity of male mice. Five animals were designated per survival time interval of 4, 16, 24, and 48 h, 1, 2, 4, 8 and 16 weeks. Three control mice per survival period of time were treated with HBSS. For each assay, peritoneal samples were tested for total number of cells and percentages of macrophages, lymphocytes and polymorphonuclear (PMN) cells. The follow-up study revealed that stainless steel corrosion products induced an acute inflammatory response for a duration of one week as shown by the influx of PMN cells and macrophages. In contrast, neither a chronic inflammation nor an immune response was noted suggesting that stainless steel solution caused a minor tissue response.
Keywords: animal cell; animal experiment; Animalia; article; Assays; Cell Count; Cells; Chromium; Chronoamperometry; controlled study; Corrosion; Dissolution; follow up; immune response; immunology; Inflammation; Inflammatory response; Iron; Lymphocyte; Lymphocytes; macrophage; Macrophages; male; metal implantation; Mice (animal); molybdenum; mouse; Nickel; nonhuman; Peritoneal cavity; Polymorphonuclear; polymorphonuclear cell; priority journal; Stainless steel; time; Tissue; Wright stained cytocentrifuge

Stability of hydroxylapatite plasma-sprayed coated Ti-6Al-4V under cyclic bending in simulated physiological solutions - Reis, R.L.; Monteiro, F.J.; Hastings, G.W. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1994)
The aim of this research was to study the stability of plasma-sprayed coated metal systems and to evaluate their susceptibility to the occurrence of corrosion fatigue. Hydroxylapatite plasma-sprayed coated samples of Ti-6Al-4V were studied under cyclic bending. During fatigue testing samples were immersed in a simulated physiological solution and mechanical and electrochemical degradation were monitored. Applied loads were intended to crack the ceramic coating and not the metal substrate. Electrochemical impedance spectroscopy was used to further characterize the electrochemical behaviour. No increase in tendency to corrode was detected in open-circuit corrosion fatigue testing. It appears as if the coating cracking does not increase metal substrate corrosion susceptibility. The coating integrity has been seriously affected, with marked decrease in thickness, due to the synergistic effect of load and presence of simulated body fluids environment. Impedance results, however, show a general tendency to an increase in corrosion kinetics after corrosion fatigue testing.The aim of this research was to study the stability of plasma-sprayed coated metal systems and to evaluate their susceptibility to the occurrence of corrosion fatigue. Hydroxylapatite plasma-sprayed coated samples of Ti-6Al-4V were studied under cyclic bending. During fatigue testing samples were immersed in a simulated physiological solution and mechanical and electrochemical degradation were monitored. Applied loads were intended to crack the ceramic coating and not the metal substrate. Electrochemical impedance spectroscopy was used to further characterize the electrochemical behaviour. No increase in tendency to corrode was detected in open-circuit corrosion fatigue testing. It appears as if the coating cracking does not increase metal substrate corrosion susceptibility. The coating integrity has been seriously affected, with marked decrease in thickness, due to the synergistic effect of load and presence of simulated body fluids environment. Impedance results, however, show a general tendency to an increase in corrosion kinetics after corrosion fatigue testing.
Keywords: article; Bending (deformation); biomaterial; biomechanics; body fluid; Ceramic coatings; ceramics; controlled study; Corrosion; Corrosion fatigue; Corrosion susceptibility; Degradation; Electrochemical impedance spectroscopy; electrochemistry; fatigue; Fatigue testing; hydroxyapatite; impedance; mechanical stress; Physiological solutions; Plasma spraying; priority journal; sodium chloride; Solutions; Spectroscopy; Stability; Substrates; thickness; Titanium; Titanium alloys

In vitro immuno-cytotoxicity of iron evaluated by DNA synthesis of human T lymphocytes stimulated via CD2 and CD3 - Carvalho, G.S.; Bravo, I. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1993)
In previous studies it was demonstrated that the in vitro exposure of human lymphocytes to iron, nickel or cobalt salts causes a significant reduction of lymphocytes expressing CD2 and CD3 surface antigens. Since both molecules are involved in T lymphocyte activation, these studies suggest that the above metals might affect T-cell activation and proliferation. Thus a method was developed for the stimulation of lymphocytes in which both CD2 and CD3 molecules were triggered simultaneously. For this purpose an anti-CD3 monoclonal antibody (mAb) was chemically bound to human erythrocytes (HE), forming HEαCD3 conjugates, which were used for lymphocyte stimulation. In this work the effects of iron on lymphocyte proliferation was studied, following stimulation.
Keywords: article; Biochemistry; Biomedical engineering; cd2 antigen; cd3 antigen; cd8 antigen; Cell culture; cell stimulation; concentration response; DNA; DNA synthesis; erythrocyte; human; human cell; Human lymphocytes; Immuno-cytotoxicity; immunocytotoxicity; Iron; lymphocyte proliferation; monoclonal antibody; monocyte; Synthesis (chemical); t lymphocyte; toxicity

Stimulation of human T lymphocytes via CD2 and CD3 molecules: establishment of the method and characterisation of proliferating cells. - Bravo, I.; Carvalho, G.S. (CytobiosCytobios, 1993)
The in vitro exposure of human lymphocytes to degradation products (Fe, Ni or Co) of metallic biomaterials causes a significant reduction of lymphocytes expressing the molecules involved in T lymphocyte activation, CD2 and CD3. A method is described which was developed for the stimulation of lymphocytes in which both CD2 and CD3 molecules were triggered simultaneously. For this purpose an anti-CD3 monoclonal antibody (mAb) was chemically bound to sheep (SE) or human (HE) erythrocytes, forming SE alpha CD3 or HE alpha CD3 conjugates, respectively, which were used for lymphocyte stimulation. Stimulation via CD2 and CD3 was compared with classical phytohaemagglutinin stimulation as well as with soluble alpha CD3 mAb stimulation. Phenotypical characterisation of DNA synthesising lymphocytes was assessed by autoradiography of 3H-thymidine pulsed cultures combined with immunocytochemical tests. Results indicate that this method of T lymphocyte stimulation via CD2 and CD3 is reliable and consistent, and it seems to be very convenient for the evaluation of immunocytotoxicity of metal ions derived from metallic biomaterials.
Keywords: Antigens, CD2; Antigens, CD3; Antigens, Differentiation, T Lymphocyte; Antigens, Differentiation, T-Lymphocyte; article; cd2 antigen; cd3 antigen; Cell culture; Cell Division; Cells, Cultured; cytology; human; immunoglobulin receptor; immunology; lymphocyte activation; metabolism; Receptors, Immunologic; t lymphocyte; T lymphocyte antigen; T-Lymphocytes